Implementing genomic screening in diverse populations - Abul-Husn, N.S.; Soper, E.R.; Braganza, G.T.; Rodriguez, J.E.; Zeid, N.; Cullina, S.; Bobo, D.; Moscati, A.; Merkelson, A.; Loos, R.J.F.; Cho, J.H.; Belbin, G.M.; et al. (Genome Medicine, 2021)
Background: Population-based genomic screening has the predicted ability to reduce morbidity and mortality associated with medically actionable conditions. However, much research is needed to develop standards for genomic screening and to understand the perspectives of people offered this new testing modality. This is particularly true for non-European ancestry populations who are vastly underrepresented in genomic medicine research. Therefore, we implemented a pilot genomic screening program in the BioMe Biobank in New York City, where the majority of participants are of non-European ancestry. Methods: We initiated genomic screening for well-established genes associated with hereditary breast and ovarian cancer syndrome (HBOC), Lynch syndrome (LS), and familial hypercholesterolemia (FH). We evaluated and included an additional gene (TTR) associated with hereditary transthyretin amyloidosis (hATTR), which has a common founder variant in African ancestry populations. We evaluated the characteristics of 74 participants who received results associated with these conditions. We also assessed the preferences of 7461 newly enrolled BioMe participants to receive genomic results. Results: In the pilot genomic screening program, 74 consented participants received results related to HBOC (N = 26), LS (N = 6), FH (N = 8), and hATTR (N = 34). Thirty-three of 34 (97.1%) participants who received a result related to hATTR were self-reported African American/African (AA) or Hispanic/Latinx (HL), compared to 14 of 40 (35.0%) participants who received a result related to HBOC, LS, or FH. Among the 7461 participants enrolled after the BioMe protocol modification to allow the return of genomic results, 93.4% indicated that they would want to receive results. Younger participants, women, and HL participants were more likely to opt to receive results. Conclusions: The addition of TTR to a pilot genomic screening program meant that we returned results to a higher proportion of AA and HL participants, in comparison with genes traditionally included in genomic screening programs in the USA. We found that the majority of participants in a multi-ethnic biobank are interested in receiving genomic results for medically actionable conditions. These findings increase knowledge about the perspectives of diverse research participants on receiving genomic results and inform the broader implementation of genomic medicine in underrepresented patient populations. © 2021, The Author(s).

An open-label, pilot study of veliparib and lapatinib in patients with metastatic, triple-negative breast cancer - Stringer-Reasor, E.M.; May, J.E.; Olariu, E.; Caterinicchia, V.; Li, Y.; Chen, D.; Della Manna, D.L.; Rocque, G.B.; Vaklavas, C.; Falkson, C.I.; Nabell, L.M.; Acosta, E.P.; et al. (Breast Cancer Research, 2021)
Background: Poly (ADP-ribose)-polymerase inhibitors (PARPi) have been approved for cancer patients with germline BRCA1/2 (gBRCA1/2) mutations, and efforts to expand the utility of PARPi beyond BRCA1/2 are ongoing. In preclinical models of triple-negative breast cancer (TNBC) with intact DNA repair, we have previously shown an induced synthetic lethality with combined EGFR inhibition and PARPi. Here, we report the safety and clinical activity of lapatinib and veliparib in patients with metastatic TNBC. Methods: A first-in-human, pilot study of lapatinib and veliparib was conducted in metastatic TNBC (NCT02158507). The primary endpoint was safety and tolerability. Secondary endpoints were objective response rates and pharmacokinetic evaluation. Gene expression analysis of pre-treatment tumor biopsies was performed. Key eligibility included TNBC patients with measurable disease and prior anthracycline-based and taxane chemotherapy. Patients with gBRCA1/2 mutations were excluded. Results: Twenty patients were enrolled, of which 17 were evaluable for response. The median number of prior therapies in the metastatic setting was 1 (range 0–2). Fifty percent of patients were Caucasian, 45% African–American, and 5% Hispanic. Of evaluable patients, 4 demonstrated a partial response and 2 had stable disease. There were no dose-limiting toxicities. Most AEs were limited to grade 1 or 2 and no drug–drug interactions noted. Exploratory gene expression analysis suggested baseline DNA repair pathway score was lower and baseline immunogenicity was higher in the responders compared to non-responders. Conclusions: Lapatinib plus veliparib therapy has a manageable safety profile and promising antitumor activity in advanced TNBC. Further investigation of dual therapy with EGFR inhibition and PARP inhibition is needed. Trial registration: ClinicalTrials.gov, NCT02158507. Registered on 12 September 2014 © 2021, The Author(s).
Keywords: DNA repair; PARP inhibitors; Synthetic lethality; Targeted therapy; Triple-negative breast cancer

Randomized trial of community health worker-led decision coaching to promote shared decision-making for prostate cancer screening among Black male patients and their providers - Makarov, D.V.; Feuer, Z.; Ciprut, S.; Lopez, N.M.; Fagerlin, A.; Shedlin, M.; Gold, H.T.; Li, H.; Lynch, G.; Warren, R.; Ubel, P.; Ravenell, J.E. (Trials, 2021)
Background: Black men are disproportionately affected by prostate cancer, the most common non-cutaneous malignancy among men in the USA. The United States Preventive Services Task Force (USPSTF) encourages prostate-specific antigen (PSA) testing decisions to be based on shared decision-making (SDM) clinician professional judgment, and patient preferences. However, evidence suggests that SDM is underutilized in clinical practice, especially among the most vulnerable patients. The purpose of this study is to evaluate the efficacy of a community health worker (CHW)-led decision-coaching program to facilitate SDM for prostate cancer screening among Black men in the primary care setting, with the ultimate aim of improving/optimizing decision quality. Methods: We proposed a CHW-led decision-coaching program to facilitate SDM for prostate cancer screening discussions in Black men at a primary care FQHC. This study enrolled Black men who were patients at the participating clinical site and up to 15 providers who cared for them. We estimated to recruit 228 participants, ages 40–69 to be randomized to either (1) a decision aid along with decision coaching on PSA screening from a CHW or (2) receiving a decision aid along with CHW-led interaction on modifying dietary and lifestyle to serve as an attention control. The independent randomization process was implemented within each provider and we controlled for age by dividing patients into two strata: 40–54 years and 55–69 years. This sample size sufficiently powered the detection differences in the primary study outcomes: knowledge, indicative of decision quality, and differences in PSA screening rates. Primary outcome measures for patients will be decision quality and decision regarding whether to undergo PSA screening. Primary outcome measures for providers will be acceptability and feasibility of the intervention. We will examine how decision coaching about prostate cancer screening impact patient-provider communication. These outcomes will be analyzed quantitatively through objective, validated scales and qualitatively through semi-structured, in-depth interviews, and thematic analysis of clinical encounters. Through a conceptual model combining elements of the Preventative Health Care Model (PHM) and Informed Decision-Making Model, we hypothesize that the prostate cancer screening decision coaching intervention will result in a preference-congruent decision and decisional satisfaction. We also hypothesize that this intervention will improve physician satisfaction with counseling patients about prostate cancer screening. Discussion: Decision coaching is an evidence-based approach to improve decision quality in many clinical contexts, but its efficacy is incompletely explored for PSA screening among Black men in primary care. Our proposal to evaluate a CHW-led decision-coaching program for PSA screening has high potential for scalability and public health impact. Our results will determine the efficacy, cost-effectiveness, and sustainability of a CHW intervention in a community clinic setting in order to inform subsequent widespread dissemination, a critical research area highlighted by USPSTF. Trial registration: The trial was registered prospectively with the National Institute of Health registry (www.clinicaltrials.gov), registration number NCT03726320, on October 31, 2018. © 2021, The Author(s).
Keywords: Community health worker; Prostate cancer; PSA; Racial disparity; Randomized controlled trial; Screening; Shared decision-making

Aspirin use and prostate cancer among African-American men in the southern community cohort study - Tang, W.; Fowke, J.H.; Hurwitz, L.M.; Steinwandel, M.; Blot, W.J.; Ambs, S. (Cancer Epidemiology Biomarkers and Prevention, 2021)
Background: The association of aspirin use with prostate cancer has been investigated, but few studies included African-American men. Here, we analyzed the relationship of aspirin intake with prostate cancer risk and mortality among African-American men in the Southern Community Cohort Study (SCCS). Methods: SCCS recruited 22,426 African-American men between 2002 and 2009. Aspirin use was assessed at enrollment. Our exposures of interest were any aspirin use (regular strength, low-dose or baby aspirin, or half tablets of aspirin) and regular strength aspirin. Each exposure variable was compared with nonusers. Associations between aspirin use and prostate cancer risk and mortality were examined with Cox proportional hazards models. Results: At enrollment, 5,486 men (25.1%) reported taking any aspirin and 2,634 men (12.1%) reported regular strength aspirin use. During follow-up (median, 13 years), 1,058 men developed prostate cancer, including 103 prostate cancer–specific deaths. Aspirin use was not associated with prostate cancer development [adjusted HR, 1.07; 95% confidence interval (CI), 0.92–1.25 for any aspirin use and HR, 0.97; 95% CI, 0.78–1.19 for regular strength aspirin], but was suggestively associated with reduced prostate cancer mortality (HR, 0.66; 95% CI, 0.39–1.14 for any aspirin use and HR, 0.41; 95% CI, 0.17–1.00 for regular strength aspirin). Conclusions: Aspirin use at enrollment was tentatively associated with reduced prostate cancer mortality, but not risk, among African-American men in SCCS. Impact: Prospective SCCS data suggest that aspirin use may help prevent lethal prostate cancer among this high-risk group of men. ©2020 American Association for Cancer Research.

Improving Lifestyle Behaviors After Breast Cancer Treatment Among African American Women With and Without Diabetes: Role of Health Care Professionals - Jarvandi, S.; Pérez, M.; Margenthaler, J.; Colditz, G.A.; Kreuter, M.W.; Jeffe, D.B. (Annals of behavioral medicine : a publication of the Society of Behavioral Medicine, 2021)
BACKGROUND: Little is known about the effect of health professionals' advice on promoting healthy lifestyle behaviors (diet and exercise) among breast cancer patients. PURPOSE: To identify predictors of receiving lifestyle advice from health professionals and its impact on healthy lifestyle behaviors. METHODS: We used data from a randomized controlled trial of an interactive, cancer-communication video program using African American breast cancer survivor stories for newly diagnosed African American breast cancer patients (Stages 0-III). Participants completed five interviews over 2 years. This intervention did not significantly affect changes in quality-of-life outcomes. In secondary analysis, we examined differences in baseline variables between women with and without diabetes. Logistic regression models identified independent predictors of receiving advice from "a doctor or other health professional" to improve diet and exercise and of self-reported change in diet and exercise habits at 2 year follow-up. RESULTS: Of 193 patients included (85% of 228 enrolled), 53 (28%) had diabetes. At 2 year follow-up, a greater proportion of women with (vs. without) diabetes reported receiving advice by a doctor/health professional to improve their diet (73% vs. 57%, p = .04,). Predictors of receiving dietary advice were obesity, diabetes, and breast-conserving surgery (each p < .05). Women receiving dietary advice were 2.75 times more likely to report improving their diet (95% confidence interval: 1.17, 6.46) at follow-up, but receiving physical activity advice was not significantly associated with patients reporting an increase in exercise. CONCLUSIONS: Although receiving dietary advice predicted dietary improvements, receiving exercise advice did not lead to an increase in physical activity. CLINICAL TRIAL REGISTRATION: Trial Number NCT00929084. © Society of Behavioral Medicine 2020. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.
Keywords: Advice; Breast cancer; Diabetes; Diet; Exercise; Healthcare professionals

Health-related quality of life outcomes for the LEAP study—CALGB 70305 (Alliance): A lymphedema prevention intervention trial for newly diagnosed breast cancer patients - Naughton, M.J.; Liu, H.; Seisler, D.K.; Le-Rademacher, J.; Armer, J.M.; Oliveri, J.M.; Sloan, J.A.; Hock, K.; Schwartz, M.; Unzeitig, G.; Melnik, M.; Yee, L.D.; et al. (Cancer, 2021)
Background: Lymphedema is an adverse effect of breast cancer treatment that causes swelling and pain in the arm and hand. We tested 2 lymphedema prevention interventions and their impact on health-related quality of life (HRQOL) in a group-randomized trial at 38 cooperative group sites within the United States. Methods: Patients were recruited before breast surgery. Sites were randomly assigned to education-only (EO) lymphedema prevention or education plus exercise and physical therapy (LEAP). Lymphedema was defined as a ≥10% difference in arm volume at any time from baseline to 18 months postsurgery. HRQOL was assessed using the Functional Assessment of Cancer Therapy–Breast plus 4 lymphedema items (FACT-B+4). Longitudinal mixed model regression analysis, adjusting for key demographic and clinical variables, examined participants' HRQOL by intervention group and lymphedema status. Results: A total of 547 patients (56% LEAP) were enrolled and completed HRQOL assessments. The results revealed no differences between the interventions in preventing lymphedema (P =.37) or HRQOL (FACT-B+4 total score; P =.8777). At 18 months, the presence of lymphedema was associated with HRQOL at borderline significance (P =.0825). However, African American patients reported greater lymphedema symptoms (P =.0002) and better emotional functioning (P =.0335) than patients of other races or ethnicities. Lower HRQOL during the intervention was associated with younger age (P ≤.0001), Eastern Cooperative Oncology Group performance status >0 (P =.0002), ≥1 positive lymph nodes (P =.0009), having no education beyond high school (P <.0001), having undergone chemotherapy (P =.0242), and having had only axillary node dissection or sentinel node biopsy versus both (P =.0007). Conclusion: The tested interventions did not differ in preventing lymphedema or in HRQOL outcomes. African American women reported greater HRQOL impacts due to lymphedema symptoms than women of other races or ethnicities. © 2020 American Cancer Society
Keywords: breast cancer; lymphedema; quality of life; race; symptoms

Successful Recruitment of Black Men to Prostate Cancer Clinical Trials-A Lesson in Achievement - Hahn, A.W.; Bilen, M.A.; Agarwal, N. (JAMA network open, 2021)

Clinical Efficacy of Enzalutamide vs Bicalutamide Combined With Androgen Deprivation Therapy in Men With Metastatic Hormone-Sensitive Prostate Cancer: A Randomized Clinical Trial - Vaishampayan, U.N.; Heilbrun, L.K.; Monk, P., 3rd; Tejwani, S.; Sonpavde, G.; Hwang, C.; Smith, D.; Jasti, P.; Dobson, K.; Dickow, B.; Heath, E.I.; Semaan, L.; et al. (JAMA network open, 2021)
Importance: Black patients have been underrepresented in prospective clinical trials of advanced prostate cancer. This study evaluated the efficacy of enzalutamide compared with bicalutamide, with planned subset analysis of Black patients with metastatic hormone-sensitive prostate cancer (mHSPC), which is a disease state responsive to androgen deprivation therapy (ADT). Objective: To compare the efficacy of enzalutamide vs bicalutamide in combination with ADT in men with mHSPC, with a subset analysis of Black patients. Design, Setting, and Participants: In this randomized clinical trial, a phase 2 screening design enabled a nondefinitive comparison of the primary outcome by treatment. Patients were stratified by race (Black or other) and bone pain (present or absent). Accrual of at least 30% Black patients was required. This multicenter trial was conducted at 4 centers in the US. Men with mHSPC with no history of seizures and adequate marrow, renal, and liver function were eligible. Data analysis was performed from February 2019 to March 2020. Interventions: Participants were randomized 1:1 to receive oral enzalutamide (160 mg daily) or bicalutamide (50 mg daily) in addition to ADT. Main Outcomes and Measures: The primary end point was the 7-month prostate-specific antigen (PSA) response (SMPR) rate, a previously accepted surrogate for overall survival (OS) outcome. Secondary end points included adverse reactions, time to PSA progression, and OS. Results: A total of 71 men (median [range] age, 65 [51-86] years) were enrolled; 29 (41%) were Black, 41 (58%) were White, and 1 (1%) was Asian. Thirty-six patients were randomized to receive enzalutamide, and 35 were randomized to receive bicalutamide. Twenty-six patients (37%) had bone pain and 37 patients (52%) had extensive disease. SMPR was achieved in 30 of 32 patients (94%; 95% CI, 80%-98%) taking enzalutamide and 17 of 26 patients (65%; 95% CI, 46%-81%) taking bicalutamide (P = .008) (difference, 29%; 95% CI, 5%-50%). Among Black patients, the SMPR was 93% (95% CI, 69%-99%) among those taking enzalutamide and 42% (95% CI, 19%-68%) among those taking bicalutamide (P = .009); among non-Black patients, the SMPR was 94% (95% CI, 74%-99%) among those taking enzalutamide and 86% (95% CI, 60%-96%) among those taking bicalutamide. The 12-month PSA response rates were 84% with enzalutamide and 34% with bicalutamide. Conclusions and Relevance: The findings of this randomized clinical trial comparing enzalutamide with bicalutamide suggest that enzalutamide is associated with improved outcomes compared with bicalutamide, in terms of the rate and duration of PSA response, in Black patients with mHSPC. Trial Registration: ClinicalTrials.gov Identifier: NCT02058706.

Effect of Text Messaging on Bowel Preparation and Appointment Attendance for Outpatient Colonoscopy: A Randomized Clinical Trial - Mahmud, N.; Asch, D.A.; Sung, J.; Reitz, C.; Coniglio, M.S.; McDonald, C.; Bernard, D.; Mehta, S.J. (JAMA network open, 2021)
Importance: Outpatient colonoscopy is important for colorectal cancer screening. However, nonadherence and poor bowel preparation are common. Objective: To determine if an automated text messaging intervention with a focus on informational and reminder functions could improve attendance rates and bowel preparation quality for outpatient colonoscopy. Design, Setting, and Participants: This randomized clinical trial was conducted in an endoscopy center at an urban academic medical center. Adult patients scheduled for outpatient colonoscopy between January and September 2019 were enrolled by telephone call (early phase) or by automated text message (late phase). Data were analyzed from October 2019 to January 2020. Interventions: After enrollment, patients were randomized in a 1:1 ratio to usual care (ie, written instructions and nurse telephone call) or to the intervention (ie, usual care plus an automated series of 9 educational or reminder text messages in the week prior to scheduled colonoscopy). Main Outcomes and Measures: The primary outcome was appointment attendance rate with good or excellent bowel preparation. Secondary outcomes included appointment attendance rate, bowel preparation quality (poor or inadequate, fair or adequate, and good or excellent), and cancellation lead time (in days). Results: Among 753 patients included and randomized in the trial (median [interquartile range] age, 56 [49-64] years; 364 [48.3%] men; 429 [57.2%] Black), 367 patients were randomized to the intervention group and 386 patients were randomized to the control group. There was no significant difference in the primary outcome between groups (patients attending appointments with good or excellent bowel preparation: intervention, 195 patients [53.1%]; control, 210 patients [54.4%]; P = .73), including when stratified by early or late phase enrollment groups. Similarly, there were no significant differences in secondary outcomes. Conclusions and Relevance: This randomized clinical trial found no significant difference in appointment attendance or bowel preparation quality with an automated text messaging intervention compared with the usual care control. Future work could optimize the content and delivery of text message interventions or identify patient subgroups that may benefit from this approach. Trial Registration: ClinicalTrials.gov Identifier: NCT03710213.

The Effectiveness of Shared Compared to Informed Decision Making for Prostate Cancer Screening in a High-Risk African American Population: A Randomized Control Trial - Carlson, D.S.; Grivas, P.; Wei, W.; Dhillon, P.K.; Abraksia, S. (Cancer Investigation, 2021)
Background: Prostate cancer incidence and mortality in the United States in African Americans (AA) are higher than in Caucasians. Eastern Cuyahoga County in Ohio is majority AA and is considered an underserved population particularly vulnerable to healthcare disparities. There is a paucity of data about shared decision making among high-risk AA men with regard to prostate cancer screening. This study aims to examine shared versus informed decision making (SDM versus IDM) in a randomized, control trial among a large, high-risk AA population. Methods: Patients were included in annual one-day outreach events, each held over 3 years (2017–2019), and were randomized at each event into IDM (control) and SDM (investigational) groups and then were offered screening via prostate specific antigen (PSA) and digital rectal exam (DRE). The primary endpoints were proportion of participants over 40 who did not demonstrate decisional conflict about prostate cancer screening measured by the SURE score, as well as change of knowledge score about prostate cancer screening. Results: Overall, 175 patients were enrolled in the trial; 79 in the SDM arm and 96 in the IDM arm. The investigational (SDM) arm had 3/79 (3.9%) conflict versus 6/96 (6.4%) in the control (IDM) arm (p = 0.74). With regard to knowledge improvement, the SDM cohort demonstrated improvement following educational tools for 66/79 (81%) of participants versus 76/96 (79%) in the IDM cohort (p = 0.85). There was no difference in the proportion (63%) of participants in either group who found the information very helpful (using a Likert scale). Conclusions: Our education-based study showed no significant difference between SDM and IDM with regard to decisional conflict about prostate cancer screening. The study also demonstrated significant improvement in knowledge about prostate cancer screening in a high-risk AA population in both groups. Our results should be interpreted with caution due to several limitations; however, the study can serve as a benchmark for future studies in this very important topic. © 2021 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: African American; education; high-risk population; Prostate cancer screening; randomized controlled trial; shared decision making informed decision making

IMPROVE, a community-based exercise intervention versus support group to improve functional and health outcomes among older African American and Non-Hispanic White breast cancer survivors from diverse socioeconomic backgrounds: Recruitment strategies and baseline characteristics - Owusu, C.; Nock, N.L.; Feuntes, V.; Margevicius, S.; Hergenroeder, P.; Austin, K.; Bennet, E.; Cerne, S.; Moore, H.C.F.; Petkac, J.; Schluchter, M.; Schmitz, K.H.; et al. (Cancer, 2021)
Background: Behavioral intervention studies in older breast cancer survivors, particularly older African American (AA) and socioeconomic status–disadvantaged breast cancer survivors, are lacking. To inform future studies, the authors examined recruitment strategies in older breast cancer survivors who participated in an exercise intervention study. Methods: IMPROVE is a randomized trial designed to evaluate a group-based exercise intervention versus a support group (ClinicalTrials.gov identifier, NCT02763228). Participants were aged ≥65 years who had survived stage I through III breast cancer and were within 5 years of treatment completion. Participants were recruited through multiple approaches, including peripheral, linguistic, and constituent-involving strategies that incorporated the identification of potentially eligible patients from 3 local hospitals and from State of Ohio registries and through direct clinician and community organization referrals. Results: Between October 2016 and November 2019, 7487 patients were screened, 4790 were potentially eligible, and 213 were randomized into the study. The eligible:randomization rates were 4.4% overall and 84%, 8%, and 2% for recruitment using direct referrals, hospital registries, and state registries, respectively. The median age of the randomized cohort was 70 years (range, 65-88 years) and included 44% AA and 44% socioeconomic status–disadvantaged breast cancer survivors. Compared with all registry-eligible patients, directly referred-eligible patients were more likely to be AA versus Non-Hispanic White (41% vs 19%; P =.006), to be contacted successfully (100% vs 33%; P <.0001), and to accept study participation (88% vs 16%; P <.0001). Conclusions: Direct referrals appeared to be the most efficient strategy for recruiting AA survivors. Behavioral intervention studies seeking to target older AA and socioeconomic status–disadvantaged breast cancer survivors should include strategies that foster direct referrals to study participation. © 2021 American Cancer Society
Keywords: African American (AA); exercise; older breast cancer; socioeconomic status-disadvantaged

Representativeness of black patients in cancer clinical trials sponsored by the national cancer institute compared with pharmaceutical companies - Unger, J.M.; Hershman, D.L.; Osarogiagbon, R.U.; Gothwal, A.; Anand, S.; Dasari, A.; Overman, M.; Loree, J.M.; Raghav, K. (JNCI Cancer Spectrum, 2021)
Background: Many clinical trials supporting new drug applications underrepresent minority patients. Trials conducted by the National Cancer Institute's National Clinical Trial's Network (NCTN) have greater outreach to community sites, potentially allowing better representation. We compared the representation of Black patients in pharmaceutical company-sponsored cancer clinical trials with NCTN trials and with the US cancer population. Methods: We established a large cohort of study publications representing the results of trials that supported new US Food and Drug Administration drug approvals from 2008 to 2018. NCTN trial data were from the SWOG Cancer Research Network. US cancer population rates were estimated using Surveillance, Epidemiology, and End Results survey data. We compared the proportion of Black patients by enrollment year for each cancer type and overall. Tests of proportions were used. All statistical tests were 2-sided. Results: A total 358 trials (pharmaceutical company-sponsored trials, 85; SWOG trials, 273) comprised of 93 825 patients (pharmaceutical company-sponsored trials, 46 313; SWOG trials, 47 512) for 15 cancer types were analyzed. Overall, the proportion of Black patients was 2.9% for pharmaceutical company-sponsored trials, 9.0% for SWOG trials, and 12.1% for the US cancer population (P<.001 for each pairwise comparison). These findings were generally consistent across individual cancer types. Conclusions: The poor representation of Black patients in pharmaceutical company-sponsored trials supporting new drug applications could result in the use of new drugs with little data about efficacy or side effects in this key population. Moreover, because pharmaceutical company-sponsored trials test the newest available therapies, limited access to these trials represents a disparity in access to potential breakthrough therapies. © 2020 Oxford University Press. All rights reserved.

A case-control study examining disparities in clinical trial participation among breast surgical oncology patients - Fayanju, O.M.; Ren, Y.; Thomas, S.M.; Greenup, R.A.; Hyslop, T.; Shelley Hwang, E.; Stewart, J.H., IV (JNCI Cancer Spectrum, 2021)
Background: Clinical trial participation among racial and ethnic minorities remains low despite national efforts. We sought to determine how participation in clinical trials by breast surgical oncology patients has changed over time and what characteristics are associated with participation. Methods:Women with breast cancer enrolled in National Cancer Institute-sponsored, cooperative-group trials from 2000 to 2012 and who underwent oncologic surgery (n 17 125) were compared with trial-eligible women in the National Cancer Database diagnosed in 2000-2012 (n 792 719). Race-specific trial participation was plotted over time by income and reported as a proportion of the combined cohorts. Factors associated with trial participation were estimated using logistic regression; we report odds ratios (ORs) with 95% confidence intervals (CIs). A P value less than .05 was considered statistically significant for all analyses. All tests were two-sided. Results: Participation declined across all groups over time because of a decrease in the scale and number of trials. In 2000- 2003, Asian-Pacific Islander (7.17%), Hispanic (3.48%), and white (7.13%) patients from the highest income group had higher participation than their lower-income counterparts (Asian-Pacific Islander: 3.95%; Hispanic: 2.67%; white: 5.96%), but by 2008- 2012, only high-income white patients participated more than lower-income whites (0.32% vs 0.25%, all P<.01). Black (OR 0.80, 95% CI 0.75 to 0.85) and Hispanic (OR 0.84, 95% CI 0.77 to 0.92) patients were less likely to participate than whites, but there were statistically significant interactions between income and race and ethnicity, with high-income black patients being approximately 50% less likely to participate than lower-income blacks (all P<.001). Conclusions: Multifaceted interventions addressing the intersectionality of race, ethnicity, and other patient characteristics are needed to address persistent disparities in trial participation among breast surgical oncology patients. © The Author(s) 2020.

Does Scalp Cooling Have the Same Efficacy in Black Patients Receiving Chemotherapy for Breast Cancer? - Dilawari, A.; Gallagher, C.; Alintah, P.; Chitalia, A.; Tiwari, S.; Paxman, R.; Adams-Campbell, L.; Dash, C. (Oncologist, 2021)
Lessons Learned: Despite U.S. Food and Drug Administration approval to reduce alopecia, data on efficacy of scalp cooling in Black patients with cancer are limited by lack of minority representation in prior clinical trials. Scalp cooling devices may have less efficacy in Black patients; additional studies are required to explore the possible causes for this, including hair texture and cap design. Background: The Paxman scalp cooling (SC) device is U.S. Food and Drug Administration (FDA)-approved for prevention of chemotherapy-induced alopecia. Studies report 50%–80% success rates and high patient satisfaction, yet there have been no studies of SC in Black patients. We conducted a phase II feasibility study of Paxman SC with a planned enrollment of 30 Black patients receiving chemotherapy for stage I–III breast cancer. Methods: Black patients who planned to receive at least four cycles of chemotherapy with non-anthracycline (NAC) or anthracycline (AC) regimens were eligible. Alopecia was assessed by trained oncology providers using the modified Dean scale (MDS) prior to each chemotherapy session. Distress related to alopecia was measured by the Chemotherapy Alopecia Distress Scale (CADS). Results: Fifteen patients enrolled in the intervention before the study was closed early because of lack of efficacy. Median MDS and CADS increased after SC, suggesting increased hair loss (p <.001) and alopecia distress (p =.04). Only one participant was successful in preventing significant hair loss; the majority stopped SC before chemotherapy completion because of grade 3 alopecia (>50% hair loss). Conclusion: SC may not be efficacious in preventing alopecia in Black women. Differences in hair thickness, hair volume, and limitations of cooling cap design are possible contributing factors. © AlphaMed Press; the data published online to support this summary are the property of the authors.
Keywords: Breast cancer; Chemotherapy-induced alopecia; Paxman scalp cooling device

Integration of electronic pathology reporting with clinical trial matching for advanced prostate cancer - Borno, H.T.; Duffy, C.; Zhang, S.; Canchola, A.J.; Loya, Z.; Golden, T.; Oh, D.L.; Odisho, A.Y.; Gomez, S. (Urologic Oncology: Seminars and Original Investigations, 2021)
Introduction: Racial/ethnic diversity in prostate cancer (CaP) clinical trials (CTs) is essential to address CaP disparities. California Cancer Registry mandated electronic reporting (e-path) of structured data elements from pathologists diagnosing cancer thereby creating an opportunity to identify and approach patients rapidly. This study tested the utility of an online CT matching tool (called Trial Library) used in combination with e-path to improve matching of underrepresented CaP patients into CTs at time of diagnosis. Methods: This was a nonrandomized, single-arm feasibility study among patients with a new pathologic diagnosis of high-risk CaP (Gleason Score ≥8). Eligible patients were sent recruitment materials and enrolled patients were introduced to Trial Library. Results: A total of 419 case listings were assessed. Patients were excluded due to physician contraindication, not meeting baseline eligibility, or unable to be reached. Final participants (N = 52) completed a baseline survey. Among study participants, 77% were White, 10% were Black/Hispanic/Missing, and 14% were Asian. The majority of the study participants were over 65 years of age (81%) and Medicare insured (62%). Additionally, 81% of participants reported using the Internet to learn about CaP. The majority (62%) of participants reported that Trial Library increased their interest in CT participation. Conclusions: The current study demonstrated that leveraging structured e-path data reporting to a population-based cancer registry to recruit men with high risk CaP to clinical research is feasible and acceptable. We observed that e-path may be linked with an online CT matching tool, Trial Library. Future studies will prioritize recruitment from reporting facilities that serve more racially/ethnically diverse patient populations. © 2020 Elsevier Inc.
Keywords: Cancer disparities; Clinical trials; Early case ascertainment; Electronic pathology; Prostate cancer

Phase II study of neratinib in older adults with HER2 amplified or HER2/3 mutated metastatic breast cancer - Yuan, Y.; Lee, J.S.; Yost, S.E.; Stiller, T.; Blanchard, M.S.; Padam, S.; Katheria, V.; Kim, H.; Sun, C.; Tang, A.; Martinez, N.; Patel, N.D.; et al. (Journal of Geriatric Oncology, 2021)
Objective: The tolerability and efficacy of targeted therapy in older adults with cancer has not been adequately studied. Neratinib is a novel HER1, HER2, HER4 tyrosine kinase inhibitor that has recently been granted FDA approval for treatment of breast cancer. The major toxicity of neratinib is diarrhea, which affects up to 90% of patients. This phase II trial evaluates the safety and tolerability of neratinib in adults ≥60. Methods: Patients aged 60 or older with histologically proven metastatic breast cancer and HER2 amplification (defined by ASCO/CAP guideline) or HER2/HER3 activating mutation were enrolled to receive neratinib at 240 mg daily in 28-day cycles. The association between tolerability, defined as dose reduction and number of completed courses, and log2 Cancer and Aging Research Group (CARG) toxicity risk score was assessed using a Student's t-test and linear regression, respectively. Response rate, progression free survival, and overall survival were also evaluated. Results: 25 patients were enrolled with median age of 66 (range 60–79). Seventy-six percent of patients were white, 16% Asian, and 8% African-American. Seventy-six percent were patients with hormone receptor (HR) positive metastatic breast cancer (MBC) and 24% were patients with HR negative MBC. Median number of prior lines of metastatic therapy were 3 (range 0–11). 20/25 (80%) had worst grade toxicities ≥2. A total of 9/25 (36%) had grade 3 toxicities including 5/20 (20%) diarrhea, 2/20 (8%) vomiting, and 2/20 (8%) abdominal pain. There were no grade 4 or 5 toxicities. A total of 9/25 (36%) had dose reduction, and 2/25 (8%) discontinued therapy due to toxicity. The association between dose reductions and CARG toxicity score reached borderline statistical significance suggesting a trend with participants with higher CARG toxicity risk scores being more likely to require a dose modification (p = 0.054). 1/25 (4%) had a partial response, 11/25 (44%) had stable disease, 12/25 (48%) had progression of disease, and 1/25 (4%) was not assessed. Median progression free survival (PFS) was 2.6 months (95% CI [2.56–5.26]), and median overall survival (OS) was 17.4 months (95% CI [10.3, NA]). Conclusions: Neratinib was safe in this population of older adults with HER2 amplified or HER2/3 mutated metastatic breast cancer (BC). Higher CARG toxicity risk score may be associated with greater need for dose adjustments. Future studies are needed to confirm this finding. © 2021 Elsevier Inc.
Keywords: CARG toxicity risk score; Metastatic breast cancer; Neratinib; Phase II trial

Knowledge and perceptions of BRCA1/2 genetic testing and needs of diverse women with a personal or family history of breast cancer in South Florida - Jones, T.; Howard, H.; Freeman-Costin, K.; Creighton, A.; Wisdom-Chambers, K.; Underhill-Blazey, M. (Journal of Community Genetics, 2021)
The vast majority of (BRCA1/2) genetic testing has been conducted in White women, in particular Ashkenazi Jewish women, with limited information available for Black and Hispanic women. Understanding perspectives of those who are underserved is critical to developing interventions to support inclusive approaches to genetic testing. This qualitative study explored knowledge and perceptions of BRCA1/2 genetic testing among diverse women in South Florida. We also explored participants’ information needs. Convenience sampling was used to recruit a diverse group of 15 women with a personal or family history of breast cancer. We conducted semi-structured interviews and used grounded theory method to analyze the data. Five themes were identified: (1) lacking awareness and knowledge of BRCA1/2 genetic testing and results among Black women, (2) perceiving BRCA1/2 genetic testing as beneficial to themselves and a way to be proactive about cancer risk, (3) perceiving BRCA1/2 genetic testing as beneficial to family members, (4) interactions with healthcare providers and the healthcare system that shape genetic testing experiences, and (5) information needs for reducing cancer risk and promoting health. Our findings suggest that diverse underserved women perceived genetic testing as beneficial to themselves and family members. Women needed more information about the BRCA genes and genetic testing, prevention strategies, and the latest breast cancer research. Healthcare providers, particularly nurse practitioners, need to engage diverse high-risk women in discussions about their cancer risk, address unmet information needs, and, in particular, educate Black women about the benefits of pursuing genetic testing. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.
Keywords: BRCA1 and BRCA2; Breast cancer; Diverse women; Genetic testing; Personal or family history; Qualitative research

Racial differences in veterans’ response to a standard vs. patient-centered decision aid for prostate cancer: Implications for decision making in African American and White men - Langford, A.T.; Scherer, L.D.; Ubel, P.A.; Holmes-Rovner, M.; Scherr, K.A.; Fagerlin, A. (Patient Education and Counseling, 2020)
Objective: To determine whether racial differences exist in patient preferences for prostate cancer treatment after being informed about options using a patient-centered vs. a standard decision aid (DA). Methods: This article reports secondary analyses of a large study of men diagnosed with early stage prostate cancer. Men were recruited from 4 VA Health Systems and randomized to receive a patient-centered or standard DA about prostate cancer treatment options. Data were collected at 1) baseline, 2) after reading the DA but prior to diagnosis, and 3) after receiving a cancer diagnosis and meeting with a urologist. Results: White patients who received the patient-centered DA written at a 7th grade reading level were more likely to prefer active surveillance and less likely to prefer radiation compared to those who received the standard DA written at >9th grade reading level. African American patients’ treatment preferences did not differ as a function of DA. Conclusions: When informed about prostate cancer treatment options through a patient-centered DA, White patients changed their treatment preferences but African American patients did not. Practice Implications: As DAs are increasingly being used in clinical practice, more research is needed regarding the efficacy, relevance, and receptivity of DAs for African Americans. © 2020 Elsevier B.V.
Keywords: African Americans; Decision making; Patient preference; Prostatic neoplasms; Race factors; Therapy

Characteristics Associated with Participation in ENGAGED 2 - A Web-based Breast Cancer Risk Communication and Decision Support Trial - Wernli, K.J.; Bowles, E.A.; Knerr, S.; Leppig, K.A.; Ehrlich, K.; Gao, H.; Schwartz, M.D.; O'Neill, S.C. (The Permanente journal, 2020)
PURPOSE: We evaluated demographic and clinical characteristics associated with participation in a clinical trial testing the efficacy of an online tool to support breast cancer risk communication and decision support for risk mitigation to determine the generalizability of trial results. METHODS: Eligible women were members of Kaiser Permanente Washington aged 40-69 years with a recent normal screening mammogram, heterogeneously or extremely dense breasts and a calculated risk of > 1.67% based on the Breast Cancer Surveillance Consortium 5-year breast cancer risk model. Trial outcomes were chemoprevention and breast magnetic resonance imaging by 12-months post-baseline. Women were recruited via mail with phone follow-up using plain language materials notifying them of their density status and higher than average breast cancer risk. Multivariable logistic regression calculated independent odds ratios (ORs) for associations between demographic and clinical characteristics with trial participation. RESULTS: Of 2,569 eligible women contacted, 995 (38.7%) participated. Women with some college (OR = 1.99, 95% confidence interval [CI] 1.34-2.96) or college degree (OR = 3.35, 95% CI 2.29-4.90) were more likely to participate than high school-educated women. Race/ethnicity also was associated with participation (African-American OR = 0.50, 95% CI 0.29-0.87; Asian OR = 0.22, 95% CI 0.12-0.41). Multivariate adjusted ORs for family history of breast/ovarian cancer were not associated with trial participation. DISCUSSION: Use of plain language and potential access to a website providing personal breast cancer risk information and education were insufficient in achieving representative participation in a breast cancer prevention trial. Additional methods of targeting and tailoring, potentially facilitated by clinical and community outreach, are needed to facilitate equitable engagement for all women. Copyright © 2020 The Permanente Press. All rights reserved.

Screening strategies for the detection of anal high-grade squamous intraepithelial lesions in women living with HIV - Chiao, E.Y.; Lensing, S.Y.; Wiley, D.J.; Deshmukh, A.A.; Lee, J.; Darragh, T.M.; Einstein, M.H.; Jay, N.; Berry-Lawhorn, J.M.; Palefsky, J.M.; Wilkin, T.; Barroso, L.F.; et al. (AIDS (London, England), 2020)
OBJECTIVE: HIV-infected women (WLHIV) have more than 10-fold higher risk for squamous cell cancer of the anus. Experts suggest cytology-based strategies developed for cervical cancer screening may prevent anal cancer by detecting anal cytologic or histological high-grade squamous intraepithelial lesion (hHSIL) for treatment. Currently, there is no consensus on anal-hHSIL screening strategies for WLHIV. DESIGN: Between 2014 and 2016, 276 WLHIV were recruited at 12 US AIDS Malignancy Consortium clinical trials sites to evaluate hHSIL prevalence and (test) screening strategies. METHODS: Participants completed detailed questionnaire, underwent anal assessments including high-risk human papillomavirus (hrHPV) testing using hrHPV-Hybrid Capture 2 (HC2) and hrHPV-APTIMA, anal cytology, and concurrent high-resolution anoscopy. Screening test characteristics for predicting hHSIL validated by central review of histologic diagnosis were estimated sensitivity, specificity, positive predictive value, and false-omission rate. Paired analyses compared sensitivity and specificity for hrHPV single tests to anal cytology alone. RESULTS: 83% (229/276) of enrolled WLHIV had complete anal assessment data and were included in this analysis. Mean age was 50, 62% black and 60 (26%) had hHSIL. Anal cyotology (>atypical squamous cells of undetermined significance), hrHPV-HC2, and hrHPV-APTIMA sensitivity estimates were similarly high (83, 77, and 75%, respectively, P values > 0.2). Specificity was higher for both hrHPV-APTIMA and hrHPV-HC2 compared with anal cytology (67 vs. 50%, P < 0.001) and (61 vs. 50%, P = 0.020), respectively. CONCLUSION: Anal hrHPV testing demonstrated similar sensitivity for anal cytology (>atypical squamous cells of undetermined significance) to predict anal hHSIL. Among tests with similar sensitivity, the specificity was significantly higher for hrHPV-APTIMA and hrHPV-HC2. Thus, anal hrHPV testing may be an important alternative strategy to anal cytology for anal hHSIL screening among WLHIV.

Tailoring virtual human-delivered interventions: A digital intervention promoting colorectal cancer screening for Black women - Vilaro, M.J.; Wilson-Howard, D.S.; Griffin, L.N.; Tavassoli, F.; Zalake, M.S.; Lok, B.C.; Modave, F.P.; George, T.J.; Carek, P.J.; Krieger, J.L. (Psycho-Oncology, 2020)
Objective: Despite efforts to reduce cancer disparities, Black women remain underrepresented in cancer research. Virtual health assistants (VHAs) are one promising digital technology for communicating health messages and promoting health behaviors to diverse populations. This study describes participant responses to a VHA-delivered intervention promoting colorectal cancer (CRC) screening with a home-stool test. Methods: We recruited 53 non-Hispanic Black women 50 to 73 years old to participate in focus groups and think-aloud interviews and test a web-based intervention delivered by a race- and gender-concordant VHA. A user-centered design approach prioritized modifications to three successive versions of the intervention based on participants' comments. Results: Participants identified 26 cues relating to components of the VHA's credibility, including trustworthiness, expertise, and authority. Comments on early versions revealed preferences for communicating with a human doctor and negative critiques of the VHA's appearance and movements. Modifications to specific cues improved the user experience, and participants expressed increased willingness to engage with later versions of the VHA and the screening messages it delivered. Informed by the Modality, Agency, Interactivity, Navigability Model, we present a framework for developing credible VHA-delivered cancer screening messages. Conclusions: VHAs provide a systematic way to deliver health information. A culturally sensitive intervention designed for credibility promoted user interest in engaging with guideline-concordant CRC screening messages. We present strategies for effectively using cues to engage audiences with health messages, which can be applied to future research in varying contexts. © 2020 The Authors. Psycho-Oncology published by John Wiley & Sons Ltd.
Keywords: colorectal neoplasms; cues; early detection of cancer; health communication; internet-based intervention; oncology; psycho-oncology; qualitative research

Pre-diagnostic allostatic load and health-related quality of life in a cohort of Black breast cancer survivors - Xing, C.Y.; Doose, M.; Qin, B.; Lin, Y.; Carson, T.L.; Plascak, J.J.; Demissie, K.; Hong, C.-C.; Bandera, E.V.; Llanos, A.A.M. (Breast Cancer Research and Treatment, 2020)
Purpose: To determine the association of pre-diagnostic allostatic load (AL) with health-related quality of life (HRQOL) among Black women with breast cancer. Methods: In a sample of 409 Black women with non-metastatic breast cancer enrolled in the Women’s Circle of Health Follow-Up Study (WCHFS), two pre-diagnostic AL measures were estimated using medical records data from up to 12 months prior to breast cancer diagnosis: AL-lipid/metabolic profile-based measure and AL-inflammatory profile-based measure. HRQOL was assessed approximately 24 months post diagnosis, using the Functional Assessment of Cancer Therapy-Breast Cancer (FACT-B) instrument, including 5 subscale scores [presented by physical well-being (PWB), social & family well-being (SFWB), emotional well-being (EWB), functional well-being (FWB), and breast cancer-specific scale (BCS)] and 3 derived total scores [presented by trial outcome index (TOI), Functional Assessment of Cancer Therapy-General (FACT-G) and FACT-B]. We used multivariable logistic regression models, using dichotomized AL scores (lower AL: 0–3 points, higher AL: 4–8 points), to assess the associations between the two pre-diagnostic AL measures and HRQOL. Results: Higher pre-diagnostic AL was associated with poorer FWB and lower FACT-G, but these associations were statistically significant for the AL-inflammatory profile-based measure (FWB: OR 1.63, 95% CI 1.04, 2.56; FACT-G: OR 1.62, 95% CI 1.04, 2.54), but not the AL-lipid/metabolic profile-based measure (FWB: OR 1.45, 95% CI 0.81, 2.59; FACT-G: OR 1.33, 95% CI 0.75, 2.37). Conclusion: These findings suggest that higher AL, particularly when measured using the inflammatory profile-based measure, was associated with poorer HRQOL, namely FWB and FACT-G, among Black breast cancer survivors. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Allostatic load; Black women; Breast cancer survivorship; Health-related quality of life; Longitudinal study

Racial and ethnic disparities in care for health system-affiliated physician organizations and non-affiliated physician organizations - Timbie, J.W.; Kranz, A.M.; DeYoreo, M.; Eshete-Roesler, B.; Elliott, M.N.; Escarce, J.J.; Totten, M.E.; Damberg, C.L. (Health Services Research, 2020)
Objective: To assess racial and ethnic disparities in care for Medicare fee-for-service (FFS) beneficiaries and whether disparities differ between health system-affiliated physician organizations (POs) and nonaffiliated POs. Data Sources: We used Medicare Data on Provider Practice and Specialty (MD-PPAS), Medicare Provider Enrollment, Chain, and Ownership System (PECOS), IRS Form 990, 100% Medicare FFS claims, and race/ethnicity estimated using the Medicare Bayesian Improved Surname Geocoding 2.0 algorithm. Study Design: Using a sample of 16 007 POs providing primary care in 2015, we assessed racial/ethnic disparities on 12 measures derived from claims (2 cancer screenings; diabetic eye examinations; continuity of care; two medication adherence measures; three measures of follow-up visits after acute care; all-cause emergency department (ED) visits, all-cause readmissions, and ambulatory care-sensitive admissions). We decomposed these “total” disparities into within-PO and between-PO components using models with PO random effects. We then pair-matched 1853 of these POs that were affiliated with health systems to similar nonaffiliated POs. We examined differences in within-PO disparities by affiliation status by interacting each nonwhite race/ethnicity with an affiliation indicator. Data Collection/Extraction methods: Medicare Data on Provider Practice and Specialty identified POs billing Medicare; PECOS and IRS Form 990 identified health system affiliations. Beneficiaries age 18 and older were attributed to POs using a plurality visit rule. Principal Findings: We observed total disparities in 12 of 36 comparisons between white and nonwhite beneficiaries; nonwhites received worse care in 10. Within-PO disparities exceeded between-PO disparities and were substantively important (>=5 percentage points or>=0.2 standardized differences) in nine of the 12 comparisons. Among these 12, nonaffiliated POs had smaller disparities than affiliated POs in two comparisons (P <.05): 1.6 percentage points smaller black-white disparities in follow-up after ED visits and 0.6 percentage points smaller Hispanic-white disparities in breast cancer screening. Conclusions: We find no evidence that system-affiliated POs have smaller racial and ethnic disparities than nonaffiliated POs. Where differences existed, disparities were slightly larger in affiliated POs. © Health Research and Educational Trust
Keywords: delivery of health care; health care disparities; primary health care; quality of health care; race factors

Erratum regarding missing Declaration of Competing Interest statements in previously published articles (Contemporary Clinical Trials Communications (2019) 16, (S2451865419302236), (10.1016/j.conctc.2019.100461)) (Contemporary Clinical Trials Communications, 2020)
Declaration of Competing Interest statements were not included in the published version of the following articles that appeared in previous issues of Contemporary Clinical Trials Communications. The appropriate Declaration/Competing Interest statements, provided by the Authors, are included below. 1. “Intestinal-level anti-inflammatory bioactivities of catechin-rich green tea: Rationale, design, and methods of a double-blind, randomized, placebo-controlled crossover trial in metabolic syndrome and healthy adults” [Contemporary Clinical Trials Communications, 2019; 17: 100495] https://doi.org/10.1016/j.conctc.2019.100495 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.2. “Trauma Management Therapy and Prolonged Exposure Therapy for PTSD in an active duty sample: Design and methodology of a randomized clinical trial” [Contemporary Clinical Trials Communications, 2019; 17: 100491] https://doi.org/10.1016/j.conctc.2019.100491 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.3. “Virtual reality for pain management in patients with heart failure: Study rationale and design” [Contemporary Clinical Trials Communications, 2019; 16: 100470] https://doi.org/10.1016/j.conctc.2019.100470 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.4. “Recruitment and retention of families interested in a parent-based pediatric obesity intervention” [Contemporary Clinical Trials Communications, 2019; 16: 100467] https://doi.org/10.1016/j.conctc.2019.100467 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.5. “2D (2 Dimensional) TEQR design for Determining the optimal Dose for safety and efficacy” [Contemporary Clinical Trials Communications, 2019; 16: 100461] https://doi.org/10.1016/j.conctc.2019.100461 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.6. “Design of a novel digital intervention to promote healthy weight management among postpartum African American women” [Contemporary Clinical Trials Communications, 2019; 16: 100460] https://doi.org/10.1016/j.conctc.2019.100460 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.7. “Integrating smartphone technology, social support and the outdoor built environment to promote community-based aerobic and resistance-based physical activity: Rationale and study protocol for the ‘ecofit’ randomized controlled trial” [Contemporary Clinical Trials Communications, 2019; 16: 100457] https://doi.org/10.1016/j.conctc.2019.100457 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.8. “Qualitative analysis of COACH: A community-based behavioral intervention to reduce obesity health disparities within a marginalized community” [Contemporary Clinical Trials Communications, 2019; 16: 100452] https://doi.org/10.1016/j.conctc.2019.100452 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.9. “Statistical considerations for testing an AI algorithm used for prescreening lung CT images” [Contemporary Clinical Trials Communications, 2019; 16: 100434] https://doi.org/10.1016/j.conctc.2019.100434 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.10. “Study protocol: Randomized controlled trial of web-based decision support tools for high-risk women and healthcare providers to increase breast cancer chemoprevention” [Contemporary Clinical Trials Communications, 2019; 16: 100433] https://doi.org/10.1016/j.conctc.2019.100433 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.11. “Bayesian adaptive randomization trial of intravenous ketamine for veterans with late-life, treatment-resistant depression” [Contemporary Clinical Trials Communications, 2019; 16: 100432] https://doi.org/10.1016/j.conctc.2019.100432 Declaration of competing interest: The authors declare the following financial interests/personal relationships which may be considered as potential competing interests: Dr. Sanjay Mathew has served as a consultant to Allergan, Alkermes, Bracket, Clexio Biosciences, Janssen, Perception Neurosciences, and Sage Therapeutics. He has served as a co-investigator for clinical trials funded by NeuroRx and Janssen and has received research support from Biohaven Pharmaceuticals and VistaGen Therapeutics. Dr. Marijn Lijffijt has served as principal investigator for trials funded by NeuroRx and Vistagen Therapeutics.12. “A descriptive research: Exclusion from submitted clinical data package in the review process of new drug approval due to GCP violation in Japan” [Contemporary Clinical Trials Communications, 2019; 15: 100416] https://doi.org/10.1016/j.conctc.2019.100416 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.13. “Ultrafiltration-profiled hemodialysis to reduce dialysis-related cardiovascular stress: Study protocol for a randomized controlled trial” [Contemporary Clinical Trials Communications, 2019; 15: 100415] https://doi.org/10.1016/j.conctc.2019.100415 Declaration of competing interest: In the last 3 years, JEF has received speaking honoraria from American Renal Associates, the American Society of Nephrology, Dialysis Clinic, Inc., the National Kidney Foundation, and multiple universities. JEF is on the medical advisory board of NxStage Medical, Inc. and has received consulting fees from Fresenius Medical Care, North America and AstraZeneca. In the last 3 years, MMA has received investigator-initiated research funding from the Renal Research Institute, a subsidiary of Fresenius Medical Care, North America and honoraria from the International Society of Nephrology. The remaining authors have no competing interests.14. “Efficacy of smoking cessation with varenicline plus counselling for e-cigarettes users (VAREVAPE): A protocol for a randomized controlled trial” [Contemporary Clinical Trials Communications, 2019; 15: 100412] https://doi.org/10.1016/j.conctc.2019.100412 Declaration of competing interest: “The authors declare the following financial interests/personal relationships which may be considered as potential competing interests: PC is fixed-term researcher at University of Catania, Italy and won the 2015 unrestricted grant from Pfizer,GRAND, Global Research Award for Nicotine Dependence, that as declared in the text support this study. MM is fixed-term researcher at Centro per la Prevenzione e Cura del Tabagismo, University of Catania. In relation to his work in the area of tobacco control and respiratory diseases, P has received lecture fees and research funding from Pfizer, Inc., GlaxoSmithKline plc, CV Therapeutics, NeuroSearch A/S, Sandoz, MSD, Boehringer Ingelheim, Novartis, Duska Therapeutics, and Forest Laboratories. He has also served as a consultant for Pfizer, Inc., Global Health Alliance for treatment of tobacco dependence, CV Therapeutics, NeuroSearch A/S, Boehringer Ingelheim, Duska Therapeutics, Forest Laboratories, ECITA (Electronic Cigarette Industry Trade Association, in the UK), and Health Diplomat (consulting company that delivers solutions to global health problems with special emphasis on harm minimization). Lecture fees from a number of European EC industry and trade associations (including Fédération Interprofessionnelle de la VAPE in France and Federazione Italiana Esercenti Svapo Elettronico in Italy) were directly donated to vaper advocacy no-profit organizations. He is currently Head of the European Technical Committee for standardization on “Requirements and test methods for emissions of electronic cigarettes” (CEN/TC 437; WG4). He is also founder of the Center of Excellence for the acceleration of Harm Reduction at the University of Catania (CoEHAR), which has received a grant from the Foundation for a Smoke Free World to support 8 independent investigator-initiated research projects on tobacco harm reduction, and scientific advisor for LIAF, Lega Italiana Anti Fumo (Italian acronym for Italian Anti- Smoking League). The other authors have no conflict of interests to declare.15. “Recruitment challenges in stroke neurorecovery clinical trials” [Contemporary Clinical Trials Communications, 2019; 15: 100404] https://doi.org/10.1016/j.conctc.2019.100404 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper. © 2020

Race-dependent differences in risk, genomics, and Epstein-barr virus exposure in monoclonal gammopathies: Results of SWOG S0120 - Dhodapkar, M.V.; Sexton, R.; Hoering, A.; van Rhee, F.; Barlogie, B.; Orlowski, R. (Clinical Cancer Research, 2020)
Purpose: Risk of multiple myeloma is increased in African American (AA) populations compared with European American (EA) cohorts. Current estimates of risk of progression of monoclonal gammopathy of undetermined significance (MGUS) are based largely on studies in EA cohorts. Prospective analyses of this risk in AA cohorts are lacking. Patients and Methods: Between 2003 and 2011, 331 eligible patients with IgG/A monoclonal gammopathy were enrolled in a prospective observational trial (SWOG S0120). Results: Of 331 eligible patients, 57 (17%) were of AA descent. The risk of transformation to clinical malignancy in AA patients was significantly lower than in non-AA cohort (2-year risk 5% vs. 15%; 5-year risk 13% vs. 24%; log-rank P ¼ 0.047). Differences in risk were evident for both MGUS and asymptomatic multiple myeloma. Gene expression profile (GEP) of CD138-purified plasma cells revealed that all molecular multiple myeloma subsets can be identified in both cohorts. However, the proportion of patients with high-risk GEP risk score (GEP-70 gene risk > -0.26) was lower in the AA cohort (0% vs. 33%, P ¼ 0.01). AA cohorts also have higher levels of antibodies against Epstein-Barr nuclear antigen-1 (EBNA-1; P < 0.001). Conclusions: These data provide the first prospective evidence that multiple myeloma precursor states in AA patients may have lower risk of disease compared with non-AA counterparts with lower incidence of high-risk GEP and increased EBV seropositivity. Race-dependent differences in biology and clinical risk of gammopathy may impact optimal management of these patients. © 2020 American Association for Cancer Research.

Increasing accrual of minority patients in breast cancer clinical trials - Trant, A.A.; Walz, L.; Allen, W.; DeJesus, J.; Hatzis, C.; Silber, A. (Breast Cancer Research and Treatment, 2020)
Background: Black and Hispanic patients participate in clinical trials at lower rates than white patients nationally; lack of diversity in clinical trials prevents appropriate safety and efficacy testing of new treatments in these populations. Methods: The Oncology Welcomes New Haven into Trials (OWN IT) initiative at the Yale Cancer Center used a multi-tiered approach to improve breast cancer minority clinical trial accrual through community focus groups, ongoing community outreach, institutional executive council representation, grand rounds presentation, and didactic lectures with healthcare providers. Eligibility criteria of breast cancer trials at Smilow Cancer Center were reviewed using clinicaltrials.gov. Also, an anonymous, 5-min survey was conducted at regular visits with Smilow Breast Center patients to gauge awareness of and access to clinical trials. Survey data were compared to the Yale Cancer Center Clinical Trials Office, Connecticut Tumor Registry, and U.S. Census records. Two-tailed Fisher’s tests were used for all analyses. Results: There was a significant increase in the number of minority patients who participated in clinical trials at Smilow Cancer Center from 2016 (95/750) to 2018 (155/944) (p = 0.0325). Two hundred patients participated in the survey; response rate 92%. There was no significant difference in the rate at which patients were invited to participate in clinical trials or the rate at which they declined to participate based on race or ethnicity. Black and Hispanic patients were significantly less likely to be aware of clinical trials than white patients (p <.001). The review of eligibility criteria showed that over half of the studies reviewed had restrictions regarding increased liver function tests, and many restricted the participation of patients with other chronic conditions. Conclusions: Low participation in clinical trials among black and Hispanic patients is likely multifaceted. This study indicated that there are likely structural factors at work which can be modified with institutional effort. The role of patient education regarding clinical trials and accrual should be studied further as should eligibility criteria as a potential barrier to participation. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Breast cancer; Clinical trials; Eligibility criteria; Health disparities

A novel CNN algorithm for pathological complete response prediction using an I-SPY TRIAL breast MRI database - Liu, M.Z.; Mutasa, S.; Chang, P.; Siddique, M.; Jambawalikar, S.; Ha, R. (Magnetic Resonance Imaging, 2020)
Purpose: To apply our convolutional neural network (CNN) algorithm to predict neoadjuvant chemotherapy (NAC) response using the I-SPY TRIAL breast MRI dataset. Methods: From the I-SPY TRIAL breast MRI database, 131 patients from 9 institutions were successfully downloaded for analysis. First post-contrast MRI images were used for 3D segmentation using 3D slicer. Our CNN was implemented entirely of 3 × 3 convolutional kernels and linear layers. The convolutional kernels consisted of 6 residual layers, totaling 12 convolutional layers. Dropout with a 0.5 keep probability and L2 normalization was utilized. Training was implemented by using the Adam optimizer. A 5-fold cross validation was used for performance evaluation. Software code was written in Python using the TensorFlow module on a Linux workstation with one NVidia Titan X GPU. Results: Of 131 patients, 40 patients achieved pCR following NAC (group 1) and 91 patients did not achieve pCR following NAC (group 2). Diagnostic accuracy of our CNN two classification model distinguishing patients with pCR vs non-pCR was 72.5 (SD ± 8.4), with sensitivity 65.5% (SD ± 28.1) and specificity of 78.9% (SD ± 15.2). The area under a ROC Curve (AUC) was 0.72 (SD ± 0.08). Conclusion: It is feasible to use our CNN algorithm to predict NAC response in patients using a multi-institution dataset. © 2020 Elsevier Inc.

Physiologic vasomotor symptoms are associated with verbal memory dysfunction in breast cancer survivors - Fogel, J.; Rubin, L.H.; Kilic, E.; Walega, D.R.; Maki, P.M. (Menopause (New York, N.Y.), 2020)
OBJECTIVE: Vasomotor symptoms (VMS), sleep disturbance, and cognitive complaints are common among women with a history of breast cancer and contribute to decreased quality of life. Studies in healthy women showed an association between verbal memory performance and physiologic VMS measured with ambulatory skin conductance monitors but not with VMS by self-report. We hypothesized that we would find a similar association in women with breast cancer. METHODS: Participants included 30 female breast cancer survivors (mean age 52.7 y; 26.7% African-American) with moderate-to-severe VMS enrolled in a larger clinical trial of a nonhormonal intervention for VMS. At baseline, participants completed assessments of physiologic VMS, actigraphy-based assessments of sleep, questionnaires about mood, and two tests of verbal memory - Logical Memory (LM) and the California Verbal Learning Test (CVLT). Using baseline data, we conducted multivariate regression analyses to examine the association between VMS and memory, controlling for sleep and other factors. RESULTS: On average, women reported 46% of total physiologic VMS. A higher frequency of physiologic VMS - but not reported VMS - was significantly associated with lower scores on the California Verbal Learning Test short-delay free recall (r[28] = -0.41, P = 0.03), long-delay free recall (r[28] = -0.42, P = 0.03), and total clustering, (r[28] = -0.39, P = 0.04). These associations were independent of sleep, mood, and other factors. CONCLUSIONS: Independent of their effect on sleep, VMS may be a modifiable contributor to memory difficulties in women with breast cancer. These findings underscore the importance of objective measurement of VMS in cognitive studies. : Video Summary:http://links.lww.com/MENO/A623.

A population-based study of invitation to and participation in clinical trials among women with early-stage breast cancer - Patel, M.A.; Shah, J.L.; Abrahamse, P.H.; Jagsi, R.; Katz, S.J.; Hawley, S.T.; Veenstra, C.M. (Breast Cancer Research and Treatment, 2020)
Purpose: Although many studies clearly demonstrate disparities in cancer clinical trial enrollment, there is a lack of consensus on potential causes. Furthermore, virtually nothing is known about associations between patients’ decision-making style and their participation in clinical trials. Methods: Women with newly diagnosed, stage 0–II breast cancer reported to the Georgia and Los Angeles County Surveillance, Epidemiology, and End Results (SEER) registries in 2013–2014 were surveyed approximately seven months after diagnosis. We investigated two primary outcome variables: (1) invitation to participate in a clinical trial, (2) participation in a clinical trial. We evaluated bivariate associations using Chi-squared tests and used multivariable logistic regression models to investigate associations between patient variables, including decision-making style, and the primary outcomes. Results: 2578 patients responded (71% response rate); 30% were > age 65, 18% were black, 18% were Latina, 29% had ≤ high school education. 10% of patients reported invitation to participate in a clinical trial; 5% reported participation in a clinical trial. After adjustment younger age, receipt of chemotherapy or radiation, disease stage, and a more rational (versus more intuitive) decision-making style were associated with a higher odds of invitation to participate. Being married was associated with a higher odds of participation; having an annual family income ≥ $40,000 was associated with a lower odds of participation. Conclusions: 10% of patients reported invitation to participate in a clinical trial, and half of these reported participation. Invitation to participate varied by age and decision-making style, and participation varied by marital status and income. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Breast cancer; Clinical trial; Disparities; Enrollment; Participation

The Problem of Underrepresentation: Black Participants in Lifestyle Trials Among Patients with Prostate Cancer - Zuniga, K.B.; Borno, H.; Chan, J.M.; Van Blarigan, E.L.; Friedlander, T.W.; Wang, S.; Zhang, L.; Kenfield, S.A. (Journal of Racial and Ethnic Health Disparities, 2020)
Introduction: Healthy lifestyle behaviors are an essential component of prostate cancer survivorship; however, it is unknown whether Black participants are adequately represented in randomized controlled trials (RCTs) on lifestyle interventions. The goal of this study was to identify types of lifestyle RCTs that may require improved recruitment resources to enhance generalizability of lifestyle recommendations to Black patients. Materials and Methods: ClinicalTrials.gov was used to identify lifestyle RCTs among patients with prostate cancer. Using racial distribution data from the Surveillance, Epidemiology, and End Results (SEER) program as a reference, one-sample proportion tests were performed to assess adequate recruitment of Black participants. Results: Of 31 lifestyle trials, one trial reported race-specific results. Proportion of Black participants was acquired from 26 trials. Compared to the US population, Black participants were overrepresented in the overall study population (17% versus 15%, p = 0.019). Black participants were underrepresented in trials exploring exercise interventions (9% versus 15%, p = 0.041), trials among patients with advanced disease (9% versus 16%, p ' 0.001), and in university-funded trials (12% versus 15%, p = 0.026). Conclusions: The reporting of race data, and race-specific results when feasible, is essential for clinicians to accurately generalize findings from lifestyle trials. Additional resources may be necessary to aid in strategic recruitment of Black participants for trials on exercise interventions, trials among patients with advanced disease, and in university-funded trials. © 2020, W. Montague Cobb-NMA Health Institute.
Keywords: African Americans; Diet; Exercise; Prostatic neoplasms; Randomized controlled trial

Subtype-specific risk factors for postmenopausal breast cancer: findings from the PLCO trial - Abdel-Rahman, O.; Tang, P.A.; Cheung, W.Y. (Clinical and Translational Oncology, 2020)
Objective: The aim of this analysis is to evaluate the relative weight of different epidemiological risk factors on the development of different breast cancer subtypes (i.e. luminal, Her2+ overexpressed or triple negative). Methods: De-identified datasets of female participants recruited within the Prostate, Lung, Colorectal, and Ovarian (PLCO) trial were accessed. Multivariate Cox regression analysis was utilized to assess factors affecting the development of breast cancer (regardless of subtype). Additional multivariate analyses were conducted to assess factors affecting the development of the three principal subtypes of breast cancer (ER+/Her2− breast cancer; Her2 overexpressed breast cancer and ER−/Her2− breast cancer). Results: A total of 73,570 eligible participants were evaluated in the current analysis of which 2370 participants subsequently developed breast cancer. The following factors were associated with a higher risk of ER+/Her2− breast cancer: white race (P < 0.001), nulliparity (P < 0.001), higher body mass index (P = 0.003), prior exposure to hormone treatment (P = 0.004) and breast cancer in first-degree female relatives (P < 0.001). The following factors were associated with a higher risk of Her2 overexpressed breast cancer: prior exposure to hormone treatment (P = 0.002) and breast cancer in first-degree female relatives (P = 0.001). The following factors were associated with a higher risk of ER−/Her2− breast cancer: black race (P = 0.013), younger age (P = 0.017) and breast cancer in first-degree female relatives (P 0.023). Conclusions: There is considerable heterogeneity in risk factors among patients with different subtypes of breast cancer. In particular, factors associated with high estrogen levels seem to be associated with luminal breast cancer rather than other breast cancer subtypes. © 2020, Federación de Sociedades Españolas de Oncología (FESEO).
Keywords: Breast cancer; Epidemiology; Risk factors; Subtypes

A Multi-faceted Intervention Aimed at Black-White Disparities in the Treatment of Early Stage Cancers: The ACCURE Pragmatic Quality Improvement trial - Cykert, S.; Eng, E.; Manning, M.A.; Robertson, L.B.; Heron, D.E.; Jones, N.S.; Schaal, J.C.; Lightfoot, A.; Zhou, H.; Yongue, C.; Gizlice, Z. (Journal of the National Medical Association, 2020)
Background: Reports continue to show that Blacks with curable lung or breast cancer complete treatment less often than similar Whites contributing to worse survival. ACCURE is an intervention trial designed to address this problem. Patients and methods: A pragmatic, quality improvement trial comparing an intervention group to retrospective and concurrent controls. Patients with early stage breast or lung cancer aged 18 to 85 were enrolled (N = 302) at 2 cancer centers between April 2013 and March 2015 for the intervention component. Data from patients seen between January 2007 and December 2012 with these diagnoses were obtained to establish control completion rates. Concurrent data for non-study patients were used to identify secular trends. The intervention included: a real time registry derived from electronic health records of participants to signal missed appointments or unmet care milestones, a navigator, and clinical feedback. The primary outcome was “Treatment Complete”, a composite variable representing completion of surgery, recommended radiation and chemotherapy for each patient. Results: The mean age in the intervention group was 63.1 years; 37.1% of patients were Black. Treatment completion in retrospective and concurrent controls showed significant Black-White differences (Blacks (B) 79.8% vs. Whites (W) 87.3%, p < 0.001; 83.1% B vs. 90.1% W, p < 0.001, respectively). The disparity lessened within the intervention (B 88.4% and W 89.5%, p = 0.77). Multivariate analyses confirmed disparities reduction. OR for Black-White disparity within the intervention was 0.98 (95% CI 0.46–2.1); Black completion in the intervention compared favorably to Whites in retrospective (OR 1.6; 95% CI 0.90–2.9) and concurrent (OR 1.1; 95% CI 0.59–2.0) controls. Conclusion: A real time registry combined with feedback and navigation improved completion of treatment for all breast and lung cancer patients and narrowed disparities. Similar multi-faceted interventions could mitigate disparities in the treatment of other cancers and chronic conditions. © 2019 National Medical Association
Keywords: Cancer disparities; Institutional racism; Intervention; Quality improvement

A phase I/II study of docetaxel in combination with pegylated liposomal doxorubicin in metastatic castration-resistant prostate cancer - Laber, D.A.; Eatrides, J.; Jaglal, M.V.; Haider, M.; Visweshwar, N.; Patel, A. (Medical Oncology, 2020)
Taxanes and anthracyclines have been among the best-studied chemotherapy classes in castration-resistant prostate cancer (CRPC). Docetaxel (D) 75 mg/m2 every 3 weeks has been the standard first line chemotherapy for CRPC. Encapsulation of doxorubicin in polyethylene glycol-coated liposomes (PLD) was developed to enhance the safety and efficacy of conventional doxorubicin. We hypothesize that the combination of weekly low dose-D and PLD would result in a high response rate and low toxicity. Eligibility criteria included metastatic progressive CRPC, no prior D or PLD and good organ function. After a short phase I with no dose-limiting toxicity, D 30 mg/m2 was administered on days 1, 8 and 15; and PLD 30 mg/m2 on day 1 only, every 28 days. Thirty-seven patients were enrolled. The PSA response rate was 53%. Twenty-two subjects had measurable disease; one (5%) achieved complete response, five (23%) partial response, and twelve (54%) stable disease. Twenty-seven patients (73%) manifested pain relief. The median time to progression was 3.7 months for all patients and 7.9 months for responders. Median overall survival was 16.3 months. Grade 4 neutropenia without infection and anemia occurred in 1 patient each. Grade 3 treatment-related toxicities included: 15% fatigue; 9% neutropenia, anemia and nausea; 6% dehydration and hand-foot syndrome; and 3% infection, febrile neutropenia, thrombosis, stomatitis, headache, vomiting, weight loss and weakness. In this non-comparative study D-PLD demonstrated a higher activity than previously reported with single agent D with favorable side effect profile. A phase 3 study would be needed to evaluate the true benefit of this combination. ClinicalTrials.gov Identifier: NCT00456989. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Castration-resistant prostate cancer; Docetaxel; Doxorubicin; Phase 2 clinical trial; Polyethylene glycol-coated liposome

Genetic testing and surveillance of young breast cancer survivors and blood relatives: A cluster randomized trial - Katapodi, M.C.; Ming, C.; Northouse, L.L.; Duffy, S.A.; Duquette, D.; Mendelsohn-Victor, K.E.; Milliron, K.J.; Merajver, S.D.; Dinov, I.D.; Janz, N.K. (Cancers, 2020)
We compared a tailored and a targeted intervention designed to increase genetic testing, clinical breast exam (CBE), and mammography in young breast cancer survivors (YBCS) (diagnosed <45 years old) and their blood relatives. A two-arm cluster randomized trial recruited a random sample of YBCS from the Michigan cancer registry and up to two of their blood relatives. Participants were stratified according to race and randomly assigned as family units to the tailored (n = 637) or the targeted (n = 595) intervention. Approximately 40% of participants were Black. Based on intention-to-treat analyses, YBCS in the tailored arm reported higher self-efficacy for genetic services (p = 0.0205) at 8-months follow-up. Genetic testing increased approximately 5% for YBCS in the tailored and the targeted arm (p ≤ 0.001; p < 0.001) and for Black and White/Other YBCS (p < 0.001; p < 0.001). CBEs and mammograms increased significantly in both arms, 5% for YBCS and 10% for relatives and were similar for Blacks and White/Others. YBCS and relatives needing less support from providers reported significantly higher self-efficacy and intention for genetic testing and surveillance. Black participants reported significantly higher satisfaction and acceptability. Effects of these two low-resource interventions were comparable to previous studies. Materials are suitable for Black women at risk for hereditary breast/ovarian cancer (HBOC). © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Black participants; Cancer survivorship; Cascade genetic testing in families; Family recruitment; HBOC; Statewide random sampling; Tailored intervention; Targeted intervention

The impact of a randomized dietary and physical activity intervention on chronic inflammation among obese African-American women - Babatunde, O.A., PhD; Arp Adams, S., PhD; Truman, S.; Sercy, E., MSPH; Murphy, A.E., PhD; Khan, S., MSW; Hurley, T.G., MS; Wirth, M.D., PhD; Choi, S.K., PhD; Johnson, H., BA; Hebert, J.R., ScD (Women and Health, 2020)
Lifestyle interventions may reduce inflammation and lower breast cancer (BrCa) risk. This randomized trial assessed the impact of the Sistas Inspiring Sistas Through Activity and Support (SISTAS) study on plasma C-reactive protein (CRP), interleukin-6 (IL-6) and Dietary Inflammatory Index (DII). This unblinded, dietary and physical activity trial was implemented in 337 obese (body mass index [BMI] ≥30 kg/m2) African American (AA) women recruited between 2011 and 2015 in South Carolina through a community-based participatory approach with measurements at baseline, 3 months, and 12 months. Participants were randomized into either intervention (n = 176) or wait-list control group (n = 161). Linear mixed-effect models were used for analyses of CRP and IL-6. Baseline CRP was significantly higher in those with greater obesity, body fat percentage, and waist circumference (all p <.01). No difference was observed between groups for CRP or IL-6 at 3 or 12 months; however, improvements in diet were observed in the intervention group compared to the control group (p = .02) at 3 months but were not sustained at 12 months. Although the intervention was not successful at reducing levels of CRP or IL-6, a significant decrease was observed in DII score for the intervention group, indicating short-term positive dietary change. © 2020, © 2020 Taylor & Francis Group, LLC.
Keywords: African Americans; breast cancer; c-reactive protein; dietary Inflammatory Index; inflammation

#BlackBreastsMatter: Process evaluation of recruitment and engagement of pregnant African American women for a social media intervention study to increase breastfeeding - Dauphin, C.; Clark, N.; Cadzow, R.; Saad-Harfouche, F.; Rodriguez, E.; Glaser, K.; Kiviniemi, M.; Keller, M.; Erwin, D. (Journal of Medical Internet Research, 2020)
Background: In the United States, there are lower rates of breastfeeding among African American mothers, particularly those who are younger women. Recent epidemiological studies have shown a strong association of more aggressive types of breast cancer (estrogen receptor negative) among African American women, with a higher risk in African American women who did not breastfeed their children. Objective: This study aims to describe the process evaluation of recruitment and educational strategies to engage pregnant African American participants for a pilot study designed to determine whether social media messaging about breast cancer risk reduction through breastfeeding may positively influence breastfeeding rates. Methods: This pilot study is conducted in collaboration with a local Women, Infants, and Children (WIC) organization and hospital and prenatal clinics of a local health care network. To engage African American women to enroll in the study, several methods and monitoring processes were explored, including WIC electronic text-based messages sent out to all phones of current WIC recipients (referred to as e-blasts); keyword responses to texts from flyers and posters in local community-based organizations, hospitals, and prenatal clinics; keyword responses using electronic links posted in established Facebook groups; and snowball recruitment of other pregnant women by current participants through Facebook. Once enrolled, participants were randomized to 2 study conditions: (1) an intervention group receiving messages about breast cancer risk reduction and breastfeeding or (2) a control group receiving breastfeeding-only messages. Data were obtained through electronic monitoring, SurveyMonkey, qualitative responses on Facebook, focus groups, and interviews. Results: More than 3000 text messages were sent and received through WIC e-blasts and keyword responses from flyers. A total of 472 women were recruited through WIC e-blast, and 161 responded to flyers and contacts through the local health care network, community-based organizations, Facebook, and friend referrals. A total of 633 women were assessed for eligibility to participate in the study. A total of 288 pregnant African American women were enrolled, consented, and completed presurvey assessments (102.8% of the goal), and 22 participants attended focus groups or interviews reporting on their experiences with Facebook and the educational messages. Conclusions: This process evaluation suggests that using electronic, smartphone apps with social media holds promise for both recruitment and conduct of health education intervention studies for pregnant African American women. Providing messaging and resources through social media to reinforce and educate women about breastfeeding and potentially provide lactation support is intriguing. Convenience (for researchers and participants) is an attribute of social media for this demographic of women and worthy of further research as an educational tool. © 2020 Journal of Medical Internet Research. All rights reserved.
Keywords: African American mothers; Breast cancer education; Breastfeeding; Facebook; Mobile phone; Social media

Feasibility and potential efficacy of commercial mHealth/eHealth tools for weight loss in African American breast cancer survivors: Pilot randomized controlled trial - Ferrante, J.M.; Devine, K.A.; Bator, A.; Rodgers, A.; Ohman-Strickland, P.A.; Bandera, E.V.; Hwang, K.O. (Translational Behavioral Medicine, 2020)
Weight management after breast cancer (BC) treatment in African American (AA) women is crucial to reduce comorbid conditions and health disparities. We examined feasibility and potential efficacy of commercial eHealth/mHealth tools for weight management in AA BC survivors in New Jersey. Participants (N = 35) were randomized to an intervention (SparkPeople) plus activity tracker, Fitbit Charge (n = 18), or wait-list active control group (Fitbit only, n = 17). Anthropometric, behavioral, and quality of life (QOL) outcomes were collected at baseline, 3, 6, and 12 months. Differences in outcomes were assessed using intent-to-treat analysis. Retention was 97.1%. Both groups lost weight, with no significant differences between groups. At month 6, mean weight change was: intervention: -1.71 kg (SD 2.33; p =. 006), 33.3% lost ≥3% of baseline weight; control: -2.54 kg (SD 4.00, p =. 002), 23.5% lost ≥3% weight. Intervention participants achieved significant improvements in waist circumference (-3.56 cm, SD 4.70, p =. 005), QOL (p =. 030), and use of strategies for healthy eating (p =. 025) and decreasing calories (p <. 001). Number of days logged food per week was associated with decreases in waist circumference at 6 months (β -0.79, 95% CI, -1.49, -0.09, p =. 030) and 12 months (β -2.16, 95% CI, -4.17, -0.15, p =. 038). Weight loss was maintained at 12 months. This is the first study to demonstrate potential efficacy of commercial eHealth/mHealth tools for weight loss in AA BC survivors, without additional counseling from the research team. If effective, they may be convenient weight loss tools that can be easily and widely disseminated. Clinical Trials registration: ClinicalTrials.gov NCT02699983. © 2018 Society of Behavioral Medicine 2018. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.
Keywords: African Americans; Breast cancer survivors; Fitness trackers; Health status disparities; Internet; Weight loss programs

Effect of a digital health intervention on decreasing barriers and increasing facilitators for colorectal cancer screening in vulnerable patients - Denizard-Thompson, N.M.; Miller, D.P.; Snavely, A.C.; Spangler, J.G.; Doug Case, L.; Weaver, K.E. (Cancer Epidemiology Biomarkers and Prevention, 2020)
Background: Colorectal cancer is the second leading cause of cancer-related death in the United States, in part, because one third of Americans fail to get screened. In a prior randomized controlled trial, we found that an iPad patient decision aid called Mobile Patient Technology for Health-CRC (mPATH-CRC) doubled the proportion of patients who completed colorectal cancer screening. Methods: All data for the current analysis were collected as part of a randomized controlled trial to determine the impact of mPATH-CRC on receipt of colorectal cancer screening within 24 weeks. Participants were enrolled from six community-based primary care practices between June 2014 and May 2016 and randomized to either usual care or mPATH-CRC. Six potential mediators of the intervention effect on screening were considered. The Iacobucci method was used to assess the significance of the mediation. Results: A total of 408 patients had complete data for all potential mediators. Overall, the potential mediators accounted for approximately three fourths (76.3%) of the effect of the program on screening completion. Perceived benefits, self-efficacy, ability to state a screening decision, and patient–provider discussion were statistically significant mediators. Patient–provider discussion accounted for the largest proportion of the effect of mPATH-CRC (70.7%). Conclusions: mPATH-CRC increased completion of colorectal cancer screening by affecting patient-level and system-level mediators. However, the most powerful mediator was the occurrence of a patient–provider discussion about screening. Digital interventions like mPATH-CRC are an important adjunct to the patient–provider encounter. Impact: Understanding the factors that mediated mPATH-CRC's success is paramount to developing other effective interventions. © 2020 American Association for Cancer Research.

Diversity of enrollment in prostate cancer clinical trials: current status and future directions - Rencsok, E.M.; Bazzi, L.A.; McKay, R.R.; Huang, F.W.; Friedant, A.; Vinson, J.; Peisch, S.; Zarif, J.C.; Simmons, S.; Hawthorne, K.; Villanti, P.; Kantoff, P.W.; et al. (Cancer Epidemiology Biomarkers and Prevention, 2020)
Background: Although there are considerable racial and ethnic disparities in prostate cancer incidence and mortality in the United States and globally, clinical trials often do not reflect disease incidence across racial and ethnic subgroups. This study aims to comprehensively review the reporting of race and ethnicity data and the representation of race and ethnicity across prostate cancer treatment-, prevention-, and screening-based clinical trials. Methods: Seventy-two global phase III and IV prevention, screening, and treatment prostate cancer clinical trials with enrollment start dates between 1987 and 2016 were analyzed in this study, representing a total of 893,378 individual trial participants. Availability and representation of race and ethnicity data by trial funding type, temporal changes in the racial/ethnic diversity of participants, and geographic representation of countries were assessed. Results: Of the 72 trials analyzed, 59 (81.9%) had available race data, and 11 (15.3%) of these trials additionally reported ethnicity. Of the trials reporting data, participants were overwhelmingly white men (with the highest proportion in U.S. nonpublicly funded trials), comprising over 96% of the study population. The proportion of white participants in prostate cancer clinical trials has remained at over 80% since 1990. Geographically, Africa and the Caribbean were particularly underrepresented with only 3% of countries included. Conclusions: Trial participants continue to be majority white despite the known racial disparities in prostate cancer clinical outcomes. Impact: Current and future trials must use novel recruitment strategies to ensure enrollment of underrepresented men. Targeting the inclusion of African and Caribbean medical centers is crucial to achieve equity in representation. © 2020 American Association for Cancer Research.

Tracking the Nonenrolled: Lung Cancer Screening Patterns Among Individuals not Accrued to a Clinical Trial - Gerber, D.E.; Hamann, H.A.; Chavez, C.; Dorsey, O.; Santini, N.O.; Browning, T.; Ochoa, C.D.; Adesina, J.; Natchimuthu, V.S.; Steen, E.; Zhu, H.; Lee, S.J.C. (Clinical Lung Cancer, 2020)
Introduction: For lung cancer screening, the available data are often derived from patients enrolled prospectively in clinical trials. We, therefore, investigated lung cancer screening patterns among individuals eligible for, but not enrolled in, a screening trial. Patients and Methods: From February 2017 through February 2019, we enrolled subjects in a trial examining telephone-based navigation during low-dose computed tomography (LDCT) for lung cancer screening. We identified patients for whom LDCT was ordered and who were approached, but not enrolled, in the trial. We categorized nonenrollment as the patient had declined or could not be reached. We compared the characteristics and LDCT completion rates among these groups and the enrolled population using the 2-sample t test and χ2 test. Results: Of 900 individuals approached for participation (mean age, 62 years; 45% women, 53% black), 447 were enrolled in the screening clinical trial. No significant demographic differences were found between the enrolled and nonenrolled cohorts. Of the 453 individuals not enrolled, 251 (55%) had declined participation and 202 (45%) could not be reached, despite up to 6 attempts. LDCT completion was significantly associated with enrollment status: 81% of enrolled individuals, 73% of individuals who declined participation, and 49% of those who could not be reached (P < .001). Conclusions: In the present single-center study, demographic factors did not predict for participation in a lung cancer screening trial. Lung cancer screening adherence rates were substantially lower for those not enrolled in a screening trial, especially for those who could not be contacted. These findings may inform the broader implementation of screening programs. © 2020 Elsevier Inc. Data on lung cancer screening come from prospective clinical trials. We determined the characteristics and screening adherence among individuals eligible for, but not enrolled in, a trial. Although the demographic data did not differ, adherence was significantly lower among nonenrolled individuals, especially those who could not be reached. These findings may inform the broader implementation of screening programs. © 2020 Elsevier Inc.
Keywords: Adherence; Communication; Computed tomography; Demographics; Underserved

Clinical outcomes in men of diverse ethnic backgrounds with metastatic castration-resistant prostate cancer - Halabi, S.; Dutta, S.; Tangen, C.M.; Rosenthal, M.; Petrylak, D.P.; Thompson, I.M., Jr.; Chi, K.N.; De Bono, J.S.; Araujo, J.C.; Logothetis, C.; Eisenberger, M.A.; Quinn, D.I.; et al. (Annals of Oncology, 2020)
Background: We have shown previously in multivariable analysis that black men had 19% lower risk of death than white men with metastatic castration-resistant prostate cancer (mCRPC) treated with a docetaxel and prednisone (DP)-based regimen. The primary goal of this analysis was to compare progression-free survival (PFS), biochemical PFS, ≥50% decline in prostate-specific antigen (PSA) from baseline and objective response rate (ORR) in white, black and Asian men with mCRPC treated with a DP-based regimen. Patients and methods: Individual patient data from 8820 mCRPC men randomized on nine phase III trials to a DP-containing regimen were combined. Race used in the analysis was based on self-report. End points were PFS, biochemical PSA, ≥50% decline in PSA from baseline and ORR. The proportional hazards and the logistic regression models were employed to assess the prognostic importance of race in predicting outcomes adjusting for established prognostic factors. Results: Of 8820 patients, 7528 (85%) were white, 500 (6%) were black, 424 were Asian (5%) and 368 (4%) had race unspecified. Median PFS were 8.3 [95% confidence interval (CI) 8.2–8.5], 8.2 (95% CI 7.4–8.8) and 8.3 (95% CI 7.6–8.8) months in white, black and Asian men, respectively. Median PSA PFS were 9.9 (95% CI 9.7–10.4), 8.5 (95% CI 8.0–10.3) and 11.1 (95% CI 9.9–12.5) months in white, black and Asian men, respectively. Conclusions: We observed no differences in clinical outcomes by race and ethnic groups in men with mCRPC enrolled on these phase III clinical trials with DP. © 2020 European Society for Medical Oncology
Keywords: biochemical progression; disparity; docetaxel; objective response rate; progression-free survival; PSA decline

Pharmacist intervention in colorectal cancer screening initiative - Holle, L.M.; Levine, J.; Buckley, T.; White, C.M.; White, C.; Hadfield, M.J. (Journal of the American Pharmacists Association, 2020)
Objectives: To assess the novel approach of using the community pharmacist as the primary health care team member to facilitate colorectal cancer (CRC) risk counseling and screening in socioeconomically disadvantaged populations. Setting: A collaborative effort between the UConn Health Colon Cancer Prevention Program and UConn School of Pharmacy in conjunction with large independent chain pharmacies (medium to medium-high volume) located in metropolitan areas of Connecticut, including Hartford, Bridgeport, New Haven, and Stamford. Pharmacies located in hospitals, across the street from a large physician practice, or within the community. Practice description: The study involved 2 phases. The first phase involved education and training for community pharmacists regarding counseling approaches for patients on the topic of CRC. The second phase of the study involved patient recruitment and counseling with subsequent fecal immunohistochemical testing (FIT). Practice innovation: A community pharmacist provided face-to-face counseling on CRC risk factor reduction and provided CRC screening to patients who were without insurance or underinsured. No CRC screening or education program existed beforehand. Evaluation: A target sample size of 60 participants was needed with a type 1 error rate of 5% and a power of 80%. Exploration of variables using multivariate logistic regression model included any variable with a univariate P < 0.2. Multivariate P values < 0.05 were considered independent predictors. Results: After approaching 312 consumers, 16 of them consented to the study. The majority of participants (88%) were African American or Latino, and 69% were currently unemployed. Eight participants agreed to complete FIT, and 88% of participants completed FIT correctly. Only 1 positive FIT result was observed, but a subsequent colonoscopy was negative. Of the 12 questions that assessed baseline CRC knowledge in the initial survey, 16 participants answered an average of 2.6 (range, 0–6, SD, 1.6) questions incorrectly. Only 4 participants completed the follow-up survey of CRC knowledge and program satisfaction; thus, exploration of variables was not conducted. Patients indicated high satisfaction with the program of education and FIT dispensing. Conclusion: This study faced difficulty in recruiting pharmacists to participate, with the main reason being lack of compensation and disruption to workflow. Patient participation in the trial was also low because of a lack of time or interest in participation. Of the patients who did participate, the level of satisfaction in having the pharmacist speak to them about CRC screening was high. This service is an excellent example of how the pharmacist can provide a more accessible, convenient, and responsive approach to patients’ needs while improving health equity. Future studies that employ a revenue model to build the infrastructure and capacity necessary to offer this service efficiently and consistently are needed. © 2020 American Pharmacists Association®

A Phase I Study of Safety, Pharmacokinetics, and Pharmacodynamics of Concurrent Everolimus and Buparlisib Treatment in Advanced Solid Tumors - Owonikoko, T.K.; Harvey, R.D.; Carthon, B.; Chen, Z.; Lewis, C.; Collins, H.; Zhang, C.; Lawson, D.H.; Alese, O.B.; Bilen, M.A.; Sica, G.L.; Steuer, C.E.; et al. (Clinical Cancer Research, 2020)
Purpose: Concurrent inhibition of mTOR and PI3K led to improved efficacy in preclinical models and provided the rationale for this phase I study of everolimus and buparlisib (BKM120) in patients with advanced solid tumor. Patients and Methods: We used the Bayesian Escalation with Overdose Control design to test escalating doses of everolimus (5 or 10 mg) and buparlisib (20, 40, 60, 80, and 100 mg) in eligible patients. Pharmacokinetic assessment was conducted using blood samples collected on cycle 1, days 8 and 15. Pharmacodynamic impact on mTOR/PI3K pathway modulation evaluated in paired skin biopsies collected at baseline and end of cycle 1. Results: We enrolled 43 patients, median age of 63 (range, 39–78) years; 25 (58.1%) females, 35 (81.4%) Caucasians, and 8 (18.6%) Blacks. The most frequent toxicities were hyperglycemia, diarrhea, nausea, fatigue, and aspartate aminotransferase elevation. Dose-limiting toxicities observed in 7 patients were fatigue (3), hyperglycemia (2), mucositis (1), acute kidney injury (1), and urinary tract infection (1). The recommended phase II dose (RP2D) for the combination was established as everolimus (5 mg) and buparlisib (60 mg). The best response in 27 evaluable patients was progressive disease and stable disease in 3 (11%) and 24 (89%), respectively. The median progression-free survival and overall survival were 2.7 (1.8–4.2) and 9 (6.4–13.2) months. Steady-state pharmacokinetic analysis showed dose-normalized maximum concentrations and AUC values for everolimus and buparlisib in combination to be comparable with single-agent pharmacokinetic. Conclusions: The combination of everolimus and buparlisib is safe and well-tolerated at the RP2D of 5 and 60 mg on a continuous daily schedule. © 2020 American Association for Cancer Research.

Healthcare utilization and cost of care in elderly breast cancer patients enrolled in SWOG clinical trials - Hershman, D.L.; Till, C.; Wright, J.D.; Accordino, M.; Vaidya, R.; Barlow, W.E.; Ramsey, S.; Unger, J.M. (Breast Cancer Research and Treatment, 2020)
Importance: Patients with cancer are at risk for unplanned hospitalizations during treatment which can increase the cost of care. Objectives: To determine demographic and clinical factors associated with healthcare utilization and costs among clinical trial participants. Design, setting, and patients: We conducted a retrospective analysis among breast cancer patients over the age of 65 treated on SWOG clinical trials from 1999 to 2011 with trial data linked to Medicare claims. Main outcomes and measures: The outcomes were healthcare utilization (emergency room visits (ER), hospitalizations) and costs from Medicare Claims. Demographic, clinical, and prognostic factors were captured from clinical trial records. We identified cardiovascular comorbidities/risk factors (CVD-RFs) of diabetes, hypertension, hypercholesterolemia, and coronary artery disease (CAD) from Medicare claims. Multivariable logistic and linear regression were used to assess the association between CVD-RFs and outcomes. Results: Among the 708 patients included in the analysis, 160 (22.6%) experienced 234 separate hospitalizations, and 193 (27.3%) experienced 311 separate ER visits. Black race was associated with an increase in hospitalizations (OR [95% CI], 2.52 [1.10–5.79], p = 0.03), but not emergency room visits compared to white race. Diabetes, hypertension, hypercholesterolemia, and CAD were all independently associated with increased risk of both hospitalizations and ER visit. Hypertension had the strongest association, with more than a threefold risk of hospitalization for those with hypertension compared to those without (OR [95% CI], 3.16 [1.85–5.40], p < 0.001). For those with ≥ 3 RFs, the risk of hospitalization was nearly 3 times greater compared to 0 or 1 CVD-RFs (OR [95% CI], 2.74 [1.71–4.38], p < 0.001). Similar results were seen for ER visits. In the first 12 months after trial registration, patients with diabetes ($38,324 vs $30,923, 23.9% increase, p = 0.05), hypercholesterolemia ($34,168 vs $30,661, 11.4% increase, p = 0.02), and CAD ($37,781 vs $31,698, 19.2% increase, p = 0.04) had statistically significantly higher total healthcare costs. Additionally, those with ≥ 2 significant CVD-RFs ($35,353 vs. $28,899, 22.3% increase, p = 0.005) had statistically significantly higher total healthcare costs. Conclusions: Among participants treated on clinical trials, black race and presence of multiple cardiovascular comorbidities was associated with a substantial increase in ER visits, hospitalizations and healthcare costs. Efforts to reduce unplanned hospitalizations should focus on this high-risk group. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Breast cancer; Elderly; Hospitalizations; Resource utilization

Outcomes Among Minority Patients With Metastatic Colorectal Cancer in a Safety-net Health Care System - Lau-Min, K.; Prakash, P.; Jo, E.; Thrift, A.P.; Hilsenbeck, S.; Musher, B.L. (Clinical Colorectal Cancer, 2020)
Metastatic colorectal cancer outcomes continue to improve, but they vary significantly by race and ethnicity. Hypothesizing that these disparities arise from unequal access to care rather than intrinsic biology, we showed that survival of 103 consecutive patients with metastatic colorectal cancer treated at an academic safety-net hospital that treats the underserved, predominantly minority population of Harris County, Texas, was superior to that of subjects enrolled in the CRYSTAL (Cetuximab Combined with Irinotecan in First-Line Therapy for Metastatic Colorectal Cancer) trial. Our findings suggest that administering high-quality comprehensive cancer care to vulnerable populations can overcome disparities reported in the medical literature. © 2020 Elsevier Inc. Background: Metastatic colorectal cancer (CRC) outcomes continue to improve, but they vary significantly by race and ethnicity. We hypothesize that these disparities arise from unequal access to care. Materials and Methods: The Harris Health System (HHS) is an integrated health delivery network that provides medical care to the underserved, predominantly minority population of Harris County, Texas. As the largest HHS facility and an affiliate of Baylor College of Medicine's Dan L. Duncan Comprehensive Cancer Center, Ben Taub Hospital (BTH) delivers cancer care through multidisciplinary subspecialty that prioritize access to care, adherence to evidence-based clinical pathways, integration of supportive services, and mitigation of financial toxicity. We performed a retrospective analysis of minority patients diagnosed with and treated for metastatic CRC at BTH between January 2010 and December 2012. Kaplan-Meier survival curves were compared with survival curves from randomized control trials reported during that time period. Results: We identified 103 patients; 40% were black, 49% were Hispanic, and 12% were Asian or Middle Eastern. Thirty-five percent reported a language other than English as their preferred language. Seventy-four percent of patients with documented coverage status were uninsured. Eighty-four percent of patients received standard chemotherapy with a clinician-reported response rate of 63%. Overall survival for BTH patients undergoing chemotherapy was superior to that of subjects enrolled in the CRYSTAL (Cetuximab Combined with Irinotecan in First-Line Therapy for Metastatic Colorectal Cancer) trial (median, 24.0 vs. 19.9 months; P = .014). Conclusion: HHS provides a health delivery infrastructure through which minority patients with socioeconomic challenges experience clinical outcomes comparable with highly selected patients enrolled in randomized control trials. Efforts to resolve CRC disparities should focus on improving access of at-risk populations to high-quality comprehensive cancer care. © 2020 Elsevier Inc.
Keywords: Black; Disparities; Hispanic; Stage 4; Survival; Underserved

Insulin resistance contributes to racial disparities in breast cancer prognosis in US women - Gallagher, E.J.; Fei, K.; Feldman, S.M.; Port, E.; Friedman, N.B.; Boolbol, S.K.; Killelea, B.; Pilewskie, M.; Choi, L.; King, T.; Nayak, A.; Franco, R.; et al. (Breast Cancer Research, 2020)
Background: Racial disparities in breast cancer survival between Black and White women persist across all stages of breast cancer. The metabolic syndrome (MetS) of insulin resistance disproportionately affects more Black than White women. It has not been discerned if insulin resistance mediates the link between race and poor prognosis in breast cancer. We aimed to determine whether insulin resistance mediates in part the association between race and breast cancer prognosis, and if insulin receptor (IR) and insulin-like growth factor receptor (IGF-1R) expression differs between tumors from Black and White women. Methods: We conducted a cross-sectional, multi-center study across ten hospitals. Self-identified Black women and White women with newly diagnosed invasive breast cancer were recruited. The primary outcome was to determine if insulin resistance, which was calculated using the homeostatic model assessment of insulin resistance (HOMA-IR), mediated the effect of race on prognosis using the multivariate linear mediation model. Demographic data, anthropometric measurements, and fasting blood were collected. Poor prognosis was defined as a Nottingham Prognostic Index (NPI) > 4.4. Breast cancer pathology specimens were evaluated for IR and IGF-1R expression by immunohistochemistry (IHC). Results: Five hundred fifteen women were recruited (83% White, 17% Black). The MetS was more prevalent in Black women than in White women (40% vs 20%, p < 0.0001). HOMA-IR was higher in Black women than in White women (1.9 ± 1.2 vs 1.3 ± 1.4, p = 0.0005). Poor breast cancer prognosis was more prevalent in Black women than in White women (28% vs 15%. p = 0.004). HOMA-IR was positively associated with NPI score (r = 0.1, p = 0.02). The mediation model, adjusted for age, revealed that HOMA-IR significantly mediated the association between Black race and poor prognosis (β = 0.04, 95% CI 0.005-0.009, p = 0.002). IR expression was higher in tumors from Black women than in those from White women (79% vs 52%, p = 0.004), and greater IR/IGF-1R ratio was also associated with higher NPI score (IR/IGF-1R > 1: 4.2 ± 0.8 vs IR/IGF-1R = 1: 3.9 ± 0.8 vs IR/IGF-1R < 1: 3.5 ± 1.0, p < 0.0001). Conclusions: In this multi-center, cross-sectional study of US women with newly diagnosed invasive breast cancer, insulin resistance is one factor mediating part of the association between race and poor prognosis in breast cancer. © 2020 The Author(s).
Keywords: Breast cancer; Cross-sectional study; Disparities; Insulin receptor; Insulin resistance; Insulin-like growth factor receptor; Prognosis

IMPROVE, a community-based exercise intervention versus support group to improve functional and health outcomes among older African American and non-Hispanic White breast cancer survivors from diverse socioeconomic backgrounds: Rationale, design and methods - Owusu, C.; Nock, N.L.; Hergenroeder, P.; Austin, K.; Bennet, E.; Cerne, S.; Moore, H.; Petkac, J.; Schluchter, M.; Schmitz, K.H.; Webb-Hooper, M.; Atkins, L.; et al. (Contemporary Clinical Trials, 2020)
Background: African Americans (AA) and socioeconomic status (SES) disadvantaged older breast cancer survivors (BCS) are more likely to experience poor functional and health outcomes. However, few studies have evaluated the putative beneficial effects of exercise on these outcomes in older racial minority and SES-disadvantaged BCS. Methods: This is a mixed-methods study that includes a randomized-controlled trial, “IMPROVE”, to evaluate a group-based exercise intervention compared to a support group program in older BCS, followed by post-intervention semi-structured interviews to evaluate the intervention. The trial aims to recruit 220 BCS with 55 in each of four strata defined by race (AA versus Non-Hispanic Whites) and SES (disadvantaged vs. non-disadvantaged). Participants are ≥65 years old and within five years of treatment completion for stage I-III breast cancer. Participants are randomized to a 52-week, three sessions/week, one-hour/session, moderate intensity aerobic and resistance group exercise intervention, (n = 110) or a 52-week, one hour/week, support group intervention [attention-control arm], (n = 110). The first 20 weeks of both programs are supervised and the last 32 weeks, unsupervised. The primary outcome is the change in Short Physical Performance Battery (SPPB) Scores at 20 weeks from baseline, between the two arms. Secondary outcomes include change in SPPB scores at 52 weeks, change in body composition and biomarkers, at 20 and 52 weeks from baseline, between arms. Discussion: Results of the trial may contribute to a better understanding of factors associated with recruitment, and acceptability, and will inform future exercise programs to optimally improve health outcomes for older BCS. © 2020 Elsevier Inc.
Keywords: African American; Cancer exercise; Older breast; socioeconomic status-disadvantaged

Preparing African American men to make informed prostate cancer screening decisions: Development and pilot testing of an interactive online decision aid - Allen, J.D.; Reich, A.; Cuevas, A.G.; Ladin, K. (JMIR mHealth and uHealth, 2020)
Background: African American men are at a higher risk of developing and dying from prostate cancer compared to white men. The serum prostate-specific antigen (PSA) screening test has a high risk of false-positive results and overdiagnosis; therefore, it is not routinely recommended. Rather, men are encouraged to make individualized decisions with their medical providers, after being fully informed about its potential benefits, limitations, and risks. Objective: This study aimed to describe the development and pilot testing of an interactive Web-based decision aid (DA; Prostate Cancer Screening Preparation [PCSPrep]) for African American men, designed to promote informed decision making for prostate cancer screening. Methods: Four focus groups (n=33) were conducted to assess men’s reactions to DAs developed in prior studies and gather information to modify the content and format. The pilot test employed a pre-posttest evaluation design. A convenience sample of 41 men aged 45-70 years with no history of prostate cancer was recruited from community settings. Participants completed online surveys before and after using PCSPrep that assessed prostate cancer screening knowledge, decision self-efficacy, decisional conflict, and preparation for decision making. Results: Use of PCSPrep was associated with a significant increase in prostate cancer knowledge (49% vs 62% correct responses; P<.001), and men also experienced less decisional conflict (24 vs 15 on a scale of 0-100; P=.008). No changes in self-efficacy about decision making or screening preferences were observed. Most men (81%) reported that using PCSPrep prepared them to make informed decisions in partnership with their provider. Conclusions: PCSPrep was an acceptable DA that improved men’s knowledge, reduced decisional conflict, and promoted the perception of being prepared for shared decision making. Further research is needed to test the DA in a larger randomized trial. ©Jennifer Dacey Allen, Amanda Reich, Adolfo G Cuevas, Keren Ladin.
Keywords: Decision making (shared); Decision support techniques; Early detection of cancer; Men’s health; Minority health; Prostate neoplasms

Dose-Dependent Increases in Ellagitannin Metabolites as Biomarkers of Intake in Humans Consuming Standardized Black Raspberry Food Products Designed for Clinical Trials - Roberts, K.M.; Grainger, E.M.; Thomas-Ahner, J.M.; Hinton, A.; Gu, J.; Riedl, K.; Vodovotz, Y.; Abaza, R.; Schwartz, S.J.; Clinton, S.K. (Molecular Nutrition and Food Research, 2020)
Scope: Black raspberry (BRB) phytochemicals demonstrate anti-carcinogenic properties in experimental models, including prostate cancer. Two BRB foods, a confection and nectar, providing a consistent and reproducible product for human clinical studies are designed and characterized. Methods and results: Men with clinically localized prostate cancer are sequentially enrolled to a control group or one of four intervention groups (confection or nectar, 10 or 20 g dose; n = 8 per group) for 4 weeks prior to prostatectomy. Primary outcomes include: safety, adherence, and ellagitannin metabolism. Adherence to the intervention is >96%. No significant (≥grade II) toxicities are detected. Urinary urolithins (A, B, C, and D) and dimethyl ellagic acid (DMEA) quantified by Ultra high performance liquid chromatography tandem mass spectroscopy (UPLC/MS/MS) indicate a dose-dependent excretion yet heterogeneous patterns among men. Men in the BRB confection groups have greater urinary excretion of the microbial urinary metabolites urolithin A and DMEA, suggesting that this food matrix provides greater colonic microflora exposure. Conclusion: Fully characterized BRB confections and nectar are ideal for food-based large phase III human clinical studies. BRB products provide a bioavailable source of BRB phytochemicals, however large inter individual variation in polyphenol metabolism suggests that host genetics, microflora, and other factors are critical to understanding bioactivity and metabolism. © 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: black raspberries; ellagitannins; polyphenol explorer database; polyphenols; urolithins

Increasing uptake of evidence-based screening services though a community health worker-delivered multimodality program: Study protocol for a randomized pragmatic trial - Carrasquillo, O.; Seay, J.; Jhaveri, V.; Long, T.; Kenya, S.; Thomas, E.; Sussman, D.; Trevil, D.; Koru-Sengul, T.; Kobetz, E. (Trials, 2020)
Background: Underserved ethnic minority populations experience significant disparities in HIV, hepatitis C virus (HCV), colorectal cancer (CRC), and cervical cancer incidence and mortality. Much of the excess burden of these diseases among underserved communities is due to lack of preventive care, including screening. Barriers to disease screening include low awareness, lack of access to care and health insurance, and cultural beliefs regarding disease prevention. Our current trial aims to examine community health worker (CHW)-delivered, home-based multi-modality screening for HIV, HCV, CRC, and cervical cancer simultaneously. Design: We are conducting a randomized pragmatic trial among 900 Haitian, Hispanic, and African-American participants from diverse underserved communities in South Florida. People between the ages of 50 and 65 who have not had appropriate HIV, HCV, CRC, and cervical cancer screening per United States Preventive Services Task Force (USPSTF) recommendations are eligible for the study. Participants are recruited by CHWs and complete a structured interview to assess multilevel determinants of disease risk. Participants are then randomized to receive HIV, HCV, CRC, and cervical cancer screening via navigation to care by a CHW (Group 1) or via CHW-delivered home-based screening (Group 2). The primary outcome is completion of screening for each of these diseases within 6 months post-enrollment. Discussion: Our trial is among the first to examine the effectiveness of a CHW-delivered, multimodality, home-based disease-screening approach. If found to be effective, this approach may represent a cost-effective strategy for disease screening within underserved and underscreened minority groups. Trial registration: Clinical Trials.gov # NCT02970136, registered November 21, 2016. © 2020 The Author(s).
Keywords: Cervical cancer; Colorectal cancer; Haitian; Hepatitis C; Hispanic; HIV; HPV; Immigrant; Screening

Prevalence of and risk factors for anal high-grade squamous intraepithelial lesions in women living with human immunodeficiency virus - Stier, E.A.; Lensing, S.Y.; Darragh, T.M.; Deshmukh, A.A.; Einstein, M.H.; Palefsky, J.M.; Jay, N.; Michael Berry-Lawhorn, J.; Wilkin, T.; Wiley, D.J.; Barroso, L.F.; Cranston, R.D.; et al. (Clinical Infectious Diseases, 2020)
Background. Women living with human immunodeficiency virus (WLHIV) have disproportionately high rates of squamous cell carcinoma of the anus compared with the general population of women. Anal high-grade squamous intraepithelial lesions (HSILs) precede anal cancer, and accurate studies of HSIL prevalence among WLHIV in the United States are lacking. Methods. The AIDS Malignancy Consortium 084 study was a multicenter national trial to evaluate the prevalence of and risk factors for anal HSIL in a US cohort. Eligible participants were WLHIV aged ≥18 years with no history of anal HSIL. Study participants had an examination including collection of cervical/vaginal and anal specimens, followed by high-resolution anoscopy with biopsy. Results. We enrolled 256 women with evaluable anal pathology. The mean age was 49.4 years, 64% women were non-Hispanic black, 67% were former or current smokers, and 56% reported ever having anal sex with a man. The median CD4 T-cell count was 664 cells/μL. The prevalence of anal histologic HSIL (hHSIL) was 27% (95% confidence interval [CI], 22%-33%). There was a strong concordance (240/254) between local and consensus pathologists for hHSIL vs less than hHSIL (κ = 0.86 [95% CI,.79-.93]). Current CD4 count of ≤200 cells/μL was the strongest predictor of consensus anal hHSIL diagnosis (adjusted odds ratio [aOR], 10.34 [95% CI, 3.47-30.87]). History of anoreceptive intercourse was also associated with hHSIL (aOR, 2.44 [95% CI, 1.22-4.76]). Conclusions. The prevalence of anal hHSIL in WLHIV in the United States was 27% in this study where all participants received high-resolution anoscopy and biopsy. © The Author(s) 2019. Published by Oxford University Press for the Infectious Diseases Society of America. All rights reserved.
Keywords: Epidemiology; HIV; HPV; HSIL; Women's health

Association of Sociodemographic and Health-Related Factors With Receipt of Nondefinitive Therapy Among Younger Men With High-Risk Prostate Cancer - Bagley, A.F.; Anscher, M.S.; Choi, S.; Frank, S.J.; Hoffman, K.E.; Kuban, D.A.; McGuire, S.E.; Nguyen, Q.-N.; Chapin, B.; Aparicio, A.; Pezzi, T.A.; Smith, G.L.; et al. (JAMA network open, 2020)
Importance: Multiple randomized clinical trials have shown that definitive therapy improves overall survival among patients with high-risk prostate cancer. However, many patients do not receive definitive therapy because of sociodemographic and health-related factors. Objective: To identify factors associated with receipt of nondefinitive therapy (NDT) among patients aged 70 years and younger with high-risk prostate cancer. Design, Setting, and Participants: This cohort study identified 72 036 patients aged 70 years and younger with high-risk prostate cancer and Charlson Comorbidity Index scores of 2 or less who were entered in the National Cancer Database between January 2004 and December 2014. Data analysis was conducted from November 2018 to December 2019. Exposure: Receipt of NDT as an initial treatment approach. Main Outcomes and Measures: Survival rates were compared based on receipt of definitive therapy or NDT, and sociodemographic and health-related factors were associated with the type of therapy received. Residual life expectancy was estimated from the National Center for Health Statistics to calculate person-years of life lost. Results: A total of 72 036 men with a median (range) age of 63 (30-70) years, Charlson Comorbidity Index scores of 2 or less, and high-risk prostate cancer without regional lymph node or distant metastatic disease were analyzed. Among eligible patients, 5252 (7.3%) received NDT as an initial therapeutic strategy. On univariate and multivariate analyses, NDT was associated with worse overall survival (univariate analysis hazard ratio, 2.54; 95% CI, 2.40-2.69; P < .001; multivariate analysis hazard ratio, 2.40; 95% CI, 2.26-2.56; P < .001). Compared with patients with private insurance or managed care, those with no insurance, Medicaid, or Medicare were more likely to receive systemic therapy only (no insurance: odds ratio [OR], 3.34; 95% CI, 2.81-3.98; P < .001; Medicaid: OR, 2.92; 95% CI, 2.48-3.43; P < .001; Medicare: OR, 1.36; 95% CI, 1.20-1.53; P < .001) or no treatment (no insurance: OR, 2.63; 95% CI, 2.24-3.08; P < .001; Medicaid: OR, 1.71; 95% CI, 1.45-2.01; P < .001; Medicare: OR, 1.14; 95% CI, 1.04-1.24; P = .004). Compared with white patients, black patients were more likely to receive systemic therapy only (OR, 1.93; 95% CI, 1.74-2.14; P < .001) or no treatment (OR, 1.46; 95% CI, 1.32-1.61; P < .001), and Hispanic patients were more likely to receive systemic therapy only (OR, 1.36; 95% CI, 1.13-1.64; P = .001) or no treatment (OR, 1.36; 95% CI, 1.14-1.60; P < .001). Between 2004 and 2014, patients without insurance or enrolled in Medicaid had 1.83-fold greater person-years of life lost compared with patients with private insurance (area under the curve, 77 600 vs 42 300 person-years of life lost). Conclusions and Relevance: In this study, receipt of NDT was associated with insurance status and race/ethnicity. While treatment decisions should be individualized for every patient, younger men with high-risk prostate cancer and minimal comorbidities should be encouraged to receive definitive local therapy regardless of other factors. These data suggest that significant barriers to life-extending treatment options for patients with prostate cancer remain.

Physical Activity Maintenance Following Home-Based, Individually Tailored Print Interventions for African American Women - Pekmezi, D.; Ainsworth, C.; Desmond, R.; Pisu, M.; Williams, V.; Wang, K.; Holly, T.; Meneses, K.; Marcus, B.; Demark-Wahnefried, W. (Health Promotion Practice, 2020)
African American women report low participation in physical activity and are disproportionately burdened by related conditions (obesity, breast, and colon cancer). Physical activity interventions have shown promising results among African American women, but most studies in this area have focused on short-term increases. More enduring changes in health behavior will be needed to eliminate existing health disparities. Thus, the current study examined 12-month physical activity and psychosocial outcomes from a pilot randomized controlled trial (N = 84) of a Home-based Individually tailored Physical activity Print (HIPP) intervention for African American women in the Deep South. Retention was 77.4% at 12 months. HIPP participants increased self-reported moderate-to-vigorous physical activity from 35.1 minutes/week (standard deviation [SD] = 47.8) at baseline to 124 minutes/week (SD = 95.5) at 12 months, compared with the wellness contact control participants who reported increases from 48.2 minutes/week (SD = 51.3) to 102.5 minutes/week (SD = 94.5) over 12 months (between-group p >.05). Results indicate that modest improvements in moderate-to-vigorous physical activity and related psychosocial variables occurred during the active intervention phase (months 0-6) and were sustained during the tapered maintenance period (months 6-12). Low-cost, high-reach, home-based strategies have great potential for supporting sustained participation in physical activity and achieving long-term health benefits among African American women in the Deep South. © 2018 Society for Public Health Education.
Keywords: behavior change; Black/African American; cancer prevention and control; health disparities; health promotion; minority health; physical activity/exercise; women’s health

Internalized HIV-Related Stigma and Breast Health Beliefs Among African–American Women Receiving Care for HIV in the USA - Fabian, K.; Molina, Y.; Kemp, C.G.; Nevin, P.E.; McCoy, K.; Simoni, J.M.; Andrasik, M.; Cohn, S.E.; Micci, S.; Rao, D. (Journal of Racial and Ethnic Health Disparities, 2020)
Objectives: African–American women suffer disproportionately from HIV, breast cancer, and other illnesses. Little is known about the relationship between internalized HIV-related stigma and health beliefs related to other illnesses, including breast cancer. Our study examined (1) the relationship between internalized HIV-related stigma and breast health beliefs over time and (2) the moderating effects of participating in a stigma reduction intervention and/or social support. Methods: Data from 239 African–American women receiving care for HIV in Chicago, IL, or Birmingham, AL, enrolled in the Unity randomized controlled trial, were used in this secondary analysis. Threat of breast cancer was measured in terms of perceived susceptibility, fear, and adverse consequences as well as an overall perceived threat of breast cancer. We used multivariate models with generalized estimating equations to examine the relationship between internalized HIV-related stigma and breast health beliefs across three time points (baseline, immediately post-workshop, and at 12-month follow-up) and to examine if the study arm (HIV stigma reduction vs. breast cancer education) or social support moderated the relationship. Results: Internalized HIV-related stigma was associated with greater overall perceived threat (p < 0.001), susceptibility (p = 0.03), fear (p < 0.001), and perceived adverse consequences (p < 0.001) of breast cancer. These associations remained consistent across study arms and across all levels of social support. Conclusions: Future studies that examine co-morbid health conditions among African–American women living with HIV should consider the impact of HIV-related stigma on attitudes and beliefs related to co-morbid conditions. © 2019, W. Montague Cobb-NMA Health Institute.
Keywords: African–American women; Breast cancer; HIV; Stigma

Association between ambient air pollution and breast cancer risk: The multiethnic cohort study - Cheng, I.; Tseng, C.; Wu, J.; Yang, J.; Conroy, S.M.; Shariff-Marco, S.; Li, L.; Hertz, A.; Gomez, S.L.; Le Marchand, L.; Whittemore, A.S.; Stram, D.O.; et al. (International Journal of Cancer, 2020)
Previous studies using different exposure methods to assess air pollution and breast cancer risk among primarily whites have been inconclusive. Air pollutant exposures of particulate matter and oxides of nitrogen were estimated by kriging (NOx, NO2, PM10, PM2.5), land use regression (LUR, NOx, NO2) and California Line Source Dispersion model (CALINE4, NOx, PM2.5) for 57,589 females from the Multiethnic Cohort, residing largely in Los Angeles County from recruitment (1993–1996) through 2010. Cox proportional hazards models were used to examine the associations between time-varying air pollution and breast cancer incidence adjusting for confounding factors. Stratified analyses were conducted by race/ethnicity and distance to major roads. Among all women, breast cancer risk was positively but not significantly associated with NOx (per 50 parts per billion [ppb]) and NO2 (per 20 ppb) determined by kriging and LUR and with PM2.5 and PM10 (per 10 μg/m3) determined by kriging. However, among women who lived within 500 m of major roads, significantly increased risks were observed with NOx (hazard ratio [HR] = 1.35, 95% confidence interval [95% CI]: 1.02–1.79), NO2 (HR = 1.44, 95% CI: 1.04–1.99), PM10 (HR = 1.29, 95% CI: 1.07–1.55) and PM2.5 (HR = 1.85, 95% CI: 1.15–2.99) determined by kriging and NOx (HR = 1.21, 95% CI:1.01–1.45) and NO2 (HR = 1.26, 95% CI: 1.00–1.59) determined by LUR. No overall associations were observed with exposures assessed by CALINE4. Subgroup analyses suggested stronger associations of NOx and NO2 among African Americans and Japanese Americans. Further studies of multiethnic populations to confirm the effects of air pollution, particularly near-roadway exposures, on the risk of breast cancer is warranted. © 2019 UICC
Keywords: air pollution; breast cancer; epidemiology; multiethnic cohort

Unpacking trial offers and low accrual rates: A qualitative analysis of clinic visits with physicians and patients potentially eligible for a prostate cancer clinical trial - Hamel, L.M.; Dougherty, D.W.; Albrecht, T.L.; Wojda, M.; Jordan, A.; Moore, T.F.; Senft, N.; Carducci, M.; Heath, E.I.; Manning, M.A.; Penner, L.A.; Kim, S.; et al. (JCO Oncology Practice, 2020)
PURPOSE Cancer clinical trial accrual rates are low, and information about contributing factors is needed. We examined video-recorded clinical interactions to identify circumstances under which patients potentially eligible for a trial at a major cancer center were offered a trial. METHODS We conducted a qualitative directed content analysis of 62 recorded interactions with physicians (n = 13) and patients with intermediate- or high-risk prostate cancer (n = 43). Patients were screened and potentially eligible for a trial. We observed and coded the interactions in 3 steps: (1) classification of all interactions as explicit offer, offer pending, trial discussed/not offered, or trial not discussed; (2) in interactions with no explicit offer, classification of whether the cancer had progressed; (3) in interactions classified as progression but no trial offered, identification of factors discussed that may explain the lack of an offer. RESULTS Of the 62 interactions, 29% were classified as explicit offer, 12% as offer pending, 18% as trial discussed/not offered, and 39% as trial not discussed. Of those with no offer, 57% included information that the cancer had not progressed. In 68% of the remaining interactions with patients whose cancer had progressed but did not receive an offer, reasons for the lack of offer were identified, but in 32%, no explanation was provided. CONCLUSION Even in optimal circumstances, few patients were offered a trial, often because their cancer had not progressed. Findings support professional recommendations to broaden trial inclusion criteria. Findings suggest accrual rates should reflect the proportion of eligible patients who enroll. © 2019 by American Society of Clinical Oncology.

Effect of a Patient Decision Aid on Lung Cancer Screening Decision-Making by Persons Who Smoke: A Randomized Clinical Trial - Volk, R.J.; Lowenstein, L.M.; Leal, V.B.; Escoto, K.H.; Cantor, S.B.; Munden, R.F.; Rabius, V.A.; Bailey, L.; Cinciripini, P.M.; Lin, H.; Housten, A.J.; Luckett, P.G.; et al. (JAMA network open, 2020)
Importance: Lung cancer screening with low-dose computed tomography lowers lung cancer mortality but has potential harms. Current guidelines support patients receiving information about the benefits and harms of lung cancer screening during decision-making. Objective: To examine the effect of a patient decision aid (PDA) about lung cancer screening compared with a standard educational material (EDU) on decision-making outcomes among smokers. Design, Setting, and Participants: This randomized clinical trial was conducted using 13 state tobacco quitlines. Current and recent tobacco quitline clients who met age and smoking history eligibility for lung cancer screening were enrolled from March 30, 2015, to September 12, 2016, and followed up for 6 months until May 5, 2017. Data analysis was conducted between May 5, 2017, and September 30, 2018. Interventions: Participants were randomized to the PDA video Lung Cancer Screening: Is It Right for Me? (n = 259) or to EDU (n = 257). Main Outcomes and Measures: The primary outcomes were preparation for decision-making and decisional conflict measured at 1 week. Secondary outcomes included knowledge, intentions, and completion of screening within 6 months of receiving the intervention measured by patient report. Results: Of 516 quit line clients enrolled, 370 (71.7%) were younger than 65 years, 320 (62.0%) were female, 138 (26.7%) identified as black, 47 (9.1%) did not have health insurance, and 226 (43.8%) had a high school or lower educational level. Of participants using the PDA, 153 of 227 (67.4%) were well prepared to make a screening decision compared with 108 of 224 participants (48.2%) using EDU (odds ratio [OR], 2.31; 95% CI, 1.56-3.44; P < .001). Feeling informed about their screening choice was reported by 117 of 234 participants (50.0%) using a PDA compared with 66 of 233 participants (28.3%) using EDU (OR, 2.56; 95% CI, 1.72-3.79; P < .001); 159 of 234 participants (68.0%) using a PDA compared with 110 of 232 (47.4%) participants using EDU reported being clear about their values related to the harms and benefits of screening (OR, 2.37; 95% CI, 1.60-3.51; P < .001). Participants using a PDA were more knowledgeable about lung cancer screening than participants using EDU at each follow-up assessment. Intentions to be screened and screening behaviors did not differ between groups. Conclusions and Relevance: In this study, a PDA delivered to clients of tobacco quit lines improved informed decision-making about lung cancer screening. Many smokers eligible for lung cancer screening can be reached through tobacco quit lines. Trial Registration: ClinicalTrials.gov identifier: NCT02286713.

Effect of Supplementation with Marine ω-3 Fatty Acid on Risk of Colorectal Adenomas and Serrated Polyps in the US General Population: A Prespecified Ancillary Study of a Randomized Clinical Trial - Song, M.; Lee, I.-M.; Manson, J.E.; Buring, J.E.; Dushkes, R.; Gordon, D.; Walter, J.; Wu, K.; Chan, A.T.; Ogino, S.; Fuchs, C.S.; Meyerhardt, J.A.; et al. (JAMA Oncology, 2020)
Importance: Marine ω-3 fatty acid has been suggested to protect against colorectal cancer. Objective: To assess the effect of daily marine ω-3 fatty acid supplementation on the risk of colorectal cancer precursors, including conventional adenomas and serrated polyps. Design, Setting, and Participants: This study was a prespecified ancillary study of the placebo-controlled randomized clinical trial VITAL (Vitamin D and Omega-3 Trial). An intention-to-treat analysis was used to examine the effect of daily marine ω-3 supplements among 25871 adults in the US general population (including 5106 African American persons) free of cancer and cardiovascular disease at enrollment. Randomization was from November 2011 to March 2014, and intervention ended as planned on December 31, 2017. Interventions: Marine ω-3 fatty acid, 1 g daily (which included eicosapentaenoic acid, 460 mg, and docosahexaenoic acid, 380 mg) and vitamin D3 (2000 IU daily) supplements. Main Outcomes and Measures: Risk of conventional adenomas (including tubular adenoma, tubulovillous adenoma, villous adenoma, and adenoma with high-grade dysplasia) or serrated polyps (including hyperplastic polyp, traditional serrated adenoma, and sessile serrated polyp). In a subset of participants who reported receiving a diagnosis of polyp on follow-up questionnaires, endoscopic and pathologic records were obtained to confirm the diagnosis. Odds ratios (ORs) and 95% CIs were calculated using logistic regression, after adjusting for age, sex, vitamin D treatment assignment, and use of endoscopy. Secondary analyses were performed according to polyp features and participants' characteristics. Results: The demographic characteristics of participants at randomization were well balanced between the treatment and placebo groups; for example, 50.6% vs 50.5% were women, and 19.7% vs 19.8% were African American persons were included in each group. The mean (SD) age was 67.1 (7.1) years in the placebo group and 67.2 (7.1) in the ω-3 treatment group. During a median follow-up of 5.3 years (range, 3.8-6.1 years), 294 cases of conventional adenomas were documented in the ω-3 group and 301 in the control group (multivariable OR, 0.98; 95% CI, 0.83-1.15) (1:1 ratio between number of cases and number of participants). In addition, 174 cases of serrated polyps were documented in the ω-3 group and 167 in the control group (OR, 1.05; 95% CI, 0.84-1.29). Null associations were found for polyp subgroups according to size, location, multiplicity, or histology. In secondary analyses, marine ω-3 treatment appeared to be associated with lower risk of conventional adenomas among individuals with low plasma levels of ω-3 index at baseline (OR, 0.76; 95% CI, 0.57-1.02; P =.03 for interaction by ω-3 index). A beneficial association of supplementation was also noted in the African American population (OR, 0.59; 95% CI, 0.35-1.00) but not in other racial/ethnic groups (P =.11 for interaction). Conclusions and Relevance: Supplementation with marine ω-3 fatty acids, 1 g per day, was not associated with reduced risk of colorectal cancer precursors. A potential benefit of this supplementation for individuals with low baseline ω-3 levels or for African American persons requires further confirmation. © 2019 American Medical Association. All rights reserved.

Age and race distribution in patients in phase III oncology clinical trials - Gopishetty, S.; Kota, V.; Guddati, A.K. (American Journal of Translational Research, 2020)
Background: Geriatric patients and minority patients are often under-represented in cancer clinical trials. The presence of multiple comorbidities makes geriatric patients ineligible for most clinical trials. Racial diversity may vary by geographical location and socio-economically backward areas may have a very different racial mix. The increase in cancer incidence in geriatric patients' raises the question of applicability of the results is such clinical trials. This study also explores the representation of different races in phase 3 clinical trials conducted in the past 10 years. Methods: Data about Phase III trials was extracted from the clinical trials.gov for 3 common solid organs and 3 hematological malignancies [breast, colon, lung, diffuse large B-cell lymphoma (DLBCL), acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL)]. The time period studied was for the past 10 years and included only adult patients (≥18 years). The age and race distribution of the patient population in these trials were extracted and analyzed. Results: Geriatric patients and minorities are under-represented in all phase III cancer clinical trials. The range of the proportion of geriatric patients varied from 10% to 40%. African American and Asian patients are under-represented in all phase III cancer clinical trials. Conclusions: The results of phase III clinical trials that are currently conducted on non-geriatric and Caucasian patient population may not meaningfully be applicable to geriatric patients and minorities. This study highlights the disparity of age and race for patients enrolled in clinical trials as against the patients seen in the real world. © 2020 E-Century Publishing Corporation. All rights reserved.
Keywords: Cancer clinical trial; Geriatric population; Minorities; Racial distribution

Pilot Feasibility Study of a Video Intervention to Educate Patients with Breast Cancer About Clinical Trials - Yeager, K.A.; Bai, J.; Gogineni, K.; Meisel, J.L.; Kweon, J.; Bruner, D.W.; Waldrop-Valverde, D. (Journal of Cancer Education, 2020)
The purpose of this project was to develop and test the feasibility and preliminary efficacy of a video about cancer clinical trials (CCTs) developed for breast cancer patients. We developed 2 brief 7-min videos that focused on breast cancer patients describing their experiences participating in CCTs, supplemented with doctors and research staff explaining key research concepts. One video was culturally tailored to Black patients and the other to White patients. To assess feasibility study, participants and their care providers completed a survey to evaluate their satisfaction with the video. Eligibility criteria for the study included ≥ 21 years of age, English-speaking, no prior experience participating in a CCT, and being potentially eligible for breast CCT enrollment. Preliminary efficacy was evaluated with a pretest-posttest design using a single item asking about intent to enroll in a clinical trial. The mean age of the patient sample (n = 50) was 53.0 years, and 50.0% were Black. Participants reported that the video was in the right length, useful, and easy to understand. Providers’ evaluation (n = 5) revealed that viewing the video helped prepare patients for further CCT discussion. Preliminary efficacy showed no statistically significant difference in participant interest in CCT enrollment pre- and post-video. Changes in patients’ intent in enrollment were associated with age and education. Culturally adapted video interventions can be helpful in supporting both patients and providers throughout the CCT education process but additional work is needed to improve enrollment into clinical trials. © 2020, American Association for Cancer Education.
Keywords: Breast cancer; Clinical trial; Education; Video intervention

A large-cohort retrospective study of metastatic patterns and prognostic outcomes between inflammatory and non-inflammatory breast cancer - Wang, Z.; Wang, H.; Ding, X.; Chen, X.; Shen, K. (Therapeutic Advances in Medical Oncology, 2020)
Background and aims: Breast cancer-related death is attributable mainly to metastasis. Inflammatory breast cancer (IBC) is an infrequent subtype of breast cancer that shows a relatively high rate of metastasis. In this study, we aimed to compare the metastatic patterns and prognostic outcomes of IBC and non-inflammatory breast cancer (non-IBC). Methods: We extracted data between 2010 and 2014 from the Surveillance, Epidemiology and End Results (SEER) database. The Chi-square test and Fisher’s exact test were used to compare the categorical parameters among different groups. Logistic regression was applied for multivariate analysis. The Kaplan–Meier method and multivariate Cox regression models were performed to analyze prognosis. Results: We enrolled 233,686 breast cancer patients between 2010 and 2014 in our research, including 2806 IBC and 230,880 non-IBC patients. Compared with the non-IBC group, the IBC group tended to have a higher incidence of the human epidermal growth factor receptor 2 positive (HER2+) and triple-negative breast cancer (TNBC) subtypes, older age, a higher rate of unmarried status, a lower incidence of black race, poorer tumor differentiation, larger tumor sizes, and a higher frequency of regional lymph node invasion. IBC and non-IBC shared similar trends in molecular subtypes among different metastatic organs. The percentage of the hormone receptor positive (HR+)/human epidermal growth factor receptor 2 negative (HER2–) subtype decreased gradually in patients with lung (IBC 42.5%, non-IBC 55.7%), distant lymph node (IBC 41.5%, non-IBC 54.6%), liver (IBC 31.1%, non-IBC 46.7%), and brain (IBC 30.6%, non-IBC 47.9%) metastases compared with that in patients with bone (IBC 50.8%, non-IBC 69.0%) metastasis in both cohorts. In both the IBC and non-IBC cases, the proportion of visceral metastases increased in the TNBC subtype, especially brain metastasis (IBC 26.4%, non-IBC 21.2%), which had the largest increase. The frequencies of all sites (bone, lung, liver, brain, and distant lymph node) in IBC were much higher than those in non-IBC (bone: IBC 21.1%, non-IBC 3.0%; lung: IBC 11.4%, non-IBC 1.4%; liver: IBC 9.6%, non-IBC 1.2%; brain: IBC 2.6%, non-IBC 0.3%; distant lymph node: IBC 12.9%, non-IBC 1.0%). The most frequent bi-site metastasis was the bone and liver (IBC 2.5%, non-IBC 0.3%), and the most frequent tri-site combination was the bone, lung, and liver (IBC 1.1%, non-IBC 0.2%). Kaplan–Meier curves and multivariate Cox regression models suggested that the IBC cohort had poorer overall survival [hazard ratio (HR) 1.602, 95% confidence interval (CI) 1.496–1.716, p < 0.001] and breast cancer-specific survival (HR 1.511, 95% CI 1.402–1.628, p < 0.001) than the non-IBC cohort. Furthermore, univariate and multivariate analyses indicated that IBC was an independent prognostic factor in patients with different metastatic sites. Conclusion: IBC and non-IBC patients presented with different metastatic frequencies, clinical features and prognostic outcomes. Our findings provide more information for therapeutic decision making and clinical study designs. © The Author(s), 2020.
Keywords: advanced breast cancer; metastasis; molecular subtype; prognosis; SEER

Association of diet quality and physical activity on obesity-related cancer risk and mortality in black women: Results from the Women's Health Initiative - Chebet, J.J.; Thomson, C.A.; Kohler, L.N.; Ehiri, J.E.; Luo, J.; Cheng, T.-Y.D.; Pan, K.; Chlebowski, R.T.; Nassir, R.; Sealy-Jefferson, S.; Manson, J.E.; Saquib, N.; et al. (Cancer Epidemiology Biomarkers and Prevention, 2020)
Background: Obesity-related cancers disproportionately affect the Black community. We assessed the relationship between diet quality, physical activity, and their combined effect on obesity-related cancer risk and mortality in Black women enrolled in the Women's Health Initiative (WHI). Methods: Data from postmenopausal (50-79 years of age) Black women enrolled in WHI clinical trials or observational studies were analyzed. Exposure variables included baseline physical activity [metabolic equivalent of tasks (MET)-hours/ week of moderate-to-vigorous physical activity (MVPA)] and diet quality [Healthy Eating Index (HEI)-2015]. Outcomes included adjudicated obesity-related cancer incidence and mortality. Cox proportional hazard models were used to evaluate the association between MVPA and HEI-2015 and obesity-related cancer risk and mortality. Results: The analytical sample included 9,886 Black women, with a baseline mean body mass index (BMI) of 31.1 kg/m2 (SD ¼ 6.8); mean HEI-2015 score of 63.2 (SD ¼ 11.0, possible range 0 to 100); and mean MVPA of 5.0 (SD ¼ 9.4) MET-hours/week. Over an average of 13 years of follow-up, 950 (9.6%) obesity-related cancer cases were observed, with 313 (32.9%) resulting in death. Physical activity [HR, 1.05; 95% confidence interval (CI), 0.86-1.30], diet quality (HR, 0.99; 95% CI, 0.92-1.08), and their combination (HR, 1.05; 95% CI, 0.85-1.29) were not associated with risk for any or site-specific obesity-related cancers. Similarly, these health behaviors had no association with mortality. Conclusions: Diet quality, physical activity and their combined effect, as measured, were not associated with obesity-related cancer risk and mortality in Black women enrolled in WHI. Impact: Other social, behavioral, and biological factors may contribute to racial disparities observed in obesity-related cancer rates. © 2020 American Association for Cancer Research.

Prediagnostic allostatic load as a predictor of poorly differentiated and larger sized breast cancers among black women in the Women's Circle of health follow-up study - Xing, C.Y.; Doose, M.; Qin, B.; Lin, Y.; Plascak, J.J.; Omene, C.; He, C.; Demissie, K.; Hong, C.-C.; Bandera, E.V.; Llanos, A.A.M. (Cancer Epidemiology Biomarkers and Prevention, 2020)
Background: Few studies have empirically tested the association of allostatic load (AL) with breast cancer clinicopathology. The aim of this study was to examine the association of AL, measured using relevant biomarkers recorded in medical records before breast cancer diagnosis, with unfavorable tumor clinicopathologic features among Black women. Methods: In a sample of 409 Black women with nonmetastatic breast cancer who are enrolled in the Women's Circle of Health Follow-Up Study, we estimated prediagnostic AL using two measures: AL measure 1 [lipid profile–based—assessed by systolic and diastolic blood pressure (SBP, DBP), high-density lipoprotein, low-density lipoprotein, total cholesterol, triglycerides, and glucose levels; waist circumference; and use of diabetes, hypertension, or hypercholesterolemia medication] and AL measure 2 (inflammatory index–based—assessed by SBP, DBP, glucose, and albumin levels; estimated glomerular filtration rate; body mass index; waist circumference; and use of medications previously described). We used Cohen's statistic to assess agreement between the two AL measures and multivariable logistic models to assess the associations of interest. Results: AL measures 1 and 2 moderately agreed (k = 0.504). Higher prediagnostic AL predicted higher grade (poorly differentiated vs. well/moderately differentiated) using AL measure 1 [OR = 2.16; 95% confidence interval (CI), 1.18–3.94] and AL measure 2 (OR = 1.60; 95% CI, 1.02–2.51), and larger tumor size (≥2 cm vs. <2 cm; OR = 1.58; 95% CI, 1.01–2.46) using AL measure 2 only. Conclusions: Elevated prediagnostic AL might contribute to more unfavorable breast cancer clinicopathology. Impact: Addressing elevated prediagnostic levels of AL has potentially important clinical implications. ©2019 American Association for Cancer Research.

THRIVE study protocol: A randomized controlled trial evaluating a web-based app and tailored messages to improve adherence to adjuvant endocrine therapy among women with breast cancer - Paladino, A.J.; Anderson, J.N.; Krukowski, R.A.; Waters, T.; Kocak, M.; Graff, C.; Blue, R.; Jones, T.N.; Buzaglo, J.; Vidal, G.; Schwartzberg, L.; Graetz, I. (BMC Health Services Research, 2019)
Background: Long-term use of adjuvant endocrine therapy (AET) among women with early-stage, hormone receptor-positive breast cancer significantly reduces the risk of hospitalizations, cancer recurrence, and mortality. AET is associated with adverse symptoms that often result in poor adherence. A web-enabled app offers a novel way to communicate and manage symptoms for women on AET. In a region with significant racial disparities in breast cancer outcomes, our study tests the impact of a web-enabled app that collects and transmits patient-reported symptoms to healthcare teams to facilitate timely and responsive symptom management on medication adherence. Methods: In this randomized controlled trial, we randomize 300 patients initiating AET to one of three arms: 1) an "App" group (n = 100) that receives weekly reminders to use the THRIVE study app; 2) an "App+Feedback" group (n = 100) that receives weekly reminders and tailored feedback based on their use of the app; or 3) a "Usual Care" group (n = 100) that receives usual care only. Participants are stratified by race: 50% White and 50% Black. The duration of the intervention is six months following enrollment, and outcomes are assessed at 12-months. The primary outcome is adherence, which is captured using an electronic monitoring pillbox. Secondary outcomes include symptom burden, quality of life, self-efficacy for managing symptoms, and healthcare costs. We also evaluate the impact of the intervention on racial disparities in adherence. Data are derived from three sources: electronic health record data to capture treatment changes, healthcare utilization, and health outcomes; self-report survey data related to adherence, symptom burden, and quality of life; and an electronic medication monitoring device that captures adherence. Discussion: A successful web-enabled intervention could be disseminated across systems, conditions, and populations. By evaluating the impact of this intervention on a comprehensive set of measures, including AET adherence, patient outcomes, and costs, our study will provide valuable and actionable results for providers, policy makers, and insurers who strive to achieve the "Triple Aim" - reduce costs while improving health outcomes and the patient care experience. Trial registration: NCT03592771. Prospectively registered on July 19, 2018. © 2019 The Author(s).
Keywords: Adjuvant endocrine therapy; Breast cancer; Medication adherence; Mhealth; Patient-reported outcomes; Quality of life; Randomized controlled trial

Recurrent PTPRT/JAK2 mutations in lung adenocarcinoma among African Americans - Mitchell, K.A.; Nichols, N.; Tang, W.; Walling, J.; Stevenson, H.; Pineda, M.; Stefanescu, R.; Edelman, D.C.; Girvin, A.T.; Zingone, A.; Sinha, S.; Bowman, E.; et al. (Nature Communications, 2019)
Reducing or eliminating persistent disparities in lung cancer incidence and survival has been challenging because our current understanding of lung cancer biology is derived primarily from populations of European descent. Here we show results from a targeted sequencing panel using NCI-MD Case Control Study patient samples and reveal a significantly higher prevalence of PTPRT and JAK2 mutations in lung adenocarcinomas among African Americans compared with European Americans. This increase in mutation frequency was validated with independent WES data from the NCI-MD Case Control Study and TCGA. We find that patients carrying these mutations have a concomitant increase in IL-6/STAT3 signaling and miR-21 expression. Together, these findings suggest the identification of these potentially actionable mutations could have clinical significance for targeted therapy and the enrollment of minority populations in clinical trials. © 2019, This is a U.S. government work and not under copyright protection in the U.S.; foreign copyright protection may apply.

Real-world outcomes of sipuleucel-T treatment in PROCEED, a prospective registry of men with metastatic castration-resistant prostate cancer - Higano, C.S.; Armstrong, A.J.; Sartor, A.O.; Vogelzang, N.J.; Kantoff, P.W.; McLeod, D.G.; Pieczonka, C.M.; Penson, D.F.; Shore, N.D.; Vacirca, J.; Concepcion, R.S.; Tutrone, R.F.; et al. (Cancer, 2019)
Background: The large registry, PROVENGE Registry for the Observation, Collection, and Evaluation of Experience Data (PROCEED)(NCT01306890), evaluated sipuleucel-T immunotherapy for asymptomatic/minimally symptomatic metastatic castration-resistant prostate cancer (mCRPC). Methods: PROCEED enrolled patients with mCRPC receiving 3 biweekly sipuleucel-T infusions. Assessments included overall survival (OS), serious adverse events (SAEs), cerebrovascular events (CVEs), and anticancer interventions (ACIs). Follow-up was for ≥3 years or until death or study withdrawal. Results: In 2011-2017, 1976 patients were followed for 46.6 months (median). The median age was 72 years, and the baseline median prostate-specific antigen level was 15.0 ng/mL; 86.7% were white, and 11.6% were African American. Among the patients, 1902 had 1 or more sipuleucel-T infusions. The median OS was 30.7 months (95% confidence interval [CI], 28.6-32.2 months). Known prognostic factors were independently associated with OS in a multivariable analysis. Among the 1255 patients who died, 964 (76.8%) died of prostate cancer (PC) progression. The median time from the first infusion to PC death was 42.7 months (95% CI, 39.4-46.2 months). The incidence of sipuleucel-T–related SAEs was 3.9%. The incidence of CVEs was 2.8%, and the rate per 100 person-years was 1.2 (95% CI, 0.9-1.6). The CVE incidence among 11,972 patients with mCRPC from the Surveillance, Epidemiology, and End Results–Medicare database was 2.8%; the rate per 100 person-years was 1.5 (95% CI, 1.4-1.7). One or more ACIs (abiraterone, enzalutamide, docetaxel, cabazitaxel, or radium 223) were received by 77.1% of the patients after sipuleucel-T; 32.5% and 17.4% of the patients experienced 1- and 2-year treatment-free intervals, respectively. Conclusions: PROCEED provides contemporary survival data for sipuleucel-T–treated men in a real-world setting of new life-prolonging agents, which will be useful in discussing treatment options with patients and in powering future trials with sipuleucel-T. The safety and tolerability of sipuleucel-T in PROCEED were consistent with previous findings. © 2019 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society.
Keywords: immunotherapy; overall survival; prostate cancer; safety

A comparative effectiveness analysis of the PBCG vs. PCPT risks calculators in a multi-ethnic cohort - Carbunaru, S.; Nettey, O.S.; Gogana, P.; Helenowski, I.B.; Jovanovic, B.; Ruden, M.; Hollowell, C.M.P.; Sharifi, R.; Kittles, R.A.; Schaeffer, E.; Gann, P.; Murphy, A.B. (BMC Urology, 2019)
Background: Predictive models that take race into account like the Prostate Cancer Prevention Trial Risk Calculator 2.0 (PCPT RC) and the new Prostate Biopsy Collaborative Group (PBCG) RC have been developed to equitably mitigate the overdiagnosis of prostate specific antigen (PSA) screening. Few studies have compared the performance of both calculators across racial groups. Methods: From 1485 prospectively recruited participants, 954 men were identified undergoing initial prostate biopsy for abnormal PSA or digital rectal examination in five Chicago hospitals between 2009 and 2014. Discrimination, calibration, and frequency of avoided biopsies were calculated to assess the performance of both risk calculators. Results: Of 954 participants, 463 (48.5%) were Black, 355 (37.2%) were White, and 136 (14.2%) identified as Other. Biopsy results were as follows: 310 (32.5%) exhibited no cancer, 323 (33.9%) indolent prostate cancer, and 321 (33.6%) clinically significant prostate cancer (csPCa). Differences in area under the curve (AUC)s for the detection of csPCa between PCPT and PBCG were not statistically different across all racial groups. PBCG did not improve calibration plots in Blacks and Others, as it showed higher levels of overprediction at most risk thresholds. PCPT led to an increased number of avoidable biopsies in minorities compared to PBCG at the 30% threshold (68% vs. 28% of all patients) with roughly similar rates of missed csPCa (23% vs. 20%). Conclusion: Significant improvements were noticed in PBCG's calibrations and net benefits in Whites compared to PCPT. Since PBCG's improvements in Blacks are disputable and potentially biases a greater number of low risk Black and Other men towards unnecessary biopsies, PCPT may lead to better biopsy decisions in racial minority groups. Further comparisons of commonly used risk calculators across racial groups is warranted to minimize excessive biopsies and overdiagnosis in ethnic minorities. © 2019 The Author(s).
Keywords: African American validation; Prostate biopsy collaborative group risk calculator; Prostate Cancer prevention trial risk calculator 2.0; Prostate cancer risk prediction; Risk calculator

Challenges and opportunities using online portals to recruit diverse patients to behavioral trials - Tabriz, A.A.; Fleming, P.J.; Shin, Y.; Resnicow, K.; Jones, R.M.; Flocke, S.A.; Shires, D.A.; Hawley, S.T.; Willens, D.; Lafata, J.E. (Journal of the American Medical Informatics Association, 2019)
We describe the use of an online patient portal to recruit and enroll primary care patients in a randomized trial testing the effectiveness of a colorectal cancer (CRC) screening decision support program. We use multiple logistic regression to identify patient characteristics associated with trial recruitment, enrollment, and engagement. We found that compared to Whites, Blacks had lower odds of viewing the portal message (OR = 0.46, 95% CI = 0.37-0.57), opening the attached link containing the study material (OR = 0.75, 95% CI = 0.62-0.92), and consenting to participate in the trial (OR = 0.85, 95% CI = 0.67-0.93). We also found that compared to Whites, Asians had lower odds of viewing the portal message (OR = 0.53, 95% CI = 0.33-0.64), opening the attached link containing the study material (OR = 0.76, 95% CI = 0.54-0.97), consenting to participate in the trial (OR = 0.68, 95% CI = 0.53-0.95), and completing the trial's baseline questionnaire (OR = 0.59, 95% CI = 0.36-0.90). While portals offer an opportunity to mitigate human bias in trial invitations, because of racial disparities - not only in who has a portal account, but in how they interact with trial recruitment and enrollment material within the portal - using portals alone for trial recruitment may generate study samples that are not racially diverse. © 2019 The Author(s) 2019. Published by Oxford University Press on behalf of the American Medical Informatics Association. All rights reserved. For permissions, please email: journals.permissions@oup.com.
Keywords: colorectal cancer screening; electronic health record; health disparities; patient portal; pragmatic clinical trial

Follow-up approaches to a health literacy intervention to increase colorectal cancer screening in rural community clinics: A randomized controlled trial - Arnold, C.L.; Rademaker, A.W.; Morris, J.D.; Ferguson, L.A.; Wiltz, G.; Davis, T.C. (Cancer, 2019)
Background: Significant disparities exist in colorectal cancer (CRC) screening rates among those of low socioeconomic status, with fewer years of education, lacking health insurance, or living in rural areas. Methods: A randomized controlled trial was conducted to compare the effectiveness of 2 follow-up approaches to a health literacy intervention to improve CRC screening: automated telephone call or personal call. Patients aged 50 to 75 years residing in 4 rural community clinics in Louisiana were given a structured interview that assessed demographic, health literacy and CRC screening barriers, knowledge, and attitudes. All were given health literacy–informed CRC education, a patient-friendly CRC screening pamphlet, simplified fecal immunochemical test (FIT) instructions, and a FIT kit, and a “teach-back” method was used to confirm understanding. Patients were randomized to 1 of 2 telephone follow-up arms. If they did not mail their FIT kit within 4 weeks, they received a reminder call and were called again at 8 weeks if the test still was not received. Results: A total of 620 patients were enrolled. Approximately 55% were female, 66% were African American, and 40% had limited literacy. The overall FIT completion rate was 68%: 69.2% in the automated telephone call arm and 67% in the personal call arm. Greater than one-half of the patients (range, 58%-60%) returned the FIT kit without receiving a telephone call. There was no difference noted with regard to the effectiveness of the follow-up calls; each increased the return rate by 9%. Conclusions: Providing FIT kits and literacy-appropriate education at regularly scheduled clinic visits with a follow-up telephone call when needed was found to increase CRC screening among low-income, rural patients. The lower cost automated call was just as effective as the personal call. © 2019 American Cancer Society
Keywords: colorectal cancer screening; disparities; health literacy; prevention; randomized controlled trial; rural community clinics

Black Light Smokers: How Nicotine Intake and Carcinogen Exposure Differ Across Various Biobehavioral Factors - St.Helen, G.; Benowitz, N.L.; Ahluwalia, J.S.; Tyndale, R.F.; Addo, N.; Gregorich, S.E.; Pérez-Stable, E.J.; Cox, L.S. (Journal of the National Medical Association, 2019)
Objective: The study objective was to identify biobehavioral variables associated with greater intake of nicotine and a tobacco carcinogen among Black light smokers who smoke 1 to 10 cigarettes per day (CPD). Methods: We analyzed baseline data collected from 426 Black light smokers enrolled in Kick It at Swope III (KIS III), a smoking cessation trial for Black smokers. We examined differences in concentrations of tobacco biomarkers, including urinary total nicotine equivalents (TNE) and total 4-(methylnitrosamino)-1-(3)pyridyl-1-butanonol (NNAL; a human carcinogen), across gender, age, plasma nicotine metabolite ratio (NMR), CPD, and measures of tobacco dependence, including time to first cigarette (TFC), using ANOVA. Results: Tobacco biomarker levels were significantly higher among those who smoked more CPD (6–10 vs 1–5 CPD) and those with greater reported physical dependence on tobacco. Concurrently, those who smoked 1–5 CPD smoked each cigarette more intensely than those who smoked 6–10 CPD. While we found no gender differences overall, among those who smoked 1–5 CPD, women had higher NNAL levels compared to men. The rate of nicotine metabolism, measured by the nicotine metabolite ratio, was not significantly related to TNE or NNAL levels. Conclusion: Among Black Light smokers, higher cigarette consumption and greater physical dependence—but not rate of nicotine metabolism, menthol use, or socioeconomic status—were associated with greater toxicant exposure and thus a likely increased risk of tobacco-related diseases. The lack of data on light smokers, and specifically on Blacks, make this observation important given the disproportionate burden of lung cancer in this population. © 2019 National Medical Association
Keywords: Black smokers; Carcinogen exposure; Correlates of exposure; Light smokers; Nicotine

Effect of Erlotinib Plus Bevacizumab vs Erlotinib Alone on Progression-Free Survival in Patients with Advanced EGFR-Mutant Non-Small Cell Lung Cancer: A Phase 2 Randomized Clinical Trial - Stinchcombe, T.E.; Jänne, P.A.; Wang, X.; Bertino, E.M.; Weiss, J.; Bazhenova, L.; Gu, L.; Lau, C.; Paweletz, C.; Jaslowski, A.; Gerstner, G.J.; Baggstrom, M.Q.; et al. (JAMA Oncology, 2019)
Importance: Erlotinib is a standard first-line therapy for patients with epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancer (NSCLC). Median progression-free survival (PFS) with erlotinib is approximately 10 months. Objective: To determine whether adding bevacizumab to erlotinib treatment results in superior progression-free survival compared with erlotinib alone. Design, Setting, and Participants: This phase 2 randomized clinical trial compared erlotinib plus bevacizumab with erlotinib alone in EGFR-mutant NSCLC. The trial was conducted in 17 US academic and community medical centers among 88 patients with EGFR exon 19 deletion or exon 21 L858R mutation based on local testing and stage 4 NSCLC who were eligible for bevacizumab. Patients were enrolled between November 2, 2012, and August 22, 2016, and followed up for a median (range) of 33 (0.7-62.5) months. Data were analyzed on August 28, 2018, and included data from November 2, 2012, to August 20, 2018. Interventions: Patients were randomized with equal allocation to 150 mg of oral erlotinib daily alone or with 15 mg/kg of intravenous bevacizumab every 3 weeks. Study therapy continued until disease progression, unacceptable adverse event, or withdrawal of consent. Main Outcomes and Measures: The primary outcome was PFS as assessed by the investigator; secondary outcomes were objective response rate (ORR), adverse events, and overall survival (OS). Analysis was designed to detect a hazard ratio (HR) of 0.667 for PFS (an improvement from a median PFS of 10 to 15 months). Results: Among 88 patients enrolled, the median (range) age was 63 (31-84) years; 62 patients (70%) were female; 75 (85%) were white, 8 (9%) were African American, 3 (3%) were Asian, and for 2 (2%), data on race were not available. Forty-eight patients (55%) were never smokers, 45 patients (51%) were of Eastern Cooperative Oncology Group performance status 1, and 59 patients (67%) had EGFR exon 19 deletion. Compared with erlotinib, the combination did not result in a significant difference in PFS (HR, 0.81; 95% CI, 0.50-1.31; P =.39; median PFS 17.9 [combination] and 13.5 months [erlotinib]), ORR (81% vs 83%; P =.81), and OS (HR, 1.41; 95% CI, 0.71-2.81; P =.33; median OS, 32.4 months [combination] and 50.6 months [erlotinib]). Adverse events of grade 3 or higher observed in 5 or more patients in the combination and erlotinib arms were skin eruption in 11 (26%) vs 7 (16%) patients, diarrhea in 4 (9%) vs 6 (13%) patients, hypertension in 17 (40%) vs 9 (20%) patients, and proteinuria in 5 (12%) vs 0 (0%) patients. Conclusions and Relevance: Erlotinib plus bevacizumab compared with erlotinib did not result in a significant improvement in PFS in EGFR-mutant NSCLC. © 2019 American Medical Association. All rights reserved.

Cognitive and Affective Responses to Mass-media Based Genetic Risk Information in a Socio-demographically Diverse Sample of Smokers - Waters, E.A.; Ackerman, N.; Wheeler, C.S. (Journal of Health Communication, 2019)
Many individuals receive information about genomics from the mass media. When media reports are about conditions that are considered behavioral, such as smoking, they may negatively affect some health-promoting cognitions. We examined how informing adult smokers about the genetic basis for nicotine addiction influenced smoking-related health cognitions and affect and whether responses varied by socio-demographics or genetics beliefs. We recruited 392 smokers (Mage = 44.5, 52.8% African American, 51.3% no college experience, 66.2% women) from public locations in a mid-sized Midwestern city. They were randomly assigned to read a news article describing either a pharmacy’s decision to stop selling tobacco (n = 78) or the discovery of a gene associated with increased risk of nicotine addiction and lung cancer (n = 314). Participants also completed a survey assessing socio-demographics, health cognitions (quit intentions, self-efficacy, response efficacy, perceived risk), affect (worry, anticipated regret), genetic determinism, and other genetics beliefs. ANOVAs revealed no statistically significant main effects of genetic information on any health cognitions or affects. Linear regressions revealed that socio-demographics and genetics beliefs moderated very few effects. This suggests that concerns that mass media-based dissemination of genetic discoveries may have detrimental effects on smoking-related cognitions and affects are likely unwarranted. ©, Copyright © Taylor & Francis Group, LLC.

Bridging the Gap: Racial concordance as a strategy to increase African American participation in breast cancer research - Frierson, G.M.; Pinto, B.M.; Denman, D.C.; Leon, P.A.; Jaffe, A.D. (Journal of Health Psychology, 2019)
Lack of African American females in breast cancer research has been receiving substantial attention. This study seeks to identify research perceptions and motivating factors needed to increase racial/ethnic minority participation in breast cancer research. A total of 57 African American women (Σ = 47.8 years), from Rhode Island and Texas, completed a questionnaire and focus group. While many participants were not breast cancer survivors, they reported knowledge of their racial group’s risk for breast cancer. One major finding that could be seen as both a facilitator and barrier is racial concordance between participant and researcher. Cultural sensitivity and trust building is recommended to increase minority participation. © The Author(s) 2017.
Keywords: breast cancer; minority; psycho-oncology; racial concordance; recruitment strategies

Variation in Accrual and Race/Ethnicity Reporting in Urological and Nonurological Related Cancer Trials - Paul, K.; Sathianathen, N.; Dahm, P.; Le, C.; Konety, B.R. (Journal of Urology, 2019)
We performed a multiregistry analysis to assess relative differences in accrual sufficiency and race/ethnicity reporting in trials of common urological cancers and other nonurological solid organ tumors.Materials and Methods:We queried ClinicalTrials.gov and the ISRCTN (International Standard Randomised Controlled Trial Number) Registry for closed phase III and IV trials focused on prostate, colorectal, kidney, bladder, testicular, breast and lung cancer. Identified trials were cross-verified with appropriate published data sources. Comparative accrual sufficiency and rates of race/ethnicity reporting were calculated. Multivariable logistic regression analysis was performed to determine factors associated with accrual status and race/ethnicity reporting.Results:A total of 326 trials were identified based on our prespecified criteria, of which 63% reported sufficient accrual by time of closure and 58% reported data by race/ethnicity. Nonurological trials were significantly more likely to mention race data than urological trials (OR 3.25, 95% CI 1.24-8.55, p = 0.02). Industry sponsored trials were more likely to meet accrual targets than government funded projects (OR 5.44, 95% CI 1.64-18.20, p = 0.001). Although funding source did not influence race reporting, the reported recruitment of participants of African ethnicity was lower in industry sponsored trials (11.49% vs 3.18%, p <0.01). Two-thirds of the studies did not report baseline characteristics by African American race/ethnicity.Conclusions:Insufficient accrual and inadequate race/ethnicity reporting are prevalent issues, limiting interpretation of the results of clinical trials of major solid organ malignancies. Addressing these shortcomings would enhance result validity by raising statistical power and improving the transparency of reporting to better evaluate the generalizability of results. reproduction of this article is prohibited. © 2019 American Urological Association Education and Research, Inc. Unauthorized.
Keywords: African Americans; clinical trial protocols as topic; registries; research design; urogenital neoplasms

Web-based versus in-person methods for training lay community health advisors to implement health promotion workshops: Participant outcomes from a cluster-randomized trial - Holt, C.L.; Tagai, E.K.; Santos, S.L.Z.; Scheirer, M.A.; Bowie, J.; Haider, M.; Slade, J. (Translational Behavioral Medicine, 2019)
Project HEAL (Health through Early Awareness and Learning) is an implementation trial that compared two methods of training lay peer community health advisors (CHAs) - in-person ("Traditional") versus web-based ("Technology") - to conduct a series of three evidence-based cancer educational workshops in African American churches. This analysis reports on participant outcomes from Project HEAL. Fifteen churches were randomized to the two CHA training methods and the intervention impact was examined over 24 months. This study was conducted in Prince George's County, MD, and enrolled 375 church members age 40-75. Participants reported on knowledge and screening behaviors for breast, prostate, and colorectal cancer. Overall, cancer knowledge in all areas increased during the study period (p <. 001). There were significant increases in digital rectal exam (p <. 05), fecal occult blood test (p <. 001), and colonoscopy (p <. 01) at 24 months; however, this did not differ by study group. Mammography maintenance (56% overall) was evidenced by women reporting multiple mammograms within the study period. Participants attending all three workshops were more likely to report a fecal occult blood test or colonoscopy at 24 months (p <. 05) than those who attended only one. These findings suggest that lay individuals can receive web-based training to successfully implement an evidence-based health promotion intervention that results in participant-level outcomes comparable with (a) people trained using the traditional classroom method and (b) previous efficacy trials. Findings have implications for resources and use of technology to increase widespread dissemination of evidence-based health promotion interventions through training lay persons in community settings. © 2018 Society of Behavioral Medicine 2018. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.
Keywords: African Americans; Cancer early detection; Community health advisors; Implementation; Web-based learning

Brief report of a tablet-delivered psychosocial intervention for men with advanced prostate cancer: Acceptability and efficacy by race - Bouchard, L.C.; Yanez, B.; Dahn, J.R.; Flury, S.C.; Perry, K.T.; Mohr, D.C.; Penedo, F.J. (Translational Behavioral Medicine, 2019)
Relative to non-Hispanic whites (NHW), black men are disproportionately affected by prostate cancer (PC) incidence, have poorer PC outcomes, and report greater compromises in health-related quality of life. Despite these challenges, black men are underrepresented in psychosocial cancer research, possibly due to limited access to supportive oncology programs. The purpose of this article is to examine the acceptability and efficacy for reducing disease-specific distress of a tablet-delivered psychosocial intervention for older men with advanced PC (APC) and explore differences by race. Men with APC (N = 192, 37.5% black, age M = 68.84 years) were randomized to 10-week Cognitive Behavioral Stress Management (CBSM) or attention-control Health Promotion (HP), both delivered via tablets. Assessments occurred at baseline in person, weekly during the 10-week program via tablets, and at 6 and 12 months in person. Weekly session evaluations and postprogram exit surveys assessed acceptability. Efficacy was assessed with a measure of PC-anxiety validated with racially diverse PC patients using linear mixed effects modeling. Study retention and group attendance did not differ by race. CBSM and HP were both acceptable among older APC patients. Black men rated both conditions more favorably than NHW men. Men in CBSM (vs. HP) reported greater reductions in PC-anxiety at 6 months (not sustained at 12 months). Black men in CBSM reported greater decreases in PC-anxiety over time compared with all other groups. Tablet-delivered CBSM and HP were acceptable for black and NHW APC patients, although black men rated both conditions more favorably. Black men reported a unique intervention benefit related to reduced disease-specific distress. © 2018 Society of Behavioral Medicine 2018. All rights reserved.
Keywords: Black men; Disparities; E-health; Prostate cancer; Psychosocial intervention

Study protocol for developing #CuttingCRC: A barbershop-based trial on masculinity barriers to care and colorectal cancer screening uptake among African-American men using an exploratory sequential mixed-methods design - Rogers, C.R.; Okuyemi, K.; Paskett, E.D.; Thorpe, R.J.; Rogers, T.N.; Hung, M.; Zickmund, S.; Riley, C.; Fetters, M.D. (BMJ Open, 2019)
Introduction Colorectal cancer (CRC) is preventable, as screening leads to the identification and removal of precancerous polyps. African-American men consistently have the highest CRC mortality rates, and their CRC-screening uptake remains low for complex reasons. Culture-specific masculinity barriers to care may contribute to the low uptake among African-American men. Examining these barriers to care is vital as CRC screening may challenge cultural role expectations of African-American men, whose tendency is to delay help-seeking medical care. Barbershops provide a pathway for reaching African-American men with masculinity barriers to care who are not regularly receiving healthcare services and CRC screening. This study aims to develop and pilot test a theory-driven, culture-specific, barbershop-based intervention targeting masculinity barriers to care and CRC-screening uptake among African-American men ages 45-75. Methods and analysis Guided by the theory of planned behaviour and the behaviour change wheel, we will use a multistage mixed-methods study design, beginning with an exploratory sequential approach to validate items for subsequent use in a pilot mixed-methods intervention. First, we will collect and analyse qualitative data from focus groups, cognitive interviews and expert item review to validate and test a culture-specific Masculinity Barriers to Care Scale (MBCS) among African-American men. Next, we will administer the MBCS to our target population as an online quantitative survey and evaluate the association between scores and CRC-screening uptake. Then, we will consider existing evidence-based approaches, our integrated results (qualitative +quantitative), and community input to design a culture-specific, behavioural intervention aimed at increasing CRC-screening uptake among African-American men and feasible for barbershop delivery. We will test the peer intervention in a pilot study with a two-Arm cluster randomised design (six barbershops, randomised by site) to reduce contamination and account for barbershop culture differences. Our primary outcomes for the pilot are recruitment, sample size estimation, preliminary efficacy and acceptability. Ethics and dissemination Ethics approval was obtained from the University of Utah Institutional Review Board (00113679), who will also be responsible for receiving communication updates regarding important protocol modifications. To ensure confidentiality, data dispersed to project team members will be blinded of any identifying participant information. Study results will be disseminated through publications in peer-reviewed journals, community dialogue sessions, and presentations at conferences. Trial registration number ClinicalTrials.gov identifier: NCT03733197 (Pre-results);https://clinicaltrials.gov/ct2/show/NCT03733197 © Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.
Keywords: african-Americans; colonic neoplasms; community-based participatory research; men's health; minority health

Increasing the Representation of Minority Students in the Biomedical Workforce: the ReTOOL Program - Odedina, F.T.; Reams, R.R.; Kaninjing, E.; Nguyen, J.; Mochona, B.; Lyon, D.E.; Askins, N.; Behar-Horenstein, L.S. (Journal of Cancer Education, 2019)
With the growing burden of cancer in minority populations and limited progress in eliminating cancer disparities, it has become important to develop a diverse oncology workforce in basic, clinical, and behavioral research who will address cancer disparities and increase the participation of minority populations in clinical trials. To address the lack of well-trained underrepresented minority cancer scientists in Florida, the University of Florida collaborated with Florida A&M University in 2012 to establish the Florida Prostate Cancer Research Training Opportunities for Outstanding Leaders (ReTOOL) Program. Since 2012, the ReTOOL program has expanded to (1) cover all areas of cancer disparities; (2) offer training opportunities to minority students from all historically Black colleges and universities (HBCUs) in Florida; and (3) successfully secure both intramural and extramural federal funding to continuously provide research training opportunities for minority students in Florida. Focusing primarily on training Black students, the ReTOOL model includes culturally sensitive recruitment, mentorship, didactic curriculum, networking, and hands on experience in cancer research. This paper discusses the lessons learned from administering the ReTOOL program for 5 years, which includes having the right inputs (such as majority-minority institutions partnership, funding, faculty advisors, committed mentors, culturally competent staff, and standardized program requirements) and processes (such as pipeline approach, structured applications system, didactic curriculum, research experience, and continuous mentoring) for an effective research training program. The program impact is an increase in the pool of underrepresented minority candidates with scientific and academic career progression paths focused on reducing cancer health disparities. © 2018, American Association for Cancer Education.
Keywords: Biomedical research workforce; Cancer research training; Minority undergraduate research; ReTOOL program; Summer research training program; Underrepresented minorities

Clinical Validation of IsoPSA™, a Single Parameter, Structure Based Assay for Improved Detection of High Grade Prostate Cancer - Stovsky, M.; Klein, E.A.; Chait, A.; Manickam, K.; Stephenson, A.J.; Wagner, M.; Dineen, M.; Lotan, Y.; Partin, A.; Baniel, J.; Kestranek, A.; Gawande, P.; et al. (Journal of Urology, 2019)
Purpose: Current prostate specific antigen markers to detect prostate cancer are limited by low specificity for high grade disease. IsoPSA™ is a blood based, structure focused assay which predicts risk by partitioning the isoforms of prostate specific antigen that are linked to cancer in an aqueous 2-phase reagent system. We validated the clinical performance of this assay for identifying high grade disease in a new contemporary biopsy cohort. Materials and Methods: We performed a multicenter prospective validation in 271 men scheduled for prostate biopsy at a total of 7 academic and community centers who were enrolled between May 2017 and March 2018. Blood samples were obtained for assay prior to biopsy. The discrimination power of the assay to detect high grade prostate cancer (Gleason 7 or greater) was evaluated by ROC analysis and compared to prior results. Clinical performance was further improved by comparison with multiparametric magnetic resonance imaging-ultrasound vs transrectal ultrasound guided biopsies. Results: The assay AUC was 0.784 for high grade vs low grade cancer/benign histology, which was superior to the AUCs of total prostate specific antigen and percent free prostate specific antigen. If 1,000 patients were biopsied, the assay would have reduced the number of unnecessary biopsies from 705 to 402 (43%) with only 22 missed high grade cancers, of which 7 would have been Gleason sum 4 + 3 or higher. Subset analysis of multiparametric magnetic resonance imaging guided biopsy produced a substantial improvement of the AUC to 0.831. Conclusions: Validation of the structure based IsoPSA assay demonstrated statistical concordance with previously reported results and verified its superior performance vs concentration based prostate specific antigen and the free-to-total prostate specific antigen ratio. The assay improvement in detecting high grade prostate cancer using multiparametric magnetic resonance imaging-ultrasound guided biopsy may help define a new diagnostic paradigm. © 2019 by American Urological Association Education and Research, Inc.
Keywords: biomarkers; neoplasm grading; prostate specific antigen; prostatic neoplasms; protein isoforms; tumor

Reliability and between-group stability of a health-related quality of life symptom index for persons with anal high-grade squamous intraepithelial lesions: an AIDS Malignancy Consortium Study (AMC-A03) - Atkinson, T.M.; Palefsky, J.; Li, Y.; Webb, A.; Berry, J.M.; Goldstone, S.; Levine, R.; Wilkin, T.J.; Bucher, G.; Cella, D.; Burkhalter, J.E.; Holland, S.M.; et al. (Quality of Life Research, 2019)
Purpose: The Anal Cancer HSIL Outcomes Research (ANCHOR) trial aims to determine whether treating precancerous anal high-grade squamous intraepithelial lesions (HSIL), versus active surveillance, is effective in reducing anal cancer incidence in HIV-infected individuals. We evaluated the reliability (i.e., internal consistency, test–retest) and between-group stability of a 25-item ANCHOR Health-Related Symptom Index (A-HRSI). Methods: ANCHOR participants at least 1-month post-randomization to treatment or active surveillance completed the A-HRSI via telephone. Participants were contacted 7–10 days later to complete the A-HRSI and a participant global impression of change (PGIC) item. Results: Participants (n = 100) were enrolled (mean age = 51.4, 79% cisgender-male, 73% African American, 9% Hispanic) from five ANCHOR sites. Cronbach’s α was good for the physical symptoms (0.82) domain and fair for the physical impacts (0.79) and psychological symptoms (0.73) domains. Intraclass correlation coefficients were good for each of respective domains (i.e., 0.80, 0.85, and 0.82). There were no significant differences in PGIC between the treatment (n = 56) and active surveillance (n = 44) groups (F(1,98) = 2.03, p = 0.16). Conclusions: The A-HRSI is able to reliably assess participant-reported symptoms and impacts of anal HSIL across a 7–10 days of timeframe. Future work will involve the establishment of construct and discriminant validity prior to inclusion in the full ANCHOR trial. © 2019, Springer Nature Switzerland AG.
Keywords: ANCHOR trial; Clinical outcome assessments; Health-related quality of life; Neoplasms; Patient-reported outcomes

Blood and dietary magnesium levels are not linked with lower prostate cancer risk in black or white men - Fowke, J.H.; Koyama, T.; Dai, Q.; Zheng, S.L.; Xu, J.; Howard, L.E.; Freedland, S.J. (Cancer Letters, 2019)
Recent studies suggest a diet low in dietary magnesium intake or lower blood magnesium levels is linked with increased prostate cancer risk. This study investigates the race-specific link between blood magnesium and calcium levels, or dietary magnesium intake, and the diagnosis of low-grade and high-grade prostate cancer. The study included 637 prostate cancer cases and 715 biopsy-negative controls (50% black) recruited from Nashville, TN or Durham, NC. Blood was collected at the time of recruitment, and dietary intake was assessed by food frequency questionnaire. Percent genetic African ancestry was determined as a compliment to self-reported race. Blood magnesium levels and dietary magnesium intake were significantly lower in black compared to white men. However, magnesium levels or intake were not associated with risk of total prostate cancer or aggressive prostate cancer. Indeed, a higher calcium-to-magnesium diet intake was significantly protective for high-grade prostate cancer in black (OR = 0.66 (0.45, 0.96), p = 0.03) but not white (OR = 1.00 (0.79, 1.26), p = 0.99) men. In summary, there was a statistically significant difference in magnesium intake between black and white men, but the biological impact was unclear, and we did not confirm a lower prostate cancer risk associated with magnesium levels. © 2019 Elsevier B.V.
Keywords: Biomarker; Calcium; Diet; Genetic African ancestry; Race

Physical activity and colorectal cancer risk by sex, race/ethnicity, and subsite: The multiethnic cohort study - Park, S.-Y.; Wilkens, L.R.; Haiman, C.A.; Marchand, L.L. (Cancer Prevention Research, 2019)
Physical activity has been associated with a lower risk of colorectal cancer. However, data is lacking on whether the association is consistent between sexes and across different races/ethnicities and anatomic subsites of tumors. We analyzed data from the Multiethnic Cohort in Hawaii and California, consisting of mostly African Americans, Native Hawaiians, Japanese Americans, Latinos, and whites ages 45–75 years at recruitment. During a mean follow-up of 16.8 years, 4,430 invasive adenocarcinoma cases of the colorectum were identified among 172,502 eligible participants. Cox proportional hazards models were used to estimate the HR and 95% confidence interval (CI). The multivariate-adjusted HR (95% CI) for the highest versus lowest quintiles of physical activity (metabolic equivalent hours of moderate or vigorous activities per day) was 0.76 (0.66–0.87) in men (Ptrend < 0.001) and 0.94 (0.80–1.11) in women (Ptrend ¼ 0.53, Pheterogeneity by sex ¼ 0.07). Sleeping and sitting hours were not associated with colorectal cancer risk both in men and women. In men, the inverse association was statistically significant among African Americans and Japanese Americans, for right colon and rectal cancer, and in all body mass index groups, although heterogeneity tests were not significant across race/ethnicity or anatomic subsite of tumors. The findings confirm the inverse association between physical activity and colorectal cancer, which appears to be stronger in men, and suggest possible differences in the strength of the association by race/ethnicity and anatomic subsite of tumors. © 2019 American Association for Cancer Research.

Enrollment and biospecimen collection in a multiethnic family cohort: the Northern California site of the Breast Cancer Family Registry - John, E.M.; Sangaramoorthy, M.; Koo, J.; Whittemore, A.S.; West, D.W. (Cancer Causes and Control, 2019)
Purpose: Racial/ethnic minorities are often assumed to be less willing to participate in and provide biospecimens for biomedical research. We examined racial/ethnic differences in enrollment of women with breast cancer (probands) and their first-degree relatives in the Northern California site of the Breast Cancer Family Registry from 1996 to 2011. Methods: We evaluated participation in several study components, including biospecimen collection, for probands and relatives by race/ethnicity, cancer history, and other factors. Results: Of 4,780 eligible probands, 76% enrolled in the family registry by completing the family history and risk factor questionnaires and 68% also provided a blood or mouthwash sample. Enrollment was highest (81%) for non-Hispanic whites (NHWs) and intermediate (73–76%) for Hispanics, African Americans, and all Asian American subgroups, except Filipina women (66%). Of 4,279 eligible relatives, 77% enrolled in the family registry, and 65% also provided a biospecimen sample. Enrollment was highest for NHWs (87%) and lowest for Chinese (68%) and Filipinas (67%). Among those enrolled, biospecimen collection rates were similar for NHW, Hispanic, and African American women, both for probands (92–95%) and relatives (82–87%), but lower for some Asian–American subgroups (probands: 72–88%; relatives: 71–88%), foreign-born Asian Americans, and probands those who were more recent immigrants or had low English language proficiency. Conclusions: These results show that racial/ethnic minority populations are willing to provide biospecimen samples for research, although some Asian American subgroups in particular may need more directed recruitment methods. To address long-standing and well-documented cancer health disparities, minority populations need equal opportunities to contribute to biomedical research. © 2019, Springer Nature Switzerland AG.
Keywords: African Americans; Asian Americans; Biospecimen collection; Breast cancer; Epidemiology; Hispanics; Race/ethnicity; Study participation

Adherence to American Cancer Society and American Institute of Cancer Research dietary guidelines in overweight African American breast cancer survivors - Springfield, S.; Odoms-Young, A.; Tussing-Humphreys, L.; Freels, S.; Stolley, M. (Journal of Cancer Survivorship, 2019)
Purpose: The American Cancer Society (ACS) and the American Institute for Cancer Research (AICR) each created dietary and physical activity guidelines to improve cancer survivorship. Despite African American breast cancer survivors (AABCS) having the lowest survival rates of any racial or ethnic group, limited information exists on their adherence to cancer-specific lifestyle recommendations. The study’s purpose was to measure adherence to ACS/AICR dietary recommendations in AABCS. Methods: Two hundred ten AABCS enrolled in the Moving Forward intervention trial, a randomized, community-based, 6-month weight loss study, were assessed for socio-demographics, dietary intake (via food frequency questionnaire), and related health factors at baseline. We operationalized the dietary recommendations put forth by ACS/AICR and created component and total adherence index scores. Descriptive statistics were used to calculate the proportion of women who met recommendations. Student’s t test and χ2 tests were used to compare participant characteristics by median adherence scores. Results: The mean total ACS/AICR score was 12.7 ± 2.5 out of 21 points (median, 13; range, 5 to 21). Over 90% were moderately or completely adherent to limiting alcohol and red & processed meat consumption, but the majority failed to meet the other recommendations to eat whole grains, legumes, fruits, vegetables, and avoid added sugars. Women with total scores below the median were younger, with higher BMI, had fewer years of education, and lower income levels. Implications for Cancer Survivors: The present study extends the literature on AABCS adherence to cancer survivor–specific dietary guidelines. Findings will inform future dietary lifestyle interventions in this population. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: African American women; Breast cancer survivors; Diet quality; Dietary adherence; Racial-ethnic disparities

The Detroit research on cancer survivors (ROCS) pilot study: A focus on outcomes after cancer in a racially diverse patient population - Beebe-Dimmer, J.L.; Albrecht, T.L.; Baird, T.E.; Ruterbusch, J.J.; Hastert, T.; Harper, F.W.K.; Simon, M.S.; Abrams, J.; Schwartz, K.L.; Schwartz, A.G. (Cancer Epidemiology Biomarkers and Prevention, 2019)
Background: African Americans are often diagnosed with advanced stage cancer and experience higher mortality compared with whites in the United States. Contributing factors, like differences in access to medical care and the prevalence of comorbidities, do not entirely explain racial differences in outcomes. Methods: The Detroit Research on Cancer Survivors (ROCS) pilot study was conducted to investigate factors related to short- and long-term outcomes among patients with cancer. Participants completed web-based surveys, and mailed saliva specimens were collected for future genetic studies. Results: We recruited 1,000 participants with an overall response rate of 68%. Thirty-one percent completed the survey without any interviewer support and the remaining participated in an interviewer-administered survey. Seventy-four percent provided a saliva specimen and 64% consented for tumor tissue retrieval. African American survivors required more interviewer support (P < 0.001); however, their response rate (69.6%) was higher than non-Hispanic whites (65.4%). African Americans reported poorer overall cancer-related quality of life compared with non-Hispanic whites, measured by FACT-G score (P < 0.001), however, this relationship was reversed after controlling for socioeconomic factors, marital status, and the presence of comorbidities. Conclusions: In this pilot study, we demonstrated that a web-based survey supplemented with telephone interviews and mailed saliva kits are cost-effective methods to collect patient-reported data and DNA for large studies of cancer survivors with a high proportion of minority patients. The preliminary data collected reinforces differences by race in factors affecting cancer outcomes. Our efforts continue as we expand this unique cohort to include more than 5,000 African American cancer survivors. Impact: Formal investigation of factors influencing adverse outcomes among African American cancer survivors will be critical in closing the racial gap in morbidity and mortality. © 2019 American Association for Cancer Research.

Prevalence of Hepatitis B Virus, Hepatitis C Virus, and HIV Infection among Patients with Newly Diagnosed Cancer from Academic and Community Oncology Practices - Ramsey, S.D.; Unger, J.M.; Baker, L.H.; Little, R.F.; Loomba, R.; Hwang, J.P.; Chugh, R.; Konerman, M.A.; Arnold, K.; Menter, A.R.; Thomas, E.; Michels, R.M.; et al. (JAMA Oncology, 2019)
Importance: Universal screening of patients with newly diagnosed cancer for hepatitis B virus (HBV), hepatitis C virus (HCV), and HIV is not routine in oncology practice, and experts disagree about whether universal screening should be performed. Objective: To estimate the prevalence of HBV, HCV, and HIV infection among persons with newly diagnosed cancer. Design, Setting, and Participants: Multicenter prospective cohort study of patients with newly diagnosed cancer (ie, identified within 120 days of cancer diagnosis) at 9 academic and 9 community oncology institutions affiliated with SWOG (formerly the Southwest Oncology Group) Cancer Research Network, a member of the National Clinical Trials Network, with enrollment from August 29, 2013, through February 15, 2017. The data analysis was conducted using data available through August 17, 2017. Main Outcomes and Measures: The accrual goal was 3000 patients and the primary end point was the presence of HBV infection (previous or chronic), HCV infection, or HIV infection at enrollment. Patients with previous knowledge of infection as well as patients with unknown viral viral status were evaluated. Results: Of 3092 registered patients, 3051 were eligible and evaluable. Median (range) age was 60.6 (18.2-93.7) years, 1842 (60.4%) were female, 553 (18.1%) were black, and 558 (18.3%) were Hispanic ethnicity. Screened patients had similar clinical and demographic characteristics compared with those registered. The observed infection rate for previous HBV infection was 6.5% (95% CI, 5.6%-7.4%; n = 197 of 3050 patients); chronic HBV, 0.6% (95% CI, 0.4%-1.0%; n = 19 of 3050 patients); HCV, 2.4% (95% CI, 1.9%-3.0%; n = 71 of 2990 patients); and HIV, 1.1% (95% CI, 0.8%-1.6%; n = 34 of 3045). Among those with viral infections, 8 patients with chronic HBV (42.1%; 95% CI, 20.3%-66.5%), 22 patients with HCV (31.0%; 95% CI, 20.5%-43.1%), and 2 patients with HIV (5.9%; 95% CI, 0.7%-19.7%) were newly diagnosed through the study. Among patients with infections, 4 patients with chronic HBV (21.1%; 95% CI, 6.1%-45.6%), 23 patients with HCV (32.4%; 95% CI, 21.8%-44.5%), and 7 patients with HIV (20.6%; 95% CI, 8.7%-37.9%) had no identifiable risk factors. Conclusions and Relevance: Results of this study found that a substantial proportion of patients with newly diagnosed cancer and concurrent HBV or HCV are unaware of their viral infection at the time of cancer diagnosis, and many had no identifiable risk factors for infection. Screening patients with cancer to identify HBV and HCV infection before starting treatment may be warranted to prevent viral reactivation and adverse clinical outcomes. The low rate of undiagnosed HIV infection may not support universal screening of newly diagnosed cancer patients. © 2019 American Medical Association. All rights reserved.

Safety and efficacy of the selective progesterone receptor modulator asoprisnil for heavy menstrual bleeding with uterine fibroids: Pooled analysis of two 12-month, placebo-controlled, randomized trials - Stewart, E.A.; Diamond, M.P.; Williams, A.R.W.; Carr, B.R.; Myers, E.R.; Feldman, R.A.; Elger, W.; Mattia-Goldberg, C.; Schwefel, B.M.; Chwalisz, K. (Human Reproduction, 2019)
STUDY QUESTION Can asoprisnil, a selective progesterone receptor modulator, provide clinically meaningful improvements in heavy menstrual bleeding (HMB) associated with uterine fibroids with an acceptable safety profile? SUMMARY ANSWER Uninterrupted treatment with asoprisnil for 12 months effectively controlled HMB and reduced fibroid and uterine volume with few adverse events. WHAT IS KNOWN ALREADY In a 3-month study, asoprisnil (5, 10 and 25 mg) suppressed uterine bleeding, reduced fibroid and uterine volume, and improved hematological parameters in a dose-dependent manner. STUDY DESIGN, SIZE, DURATION In two Phase 3, double-blind, randomized, placebo-controlled, multicentre studies, women received oral asoprisnil 10 mg, asoprisnil 25 mg or placebo (2:2:1) once daily for up to 12 months. PARTICIPANTS/MATERIALS, SETTING, METHODS Premenopausal women ≥18 years of age in North America with HMB associated with uterine fibroids were included (N = 907). The primary efficacy endpoint was the percentage of women who met all three predefined criteria at 12 months or the final month for patients who prematurely discontinued: (1) ≥50% reduction in monthly blood loss (MBL) by menstrual pictogram, (2) hemoglobin concentration ≥11 g/dL or an increase of ≥1 g/dL, and (3) no interventional therapy for uterine fibroids. Secondary efficacy endpoints included changes in other menstrual bleeding parameters, volume of the largest fibroids, uterine volume and health-related quality of life (HRQL). MAIN RESULTS AND THE ROLE OF CHANCE In all, 90% and 93% of women in the asoprisnil 10-mg and 25-mg groups, respectively, and 35% of women in the placebo group met the primary endpoint (P < 0.001). Similar results were observed at month 6 (P < 0.001). The percentage of women who achieved amenorrhea in any specified month ranged from 66-78% in the asoprisnil 10-mg group and 83-93% in the asoprisnil 25-mg group, significantly higher than with placebo (3-12%, P < 0.001). Hemoglobin increased rapidly (by month 2) with asoprisnil treatment and was significantly higher versus placebo throughout treatment. The primary fibroid and uterine volumes were significantly reduced from baseline through month 12 with asoprisnil 10 mg (median changes up to-48% and-28%, respectively) and 25 mg (median changes up to-63% and-39%, respectively) versus placebo (median changes up to +16% and +13%, respectively; all P < 0.001). Dose-dependent, significant improvements in HRQL (Uterine Fibroid Symptom and Quality of Life instrument) were observed with asoprisnil treatment. Asoprisnil was generally well tolerated. Endometrial biopsies indicated dose-and time-dependent decreases in proliferative patterns and increases in quiescent or minimally stimulated endometrium at month 12 of treatment. Although not statistically significantly different at month 6, mean endometrial thickness at month 12 increased by ∼2 mm in both asoprisnil groups compared with placebo (P < 0.01). This effect was associated with cystic changes in the endometrium on MRI and ultrasonography, which led to invasive diagnostic and therapeutic procedures in some asoprisnil-treated women. LIMITATIONS, REASONS FOR CAUTION Most study participants were black; few Asian and Hispanic women participated. The study duration may have been insufficient to fully characterize the endometrial effects. WIDER IMPLICATIONS OF THE FINDINGS Daily uninterrupted treatment with asoprisnil was highly effective in controlling menstrual bleeding, improving anemia, reducing fibroid and uterine volume, and increasing HRQL in women with HMB associated with uterine fibroids. However, this treatment led to an increase in endometrial thickness and invasive diagnostic and therapeutic procedures, with potential unknown consequences. STUDY FUNDING/COMPETING INTEREST(S) This trial was funded by AbbVie Inc. (prior sponsors: TAP Pharmaceutical Products Inc., Abbott Laboratories). E.A. Stewart was a site investigator in the Phase 2 study of asoprisnil and consulted for TAP during the design and conduct of these studies while at Harvard Medical School and Brigham and Women's Hospital. She received support from National Institutes of Health grants HD063312, HS023418 and HD074711 and research funding, paid to Mayo Clinic for patient care costs related to an NIH-funded trial from InSightec Ltd. She consulted for AbbVie, Allergan, Bayer HealthCare AG, Gynesonics, and Welltwigs. She received royalties from UpToDate and the Med Learning Group. M.P. Diamond received research funding for the conduct of the studies paid to the institution and consulted for AbbVie. He is a stockholder and board and director member of Advanced Reproductive Care. He has also received funding for study conduct paid to the institution from Bayer and ObsEva. A.R.W. Williams consulted for TAP and Repros Therapeutics Inc. He has current consultancies with PregLem SA, Gedeon Richter, HRA Pharma and Bayer. B.R. Carr consulted for and received research funding from AbbVie. E.R. Myers consulted for AbbVie, Allergan and Bayer. R.A. Feldman received compensation for serving as a principal investigator and participating in the conduct of the trial. W. Elger was co-inventor of several patents related to asoprisnil. C. Mattia-Goldberg is a former employee of AbbVie and may own AbbVie stock or stock options. B.M. Schwefel and K. Chwalisz are employees of AbbVie and may own AbbVie stock or stock options. TRIAL REGISTRATION NUMBER NCT00152269, NCT00160381 (clinicaltrials.gov). TRIAL REGISTRATION DATE 7 September 2005; 8 September 2005. DATE OF FIRST PATIENT'S ENROLMENT 12 September 2002; 6 September 2002. © 2019 The Author(s).
Keywords: asoprisnil; fibroids; heavy menstrual bleeding; J867; selective progesterone receptor modulator; uterine fibroid; uterine leiomyoma; uterine leiomyomata

Surgical Tumor-Derived Personalized Photothermal Vaccine Formulation for Cancer Immunotherapy - Ye, X.; Liang, X.; Chen, Q.; Miao, Q.; Chen, X.; Zhang, X.; Mei, L. (ACS Nano, 2019)
Personalized cancer vaccines show great potential in cancer immunotherapy by inducing an effective and durable antitumor response. However, the limitation of neoantigen identification, low immunogenicity, and weak immune response hamper the development of personalized cancer vaccines. The surgically removed tumor contains tumor antigens specific to the patient, which provides a promising source for personalized cancer vaccines. Here, we utilized the surgically removed tumor to prepare a personalized photothermal vaccine combined with the PD-1 checkpoint blockade antibody to prevent tumor relapse and metastasis. Black phosphorus quantum dot nanovesicles (BPQD-CCNVs) coated with surgically removed tumor cell membrane were prepared and loaded into a thermosensitive hydrogel containing GM-CSF and LPS. The sustained release of GM-CSF from the hypodermic injection of Gel-BPQD-CCNVs effectively recruited dendritic cells to capture tumor antigen. NIR irradiation and LPS stimulated the expansion and activation of DCs, which then traveled to the lymph nodes to present antigen to CD8 + T cells. Moreover, the combination with PD-1 antibody significantly enhanced tumor-specific CD8 + T cell elimination of the surgical residual and lung metastatic tumor. Hence, our work may provide a promising strategy for the clinical development of a personalized cancer vaccine. © 2019 American Chemical Society.
Keywords: Black phosphorus; cancer cell membrane; immunotherapy; personal vaccine; photothermal

Baseline Prostate-specific Antigen Level in Midlife and Aggressive Prostate Cancer in Black Men(Figure presented.) - Preston, M.A.; Gerke, T.; Carlsson, S.V.; Signorello, L.; Sjoberg, D.D.; Markt, S.C.; Kibel, A.S.; Trinh, Q.-D.; Steinwandel, M.; Blot, W.; Vickers, A.J.; Lilja, H.; et al. (European Urology, 2019)
Background: Prostate-specific antigen (PSA) measurement in midlife predicts long-term prostate cancer (PCa) mortality among white men. Objective: To determine whether baseline PSA level during midlife predicts risk of aggressive PCa in black men. Design, setting, and participants: Nested case-control study among black men in the Southern Community Cohort Study recruited between 2002 and 2009. A prospective cohort in the southeastern USA with recruitment from community health centers. A total of 197 incident PCa patients aged 40–64 yr at study entry and 569 controls matched on age, date of blood draw, and site of enrollment. Total PSA was measured in blood collected and stored at enrollment. Outcome measurements and statistical analysis: Total and aggressive PCa (91 aggressive: Gleason ≥7, American Joint Committee on Cancer stage III/IV, or PCa-specific death). Exact conditional logistic regression estimated odds ratios (ORs) with 95% confidence intervals (CIs) for PCa by category of baseline PSA. Results and limitations: Median PSA among controls was 0.72, 0.80, 0.94, and 1.03 ng/ml for age groups 40–49, 50–54, 55–59, and 60–64 yr, respectively; 90th percentile levels were 1.68, 1.85, 2.73, and 3.33 ng/ml. Furthermore, 95% of total and 97% of aggressive cases had baseline PSA above the age-specific median. Median follow-up was 9 yr. The OR for total PCa comparing PSA >90th percentile versus ≤median was 83.6 (95% CI, 21.2–539) for 40–54 yr and 71.7 (95% CI, 23.3–288) for 55–64 yr. For aggressive cancer, ORs were 174 (95% CI, 32.3–infinity) for 40–54 yr and 51.8 (95% CI, 11.0–519) for 55–64 yr. A composite endpoint of aggressive PCa based on stage, grade, and mortality was used and is a limitation. Conclusions: PSA levels in midlife strongly predicted total and aggressive PCa among black men. PSA levels among controls were similar to those among white controls in prior studies. Patient summary: Prostate-specific antigen (PSA) level during midlife strongly predicted future development of aggressive prostate cancer among black men. Targeted screening based on a midlife PSA might identify men at high risk while minimizing screening in those men at low risk. © 2018 European Association of Urology Prostate-specific antigen (PSA) level during midlife strongly predicted total and aggressive prostate cancer among black men. Risk-stratified screening based on midlife PSA might retain the benefits of screening while reducing harms. © 2018 European Association of Urology
Keywords: African-American; Baseline; Prostate cancer; Prostate-specific antigen; Screening

Aspirin and non-aspirin NSAID use and prostate cancer incidence, mortality, and case fatality in the Atherosclerosis Risk in Communities study - Hurwitz, L.M.; Joshu, C.E.; Barber, J.R.; Prizment, A.E.; Vitolins, M.Z.; Jones, M.R.; Folsom, A.R.; Han, M.; Platz, E.A. (Cancer Epidemiology Biomarkers and Prevention, 2019)
Background: NSAIDs appear to moderately reduce prostate cancer risk. However, evidence is limited on whether NSAIDs protect against prostate cancer mortality (death from prostate cancer among men without a cancer history) and case fatality (death from prostate cancer among men with prostate cancer), and whether benefits are consistent in white and black men. This study investigated associations of aspirin and non-aspirin (NA) NSAID use with prostate cancer incidence, mortality, and case fatality in a population-based cohort of white and black men. Methods: We included 6,594 men (5,060 white and 1,534 black) from the Atherosclerosis Risk in Communities study without a cancer history at enrollment from 1987 to 1989. NSAID use was assessed at four study visits (1987–1998). Cancer outcomes were ascertained through 2012. Cox proportional hazards regression was used to estimate adjusted HRs, overall and by race. Results: Aspirin use was not associated with prostate cancer incidence. However, aspirin use was inversely associated with prostate cancer mortality [HR, 0.59; 95% confidence interval (CI), 0.36–0.96]. This association was consistent among white and black men and appeared restricted to men using aspirin daily and/or for cardiovascular disease prevention. Aspirin use was inversely associated with case fatality (HR, 0.45; 95% CI, 0.22–0.94). NA-NSAID use was not associated with these endpoints. Conclusions: Aspirin use was inversely associated with prostate cancer mortality and case fatality among white and black men. Impact: If confirmed by additional studies, benefits of aspirin for preventing prostate cancer mortality may need to be factored into risk–benefit calculations of men considering an aspirin regimen. © 2018 American Association for Cancer Research.

Overall survival of black and white men with metastatic castration-resistant prostate cancer treated with docetaxel - Halabi, S.; Dutta, S.; Tangen, C.M.; Rosenthal, M.; Petrylak, D.P.; Thompson, I.M., Jr.; Chi, K.N.; Araujo, J.C.; Logothetis, C.; Quinn, D.I.; Fizazi, K.; Morris, M.J.; et al. (Journal of Clinical Oncology, 2019)
PURPOSE Several studies have reported that among patients with localized prostate cancer, black men have a shorter overall survival (OS) time than white men, but few data exist for men with advanced prostate cancer. The primary goal of this analysis was to compare the OS in black and white men with metastatic castration-resistant prostate cancer (mCRPC) who were treated in phase III clinical trials with docetaxel plus prednisone (DP) or a DP-containing regimen. METHODS Individual participant data from 8,820 men with mCRPC randomly assigned in nine phase III trials to DP or a DP-containing regimen were combined. Race was based on self-report. The primary end point was OS. The Cox proportional hazards regression model was used to assess the prognostic importance of race (black v white) adjusted for established risk factors common across the trials (age, prostate-specific antigen, performance status, alkaline phosphatase, hemoglobin, and sites of metastases). RESULTS Of 8,820 men, 7,528 (85%) were white, 500 (6%) were black, 424 (5%) were Asian, and 368 (4%) were of unknown race. Black men were younger and had worse performance status, higher testosterone and prostate-specific antigen, and lower hemoglobin than white men. Despite these differences, the median OS was 21.0 months (95% CI, 19.4 to 22.5 months) versus 21.2 months (95% CI, 20.8 to 21.7 months) in black and white men, respectively. The pooled multivariable hazard ratio of 0.81 (95% CI, 0.72 to 0.91) demonstrates that overall, black men have a statistically significant decreased risk of death compared with white men (P, .001). CONCLUSION When adjusted for known prognostic factors, we observed a statistically significant increased OS in black versus white men with mCRPC who were enrolled in these clinical trials. The mechanism for these differences is not known. © 2019 American Society of Clinical Oncology. All rights reserved.

Minority Recruitment Trends in Phase III Prostate Cancer Clinical Trials (2003 to 2014): Progress and Critical Areas for Improvement - Balakrishnan, A.S.; Palmer, N.R.; Fergus, K.B.; Gaither, T.W.; Baradaran, N.; Ndoye, M.; Breyer, B.N. (Journal of Urology, 2019)
Purpose:American minority groups have been historically underrepresented in phase III prostate cancer clinical trials despite often having higher risk disease. We analyzed enrollment trends of major racial/ethnic groups in the United States in phase III prostate cancer trials between 2003 and 2014 compared to SEER (Surveillance, Epidemiology and End Results) incidence data.Materials and Methods:Phase III prostate cancer trials primarily enrolling patients from the United States were identified in the ClinicalTrials.gov database. Enrollment trends were analyzed for major racial/ethnic groups. Prostate cancer incidence data from the SEER registry were used to identify enrollment targets. The enrollment difference was determined by calculating the absolute difference between the percent of a racial/ethnic subgroup in the SEER registry population and the percent of that subgroup in the phase III prostate cancer trial population.Results:Among 39 studies identified African American enrollment in therapeutic trials increased across the study period (p <0.001). The enrollment difference for African Americans was-9.0% (95% CI-7.6-10.5, p <0.001) in 2003 to 2005 and 1.4% (95% CI 0.2-2.6, p = 0.020) in 2012 to 2014. However, African American men were under enrolled in metastatic disease trials (enrollment difference-5.8%, 95% CI-4.8-6.8, p <0.001). Latino and Asian American men were consistently under enrolled in all trial types.Conclusions:Minority groups in the United States were largely under enrolled in phase III prostate cancer trials between 2003 and 2014. While recruitment efforts may have had an impact, as demonstrated by increased enrollment of African American men, there remains a need to expand recruitment efforts to achieve diversity in trials. © 2019 by AMERICAN UROLOGICAL ASSOCIATION EDUCATION AND RESEARCH, INC.
Keywords: clinical trials as topic; minority health; patient selection; prostatic neoplasms; SEER Program

Mobile Mammography Screening as an Opportunity to Increase Access of Rural Women to Breast Cancer Research Studies - McElfish, P.A.; Su, L.J.; Lee, J.Y.; Runnells, G.; Henry-Tillman, R.; Kadlubar, S.A. (Breast Cancer: Basic and Clinical Research, 2019)
Objectives: Rural women are underrepresented in cancer research. We hypothesized that providing access to a research study to rural, medically underserved women who were receiving their breast cancer screening using a mobile mammography unit would increase the representation of rural women in a cancer cohort study. Design: This study is a cross-sectional study using a cohort of women who have been recruited to a breast cancer study in Arkansas. Setting: Recruiters accompanied a mobile mammography unit, the MammoVan, to implement a novel method for reaching and recruiting underrepresented rural Arkansas women into the study. Participants include 5850 women recruited from 2010 through 2012 as part of the Arkansas Rural Community Health (ARCH) study. Results: Participants recruited during their mammography screening on the MammoVan tended to be more rural, less educated, and more likely to be non-Hispanic than those recruited in other venues. A significant difference was not noted for race or age. Conclusion: Collaboration with the MammoVan greatly aided the recruitment of rural participants. These strategies can facilitate the representation of this historically underserved and understudied rural population in future research studies. © The Author(s) 2019.
Keywords: Breast cancer research; mobile mammography; rural; under-represented population

Treatment of childhood nasopharyngeal carcinoma with induction chemotherapy and concurrent chemoradiotherapy: Results of the Children's Oncology Group ARAR0331 study - Rodriguez-Galindo, C.; Krailo, M.D.; Krasin, M.J.; Huang, L.; Beth McCarville, M.; Hicks, J.; Pashankar, F.; Pappo, A.S. (Journal of Clinical Oncology, 2019)
PURPOSE The treatment of childhood nasopharyngeal carcinoma has been adapted from adult regimens; pediatric-specific studies are limited. The ARAR0331 study sought to evaluate the impact of induction chemotherapy (IC) and concurrent chemoradiotherapy (CCR). PATIENTS AND METHODS Patients with American Joint Committee on Cancer stages IIb to IV were scheduled to receive three cycles of IC with cisplatin and fluorouracil, followed by CCR with three cycles of cisplatin. Patients with complete or partial response to IC received 61.2 Gy to the nasopharynx and neck, and patients with stable disease received 71.2 Gy. RESULTS Between February 2006 and January 2012, 111 patients (75 male) were enrolled. Median age was 15 years, and 46.8% of the patients were African American. After a feasibility analysis, the study was amended to reduce cisplatin to two cycles during CCR. The 5-year event-free survival (EFS) and overall survival estimates were 84.3% and 89.2%, respectively. The 5-year EFS for stages IIb, III, and IV were 100%, 82.8%, and 82.7%, respectively. The 5-year cumulative incidence estimates of local, distant, and combined relapse were 3.7%, 8.7%, and 1.8%, respectively. Patients treated with three versus two CCR cycles of cisplatin had improved 5-year postinduction EFS (90.7% v 81.2%, P = .14). CONCLUSION Patients in ARAR0331 were characterized by advanced disease and by a high proportion of black children and adolescents. Treatment with IC and CRT resulted in excellent outcomes. A radiation dose reduction is possible for patients responding to IC. Although the outcomes are comparable, we observed a trend toward decreased EFS for patients assigned to receive fewer doses of cisplatin during CCR. © 2019 American Society of Clinical Oncology. All rights reserved.

Prospective assessment of demographic characteristics associated with worse health related quality of life measures following definitive chemoradiation in patients with locally advanced non-small cell lung cancer - Vogel, J.; Wang, X.; Troxel, A.B.; Simone, C.B., II; Rengan, R.; Lin, L.L. (Translational Lung Cancer Research, 2019)
Background: The purpose of this study was to evaluate baseline demographic characteristics which may be associated with worse health related quality of life (HRQOL) for patients with locally advanced non-small cell lung cancer (NSCLC) receiving definitive chemoradiation (CRT). Materials: Patients with NSCLC were prospectively enrolled on an Institutional Review Board-approved clinical trial between 2009 and 2012. HRQOL assessments were collected pre-radiation therapy (RT), during RT, and within 3 months post-RT using Euroqol (EQ-5D), MD Anderson Symptom Inventory (MDASI), and Functional Assessment of Cancer Therapy General (FACT-G). HRQOL correlation was assessed with categorical variables by Wilcoxon rank sum tests and with continuous variables by Pearson correlation. P<0.05 was defined as statistically significant. Results: Forty-three consecutive patients received definitive concurrent CRT and completed assessments at one or more time-points. Patients most commonly had stage IIIB disease (72%), were married or with a partner (70%) and Caucasian (91%). Median patient age was 65 (range: 39–79) years and Charlson comorbidity index (CCI) was 0 (range: 0–5). Female gender, African-American ethnicity, age, chemotherapy type, baseline hemoglobin, and CCI were associated with worse post-treatment HRQOL measures. Conclusions: We have identified novel characteristics associated with worse quality of life following definitive CRT for lung cancer. Patients at risk for worse post-treatment quality of life may benefit from earlier follow-up and greater supportive measures following treatment. © Translational lung cancer research. All rights reserved.
Keywords: Chemoradiation (CRT); Non-small cell lung cancer (NSCLC); Quality of life

Feasibility randomised controlled trial of a guided workbook intervention to support work-related goals among cancer survivors in the UK - Grunfeld, E.A.; Schumacher, L.; Armaou, M.; Woods, P.L.; Rolf, P.; Sutton, A.J.; Zarkar, A.; Sadhra, S.S. (BMJ Open, 2019)
Objectives Employment following illness is associated with better physical and psychological functioning. This study aimed to assess the feasibility and acceptability of a theoretically led workbook intervention designed to support patients with cancer returning to work. Design Parallel-group randomised controlled trial with embedded qualitative interviews. Setting Oncology clinics within four English National Health Service Trusts. Participants Patients who had received a diagnosis of breast, gynaecological, prostate or colorectal cancer and who had been receiving treatment for a minimum of two weeks. Intervention A self-guided WorkPlan workbook designed to support patients with cancer to return to work with fortnightly telephone support calls to discuss progress. The control group received treatment as usual and was offered the workbook at the end of their 12-month follow-up. Outcome measures We assessed aspects of feasibility including eligibility, recruitment, data collection, attrition, feasibility of the methodology, acceptability of the intervention and potential to calculate cost-effectiveness. Results The recruitment rate of eligible patients was 44%; 68 participants consented and 58 (85%) completed baseline measures. Randomisation procedures were acceptable, data collection methods (including cost-effectiveness data) were feasible and the intervention was acceptable to participants. Retention rates at 6-month and 12-month follow-up were 72% and 69%, respectively. At 6-month follow-up, 30% of the usual care group had returned to full-time or part-time work (including phased return to work) compared with 43% of the intervention group. At 12 months, the percentages were 47% (usual care) and 68% (intervention). Conclusions The findings confirm the feasibility of a definitive trial, although further consideration needs to be given to increasing the participation rates among men and black and ethnic minority patients diagnosed with cancer. © Author(s) (or their employer(s)) 2018.
Keywords: cancer; employment; feasibility; intervention; randomised controlled trial

Disease-Free and Overall Survival among Patients with Operable HER2-Positive Breast Cancer Treated with Sequential vs Concurrent Chemotherapy: The ACOSOG Z1041 (Alliance) Randomized Clinical Trial - Buzdar, A.U.; Suman, V.J.; Meric-Bernstam, F.; Leitch, A.M.; Ellis, M.J.; Boughey, J.C.; Unzeitig, G.W.; Royce, M.E.; Hunt, K.K. (JAMA Oncology, 2019)
Importance: Pathologic complete response rate (pCR), the primary end point of the ACOSOG (American College of Surgeons Oncology Group) Z1041 (Alliance) trial, and disease-free survival (DFS) and overall survival (OS) in women with operable HER2-positive breast cancer are similar between treatment regimens. Objective: To assess DFS and OS for patients treated with sequential vs concurrent anthracycline plus trastuzumab. Design, Setting, and Participants: Phase 3 randomized clinical trial conducted at 36 centers in the continental United States and Puerto Rico. Women 18 years or older with invasive operable HER2-positive breast cancer were enrolled from September 15, 2007, to December 15, 2011, and randomized to 1 of 2 treatment arms. The analysis data set was locked on October 15, 2017, and analysis was completed on December 15, 2017. Interventions: Patients randomized to arm 1 received 500 mg/m 2 of fluorouracil, 75 mg/m 2 of epirubicin, and 500 mg/m 2 of cyclophosphamide (FEC) every 3 weeks for 12 weeks followed by the combination of 80 mg/m 2 of paclitaxel and 2 mg/kg (except initial dose of 4 mg/kg) of trastuzumab weekly for 12 weeks. Patients randomized to arm 2 received the same combination of paclitaxel with trastuzumab weekly for 12 weeks followed by FEC every 3 weeks with weekly trastuzumab for 12 weeks. Women with hormone receptor-positive disease received endocrine therapy, and radiotherapy was delivered at physician discretion. Main Outcomes and Measures: The primary outcomes were DFS and OS and pCR in the breast and nodes. Results: Two hundred eighty-two women with HER2-positive breast cancer were enrolled in the trial, and 2 withdrew consent before treatment. Among the remaining 280 women, the median age was 50 years (range, 28-76 years), 232 (82.9%) were white, 29 (10.3%) were black, 8 (2.9%) were Asian, 4 (1.4%) were American Indian or Alaskan Native, and 7 (2.5%) did not report race/ethnicity. There were 22 disease events in arm 1 and 27 in arm 2. Disease-free survival rates did not differ with respect to treatment arm (stratified log-rank P =.96; stratified hazard ratio [HR] [arm 2 to arm 1], 1.02; 95% CI, 0.56-1.83). Overall survival did not differ with respect to treatment arm (stratified log-rank P =.73; stratified HR [arm 2 to arm 1], 1.17; 95% CI, 0.48-2.88). Conclusions and Relevance: Across a median follow-up of 5.1 years (range, 26 days to 6.2 years), pCR, DFS, and OS did not differ with respect to sequential or concurrent administration of FEC with trastuzumab. Trial Registration: ClinicalTrials.gov identifier: NCT00513292. © 2018 American Medical Association. All rights reserved.

Serum urate, genetic variation, and prostate cancer risk: Atherosclerosis risk in Communities (ARIC) study - Wang, A.; Barber, J.R.; Tin, A.; De Marzo, A.M.; Kottgen, A.; Joshu, C.E.; Platz, E.A. (Cancer Epidemiology Biomarkers and Prevention, 2019)
Background: Evidence is mounting that intraprostatic inflammation influences prostate cancer development. Uric acid crystals depositing in the prostate could result in injury and inflammation, increasing prostate cancer risk. Methods: Included were 6,574 men ages 45–64 years who enrolled in the Atherosclerosis Risk in Communities study in 1987 to 1989. We used Cox proportional hazards regression to estimate the association of serum urate concentration alone and to improve accuracy, jointly with a genetic risk score (GRS, N ¼ 4,983) derived from variants predictive of urate concentration, with prostate cancer (N ¼ 813) risk. Results: Serum urate concentration or joint categories of urate concentration and GRS were not associated with prostate cancer risk (Ptrend for quartiles ¼ 0.3). Results were generally similar by race and after excluding users of medications that influence uric acid. Conclusions: Serum urate alone and with a urate-associated GRS were not associated with prostate cancer risk. Impact: It is unlikely that circulating urate concentration influences prostate cancer development. © 2019 American Association for Cancer Research.

Aerobic fitness and adherence to guideline-recommended minimum physical activity among ambulatory patients with type 2 diabetes mellitus - Jarvie, J.L.; Pandey, A.; Ayers, C.R.; McGavock, J.M.; Sénéchal, M.; Berry, J.D.; Patel, K.V.; McGuire, D.K. (Diabetes Care, 2019)
OBJECTIVE Lifestyle intervention remains the cornerstone of management of type 2 diabetes mellitus (T2DM). However, adherence to physical activity (PA) recommendations and the impact of that adherence on cardiorespiratory fitness in this population have been poorly described. We sought to investigate adherence to PA recommendations and its association with cardiorespiratory fitness in a population of patients with T2DM. RESEARCH DESIGN AND METHODS A cross-sectional analysis of baseline data from a randomized clinical trial (NCT00424762) was performed. A total of 150 individuals with medically treated T2DM and atherosclerotic cardiovascular disease (ASCVD) or risk factors for ASCVD were recruited from outpatient clinics at a single academic medical center. All individuals underwent a graded maximal exercise treadmill test to exhaustion with breath-by-breath gas exchange analysis to determine VO2peak. PA was estimated using a structured 7-Day Physical Activity Recall interview. RESULTS Participants had a mean6SD age of 54.969.0 years; 41% were women, 40% were black, and 21% were Hispanic. The mean HbA1c was 7.761.8% and the mean BMI, 34.5 6 7.2 kg/m2. A total of 72% had hypertension, 73% had hyperlipidemia, and 35% had prevalent ASCVD. The mean6SD reported daily PA was 34.364 kcal/kg, only 7% above a sedentary state; 47% of the cohort failed to achieve the minimum recommended PA. Mean 6 SD VO2peak was 27.4 6 6.5 mL/kg fat-free mass/min (18.8 6 5.0 mL/kg/min). CONCLUSIONS On average, patients with T2DM who have or are at risk for ASCVD report low levels of PA and have low measured cardiopulmonary fitness. This underscores the importance of continued efforts to close this therapeutic gap. © 2019 by the American Diabetes Association.

Sistas taking a stand for breast cancer research (STAR) study: A community-based participatory genetic research study to enhance participation and breast cancer equity among African American women in Memphis, TN - Smith, A.; Vidal, G.A.; Pritchard, E.; Blue, R.; Martin, M.Y.; Rice, L.J.; Brown, G.; Starlard-Davenport, A. (International Journal of Environmental Research and Public Health, 2018)
African American women are substantially underrepresented in breast cancer genetic research studies and clinical trials, yet they are more likely to die from breast cancer. Lack of trust in the medical community is a major barrier preventing the successful recruitment of African Americans into research studies. When considering the city of Memphis, TN, where the percentage of African Americans is significantly higher than the national average and it has a high rate of breast cancer mortality inequities among African American women, we evaluated the feasibility of utilizing a community-based participatory (CBPR) approach for recruiting African American women into a breast cancer genetic study, called the Sistas Taking A Stand for Breast Cancer Research (STAR) study. From June 2016 and December 2017, African American women age 18 and above were recruited to provide a 2 mL saliva specimen and complete a health questionnaire. A total of 364 African American women provided a saliva sample and completed the health questionnaire. Greater than 85% agreed to be contacted for future studies. Educational workshops on the importance of participating in cancer genetic research studies, followed by question and answer sessions, were most successful in recruitment. Overall, the participants expressed a strong interest and a willingness to participate in the STAR study. Our findings highlight the importance of implementing a CBPR approach that provides an educational component detailing the importance of participating in cancer genetic research studies and that includes prominent community advocates to build trust within the community. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: African American women; Breast cancer; Community-based participatory research; Genetics; Health equity; Memphis; TN

A Prospective Adaptive Utility Trial to Validate Performance of a Novel Urine Exosome Gene Expression Assay to Predict High-grade Prostate Cancer in Patients with Prostate-specific Antigen 2–10 ng/ml at Initial Biopsy - McKiernan, J.; Donovan, M.J.; Margolis, E.; Partin, A.; Carter, B.; Brown, G.; Torkler, P.; Noerholm, M.; Skog, J.; Shore, N.; Andriole, G.; Thompson, I.; et al. (European Urology, 2018)
Background: Discriminating indolent from clinically significant prostate cancer (PCa) in the initial biopsy setting remains an important issue. Prospectively evaluated diagnostic assays are necessary to ensure efficacy and clinical adoption. Objective: Performance and utility assessment of ExoDx Prostate (IntelliScore) (EPI) urine exosome gene expression assay versus standard clinical parameters for discriminating Grade Group (GG) ≥2 PCa from GG1 PCa and benign disease on initial biopsy. Design, setting, and participants: A two-phase adaptive clinical utility study (NCT03031418) comparing EPI results with biopsy outcomes in men, with age ≥50 yr and prostate-specific antigen (PSA) 2–10 ng/ml, scheduled for initial prostate biopsy. After EPI performance assessment during phase I, a clinical implementation document (ie, CarePath) was developed for utilizing the EPI test in phase II, where the biopsy decision is uncertain. Outcome measurements and statistical analysis: Performance evaluation of the EPI test in patients enrolled in phase I and publication of a consensus CarePath for phase II. Results and limitations: In a total of 503 patients, with median age of 64 yr, median PSA 5.4 ng/ml, 14% African American, 70% Caucasian, 53% positive biopsy rate (22% GG1, 17% GG2, and 15% ≥ GG3), EPI was superior to an optimized model of standard clinical parameters with an area under the curve (AUC) 0.70 versus 0.62, respectively, comparable with previously published results (n = 519 patients, EPI AUC 0.71). Validated cut-point 15.6 would avoid 26% of unnecessary prostate biopsies and 20% of total biopsies, with negative predictive value (NPV) 89% and missing 7% of ≥GG2 PCa. Alternative cut-point 20 would avoid 40% of unnecessary biopsies and 31% of total biopsies, with NPV 89% and missing 11% of ≥GG2 PCa. The clinical investigators reached consensus recommending use of the 15.6 cut-point for phase II. Outcome of the decision impact cohort in phase II will be reported separately. Conclusions: EPI is a noninvasive, easy-to-use, gene expression urine assay, which has now been successfully validated in over 1000 patients across two prospective validation trials to stratify risk of ≥GG2 from GG1 cancer and benign disease. The test improves identification of patients with higher grade disease and would reduce the total number of unnecessary biopsies. Patient summary: It is challenging to predict which men are likely to have high-grade prostate cancer (PCa) at initial biopsy with prostate-specific antigen 2–10 ng/ml. This study further demonstrates that the ExoDx Prostate (IntelliScore) test can predict ≥GG2 PCa at initial biopsy and defer unnecessary biopsies better than existing risk calculator's and standard clinical data. ExoDx Prostate (IntelliScore) is a urine-based test that relies solely on a three-gene signature to predict high-grade prostate cancer at initial biopsy for men with prostate-specific antigen 2–10 ng/ml. The test has been prospectively validated on over 1000 men from two multisite trials. © 2018 The Author(s)
Keywords: Exosomes; Extended validation study; High grade prostate cancer; Initial biopsy; Prostate cancer; Risk assessment tools

Low-dose computed tomography lung cancer screening as a teachable moment for smoking cessation among African American smokers: A feasibility study - Sly, J.R.; Miller, S.J.; Li, Y.; Bolutayo, K.; Jandorf, L. (Journal of Psychosocial Oncology, 2018)
Low-dose computed tomography (LDCT) screening may be a teachable moment for smoking cessation among African Americans. African Americans have been understudied within the context of LDCT and smoking cessation. The study objective was to evaluate the feasibility of recruiting African Americans to a future longitudinal trial and to obtain sample size estimates for that trial. Participants (N = 18) were African Americans eligible for LDCT screening who completed a questionnaire at three time points. Self-efficacy and intention to quit smoking were compared. The results of the current study show that it is feasible to recruit African Americans eligible for LDCT. © 2018, © 2018 Taylor & Francis Group, LLC.
Keywords: African Americans; cancer prevention; lung cancer screening; smoking cessation; teachable moment

Barriers and facilitators of using sensored medication adherence devices in a diverse sample of patients with multiple myeloma: Qualitative study - Asfaw, A.A.; Yan, C.H.; Sweiss, K.; Wirth, S.; Ramirez, V.H.; Patel, P.R.; Sharp, L.K. (Journal of Medical Internet Research, 2018)
Background: Many recently approved medications to manage multiple myeloma (MM) are oral, require supportive medications to prevent adverse effects, and are taken under complex schedules. Medication adherence is a concern; however, little attention has been directed toward understanding adherence in MM or associated barriers and facilitators. Advanced sensored medication devices (SMDs) offer opportunities to intervene; however, acceptability among patients with MM, particularly African American patients, is untested. Objective: This study aimed to explore patients’ (1) perceptions of their health before MM including experiences with chronic medications, (2) perceptions of adherence barriers and facilitators, and (3) attitudes toward using SMDs. Methods: An in-person, semistructured, qualitative interview was conducted with a convenience sample of patients being treated for MM. Patients were recruited from within an urban, minority-serving, academic medical center that had an established cancer center. A standardized interview guide included questions targeting medication use, attitudes, adherence, barriers, and facilitators. Demographics included the use of cell phone technology. Patients were shown 2 different pill bottles with sensor technology—Medication Event Monitoring System and the SMRxT bottle. After receiving information on the transmission ability of the bottles, patients were asked to discuss their reactions and concerns with the idea of using such a device. Medical records were reviewed to capture information on medication and diagnoses. The interviews were audio-recorded and transcribed. Interviews were independently coded by 2 members of the team with a third member providing guidance. Results: A total of 20 patients with a mean age of 56 years (median=59 years; range=29-71 years) participated in this study and 80% (16/20) were African American. In addition, 18 (90%, 18/20) owned a smartphone and 85% (17/20) were comfortable using the internet, text messaging, and cell phone apps. The average number of medications reported per patient was 13 medications (median=10; range=3-24). Moreover, 14 (70%, 14/20) patients reported missed doses for a range of reasons such as fatigue, feeling ill, a busy schedule, forgetting, or side effects. Interest in using an SMD ranged from great interest to complete lack of interest. Examples of concerns related to the SMDs included privacy issues, potential added cost, and the size of the bottle (ie, too large). Despite the concerns, 60% (12/20) of the patients expressed interest in trying a bottle in the future. Conclusions: Results identified numerous patient-reported barriers and facilitators to missed doses of oral anticancer therapy. Many appear to be potentially mutable if uncovered and addressed. SMDs may allow for capture of these data. Although patients expressed concerns with SMDs, most remained willing to use one. A feasibility trial with SMDs is planned. © Alemseged Ayele Asfaw, Connie H Yan, Karen Sweiss, Scott Wirth, Victor H Ramirez, Pritesh R Patel, Lisa K Sharp.
Keywords: Antineoplastic therapy; Challenges; Medication adherence; Multiple myeloma; Race/ethnicity

Adjuvant Pelvic Radiation "sandwiched" between Paclitaxel/Carboplatin Chemotherapy in Women with Completely Resected Uterine Serous Carcinoma: Long-term Follow-up of a Prospective Phase 2 Trial - Frimer, M.; Miller, E.M.; Shankar, V.; Girda, E.; Mehta, K.; Smith, H.O.; Kuo, D.Y.S.; Goldberg, G.L.; Einstein, M.H. (International Journal of Gynecological Cancer, 2018)
Objective We prospectively evaluated patients with completely resected uterine serous carcinoma (USC) treated with radiation "sandwiched" between carboplatin/paclitaxel (C/T). The primary objective was to determine the safety profile, and the secondary outcome was to evaluate progression-free and overall survival. Methods Surgically staged patients with completely resected USC were enrolled to receive 3 cycles of paclitaxel 175 mg/m2 and carboplatin (area under the curve, 6-7.5) every 21 days, followed by radiotherapy and an additional 3 cycles of T/C at area under the curve of 5-6 (6 cycles + radiotherapy). Toxicity was graded according to National Cancer Institute Common Toxicity Criteria, version 4.03. Kaplan-Meier and log-rank tests were used to compare survival probabilities. Results One hundred forty patients were enrolled, of which 132 were evaluable, completed at least 3 cycles of chemotherapy and radiation. One hundred seven (81%) completed 6 cycles of chemotherapy and radiation. Patients with early-stage (I/II) disease have survival probabilities of 0.96 and 0.81 at 2 and 5 years. Patients with stage I USC and lymphovascular invasion have considerably worse overall survival, with 2.7 times' higher risk of death than those without lymphovascular invasion. Patients with late-stage (III/IV) disease had overall survival probabilities of 0.64 and 0.18 at 2 and 5 years, which is far higher survival than what has been reported in single-modality trials. Interestingly, and different than what is reported in other studies, there is no difference in survival in African Americans versus whites/other races who were evaluable. Of the 779 cycles administered, 22% and 14% of cycles were associated with grades 3 and 4 hematologic toxicities, respectively. Grades 3 and 4 nonhematologic toxicities occurred in 6.9% of cycles. Conclusions The long-term follow-up in this study demonstrates that "sandwich" therapy is an efficacious, well-tolerated treatment approach with acceptable toxicities. Lymphovascular invasion (LVSI) is a significantly poor prognostic factor in stage I USC. Multimodal "sandwich" therapy should be considered in all USC patients who have undergone complete surgical resection and staging. © 2018 by IGCS and ESGO.

Vitamin D Supplementation in Elderly Black Women Does Not Prevent Bone Loss: A Randomized Controlled Trial - Aloia, J.; Fazzari, M.; Islam, S.; Mikhail, M.; Shieh, A.; Katumuluwa, S.; Dhaliwal, R.; Stolberg, A.; Usera, G.; Ragolia, L. (Journal of Bone and Mineral Research, 2018)
Black Americans have lower levels of serum 25(OH)D but superior bone health compared to white Americans. There is controversy over whether they should be screened for vitamin D deficiency and have higher vitamin D requirements than recommended by the Institute of Medicine (IOM). The purpose of this trial was to determine whether Vitamin D supplementation in elderly black women prevents bone loss. A total of 260 healthy black American women, 60 years of age and older were recruited to take part in a two-arm, double-dummy 3-year randomized controlled trial (RCT) of vitamin D3 versus placebo. The study was conducted in an ambulatory clinical research center. Vitamin D3 dose was adjusted to maintain serum 25(OH)D above 75 nmol/L. Bone mineral density (BMD) and serum were measured for parathyroid hormone (PTH), C-terminal crosslink telopeptide (CTX), and bone-specific alkaline phosphatase (BSAP) every 6 months. Baseline serum 25(OH)D3 was 54.8 ± 16.8 nmol/L. There was no group × time interaction effect for any BMD measurement. For all BMD measurements, except for total body and spine, there was a statistically significant negative effect of time (p < 0.001). An equivalency analysis showed that the treatment group was equivalent to the control group. Serum PTH and BSAP declined, with a greater decline of PTH in the treatment group. The rate of bone loss with serum 25(OH)D above 75 nmol/L is comparable to the rate of loss with serum 25(OH)D at the Recommended Dietary Allowance (RDA) of 50 nmol/L. Black Americans should have the same exposure to vitamin D as white Americans. © 2018 American Society for Bone and Mineral Research. © 2018 American Society for Bone and Mineral Research
Keywords: ANALYSIS/QUANTITATION OF BONE; BIOCHEMICAL MARKERS OF BONE TURNOVER; BONE MODELING AND REMODELING; CELL/TISSUE SIGNALING; CLINICAL TRIALS; DISEASES AND DISORDERS OF/RELATED TO BONE; DXA; ENDOCRINE PATHWAYS; OSTEOPOROSIS; PTH/VIT D/FGF23

A randomized phase II trial of MOVING ON: An intervention to increase exercise outcome expectations among breast cancer survivors - Hirschey, R.; Kimmick, G.; Hockenberry, M.; Shaw, R.; Pan, W.; Page, C.; Lipkus, I. (Psycho-Oncology, 2018)
Objective: The objective of the study is to test theoretical intervention fidelity and feasibility of MOVING ON, a self-directed, home-based, randomized controlled trial to increase exercise outcome expectations (OEs) (what one expects to obtain or avoid as a result of a behavior or lack thereof), among breast cancer survivors. Method: Stage Ia to IIb survivors (n = 60) were given the MOVING ON intervention or control booklet. Data were collected through online surveys and an accelerometer at baseline, 4, 8, and 12 weeks postintervention. Fidelity was measured by questions assessing participant perceptions of MOVING ON (score ≥2) and direction of intervention effects. Feasibility was measured by recruitment rate (target of 60 participants in 6 months), retention (total attrition <17%), and acquisition of accelerometer data (% ≥subjective exercise data obtained). Analyses consisted of descriptive statistics, mixed models, and content analysis. Results: Fidelity met a priori criteria (mean = 3.31, SD = 0.87). Outcome expectations increased 0.01 points, and weekly steps increased by 970 every 4 weeks in the intervention arm compared to the control arm. All effect sizes were small, ranging from 0.01 to 0.09. Target enrollment, achieved in 17 weeks, met a priori feasibility criteria. Retention (66%) and accelerometer data acquisition (60%) (compared to 73% of subjective exercise data) did not. Conclusion: MOVING ON influenced OEs as intended and was well received by participants. A fully powered study, of this low-cost, easy-to-implement intervention, is warranted. Intervention and measurement strategies used in MOVING ON can be incorporated in any study targeting OEs as a mediator of exercise or collecting exercise data with an accelerometer. © 2018 John Wiley & Sons, Ltd.
Keywords: behavior change; breast cancer; cancer; cancer survivor; exercise; outcome expectations; physical activity; survivorship

At What Cost to Clinical Trial Enrollment? A Retrospective Study of Patient Travel Burden in Cancer Clinical Trials - Borno, H.T.; Zhang, L.; Siegel, A.; Chang, E.; Ryan, C.J. (Oncologist, 2018)
Background: Recent literature suggests that living in a rural setting may be associated with adverse cancer outcomes. This study examines the burden of travel from home to cancer center for clinical trial (CT) enrollees. Materials and Methods: Patients from the University of California San Francisco Clinical Trial Management System database who enrolled in a cancer CT for a breast, genitourinary, or gastrointestinal malignancy between 1993 and 2014 were included. Cancer type, household zip code, race/ethnicity, phase of study, study sponsor, and year of signed consent were exported. Distance traveled from home to center was calculated using a GoogleMaps application programming interface. The relationships of distance with phase of CT, household income, and race/ethnicity were examined. Results: A total of 1,600 patients were enrolled in breast (55.8%), genitourinary (29.4%), or gastrointestinal (14.9%) cancer CTs. The overall median unidirectional distance traveled from home to study site was 25.8 miles (interquartile range [IQR] 11.5–75.3). Of the trial sponsors examined, principal investigator (56.4%), industry (22.2%), cooperative group (11.6%), and National Institutes of Health (NIH; 9.8%), the longest distance traveled was for NIH-sponsored trials, with a median of 39.4 miles (p <.001). Phase I (8.4%) studies had the longest distance traveled, with a median of 41.2 miles (IQR 14.5–101.0 miles; p =.001). White patients (83%) traveled longer compared with black patients (4.4%), with median distances of 29.9 and 13.9 miles, respectively (p <.001). Patients from lower-income areas (n = 799) traveled longer distances compared with patients from higher-income areas (n = 773; 58.3 vs. 17.8 miles, respectively; p <.001). A multivariable linear model where log10 (distance) was the outcome and adjusting for the exported variables and income revealed that cancer type, year of consent, race/ethnicity, and income were significantly associated with distance traveled. Conclusion: This study found that the burden of travel is highest among patients enrolled in NIH-sponsored trials, phase I studies, or living in low-income areas. These data suggest that travel burden for cancer CT participants may be significant. Implications for Practice: This study is one of the first to measure travel distance for patients in cancer clinical trials using a real-world GoogleMaps calculator. Out-of-pocket expenses such as travel are not typically covered by health care payers; therefore, patients may face considerable cost to attend each study visit. Using a single-center clinical trials enrollment database, this study found that the burden of travel is highest for patients enrolled in National Institutes of Health-sponsored trials and phase I studies, as well as for patients living in low-income areas. Results suggest that a significant proportion of patients enrolled in clinical trials face a substantial travel burden. © AlphaMed Press 2018
Keywords: Cancer clinical trial disparities; Health care costs; Recruitment science; Representativeness in clinical trials; Travel distance

Representation of Minorities and Elderly Patients in Multiple Myeloma Clinical Trials - Duma, N.; Azam, T.; Riaz, I.B.; Gonzalez-Velez, M.; Ailawadhi, S.; Go, R. (Oncologist, 2018)
Multiple myeloma (MM) occurs in all races, but the incidence in non-Hispanic black patients (NHBs) is two to three times higher than in non-Hispanic white patients (NHWs). We determined the representation of minorities and elderly patients in MM clinical trials. Enrollment data from all therapeutic trials reported in ClinicalTrials.gov from 2000 to 2016 were analyzed. Enrollment fraction (EF) was defined as the number of trial enrollees divided by the 2014 MM prevalence. Participation in MM clinical trials varied significantly across racial and ethnic groups; NHWs were more likely to be enrolled in clinical trials (EF 0.18%) than NHBs (EF 0.06%, p <.0001) and Hispanic patients (EF 0.04%, p <.0001). The median age of trial participants was 62 years, with 7,956 participants (66%) being less than 65 years of age. Collaborations between investigators, sponsors, and the community are necessary to increase access to clinical trials to our minority and elderly patients. © AlphaMed Press 2018
Keywords: Clinical trials; Elderly; Hematologic malignancies; Minorities; Multiple myeloma

Establishment of the Alabama Hereditary Cancer Cohort - strategies for the inclusion of underrepresented populations in cancer genetics research - Bishop, M.R.; Shah, A.; Shively, M.; Huskey, A.L.W.; Omeler, S.M.; Bilgili, E.P.; Jackson, E.; Daniell, K.; Stallworth, E.; Spina, S.; Shepp, K.; Bergstresser, S.; et al. (Molecular Genetics and Genomic Medicine, 2018)
Background: Historically, groups that are most susceptible to health and healthcare disparities have been underrepresented in medical research. It is imperative to explore approaches that can facilitate the recruitment of underrepresented individuals into research studies. Methods: Two approaches, hospital and community-based recruitment (CBR), were developed and implemented over 36 months to study the genetics of hereditary breast cancer and associated cancers in Alabama, a medically underserved state with double the national percentage of self-identifying African Americans, establishing the Alabama Hereditary Cancer Cohort. Results: Overall, 242 individuals enrolled. This included 84 cancer probands through hospital recruitment, as well as 76 probands and 82 family members through CBR. Eighty-one percent of the study participants’ counties of residence are completely medically underserved. Furthermore, African Americans represent 26% of the hospital probands compared to 49% and 70% of the probands and family members who, respectively, enrolled through CBR. Conclusion: Although both recruitment mechanisms were instrumental, the unique trust building, educational, and traveling components of CBR facilitated the enrollment of African Americans resulting in large families for genetic analyses. The ultimate goal is to gain insight from these rudimentary efforts in order to expand recruitment and accrue a unique resource for cancer genetics research. © 2018 The Authors. Molecular Genetics & Genomic Medicine published by Wiley Periodicals, Inc.
Keywords: African American; biobank; hereditary breast cancer; recruitment; underrepresented individuals

Geographic Distribution and Survival Outcomes for Rural Patients With Cancer Treated in Clinical Trials - Unger, J.M.; Moseley, A.; Symington, B.; Chavez-MacGregor, M.; Ramsey, S.D.; Hershman, D.L. (JAMA network open, 2018)
Importance: Studies showing that patients with cancer from rural areas have worse outcomes than their urban counterparts have relied on cancer population data and did not account for differences in access to care. Clinical trial patients receive protocol-directed care by design, so large clinical trial databases are ideal for examining the impact of rural vs urban residency on outcomes. Objective: To compare the geographic distribution and survival outcomes for rural vs urban patients with cancer treated in clinical trials. Design, Setting, and Participants: In this comparative effectiveness retrospective cohort analysis, 36 995 patients from all 50 states enrolled in 44 phase 3 and phase 2/3 SWOG (formerly the Southwest Oncology Group) treatment trials from January 1, 1986, to December 31, 2012, were examined. Seventeen different cancer-specific analysis cohorts were constructed. Data through January 30, 2018, were analyzed. Main Outcomes and Measures: Rural vs urban residency was defined using the Rural-Urban Continuum Codes developed by the US Department of Agriculture. Multivariate Cox regression was used to estimate the association of residency with overall survival, progression-free survival, and cancer-specific survival, controlling for major disease-specific prognostic factors and demographic variables and stratifying by study. Different definitions of rurality were examined. The distribution of rural vs urban patients by geographic region was described. Results: Overall, 27.7% of patients were 65 years or older (range across 17 cohort analyses, 7.8%-74.5%), 40.3% were female in the non-sex-specific analyses (range across 17 cohort analyses, 28.1%-45.9%), and 10.8% were black (range across 17 cohort analyses, 1.9%-22.4%). Overall, 19.4% of patients (7184 of 36 995) were from rural locations. Rural patients were more likely to be aged 65 years or older (rural, 30.7% aged ≥65 years vs urban, 27.0% aged ≥65 years; difference, 3.7%; 95% CI, 2.5%-4.9%; P < .001), were less likely to be black (rural, 5.4% vs urban, 12.1%; difference, 6.7%; 95% CI, 6.1%-7.3%; P < .001), were similar with respect to sex (rural, 40.4% female vs urban, 39.7% female; difference, 0.6%; 95% CI, -1.4% to 2.6%; P = .53), and were well represented within major US geographic regions (West, Midwest, South, and Northeast). Clinical prognostic factors were similar. In multivariable regression, rural patients with adjuvant-stage estrogen receptor-negative and progesterone receptor-negative breast cancer had worse overall survival (hazard ratio, 1.27; 95% CI, 1.06-1.51; P = .008) and cancer-specific survival (hazard ratio, 1.26; 95% CI, 1.04-1.52; P = .02). No other statistically significant differences for overall, progression-free, or cancer-specific survival were found. Results were consistent regardless of the definition of rurality. Conclusions and Relevance: Rural and urban patients with uniform access to cancer care through participation in a SWOG clinical trial had similar outcomes. This finding suggests that improving access to uniform treatment strategies for patients with cancer may help resolve the disparity in cancer outcomes between rural and urban patients.

Association of anthropometric measures with prostate cancer among African American men in the NCI-Maryland prostate cancer case-control study - Pichardo, M.S.; Smith, C.J.; Dorsey, T.H.; Loffredo, C.A.; Ambs, S. (Cancer Epidemiology Biomarkers and Prevention, 2018)
Background: Obesity is a cancer risk factor. Although it does not increase the risk of localized prostate cancer, it raises the risk of the aggressive disease in men of European ancestry. Few studies investigated obesity as a prostate cancer risk factor in men of African ancestry. Findings from those studies were heterogeneous, but some reported an association of excess body fatness with aggressive disease. Methods: We examined the relationship of body mass index (BMI), waist circumference, and waist–hip ratio with prostate cancer in African American (AA) and European American (EA) men in the NCI-Maryland Prostate Cancer Case-Control Study consisting of 798 men with incident prostate cancer (402 AA and 496 EA) and 1,008 population-based controls (474 AA and 534 EA). BMI was self-reported. Waist circumference and waist–hip ratio were calculated from measurements at enrollment. Results: A high BMI either at enrollment or years prior to it was associated with a decreased risk of prostate cancer in AA men. In contrast, an elevated BMI tended to increase the disease risk in EA men. Waist circumference was inversely associated with prostate cancer in both AA and EA men, whereas a high waist–hip ratio did not associate with prostate cancer in AA men but tended to be associated with advanced/aggressive disease in EA men. Conclusions: Our findings reveal an obesity paradox among AA men in this study population, where a high BMI and waist circumference associated with a decreased disease risk. Impact: Our observations expand the knowledge of how obesity may affect prostate cancer risks in AAs. © 2018 American Association for Cancer Research.

An estrogen-related lifestyle score is associated with risk of postmenopausal breast cancer in the PLCO cohort - Guinter, M.A.; McLain, A.C.; Merchant, A.T.; Sandler, D.P.; Steck, S.E. (Breast Cancer Research and Treatment, 2018)
Purpose: Healthy or unhealthy lifestyle behaviors are often adopted together. We aimed to investigate the combined effect of estrogen-related lifestyle factors on postmenopausal breast cancer risk. Methods: Data from 27,153 women enrolled in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial were used. We created an estrogen-related lifestyle score (ERLS) by incorporating a previously developed measure of estrogenic diet, alcohol intake, body mass index (BMI), and physical activity. The scores ranged from 0 to 6 with alcohol and BMI accounting for higher weights than the other factors. To evaluate the preventive possibilities of a low estrogen-related lifestyle and to be consistent with other published lifestyle scores, higher scores were set to correspond with potentially lower estrogenic lifestyle. The association between the ERLS and incident breast cancer was examined using Cox proportional hazards models. Results: Participants with an ERLS of 4 or ≥ 5 had a 23% (HR 0.77; 95% CI 0.67–0.89) and 34% (HR 0.66; 95% CI 0.56–0.78) lower risk of breast cancer, respectively, compared to those with an ERLS ≤ 2 after multivariable adjustment. Estimates were similar when restricting to invasive cases or estrogen receptor-positive subtypes. No single lifestyle component appeared to drive the association. Conclusions: Our findings suggest that the combined effect of a lifestyle characterized by a low estrogenic diet, low alcohol consumption, low body weight, and high levels of physical activity are associated with a reduction in postmenopausal breast cancer risk, possibly through an influence on estrogen metabolism. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Behavior; Breast cancer; Epidemiology; Estrogen metabolism; Lifestyle score; Prospective cohort study

Effect of exercise on metabolic syndrome in black women by family history and predicted risk of breast cancer: The FIERCE Study - Dash, C.; Taylor, T.R.; Makambi, K.H.; Hicks, J.; Hagberg, J.M.; Adams-Campbell, L.L. (Cancer, 2018)
Background: This study examined the effects of supervised and home-based exercise interventions on changes in metabolic syndrome (MetS) according to breast cancer risk (high vs low) in black women enrolled in the Focused Intervention on Exercise to Reduce Cancer (FIERCE) trial. Methods: Postmenopausal, obese, metabolically unhealthy black women, 45 to 65 years old, were randomized to supervised aerobic exercise (73 women), home-based walking-based exercise (69 women), or a control arm (71 women). Participants in the exercise arms underwent a 6-month intervention with study assessments conducted at the baseline and 6 months. The primary outcome measure was MetS (fasting glucose, waist circumference, blood pressure, serum triglycerides, and high-density lipoprotein [HDL]). The intervention effects on MetS, stratified by breast cancer risk as measured by the family history of breast cancer and model-based projected breast cancer risk, were examined with intent-to-treat analyses using generalized estimating equation models. Results: Among women with a family history of breast cancer, the exercise arms had lower mean MetS z scores, which suggested an improvement in the metabolic profile, than controls at 6 months (controls, + 0.55; home-based arm, –0.97, P <.01; supervised arm, –0.89, P <.01). Stratified analyses by projected breast cancer risk suggested similar but statistically nonsignificant findings, with those at high risk having more favorable changes in the MetS z score in the exercise arms versus the control arm. These changes were primarily attributable to changes in blood pressure, triglycerides, and HDL. Conclusions: Short-term aerobic activity regimens may improve the metabolic profile and thereby reduce breast cancer risk in obese, metabolically unhealthy black women at high risk for cancer. © 2018 American Cancer Society. © 2018 American Cancer Society
Keywords: black; breast cancer; clinical trial; exercise; metabolic syndrome

Race-, Age-, and Gender-Based Characteristics and Toxicities of Targeted Therapies on Phase i Trials - Owonikoko, T.K.; Busari, A.K.; Kim, S.; Chen, Z.; Akintayo, A.; Lewis, C.; Carthon, B.C.; Alese, O.B.; El-Rayes, B.F.; Ramalingam, S.S.; Harvey, R.D. (Oncology (Switzerland), 2018)
Background: The impact of age-, gender-, and race-based differences on safety and efficacy in phase I clinical trials has not been well studied. Methods: We analyzed data from phase I clinical trials evaluating targeted biologic agents in patients with advanced solid malignancies. Race and gender distribution of enrolled patients was compared to the referral population demographics at the city, metro, and state levels. The association between age, gender, and race with type, frequency, and severity of treatment-emergent toxicities and clinical benefit was assessed using univariate and multivariable models. Results: Data from 117 eligible patients - Blacks/Caucasians/Others (27/85/5); male/female (66/51) - were obtained. Blacks were younger than Caucasian patients (median age of 56 vs. 62 years, p = 0.004). Nausea/vomiting was more frequent in female patients (43 vs. 24%, p = 0.03), while hematologic toxicity was more likely in Whites. While median time on treatment was comparable (113 vs. 91; p = 0.840), the median overall survival was significantly shorter for Blacks versus Caucasians (7.4 vs. 11.4 months; p = 0.0227). Black race (HR 2.11; 95% CI 1.24-3.60; p = 0.006) and older age (HR 1.03; 95% CI 1.00-1.06; p = 0.029) were associated with an increased risk of death. Conclusions: Age-, gender-, and race-based disparities were observed with specific toxicity and survival outcomes on phase I clinical trials of anticancer agents. © 2018 S. Karger AG, Basel. Copyright: All rights reserved.
Keywords: Gender; Phase I study; Race; Targeted therapy; Tolerability; Toxicity

Age of Menarche in a Longitudinal US Cohort - Biro, F.M.; Pajak, A.; Wolff, M.S.; Pinney, S.M.; Windham, G.C.; Galvez, M.P.; Greenspan, L.C.; Kushi, L.H.; Teitelbaum, S.L. (Journal of Pediatric and Adolescent Gynecology, 2018)
Study Objective: Menarche is a critical milestone in a woman's life, and historically has been determined using several approaches. The goals of this study were to: (1) determine age at menarche from multiple reports of parents and adolescent participants in a prospective study; (2) examine factors affecting age at menarche; and (3) determine correlates of menarche and pubertal tempo. Design: Longitudinal observational study. Setting: Three sites of the Breast Cancer and the Environment Research Program. Participants: Girls enrolled at 6-8 years of age. Interventions and Main Outcome Measures: Parental and participant reported age of menarche, and tempo of puberty. Results: There were 946 girls who were assigned an age of menarche. The correlation between parent and participant reports was high (Spearman R = 0.799, P <.001), and the difference was insignificant. Median age at menarche overall was 12.25 years. Compared with black participants, Hispanic girls were more likely to have menarche earlier, whereas white and Asian girls were more likely to have menarche later. Age of menarche was highly correlated with age of breast development (Spearman R = 0.547; P <.001), and inversely with body mass index (Spearman R = −0.403; P <.001). Tempo (interval of age of breast development to menarche) was slower in those with earlier breast development. Conclusion: Parental and adolescent reports of menarche are highly correlated. Earlier breast maturation was associated with slower tempo through puberty. Body mass index had a greater effect on age at menarche than did race and ethnicity. © 2018 North American Society for Pediatric and Adolescent Gynecology
Keywords: Breast development; Menarche; Pubertal tempo; Puberty

The IMAAGEN Study: Effect of Abiraterone Acetate and Prednisone on Prostate Specific Antigen and Radiographic Disease Progression in Patients with Nonmetastatic Castration Resistant Prostate Cancer - Ryan, C.J.; Crawford, E.D.; Shore, N.D.; Underwood, W., III; Taplin, M.-E.; Londhe, A.; Francis, P.S.J.; Phillips, J.; McGowan, T.; Kantoff, P.W. (Journal of Urology, 2018)
Purpose: We evaluated the use of abiraterone acetate (1,000 mg) plus prednisone (5 mg) in patients with high risk, nonmetastatic, castration resistant prostate cancer. Materials and Methods: Patients considered at high risk for progression to metastatic disease (prostate specific antigen 10 ng/ml or greater, or prostate specific antigen doubling time 10 months or less) received abiraterone acetate plus prednisone daily in 28-day cycles. The primary study end point was the proportion of patients in whom a 50% or greater prostate specific antigen reduction was achieved during cycles 1 to 6. Secondary end points included time to prostate specific antigen progression, time to radiographic evidence of disease progression and safety. Results: Of the 131 enrolled patients 44 (34%) remained on treatment with a median followup of 40.0 months. Median age was 72 years (range 48 to 90). Of the patients 82.4% were white and 14.5% were black. Median screening prostate specific antigen was 11.9 ng/dl and median prostate specific antigen doubling time was 3.4 months. Prostate specific antigen was significantly reduced (p <0.0001) with a 50% or greater prostate specific antigen reduction in 86.9% of cases and a 90% or greater reduction in 59.8%. Median time to prostate specific antigen progression was 28.7 months (95% CI 21.2–38.2). Median time to radiographic evidence of disease progression was not reached but on sensitivity analysis in 15 patients it was estimated to be 41.4 months (95% CI 27.6–not estimable). Baseline testosterone 12.5 ng/dl or greater and a 90% or greater prostate specific antigen reduction at cycle 3 were associated with longer time to prostate specific antigen progression and radiographic evidence of disease progression. Outcomes in black patients were similar to those in other patients. Adverse events, grade 3 or greater adverse events and serious adverse events were reported in 96.2%, 61.1% and 43.5% of patients, respectively. Conclusions: In patients with high risk, nonmetastatic, castration resistant prostate cancer treatment with abiraterone acetate plus prednisone demonstrated a significant 50% or greater prostate specific antigen reduction with encouraging results for the secondary end points, including the safety of 5 mg prednisone. © 2018 American Urological Association Education and Research, Inc.
Keywords: abiraterone acetate; adverse events; prednisone; prostate-specific antigen; prostatic neoplasms

Disease and outcome disparities in multiple myeloma: Exploring the role of race/ethnicity in the Cooperative Group clinical trials - Ailawadhi, S.; Jacobus, S.; Sexton, R.; Stewart, A.K.; Dispenzieri, A.; Hussein, M.A.; Zonder, J.A.; Crowley, J.; Hoering, A.; Barlogie, B.; Orlowski, R.Z.; Rajkumar, S.V. (Blood Cancer Journal, 2018)
Multiple myeloma (MM) is an incurable hematologic malignancy with disparities in outcomes noted among racial-ethnic subgroups, likely due to disparities in access to effective treatment modalities. Clinical trials can provide access to evidence-based medicine but representation of minorities on therapeutic clinical trials has been dismal. We evaluated the impact of patient race-ethnicity in pooled data from nine large national cooperative group clinical trials in newly diagnosed MM. Among 2896 patients enrolled over more than two decades, only 18% were non-White and enrollment of minorities actually decreased in most recent years (2002-2011). African-Americans were younger and had more frequent poor-risk markers, including anemia and increased lactate dehydrogenase. Hispanics had the smallest proportion of patients on trials utilizing novel therapeutic agents. While adverse demographic (increased age) and clinical (performance status, stage, anemia, kidney dysfunction) factors were associated with inferior survival, patient race-ethnicity did not have an effect on objective response rates, progression-free, or overall survival. While there are significant disparities in MM incidence and outcomes among patients of different racial-ethnic groups, this disparity seems to be mitigated by access to appropriate therapeutic options, for example, as offered by clinical trials. Improved minority accrual in therapeutic clinical trials needs to be a priority. © 2018 The Author(s).

Modelling attrition and nonparticipation in a longitudinal study of prostate cancer - Spiers, S.; Oral, E.; Fontham, E.T.H.; Peters, E.S.; Mohler, J.L.; Bensen, J.T.; Brennan, C.S. (BMC Medical Research Methodology, 2018)
Background: Attrition occurs when a participant fails to respond to one or more study waves. The accumulation of attrition over several waves can lower the sample size and power and create a final sample that could differ in characteristics than those who drop out. The main reason to conduct a longitudinal study is to analyze repeated measures; research subjects who drop out cannot be replaced easily. Our group recently investigated factors affecting nonparticipation (refusal) in the first wave of a population-based study of prostate cancer. In this study we assess factors affecting attrition in the second wave of the same study. We compare factors affecting nonparticipation in the second wave to the ones affecting nonparticipation in the first wave. Methods: Information available on participants in the first wave was used to model attrition. Different sources of attrition were investigated separately. The overall and race-stratified factors affecting attrition were assessed. Kaplan-Meier survival curve estimates were calculated to assess the impact of follow-up time on participation. Results: High cancer aggressiveness was the main predictor of attrition due to death or frailty. Higher Charlson Comorbidity Index increased the odds of attrition due to death or frailty only in African Americans (AAs). Young age at diagnosis for AAs and low income for European Americans (EAs) were predictors for attrition due to lost to follow-up. High cancer aggressiveness for AAs, low income for EAs, and lower patient provider communication scores for EAs were predictors for attrition due to refusal. These predictors of nonparticipation were not the same as those in wave 1. For short follow-up time, the participation probability of EAs was higher than that of AAs. Conclusions: Predictors of attrition can vary depending on the attrition source. Examining overall attrition (combining all sources of attrition under one category) instead of distinguishing among its different sources should be avoided. The factors affecting attrition in one wave can be different in a later wave and should be studied separately. © 2018 The Author(s).
Keywords: Attrition; Longitudinal study; Nonresponse bias; Prostate cancer; Unit nonresponse

Association of externalizing religious and spiritual beliefs on stage of colon cancer diagnosis among black and white multicenter urban patient populations - Polite, B.N.; Cipriano-Steffens, T.M.; Hlubocky, F.J.; Jean-Pierre, P.; Cheng, Y.; Brewer, K.C.; Rauscher, G.H.; Fitchett, G.A. (Cancer, 2018)
BACKGROUND: This study explores whether externalizing religious and spiritual beliefs is associated with advanced-stage colon cancer at initial oncology presentation and whether this association is stronger for blacks than for whites. METHODS: Patients who had newly diagnosed, invasive colon cancer were recruited at 9 sites in the Chicago metropolitan area. Eligible patients were non-Hispanic white or black, ages 30 to 79 years, and diagnosed with a primary invasive colon cancer. Patients were interviewed on prior screening and diagnosis. Social and attitudinal constructs were measured, including the God Locus of Health Control (GLHC) and Religious Problem Solving. The final response rate was 52% and included 407 patients. RESULTS: The median age was 59 years (range, 30-79 years), and 51% of participants were black. Cancer stage was available for 389 (96%) patients and was divided between late stage (stages III-IV; 60%) and early stage (stages I-II; 40%). Multivariate analysis indicated that patients in the highest tertile of scores on the GLHC were more likely have an advanced stage of disease at presentation (odds ratio, 2.14; 95% confidence interval, 1.00-4.59; P =.05) compared with those in the lowest tertile. No significant interaction was identified between race and GLHC scores for stage at presentation (P =.78). CONCLUSIONS: In a large sample of black and white individuals across diverse health care systems, higher scores on the GLHC predicted late disease stage at presentation. Although blacks had significantly higher GLHC scores, race was not associated with stage at presentation, nor was the association between GLHC and stage limited to blacks. Further work is needed to better understand this association and to develop interventions to better connect the religious and health care spheres. Cancer 2018;124:2578-87. © 2018 American Cancer Society. © 2018 American Cancer Society
Keywords: African Americans; colonic neoplasms; health care disparities; minority health; religion; spirituality

A Multi-Institutional Prospective Trial Confirms Noninvasive Blood Test Maintains Predictive Value in African American Men - Punnen, S.; Freedland, S.J.; Polascik, T.J.; Loeb, S.; Risk, M.C.; Savage, S.; Mathur, S.C.; Uchio, E.; Dong, Y.; Silberstein, J.L. (Journal of Urology, 2018)
Purpose: The 4Kscore® test accurately detects aggressive prostate cancer and reduces unnecessary biopsies. However, its performance in African American men has been unknown. We assessed test performance in a cohort of men with a large African American representation. Materials and Methods: Men referred for prostate biopsy at 8 Veterans Affairs medical centers were prospectively enrolled in the study. All men underwent phlebotomy for 4Kscore test assessment prior to prostate biopsy. The primary outcome was the detection of Grade Group 2 or higher cancer on biopsy. We assessed the discrimination, calibration and clinical usefulness of 4Kscore to predict Grade Group 2 or higher prostate cancer and compared it to a base model consisting of age, digital rectal examination and prostate specific antigen. Additionally, we compared test performance in African American and nonAfrican American men. Results: Of the 366 enrolled men 205 (56%) were African American and 131 (36%) had Grade Group 2 or higher prostate cancer. The 4Kscore test showed better discrimination (AUC 0.81 vs 0.74, p <0.01) and higher clinical usefulness on decision curve analysis than the base model. Test prediction closely approximated the observed risk of Grade Group 2 or higher prostate cancer. There was no difference in test performance in African American and nonAfrican American men (0.80 vs 0.84, p = 0.32), The test outperformed the base model in each group. Conclusions: The 4Kscore test accurately predicts aggressive prostate cancer for biopsy decision making in African American and nonAfrican American men. © 2018 American Urological Association Education and Research, Inc.
Keywords: African Americans; biomarkers; kallikreins; neoplasm grading; prostatic neoplasms; tumor

PALINA: A phase II safety study of palbociclib in combination with letrozole or fulvestrant in African American women with hormone receptor positive HER2 negative advanced breast cancer - Lynce, F.; Saleh, M.; Shajahan-Haq, A.; Gallagher, C.; Dilawari, A.; Hahn, O.; Abu-Khalaf, M.; Cai, L.; Pohlmann, P.; Mohebtash, M.; Kamugisha, L.; Isaacs, C. (Contemporary Clinical Trials Communications, 2018)
Palbociclib has been shown to be a highly effective therapy in hormone receptor positive metastatic breast cancer when used in combination with letrozole or fulvestrant. Grade 3/4 neutropenia is a common side effect although febrile neutropenia is relatively uncommon. Insufficient data exist to describe the hematological safety of palbociclib in African American women (AAW) known to have a high incidence of benign ethnic neutropenia (BEN). PALOMA 1, 2 and 3, the initial phase II/III studies that led to the U.S. Food and Drug Administration (FDA) approval of palbociclib in metastatic breast cancer, only included participants with baseline absolute neutrophil count (ANC) of 1500/mm3 or higher. African American women (AAW) were underrepresented in the PALOMA trials and this may be partially explained by strict requirements for minimal ANC ≥1500/mm3. The ANC of 1500/mm3 for initiation of treatment in those with BEN has been previously challenged. In this study, we propose to lower the ANC cutoff for enrollment to 1000/mm3. PALINA (NCT02692755) is a phase II, single arm, multicenter clinical trial that will enroll 35 patients. The primary endpoint is to assess the proportion of patients who complete therapy without the development of febrile neutropenia or treatment discontinuation due to neutropenia. The secondary endpoints include number of patients who required dose delays or dose reductions in palbociclib attributed to neutropenia, rate of grade 3/4 neutropenia, clinical benefit rate at 24 weeks, the association between metabolite and exosomal signature with disease response and the association between baseline ANC prior to cancer diagnosis and the Duffy Null polymorphism (SNP rs2814778) with hematological safety. PALINA will provide important information about the hematologic safety of palbociclib in AAW with advanced breast cancer. © 2018
Keywords: African-American; Fulvestrant; Letrozole; Palbociclib

Conducting a randomized trial in rural and urban safety-net health centers: Added value of community-based participatory research - Muthukrishnan, M.; Sutcliffe, S.; Hunleth, J.M.; Wang, J.S.; Colditz, G.A.; James, A.S. (Contemporary Clinical Trials Communications, 2018)
Background: Colorectal cancer (CRC) is the second most common cancer in the US. Despite evidence that screening reduces CRC incidence and mortality, screening rates are sub-optimal with disparities by race/ethnicity, income, and geography. Rural-urban differences in CRC screening are understudied even though approximately one-fifth of the US population lives in rural areas. This focus on urban populations limits the generalizability and dissemination potential of screening interventions. Methods: Using community-based participatory research (CBPR) principles, we designed a cluster-randomized trial, adaptable to a range of settings, including rural and urban health centers. We enrolled 483 participants across 11 health centers representing 2 separate networks. Both networks serve medically-underserved communities; however one is primarily rural and one primarily urban. Results: Our goal in this analysis is to describe baseline characteristics of participants and examine setting-level differences. CBPR was a critical for recruiting networks to the trial. Patient respondents were predominately female (61.3%), African-American (66.5%), and earned <$1200 per month (87.1%). The rural network sample was older; more likely to be female, white, disabled or retired, and have a higher income, but fewer years of education. Conclusions: Variation in the samples partly reflects the CBPR process and partly reflects inherent differences in the communities. This confirmed the importance of using CBPR when planning for eventual dissemination, as it enhanced our ability to work within diverse settings. These baseline findings indicate that using a uniform approach to implementing a trial or intervention across diverse settings might not be effective or efficient. © 2018 The Authors
Keywords: Colorectal cancer screening; Community-based participatory research; Dissemination and implementation; Health disparities; Medically underserved populations; Randomized trial

Assessing brain volume changes in older women with breast cancer receiving adjuvant chemotherapy: A brain magnetic resonance imaging pilot study - Chen, B.T.; Sethi, S.K.; Jin, T.; Patel, S.K.; Ye, N.; Sun, C.-L.; Rockne, R.C.; Haacke, E.M.; Root, J.C.; Saykin, A.J.; Ahles, T.A.; Holodny, A.I.; et al. (Breast Cancer Research, 2018)
Background: Cognitive decline is among the most feared treatment-related outcomes of older adults with cancer. The majority of older patients with breast cancer self-report cognitive problems during and after chemotherapy. Prior neuroimaging research has been performed mostly in younger patients with cancer. The purpose of this study was to evaluate longitudinal changes in brain volumes and cognition in older women with breast cancer receiving adjuvant chemotherapy. Methods: Women aged ≥ 60 years with stage I-III breast cancer receiving adjuvant chemotherapy and age-matched and sex-matched healthy controls were enrolled. All participants underwent neuropsychological testing with the US National Institutes of Health (NIH) Toolbox for Cognition and brain magnetic resonance imaging (MRI) prior to chemotherapy, and again around one month after the last infusion of chemotherapy. Brain volumes were measured using Neuroreader™ software. Longitudinal changes in brain volumes and neuropsychological scores were analyzed utilizing linear mixed models. Results: A total of 16 patients with breast cancer (mean age 67.0, SD 5.39 years) and 14 age-matched and sex-matched healthy controls (mean age 67.8, SD 5.24 years) were included: 7 patients received docetaxel and cyclophosphamide (TC) and 9 received chemotherapy regimens other than TC (non-TC). There were no significant differences in segmented brain volumes between the healthy control group and the chemotherapy group pre-chemotherapy (p > 0.05). Exploratory hypothesis generating analyses focusing on the effect of the chemotherapy regimen demonstrated that the TC group had greater volume reduction in the temporal lobe (change = - 0.26) compared to the non-TC group (change = 0.04, p for interaction = 0.02) and healthy controls (change = 0.08, p for interaction = 0.004). Similarly, the TC group had a decrease in oral reading recognition scores (change = - 6.94) compared to the non-TC group (change = - 1.21, p for interaction = 0.07) and healthy controls (change = 0.09, p for interaction = 0.02). Conclusions: There were no significant differences in segmented brain volumes between the healthy control group and the chemotherapy group; however, exploratory analyses demonstrated a reduction in both temporal lobe volume and oral reading recognition scores among patients on the TC regimen. These results suggest that different chemotherapy regimens may have differential effects on brain volume and cognition. Future, larger studies focusing on older adults with cancer on different treatment regimens are needed to confirm these findings. © 2018 The Author(s).
Keywords: Brain MRI; Brain volume; Breast cancer; Cancer-related cognitive impairment; Chemotherapy

Early-stage breast cancer and employment participation after 2 years of follow-up: A comparison with age-matched controls - Ekenga, C.C.; Pérez, M.; Margenthaler, J.A.; Jeffe, D.B. (Cancer, 2018)
BACKGROUND: Although cancer survivors are more likely to be unemployed than individuals without a cancer history, employment participation after treatment of early-stage breast cancer has not been widely studied to date. The objectives of the current study were to evaluate employment trajectories in a cohort of patients with early-stage breast cancer and age-matched controls from the time of diagnosis to the 2-year follow-up, and identify factors associated with diminished and emerging employment participation. METHODS: As part of a larger cohort study of 1096 patients with early-stage breast cancer and same-aged women without breast cancer, data from 723 working-age (aged 40-64 years) women (347 patients and 376 controls) were analyzed to evaluate 4 employment trajectories (sustained unemployment, diminished employment, emerging employment, and sustained employment). Multivariable logistic regression models were used to identify factors associated with diminished employment versus sustained employment, and emerging employment versus sustained unemployment. RESULTS: Lower percentages of patients (71%) compared with controls (79%) reported full-time or part-time employment at enrollment (P<.01). Fatigue was a significant predictor of diminished employment for both patients (odds ratio [OR], 5.71; 95% confidence interval [95% CI], 2.48-13.15) and controls (OR, 2.38; 95% CI, 1.21-4.68). Among patients, African American race (OR, 4.02; 95% CI, 1.57-10.28) and public/uninsured insurance status (OR, 4.76; 95% CI, 1.34-12.38) were found to be associated with diminished employment. Among controls, high social support was associated with emerging employment (OR, 3.12; 95% CI, 1.25-7.79). CONCLUSIONS: Fatigued patients, African American patients, and publicly insured/uninsured patients with cancer were more likely to experience diminished employment after 2 years of follow-up. Further investigation with longer follow-up is warranted to identify factors associated with these disparities in employment participation after treatment of early-stage breast cancer. Cancer 2018;124:2026-35. © 2018 American Cancer Society. © 2018 American Cancer Society
Keywords: breast cancer; employment; fatigue; return to work; survivorship

Challenges in recruiting African-American women for a breast cancer genetics study - Compadre, A.J.; Simonson, M.E.; Gray, K.; Runnells, G.; Kadlubar, S.; Zorn, K.K. (Hereditary Cancer in Clinical Practice, 2018)
Background: African-American women, especially in the southern United States, are underrepresented in cancer genetics research. A study was designed to address this issue by investigating the germline mutation rate in African-American women in Arkansas with a personal and/or family history of breast cancer. Women were tested for these mutations using a large panel of breast cancer susceptibility genes. In this analysis, we discuss the challenges encountered in recruiting African-American women from an existing biorepository to participate in this study. Methods: We attempted to contact 965 African-American women with a personal and/or family history of breast cancer who participated in Spit for the Cure (SFTC) between 2007 and 2013 and provided consent to be recontacted. The SFTC participants were invited by telephone and email to participate in the genetic study. Enrollment required completion of a phone interview to obtain a family and medical history and return of a signed consent form. Results: Among eligible SFTC participants, 39.6% (382/965) were able to be contacted with the phone numbers and email addresses they provided. Of these, 174 (45.5%) completed a phone interview and returned a signed consent form. Others were not able to be contacted (n=583), declined to participate (n=57), did not keep phone interview appointments (n=82), completed the phone interview but never returned a signed consent (n=54), were deceased (n=13), or were too confused to consent to participate (n=2). Conclusions: Recruiting African-American women into our breast cancer genetics study proved challenging primarily due to difficulty establishing contact with potential participants. Given their prior participation in breast cancer research, we anticipated that this would be a highly motivated population. Indeed, when we were able to contact SFTC participants, only 14.9% declined to participate in our study. Innovative communication, retention, and recruitment strategies are needed in future studies to address the recruitment challenges we faced. © 2018 The Author(s).
Keywords: African American; Biorepository; Hereditary breast cancer; Subject recruitment

Prevalence and Predictors of Low Serum 25-Hydroxyvitamin D among Female African-American Breast Cancer Survivors - Sheean, P.; Arroyo, C.; Woo, J.; Schiffer, L.; Stolley, M. (Journal of the Academy of Nutrition and Dietetics, 2018)
Background: African-American breast cancer survivors commonly demonstrate low serum 25-hydroxyvitamin D (25(OH)D). Decreased cutaneous conversion, high levels of adiposity, and even breast cancer treatment may influence vitamin D status. Previous investigations have analyzed African-American women in aggregate with other breast cancer survivors and have not comprehensively addressed these influential factors. Objectives: To determine the prevalence of low serum 25(OH)D in an exclusively African-American cohort of female breast cancer survivors with overweight/obesity and to evaluate the role of ultraviolet (UV) light exposure, body composition, and dietary sources of vitamin D on serum 25(OH)D levels. Design: Cross-sectional. Participants: Pre- and postmenopausal African-American breast cancer survivors (n=244) were recruited from various neighborhoods in the city of Chicago, IL, between September 2011 and September 2014 for a larger weight loss trial. Main outcome measures: Demographic, clinical, anthropometric (body mass index [calculated as kg/m2], waist circumference, and hip circumference), blood specimen, dietary intake (food frequency questionnaire), and sun behavior data were collected by trained study personnel before trial participation. Dual-energy x-ray absorptiometry was used to quantify adiposity (total, percentage, regional, visceral) and lean mass. Serum 25(OH)D was used as the biomarker reflective of vitamin D status. Statistical analyses: Mean (±standard deviation), frequencies, and multivariate linear regression modeling. Results: The average participant was 57.4 years old (±10.0), 6.9 years (±5.2) from initial breast cancer diagnosis with a body mass index of 36.2 (±6.2). The majority of participants (60%) reported habitual oral vitamin D supplementation with mean intake of 327 IU (±169). Vitamin D deficiency was prevalent in 81% and 43%, when the cut points of the Endocrine Society (<30 ng/mL or <75 nmol/L) and the Institute of Medicine (<20 ng/mL or <50 nmol/L) were applied, respectively. A multivariate model adjusting for age, seasonality of blood draw, total energy intake, use of supplemental vitamin D, darker skin pigmentation, breast cancer stage, and waist-to-hip ratio was able to explain 28.8% of the observed variance in serum 25(OH)D concentrations. No significant associations were detected for body mass index or any dual-energy x-ray absorptiometry measures of body composition. Conclusions: Considering the number of women who endorsed use of vitamin D supplementation, the prevalence of vitamin D deficiency among these African-American breast cancer survivors was high. Vitamin D supplementation, sun behavior, and waist-to-hip ratio may serve as future points of intervention to improve the vitamin D status of this minority survivor population. © 2018 Academy of Nutrition and Dietetics
Keywords: African American; Breast cancer; Obesity; Serum 25(OH)D; Vitamin D

The effect of a randomized controlled physical activity trial on health related quality of life in metabolically unhealthy African-American women: FIERCE STUDY - Taylor, T.R.; Dash, C.; Sheppard, V.; Makambi, K.; Ma, X.; Adams-Campbell, L.L. (Contemporary Clinical Trials, 2018)
Purpose: African-American women (AAW) are more likely to be metabolically unhealthy than White women (WW). Metabolic syndrome (MetS) is associated with increased breast cancer risk and mortality from breast cancer is greater in AAW compared to WW. Data show MetS affects health-related quality of life (HRQoL). Exercise studies report improvements in MetS, however, no study to date has examined HRQoL in metabolically unhealthy AAW enrolled in an exercise trial. Methods: This report examined the effect of a 6-month, 3-arm (supervised exercise, home-based exercise, control) randomized exercise controlled trial on HRQoL among 213 obese, metabolically unhealthy, postmenopausal AAW at high risk for breast cancer. Results: Certain baseline participant characteristics were related to baseline HRQoL dimensions. The “exercise group” (supervised group combined with the home-based group) showed significantly greater improvement in health change scores (M = 13.6, SD = 3.1) compared to the control group (M = 0.7, SD = 4.4) (p = 0.02) over the 6-month study period. There were no significant differences in HRQoL change scores between the 3 study groups, however, although non-significant, data indicated most HRQoL change scores were more favorable in the supervised group. Conclusion: While significant improvement occurred in health change scores in the combined supervised and home-based group compared to the control group, we did not observe any significant differences on HRQoL change scores between all three study groups. However, while non-significant, there was a trend for more favorable HRQoL change scores in the supervised group versus the home-based and control groups. Additional research is needed to further explore this topic. © 2018 Elsevier Inc.
Keywords: Blacks; Exercise; Metabolic syndrome; Quality of life; Women

Men's Eating and Living (MEAL) study (CALGB 70807 [Alliance]): recruitment feasibility and baseline demographics of a randomized trial of diet in men on active surveillance for prostate cancer - Parsons, J.K.; Pierce, J.P.; Mohler, J.; Paskett, E.; Jung, S.-H.; Morris, M.J.; Small, E.; Hahn, O.; Humphrey, P.; Taylor, J.; Marshall, J. (BJU International, 2018)
Objective: To assess the feasibility of performing national, randomized trials of dietary interventions for localized prostate cancer. Methods: The Men's Eating and Living (MEAL) study (CALGB 70807 [Alliance]) is a phase III clinical trial testing the efficacy of a high-vegetable diet to prevent progression in patients with prostate cancer on active surveillance (AS). Participants were randomized to a validated diet counselling intervention or to a control condition. Chi-squared and Kruskal–Wallis analyses were used to assess between-group differences at baseline. Results: Between 2011 and 2015, 478 (103%) of a targeted 464 patients were randomized at 91 study sites. At baseline, the mean (sd) age was 64 (6) years and mean (sd) PSA concentration was 4.9 (2.1) ng/mL. Fifty-six (12%) participants were African-American, 17 (4%) were Hispanic/Latino, and 16 (3%) were Asian-American. There were no significant between-group differences for age (P = 0.98), race/ethnicity (P = 0.52), geographic region (P = 0.60), time since prostate cancer diagnosis (P = 0.85), PSA concentration (P = 0.96), clinical stage (T1c or T2a; P = 0.27), or Gleason sum (Gleason 6 or 3+4 = 7; P = 0.76). In a pre-planned analysis, the baseline prostate biopsy samples of the first 50 participants underwent central pathology review to confirm eligibility, with an expectation that <10% would become ineligible. One of 50 participants (2%) became ineligible. Conclusion: The MEAL study shows the feasibility of implementing national, multi-institutional phase III clinical trials of diet for prostate cancer and of testing interventions to prevent disease progression in AS. © 2017 The Authors BJU International © 2017 BJU International Published by John Wiley & Sons Ltd
Keywords: #PCSM; #ProstateCancer; active surveillance; carotenoids; diet; outcomes; prevention

High baseline anal human papillomavirus and abnormal anal cytology in a phase 3 trial of the quadrivalent human papillomavirus vaccine in human immunodeficiency virus-infected individuals older than 26 years: ACTG 5298 - Cranston, R.D.; Cespedes, M.S.; Paczuski, P.; Yang, M.; Coombs, R.W.; Dragavon, J.; Saah, A.; Godfrey, C.; Webster-Cyriaque, J.Y.; Chiao, E.Y.; Bastow, B.; Wilkin, T. (Sexually Transmitted Diseases, 2018)
Background The quadrivalent human papillomavirus (HPV) vaccine (qHPV; types 6, 11, 16, 18) is indicated for men and women aged 9 to 26 years to prevent HPV associated anogenital high-grade squamous intraepithelial lesions (HSIL) and cancer. ACTG 5298 was a randomized placebo controlled Phase 3 study in human immunodeficiency virus (HIV)-infected men who have sex with men, and women of qHPV to prevent persistent anal HPV infection. Baseline data are presented here. Methods Human immunodeficiency virus-infected men who have sex with men, and women 27 years or older without previous anogenital or oral cancer were enrolled. Baseline anal cytology, high-resolution anoscopy and collection of anal, oral, and vaginal specimens for HPV genotyping were performed and acceptability assessed. Results Five hundred seventy-five (575) participants were enrolled (82% men and 18% women). Median age was 47 years. Race/ethnicity was 46% white, 31% black, and 20% Hispanic. Plasma HIV-1 RNA was less than 50 copies/mL in 83% and median CD4 T count was 602 cells/μL. Abnormal anal cytology was detected in 62%, with corresponding HSIL on biopsy (bHSIL) in 33%. Anal HPV 6, 11, 16, and 18 were detected in 25%, 13%, 32%, and 18% of the participants, respectively. Prevalence of 0, 1, 2, 3, and 4 qHPV types was 40%, 38%, 17%, 4%, and 1%, respectively. Oral infection with 1 or more qHPV type was detected in 10% of the participants. Study procedures were generally acceptable. Conclusions At study baseline, there was a high prevalence of abnormal anal cytology, bHSIL, and HPV infection. Sixty percent of the participants had anal infection with preventable qHPV types. Copyright © 2018 by the American Sexually Transmitted Diseases Association. Unauthorized reproduction of this article is prohibited.

Barriers to non-small cell lung cancer trial eligibility - Hardesty, J.J.; Kanarek, N.F. (Contemporary Clinical Trials Communications, 2018)
Introduction Cancer clinical trial (CCT) enrollment is low potentially threatening the generalizability of trial results and expedited regulatory approvals. We assessed whether type of initial patient appointment for non-small cell lung cancer (NSCLC) is associated with CCT eligibility. Methods Using a patient-to-accrual framework, we conducted a quasi-retrospective cohort pilot study at Sidney Kimmel Comprehensive Cancer Center (SKCCC), Baltimore, Maryland. 153 NSCLC patients new to SKCCC were categorized based on type of initial appointment: patients diagnosed or treated and patients seen for a consultation. CCT eligibility was determined by comparing eligibility criteria for each open trial to the electronic medical record (EMR) of each patient at every office visit occurring within 6-months of initial visit. Results We found no association between type of initial appointment and CCT eligibility (OR, 1.15; 95% CI, 0.49–2.73). Analyses did suggest current smokers were less likely to be eligible for trials compared to never smokers (OR, 0.15; 95% CI, 0.03–0.64), and stage 4 patients with second line therapy or greater were more likely to be eligible than stage 1 or 2 patients (OR, 5.18; 95% CI, 1.08–24.75). Additional analyses suggested most current smokers and stage 1 or 2 patients had trials available but were still ineligible. Conclusions SKCCC has a diverse portfolio of trials available for NSCLC patients and should consider research strategies to re-examine eligibility criteria for future trials to ensure increased enrollment of current smokers and stage 1 or 2 patients. We could not confirm whether type of initial visit was related to eligibility. © 2017
Keywords: Barriers; Eligibility; Lung cancer; Trials

Effective project management of a pan-African cancer research network: Men of African descent and carcinoma of the prostate (MadCap) - Odiaka, E.; Lounsbury, D.W.; Jalloh, M.; Adusei, B.; Diallo, T.A.; Kane, P.M.S.; Rockson, I.; Okyne, V.; Irusen, H.; Pentz, A.; Makinde, I.; Ajibola, O.H.; et al. (Journal of Global Oncology, 2018)
Purpose Health research in low- and middle-income countries can generate novel scientific knowledge and improve clinical care, fostering population health improvements to prevent premature death. Project management is a critical part of the success of this research, applying knowledge, skills, tools, and techniques to accomplish required goals. Here, we describe the development and implementation of tools to support a multifaceted study of prostate cancer in Africa, focusing on building strategic and operational capacity. Methods Applying a learning organizational framework, we developed and implemented a project management toolkit (PMT) that includes a management process flowchart, a cyclical center-specific schedule of activities, periodic reporting and communication, and center-specific monitoring and evaluation metrics. Results The PMT was successfully deployed during year one of the project with effective component implementation occurring through periodic cycles of dissemination and feedback to local center project managers. A specific evaluation was conducted 1 year after study initiation to obtain enrollment data, evaluate individual quality control management plans, and undertake risk log assessments and follow-up. Pilot data obtained identified areas in which centers required mentoring, strengthening, and capacity development. Strategies were implemented to improve project goals and operational capacity through local problem solving, conducting quality control checks and following compliancy with study aims. Moving forward, centers will perform quarterly evaluations and initiate strengthening measures as required. Conclusion The PMT has fostered the development of both strategic and operational capacity across project centers. Investment in project management resources is essential to ensuring high-quality, impactful health research in low- and middle-income countries. © 2018 by American Society of Clinical Oncology

Development, evaluation, and implementation of a pan-African cancer research network: Men of African descent and carcinoma of the prostate - Andrews, C.; Fortier, B.; Hayward, A.; Lederman, R.; Petersen, L.; McBride, J.; Petersen, D.C.; Ajayi, O.; Kachambwa, P.; Seutloali, M.; Shoko, A.; Mokhosi, M.; et al. (Journal of Global Oncology, 2018)
Purpose Cancer of the prostate (CaP) is the leading cancer among men in sub-Saharan Africa (SSA). A substantial proportion of these men with CaP are diagnosed at late (usually incurable) stages, yet little is known about the etiology of CaP in SSA. Methods We established the Men of African Descent and Carcinoma of the Prostate Network, which includes seven SSA centers partnering with five US centers to study the genetics and epidemiology of CaP in SSA. We developed common data elements and instruments, regulatory infrastructure, and biosample collection, processing, and shipping protocols. We tested this infrastructure by collecting epidemiologic, medical record, and genomic data from a total of 311 patients with CaP and 218 matched controls recruited at the seven SSA centers. We extracted genomic DNA from whole blood, buffy coat, or buccal swabs from 265 participants and shipped it to the Center for Inherited Disease Research (Baltimore, MD) and the Centre for Proteomics and Genomics Research (Cape Town, South Africa), where genotypes were generated using the UK Biobank Axiom Array. Results We used common instruments for data collection and entered data into the shared database. Double-entered data from pilot participants showed a 95% to 98% concordance rate, suggesting that data can be collected, entered, and stored with a high degree of accuracy. Genotypes were obtained from 95% of tested DNA samples (100% from blood-derived DNA samples) with high concordance across laboratories. Conclusion We provide approaches that can produce high-quality epidemiologic and genomic data in multicenter studies of cancer in SSA. © 2018 by American Society of Clinical Oncology

Sistas inspiring sistas through activity and support (SISTAS): Study design and demographics of participants - Bevel, M.; Babatunde, O.A.; Heiney, S.P.; Brandt, H.M.; Wirth, M.D.; Hurley, T.G.; Khan, S.; Johnson, H.; Wineglass, C.M.; Warren, T.Y.; Angela Murphy, E.; Sercy, E.; et al. (Ethnicity and Disease, 2018)
Introduction: Recruiting racial, ethnic, and other underserved minorities into conventional clinic-based and other trials is known to be challenging. The Sistas Inspiring Sistas Through Activity and Support (SISTAS) Program was a one-year randomized controlled trial (RCT) to promote physical activity and healthy eating among AA women in SC to reduce inflammatory biomarkers, which are linked to increased breast cancer (BrCa) risk and mortality. This study describes the development, recruitment, and implementation of the SISTAS clinical trial and provides baseline characteristics of the study participants. Methods: SISTAS was developed using community-based participatory research (CBPR) approaches. At baseline, study participants completed assessments and underwent clinical measurements and blood draws to measure C-reactive protein (CRP) and interleukin-6 (IL-6). Participants randomized to the intervention received 12 weekly classes followed by nine monthly booster sessions. Post-intervention measurements were assessed at 12-week and 12-month follow-ups. Results: We recruited a total of 337 women who tended to: be middle-aged (mean age 48.2 years); have some college education; be employed full-time; have Medicare as their primary insurance; be non-smokers; and perceive their personal health as good. On average, the women were pre-hypertensive at baseline (mean systolic blood pressure = 133.9 mm Hg; mean diastolic blood pressure = 84.0 mm Hg) and morbidly obese (mean BMI >40.0 kg/m2); the mean fat mass and fat-free mass among participants were 106.4 lb and 121.0 lb, respectively. Conclusion: The SISTAS RCT addresses some of the gaps in the literature with respect to CBPR interventions targeting AA women, such as implementing diet and physical activity in CBPR-based studies to decrease BrCa risk. © 2018 ISHIB. All rights reserved.
Keywords: African American; Breast cancer; Community-based participatory research; Diet; Physical activity

Enhancing the infrastructure of the atherosclerosis risk in Communities (ARIC) study for cancer epidemiology research: Aric cancer - Joshu, C.E.; Barber, J.R.; Coresh, J.; Couper, D.J.; Mosley, T.H.; Vitolins, M.Z.; Butler, K.R.; Nelson, H.H.; Prizment, A.E.; Selvin, E.; Tooze, J.A.; Visvanathan, K.; et al. (Cancer Epidemiology Biomarkers and Prevention, 2018)
Background: We describe the expansion of the Atherosclerosis Risk in Communities (ARIC) Study into a cancer cohort. In 1987 to 1989, ARIC recruited 15,792 participants 45 to 64 years old to be sex (55% female), race (27% black), and geographically diverse. ARIC has exceptional data collected during 6 clinical visits and calls every 6 months, repeated biospecimens, and linkage to Medicare claims data. Methods: We established a Cancer Coordinating Center to implement infrastructure activities, convened a Working Group for data use, leveraged ARIC staff and procedures, and developed protocols. We initiated a cancer-specific participant contact, added questions to existing contacts, obtained permission to collect medical records and tissue, abstracted records, linked with state cancer registries, and adjudicated cases and characterizing data. Results: Through 2012, we ascertained and characterized 4,743 incident invasive, first, and subsequent primary cancers among 4,107 participants and 1,660 cancer-related deaths. We generated a total cancer incidence and mortality analytic case file, and analytic case files for bladder, breast, colorectal, liver, lung, pancreas, and prostate cancer incidence, mortality, and case fatality. Adjudication of multiple data sources improved case records and identified cancers not identified via registries. From 2013 onward, we ascertain cases from self-report coupled with medical records. Additional cancer registry linkages are planned. Conclusions: Compared with starting a new cohort, expanding a cardiovascular cohort into ARIC Cancer was an efficient strategy. Our efforts yielded enhanced case files with 25 years of follow-up. Impact: Now that the cancer infrastructure is established, ARIC is contributing its unique features to modern cancer epidemiology research. © 2017 American Association for Cancer Research.

Designing a randomized controlled trial to evaluate a community-based narrative intervention for improving colorectal cancer screening for African Americans - Ellis, E.M.; Erwin, D.O.; Jandorf, L.; Saad-Harfouche, F.; Sriphanlop, P.; Clark, N.; Dauphin, C.; Johnson, D.; Klasko-Foster, L.B.; Martinez, C.; Sly, J.; White, D.; et al. (Contemporary Clinical Trials, 2018)
Objective To describe the methodology of a 2-arm randomized controlled trial that compared the effects of a narrative and didactic version of the Witness CARES (Community Awareness, Reach, & Empowerment for Screening) intervention on colorectal cancer screening behavior among African Americans, as well as the cognitive and affective determinants of screening. Methods Witness CARES targeted cognitive and affective predictors of screening using a culturally competent, community-based, narrative or didactic communication approach. New and existing community partners were recruited in two New York sites. Group randomization allocated programs to the narrative or didactic arm. Five phases of data collection were conducted: baseline, post-intervention, three-month, six-month, and qualitative interviews. The primary outcome was screening behavior; secondary outcomes included cognitive and affective determinants of screening. Results A total of 183 programs were conducted for 2655 attendees. Of these attendees, 19.4% (N = 516) across 158 programs (50% narrative; 50% didactic) were study-eligible and consented to participate. Half (45.6%) of the programs were delivered to new community partners and 34.8% were delivered at faith-based organizations. Mean age of the total sample was 64.7 years and 75.4% were female. Conclusion The planned number of programs was delivered, but the proportion of study-eligible attendees was lower than predicted. This community-based participatory research approach was largely successful in involving the community served in the development and implementation of the intervention and study. © 2017
Keywords: African American; Colonoscopy; Colorectal cancer screening; Community-based intervention; Randomized controlled trial; Recruitment

Biospecimen donation among black and white breast cancer survivors: opportunities to promote precision medicine - Sheppard, V.B.; Hurtado-de-Mendoza, A.; Zheng, Y.-L.; Wang, Y.; Graves, K.D.; Lobo, T.; Xu, H.; Jennings, Y.; Tolsma, D.; Trout, M.; Robinson, B.E.; McKinnon, B.; et al. (Journal of Cancer Survivorship, 2018)
Purpose: Advances in precision medicine (PM) have potential to reduce and/or eliminate breast cancer disparities in both treatment and survivorship. However, compared to white Americans, black Americans are often underrepresented in genetic research. This report assessed factors that influence receipt of buccal cells via saliva kits. Methods: This prospective study recruited women with confirmed hormonal-positive (HR+) breast cancer (BC). A standardized telephone survey collected sociodemographic, socio-cultural (e.g., religiosity), and healthcare process factors. Clinical information was abstracted from medical records. After the baseline survey, return postage-paid envelopes and mouthwash collection kits were mailed. Univariate and adjusted logistic regression models estimated the probability of biospecimen donation. Results: Seventy percent of the sample provided buccal cells which were of good quality. No differences were noted by race or other demographic factors. In the multivariable logistic model, time spent with providers (OR 1.61 per 1-point increase; 95% CI 1.242, 2.088) and religiosity (OR 0.957 per 1-point increase; 95% CI 0.931, 0.984) remained associated with biospecimen provision. Women with lower-stage cancer (vs. higher stage III+) were more likely to donate biospecimens (p < 0.05). Conclusions: Cancer care experiences predicted specimen donation. Understanding the contextual reasons for lower receipt among women with higher religiosity scores and higher stage warrants further examination. Implications for cancer survivors: PM is relevant to cancer survivors because of its potential to inform targeted therapies, understand disease resistance, and aide in prediction of toxicity and/or recurrence. Future efforts to launch precision medicine trials with BC survivors may benefit from engaging medical oncologists and/or leveraging patient-provider encounters for trial participation. © 2017, Springer Science+Business Media, LLC.
Keywords: Biospecimen; Disparities; Precision medicine; Survivors

Speed of processing training in middle-aged and older breast cancer survivors (SOAR): results of a randomized controlled pilot - Meneses, K.; Benz, R.; Bail, J.R.; Vo, J.B.; Triebel, K.; Fazeli, P.; Frank, J.; Vance, D.E. (Breast Cancer Research and Treatment, 2018)
Purpose: Cognitive changes are common among breast cancer survivors. There is limited evidence to guide management of cognitive changes. This randomized controlled pilot evaluated the preliminary efficacy of a speed of processing (SOP) training among middle-aged and older breast cancer survivors. Methods: Sixty breast cancer survivors with self-reported cognitive changes were recruited to the SOAR study. Participants were randomized to either a home-based SOP training (n = 30) or no-contact control group (n = 30). Primary outcomes were SOP (Useful Field of View Test ® ), and executive function (NIH Toolbox Cognition Battery). Neuropsychological assessments were completed at baseline, 6 weeks, and 6 months post study entry. Data were analyzed using repeated measures t tests, analysis of covariance, and sensitivity analyses. Results: SOP training resulted in improvement in objective measures of SOP and executive function. Immediate (6 week) posttest and 6-month follow-up demonstrated large SOP training effects over time. Large representation of African American women (51.2%) and 96% retention in the SOAR study add to study strengths. Conclusion: Home-based SOP training shows promise for remediating cognitive changes following breast cancer treatment, particularly improved SOP, and executive function. © 2017, The Author(s).
Keywords: Aging; Breast cancer survivors; Cognitive changes; Cognitive impairment; Speed of processing interventions

Feasibility of the mobile mindfulness-based stress reduction for breast cancer (mMBSR(BC)) program for symptom improvement among breast cancer survivors - Lengacher, C.A.; Reich, R.R.; Ramesar, S.; Alinat, C.B.; Moscoso, M.; Cousin, L.; Marino, V.R.; Elias, M.N.; Paterson, C.L.; Pleasant, M.L.; Rodriguez, C.S.; Wang, H.-L.; et al. (Psycho-Oncology, 2018)
Objective: The purpose of this pilot study was to test the feasibility of delivering the mobile mindfulness-based stress reduction for breast cancer (mMBSR(BC)) program using an iPad and to evaluate its impact on symptom improvement. Methods: A single group, pre-posttest design was implemented among female stages 0-III breast cancer survivors (BCS) who completed treatment. Data were collected at baseline and week 6 on measures of psychological and physical symptoms and quality of life. The mMBSR(BC) program is a standardized, stress-reducing intervention that combines sitting and walking meditation, body scan, and yoga and is designed to deliver weekly 2-hour sessions for 6 weeks using an iPad. Results: The mean age of the 15 enrolled BCS was 57 years; one participant was non-Hispanic black, and 14 were non-Hispanic white. Of the 13 who completed the study, there were significant improvements from baseline to 6 weeks post-mMBSR(BC) in psychological and physical symptoms of depression, state anxiety, stress, fear of recurrence, sleep quality, fatigue, and quality of life (P's <.05). Effect sizes for improvements of multiple symptoms ranged from medium to large. Conclusions: These results provide preliminary support that the mMBSR(BC) program may be feasible and acceptable, showing a clinical impact on decreasing psychological and physical symptoms. This mobile-based program offers a delivery of a standardized MBSR(BC) intervention to BCS that is convenient for their own schedule while decreasing symptom burden in the survivorship phase after treatment for breast cancer. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: breast cancer survivors; MBSR; mobile-based; quality of life; symptom managment

Strategic recruitment of an ethnically diverse cohort of overweight survivors of breast cancer with lymphedema - Sturgeon, K.M.; Hackley, R.; Fornash, A.; Dean, L.T.; Laudermilk, M.; Brown, J.C.; Sarwer, D.B.; DeMichele, A.M.; Troxel, A.B.; Schmitz, K.H. (Cancer, 2018)
BACKGROUND: Black women are more likely to experience adverse effects from cancer treatment such as lymphedema. Thus, black women may particularly benefit from research regarding interventions to improve lymphedema. Herein, the authors report the challenges and strategies related to the recruitment of minority survivors of breast cancer and to the recruitment of survivors of breast cancer with lymphedema into the Women In Steady Exercise Research (WISER) Survivor Clinical Trial. METHODS: Subjects for this community-based trial were recruited from the Philadelphia area through active (mailings) and passive (printed materials and Web site) recruitment strategies. In addition, education sessions coordinated through partner hospitals in communities with a predominantly minority population were conducted to increase awareness of lymphedema in survivors of breast cancer. Women who were interested in the study were screened for lymphedema via telephone questionnaire and invited to see a study-related certified lymphedema therapist to confirm the presence of lymphedema. RESULTS: Screening was conducted among 2295 women: 628 were eligible, 450 consented, and 351 were randomized. Minority women comprised 38% of the study population. Letters to women on state and hospital registries resulted in a 0.4% randomization rate; education sessions yielded a 10% randomization rate. The authors observed that approximately 23.6% of the study sample had no previous diagnosis of lymphedema. CONCLUSIONS: The WISER Survivor Clinical Trial faced multiple recruitment challenges and used unique strategies to successfully enroll minority survivors of breast cancer into a lifestyle intervention. Cancer 2018;124:95-104. © 2017 American Cancer Society. © 2017 American Cancer Society
Keywords: African American; body weight; breast cancer lymphedema; exercise; patient recruitment; patient selection

Genome-wide meta-analyses identifies novel taxane-induced peripheral neuropathy-associated loci - Sucheston-Campbell, L.E.; Clay-Gilmour, A.I.; Barlow, W.E.; Budd, G.T.; Stram, D.O.; Haiman, C.A.; Sheng, X.; Yan, L.; Zirpoli, G.; Yao, S.; Jiang, C.; Owzar, K.; et al. (Pharmacogenetics and Genomics, 2018)
Objective Taxane containing chemotherapy extends survival for breast cancer patients. However, taxane-induced peripheral neuropathy (TIPN) cannot be predicted, prevented or effectively treated. Using genome-wide analyses, we sought to identify common risk variants for TIPN. Patients and methods Women with high-risk breast cancer enrolled in SWOG 0221 were genotyped using the Illumina 1M chip. Genome-wide analyses were performed in relation to ≥grade 3 Common Terminology Criteria for Adverse Events (CTCAE) neuropathy in European and African Americans. Data were meta-analyzed with GW associations of CTCAE ≥grade 3 versus <grade 3 in CALGB 40101 assuming a fixed effects model. Results The percentage of ≥grade 3 TIPN in 1269 European Americans and 139 African Americans in S0221, was 11.6 and 22.3%, respectively. CALGB 40101 ≥grade 3 TOPN was 7.2%. The most significant association with ≥grade 3 TIPN was the G allele of rs1858826 in GNGT1 (P meta =1.1×10 -7), which showed a decrease in risk of ≥grade 3 TIPN (odds ratio=0.29, 95% confidence interval: 0.18-0.46). Conclusion The genetic variants associated with ≥grade 3 TIPN are hypothesized to have biochemical functions and reside in and near genes involved in diabetes and diabetic neuropathy. This finding is consistent with results from CALGB 40101 pathway analyses. Larger homogeneous trials with similar dosing and criteria for defining neuropathy are needed to properly assess the relationship of genomics with the neuropathy spectrum. © 2018 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: breast cancer; genome-wide association study; neuropathy; taxane

Patient-reported Adherence to Adjuvant Aromatase Inhibitor Therapy Using the Morisky Medication Adherence Scale: An Evaluation of Predictors - Kesmodel, S.B.; Goloubeva, O.G.; Rosenblatt, P.Y.; Heiss, B.; Bellavance, E.C.; Chumsri, S.; Bao, T.; Thompson, J.; Nightingale, G.; Tait, N.S.; Nichols, E.M.; Feigenberg, S.J.; et al. (American Journal of Clinical Oncology: Cancer Clinical Trials, 2018)
Objectives: Endocrine therapy is part of standard adjuvant therapy for patients with hormone receptor-positive breast cancer and has been shown to improve recurrence-free and overall survival. However, adherence to endocrine therapy is suboptimal and is difficult to measure. In this study we evaluate the feasibility of using the Morisky Medication Adherence Scale (MMAS) to assess patient adherence to aromatase inhibitor (AI) therapy. Methods: Patients with stage 1 to 3, hormone receptor-positive breast cancer receiving adjuvant AI therapy were prospectively enrolled on an Institutional Review Board approved protocol. The MMAS questionnaire was administered to each patient and adherence was measured. Information on duration of AI therapy, patient and tumor characteristics, and treatment was collected. A multivariable logit model approach was utilized to evaluate potential barriers to adherence. Results: Between 2011 and 2014, 100 patients were enrolled. The distribution of adherence levels was 13% low, 37% medium, and 50% high. High adherence was reported more frequently in white women (58%), patients with stage 2 and 3 disease (54%), and patients who did not receive chemotherapy (62%). Multivariable analysis demonstrated that higher adherence was more likely in white women compared with African American women (estimated odds ratio=2.8). Conclusions: Using the MMAS, only 50% of women with stage 1 to 3 breast cancer reported high adherence to AI therapy, consistent with other reports showing suboptimal adherence to adjuvant endocrine therapy. The MMAS allows for the rapid assessment of adherence to oral adjuvant endocrine therapy and is valuable in a busy clinical setting. © 2016 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: adjuvant endocrine therapy; endocrine therapy adherence; hormone receptor-positive breast cancer; measuring adherence to medication

Educational Colonoscopy Video Enhances Bowel Preparation Quality and Comprehension in an Inner City Population - Pillai, A.; Menon, R.; Oustecky, D.; Ahmad, A. (Journal of Clinical Gastroenterology, 2018)
Background: Quality of bowel preparation and patient knowledge remains a major barrier for completing colorectal cancer screening. Few studies have tested unique ways to impact patient understanding centering on interactive computer programs, pictures, and brochures. Two studies explored instructional videos but focused on patient compliance and anxiety as endpoints. Furthermore, excessive video length and content may limit their impact on a broad patient population. No study so far has studied a video's impact on preparation quality and patient understanding of the colonoscopy procedure. Methods: We conducted a single blinded prospective study of inner city patients presenting for a first time screening colonoscopy. During their initial visit patients were randomized to watch an instructional colonoscopy video or a video discussing gastroesophageal reflux disease (GERD). All patients watched a 6 minutes long video with the same spokesperson, completed a demographic questionnaire (Supplemental Digital Content 1, http://links.lww.com/JCG/A352) and were enrolled only if screened within 30 days of their visit. On the day of the colonoscopy, patients completed a 14 question quiz of their knowledge. Blinded endoscopist graded patient preparations based on the Ottawa scale. All authors had access to the study data and reviewed and approved the final manuscript. Results: Among the 104 subjects enrolled in the study, 56 were in the colonoscopy video group, 48 were in GERD video group, and 12 were excluded. Overall, 48% were male and 52% female; 90% of patients had less than a high school education, 76% were African American, and 67% used a 4 L split-dose preparation. There were no differences between either video group with regard to any of the above categories. Comparisons between the 2 groups revealed that the colonoscopy video group had significantly better Ottawa bowel preparation score (4.77 vs. 6.85; P=0.01) than the GERD video group. The colonoscopy video group also had less-inadequate repeat bowel preparations versus the GERD video group (9% vs. 23%; P<0.01). The overall score on the knowledge questionnaire (Supplemental Digital Content 1, http://links.lww.com/JCG/A352) was significantly higher in the colonoscopy video group as compared with the GERD video group (12.77 vs. 11.08; P<0.001. In all patients the overall quiz score positively correlated with preparation quality (odds ratio, 2.31; confidence interval, 1.35-3.94; P<0.001). Conclusions: Our unique population represented an overwhelmingly under-educated (85% had a high school education or less) and minority group (76% African American). They are one of the most at risk of having multiple barriers such as comprehension and reading difficulties resulting in poor preparation examinations and no shows to procedures. Our instructional video proved to be high yield in this population. The patients assigned to watch the colonoscopy video showed a significant increase in "excellent" grade adequate bowel preparation quality by >23% and a significant decrease in "inadequate" bowel preparations by almost 50%. Our study proves that an educational video can improve both comprehension with regard to all aspects of colonoscopy. ClinicalTrials.gov number, NCT02906969. © 2017 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: colonoscopy; colonoscopy preparation; comprehension; education; educational video

A 17β-estradiol-progesterone oral capsule for vasomotor symptoms in postmenopausal women a randomized controlled trial - Lobo, R.A.; Archer, D.F.; Kagan, R.; Kaunitz, A.M.; Constantine, G.D.; Pickar, J.H.; Graham, S.; Bernick, B.; Mirkin, S. (Obstetrics and Gynecology, 2018)
OBJECTIVE: To evaluate efficacy, endometrial safety, and overall safety of a single-capsule 17b-estradiol-progesterone (TX-001HR) for treating menopausal moderate-to-severe vasomotor symptoms. METHODS: REPLENISH was a phase 3, 12-month, randomized, double-blind, placebo-controlled, multicenter trial. Women (aged 40-65 years) with vasomotor symptoms and a uterus were randomized to daily estradiol (mg)-progesterone (mg) (1/100, 0.5/100, 0.5/50, or 0.25/50), and women in the vasomotor symptoms substudy (women with moderate-to-severe hot flushes [seven or greater per day or 50 or greater per week]) to those estradiol-progesterone doses or placebo. The primary safety endpoint was endometrial hyperplasia incidence at 12 months in all women (the total population), and the primary efficacy endpoints were frequency and severity changes (from daily diaries) in moderate-to-severe vasomotor symptoms with estradiol-progesterone compared with placebo at weeks 4 and 12 in the vasomotor symptoms substudy. A sample size of 250 women in each active treatment arm with two or less endometrial hyperplasia cases would result in 1% or less annual incidence (upper bound 2.5% or less, one-sided 95% CI). RESULTS: One thousand eight hundred forty-five women were enrolled and randomized from August 2013 to October 2015; 1,835 received medication (safety population); 1,255 were eligible for the endometrial safety population; 726 comprised the vasomotor symptoms substudy; their mean age and body mass index were 55 years and 27, respectively; one third were African American. No endometrial hyperplasia was found. Frequency and severity of vasomotor symptoms significantly decreased from baseline with 1 mg estradiol and 100 mg progesterone and 0.5 mg estradiol and 100 mg progesterone compared with placebo at week 4 (frequency: by 40.6 and 35.1 points [1 mg and 100 mg and 0.5 mg and 100 mg, respectively] vs 26.4 points [placebo]; severity: by 0.48 and 0.51 vs 0.34 points) and week 12 (by 55.1 and 53.7 vs 40.2; severity: by 1.12 and 0.90 vs 0.56); 0.5 mg estradiol and 50 mg progesterone improved (P,.05) frequency and severity at week 12, and 0.25 mg estradiol and 50 mg progesterone frequency but not severity at weeks 4 and 12. CONCLUSION: No endometrial hyperplasia was observed while single-capsule estradiol-progesterone provided clinically meaningfully improvements in moderate-to-severe vasomotor symptoms. This estradiol-progesterone formulation may represent a new option, using naturally occurring hormones, for the estimated millions of women using nonregulatoryapproved, compounded hormone therapy. © 2018 by the American College of Obstetricians and Gynecologists. Published by Wolters Kluwer Health, Inc. All rights reserved.

Improving the accrual of racial and ethnic minority patients in clinical trials: Time to raise the stakes - Ibraheem, A.; Polite, B. (Cancer, 2017)

African American Women’s Perspectives on Donating Healthy Breast Tissue for Research: Implications for Recruitment - Ridley-Merriweather, K.E.; Head, K.J. (Health Communication, 2017)
African American women die of breast cancer at a higher rate than any other racial group. The Komen Tissue Bank (KTB) is an ongoing clinical trial that collects healthy breast tissue from women of all racial groups to use as controls in research and represents a critical tool in efforts to treat and prevent breast cancer; however, African Americans display reticence toward donating breast tissue to the KTB. Through the lens of the Integrated Behavioral Model, this study recruited African American women to share their perspectives on donating breast tissue for research purposes. Seventy-one (N = 71) eligible Black women who were previous tissue donors to the KTB responded to an online questionnaire. Findings revealed that (a) participants had positive instrumental attitudes or reasons for donating; (b) participants felt generally supported in their decision to donate, but revealed that the lack of Black women participating in the KTB meant that they themselves were setting the norm for others; and (c) their race was an important element in their donation decision. While acknowledging the negative history of African Americans in medical research, they offered their perceptions regarding the importance of involving themselves in medical research, and suggested that health communication strategies to recruit African Americans into research should embrace race as part of the message. The findings from this study have important implications for other those who work in applied clinical settings and are interested in addressing racial disparities in medical research through more effective and targeted recruitment messaging. © 2017 Taylor & Francis Group, LLC.

Partnering around cancer clinical trials (PACCT): Study protocol for a randomized trial of a patient and physician communication intervention to increase minority accrual to prostate cancer clinical trials - Eggly, S.; Hamel, L.M.; Heath, E.; Manning, M.A.; Albrecht, T.L.; Barton, E.; Wojda, M.; Foster, T.; Carducci, M.; Lansey, D.; Wang, T.; Abdallah, R.; et al. (BMC Cancer, 2017)
Background: Cancer clinical trials are essential for testing new treatments and represent state-of-the-art cancer treatment, but only a small percentage of patients ever enroll in a trial. Under-enrollment is an even greater problem among minorities, particularly African Americans, representing a racial/ethnic disparity in cancer care. One understudied cause is patient-physician communication, which is often of poor quality during clinical interactions between African-American patients and non-African-American physicians. Partnering Around Cancer Clinical Trials (PACCT) involves a transdisciplinary theoretical model proposing that patient and physician individual attitudes and beliefs and their interpersonal communication during racially discordant clinical interactions influence outcomes related to patients' decisions to participate in a trial. The overall goal of the study is to test a multilevel intervention designed to increase rates at which African-American and White men with prostate cancer make an informed decision to participate in a clinical trial. Methods/design: Data collection will occur at two NCI-designated comprehensive cancer centers. Participants include physicians who treat men with prostate cancer and their African-American and White patients who are potentially eligible for a clinical trial. The study uses two distinct research designs to evaluate the effects of two behavioral interventions, one focused on patients and the other on physicians. The primary goal is to increase the number of patients who decide to enroll in a trial; secondary goals include increasing rates of physician trial offers, improving the quality of patient-physician communication during video recorded clinical interactions in which trials may be discussed, improving patients' understanding of trials offered, and increasing the number of patients who actually enroll. Aims are to 1) determine the independent and combined effects of the two interventions on outcomes; 2) compare the effects of the interventions on African-American versus White men; and 3) examine the extent to which patient-physician communication mediates the effect of the interventions on the outcomes. Discussion: PACCT has the potential to identify ways to increase clinical trial rates in a diverse patient population. The research can also improve access to high quality clinical care for African American men bearing the disproportionate burden of disparities in prostate and other cancers. Trial registration: Clinical Trials.gov registration number: NCT02906241(September 8, 2016). © 2017 The Author(s).
Keywords: Clinical trials; Health disparities; Patient-physician communication; Prostate cancer

Can Women Facilitate Men’s Prostate Cancer Screening Informed Decision-Making? The M-PACT Trial - Holt, C.L.; Le, D.; Slade, J.L.; Muwwakkil, B.; Saunders, D.R.; Williams, R.; Atkinson, N.L.; Naslund, M. (Journal of Health Communication, 2017)
The M-PACT study compared an all-male with a mixed-sex intervention to increase informed decision-making for prostate cancer screening among African-American men in church settings. We recruited 262 men in 18 churches randomized to the two intervention approaches. Trained and certified lay peer community health advisors in each church led a series of four men’s health workshops on informed decision-making for prostate cancer screening. African-American male workshop participants completed baseline, post-workshop, and 12-month follow-up surveys. Contrary to our expectations, including women in the workshops did not result in increased intervention efficacy for the informed decision-making outcomes as both groups showed significant improvement over time in several study outcomes including stage of decision-making for prostate cancer screening, preference for role in decision-making, prostate cancer knowledge, and self-reports of prostate specific antigen testing. Finally, men who attended multiple workshops had better informed decision-making outcomes on several indicators. The current findings suggest mixed results from including women in this men’s health educational intervention. Future work should consider optimal ways of providing family support for African-American men’s health promotion. Copyright © Taylor & Francis Group, LLC.

Comparative transcriptome profiling reveals coding and noncoding RNA differences in NSCLC from African Americans and European Americans - Mitchell, K.A.; Zingone, A.; Toulabi, L.; Boeckelman, J.; Ryan, B.M. (Clinical Cancer Research, 2017)
Purpose: To determine whether racial differences in gene and miRNA expression translates to differences in lung tumor biology with clinical relevance in African Americans (AAs) and European Americans (EAs). Experimental Design: The NCI-Maryland Case Control Study includes seven Baltimore City hospitals and is overrepresented with AA patients (∼40%). Patients that underwent curative NSCLC surgery between 1998 and 2014 were enrolled. Comparative molecular profiling used mRNA (n = 22 AAs and 19 EAs) and miRNA (n = 42 AAs and 55 EAs) expression arrays to track differences in paired fresh frozen normal tissues and lung tumor specimens from AAs and EAs. Pathway enrichment, predicted drug response, tumor microenvironment infiltration, cancer immunotherapy antigen profiling, and miRNA target enrichment were assessed. Results: AA-enriched differential gene expression was characterized by stem cell and invasion pathways. Differential gene expression in lung tumors from EAs was primarily characterized by cell proliferation pathways. Population-specific gene expression was partly driven by population-specific miRNA expression profiles. Drug susceptibility predictions revealed a strong inverse correlation between AA resistance and EA sensitivity to the same panel of drugs. Statistically significant differences in M1 and M2 macrophage infiltration were observed in AAs (P < 0.05); however, PD-L1, PD-L2 expression was similar between both. Conclusions: Comparative transcriptomic profiling revealed clear differences in lung tumor biology between AAs and EAs. Increased participation by AAs in lung cancer clinical trials are needed to integrate, and leverage, transcriptomic differences with other clinical information to maximize therapeutic benefit in both AAs and EAs. ©2017 AACR.

Comparative Effectiveness Research: The Impact of Biologic Agents in Ethnic Minorities With Metastatic Colorectal Cancer - Goel, S.; Negassa, A.; Khot, A.; Goyal, D.; Guo, S.; Nandikolla, A.; Bakirhan, K.; Polineni, R.; Shah, U.; Chaudhary, I.; Ghalib, M.H.; Rajdev, L.; et al. (Clinical Colorectal Cancer, 2017)
Micro-Abstract The survival advantage of biologic agents for patients treated for metastatic colorectal cancer was generated from trials from a predominantly white population. We carried out a comparative effectiveness research study in our center that caters to an ethnic minority population. Using a robust multi variable analysis we demonstrate that black and Hispanic patients do not enjoy a similar benefit. Background Biologic agents have improved the outcomes of patients with metastatic colorectal cancer (mCRC). However, the clinical trials included a predominately white population (85%), with Hispanic and black patients underrepresented. Thus, the real world benefit for the latter remains unknown. Comparative effectiveness research is a tool allowing for this exploration. Patients and Methods The demographic and clinical characteristics of patients treated for mCRC from 2000 to 2011 were extracted from the medical records of Montefiore Medical Center. A semiparametric accelerated failure time model was used to assess the survival differences between patients receiving chemotherapy (CT) alone versus CT plus biologic agents (CBT). Results Of the 290 patients (black, 45.9%; Hispanic, 26.2%; and white, 27.9%), 53.8% received biologic agents. The median overall survival was 15.2 months in the CT-alone group and 25.6 months in CBT group (P =.004). On univariate analysis, a lower number of metastatic sites, carcinoembryonic antigen < 41 ng/mL, and more lines of CT were associated with improved overall survival. In a propensity score-based analysis of the entire cohort, CBT offered a survival benefit compared with CT alone (increased median survival, 1.44-fold; 95% confidence interval [CI], 1.11-1.86; P =.038). The results of the subgroup analysis suggested a survival benefit for white patients (2.01; 95% CI, 1.26-3.23; P =.031) but not for Hispanic (1.42; 95% CI, 0.91-2.20; P =.370) or black (1.12; 95% CI, 0.76-1.66; P =.596) patients. Conclusion In the present cohort, CBT was associated with longer survival, with the effect mainly driven by the outcomes for white patients, with black patients not appearing to benefit. These data are provocative and warrant further confirmation. Efforts to increase ethnic minority patients' enrollment in clinical trials is required to prospectively define the benefit from novel therapies. © 2017 Elsevier Inc.
Keywords: Biologic therapy; Chemotherapy; Colorectal cancer; Comparative effectiveness research; Race

Addressing Patient Emotional and Existential Needs During Serious Illness: Results of the Outlook Randomized Controlled Trial - Steinhauser, K.E.; Alexander, S.; Olsen, M.K.; Stechuchak, K.M.; Zervakis, J.; Ammarell, N.; Byock, I.; Tulsky, J.A. (Journal of Pain and Symptom Management, 2017)
Context Few interventions exist to address patients' existential needs. Objectives Determine whether an intervention to address seriously ill patients' existential concerns improves preparation, completion (elements of quality of life [QOL] at end of life), and reduces anxiety and depression. Methods A randomized controlled trial comparing outlook intervention, relaxation meditation (RM), and usual care (UC). Measures included primary—a validated measure of QOL at the end of life and secondary—Functional Assessment of Cancer Therapy—General, anxiety (Profile of Mood States), depression (Center for Epidemiological Studies—Depression Scale), and spiritual well-being (Functional Assessment of Chronic Illness Therapy—Spiritual Well-Being). Qualitative interviews assessed outlook intervention acceptability. Enrolled patients were nonhospice eligible veterans with advanced cancer, congestive heart failure, chronic obstructive pulmonary disease, end-stage renal disease, or end-stage liver disease. Results Patients (n = 221) were randomly assigned 1:1:1 to outlook, RM, and UC. Patients were 96% males, 46% with cancer, 58.4% married, and 43.9% of African American origin. Compared with UC, outlook participants had higher preparation (a validated measure of QOL at the end of life) (mean difference 1.1; 95% CI 0.2, 2.0; P = 0.02) and mean completion (1.6; 95% CI 0.05, 3.1; P = 0.04) at the first but not second postassessment. Compared with RM, outlook participants did not show significant differences over time. Exploratory analyses indicated that in subgroups with cancer and low sense of peace, outlook participants had improved preparation at first and not second postassessment, as compared with UC (mean difference 1.4; 95% CI 0.03, 2.7; P = 0.04) (mean difference = 1.8; 95% CI 0.3, 3.3; P = 0.02), respectively. Conclusion Outlook had an impact on social well-being and preparation compared with UC. The lack of impact on anxiety and depression differs from previous results among hospice patients. Results suggest that outlook is not demonstratively effective in populations not experiencing existential or emotional distress. © 2017
Keywords: Intervention; quality of life; spirituality

Community-based, preclinical patient navigation for colorectal cancer screening among older black men recruited from barbershops: The MISTER B trial - Cole, H.; Thompson, H.S.; White, M.; Browne, R.; Trinh-Shevrin, C.; Braithwaite, S.; Fiscella, K.; Boutin-Foster, C.; Ravenell, J. (American Journal of Public Health, 2017)
Objectives. To test the effectiveness of a preclinical, telephone-based patient navigation intervention to encourage colorectal cancer (CRC) screening among older Black men. Methods. We conducted a 3-parallel-Arm, randomized trial among 731 self-identified Black men recruited at barbershops between 2010 and 2013 in New York City. Participants had to be aged 50 years or older, not be up-To-date on CRC screening, have uncontrolled high blood pressure, and have a working telephone. We randomized participants to 1 of 3 groups: (1) patient navigation by a community health worker for CRC screening (PN), (2) motivational interviewing for blood pressure control by a trained counselor (MINT), or (3) both interventions (PLUS). We assessed CRC screening completion at 6-month follow-up. Results. Intent-To-Treat analysis revealed that participants in the navigation interventions were significantly more likely than those in the MINT-only group to be screened for CRC during the 6-month study period (17.5% of participants in PN, 17.8% in PLUS, 8.4% in MINT; P < .01). Conclusions. Telephone-based preclinical patient navigation has the potential to be effective for older Black men. Our results indicate the importance of community-based health interventions forimprovinghealth among minoritymen.

Use of a 17-Gene Prognostic Assay in Contemporary Urologic Practice: Results of an Interim Analysis in an Observational Cohort - Eure, G.; Germany, R.; Given, R.; Lu, R.; Shindel, A.W.; Rothney, M.; Glowacki, R.; Henderson, J.; Richardson, T.; Goldfischer, E.; Febbo, P.G.; Denes, B.S. (Urology, 2017)
Objective To study the impact of genomic testing in shared decision making for men with clinically low-risk prostate cancer (PCa). Materials and Methods Patients with clinically low-risk PCa were enrolled in a prospective, multi-institutional study of a validated 17-gene tissue-based reverse transcription polymerase chain reaction assay (Genomic Prostate Score [GPS]). In this paper we report on outcomes in the first 297 patients enrolled in the study with valid 17-gene assay results and decision-change data. The primary end points were shared decision on initial management and persistence on active surveillance (AS) at 1 year post diagnosis. AS utilization and persistence were compared with similar end points in a group of patients who did not have genomic testing (baseline cohort). Secondary end points included perceived utility of the assay and patient decisional conflict before and after testing. Results One-year results were available on 258 patients. Shift between initial recommendation and shared decision occurred in 23% of patients. Utilization of AS was higher in the GPS-tested cohort than in the untested baseline cohort (62% vs 40%). The proportion of men who selected and persisted on AS at 1 year was 55% and 34% in the GPS and baseline cohorts, respectively. Physicians reported that GPS was useful in 90% of cases. Mean decisional conflict scores declined in patients after GPS testing. Conclusion Patients who received GPS testing were more likely to select and persist on AS for initial management compared with a matched baseline group. These data indicate that GPS help guide shared decisions in clinically low-risk PCa. © 2017 The Authors

Comparing Asian American Women's Knowledge, Self-Efficacy, and Perceived Risk of Heart Attack to Other Racial and Ethnic Groups: The mPED Trial - Fukuoka, Y.; Lisha, N.E.; Vittinghoff, E. (Journal of women's health (2002), 2017)
RESULTS: Asian/Pacific Islander women had significantly lower total scores for knowledge of heart attack and self-efficacy for heart attack recognition and care seeking behavior compared to the Caucasian women (p = 0.001 and p = 0.002, respectively). However, perceived risk did not differ among the groups. Forty-six percent of the Asian American women, compared to 25% of Caucasian women, falsely believed "breast cancer is the number one cause of death for women (p = 0.002)." In addition, Asian/Pacific Islander women were less likely to report "arm pain, numbness, tingling, or radiating" as one of the heart attack symptoms compared to the Caucasian and the multiracial group (34%, 63% [p < 0.001], and 66% [p = 0.004], respectively). OBJECTIVE: The aim of the study was to compare knowledge and awareness of heart attacks/heart disease and perceived risk for future heart attack in Asian/Pacific Islander women, compared to other racial and ethnic groups. MATERIALS AND METHODS: In this cross-sectional study, 318 women enrolled in a mobile phone-based physical activity education trial were analyzed. Heart attack knowledge, self-efficacy for recognizing and responding to heart attack symptoms, and perceived risk for a future heart attack were measured. Analyses were conducted using logistic, proportional odds, and linear regression models, depending on the outcome and adjusting for age. Pairwise differences between Asian/Pacific Islanders and the other four groups were assessed using a Bonferroni correction (p < 0.0125). CONCLUSIONS: These findings highlight the urgent need to develop effective, tailored campaigns to close the knowledge gap between Asian/Pacific Islander women and Caucasian women.
Keywords: Asian/Pacific Islanders; cardiovascular risks; heart attack symptoms; perceived risk; women

Patient Navigation for Colonoscopy Completion: Results of an RCT - DeGroff, A.; Schroy, P.C., III; Morrissey, K.G.; Slotman, B.; Rohan, E.A.; Bethel, J.; Murillo, J.; Ren, W.; Niwa, S.; Leadbetter, S.; Joseph, D. (American Journal of Preventive Medicine, 2017)
Introduction Colorectal cancer is a leading cause of cancer-related death in the U.S. Although screening reduces colorectal cancer incidence and mortality, screening rates among U.S. adults remain less than optimal, especially among disadvantaged populations. This study examined the efficacy of patient navigation to increase colonoscopy screening. Study design RCT. Setting/participants A total of 843 low-income adults, primarily Hispanic and non-Hispanic blacks, aged 50–75 years referred for colonoscopy at Boston Medical Center were randomized into the intervention (n=429) or control (n=427) groups. Participants were enrolled between September 2012 and December 2014, with analysis following through 2015. Intervention Two bilingual lay navigators provided individualized education and support to reduce patient barriers and facilitate colonoscopy completion. The intervention was delivered largely by telephone. Main outcome measure Colonoscopy completion within 6 months of study enrollment. Results Colonoscopy completion was significantly higher for navigated patients (61.1%) than control group patients receiving usual care (53.2%, p=0.021). Based on regression analysis, the odds of completing a colonoscopy for navigated patients was one and a half times greater than for controls (95% CI=1.12, 2.03, p=0.007). There were no differences between navigated and control groups in regard to adequacy of bowel preparation (95.3% vs 97.3%, respectively). Conclusions Navigation significantly improved colonoscopy screening completion among a racially diverse, low-income population. Results contribute to mounting evidence demonstrating the efficacy of patient navigation in increasing colorectal cancer screening. Screening can be further enhanced when navigation is combined with other evidence-based practices implemented in healthcare systems and the community. © 2017

Racial Variation in Patient-Reported Outcomes Following Treatment for Localized Prostate Cancer: Results from the CEASAR Study - Tyson, M.D.; Alvarez, J.; Koyama, T.; Hoffman, K.E.; Resnick, M.J.; Wu, X.-C.; Cooperberg, M.R.; Goodman, M.; Greenfield, S.; Hamilton, A.S.; Hashibe, M.; Paddock, L.E.; et al. (European Urology, 2017)
Background Relatively little is known about the relationship between race/ethnicity and patient-reported outcomes after contemporary treatments for localized prostate cancer. Objective To test the hypothesis that treatment-related changes in urinary, bowel, sexual, and hormonal function vary by race/ethnicity. Design, setting, and participants The Comparative Effectiveness Analysis of Surgery and Radiation (CEASAR) study is a prospective, population-based, observational study that enrolled 3708 men diagnosed with localized prostate cancer in 2011–2012. Outcome measurements and statistical analysis Patient-reported disease-specific function was measured using the 26-item Expanded Prostate Index Composite (EPIC) at baseline and 6 and 12 mo after enrollment. Mean treatment differences in function were compared by race using risk-adjusted generalized estimating equations. Results and limitations While all race/ethnic groups reported considerable declines in scores for urinary incontinence after radical prostatectomy (RP) when compared to active surveillance, African-American men reported a greater difference than white men did (adjusted difference-in-differences 8.4 points, 95% confidence interval 2.0–14.8; p = 0.01). No difference in bother scores was noted and the overall proportion of explained variation attributable to race/ethnicity was relatively small in comparison to primary treatment and baseline function. No clinically significant racial variation was noted for the sexual, bowel, irritative voiding, or hormone domains. Limitations include the lack of well-established thresholds for clinical significance using the EPIC instrument. Conclusion While these data demonstrate that incontinence at 1 yr after RP may be worse for African-American compared to white men, the difference appears to be modest overall. Treatment selection and baseline function explain a much greater proportion of the variation in function after treatment. Patient summary We observed that the effect of treatment for prostate cancer on patient-reported function did not vary dramatically by race/ethnicity. Compared to white men, African-American men experienced a somewhat more pronounced decline in urinary continence after radical prostatectomy, but the corresponding changes in bother scores were not significantly different between the two groups. © 2016 European Association of Urology
Keywords: Active surveillance; Comparative effectiveness; Patient-reported function; Prostate cancer; Radiation; Surgery

Effect of combined patient decision aid and patient navigation vs usual care for colorectal cancer screening in a vulnerable patient population: A randomized clinical trial - Reuland, D.S.; Brenner, A.T.; Hoffman, R.; McWilliams, A.; Rhyne, R.L.; Getrich, C.; Tapp, H.; Weaver, M.A.; Callan, D.; Cubillos, L.; Urquieta De Hernandez, B.; Pignone, M.P. (JAMA Internal Medicine, 2017)
IMPORTANCE Colorectal cancer (CRC) screening is underused, especially among vulnerable populations. Decision aids and patient navigation are potentially complementary interventions for improving CRC screening rates, but their combined effect on screening completion is unknown. OBJECTIVE To determine the combined effect of a CRC screening decision aid and patient navigation compared with usual care on CRC screening completion. DESIGN, SETTING, AND PARTICIPANTS In this randomized clinical trial, datawere collected from January 2014 to March 2016 at 2 community health center practices, 1 in North Carolina and 1 in New Mexico, serving vulnerable populations. Patients ages 50 to 75 years who had average CRC risk, spoke English or Spanish, were not current with recommended CRC screening, and were attending primary care visits were recruited and randomized 1:1 to intervention or control arms. INTERVENTIONS Intervention participants viewed a CRC screening decision aid in English or Spanish immediately before their clinician encounter. The decision aid promoted screening and presented colonoscopy and fecal occult blood testing as screening options. After the clinician encounter, intervention patients received support for screening completion from a bilingual patient navigator. Control participants viewed a food safety video before the encounter and otherwise received usual care. MAIN OUTCOMES AND MEASURES The primary outcomewas CRC screening completion within 6 months of the index study visit assessed by blinded medical record review. RESULTS Characteristics of the 265 participants were as follows: their mean age was 58 years; 173 (65%) were female, 164 (62%) were Latino; 40 (15%) were white non-Latino; 61 (23%) were black or of mixed race; 191 (78%) had a household income of less than $20 000; 101 (38%) had low literacy; 75 (28%) were on Medicaid; and 91 (34%) were uninsured. Intervention participants were more likely to complete CRC screening within 6 months (68% vs 27%); adjusted-difference, 40 percentage points (95%CI, 29-51 percentage points). The intervention was more effective in women than in men (50 vs 21 percentage point increase, interaction P = .02). No effect modification was observed across other subgroups. CONCLUSIONS AND RELEVANCE A patient decision aid plus patient navigation increased the rate of CRC screening completion in compared with usual care in vulnerable primary care patients. © 2017 American Medical Association. All rights reserved.

Prostate-specific antigen response in black and white patients treated with abiraterone acetate for metastatic castrate–resistant prostate cancer - Ramalingam, S.; Humeniuk, M.S.; Hu, R.; Rasmussen, J.; Healy, P.; Wu, Y.; Harrison, M.R.; Armstrong, A.J.; George, D.J.; Zhang, T. (Urologic Oncology: Seminars and Original Investigations, 2017)
Purpose Evidence suggests differences in androgen receptor AR signaling between black (B) and white (W) patients with prostate cancer, but pivotal trials of abiraterone acetate (AA) for patients with metastatic castration–resistant prostate cancer (mCRPC) enrolled few black patients, a population with a higher mortality from prostate cancer. Our primary objective was to determine differences in response to AA between B and W patients. Methods We performed a retrospective case-control study of B vs. W patients treated with AA between May 1, 2008 and June 16, 2015 at Duke University Medical Center. Patients were identified (W control patients were matched 2:1 to B patients stratified based on previous docetaxel exposure) through pharmacy records and were eligible if treated with AA for metastatic castration–resistant prostate cancer. Patients with previous enzalutamide use were excluded. The primary objective was to compare the rate of≥90% prostate-specific antigen (PSA) decline from baseline between B vs. W patients. Secondary outcomes included comparing time on therapy, time to PSA progression, and overall survival among groups. Results Baseline characteristics among patients (n = 45 B, n = 90 W) were identified; these included Karnofsky performance status, PSA, Gleason score, alkaline phosphatase, albumin, hemoglobin, lactate dehydrogenase, opiate use for pain, and metastatic sites. Baseline characteristics among groups were similar except for median hemoglobin (B = 11.4 g/dl, W = 12.3 g/dl). The proportion of B patients achieving a≥90% PSA level decline was 37.8% vs. 28.9% for W patients (P = 0.296). Statistically significant differences were found in the proportion of patients achieving a≥50% PSA level decline (B = 68.9%, W = 48.9% [P = 0.028]) and≥30% PSA level decline (B = 77.8%, W = 54.4% [P = 0.008]). Rates of primary abiraterone-refractory disease (PSA increase as best response) trended higher in W (31.1%) than in B (15.6%) patients (P = 0.052). Median treatment duration (B = 9.4 mo, W = 8.3 mo) did not differ (Wilcoxon P = 0.444). Median overall survival (B = 27.3 mo [95% CI: 13.9, not estimable], W = 24.8 mo [95% CI: 19, 31.6] [P = 0.669]) and median time to PSA progression (B = 11.0 mo [95% CI: 4.3, 18.0], W = 9.4 mo [95% CI: 6.2, 13.0] [P = 0.917]) did not differ. Conclusions Black patients may have a higher PSA response to AA than white patients. An ongoing prospective clinical study (NCT01940276) is evaluating outcomes between black and white patients treated with AA. © 2017 Elsevier Inc.
Keywords: Abirterone acetate; Castration-resistant; Prostate-specific antigen; Prostatic neoplasms; Race

Clinical research participation among adolescent and young adults at an NCI-designated Comprehensive Cancer Center and affiliated pediatric hospital - Sanford, S.D.; Beaumont, J.L.; Snyder, M.A.; Reichek, J.; Salsman, J.M. (Supportive Care in Cancer, 2017)
Purpose: Minimal clinical trial participation among adolescents and young adults (AYAs) with cancer limits scientific progress and ultimately their clinical care and outcomes. These analyses examine the current state of AYA clinical research participation at a Midwestern comprehensive cancer center and affiliated pediatric hospital to advise program development and increase availability of trials and AYA participation. Enrollment is examined across all diagnoses, the entire AYA age spectrum (15–39), and both cancer therapeutic and supportive care protocols. Methods: his study was a retrospective review of electronic medical records via existing databases and registries for all AYAs. Data were collected for AYAs seen by an oncologist at the adult outpatient cancer center or at the pediatric hospital between the years 2010 and 2014. Descriptive statistics and logistic regression analyses were conducted to characterize this sample. Results: In the pediatric setting, 42.3% of AYAs were enrolled in a study compared to 11.2% in the adult setting. Regression analyses in the pediatric setting revealed that AYAs with private insurance or Caucasian race were more likely to participate. Within the adult setting, ethnicity, race, insurance, and diagnosis were associated with study participation; 54.8% of study enrollments were for cancer therapeutic and 43.4% for supportive care studies. Conclusions: These results are comparable to previously published data and support the need for new local and national AYA initiatives to increase the availability of and enrollment in therapeutic clinical trials. The same is true for supportive care studies which play a crucial role in improving quality of life. © 2017, Springer-Verlag Berlin Heidelberg.
Keywords: Adolescents; Cancer survivors; Clinical trials; Young adults

A prospective study of health-related quality-of-life outcomes for patients with low-risk prostate cancer managed by active surveillance or radiation therapy - Banerji, J.S.; Hurwitz, L.M.; Cullen, J.; Wolff, E.M.; Levie, K.E.; Rosner, I.L.; Brand, T.C.; LʼEsperance, J.O.; Sterbis, J.R.; Porter, C.R. (Urologic Oncology: Seminars and Original Investigations, 2017)
Introduction Patients with low-risk prostate cancer (PCa) often have excellent oncologic outcomes. However, treatment with curative intent can lead to decrements in health-related quality of life (HRQoL). Patients treated with radical prostatectomy have been shown to suffer declines in urinary and sexual HRQoL as compared to those managed with active surveillance (AS). Similarly, patients treated with external-beam radiation therapy (EBRT) are hypothesized to experience greater declines in bowel HRQoL. As health-related quality-of-life (HRQoL) concerns are paramount when selecting among treatment options for low-risk PCa, this study examined HRQoL outcomes in men undergoing EBRT as compared to AS in a prospective, racially diverse cohort. Methods A prospective study of HRQoL in patients with PCa enrolled in the Center for Prostate Disease Research (CPDR) Multicenter National Database was initiated in 2007. The current study included patients diagnosed through April 2014. HRQoL was assessed with the Expanded Prostate Cancer Index Composite (EPIC) and the Medical Outcomes Study Short Form (SF-36). Temporal changes in HRQoL were compared for patients with low-risk PCa managed on AS vs. EBRT at baseline, 1-, 2-, and 3 years post-PCa diagnosis. Longitudinal patterns were modeled using linear regression models fitted with generalized estimating equations (GEE), adjusting for baseline HRQoL, demographic, and clinical patient characteristics. Results Of the 499 eligible patients with low-risk PCa, 103 (21%) selected AS and 60 (12%) were treated with EBRT. Demographic characteristics of the treatment groups were similar, though a greater proportion of patients in the EBRT group were African American (P = 0.0003). At baseline, both treatment groups reported comparable HRQoL. EBRT patients experienced significantly worse bowel function and bother at 1 year (adjusted mean score: 87 vs. 95, P = 0.001 and 89 vs. 95, P = 0.008, respectively) and 2 years (87 vs. 93, P = 0.007 and 87 vs. 96, P = 0.002, respectively) compared to patients managed on AS. In contrast to those on AS, more than half the number of patients who received EBRT experienced a decline in bowel function (52% vs. 17%, p=0.003) and bother (52% vs. 15%, P = 0.002) from baseline to 1 year. Patients who received EBRT were significantly more likely to experience a decrease in more than one functional domain (urinary, sexual, bowel, or hormonal) at 1 year when compared with those on AS (60% vs. 28%, P = 0.004). Conclusions Patients receiving EBRT for low-risk prostate cancer suffer declines in bowel HRQoL. These declines are not experienced by patients on AS, suggesting that management of low-risk prostate cancer with AS may offer a means for preserving HRQoL following prostate cancer diagnosis. © 2017 Elsevier Inc
Keywords: Active surveillance; Prostate cancer; Quality of life; Radiotherapy; Treatment

Association of antioxidant supplement use and dementia in the prevention of Alzheimer's disease by Vitamin E and selenium trial (PREADViSE) - Kryscio, R.J.; Abner, E.L.; Caban-Holt, A.; Lovell, M.; Goodman, P.; Darke, A.K.; Yee, M.; Crowley, J.; Schmitt, F.A. (JAMA Neurology, 2017)
IMPORTANCE Oxidative stress is an established dementia pathway, but it is unknown if the use of antioxidant supplements can prevent dementia. OBJECTIVE To determine if antioxidant supplements (Vitamin E or selenium) used alone or in combination can prevent dementia in asymptomatic older men. DESIGN, SETTING, AND PARTICIPANTS The Prevention of Alzheimer's Disease by Vitamin E and Selenium (PREADViSE) trial began as a double-blind randomized clinical trial in May 2002, which transformed into a cohort study from September 2009 to May 2015. The PREADViSE trial was ancillary to the Selenium and Vitamin E Cancer Prevention Trial (SELECT), a randomized clinical trial of the same antioxidant supplements for preventing prostate cancer, which closed in 2009 owing to findings from a futility analysis. The PREADViSE trial recruited 7540 men, of whom 3786 continued into the cohort study. Participants were at least 60 years old at study entry and were enrolled at 130 SELECT sites, and Cox proportional hazards models were used in a modified intent-to-treat analysis to compare hazard rates among the study arms. INTERVENTIONS Participants were randomized to Vitamin E, selenium, Vitamin E and selenium, or placebo. While taking study supplements, enrolled men visited their SELECT site and were evaluated for dementia using a 2-stage screen. During the cohort study, men were contacted by telephone and assessed using an enhanced 2-stage cognitive screen. In both phases, men were encouraged to visit their physician if the screen results indicated possible cognitive impairment. MAIN OUTCOMES AND MEASURES Dementia case ascertainment relied on a consensus review of the cognitive screens and medical records for men with suspected dementia who visited their physician for an evaluation or by review of all available information, including a functional assessment screen. RESULTS The mean (SD) baseline age of the 7540 participants was 67.5 (5.3) years, with 3936 (52.2%) reporting a college education or better, 754 (10.0%) reporting black race, and 505 (6.7%) reporting Hispanic ethnicity. Dementia incidence (325 of 7338 men [4.4%]) was not different among the 4 study arms. A Cox model, which adjusted incidence for participant demographic information and baseline self-reported comorbidities, yielded hazard ratios of 0.88 (95%CI, 0.64-1.20) for Vitamin E, 0.83 (0.60-1.13) for selenium, and 1.00 (0.75-1.35) for the combination compared with placebo. CONCLUSIONS AND RELEVANCE Neither supplement prevented dementia. To our knowledge, this is the first study to investigate the long-term association of antioxidant supplement use and dementia incidence among asymptomatic men. © 2017 American Medical Association. All rights reserved.

A randomized controlled trial of a multicomponent, targeted, low-literacy educational intervention compared with a nontargeted intervention to boost colorectal cancer screening with fecal immunochemical testing in community clinics - Davis, S.N.; Christy, S.M.; Chavarria, E.A.; Abdulla, R.; Sutton, S.K.; Schmidt, A.R.; Vadaparampil, S.T.; Quinn, G.P.; Simmons, V.N.; Ufondu, C.B.; Ravindra, C.; Schultz, I.; et al. (Cancer, 2017)
BACKGROUND: The objective of the current study was to improve colorectal cancer (CRC) screening uptake with the fecal immunochemical test (FIT). The current study investigated the differential impact of a multicomponent, targeted, low-literacy educational intervention compared with a standard, nontargeted educational intervention. METHODS: Patients aged 50 to 75 years who were of average CRC risk and not up-to-date with CRC screening were recruited from either a federally qualified health center or a primary care community health clinic. Patients were randomized to the intervention condition (targeted photonovella booklet/DVD plus FIT kit) or comparison condition (standard Centers for Disease Control and Prevention brochure plus FIT kit). The main outcome was screening with FIT within 180 days of delivery of the intervention. RESULTS: Of the 416 participants, 54% were female; the participants were racially and ethnically diverse (66% white, 10% Hispanic, and 28% African American), predominantly of low income, and insured (the majority had county health insurance). Overall, the FIT completion rate was 81%, with 78.1% of participants in the intervention versus 83.5% of those in the comparison condition completing FIT (P =.17). In multivariate analysis, having health insurance was found to be the primary factor predicting a lack of FIT screening (adjusted odds ratio, 2.10; 95% confidence interval, 1.04-4.26 [P =.04]). CONCLUSIONS: The multicomponent, targeted, low-literacy materials were not found to be significantly different or more effective in increasing FIT uptake compared with the nontargeted materials. Provision of a FIT test plus education may provide a key impetus to improve the completion of CRC screening. The type of educational material (targeted vs nontargeted) may matter less. The findings of the current study provide a unique opportunity for clinics to adopt FIT and to choose the type of patient education materials based on clinic, provider, and patient preferences. Cancer 2017;123:1390–1400. © 2016 American Cancer Society. © 2016 American Cancer Society
Keywords: colorectal cancer; early detection of cancer; fecal immunochemical test; health promotion; intervention studies; medically underserved

Prognostic Significance of a Negative Prostate Biopsy: An Analysis of Subjects Enrolled in a Prostate Cancer Screening Trial - Lewicki, P.; Shoag, J.; Golombos, D.M.; Oromendia, C.; Ballman, K.V.; Halpern, J.A.; Stone, B.V.; O'Malley, P.; Barbieri, C.E.; Scherr, D.S. (Journal of Urology, 2017)
Purpose To our knowledge the optimal treatment of patients following a negative prostate biopsy is unknown. Consequently, resources are increasingly being directed toward risk stratification in this cohort. However, the risk of prostate cancer mortality in this group before the introduction of supplemental biomarkers and imaging techniques is unclear. Materials and Methods The PLCO (Prostate, Lung, Colorectal and Ovarian Cancer) Screening Trial provides survival data prior to the implementation of new diagnostic interventions. We divided men with an initial positive screen and a subsequent prostate biopsy into cohorts based on positive or negative results. Prostate cancer specific mortality was then compared to that in the trial control arm to estimate the prognostic significance of biopsy results relative to the general population. Results A total of 36,525 and 36,560 patients comprised the screening and control arms, respectively. Of 4,064 subjects with a positive first screen 1,233 underwent a linked biopsy, of which 473 were positive and 760 were negative. At a median followup of 12.9 years, 1.1% of men in the negative biopsy cohort had died of prostate cancer. The difference in mortality rates between the negative biopsy and control arms was 0.734 deaths per 1,000 person-years. The proportional subhazard ratios of prostate cancer specific mortality for negative biopsy and positive biopsy relative to the control arm were 2.93 (95% CI 1.44–5.99) and 18.77 (95% CI 12.62–27.93), respectively. Conclusions After a negative prostate biopsy, men face a relatively low risk of death from prostate cancer when followed with traditional markers and biopsy techniques. This suggests limited potential for new diagnostic interventions to improve survival in this group. © 2017 American Urological Association Education and Research, Inc.
Keywords: biopsy; diagnosis; mortality; prostatic neoplasms; risk

Correlates of Patient Intent and Preference on Colorectal Cancer Screening - Jimbo, M.; Sen, A.; Plegue, M.A.; Hawley, S.T.; Kelly-Blake, K.; Rapai, M.; Zhang, M.; Zhang, Y.; Ruffin, M.T., IV (American Journal of Preventive Medicine, 2017)
Introduction Information is limited on patient characteristics that influence their preference among screening options and intent to be screened for colorectal cancer (CRC). A mechanistic pathway to intent and preference was examined through a formal mediation analysis. Methods From 2012 to 2014, a total of 570 adults aged 50–75 years were recruited from 15 primary care practices in Metro Detroit for a trial on decision aids for CRC screening. Confirmatory factor, regression, and mediation analyses were performed in 2015–2016 on baseline cross-sectional data. Main outcomes were patient intent and preference. Perceived risk and self-efficacy were secondary outcomes. Covariates included demographic information, health status, previous CRC screening experience, patient attitudes, and knowledge. Results Mean age was 57.7 years, 56.1% were women, and 55.1% white and 36.6% black. Women had 32% and 41% lower odds than men of perceiving CRC to be high/moderate risk (OR=0.68, 95% CI=0.47, 0.97, p=0.03) and having high self-efficacy (OR=0.59, 95% CI=0.42, 0.85, p=0.006), respectively. Whites had 63% and 47% lower odds than blacks of having high self-efficacy (OR=0.37, 95% CI=0.25, 0.57, p<0.001) and intent to undergo CRC screening (OR=0.53, 95% CI=0.34, 0.84, p=0.007), respectively. Younger age, higher knowledge, lower level of test worries, and medium/high versus low self-efficacy increased the odds of intent of being screened. Self-efficacy, but not perceived risk, significantly mediated the association between race, attitude, and test worries and patient screening intent. Conclusions Self-efficacy mediated the association between race, attitude, and test worries and patient intent. © 2017

Usability of a novel mobile health iPad app by vulnerable populations - Miller, D.P., Jr.; Weaver, K.E.; Case, L.D.; Babcock, D.; Lawler, D.; Denizard-Thompson, N.; Pignone, M.P.; Spangler, J.G. (JMIR mHealth and uHealth, 2017)
Background: Recent advances in mobile technologies have created new opportunities to reach broadly into populations that are vulnerable to health disparities. However, mobile health (mHealth) strategies could paradoxically increase health disparities, if low socioeconomic status individuals lack the technical or literacy skills needed to navigate mHealth programs. Objective: The aim of this study was to determine whether patients from vulnerable populations could successfully navigate and complete an mHealth patient decision aid. Methods: We analyzed usability data from a randomized controlled trial of an iPad program designed to promote colorectal cancer (CRC) screening. The trial was conducted in six primary care practices and enrolled 450 patients, aged 50-74 years, who were due for CRC screening. The iPad program included a self-survey and randomly displayed either a screening decision aid or a video about diet and exercise. We measured participant ability to complete the program without assistance and participant-rated program usability. Results: Two-thirds of the participants (305/450) were members of a vulnerable population (limited health literacy, annual income < US $20,000, or black race). Over 92% (417/450) of the participants rated the program highly on all three usability items (90.8% for vulnerable participants vs 96.6% for nonvulnerable participants, P=.006). Only 6.9% (31/450) of the participants needed some assistance to complete the program. In multivariable logistic regression, being a member of a vulnerable population was not associated with needing assistance. Only older age, less use of text messaging (short message service, SMS), and lack of Internet use predicted needing assistance. Conclusions: Individuals who are vulnerable to health disparities can successfully use well-designed mHealth programs. Future research should investigate whether mHealth interventions can reduce health disparities. ©David P Miller Jr, Kathryn E Weaver, L Doug Case, Donald Babcock, Donna Lawler, Nancy Denizard-Thompson, Michael P Pignone, John G Spangler.
Keywords: Decision support techniques; Health literacy; Primary care; Technology assessment; Vulnerable populations

Adoption, reach, and implementation of a cancer education intervention in African American churches - Santos, S.L.Z.; Tagai, E.K.; Scheirer, M.A.; Bowie, J.; Haider, M.; Slade, J.; Wang, M.Q.; Holt, C.L. (Implementation Science, 2017)
Background: Use of technology is increasing in health promotion and has continued growth potential in intervention research. Guided by the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework, this paper reports on the adoption, reach, and implementation of Project HEAL (Health through Early Awareness and Learning)-a community-based implementation trial of a cancer educational intervention in 14 African American churches. We compare adoption, reach, and implementation at the organizational and participant level for churches in which lay peer community health advisors (CHAs) were trained using traditional classroom didactic methods compared with a new online system. Methods: Fifteen churches were randomized to one of two study groups in which two CHAs per church were trained through either classroom ("Traditional" n = 16 CHAs in 8 churches) or web-based ("Technology" n = 14 CHAs in 7 churches) training methods. Once trained and certified, all CHAs conducted a series of three group educational workshops in their churches on cancer early detection (breast, prostate, and colorectal). Adoption, reach, and implementation were assessed using multiple data sources including church-level data, participant engagement in the workshops, and study staff observations of CHA performance. Results: The project had a 41% overall adoption rate at the church level. In terms of reach, a total of 375 participants enrolled in Project HEAL-226 participants in the Traditional group (43% reach) and 149 in the Technology group (21% reach; p < .10). Implementation was evaluated in terms of adherence, dosage, and quality. All churches fully completed the three workshops; however, the Traditional churches took somewhat longer (M = 84 days) to complete the workshop series than churches in the Technology group (M = 64 days). Other implementation outcomes were comparable between both the Traditional and Technology groups (p > .05). Conclusions: Overall, the Project HEAL intervention had reasonable adoption, though reach could have been better. Implementation was strong across both study groups, suggesting the promise of using web-based methods to disseminate and implement evidence-based interventions in faith-based settings and other areas where community health educators work to eliminate health disparities. © 2017 The Author(s).

African American women's recollected experiences of adherence to breast cancer treatment - Heiney, S.P.; Messias, D.K.H.; Felder, T.M.; Phelps, K.W.; Quinn, J.C. (Oncology Nursing Forum, 2017)
Purpose/Objectives: To explore African American women's recollected experiences of breast cancer treatment. Research Approach: Qualitative description and narrative analysis. Setting: South Carolina Oncology Associates, an outpatient oncology clinic serving rural and urban populations. Participants: 16 African American women with breast cancer previously enrolled in the control arm (n = 93) of a completed randomized, controlled trial. Methodologic Approach: Feminist narrative analysis of in-depth individual interviews. Findings: The authors identified three themes within the African American breast cancer survivors' recollected experiences of treatment adherence: Embarking With Trust, Moving on Down the Road, and Being Actively Involved in Decision Making. Interpretation: Although little evidence was presented of shared decision making with providers, patients were committed to completing the prescribed therapies. The narratives highlighted the value of in-depth examination of patients' perspectives, particularly among minority and underserved groups. With the exception of voicing personal choice of surgical treatment, the women trusted providers' recommendations with a resolve to "just do it." Although trust may enhance treatment adherence, it may also reflect power differentials based on gender, race, education, and culture. Implications for Nursing: Nurses should listen to patients describe their experience with cancer treatment and compare the themes from this study with their patients' story. This comparison will help nurses support patients through various aspect of diagnosis and treatment. Copyright 2017 by the Oncology Nursing Society.
Keywords: African American; Breast cancer; Survivorship; Treatment adherence; Treatment decision making

Barriers and Strategies to Participation in Tissue Research Among African-American Men - Drake, B.F.; Boyd, D.; Carter, K.; Gehlert, S.; Thompson, V.S. (Journal of Cancer Education, 2017)
Before the burgeoning field of biospecimen collection can advance prevention and treatment methods, researchers must access diverse molecular data samples. However, minorities, especially African-American men, remain reticent to join these studies. This study, using theory-based approaches, investigated African-American men’s barriers to participating in biorepository research. Fourteen focus groups were conducted among 70 African-American men (ages 40 to 80). The groups were stratified by prostate cancer history and educational attainment background. Participants identified perceived factors that promoted or hindered study participation when questioned about their knowledge and attitudes about biospecimen research. Ninety-four percent of participants indicated never participating in a study that collected biological samples. Barriers to their participation included lack of knowledge and understanding regarding biospecimen research practices and uses. In addition, they extensively cited a prevalent mistrust of the medical community and discomfort with study recruitment practices. African-American males were more willing to participate in biorepository studies with physician endorsement or if they understood that participation could benefit future generations. Men also wanted more recruitment and advertising done in familiar places. © 2015, American Association for Cancer Education.
Keywords: African-American; Biorepository; Prostate cancer; Recruitment

Recruiting families at risk for hereditary breast and ovarian cancer from a statewide cancer registry: a methodological study - Katapodi, M.C.; Duquette, D.; Yang, J.J.; Mendelsohn-Victor, K.; Anderson, B.; Nikolaidis, C.; Mancewicz, E.; Northouse, L.L.; Duffy, S.; Ronis, D.; Milliron, K.J.; Probst-Herbst, N.; et al. (Cancer Causes and Control, 2017)
Purpose: Cancer genetic services (counseling/testing) are recommended for women diagnosed with breast cancer younger than 45 years old (young breast cancer survivors—YBCS) and at-risk relatives. We present recruitment of YBCS, identification and recruitment of at-risk relatives, and YBCS willingness to contact their cancer-free, female relatives. Methods: A random sample of 3,000 YBCS, stratified by race (Black vs. White/Other), was identified through a population-based cancer registry and recruited in a randomized trial designed to increase use of cancer genetic services. Baseline demographic, clinical, and family characteristics, and variables associated with the Theory of Planned Behavior (TPB) were assessed as predictors of YBCS’ willingness to contact at-risk relatives. Results: The 883 YBCS (33.2% response rate; 40% Black) who returned a survey had 1,875 at-risk relatives and were willing to contact 1,360 (72.5%). From 853 invited at-risk relatives (up to two relatives per YBCS), 442 responded (51.6% response rate). YBCS with larger families, with a previous diagnosis of depression, and motivated to comply with recommendations from family members were likely to contact a greater number of relatives. Black YBCS were more likely to contact younger relatives and those living further than 50 miles compared to White/Other YBCS. Conclusion: It is feasible to recruit diverse families at risk for hereditary cancer from a population-based cancer registry. This recruitment approach can be used as a paradigm for harmonizing processes and increasing internal and external validity of large-scale public health genomic initiatives in the era of precision medicine. © 2017, Springer International Publishing Switzerland.
Keywords: At-risk relatives; Cancer registry; Public health genomic trials; Recruitment; Young breast cancer survivors

Phase Ib Trial of Cabazitaxel and Tasquinimod in Men With Heavily Pretreated Metastatic Castration Resistant Prostate Cancer (mCRPC): The CATCH Trial - Armstrong, A.J.; Humeniuk, M.S.; Healy, P.; Szmulewitz, R.; Winters, C.; Kephart, J.; Harrison, M.R.; Martinez, E.; Mundy, K.; Halabi, S.; George, D. (Prostate, 2017)
BACKGROUND: Tasquinimod is an immunomodulating and anti-antiangiogenic oral agent with anti-prostate cancer activity in preclinical studies and in clinical trials of men with metastatic castration resistant prostate cancer (mCRPC), including single agent activity and in combination with taxanes. We sought to identify the maximum tolerated dose (MTD) and recommended phase 2 dose (RP2D) of tasquinimod in combination with cabazitaxel and prednisone in men with chemorefractory mCRPC. METHODS: Men with mCRPC who had failed prior docetaxel chemotherapy received cabazitaxel 25 mg/m2 every 3 weeks with oral tasquinimod at 1 of 3 escalating dose levels (0.25, 0.5, and 1.0 mg once daily) with prednisone and PEG-filgastrim support, using a 3 + 3 dose escalation design. Treatment continued until progressive disease or unacceptable toxicity. RESULTS: We enrolled 25 men with chemorefractory mCRPC. The RP2D was 0.5 mg tasquinimod based on excess DLTs (two of three men) observed at dose level 3 (1.0 mg) including grade 3 sensory neuropathy and grade 3 atrial fibrillation. Dose level 2 was expanded to 14 men, where 3 DLTs were observed: grade 3 fatigue, grade 4 febrile neutropenia, and grade 3 liver function abnormalities. The proportion of men with a ≥30% PSA decline was 63% and the median composite progression-free survival (PFS) was 8.5 months (95% CI 4.2–16.4 months) based on 12 PFS events. The median number of cycles of cabazitaxel was 6 (range 1–13), with six men receiving >10 cycles. Best overall RECIST responses (CR + PR) were observed in three men (12%), with stable disease in 12 (48%). No pharmacokinetic interactions were observed. CONCLUSIONS: We determined the RP2D of tasquinimod combined with cabazitaxel to be 0.5 mg daily following a 3 week lead-in of tasquinimod 0.25 mg with growth factor support. No unexpected toxicities occurred. Prostate 77: 385–395, 2017. © 2016 Wiley Periodicals, Inc. © 2016 Wiley Periodicals, Inc.
Keywords: angiogenesis; cabazitaxel; chemotherapy; clinical trial; immunotherapy; mCRPC; phase I; prostate cancer; tasquinimod

Application of a low polyphenol or low ellagitannin dietary intervention and its impact on ellagitannin metabolism in men - Roberts, K.M.; Grainger, E.M.; Thomas-Ahner, J.M.; Hinton, A.; Gu, J.; Riedl, K.M.; Vodovotz, Y.; Abaza, R.; Schwartz, S.J.; Clinton, S.K. (Molecular Nutrition and Food Research, 2017)
Scope: Plant polyphenols are widespread in the American diet, yet estimated intake is uncertain. We examine the application of the Polyphenol Explorer® (PED) database to quantify polyphenol and ellagitannin (ET) intake of men with prostate cancer and tested the implementation of diets restricted in polyphenols or ETs. Methods and results: Twenty-four men enrolled in a 4-week trial were randomized to usual, low-polyphenol or low-ET diet. Estimated polyphenol and ET intakes were calculated from 3-day diet records utilizing the PED. Urine and plasma metabolites were quantified by UPLC-MS. Adherence to the restricted diets was 95% for the low polyphenol and 98% for low-ET diet. In the usual diet, estimated dietary polyphenol intake was 1568 ± 939 mg/day, with coffee/tea beverages (1112 ± 1028 mg/day) being the largest contributors and estimated dietary ET intake was 12 ± 13 mg/day. The low-polyphenol and low-ET groups resulted in a reduction of total polyphenols by 45% and 85%, respectively, and omission of dietary ETs. UPLC analysis of urinary host and microbial metabolites reflect ET intake. Conclusion: PED is a useful database for assessing exposure to polyphenols. Diets restricted in total polyphenol or ET intake are feasible and UPLC assessment of ET metabolites is reflective of dietary intake. © 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: Black raspberries; Ellagitannins; Polyphenol explorer database; Polyphenols; Urolithins

Nigella sativa Supplementation Improves Asthma Control and Biomarkers: A Randomized, Double-Blind, Placebo-Controlled Trial - Koshak, A.; Wei, L.; Koshak, E.; Wali, S.; Alamoudi, O.; Demerdash, A.; Qutub, M.; Pushparaj, P.N.; Heinrich, M. (Phytotherapy Research, 2017)
Poor compliance with conventional asthma medications remains a major problem in achieving asthma control. Nigella sativa oil (NSO) is used traditionally for many inflammatory conditions such as asthma. We aimed to investigate the benefits of NSO supplementation on clinical and inflammatory parameters of asthma. NSO capsules 500 mg twice daily for 4 weeks were used as a supplementary treatment in a randomized, double-blind, placebo-controlled trial in asthmatics (clinicaltrials.gov: NCT02407262). The primary outcome was Asthma Control Test score. The secondary outcomes were pulmonary function test, blood eosinophils and total serum Immunoglobulin E. Between 1 June and 30 December 2015, 80 asthmatics were enrolled, with 40 patients in each treatment and placebo groups. After 4 weeks, ten patients had withdrawn from each group. Compared with placebo, NSO group showed a significant improvement in mean Asthma Control Test score 21.1 (standard deviation = 2.6) versus 19.6 (standard deviation = 3.7) (p = 0.044) and a significant reduction in blood eosinophils by −50 (−155 to −1) versus 15 (−60 to 87) cells/μL (p = 0.013). NSO improved forced expiratory volume in 1 second as percentage of predicted value by 4 (−1.25 to 8.75) versus 1 (−2 to 5) but non-significant (p = 0.170). This randomized, double-blind, placebo-controlled trial demonstrated that NSO supplementation improves asthma control with a trend in pulmonary function improvement. This was associated with a remarkable normalization of blood eosinophlia. Future studies should follow asthmatics for longer periods in a multicentre trial. Copyright © 2017 John Wiley & Sons, Ltd. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: allergy; asthma; black seed; clinical trial; eosinophils; Nigella sativa

Barriers to Recruitment and Adherence in a Randomized Controlled Diet and Exercise Weight Loss Intervention Among Minority Breast Cancer Survivors - Aycinena, A.C.; Valdovinos, C.; Crew, K.D.; Tsai, W.Y.; Mata, J.M.; Sandoval, R.; Hershman, D.; Greenlee, H. (Journal of Immigrant and Minority Health, 2017)
Minority recruitment to cancer trials is low and there are limited data on minority adherence to lifestyle modification interventions. We examined factors related to recruitment and adherence to a pilot weight loss intervention among Hispanic and black breast cancer survivors. Participants completed a detailed screening interview to assess barriers to enrollment. An index was created to assess adherence at 6 months. 112 potentially eligible women were identified; 66 consented and completed a screening interview. After screening, 9 were ineligible; 15 opted to not enroll; and 42 were randomized. Among eligible women, earlier stage at diagnosis, treatment type, and negative beliefs related to exercise and diet after diagnosis were negatively associated with study enrollment (P < 0.05). Self-reported barriers to adherence included fatigue, family responsibilities, illness, work, transportation, and negative perceptions of exercise and diet. Results from this study emphasize the need to adapt recruitment and adherence strategies to address these factors. © 2016, Springer Science+Business Media New York.
Keywords: Adherence; Behavioral intervention; Black; Cancer survivor; Hispanic; Recruitment

Risk stratification of prostate cancer utilizing apparent diffusion coefficient value and lesion volume on multiparametric MRI - Salami, S.S.; Ben-Levi, E.; Yaskiv, O.; Turkbey, B.; Villani, R.; Rastinehad, A.R. (Journal of Magnetic Resonance Imaging, 2017)
Purpose: To evaluate the performance of apparent diffusion coefficient (ADC) and lesion volume in potentially risk-stratifying patients with prostate cancer (PCa). Materials and Methods: Men with elevated prostate-specific antigen or abnormal digital rectal exam underwent a 3T multiparametric magnetic resonance imaging (mpMRI) with endorectal coil. ADC maps were calculated using b values of 0, 500, 1000, and 1500; additional images were obtained with b value of 2000. We prospectively enrolled 312 men with lesions suspicious for cancer (suspicion score 2–5) on mpMRI. MRI/ultrasound fusion-guided prostate biopsies were performed. Mean ADC of suspicious lesions were correlated against lesion volume, Gleason and D'Amico risk. Results: The cancer detection rate of fusion biopsy per lesion was 45.6% (206/452). Cancerous lesions were larger (median volume: 0.40 vs. 0.30 cm3; P = 0.016). The median ADC (×10−6 mm2/sec) for lesions negative and positive for PCa were 984.5 and 666.5, respectively (P < 0.0001). The AUC of ADC in predicting PCa was 0.79. Larger lesions were associated with higher risk PCa (Gleason and D'Amico) and lower ADC (all P < 0.0001). Conclusion: The mean ADC of suspicious lesions on mpMRI was inversely correlated, while lesion volume had a direct correlation with PCa detection. Future follow-up studies are needed to assess longitudinal cancer risks of suspicious mpMRI lesions. Level of Evidence: 2. J. Magn. Reson. Imaging 2017;45:610–616. © 2016 International Society for Magnetic Resonance in Medicine
Keywords: active surveillance; fusion biopsy; prostate cancer screening

Screening Mammography for Free: Impact of Eliminating Cost Sharing on Cancer Screening Rates - Jena, A.B.; Huang, J.; Fireman, B.; Fung, V.; Gazelle, S.; Landrum, M.B.; Chernew, M.; Newhouse, J.P.; Hsu, J. (Health Services Research, 2017)
Objectives: To study the impact of eliminating cost sharing for screening mammography on mammography rates in a large Medicare Advantage (MA) health plan which in 2010 eliminated cost sharing in anticipation of the Affordable Care Act mandate. Study Setting: Large MA health maintenance organization offering individual-subscriber MA insurance and employer-supplemented group MA insurance. Study Design: We investigated the impact on breast cancer screening of a policy that eliminated a $20 copayment for screening mammography in 2010 among 53,188 women continuously enrolled from 2007 to 2012 in an individual-subscriber MA plan, compared with 42,473 women with employer-supplemented group MA insurance in the same health maintenance organization who had full screening coverage during this period. We used differences-in-differences analysis to study the impact of cost-sharing elimination on mammography rates. Principal Findings: Annual screening rates declined over time for both groups, with similar trends pre-2010 and a slower decline after 2010 among women whose copayments were eliminated. Among women aged 65–74 years in the individual-subscriber MA plan, 44.9 percent received screening in 2009 compared with 40.9 percent in 2012, while 49.5 percent of women in the employer-supplemented MA plan received screening in 2009 compared with 44.1 percent in 2012, that is, a difference-in-difference effect of 1.4 percentage points less decline in screening among women experiencing the cost-sharing elimination. Effects were concentrated among women without recent screening. There were no differences by neighborhood socioeconomic status or race/ethnicity. Conclusions: Eliminating cost sharing for screening mammography was associated with modesty lower decline in screening rates among women with previously low screening adherence. © Health Research and Educational Trust
Keywords: Affordable Care Act; Cost sharing; mammography

Mutational landscapes of smoking-related cancers in Caucasians and African Americans: Precision oncology perspectives at Wake Forest Baptist comprehensive Cancer Center - Kytola, V.; Topaloglu, U.; Miller, L.D.; Bitting, R.L.; Goodman, M.M.; D'Agostino, R.B., Jr.; Desnoyers, R.J.; Albright, C.; Yacoub, G.; Qasem, S.A.; DeYoung, B.; Thorsson, V.; et al. (Theranostics, 2017)
Background: Cancers related to tobacco use and African-American ancestry are under-characterized by genomics. This gap in precision oncology research represents a major challenge in the health disparities in the United States. Methods: The Precision Oncology trial at the Wake Forest Baptist Comprehensive Cancer Center enrolled 431 cancer patients from March 2015 to May 2016. The composition of these patients consists of a high representation of tobacco-related cancers (e.g., lung, colorectal, and bladder) and African-American ancestry (13.5%). Tumors were sequenced to identify mutations to gain insight into genetic alterations associated with smoking and/or African-American ancestry. Results: Tobacco-related cancers exhibit a high mutational load. These tumors are characterized by high-frequency mutations in TP53, DNA damage repair genes (BRCA2 and ATM), and chromatin remodeling genes (the lysine methyltransferases KMT2D or MLL2, and KMT2C or MLL3). These tobacco-related cancers also exhibit augmented tumor heterogeneities. Smoking related genetic mutations were validated by The Cancer Genome Atlas dataset that includes 2,821 cases with known smoking status. The Wake Forest and The Cancer Genome Atlas cohorts (431 and 7,991 cases, respectively) revealed a significantly increased mutation rate in the TP53 gene in the African-American subgroup studied. Both cohorts also revealed 5 genes (e.g. CDK8) significantly amplified in the African-American population. Conclusions: These results provide strong evidence that tobacco is a major cause of genomic instability and heterogeneity in cancer. TP53 mutations and key oncogene amplifications emerge as key factors contributing to cancer outcome disparities among different racial/ethnic groups. © Ivyspring International Publisher.

History of diabetes and survival outcome among participants 65 years or older in SWOG clinical trials - Hershman, D.L.; Till, C.; Wright, J.D.; Ramsey, S.; Barlow, W.E.; Unger, J.M. (JCO Clinical Cancer Informatics, 2017)
Purpose Diabetes is common, increases with age, and may affect outcomes among people with cancer. Understanding the association between diabetes and cancer outcome is challenging, because patients with diabetes have increased all-cause mortality compared with patients without diabetes. Methods We systematically examined the phase III trial database of SWOG to identify patients enrolled in trials during the period from 1999 to 2011. We linked the SWOG clinical records to Medicare claims data according to Social Security number, sex, and date of birth. Medicare claims were used to identify diabetes with at least 6 months of continuous Medicare coverage immediately before registration. Multivariable Cox regression was used to compare survival outcomes between patients with and without diabetes for each of 10 tumor cohorts. The primary outcome was overall survival. We also examined progression-free survival and cancer-free survival. Results In total, 6,422 patients from 15 trials were ≥ 65.5 years of age, of whom 3,173 patients (49%) met the criteria for linkage to Medicare claims. Thirty percent (n = 952) had claims for diabetes before registration. Patients with diabetes were more likely to be black (P < .001), but no other differences in demographic characteristics were observed. In multivariable Cox regression, no association was found between baseline diabetes and overall or progression-free survival; in one case, patients with diabetes had marginally worse cancer-free survival (advanced non-small-cell lung cancer; P = .05). A global test found that baseline diabetes was associated with worse overall survival (P = .03) across the entire panel of analyses. Conclusion Diabetes is common among elderly patients enrolled in clinical trials. Unlike prior observational studies, among patients treated with uniform treatment regimens, and controlling for known prognostic factors, we did not observe an association between diabetes and progression-free or cancerfree survival. © 2018 American Society of Clinical Oncology.

Incidental findings on chest computed tomography are common and linked to inflammation in HIV-infected adults - Park, M.S.; Hileman, C.O.; Sattar, A.; Gilkeson, R.; McComsey, G.A. (Antiviral Therapy, 2017)
Background: Chest imaging is performed for a variety of reasons in HIV-infected adults. There are limited data on the prevalence of incidental findings, progression of these findings over time and the relationship with inflammation in antiretroviral therapy (ART)-treated HIV-infected adults. Methods: This study utilized data from a randomized clinical trial of rosuvastatin in HIV-infected adults on ART. Incidental findings were reported from chest computed tomography (CT) scans obtained for coronary artery calcium score at entry, week 48 and 96. Markers of immune activation and inflammation were measured concurrently. Poisson regression and generalized estimating equations were used. Results: A total of 147 participants were enrolled. Median age was 46 years, 78% were male, 68% African American and 63% current smokers. At baseline, 57% of participants had at least one incidental lung finding (ILF) and four additional participants had at least one ILF by week 96. At baseline, older age, current smoking, lower nadir CD4+ T-cell count and low-density lipoprotein and higher lipoprotein-associated phospholipase A2 (Lp-PLA2) were independently associated with having a greater number of ILFs. In the longitudinal analyses, older age, lower nadir CD4+ T-cell count and higher baseline soluble tumour necrosis factor α-receptor I (sTNF-RI) were independently associated with having a greater number of ILFs over 96 weeks. Conclusions: Over half of participants had at least one incidental finding on chest CT. Beyond traditional factors of older age and smoking, lower nadir CD4+ T-cell count and higher markers of inflammation were associated with having a greater number of ILFs in HIV-infected adults on ART. ©2017 International Medical Press.

The effect of demographics and patient location on the outcome of patients with acute respiratory distress syndrome - El-Haddad, H.; Jang, H.; Chen, W.; Haider, S.; Soubani, A.O. (Annals of Thoracic Medicine, 2017)
OBJECTIVE: Outcome of acute respiratory distress syndrome (ARDS) in relation to age, gender, race, pre-Intensive Care Unit (ICU) location, and type of ICU. METHODS: Retrospective cohort study of patients enrolled in the ARDS network randomized controlled trials. RESULTS: A total of 2914 patients were included in these trials. Outcomes were adjusted to baseline covariates including APACHE III score, vasopressor use, cause of lung injury, lung injury score, diabetes, cancer status, body mass index, and study ID. Older patients had significantly higher mortality at both 28- and 60-day (odds ratio [OR] 2.59 [95% confidence interval [CI]: 2.12-3.18] P < 0.001 and 2.79, 95% CI: 2.29-3.39, P < 0.001, respectively); less ICU and ventilator free days (relative risk [RR] 0.92, 95% CI: 0.87-0.96, P < 0.001 and 0.92, 95% CI: 0.88-0.96, P < 0.001, respectively). For preadmission location, the 28- and 60-day mortality were lower if the patient was admitted from the operating room (OR)/recovery room (OR 0.65, 95% CI: 0.44-0.95, P = 0.026; and OR = 0.66, 95% CI: 0.46-0.95, P = 0.025, respectively) or emergency department (OR = 0.78, 95% CI: 0.61-0.99, P = 0.039; and OR = 0.71, 95% CI: 0.56-0.89, P = 0.004, respectively), but no statistical differences in ICU and ventilator free days between different preadmission locations. Races other than white and black had a statistically higher mortality (28- and 60-day mortality: OR = 1.47, 95% CI: 1.09-1.98, P = 0.011; and OR 1.53, 95% CI: 1.15-2.04, P = 0.004, respectively). Between whites and blacks, females and males there were no statistically significant differences in all outcomes. CONCLUSION: Older patients and races other than blacks and whites have higher mortality associated with ARDS. Mortality is affected by patients preadmission location. There are no differences in outcome in relation to the type of ICU, gender, or between blacks and whites. © 2017 Annals of Thoracic Medicine | Published by Wolters Kluwer - Medknow.
Keywords: Acute respiratory distress syndrome; demographics; outcome

Biases in recommendations for and acceptance of prostate biopsy significantly affect assessment of prostate cancer risk factors: Results from two large randomized clinical trials - Tangen, C.M.; Goodman, P.J.; Till, C.; Schenk, J.M.; Lucia, M.S.; Thompson, I.M., Jr. (Journal of Clinical Oncology, 2016)
Purpose To identify factors related to who undergoes a prostate biopsy in a screened population and to estimate the impact of biopsy verification on risk factor-prostate cancer associations. Patients and Methods Men who were screened regularly from the placebo arms of two large prostate cancer prevention trials (Prostate Cancer Prevention Trial [PCPT] and Selenium and Vitamin E Cancer Prevention Trial [SELECT]) were examined to define incident prostate cancer cohorts. Because PCPT had an end-ofstudy biopsy, prostate cancer cases were categorized by a preceding prostate-specific antigen/digital rectal examination prompt (yes/no) and noncases by biopsy-proven negative status (yes v no). We estimated the association of risk factors (age, ethnicity, family history, body mass index, medication use) with prostate cancer and quantified differences in risk associations across cohorts. Results Men 60 to 69 years of age, those with benign prostatic hyperplasia, and those with a family history of prostate cancer were more likely, and those with a higher body mass index ($ 25), diabetes, or a smoking history were less likely, to undergo biopsy, adjusting for age and longitudinal prostatespecific antigen and digital rectal examination. Medication use, education, and marital status also influenced who underwent biopsy. Some risk factor estimates for prostate cancer varied substantially across cohorts. Black (v other ethnicities) had odds ratios (ORs) that varied from 1.20 for SELECT (community screening standards, epidemiologic-like cohort) to 1.83 for PCPT (end-of-study biopsy supplementedwith imputed end points). Statin use in SELECT provided anOR of 0.65 and statin use in in PCPT provided an OR of 0.99, a relative difference of 34%. Conclusion Among screenedmen enrolled in prostate cancer prevention trials, differences in risk factor estimates for prostate cancer likely underestimate the magnitude of bias found in other cohorts with varying screening and biopsy recommendations and acceptance. Risk factors for prostate cancer derived from epidemiologic studies not only may be erroneous but may lead to misdirected research efforts. © 2016 by American Society of Clinical Oncology.

Individual Patient Data Analysis of Randomized Clinical Trials: Impact of Black Race on Castration-resistant Prostate Cancer Outcomes - Spratt, D.E.; Chen, Y.-W.; Mahal, B.A.; Osborne, J.R.; Zhao, S.G.; Morgan, T.M.; Palapattu, G.; Feng, F.Y.; Nguyen, P.L. (European Urology Focus, 2016)
Background Population data suggest that black men have a higher risk of dying from prostate cancer (PCa) than other racial ethnicities. Objective To examine the impact of black race on progression-free survival (PFS) and overall survival (OS) among men with metastatic castration-resistant PCa (mCRPC) enrolled in randomized controlled trials (RCTs). Design, setting, and participants A pooled analysis was performed on individual patient data from five modern PCa RCTs available from Project Data Sphere. Outcome measurements and statistical analysis Adjusted hazard ratios (HRs) were calculated to compare black and white race regarding PFS and OS. Subgroup analyses of mCRPC trials were performed based on the control arm treatments (mitoxantrone or docetaxel). Relevant covariates were used for adjustment in all analyses. Results and limitations A total of 1613 patients were included; 77 were black (4.7%). No significant differences between black and white men's baseline characteristics were noted regarding age, performance status, or pretreatment prostate-specific antigen. The pooled HRs for black race for OS and PFS were 1.01 (95% confidence interval [CI], 0.73–1.35) and 1.29 (95% CI, 0.95–1.76), respectively. The median OS for black compared with white men was 254 versus 238 d (p = 0.92), respectively, with mitoxantrone and 581 versus 546 d (p = 0.53), respectively, with docetaxel. The primary limitation was the relatively small number of black men enrolled in mCRPC clinical trials. Conclusions In the context of RCTs, in which patients receive generally uniform treatment, a significant difference in OS for black men could not be detected in mCRPC. Black men continue to be dramatically underrepresented in RCTs, and efforts are needed to increase minority accrual to these trials. Patient summary We looked at the outcomes of men treated in randomized controlled trials to determine the impact of black race on survival. We found that in the context of modern clinical trials, there does not appear to be a significant difference in survival between black and white races; however, a trend for greater progression in black men was noted. © 2016 European Association of Urology
Keywords: Disparity; Prostate cancer; Randomized controlled trial

Research engagement among black men with prostate cancer - Toms, C.; Cahill, F.; George, G.; Van Hemelrijck, M. (ecancermedicalscience, 2016)
Background: Black men are three times more likely to develop prostate cancer (PCa) and often present with more aggressive disease. Nevertheless, black men are consistently underrepresented in research studies. We aimed to get more insight into the reasons for this reduced recruitment, as it is important for future research to include results that are also applicable to black men with PCa. Methods: Two focus groups (n = 10 and n = 6) of black males currently under treatment for PCa at Guys Hospital, London, UK were held to gather information regarding the understanding of and exposure to research, as well as the barriers and facilitators for recruitment into research studies. Results: Barriers to recruitment included; mistrust of researchers, lack of understanding of the research process and the mechanisms of PCa and a reliance on herbal medicine. Suggested facilitators for recruitment improvement included thorough explanations of the research process, media advertisement and word of mouth. Financial incentives were also discussed but received mixed reception. Conclusion: We uncovered a number of barriers to recruitment of black men with PCa into research and accompanying strategies for improving involvement. Many are consistent with the literature, emphasising that current efforts have not been successful in ameliorating the concerns of the black community. Beliefs in herbal medicine and aversion to financial incentives appear to be novel themes, and so further insight into these issues could prove beneficial. © the authors; licensee ecancermedicalscience.
Keywords: Black ethnicity; Consent; Prostate cancer

Enrollment trends and disparity among patients with lung cancer in national clinical trials, 1990 to 2012 - Pang, H.H.; Wang, X.; Stinchcombe, T.E.; Wong, M.L.; Cheng, P.; Ganti, A.K.; Sargent, D.J.; Zhang, Y.; Hu, C.; Mandrekar, S.J.; Redman, M.W.; Manola, J.B.; et al. (Journal of Clinical Oncology, 2016)
Purpose: Under-representation of elderly, women, and racial/ethnic minority patients with cancer in clinical trials is of national concern. The goal of this study was to characterize enrollment trends and disparities by age, sex, and race/ethnicity in lung cancer trials. Methods: We analyzed data for 23,006 National Cancer Institute cooperative group lung cancer trial participants and 578,476 patients with lung cancer from the SEER registry from 1990 to 2012. The enrollment disparity difference (EDD) and enrollment disparity ratio (EDR) were calculated on the basis of the proportion of each subgroup in the trial population and the US lung cancer population. Annual percentage changes (APCs) in the subgroup proportions in each population were compared over time. Results: Enrollment disparity for patients ≥ 70 years of age with non-small-cell lung cancer improved from 1990 to 2012 (test of parallelism, P = .020), with a remaining EDD of 0.22 (95% CI, 0.19 to 0.25) and EDR of 1.65 (95% CI, 1.51 to 1.82) in 2010 to 2012. No improvement was seen for elderly patients with small-cell lung cancer (SCLC), with an APC of 0.20 (P = .714) among trial participants, despite a rising proportion of elderly patients with SCLC in the US population (APC, 0.32; P = .020). Enrollment disparity for women with lung cancer improved overall, with the gap closing by 2012 (EDD, 0.03 [95% CI, 0.00 to 0.06]; EDR, 1.07 [95% CI, 1.00 to 1.16]). Enrollment disparities persisted without significant improvement for elderly women, blacks, Asians/Pacific Islanders, and Hispanics. Conclusion: Under-representation in lung cancer trials improved significantly from 1990 to 2012 for elderly patients with non-small-cell lung cancer and for women, but ongoing efforts to improve the enrollment of elderly patients with SCLC and minorities are needed. Our study highlights the importance of addressing enrollment disparities by demographic and disease subgroups to better target under-represented groups of patients with lung cancer. © 2016 by American Society of Clinical Oncology.

A community-based trial of educational interventions with fecal immunochemical tests for colorectal cancer screening uptake among blacks in community settings - Christy, S.M.; Davis, S.N.; Williams, K.R.; Zhao, X.; Govindaraju, S.K.; Quinn, G.P.; Vadaparampil, S.T.; Lin, H.-Y.; Sutton, S.K.; Roethzeim, R.R.; Shibata, D.; Meade, C.D.; et al. (Cancer, 2016)
BACKGROUND: Intervention studies among individuals in diverse community settings are needed to reduce health disparities in colorectal cancer (CRC) screening and mortality rates. The current study compared the efficacy of 2 intervention conditions promoting CRC screening among black individuals. METHODS: Black individuals ages 50 to 75 years (N = 330) were recruited in community settings in 4 Tampa Bay counties. After obtaining consent and conducting a baseline interview to assess sociodemographic and health-related variables, participants received either a culturally targeted CRC photonovella booklet plus a fecal immunochemical test (FIT) kit or a standard CRC screening brochure plus an FIT kit. The primary outcome was FIT kit screening uptake. RESULTS: FIT screening uptake at 6 months was 86.7% overall (90.3% in the brochure group and 81.9% in the photonovella group). Controlling for baseline between-group differences, there was no influence of intervention on FIT kit uptake (P =.756). Significant predictors of not returning an FIT kit included being unable to work (P =.010), having higher religious belief scores (P =.015), and living farther from the cancer center (P =.015). CONCLUSIONS: Providing FIT kits and educational print materials to black individuals in community settings resulted in high rates of CRC screening. The study also identified subgroups of participants who were less likely to return an FIT kit and provides insight for future interventions. Cancer 2016;122:3288–3296. © 2016 American Cancer Society. © 2016 American Cancer Society
Keywords: cancer screening; colorectal cancer; culturally targeted; intervention trial; minority health

Zinc intake and risk of prostate cancer: Case-control study and meta-analysis - Mahmoud, A.M.; Al-Alem, U.; Dabbous, F.; Ali, M.M.; Batai, K.; Shah, E.; Kittles, R.A. (PLoS ONE, 2016)
Zinc is an essential dietary element that has been implicated in the pathogenesis of prostate cancer, a cancer that disproportionately affects men of African descent. Studies assessing the association of zinc intake and prostate cancer have yielded inconsistent results. Furthermore, very little is known about the relationship between zinc intake and prostate cancer among African Americans. We examined the association between self-reported zinc intake and prostate cancer in a hospital-based case-control study of African Americans. We then compared our results with previous studies by performing a meta-analysis to summarize the evidence regarding the association between zinc and prostate cancer. Newly diagnosed African American men with histologically confirmed prostate cancer (n = 127) and controls (n = 81) were recruited from an urban academic urology clinic in Washington, DC. Controls had higher zinc intake, with a mean of 14 mg/day versus 11 mg/day for cases. We observed a non-significant, non-linear increase in prostate cancer when comparing tertiles of zinc intake (OR <6.5sv6.5-12.5mg/day 1.8, 95% CI: 0.6,5.6; OR <6.5 vs>12.5mg/day 1.3, 95% CI: 0.2,6.5). The pooled estimate from 17 studies (including 3 cohorts, 2 nested case-control, 11 case-control studies, and 1 randomized clinical trial, with a total of 111,199 participants and 11,689 cases of prostate cancer) was 1.07hi vs lo 95% CI: 0.98-1.16. Using a dose-response meta-analysis, we observed a non-linear trend in the relationship between zinc intake and prostate cancer (p for nonlinearity = 0.0022). This is the first study to examine the relationship between zinc intake in black men and risk of prostate cancer and systematically evaluate available epidemiologic evidence about the magnitude of the relationship between zinc intake and prostate cancer. Despite of the lower intake of zinc by prostate cancer patients, our meta-analysis indicated that there is no evidence for an association between zinc intake and prostate cancer. © 2016 Mahmoud et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Use of Cancer Genetics Services in African-American Young Breast Cancer Survivors - Jones, T.; Lockhart, J.S.; Mendelsohn-Victor, K.E.; Duquette, D.; Northouse, L.L.; Duffy, S.A.; Donley, R.; Merajver, S.D.; Milliron, K.J.; Roberts, J.S.; Katapodi, M.C. (American Journal of Preventive Medicine, 2016)
Introduction African-American women have higher rates of early-onset breast cancer compared with their Caucasian counterparts; yet, when diagnosed with breast cancer at a young age, they underuse genetic counseling and testing to manage their risk of developing future cancers. Methods Self-reported baseline data were collected between September 2012 and January 2013 and analyzed in 2014 from a subpopulation of 340 African-American young breast cancer survivors (YBCSs) enrolled in an RCT. YBCSs were diagnosed with invasive breast cancer or ductal carcinoma in situ between ages 20 and 45 years and were randomly selected from a statewide cancer registry. Logistic regression examined predictors of using cancer genetics services. Results Overall, 28% of the sample reported having genetic counseling and 21% reported having genetic testing, which were significantly lower (p≤0.005) compared with white/other YBCSs participating in the parent study. In a multivariate analysis, income was positively associated with counseling (B=0.254, p≤0.01) and testing (B=0.297, p≤0.01), whereas higher education levels (B=−0.328, p≤0.05) and lack of access to healthcare services owing to cost (B=−1.10, p≤0.03) were negatively associated with genetic counseling. Lower income and lack of care because of high out-of-pocket costs were commonly reported barriers. Conclusions Despite national recommendations for genetic evaluation among women with early-onset breast cancer, few African-American YBCSs reported undergoing genetic counseling and testing. Most reported that their healthcare provider did not recommend these services. Interventions addressing patient, provider, and structural healthcare system barriers to using genetic counseling and testing in this population are needed. © 2016 American Journal of Preventive Medicine

Cluster Randomized Trial of a Church-Based Peer Counselor and Tailored Newsletter Intervention to Promote Colorectal Cancer Screening and Physical Activity Among Older African Americans - Leone, L.A.; Allicock, M.; Pignone, M.P.; Walsh, J.F.; Johnson, L.-S.; Armstrong-Brown, J.; Carr, C.C.; Langford, A.; Ni, A.; Resnicow, K.; Campbell, M.K. (Health Education and Behavior, 2016)
Action Through Churches in Time to Save Lives (ACTS) of Wellness was a cluster randomized controlled trial developed to promote colorectal cancer screening and physical activity (PA) within urban African American churches. Churches were recruited from North Carolina (n = 12) and Michigan (n = 7) and were randomized to intervention (n = 10) or comparison (n = 9). Intervention participants received three mailed tailored newsletters addressing colorectal cancer screening and PA behaviors over approximately 6 months. Individuals who were not up-to-date for screening at baseline could also receive motivational calls from a peer counselor. The main outcomes were up-to-date colorectal cancer screening and Metabolic Equivalency Task (MET)-hours/week of moderate–vigorous PA. Multivariate analyses examined changes in the main outcomes controlling for church cluster, gender, marital status, weight, and baseline values. Baseline screening was high in both intervention (75.9%, n = 374) and comparison groups (73.7%, n = 338). Screening increased at follow-up: +6.4 and +4.7 percentage points for intervention and comparison, respectively (p =.25). Baseline MET-hours/week of PA was 7.8 (95% confidence interval [6.8, 8.7]) for intervention and 8.7 (95% confidence interval [7.6, 9.8]) for the comparison group. There were no significant changes (p =.15) in PA for intervention (−0.30 MET-hours/week) compared with the comparison (−0.05 MET-hours/week). Among intervention participants, PA increased more for those who participated in church exercise programs, and screening improved more for those who spoke with a peer counselor or recalled the newsletters. Overall, the intervention did not improve PA or screening in an urban church population. These findings support previous research indicating that structured PA opportunities are necessary to promote change in PA and churches need more support to initiate effective peer counselor programs. © 2015, © 2015 Society for Public Health Education.
Keywords: African American; church-based; colorectal cancer screening; peer counseling; physical activity; tailored health messages

Colorectal Cancer Screening in Vulnerable Patients: Promoting Informed and Shared Decisions - Brenner, A.T.; Hoffman, R.; McWilliams, A.; Pignone, M.P.; Rhyne, R.L.; Tapp, H.; Weaver, M.A.; Callan, D.; de Hernandez, B.U.; Harbi, K.; Reuland, D.S. (American Journal of Preventive Medicine, 2016)
Introduction Low-income, low-literacy, limited English-proficient populations have low colorectal cancer (CRC) screening rates and experience poor patient-provider communication and decision-making processes around screening. The purpose of this study was to test the effect of a CRC screening decision aid on screening-related communication and decision making in primary care visits. Study design RCT with data collected from patients at baseline and immediately after the provider encounter. Setting/participants Patients aged 50–75 years, due for CRC screening, were recruited from two safety net clinics in North Carolina and New Mexico (data collection, January 2014–September 2015; analysis, 2015). Intervention Participants viewed a CRC screening decision aid or a food safety (control) video immediately before their provider encounter. Main outcome measures CRC screening-related knowledge, discussion, intent, test preferences, and test ordering. Results The study population (N=262) had a mean age of 58.3 years and was 66% female, 61% Latino, 17% non-Latino black, and 16% non-Latino white. Among Latino participants, 71% preferred Spanish. Compared with controls, intervention participants had greater screening-related knowledge (on average 4.6 vs 2.8 of six knowledge items correct, adjusted difference [AD]=1.8, 95% CI=1.5, 2.1) and were more likely to report screening discussion (71.0% vs 45.0%, AD=26.1%, 95% CI=14.3%, 38.0%) and high screening intent (93.1% vs 84.7%, AD=9.0%, 95% CI=2.0%, 16.0%). Intervention participants were more likely to indicate a specific screening test preference (93.1% vs 68.0%, AD=26.5%, 95% CI=17.2%, 35.8%) and to report having a test ordered (56.5% vs 32.1%, AD=25.8%, 95% CI=14.4%, 37.2%). Conclusions Viewing a CRC screening decision aid before a primary care encounter improves knowledge and shared decision making around screening in a racially, ethnically, and linguistically diverse safety net clinic population. Trial registration This study is registered at www.clinicaltrials.gov NCT02054598. © 2016 American Journal of Preventive Medicine

Impact of race, ethnicity, and BMI on achievement of pathologic complete response following neoadjuvant chemotherapy for breast cancer: a pooled analysis of four prospective Alliance clinical trials (A151426) - Warner, E.T.; Ballman, K.V.; Strand, C.; Boughey, J.C.; Buzdar, A.U.; Carey, L.A.; Sikov, W.M.; Partridge, A.H. (Breast Cancer Research and Treatment, 2016)
Previous studies demonstrated poor response to neoadjuvant systemic therapy (NST) for breast cancer among black women and women who are overweight or obese, but this may be due to chemotherapy underdosing. We assessed associations of race, ethnicity, and body mass index (BMI) with pathologic complete response (pCR) in clinical trial populations. 1797 women enrolled in four NST trials (CALGB 40601, 40603; ACOSOG Z1041, Z1071) were included. Tumor subtypes were defined by estrogen receptor (ER) and HER2 status. Logistic regression generated odds ratios (OR) and 95 % confidence intervals (CI) for the associations of race, ethnicity, and BMI with in-breast pCR adjusting for subtype, study arm, lymph node status, tumor size, and tumor grade. 253 (14.1 %) were black, 199 (11.1 %) Hispanic, 520 (28.9 %) overweight, and 743 (41.4 %) obese. Compared to whites, Blacks and Hispanics were more likely to be obese and Blacks were more likely to have triple-negative cancer. pCR rates differed significantly by tumor subtype. In multivariate analyses, neither race (black vs white: OR 1.18, 95 % CI 0.85–1.62) nor ethnicity (Hispanic vs non-Hispanic; OR 1.30, 95 % CI 0.67–2.53) were significant predictors of pCR overall or by subtype. Overweight and obese women had lower pCR rates in ER+/HER2+, but higher pCR rates in ER−/HER2+ cancers. There was no difference in pCR according to race or ethnicity. Overall, there was no major difference in pCR rates by BMI. These findings suggest that pCR with optimally dosed NST is a function of tumor, rather than patient, biology. © 2016, Springer Science+Business Media New York.
Keywords: Body mass index; Breast cancer; Ethnicity; Pathologic complete response; Race

Black hood assisted colonoscopy for detection of colorectal polyps: A prospective randomized controlled study - Huang, R.-X.; Xiao, Z.-L.; Li, F.; Ji, D.-N.; Zhou, J.; Xiang, P.; Bao, Z.-J. (European Review for Medical and Pharmacological Sciences, 2016)
OBJECTIVE: Colonoscopy is considered as a standard method for detecting various kinds of colorectal polyps. However, conventional colonoscopy (CC) still has chances to miss some lesions. Some scholars have already repor ted that transparent hood assisted colonoscopy (THAC) can improve the detection rate of colorectal polyps. However, the efficacy of detection of colorectal polyps with black hood assisted colonoscopy (BHAC) is still unclear. In this study, BHAC was compared with CC for evaluating the efficacy of detection of colorectal polyps. PATIENTS AND METHODS: Between Sep 2014 and Apr 2015, 542 patients underwent CC and meanwhile 534 patients underwent BHAC were enrolled into this prospective randomized controlled study. Comparison of baseline characteristics, cecal intubation time, withdrawal time, total number of detected polyps, detection rate of polyps, location, size, morphology and pathological diagnosis of polyps between these two groups was performed. RESULTS: Cecal intubation time was significantly shorter in BHAC group than in CC group (6.31 ± 3.51 min vs. 7.05 ± 4.15 min, p = 0.002). The total number of detected polyps and detection rate of polyps were significantly higher in BHAC group than in CC group (349/65.36% vs. 264/48.71%, p = 0.004). CONCLUSIONS: Compared with CC, BHAC could significantly improve the detection rate of colorectal polyps, and cecal intubation time was significantly reduced by BHAC.
Keywords: Black hood; Colonoscopy; Colorectal polyps

Factors associated with continuous low-dose heparin infusion for central venous catheter patency in critically ill children worldwide - Onyeama, S.-J.N.; Hanson, S.J.; Dasgupta, M.; Hoffmann, R.G.; Faustino, E.V.S. (Pediatric Critical Care Medicine, 2016)
Objectives: To identify patient, hospital, and central venous catheter factors that may influence the use of low-dose heparin infusion for central venous catheter patency in critically ill children. Design: Secondary analysis of an international multicenter observational study. Setting: Fifty-nine PICUs over four study dates in 2012, involving seven countries. Patients: Children less than 18 years old with a central venous catheter who were admitted to a participating unit and enrolled in the completed Prophylaxis against Thrombosis Practice study were included. All overflow patients were excluded. Interventions: None. Measurements and Main Results: Of the 2,484 patients in the Prophylaxis against Thrombosis Practice study, 1,312 patients had a central venous catheter. Five hundred seven of those patients used low-dose heparin infusion. The frequency of low-dose heparin infusion was compared across various patient, hospital, and central venous catheter factors using chi-square, Mann-Whitney U, and Fisher exact tests. In the multivariate analysis, age was not a significant factor for low-dose heparin infusion use. Patients with pulmonary hypertension had decreased low-dose heparin infusion use, whereas those with active surgical or trauma diagnoses had increased low-dose heparin infusion use. All centrally inserted central venous catheters were more likely to use low-dose heparin infusion when compared with peripherally inserted central venous catheters. The Asia-Pacific region showed increased low-dose heparin infusion use, along with community hospitals and smaller ICUs (< 10 beds). Conclusions: Patient, central venous catheter, and hospital factors are associated with the use of low-dose heparin infusion in critically ill children. Further study is needed to evaluate the efficacy and persistence of low-dose heparin infusion use. © 2016 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: anticoagulation; central venous access device; critical care; intensive care units, pediatric; pediatrics; venous thromboembolism

Systems analysis of the prostate transcriptome in African-American men compared with European-American men - Hardiman, G.; Savage, S.J.; Hazard, E.S.; Wilson, R.C.; Courtney, S.M.; Smith, M.T.; Hollis, B.W.; Halbert, C.H.; Gattoni-Celli, S. (Pharmacogenomics, 2016)
Aim: African-Americans (AA) have increased prostate cancer risk and a greater mortality rate than European-Americans (EA). AA exhibit a high prevalence of vitamin D deficiency. We examined the global prostate transcriptome in AA and EA, and the effect of vitamin D3 supplementation. Patients & methods: Twenty-seven male subjects (ten AA and 17 EA), slated to undergo prostatectomy were enrolled in the study. Fourteen subjects received vitamin D3 (4000 IU daily) and 13 subjects received placebo for 2 months prior to surgery. Results: AA show higher expression of genes associated with immune response and inflammation. Conclusion: Systems level analyses support the concept that Inflammatory processes may contribute to disease progression in AA. These transcripts can be modulated by a short course of vitamin D3 supplementation. © 2016 Future Medicine Ltd.
Keywords: African-American; health disparities; prostate; RNA-seq; transcription; Vitamin D

Promoting Mammography with African-American Women in the Emergency Department Using Lay Health Workers - Hatcher, J.; Schoenberg, N.E.; Dignan, M.; Rayens, M.K. (Journal of National Black Nurses' Association : JNBNA, 2016)
The objective of this study was to test the efficacy of a pilot intervention to increase mammography utilization among African-American women recruited from those waiting in the emergency department (ED)for non-urgent complaints. In a 3-armed pilot of a randomized controlled trial we compared the effects of a brief motivational interview delivered by a lay health worker with those of a culturally targeted brochure and a usual care control group. The results showed that one quarter (23%) of the sample reported having never had a mammogram prior to the study. There was no group difference by mammography status at the 3-month interview. More than one quarter of those retained in the study indicated they had received a mammogram during the study (27.4%). The conclusions from the study were that lay health workers are a valuable asset and may be used in innovative settings such as the ED to increase screening among vulnerable populations.

Tamoxifen dose escalation in patients with diminished CYP2D6 activity normalizes endoxifen concentrations without increasing toxicity - Hertz, D.L.; Deal, A.; Ibrahim, J.G.; Walko, C.M.; Weck, K.E.; Anderson, S.; Magrinat, G.; Olajide, O.; Moore, S.; Raab, R.; Carrizosa, D.R.; Corso, S.; et al. (Oncologist, 2016)
Background. Polymorphic CYP2D6 is primarily responsible for metabolic activation of tamoxifen to endoxifen. We previously reported that by increasing the daily tamoxifen doseto 40mg/day in CYP2D6 intermediate metabolizer (IM), but not poor metabolizer (PM), patients achieve endoxifen concentrations similar to those of extensive metabolizer patients on 20 mg/day. We expanded enrollment to assess the safety of CYP2D6 genotypeguided dose escalation and investigate concentration differences between races. Methods. PM and IM breast cancer patients currently receiving tamoxifen at 20 mg/day were enrolled for genotype-guided escalation to 40 mg/day. Endoxifen was measured at baseline and after 4 months. Quality-of-life datawere collected using the Functional Assessment of Cancer Therapy-Breast (FACT-B) and Breast Cancer Prevention Trial Menopausal Symptom Scale at baseline and after 4 months. Results. In 353 newly enrolled patients, genotype-guided dose escalation eliminated baseline concentration differences in IM (p = .08), but not PM (p = .009), patients. Endoxifen concentrations were similar in black and white patients overall (p = .63) and within CYP2D6 phenotype groups (p>.05). In the quality-oflife analysis of 480 patients, dose escalation did not meaningfully diminish quality of life; infact,improvements were seen in several measures including the FACT Breast Cancer subscale (p 5 .004) and limitations in range of motion (p>.0001) in IM patients. Conclusion. Differences in endoxifen concentration during treatment can be eliminated by doubling the tamoxifen dose in IM patients, without an appreciable effecton quality of life. Validation of the association between endoxifen concentration and efficacy or prospective demonstration of improvedefficacy is necessary to warrant clinical uptake of this personalized treatment strategy. © AlphaMed Press 2016.
Keywords: CYP2D6; Endoxifen; Genotype; Pharmacogenetics; Quality of life; Race; Tamoxifen; Toxicity

Baseline subject characteristics predictive of compliance with study-mandated prostate biopsy in men at risk of prostate cancer: Results from REDUCE - Fischer, S.; Sun, S.; Howard, L.E.; Moreira, D.M.; Castro-Santamaria, R.; Andriole, G.L.; Vidal, A.C.; Freedland, S.J. (Prostate Cancer and Prostatic Diseases, 2016)
Background:Study compliance is crucial when the study outcome is determined by an invasive procedure, such as prostate biopsy. To investigate predictors of compliance in study-mandated prostate biopsies, we analyzed demographic, clinical and reported lifestyle data from the REDUCE trial.Methods:We retrospectively identified 8025 men from REDUCE with at least 2 years of follow-up, and used multivariable logistic regression to test the association between baseline demographic and clinical characteristics and undergoing the study-mandated prostate biopsy at 2 years. We then examined whether missing any of these data was associated with undergoing a biopsy.Results:In REDUCE, 22% of men did not undergo a 2-year biopsy. On multivariable analysis, the non-North American region was predictive of 42-44% increased likelihood of undergoing a 2-year biopsy (P≤0.001). Being enrolled at a center that enrolled >10 subjects (2nd and 3rd tertile) was associated with a 42-48% increased likelihood of undergoing a 2-year biopsy (P<0.001). In addition, black race predicted 44% lower rate of on-study 2-year biopsy (odds ratio (OR)=0.56; P=0.001). Finally, missing one or more baseline variables was associated with a 32% decreased likelihood of undergoing a 2-year biopsy (OR=0.68; P<0.001).Conclusions:In REDUCE, men outside North America, those at higher volume centers and those with complete baseline data were more likely to undergo study-mandated 2-year biopsies. Given prostate biopsy is becoming increasingly utilized as an endpoint in trials that are often multi-national, regional differences in compliance should be considered when designing future trials. Likewise, efforts are needed to ensure compliance in low-volume centers or among subjects missing baseline data. © 2016 Macmillan Publishers Limited.

National trends in nonoperative management of rectal adenocarcinoma - Ellis, C.T.; Samuel, C.A.; Stitzenberg, K.B. (Journal of Clinical Oncology, 2016)
Purpose Neoadjuvant chemoradiation for stage II/III rectal cancer results in up to 49% of patients with a clinical complete response. As a result, many have questioned whether surgery can be omitted for this group of patients. Currently, there is insufficient evidence for chemoradiation only, or nonoperative management (NOM), to support its adoption. Despite this, anecdotal evidence suggests there is a trend toward increased use of NOM. Our objective was to examine the use of NOM for rectal cancer over time, as well as the patient- And facility-level factors associated with its use. Methods We included all incident cases of invasive, nonmetastatic rectal adenocarcinoma reported to the National Cancer Database from 1998 to 2010. We performed univariate and multivariate analyses to assess for NOM use over time, as well as associated patient- And facility-level factors. Results A total of 146,135 patients met the inclusion criteria: 5,741 had NOM and 140,394 had surgery with or without additional therapy. From 1998 to 2010, NOM doubled, from 2.4% to 5% of all cases annually. Patients who were black (adjusted odds ratio [AOR], 1.71; 95% CI, 1.57 to 1.86), uninsured (AOR, 2.35; 95% CI, 2.08 to 2.65) or enrolled in Medicaid (AOR, 2.10; 95% CI, 1.90 to 2.33), or treated at low-volume facilities (AOR, 1.53; 95% CI, 1.42 to 1.64) were more likely to receive NOM than were patients who were white, privately insured, and treated at a high-volume facility, respectively. Conclusion NOM demonstrates promise for the treatment of rectal cancer; currently, however, the most appropriate strategy is to pursue this approach with well-informed patients in the context of a clinical trial. We observed evidence of increasing NOM use, with this increase occurring more frequently in black and uninsured/Medicaid patients, raising concern that increased NOM use may actually represent increasing disparities in rectal cancer care rather than innovation. Further studies are needed to assess survival differences by treatment strategy. © 2016 by American Society of Clinical Oncology.

Effects of adjuvant chemotherapy on recurrence, survival, and quality of life in stage II colon cancer patients: a 24-month follow-up - Lewis, C.; Xun, P.; He, K. (Supportive Care in Cancer, 2016)
Purpose: The purpose of this cohort study was to investigate the association of adjuvant chemotherapy with quality of life (QoL), survival, and recurrence over the 24 months following diagnosis in stage II colon cancer patients. Methods: Overall, 453 patients were recruited from North Carolina from 2009 to 2011 and interviewed with a closed-ended survey detailing quality of life, health behaviors, treatment, and cancer recurrence at three times points: diagnosis, 12-, and 24-months post-diagnosis; mortality was obtained via the National Death Index. Results: In sum, 265 patients received chemotherapy. Receipt of chemotherapy exhibited an inverse association with total Functional Assessment of Cancer Treatment (FACT)-General (P < 0.01), FACT-Colorectal (P < 0.01), physical (P < 0.01), emotional (P = 0.02), and functional (P < 0.01) well-being; the inverse association between receiving chemotherapy and emotional well-being persisted for Caucasians but not African Americans (Pinteraction = 0.049). Those who received chemotherapy demonstrated significantly higher odds of cancer recurrence (odds ratio (OR) 2.74; 95 % confidence interval (CI) 1.18, 6.35) and all-cause mortality (OR: 1.95; 95 % CI: 1.05, 3.62). Conclusions: In this study, stage II colon cancer patients who received chemotherapy treatment were more likely to have poor QoL, recurrence, and all-cause mortality after 24 months compared to those who did not receive chemotherapy. Future research focusing on subtypes of chemotherapy treatment, as well as a longer follow-up period, is needed. © 2015, Springer-Verlag Berlin Heidelberg.
Keywords: Chemotherapy; Colon cancer; Quality of life; Recurrence; Survival

Inherited mutations in women with ovarian carcinoma - Norquist, B.M.; Harrell, M.I.; Brady, M.F.; Walsh, T.; Lee, M.K.; Gulsuner, S.; Bernards, S.S.; Casadei, S.; Yi, Q.; Burger, R.A.; Chan, J.K.; Davidson, S.A.; et al. (JAMA Oncology, 2016)
Importance: Germline Mutations in BRCA1 and BRCA2 Are Relatively Com. in Women with Ovarian, Fallopian Tube, and Peritoneal Carcinoma Causing A Greatly Increased Lifetime Risk of These Cancers, but the Frequency and Relevance of Inherited Mutations in Other Genes Is Less Well Characterized. Objective: to Determine the Frequency and Importance of Germline Mutations in Cancer-Assoc. Genes in OC. Des., Setting and Participants: A Stud. Pop. of 1915woman with OC and Available Germline DNA Were Identified from the Univ. OfWashington Gynecologic Tissue Bank and from Gynecologic Oncol. Grp. Phase III Clin. Trials 218 and 262 . Patients Were Enrolled at Diagn. and Were Not Selected for Age or Fam. Hist.. Germline DNA Was Sequenced from Women with OC Using A Targeted Capture and Multiplex Sequencing Assay. Main Outcomes and Measures: Mutation Frequencies in OCwere Compared with the Natl. Heart, Lung and Blood Inst. GO Exome Sequencing Proj. and the Exome Aggregation Consortium . Clin. Characteristics and Survival Were Assessed by Mutation Status. Results: Overall, the Median Age at Diagn. Was 60 Years in Patients Recruited from UW and 61 Years in Patients Recruited from the GOG Trials. A Higher No. of Black Women Were Recruited from the GOG Trials ; but in Patients Recruited from UW, There Was A Higher Proportion of Fallopian Tube Carcinomas ; Stage i and Ii Dis. ; and Nonserous Carcinomas . of 1915 Patients, 280 Had Mutations in BRCA1 , or BRCA2 , and 8 Had Mutations in DNA Mismatch Repair Genes. Mutations in BRIP1 , RAD51C , RAD51D , PALB2 , and BARD1 Were Significantly More Com. in Patients with OC Than in the ESP or ExAC, Present in 3.3%. Race, Histologic Subtype, and Dis. Site Were Not Predictive of Mutation Frequency. Patients with A BRCA2 Mutation from the GOG Trials Had Longer Progression-free Survival and Overall Survival Compared with Those Without Mutations. Conclusions and Relevance: of 1915 Patients with OC, 347 Carried Pathogenic Germline Mutations in Genes Assoc. with OC Risk. PALB2 and BARD1 Are Suspected OC Genes and Together with Estab. OC Genes Bring the Total No. of Genes Suspected to Cause Hered. OC to 11. Copyright © 2016 Amer. Med. Assoc.. All Rights Reserved.

Randomized sham-controlled pilot trial of weekly electro-acupuncture for the prevention of taxane-induced peripheral neuropathy in women with early stage breast cancer - Greenlee, H.; Crew, K.D.; Capodice, J.; Awad, D.; Buono, D.; Shi, Z.; Jeffres, A.; Wyse, S.; Whitman, W.; Trivedi, M.S.; Kalinsky, K.; Hershman, D.L. (Breast Cancer Research and Treatment, 2016)
To investigate the effect of electro-acupuncture (EA) as a non-pharmacological intervention to prevent or reduce chemotherapy-induced peripheral neuropathy (CIPN) in breast cancer patients undergoing chemotherapy of taxane. Women with stage I-III breast cancer scheduled to receive taxane therapy were randomized to receive a standardized protocol of 12 true or sham EA (SEA) weekly treatments concurrent with taxane treatment. Subjects completed the Brief Pain Inventory-Short Form (BPI-SF), Functional Assessment of Cancer Therapy-Taxane neurotoxicity subscale (FACT-NTX), and other assessments at baseline and weeks 6, 12, and 16. A total of 180 subjects were screened, 63 enrolled and 48 completed week 16 assessments. Mean age was 50 with 25 % white, 25 % black, and 43 % Hispanic; 52 % had no prior chemotherapy. At week 12, both groups reported an increase in mean BPI-SF worst pain score, but no mean differences were found between groups (SEA 2.8 vs. EA 2.6, P = .86). By week 16, the SEA group returned to baseline, while the EA group continued to worsen (SEA 1.7 vs. EA 3.4, P = .03). The increase in BPI-SF worst pain score was 1.62 points higher in the EA group than in the SEA group at week 16 (P = .04). In a randomized, sham-controlled trial of EA for prevention of taxane-induced CIPN, there were no differences in pain or neuropathy between groups at week 12. Of concern, subjects on EA had a slower recovery than SEA subjects. Future studies should focus on EA for treatment as opposed to prevention of CIPN. © 2016, Springer Science+Business Media New York.
Keywords: Acupuncture; Breast cancer; Chemotherapy-induced peripheral neuropathy; Electro-acupuncture; Taxane

Feasibility outcomes of a presurgical randomized controlled trial exploring the impact of caloric restriction and increased physical activity versus a wait-list control on tumor characteristics and circulating biomarkers in men electing prostatectomy for prostate cancer - Demark-Wahnefried, W.; Nix, J.W.; Hunter, G.R.; Rais-Bahrami, S.; Desmond, R.A.; Chacko, B.; Morrow, C.D.; Azrad, M.; Frugé, A.D.; Tsuruta, Y.; Ptacek, T.; Tully, S.A.; et al. (BMC Cancer, 2016)
Background: Obesity is associated with tumor aggressiveness and disease-specific mortality for more than 15 defined malignancies, including prostate cancer. Preclinical studies suggest that weight loss from caloric restriction and increased physical activity may suppress hormonal, energy-sensing, and inflammatory factors that drive neoplastic progression; however, exact mechanisms are yet to be determined, and experiments in humans are limited. Methods: We conducted a randomized controlled trial among 40 overweight or obese, newly-diagnosed prostate cancer patients who elected prostatectomy to explore feasibility of a presurgical weight loss intervention that promoted a weight loss of roughly one kg. week-1 via caloric restriction and physical activity, as well as to assess effects on tumor biology and circulating biomarkers. Measures of feasibility (accrual, retention, adherence, and safety) were primary endpoints. Exploratory aims were directed at the intervention's effect on tumor proliferation (Ki-67) and other tumor markers (activated caspase-3, insulin and androgen receptors, VEGF, TNFβ, NFκB, and 4E-BP1), circulating biomarkers (PSA, insulin, glucose, VEGF, TNFβ, leptin, SHBG, and testosterone), lymphocytic gene expression of corresponding factors and cellular bioenergetics in neutrophils, and effects on the gut microbiome. Consenting patients were randomized in a 1:1 ratio to either: 1) weight loss via a healthful, guidelines-based diet and exercise regimen; or 2) a wait-list control. While biological testing is currently ongoing, this paper details our methods and feasibility outcomes. Results: The accrual target was met after screening 101 cases (enrollment rate: 39.6 %). Other outcomes included a retention rate of 85 %, excellent adherence (95 %), and no serious reported adverse events. No significant differences by age, race, or weight status were noted between enrollees vs. non-enrollees. The most common reasons for non-participation were "too busy" (30 %), medical exclusions (21 %), and "distance" (16 %). Conclusions: Presurgical trials offer a means to study the impact of diet and exercise interventions directly on tumor tissue, and other host factors that are feasible and safe, though modifications are needed to conduct trials within an abbreviated period of time and via distance medicine-based approaches. Pre-surgical trials are critical to elucidate the impact of lifestyle interventions on specific mechanisms that mediate carcinogenesis and which can be used subsequently as therapeutic targets. Trial registration: NCT01886677. © 2016 Demark-Wahnefried et al.
Keywords: Diet; Exercise; Intervention; Obesity; Physical activity; Presurgical; Prostatic neoplasms; Weight loss

Excising Additional Margins at Initial Breast-Conserving Surgery (BCS) Reduces the Need for Re-excision in a Predominantly African American Population: A Report of a Randomized Prospective Study in a Public Hospital - Jones, V.; Linebarger, J.; Perez, S.; Gabram, S.; Okoli, J.; Bumpers, H.; Burns, B.; Mosunjac, M.; Rizzo, M. (Annals of Surgical Oncology, 2016)
Background: Margin status is an important prognostic factor for local recurrence after breast conserving surgery (BCS) for breast cancer. We designed a prospective randomized trial to evaluate the effect of shave margins on positive margins and locoregional recurrence (LRR). Methods: Patients were randomized to BCS or BCS with resection of 5 additional margins (BCS + M). Tumor margins were classified as negative [>2 mm for ductal carcinoma in situ (DCIS); >1 mm for invasive carcinoma] based on guidelines at the time of accrual. Results: A total of 75 patients with stage 0–III breast cancer (76 samples) were randomized, mean age 59.6 years with median follow-up 39.5 months. Overall, 21 patients (27.6 %) had positive margins: 14 had undergone BCS and 7 BCS + M (p = 0.005). Of the 21 patients with positive margins, 19 had DCIS on final pathology (OR 7.56; 95 % CI 1.52–37.51).All patients with positive margins were offered re-excision; 11 had negative final margins after re-excision surgery. Overall, 6 patients (8.3 %) developed LRR with recurrence being more common in the BCS group when compared with the BCS + M group (17.2 vs 2.3 %; p = 0.025). Conclusions: Taking additional cavity shave margins at the time of initial excision resulted in a reduction in positive margin rate, a decrease in return to operating room for re-excision, and lower LRR. © 2015, Society of Surgical Oncology.

Correlates of quality of life in overweight or obese breast cancer survivors at enrollment into a weight loss trial - Pakiz, B.; Ganz, P.A.; Sedjo, R.L.; Flatt, S.W.; Demark-Wahnefried, W.; Liu, J.; Wolin, K.Y.; Rock, C.L. (Psycho-Oncology, 2016)
Objective The purpose of this analysis was to examine the correlates of the physical and psychosocial domains of quality of life (QOL) in a cohort of breast cancer survivors participating in a weight loss intervention trial. Methods Correlates of QOL and psychosocial functioning were examined in 692 overweight or obese breast cancer survivors at entry into a weight loss trial. QOL was explored with three measures: Short-form 36 (SF-36), Impact of Cancer scale (IOC), and the Breast Cancer Prevention Trial (BCPT) symptom scales. Available data included information on weight and physical activity, as well as demographic and medical characteristics. Multivariate analyses were used to identify associations adjusted for other characteristics. Results In multivariate analysis, younger age was associated with higher negative impact scores (p < 0.0001). Hispanic, African-American, and Asian women had higher positive IOC impact scores compared with White non-Hispanic women (p < 0.01). Increased number of comorbidities was associated with lower physical and mental QOL scores (p < 0.01). Body mass index was not independently associated with QOL measures. Physical activity was directly associated with physical and mental QOL and IOC positive impact, and inversely related to IOC negative impact and Breast Cancer Prevention Trial symptom scales. Conclusions Quality-of-life measures in breast cancer survivors are differentially associated with demographic and other characteristics. When adjusted for these characteristics, degree of adiposity among overweight or obese women does not appear to be independently associated with QOL. Among overweight or obese breast cancer survivors, higher level of physical activity is associated with higher QOL across various scales and dimensions. © 2015 John Wiley & Sons, Ltd.

Enrolling Minority and Underserved Populations in Cancer Clinical Research - Wallington, S.F.; Dash, C.; Sheppard, V.B.; Goode, T.D.; Oppong, B.A.; Dodson, E.E.; Hamilton, R.N.; Adams-Campbell, L.L. (American Journal of Preventive Medicine, 2016)
Research suggests that community involvement is integral to solving public health problems, including involvement in clinical trials - a gold standard. Significant racial/ethnic disparities exist in the accrual of participants for clinical trials. Location and cultural aspects of clinical trials influence recruitment and accrual to clinical trials. It is increasingly necessary to be aware of defining characteristics, such as location and culture of the populations from which research participants are enrolled. Little research has examined the effect of location and cultural competency in adapting clinical trial research for minority and underserved communities on accrual for clinical trials. Utilizing embedded community academic sites, the authors applied cultural competency frameworks to adapt clinical trial research in order to increase minority participation in nontherapeutic cancer clinical trials. This strategy resulted in successful accrual of participants to new clinical research trials, specifically targeting participation from minority and underserved communities in metropolitan Washington, DC. From 2012 to 2014, a total of 559 participants enrolled across six nontherapeutic clinical trials, representing a 62% increase in the enrollment of blacks in clinical research. Embedding cancer prevention programs and research in the community was shown to be yet another important strategy in the arsenal of approaches that can potentially enhance clinical research enrollment and capacity. The analyses showed that the capacity to acquire cultural knowledge about patients - their physical locales, cultural values, and environments in which they live - is essential to recruiting culturally and ethnically diverse population samples. © 2016 American Journal of Preventive Medicine.

Effect of Patient Navigation on Breast Cancer Screening Among African American Medicare Beneficiaries: A Randomized Controlled Trial - Marshall, J.K.; Mbah, O.M.; Ford, J.G.; Phelan-Emrick, D.; Ahmed, S.; Bone, L.; Wenzel, J.; Shapiro, G.R.; Howerton, M.; Johnson, L.; Brown, Q.; Ewing, A.; et al. (Journal of General Internal Medicine, 2016)
BACKGROUND: There is growing evidence that patient navigation improves breast cancer screening rates; however, there are limited efficacy studies of its effect among African American older adult women. OBJECTIVE: To evaluate the effect of patient navigation on screening mammography among African American female Medicare beneficiaries in Baltimore, MD. DESIGN: The Cancer Prevention and Treatment Demonstration (CPTD), a multi-site study, was a randomized controlled trial conducted from April 2006 through December 2010. SETTING: Community-based and clinical setting. PARTICIPANTS: The CPTD Screening Trial enrolled 1905 community-dwelling African American female Medicare beneficiaries who were ≥65 years of age and resided in Baltimore, MD. Participants were recruited from health clinics, community centers, health fairs, mailings using Medicare rosters, and phone calls. INTERVENTIONS: Participants were randomized to either: printed educational materials on cancer screening (control group) or printed educational materials + patient navigation services designed to help participants overcome barriers to cancer screening (intervention group). MAIN MEASURE: Self-reported receipt of mammography screening within 2 years of the end of the study. KEY RESULTS: The median follow-up period for participants in this analysis was 17.8 months. In weighted multivariable logistic regression analyses, women in the intervention group had significantly higher odds of being up to date on mammography screening at the end of the follow-up period compared to women in the control group (odds ratio [OR] 2.26, 95 % confidence interval [CI]1.59–3.22). The effect of the intervention was stronger among women who were not up to date with mammography screening at enrollment (OR 3.63, 95 % CI 2.09–6.38). CONCLUSION: Patient navigation among urban African American Medicare beneficiaries increased self-reported mammography utilization. The results suggest that patient navigation for mammography screening should focus on women who are not up to date on their screening. © 2015, Society of General Internal Medicine.
Keywords: African American; mammography; patient navigation

Improved Bowel Preparation with Multimedia Education in a Predominantly African-American Population: A Randomized Study - Garg, S.; Girotra, M.; Chandra, L.; Verma, V.; Kaur, S.; Allawy, A.; Secco, A.; Anand, R.; Dutta, S.K. (Diagnostic and Therapeutic Endoscopy, 2016)
Background and Aim. Inadequate bowel preparation is a major impediment in colonoscopy quality outcomes. Aim of this study was to evaluate the role of multimedia education (MME) in improving bowel preparation quality and adenoma detection rate. Methods. This was an IRB-approved prospective randomized study that enrolled 111 adult patients undergoing outpatient screening or surveillance colonoscopy. After receiving standard colonoscopy instructions, the patients were randomized into MME group (n = 48) and control group (n = 46). The MME group received comprehensive multimedia education including an audio-visual program, a visual aid, and a brochure. Demographics, quality of bowel preparation, and colonoscopy findings were recorded. Results. MME group had a significantly better bowel preparation in the entire colon (OR 2.65, 95% CI 1.16-6.09) and on the right side of the colon (OR 2.74, 95% CI 1.12-6.71) as compared to control group (p < 0.05). Large polyps (>1 cm) were found more frequently in the MME group (11/31, 35.5% versus 0/13; p < 0.05). More polyps and adenomas were detected in MME group (57 versus 39 and 31 versus 13, resp.) but the difference failed to reach statistical significance. Conclusion. MME can lead to significant improvement in the quality of bowel preparation and large adenoma detection in a predominantly African-American population. © 2016 Shashank Garg et al.

Casting a wider net: Engaging community health worker clients and their families in cancer prevention - Roman, L.A.; Zambrana, R.E.; Ford, S.; Meghea, C.; Williams, K.P. (Preventing Chronic Disease, 2016)
Engaging family members in an intervention to prevent breast and cervical cancer can be a way to reach underserved women; however, little is known about whether family member recruitment reachesat-riskwomen. This study reports the kin relationship and risk characteristics of family members who chose to participate in the Kin KeeperSM cancer prevention intervention, delivered by community health workers (CHWs) via existing community programs. African American, Latina, and Arab family members reported risk factors for inadequate screening, including comorbid health conditions and inadequate breast or cervical cancer literacy. CHW programs can be leveraged to reach underserved families with cancer preventive interventions.

Phase II trial of abiraterone acetate plus prednisone in black men with metastatic prostate cancer - Tsao, C.-K.; Sfakianos, J.; Liaw, B.; Gimpel-Tetra, K.; Kemeny, M.; Bulone, L.; Shahin, M.; Oh, W.K.; Galsky, M.D. (Oncologist, 2016)
BACKGROUND: Self-identified black men have higher incidence and mortality from prostate cancer in the United States compared with white men but are dramatically underrepresented in clinical trials exploring novel therapies for metastatic castration-resistant prostate cancer (mCRPC). METHODS: Black men with mCRPC were treated with abiraterone acetate (AA), 1,000 mg daily, and prednisone (P), 5 mg twice daily. The primary objective was to determine antitumor activity (defined by a ≥ 30% decline in prostate-specific antigen [PSA] level) and to correlate germline polymorphisms in androgen metabolism genes with antitumor activity. Secondary objectives included determining safety, post-treatment changes in measurable disease, and time to disease progression. RESULTS: From April 2013 to March 2016, a total of 11 black men were enrolled and received AA plus P (AA+P); 7 of 10 evaluable patients were docetaxel naive. Post-treatment declines in PSA level of ≥ 30% were achieved in 90% of patients. The side effect profile was consistent with prior clinical trials exploring AA+P in mCRPC. Due to poor accrual, the study was closed prematurely with insufficient sample size for the planned pharmacogenetic analyses. CONCLUSION: In this small prospective study terminated for poor accrual, the safety and activity of AA+P in black men with mCRPC was similar to that reported in prior studies exploring AA in largely white populations. Further efforts are needed to address underrepresentation of black men in mCRPC trials. © AlphaMed Press 2016.

Study design and protocol for moving forward: A weight loss intervention trial for African-American breast cancer survivors - Stolley, M.R.; Sharp, L.K.; Fantuzzi, G.; Arroyo, C.; Sheean, P.; Schiffer, L.; Campbell, R.; Gerber, B. (BMC Cancer, 2015)
Background: Breast cancer survival rates are significantly lower among African-American women compared to white women. In addition, African-American women with breast cancer are more likely than white women to die from co-morbid conditions. Obesity is common among African-American women, and it contributes to breast cancer progression and the development and exacerbation of many weight-related conditions. Intervening upon obesity may decrease breast cancer and all-cause mortality among African-American breast cancer survivors. Methods/Design: Moving Forward is a weight loss intervention being evaluated in a randomized trial with a projected sample of 240 African American breast cancer survivors. Outcomes include body mass index, body composition, waist:hip ratio, and behavioral, psychosocial and physiological measures. Survivors are randomized to either a 6-month guided weight loss intervention that involves twice weekly classes and text messaging or a self-guided weight loss intervention based on the same materials offered in the guided program. The guided intervention is being conducted in partnership with the Chicago Park District at park facilities in predominantly African-American neighborhoods in Chicago. Recruitment strategies include direct contact to women identified in hospital cancer registries, as well as community-based efforts. Data collection occurs at baseline, post-intervention (6 months) and at a 12-month follow-up. Discussion: This study evaluates a community-based, guided lifestyle intervention designed to improve the health of African-American breast cancer survivors. Few studies have addressed behavioral interventions in this high-risk population. If successful, the intervention may help reduce the risk for breast cancer recurrence, secondary cancers, and co-morbid conditions, as well as improve quality of life. Trial registration: U.S. Clinicaltrials.gov number: NCT02482506 , April 2015 © 2015 Stolley et al.
Keywords: African-American; Breast cancer; Survivorship; Weight loss

Feasibility, acceptability, and preliminary efficacy of a technology-assisted psychosocial intervention for racially diverse men with advanced prostate cancer - Yanez, B.; McGinty, H.L.; Mohr, D.C.; Begale, M.J.; Dahn, J.R.; Flury, S.C.; Perry, K.T.; Penedo, F.J. (Cancer, 2015)
BACKGROUND The utility of psychosocial interventions in reducing symptom burden and improving health-related quality of life (HRQOL) for men with localized prostate cancer has been demonstrated. However, studies have yet to demonstrate the efficacy of interventions in advanced prostate cancer (APC). This study examined the feasibility, acceptability, and preliminary efficacy of a technology-assisted, 10-week, group-based psychosocial intervention for diverse men with APC. METHODS The participants were 74 men (mean age, 68.84 years; non-Hispanic white, 57%; black, 40.5%) who were randomized to a cognitive-behavioral stress management (CBSM) treatment or health promotion (HP) attention-control condition. The participants were assessed at the baseline, weekly throughout the 10-week program, and 6 months after the baseline. Outcomes were assessed with the Patient-Reported Outcomes Measurement Information System along with established measures of HRQOL, CBSM intervention targets (eg, relaxation skills), and patient-reported acceptability. RESULTS Feasibility was demonstrated through good retention rates (>85%) and acceptable average attendance rates (>70%), and acceptability was demonstrated through very favorable weekly session evaluations (mean score, 4/5) and exit surveys (mean score, 3.6/4). Men randomized to the CBSM condition reported significant reductions (P <.05) in depressive symptoms and improvements in relaxation self-efficacy (P <.05) at the 6-month follow-up. CBSM participants reported trends for improvement in distress and functional well-being (P <.08) in comparison with those in the HP condition. Effect sizes ranged from medium (0.54) to large (1.87) and, in some instances, were clinically meaningful. CONCLUSIONS Technology-based CBSM interventions among diverse men with APC may be feasible, acceptable, and efficacious. Cancer 2015;121:4407-15. © 2015 American Cancer Society.
Keywords: eHealth; prostate cancer; psychosocial aspects; quality of life; randomized trial

Phase II Trial of Carboplatin, Everolimus, and Prednisone in Metastatic Castration-resistant Prostate Cancer Pretreated with Docetaxel Chemotherapy: A Prostate Cancer Clinical Trial Consortium Study - Vaishampayan, U.; Shevrin, D.; Stein, M.; Heilbrun, L.; Land, S.; Stark, K.; Li, J.; Dickow, B.; Heath, E.; Smith, D.; Fontana, J. (Urology, 2015)
Objective To conduct a phase II trial of the combination of carboplatin, prednisone, and everolimus in metastatic castrate-resistant prostate cancer (mCRPC) as mTOR inhibition can overcome resistance to chemotherapy in prostate cancer. Methods Patients with progressive mCRPC pretreated with docetaxel-based regimen were eligible. Performance status of 0-1 and adequate bone marrow, renal, and liver function were required. Primary end point was time to progression. Treatment consisted of carboplatin (starting dose equal to area under the curve (AUC of 5) intravenously every 21 days along with oral everolimus 5 mg once daily and prednisone 5 mg twice daily. Results Twenty-six patients were enrolled with median age of 69 years with 8 patients of African American origin. Grade 3 or 4 thrombocytopenia or neutropenia in 4 of 6 initial patients required dose adjustment of carboplatin to AUC of 4 for subsequent patients. There were no pharmacokinetic interactions between carboplatin and everolimus. The median time to progression was 2.5 months (90% confidence interval [CI], 1.8-4.3 months), and median overall survival was 12.5 months (90% CI, 7.7-18.7 months). Of 10 patients, 8 that demonstrated positive nuclear phosphorylated AKT (pAKT) staining on immunohistochemistry progressed within 9 weeks, whereas 2 patients with negative staining continued without progression for prolonged durations of 30 and 48 weeks. TSC1 gene mutations did not correlate with clinical outcome. Conclusion The addition of the mTOR inhibitor everolimus to carboplatin demonstrated minimal clinical efficacy in metastatic prostate cancer. pAKT testing warrants further evaluation as a predictive marker of response to everolimus therapy. © 2015 Elsevier Inc.

Knowledge and attitudes regarding clinical trials and willingness to participate among prostate cancer patients - Kaplan, C.P.; Nápoles, A.M.; Narine, S.; Gregorich, S.; Livaudais-Toman, J.; Nguyen, T.; Leykin, Y.; Roach, M.; Small, E.J. (Contemporary Clinical Trials, 2015)
Background: Enrollment of minorities in clinical trials remains low. Through a California population-based study of men with early stage prostate cancer, we examined the relationships between race/ethnicity and 1) attitudes, 2) knowledge and 3) willingness to participate in clinical trials. Methods: From November 2011-November 2012, we identified all incident cases of prostate cancer in African American, Latino, and Asian American men ages 18-75. years, and a random sample of white men diagnosed in 2008, through the California Cancer Registry, living within 60 miles of a site offering ≥. 1 clinical trial. Participants completed a 30-min telephone interview in English, Spanish, or Chinese. In this cross-sectional population-based study, multivariable logistic regression was used to estimate associations between race/ethnicity and 1) attitudes, 2) knowledge and 3) willingness to participate. Results: Of 855 participants, 52% were ≥. 65 years, 42% were white, 24% Latino, 19% African American and 15% Asian American. The majority (81%) had medium-to-high health literacy. Compared to non-Latino white men, African American men were less likely to have above average knowledge of clinical trials (OR. = 0.55; CI. = 0.35-0.86), as were Asian American (OR. = 0.55; CI. = 0.33-0.93) and Latino men (OR. = 0.30; CI. = 0.18-0.48). There were no racial/ethnic differences in willingness to participate. The attitude that "researchers are the main beneficiaries" was negatively associated with willingness (OR. = 0.63; CI. = 0.43-0.93); the attitude that "patients are the main beneficiaries" was positively associated with willingness to participate (OR. = 1.57; CI. = 1.07-2.29). Conclusions: Men with early stage prostate cancer are willing to take part in clinical trials and this willingness does not vary by race/ethnicity. © 2015 Elsevier Inc.
Keywords: Clinical trials participation,; Prostate cancer

Informed Decision-Making and Satisfaction with a Church-Based Men’s Health Workshop Series for African-American Men: Men-Only vs. Mixed-Gender Format - Holt, C.L.; Le, D.; Saunders, D.R.; Wang, M.Q.; Slade, J.L.; Muwwakkil, B.; Williams, R.; Atkinson, N.L.; Whitehead, T.L.; Naslund, M. (Journal of Cancer Education, 2015)
Prostate cancer incidence and mortality are highest among African-American men, and coupled with the controversy around routine prostate cancer screening, reaching African-American men with interventions to help them make an informed decision about whether or not to be screened is critical. This study compares two approaches to delivering a church-based peer community health advisor intervention consisting of a series of four men’s health workshops on informed decision-making for prostate cancer screening. In the men-only group, male community health advisors teach group workshops consisting only of men. In the health partner group, male-female pairs of community health advisors teach workshops in a mixed-gender format in which enrolled men are asked to invite a significant woman in their lives (e.g., wife/partner, sister, daughter, friend) with them to the workshops. Eighteen African-American churches were randomized to receive one of the two approaches, and 283 eligible men enrolled in the intervention. Main findings suggested that the workshops had an impact on stage of decision-making, and this increased significantly over time in the health partner group only. The intervention was highly rated by men in both groups, and these ratings increased over time, with some study group differences. Within-workshop study group differences favored the health partner group in some instances; however, men in the men-only groups reported greater increases in their ratings of trust in the workshops over time. The health partner intervention strategy appears to be promising for reaching men of color with health information. © 2014, Springer Science+Business Media New York (outside the USA (except that a license is reserved to the United States Government for all government purposes and to the University of Maryland College Park for its internal educational and research purposes)).
Keywords: African-American; Cancer screening; Church-based; Community health advisor; Health disparities; Informed decision-making; Men’s health; Prostate cancer

Randomized trial to increase colorectal cancer screening in an ethnically diverse sample of first-degree relatives - Bastani, R.; Glenn, B.A.; Maxwell, A.E.; Ganz, P.A.; Mojica, C.M.; Alber, S.; Crespi, C.M.; Chang, L.C. (Cancer, 2015)
BACKGROUND: Ethnic minorities, especially African Americans and Latinos, bear a disproportionate burden of colorectal cancer (CRC), as reflected in incidence, cancer stage, and mortality statistics. In all ethnic groups, first-degree relatives (FDRs) of CRC cases are at an elevated disease risk. However, underuse of CRC screening persists and is particularly evident among minority groups. The current study tested a stepped intervention to increase CRC screening among an ethnically diverse sample of FDRs of CRC cases. METHODS: A statewide cancer registry was used to recruit CRC cases and through them their FDRs. Relatives who were not current on CRC screening were randomized to intervention or usual-care control arms. The stepped intervention consisted of ethnically targeted and individually tailored print materials followed by telephone counseling for those unscreened at 6 months. RESULTS: The study sample of 1280 individuals consisted of 403 Latino, 284 African American, 242 Asian, and 351 white FDRs. Statistically significant effects were observed for the cumulative print plus telephone intervention at 12 months (26% in the intervention vs 18% in the control group) and the print intervention alone at 6 months (15% in the intervention vs 10% in the control group). The effect of the print intervention alone versus the cumulative interventions was not statistically significantly different. Stratified analyses indicated that the intervention was effective among white, Latino, and Asian individuals, but not among African-Americans. CONCLUSIONS: Overall, the intervention was effective in increasing screening rates. Oversampling racial/ethnic minorities allowed for the examination of effects within subgroups, revealing no effect among African American individuals. This finding illustrates the importance of including sufficient numbers of participants from diverse ethnic subgroups in intervention research to enable such stratified analyses. Cancer 2015;121:2951-2959. © 2015 American Cancer Society.
Keywords: colorectal cancer; disparities; first-degree relatives; intervention research; screening

A phase II/III randomized study to compare the efficacy and safety of rigosertib plus gemcitabine versus gemcitabine alone in patients with previously untreated metastatic pancreatic cancer - O'Neil, B.H.; Scott, A.J.; Ma, W.W.; Cohen, S.J.; Aisner, D.L.; Menter, A.R.; Tejani, M.A.; Cho, J.K.; Granfortuna, J.; Coveler, L.; Olowokure, O.O.; Baranda, J.C.; et al. (Annals of Oncology, 2015)
Background: Rigosertib (ON 01910.Na), a first-in-class Ras mimetic and small-molecule inhibitor of multiple signaling pathways including polo-like kinase 1 (PLK1) and phosphoinositide 3-kinase (PI3K), has shown efficacy in preclinical pancreatic cancer models. In this study, rigosertib was assessed in combination with gemcitabine in patients with treatment-naïve metastatic pancreatic adenocarcinoma. Materials and methods: Patients with metastatic pancreatic adenocarcinoma were randomized in a 2:1 fashion to gemcitabine 1000 mg/m2 weekly for 3 weeks of a 4-week cycle plus rigosertib 1800 mg/m2 via 2-h continuous IV infusions given twice weekly for 3 weeks of a 4-week cycle (RIG + GEM) versus gemcitabine 1000 mg/m2 weekly for 3 weeks in a 4-week cycle (GEM). Results: A total of 160 patients were enrolled globally and randomly assigned to RIG + GEM (106 patients) or GEM (54). The most common grade 3 or higher adverse events were neutropenia (8% in the RIG + GEM group versus 6% in the GEM group), hyponatremia (17% versus 4%), and anemia (8% versus 4%). The median overall survival was 6.1 months for RIG + GEM versus 6.4 months for GEM [hazard ratio (HR), 1.24; 95% confidence interval (CI) 0.85-1.81]. The median progression-free survival was 3.4 months for both groups (HR = 0.96; 95% CI 0.68-1.36). The partial response rate was 19% versus 13% for RIG + GEM versus GEM, respectively. Of 64 tumor samples sent for molecular analysis, 47 were adequate for multiplex genetic testing and 41 were positive for mutations. The majority of cases had KRAS gene mutations (40 cases). Other mutations detected included TP53 (13 cases) and PIK3CA (1 case). No correlation between mutational status and efficacy was detected. Conclusions: The combination of RIG + GEM failed to demonstrate an improvement in survival or response compared with GEM in patients with metastatic pancreatic adenocarcinoma. Rigosertib showed a similar safety profile to that seen in previous trials using the IV formulation. © The Author 2015. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved.
Keywords: Pancreatic cancer; Phase II/III; PI3K inhibitor; PLK1 inhibitor; Ras mimetic; Rigosertib

A Model of Cancer Clinical Trial Decision-making Informed by African-American Cancer Patients - Wenzel, J.A.; Mbah, O.; Xu, J.; Moscou-Jackson, G.; Saleem, H.; Sakyi, K.; Ford, J.G. (Journal of racial and ethnic health disparities, 2015)
BACKGROUND: Clinical trials are critical to advancing cancer treatment. Minority populations are underrepresented among trial participants, and there is limited understanding of their decision-making process and key determinants of decision outcomes regarding trial participation. METHODS: To understand research decision-making among clinical trial-eligible African-American cancer patients at Johns Hopkins, we conducted seven focus groups (n=32) with trial-offered patients ≥ 18 years diagnosed with lung, breast, prostate, or colorectal cancer ≤ 5 years. Three "acceptor" and four "decliner" focus groups were conducted. Questions addressed: attitudes towards clinical trials, reasons for accepting or declining participation, and recommendations to improve minority recruitment and enrollment. Data were transcribed and analyzed using traditional approaches to content and thematic analysis in NVivo 9.0. Data coding resulted in themes that supported model construction. RESULTS: Participant experiences revealed the following themes when describing the decision-making process: Information gathering, Intrapersonal perspectives, and Interpersonal influences. Decision outcomes included the presence or absence of decision regret and satisfaction. From these themes, we generated a Model of Cancer Clinical Trial Decision-making. CONCLUSION: Our model should be tested in hypothesis-driven research to elucidate factors and processes influencing decision balance and outcomes of trial-related decision-making. The model should also be tested in other disparities populations and for diagnoses other than cancer.
Keywords: African-Americans; Cancer disparities; Clinical trials; Decision balance; Decision regret

Automated pain intervention for underserved minority women with breast cancer - Anderson, K.O.; Palos, G.R.; Mendoza, T.R.; Cleeland, C.S.; Liao, K.-P.; Fisch, M.J.; Garcia-Gonzalez, A.; Rieber, A.G.; Nazario, L.A.; Valero, V.; Hahn, K.M.; Person, C.L.; et al. (Cancer, 2015)
BACKGROUND Minority patients with breast cancer are at risk for undertreatment of cancer-related pain. The authors evaluated the feasibility and efficacy of an automated pain intervention for improving pain and symptom management of underserved African American and Latina women with breast cancer. METHODS Sixty low-income African American and Latina women with breast cancer and cancer-related pain were enrolled in a pilot study of an automated, telephone-based, interactive voice response (IVR) intervention. Women in the intervention group were called twice weekly by the IVR system and asked to rate the intensity of their pain and other symptoms. The patients' oncologists received e-mail alerts if the reported symptoms were moderate to severe. The patients also reported barriers to pain management and received education regarding any reported obstacles. RESULTS The proportion of women in both groups reporting moderate to severe pain decreased during the study, but the decrease was significantly greater for the intervention group. The IVR intervention also was associated with improvements in other cancer-related symptoms, including sleep disturbance and drowsiness. Although patient adherence to the IVR call schedule was good, the oncologists who were treating the patients rated the intervention as only somewhat useful for improving symptom management. CONCLUSIONS The IVR intervention reduced pain and symptom severity for underserved minority women with breast cancer. Additional research on technological approaches to symptom management is needed. © 2015 American Cancer Society.
Keywords: assessment; breast cancer; minority groups; pain; symptoms

Prospective approach to breast cancer risk prediction in African American women: The black women's health study model - Boggs, D.A.; Rosenberg, L.; Adams-Campbell, L.L.; Palmer, J.R. (Journal of Clinical Oncology, 2015)
Purpose Breast cancer risk prediction models have underestimated risk for African American women, contributing to lower recruitment rates in prevention trials. A model previously developed for African American women was found to underestimate risk in the Black Women's Health Study (BWHS). Methods We developed a breast cancer risk model for African American women using relative risks derived from 10 years of follow-up of BWHS participants age 30 to 69 years at baseline. Using the subsequent 5 years of follow-up data, we evaluated calibration as the ratio of expected to observed number of breast cancers and assessed discriminatory accuracy using the concordance statistic. Results The BWHS model included family history, previous biopsy, body mass index at age 18 years, age at menarche, age at first birth, oral contraceptive use, bilateral oophorectomy, estrogen plus progestin use, and height. There was good agreement between predicted and observed number of breast cancers overall (expected-to-observed ratio, 0.96; 95% CI, 0.88 to 1.05) and in most risk factor categories. Discriminatory accuracy was higher for women younger than age 50 years (area under the curve [AUC], 0.62; 95% CI, 0.58 to 0.65) than for women age ≥ 50 years (AUC, 0.56; 95% CI, 0.53 to 0.59). Using a 5-year predicted risk of 1.66% or greater as a cut point, 2.8% of women younger than 50 years old and 32.2% of women ≥ 50 years old were classified as being at elevated risk of invasive breast cancer. Conclusion The BWHS model was well calibrated overall, and the predictive ability was best for younger women. The proportion of women predicted to meet the 1.66% cut point commonly used to determine eligibility for breast cancer prevention trials was greatly increased relative to previous models. © 2015 by American Society of Clinical Oncology.

In patients with a previous negative prostate biopsy and a suspicious lesion on magnetic resonance imaging, is a 12-core biopsy still necessary in addition to a targeted biopsy? - Salami, S.S.; Ben-Levi, E.; Yaskiv, O.; Ryniker, L.; Turkbey, B.; Kavoussi, L.R.; Villani, R.; Rastinehad, A.R. (BJU International, 2015)
ObjectivesTo evaluate the performance of multiparametric magnetic resonance imaging (mpMRI) in predicting prostate cancer on repeat biopsy; and to compare the cancer detection rates (CDRs) of MRI/transrectal ultrasonography (TRUS) fusion-guided biopsy with standard 12-core biopsy in men with at least one previous negative biopsy. Patients and Methods We prospectively enrolled men with elevated or rising PSA levels and/or abnormal digital rectal examination into our MRI/TRUS fusion-guided prostate biopsy trial. Participants underwent a 3 T mpMRI with an endorectal coil. Three radiologists graded all suspicious lesions on a 5-point Likert scale. MRI/TRUS fusion-guided biopsies of suspicious prostate lesions and standard TRUS-guided 12-core biopsies were performed. Analysis of 140 eligible men with at least one previous negative biopsy was performed. We calculated CDRs and estimated area under the receiver operating characteristic curves (AUCs) of mpMRI in predicting any cancer and clinically significant prostate cancer. Results The overall CDR was 65.0% (91/140). Higher level of suspicion on mpMRI was significantly associated with prostate cancer detection (P < 0.001) with an AUC of 0.744 compared with 0.653 and 0.680 for PSA level and PSA density, respectively. The CDRs of MRI/TRUS fusion-guided and standard 12-core biopsy were 52.1% (73/140) and 48.6% (68/140), respectively (P = 0.435). However, fusion biopsy was more likely to detect clinically significant prostate cancer when compared with the 12-core biopsy (47.9% vs 30.7%; P < 0.001). Of the cancers missed by 12-core biopsy, 20.9% (19/91) were clinically significant. Most cancers missed by 12-core biopsy (69.6%) were located in the anterior fibromuscular stroma and transition zone. Using a fusion-biopsy-only approach in men with an MRI suspicion score of ≥4 would have missed only 3.5% of clinically significant prostate cancers. Conclusions Using mpMRI and subsequent MRI/TRUS fusion-guided biopsy platform may improve detection of clinically significant prostate cancer in men with previous negative biopsies. Addition of a 12-core biopsy may be needed to avoid missing some clinically significant prostate cancers. © 2014 The Authors. BJU International © 2014 BJU International.
Keywords: false-negative prostate biopsy; negative prostate biopsy; prostate cancer screening; prostate fusion biopsy; prostate imaging

Demographic and HIV-specific characteristics of participants enrolled in the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial - Sharma, S.; Babiker, A.; Emery, S.; Gordin, F.; Lundgren, J.; Neaton, J.; Bakowska, E.; Schechter, M.; Wiselka, M.; Wolff, M.; International Network for Strategic Initiatives in Global HIV Trials (INSIGHT) START Study Group (HIV Medicine, 2015)
Objectives: The risks and benefits of initiating antiretroviral treatment (ART) at high CD4 cell counts have not been reliably quantified. The Strategic Timing of AntiRetroviral Treatment (START) study is a randomized international clinical trial that compares immediate with deferred initiation of ART for HIV-positive individuals with CD4 cell counts above 500cells/μL. We describe the demographics, HIV-specific characteristics and medical history of this cohort. Methods: Data collected at baseline include demographics, HIV-specific laboratory values, prior medical diagnoses and concomitant medications. Baseline characteristics were compared by geographical region, gender and age. Results: START enrolled 4685 HIV-positive participants from 215 sites in 35 countries. The median age is 36 years [interquartile range (IQR) 29-44 years], 27% are female, and 45% self-identify as white, 30% as black, 14% as Latino/Hispanic, 8% as Asian and 3% as other. The route of HIV acquisition is reported as men who have sex with men in 55% of participants, heterosexual sex in 38%, injecting drug use in 1% and other/unknown in 5%. Median time since HIV diagnosis is 1.0 year (IQR 0.4-3.0 years) and the median CD4 cell count and HIV RNA values at study entry are 651cells/μL (IQR 584-765cells/μL) and 12754 HIV RNA copies/mL (IQR 3014-43607 copies/mL), respectively. Conclusions: START has enrolled a diverse group of ART-naïve individuals with high CD4 cell counts who are comparable to the HIV-positive population from the regions in which they were enrolled. The information collected with this robust study design will provide a database with which to evaluate the risks and benefits of early ART use for many important outcomes. © 2015 British HIV Association.
Keywords: Clinical trial; HIV; START trial; When to start antiretroviral therapy

Strategies for Enrollment of African Americans into Cancer Genetic Studies - Ewing, A.; Thompson, N.; Ricks-Santi, L. (Journal of Cancer Education, 2015)
The enrollment of ethnically diverse populations in genetic and genomic research is vital to the parity of benefits resulting from research with biological specimens. Herein, we discuss strategies that may effectively improve the recruitment of African Americans into genetics studies. Specifically, we show that engaging physicians, genetic counselors, and community members is essential to enrolling participants into genetic studies. We demonstrate the impact of utilizing African American genetic counselors on study enrollment rates and implementing a two-page consent form that improved on a lengthy and inefficient consenting process. Lastly, we provided participants with the option of donating saliva instead of blood for study purposes. Descriptive statistics were used. Using the aforementioned strategies, recruitment goals for the Genetic Basis of Breast Cancer Subtype Study at Howard University (HU) were met. Our overall results yielded 182 participants in 18 months. Recruitment strategies that involve the engagement of physicians, genetic counselors, and community members may help researchers increase the enrollment of ethnically diverse and hard-to-reach participants into genetic studies. © 2014, Springer Science+Business Media New York.
Keywords: African Americans; Cancer genetic research; Genetic counseling; Research strategies

Diminutive polyps among black and Latino populations undergoing screening colonoscopy: Evidence supporting a resect and discard approach - Lee, K.K.; Jandorf, L.; Itzkowitz, S.H. (Gastrointestinal Endoscopy, 2015)
Background: A resect and discard strategy for diminutive (≤5 mm) colon polyps has been proposed to save costs of screening colonoscopy (SC). Prior studies on neoplasia prevalence based on polyp size have involved mostly white patients. Objective: To determine the prevalence of adenomas and advanced histologic features by size among primarily black and Latino patients enrolled in a prospective SC study. Design: Retrospective analysis of data from a prospective clinical trial. Setting: Urban academic medical center. Patients: Average risk, asymptomatic, minority patients aged ≤50 years undergoing SC. Interventions: Screening colonoscopy. Main Outcome Measurements: Rates of neoplasia and advanced histologic features (villous histology, highgrade dysplasia, or cancer) by polyp size and location. Results: A total of 566 polyps from 295 patients were analyzed. Diminutive polyps and small (6-9 mm) polyps had lower prevalence of ≤1 advanced feature compared with large (≤10 mm) polyps (0.9% and 2.7%, respectively, vs 13.6%; P < .001 for both comparisons). Distal polyps were less likely to be neoplastic (31.7% vs 61.4%; P < .001) than proximal polyps in all size categories (P < .001 for all comparisons). After adjusting for sex, ethnicity, age, and location, large polyps were more likely to have ≤1 advanced feature than diminutive polyps (adjusted odds ratio [OR] 19.5; 95% CI, 4.4-85.6) or small polyps (adjusted OR 6.1; 95% CI, 2.2-16.9). Limitations: Use of pathology reports for polyp size. Conclusion: Among a cohort of minority patients, advanced histologic features were very rare in diminutive polyps. Distal polyps were less likely to be neoplastic than proximal polyps in all size categories. This supports a resect and discard strategy for diminutive polyps, especially in the distal colon. Copyright © 2015 by the American Society for Gastrointestinal Endoscopy.

Exploring the influence of demographic and medical characteristics of African-American and Latinas on enrollment in a behavioral intervention study for breast cancer survivors - Ashing, K.; Rosales, M.; Fernandez, A. (Quality of Life Research, 2015)
Purpose: To better understand research participation among hard-to-reach populations, this exploratory investigation examined characteristics of enrollees and non-enrollees from a population-based longitudinal study with African-American and Latina-American breast cancer survivors. Methods: A mixed-method recruitment approach was utilized to enroll participants from cancer registries and community groups who were 1–6 years post-diagnosis. Results: Four hundred and sixty-eight participants agreed to participate constituting an 81 % participation rate; 65 and 55 % completed Time-1, and both Time-1 and Time-2 assessments, respectively. African-Americans were more likely to agree to participate and complete the T1 assessment (73 %) than Latinas (62 %) (p < 0.05). Participation was influenced by educational attainment and comorbidities (p < 0.05) for African-Americans. Among Latinas, language proficiency, comorbidities and psychological difficulties (p < 0.01) influenced participation. Conclusions: Our findings suggest that enrollment in research studies may be influenced by complex and multi-dimensional factors stemming from subjects’ characteristics including ethnicity, culture, language proficiency and literary, and socioeconomic status, as well as medical characteristics including co-occurring chronic illness and psychological status. Thus, comprehensive, multi-method research studies are urgently needed to better understand and address the challenge of minority recruitment in biomedical research. To increase research participation among cancer survivors, it is imperative to implement focused strategies that will support and encourage individuals’ enrollment and continued participation in studies. © 2014, Springer International Publishing Switzerland.
Keywords: Breast cancer; Ethnic minority; Recruitment; Response bias; Retention

Understanding disparity: Researchers strive to recruit more African Americans and other minorities to studies - Printz, C. (Cancer, 2015)

Exploratory subset analysis of African Americans from the PointBreak study: Pemetrexed-carboplatin-bevacizumab followed by maintenance pemetrexed-bevacizumab versus paclitaxel-carboplatin-bevacizumab followed by maintenance bevacizumab in patients with stage IIIB/IV nonsquamous non-small-cell lung cancer - Reynolds, C.H.; Patel, J.D.; Garon, E.B.; Olsen, M.R.; Bonomi, P.; Govindan, R.; Pennella, E.J.; Liu, J.; Guba, S.C.; Li, S.; Spigel, D.R.; Hermann, R.C.; et al. (Clinical Lung Cancer, 2015)
Introduction African Americans have a greater incidence of lung cancer than whites and have been underrepresented in clinical trials. In the PointBreak trial (pemetrexed-carboplatin-bevacizumab and maintenance pemetrexed-bevacizumab [PemCBev] vs. paclitaxel-carboplatin-bevacizumab and maintenance bevacizumab [PacCBev]), 10% of the patients were African American. PointBreak had negative findings; PemCBev did not demonstrate superior overall survival (OS). Materials and Methods PointBreak subgroup efficacy and safety data were retrospectively analyzed: African Americans versus whites for PemCBev; PemCBev versus PacCBev in African Americans; and academic versus community settings for African Americans. Hazard ratios (HRs) and P values were derived from a multivariate Cox proportional hazards model after adjusting for covariates. Results Of 939 intent-to-treat (ITT) patients, 94 were African American and 805 were white. African-American enrollment was uniform across the study sites (median, 1 African American per site). In the PemCBev arm, OS (HR, 1.125; P =.525), progression-free survival (PFS) (HR, 1.229; P =.251), response (P =.607), and toxicity profiles were similar in African Americans versus whites. For African Americans, OS (HR, 1.375; P =.209), PFS (HR, 0.902; P =.670), response (P = 1.000), and toxicity profiles were similar in the PemCBev versus PacCBev arm. For African Americans, no significant differences were seen in OS (HR, 0.661; P =.191) or PFS (HR, 0.969; P =.915) in academic versus community practice settings. Conclusion In the PemCBev arm, this exploratory analysis showed no significant differences between African Americans and whites for the efficacy outcomes or toxicity profiles. Consistent with the ITT population negative trial result, for African Americans, the median OS was not superior for either arm. For African Americans, PFS and OS were similar in the academic and community settings. Additional outcomes data for African Americans should be collected in lung cancer studies. © 2015 Elsevier Inc.
Keywords: Alimta; Avastin; Minority groups

Neuropathic symptoms and their risk factors in medical oncology outpatients with colorectal vs. breast, lung, or prostate cancer: Results from a prospective multicenter study - Lewis, M.A.; Zhao, F.; Jones, D.; Loprinzi, C.L.; Brell, J.; Weiss, M.; Fisch, M.J. (Journal of Pain and Symptom Management, 2015)
Context Few studies have examined the prevalence and severity of treatment-induced neuropathic symptoms in patients across different cancer types. Objectives This study aimed to report the prevalence of numbness/tingling (N/T) and neuropathic pain in patients with colorectal cancer (CRC) vs. other cancers, describe the prevalence of moderate-to-severe N/T by specific clinical variables, and examine factors associated with the presence of these symptoms. Methods A total of 3106 outpatients with colorectal (n = 718), breast (n = 1544), lung (n = 524), or prostate (n = 320) cancer were enrolled at any point in their treatment. Assessments were conducted at the initial visit and 28-35 days later. Patients reported pain and N/T; clinicians reported mechanism of pain and ranked the top three symptoms causing difficulties. Results Moderate-to-severe N/T was higher in patients with CRC relative to other cancer types (25.8% vs. 17.1%, P < 0.001); 25% vs. 10.5% of clinicians rated N/T as a top three symptom for patients with CRC relative to other cancers (P < 0.001). The prevalence of neuropathic pain was comparable between patients with CRC and other cancers (P = 0.654). Patients with CRC, longer duration of cancer, prior therapy, on current therapy, older patients, and patients of black race experienced worse N/T. Conclusion Patients with CRC experience significantly higher rates of N/T but comparable neuropathic pain, relative to patients with other cancers. Awareness of the prevalence and severity of neuropathic symptoms and their associated risk factors in this patient population is critical for both clinicians and patients. © 2015 American Academy of Hospice and Palliative Medicine.
Keywords: Colorectal cancer; neuropathic pain; neuropathy; numbness/tingling; oxaliplatin

A phase II clinical trial of weekly paclitaxel and carboplatin in combination with panitumumab in metastatic triple negative breast cancer - Cowherd, S.; Miller, L.D.; Melin, S.A.; Akman, S.; Isom, S.; Cole, J.; Pullikuth, A.; Lawrence, J.A. (Cancer Biology and Therapy, 2015)
Purpose: Women with metastatic triple negative breast cancer (TNBC) can have a poor prognosis with treatment limited to cytotoxic chemotherapy. The identification of effective therapies that may limit exposure to cytotoxic chemotherapy and lead to prolonged survival is an unmet medical need. We tested an inhibitor of the epidermal growth factor receptor, panitumumab in combination with chemotherapy. Methods: We conducted a single arm clinical trial in women with metastatic or locally advanced TNBC to paclitaxel 80 mg/m2 and carboplatin AUC of 2 on days 1, 8, and 15 and panitumumab 6 mg/kg on days 1 and 15 for a cycle length of 28 days. The objectives were to evaluate the response rate and safety of the combination in comparison to historical controls. Results: Fourteen patients with TNBC were enrolled with a median age of 53 years. The majority of women were African American (64.3%) with visceral metastasis (64.2%). Hematologic toxicities, particularly neutropenia and thrombocytopenia, were a major cause of missed chemotherapy and delayed treatment in this study. The overall response rate (complete and partial response) of the 13 evaluable patients was 46%. The median time to best response was 2.4 months and the median time to disease progression was 3.6 months. We were able to perform the PAM50 analysis on tumors from 7 of our subjects. All the samples tested clustered within the basal-like subtype. Conclusions: In our experience the response rate of carboplatin, paclitaxel and panitumumab was consistent with other reports of response for cytotoxic chemotherapy in metastatic TNBC. © 2015 Taylor and Francis Group, LLC.
Keywords: Epidermal growth factor inhibitor; Metastatic breast cancer; Pacliataxel carboplatin; Triple negative breast cancer

A phase 1 safety study of veliparib combined with cisplatin and etoposide in extensive stage small cell lung cancer: A trial of the ECOG-ACRIN Cancer Research Group (E2511) - Owonikoko, T.K.; Dahlberg, S.E.; Khan, S.A.; Gerber, D.E.; Dowell, J.; Moss, R.A.; Belani, C.P.; Hann, C.L.; Aggarwal, C.; Ramalingam, S.S. (Lung Cancer, 2015)
Objectives: Veliparib (V) potentiated therapeutic efficacy of cisplatin (C) and etoposide (E) in preclinical models of SCLC. We conducted this phase 1 study to establish the safety of the combination in human subjects. Materials and methods: The study employed the 3+3 dose escalation design to establish the safety and recommended phase 2 dose (RP2D) of V when combined with fixed doses of C (75mg/m2 on day 1) and E (100mg/m2 on days 1-3) in a 21-day cycle. The starting dose of V was 60mg (bid days 1-7) with plan to escalate to 100mg (days 1-7) or de-escalate to 40mg (days 1-7) depending on the dose limiting toxicity (DLT) experience during cycle 1. Patients with treatment-naïve, extensive stage SCLC were included. Results: The study enrolled 9 patients: M/F (4/5); median age (60); White/African American (8/1). V was tolerated at the 60. mg (DLT in 0 of 3 patients) and 100. mg dose (DLT in 1 of 6 patients; grade 5 cardiac failure). Veliparib at 100. mg in combination with standard doses of C and E was established as the RP2D. Grades 3-5 adverse events irrespective of attribution during cycle 1 included: dehydration (1), diarrhea (1), fatigue (1), febrile neutropenia (1), heart failure (1), leukopenia (6), lymphopenia (1), nausea (2), neutropenia (8), respiratory failure (1), and thrombocytopenia (2). Investigator-assessed efficacy outcome in 7 evaluable patients were stable disease in 2/7 (28.6%), partial response in 4/7 (57.1%), and complete response in 1/7 (14.3%) patients. Conclusions: This study demonstrated the safety of combining veliparib with cisplatin and etoposide in previously untreated SCLC patients. © 2015 Elsevier Ireland Ltd.
Keywords: PARP; Phase I; Small cell; Veliparib

Addressing health disparities in Hispanic breast cancer: Accurate and inexpensive sequencing of BRCA1 and BRCA2 - Dean, M.; Boland, J.; Yeager, M.; Im, K.M.; Garland, L.; Rodriguez-Herrera, M.; Perez, M.; Mitchell, J.; Roberson, D.; Jones, K.; Lee, H.J.; Eggebeen, R.; et al. (GigaScience, 2015)
Background: Germline mutations in the BRCA1 and BRCA2 genes account for 20-25 % of inherited breast cancers and about 10 % of all breast cancer cases. Detection of BRCA mutation carriers can lead to therapeutic interventions such as mastectomy, oophorectomy, hormonal prevention therapy, improved screening, and targeted therapies such as PARP-inhibition. We estimate that African Americans and Hispanics are 4-5 times less likely to receive BRCA screening, despite having similar mutation frequencies as non-Jewish Caucasians, who have higher breast cancer mortality. To begin addressing this health disparity, we initiated a nationwide trial of BRCA testing of Latin American women with breast cancer. Patients were recruited through community organizations, clinics, public events, and by mail and Internet. Subjects completed the consent process and questionnaire, and provided a saliva sample by mail or in person. DNA from 120 subjects was used to sequence the entirety of BRCA1 and BRCA2 coding regions and splice sites, and validate pathogenic mutations, with a total material cost of $85/subject. Subjects ranged in age from 23 to 81 years (mean age, 51 years), 6 % had bilateral disease, 57 % were ER/PR+, 23 % HER2+, and 17 % had triple-negative disease. Results: A total of seven different predicted deleterious mutations were identified, one newly described and the rest rare. In addition, four variants of unknown effect were found. Conclusions: Application of this strategy on a larger scale could lead to improved cancer care of minority and underserved populations.
Keywords: Breast cancer; Genetic testing; Health disparity; Hispanic populations; Underserved populations

A pilot randomized controlled trial testing a minimal intervention to prepare breast cancer survivors for recovery - Sterba, K.R.; Armeson, K.; Franco, R.; Harper, J.; Patten, R.; Kindall, S.; Bearden, J.; Zapka, J. (Cancer Nursing, 2015)
Background: Interventions addressing cancer survivors' posttreatment concerns can be time-intensive and require specialized staff. Research is needed to identify feasible minimal intervention strategies to improve survivors' quality of life after treatment. Objectives: The objective of this study was to evaluate the feasibility and short-term impact of a minimal clinic intervention on breast cancer survivors' quality of life, unmet needs, distress, and cancer worry. Interventions/Methods: In this randomized controlled pilot trial, we enrolled breast cancer survivors at the end of treatment and administered baseline surveys. Participants were randomized to study arm (4-week video plus educational booklet intervention group and usual care group) and completed follow-up surveys at 10 weeks. Linear regression was used to examine intervention effects on quality of life outcomes controlling for clinical and demographic factors. Open-ended questions were used to examine program satisfaction and obtain feedback to improve the intervention. Results: We enrolled 92 survivors in the trial. Participants rated the intervention highly and reported feeling less isolated and having more realistic expectations about their recovery after completing the program. Despite positive qualitative findings, no significant intervention effects were observed for quality of life, unmet needs, distress, or cancer worry in unadjusted or adjusted analyses. Conclusions: Future research is needed to define optimal intervention elements to prepare breast cancer survivors for the posttreatment period. Implications for Practice: Effective survivorship interventions may require more intensive components such as clinical input and longer follow-up periods. Copyright © 2015 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: Breast cancer; Intervention; Quality of life; Survivorship

Risk-benefit profiles of women using tamoxifen for chemoprevention - Nichols, H.B.; DeRoo, L.A.; Scharf, D.R.; Sandler, D.P. (Journal of the National Cancer Institute, 2015)
Background: Tamoxifen has been US Food and Drug Administration-approved for primary prevention of breast cancer since 1998 but has not been widely adopted, in part because of increased risk of serious side effects. Little is known about the risk-benefit profiles of women who use chemoprevention outside of a clinical trial. We examined characteristics associated with initiation and discontinuation of tamoxifen for primary prevention of breast cancer within a large cohort of women with a first-degree family history of breast cancer. Methods: This research was conducted within The Sister Study, a cohort of 50 884 US and Puerto Rican women age 35 to 74 years enrolled from 2003 to 2009. Eligible women were breast cancer-free at enrollment and had a sister who had been diagnosed with breast cancer. Participants reported tamoxifen use, ages started and stopped taking tamoxifen, and total duration of use at enrollment. We identified 788 tamoxifen users and 3131 nonusers matched on age and year of enrollment who had no history of contraindicating factors (stroke, transient ischemic attack, cataract, endometrial or uterine cancer). Characteristics associated with tamoxifen initiation were evaluated with multivariable conditional logistic regression. All statistical tests were two-sided. Results: Based on published risk-benefit indices, 20% of women who used tamoxifen had insufficient evidence that the benefits of tamoxifen outweigh the risk of serious side effects. After 4.5 years, 46% of women had discontinued tamoxifen. Conclusions: While the majority of women who used tamoxifen for primary prevention of breast cancer were likely to benefit, substantial discontinuation of tamoxifen before five years and use by women at risk of serious side effects may attenuate benefits for breast cancer prevention.

Vegetarian dietary patterns and the risk of colorectal cancers - Orlich, M.J.; Singh, P.N.; Sabaté, J.; Fan, J.; Sveen, L.; Bennett, H.; Knutsen, S.F.; Beeson, W.L.; Jaceldo-Siegl, K.; Butler, T.L.; Herring, R.P.; Fraser, G.E. (JAMA Internal Medicine, 2015)
IMPORTANCE Colorectal cancers are a leading cause of cancer mortality, and their primary prevention by diet is highly desirable. The relationship of vegetarian dietary patterns to colorectal cancer risk is not well established. OBJECTIVE To evaluate the association between vegetarian dietary patterns and incident colorectal cancers. DESIGN, SETTING, AND PARTICIPANTS The Adventist Health Study 2 (AHS-2) is a large, prospective, North American cohort trial including 96 354 Seventh-Day Adventist men and women recruited between January 1, 2002, and December 31, 2007. Follow-up varied by state and was indicated by the cancer registry linkage dates. Of these participants, an analytic sample of 77 659 remained after exclusions. Analysis was conducted using Cox proportional hazards regression, controlling for important demographic and lifestyle confounders. The analysis was conducted between June 1, 2014, and October 20, 2014. EXPOSURES Diet was assessed at baseline by a validated quantitative food frequency questionnaire and categorized into 4 vegetarian dietary patterns (vegan, lacto-ovo vegetarian, pescovegetarian, and semivegetarian) and a nonvegetarian dietary pattern. MAIN OUTCOMES AND MEASURES The relationship between dietary patterns and incident cancers of the colon and rectum; colorectal cancer cases were identified primarily by state cancer registry linkages. RESULTS During a mean follow-up of 7.3 years, 380 cases of colon cancer and 110 cases of rectal cancer were documented. The adjusted hazard ratios (HRs) in all vegetarians combined vs nonvegetarians were 0.78 (95%CI, 0.64-0.95) for all colorectal cancers, 0.81 (95%CI, 0.65-1.00) for colon cancer, and 0.71 (95%CI, 0.47-1.06) for rectal cancer. The adjusted HR for colorectal cancer in vegans was 0.84 (95%CI, 0.59-1.19); in lacto-ovo vegetarians, 0.82 (95%CI, 0.65-1.02); in pescovegetarians, 0.57 (95%CI, 0.40-0.82); and in semivegetarians, 0.92 (95%CI, 0.62-1.37) compared with nonvegetarians. Effect estimates were similar for men and women and for black and nonblack individuals. CONCLUSIONS AND RELEVANCE Vegetarian diets are associated with an overall lower incidence of colorectal cancers. Pescovegetarians in particular have a much lower risk compared with nonvegetarians. If such associations are causal, theymay be important for primary prevention of colorectal cancers. © Copyright 2015 American Medical Association. All rights reserved.

A phase II double-blinded study to evaluate the efficacy of EW02 in reducing chemotherapy-induced neutropenia in breast cancer - Wu, Y.-Y.; Liu, H.-Y.; Huang, T.-C.; Chen, J.-H.; Chang, P.-Y.; Ho, C.-L.; Chao, T.-Y. (Oncology Letters, 2015)
EW02, a polysaccharide-enriched crude extract from black soybean, has been shown to assist hematopoiesis in chemotherapy‑treated animals. The present study aimed to clarify the safety, quality of life (QOL) and efficacy for myelopoiesis of EW02 administration in early breast cancer (EBC) patients receiving adjuvant chemotherapy. A total of 60 eligible EBC patients were enrolled in a randomized, double‑blinded trial, 40 of whom were prescribed 700 mg oral EW02 three times daily for 15 days in chemotherapy cycle (C)2. The remainder were prescribed a placebo. All subjects took EW02 in C3 for 15 days. Blood samples were collected at different time‑points for determining the blood cell count, and the serum level of granulocyte colony‑stimulating factor (G‑CSF) and interleukin (IL)‑6. All patients tolerated EW02 well without severe side‑effects. QOL evaluation showed that only the score of one questionnaire section (QLQ‑C30) was significantly increased at C1 day (D)8 to C2D8 when the EW02 and placebo groups were compared (P=0.045). No significant myelopoiesis recovery, and no incremental change in IL‑6 and G‑CSF levels were found in C2. Subgroup analysis showed a slightly lower decrease in absolute neutrophil count (ANC) in the EW02 patients who underwent Adriamycin + cyclophosphamide treatment compared with the placebo group. Although EW02 failed to show efficacy for myelopoiesis in the present study, EW02 was still well tolerated in EBC patients who underwent adjuvant chemotherapy. © 2015, Spandidos Publications. All rights reserved.
Keywords: Black soybean; Breast cancer; Chemotherapy; Myelopoiesis

Retention of black and white participants in the selenium and vitamin E cancer prevention trial (SWOG-coordinated intergroup study S0000) - Arnold, K.B.; Hermos, J.A.; Anderson, K.B.; Minasian, L.; Tangen, C.M.; Probstfield, J.F.; Cook, E.D. (Cancer Epidemiology Biomarkers and Prevention, 2014)
Background: Disproportionally low retention of minority populations can adversely affect the generaliz-ability of clinical research trials. We determine the overall retention rates for White and Black participants from the Selenium and Vitamin E Cancer Prevention Trial (SELECT) and explore participant and site characteristics associated with retention failure (study disengagement) for these groups. Methods: A secondary analysis of 28,118 White (age ≥55), and 4,322 Black (age ≥ 50) SELECT participants used multivariate Cox regression to estimate overall retention rates and to calculate HRs and 95% confidence intervals (CI). Results: Blacks had higher age-adjusted risk of disengagement than Whites (HR, 1.92; 95% CI, 1.77-2.08). Among Black participants, those ages 50 to 54 were at three times the risk of disengagement than those ≥65 years of age (HR, 3.61; 95% CI, 2.41-5.41). Blacks age ≥65 had 1.6 times the risk of disengagement than Whites age >65 (HR, 1.60; 95% CI, 1.38-1.87). By 6 years after randomization, 84% of Whites and 69% of Blacks remained engaged in the study. Current smoking status was an independent risk factor for study disengagement for both White and Black participants. For both groups, sites whose staffs missed SELECT training sessions or who received SELECT Retention and Adherence grants were associated with increased and decreased disengagement risks, respectively. Conclusions: SELECT retention was disproportionately lower for Blacks than for Whites. Impact: The observed difference in retention rates for Blacks and Whites and factors identified by race for study disengagement in SELECT may inform retention efforts for future long-term, cancer prevention trials. © 2014 American Association for Cancer Research.

Communication preference moderates the effect of a tailored intervention to increase colorectal cancer screening among African Americans - Resnicow, K.; Zhou, Y.; Hawley, S.; Jimbo, M.; Ruffin, M.T.; Davis, R.E.; Shires, D.; Lafata, J.E. (Patient Education and Counseling, 2014)
Objective: Test the impact of tailoring CRC screening messages for African Americans (AAs) using novel theoretical variables and to examine moderating effect of communication preferences. Methods: Participants were randomized to receive two minimally tailored or two enhanced tailored print newsletters addressing CRC. The enhanced intervention was tailored on Self-Determination Theory and other novel psychological constructs. Minimal tailoring only used information available in the patient's EHR. The primary outcome was CRC screening based on EHR. Participants were AA members aged 50-74 of an integrated health care delivery system not up to date on CRC screening. Results: We enrolled 881 participants. CRC screening participation rates at 1-year follow up were 20.5% and 21.5% in the minimally and enhanced tailored groups, respectively. Communication preferences moderated the impact of the intervention. Specifically, among those with an autonomous communication preference, screening rates in the minimally and enhanced tailored groups were 17.1% and 25.9%, respectively, while no intervention effect was evident among those with a directive preference. Conclusion: Future research is needed to explore the impact of communication preference tailoring for other health behaviors and among other populations. Practice implications: Tailored communications should consider communication style preference to help guide the content and tone of messages. © 2014 Elsevier Ireland Ltd.
Keywords: African Americans; Colorectal cancer screening; Tailored intervention

A multi-center study of using carbon nanoparticles to track lymph node metastasis in T1–2 colorectal cancer - Yan, J.; Xue, F.; Chen, H.; Wu, X.; Zhang, H.; Chen, G.; Lu, J.; Cai, L.; Xiang, G.; Deng, Z.; Zheng, Y.; Zheng, X.; et al. (Surgical Endoscopy, 2014)
Background: How to identify whether T1–2 colorectal cancers have lymph nodes metastases pre-op or intra-op is a crucial problem in clinic. The purpose of this study was to evaluate the feasibility of using carbon nanoparticles to track lymph nodes metastases in T1–2 colorectal cancers. Methods: A multi-center study was performed between July 2012 and January 2014. Seventy-three patients with T1–2 colorectal cancer identified by pre-op endoscopic ultrasonography (EUS) were recruited. 1 ml carbon nanoparticles suspension was endoscopically injected into the submucosal layer at four points around the site of the primary tumor 1 day before surgery. Laparoscopic radical resection with lymphadenectomy was performed. Sentinel lymph nodes (SLNs) were defined as nodes that were black-dyed by carbon nanoparticles. Pathology confirmed whether lymph nodes have cancer metastases and the SLNs accuracy. Results: SLNs were easily found under laparoscopy. The mean number of SLNs was 3 (range 1–5). All patients had SLNs lying alongside the mesenteric vessel or main arterial vessel. After pathological analysis, 2 patients (9.52 %) had lymph node metastasis in 21 patients with EUS T1 cancers, and 10 patients (19.23 %) had lymph node metastasis in 52 patients with EUS T2 cancers. In two T1 cases with lymph node metastasis, SLNs were positive with 100 % accuracy. In ten T2 cases with lymph node metastasis, SLNs were positive in nine cases. In pathology, carbon nanoparticles were seen in lymphatic vessels, and lymphoid sinus and macrophages in negative SLNs. When SLNs were positive, carbon nanoparticles were seen around cancer cells in lymph nodes. The overall sensitivity, specificity, accuracy of SLNs in T1–2 colorectal cancers were 91.67, 100, 98.63 %, respectively. Conclusions: We demonstrated the feasibility of using carbon nanoparticles to track lymph nodes metastases in T1–2 colorectal cancers. Carbon nanoparticles black-dyed lymph nodes play a role as SLNs in T1–2 colorectal cancers. © 2014, Springer Science+Business Media New York.
Keywords: Carbon nanoparticles; Lymph node metastasis; Multi-center study; Sentinel lymph nodes; T1–2 colorectal cancer; Tracer

Phase II clinical trial of gefitinib for the treatment of chemonaïve patients with advanced non-small cell lung cancer with poor performance status - Karim, N.A.; Musaad, S.; Zarzour, A.; Patil, S.; Jazieh, A.R. (Clinical Medicine Insights: Oncology, 2014)
Background: Patients with advanced non-small cell lung cancer (NSCLC) have no curative treatment options; therefore, improving their quality of life (QOL) is an important goal. Gefitinib, an epidermal growth factor receptor (EGFR) inhibitor, is a safe oral agent that may be of benefit to a specific population of NSCLC. Patients and methods: A Phase II clinical trial included chemonaïve patients with advanced NSCLC and poor performance status (PS). Response rate, progression-free survival, overall survival, QOL using the Functional Assessment of Cancer Therapy – Lung (FACT-L) questionnaire, and Trial Outcome Index (TOI) were evaluated. Results: Twelve out of 19 enrolled patients were evaluable. The median age for the evaluable patients was 68.8 years (59.7–74.6). Out of all the patients, 7 (58.3%) had adenocarcinoma and 5 (41.7%) had squamous cell carcinoma. The median duration of treatment was 62.5 days (26.5–115.0) in the evaluable patients. Grade 3/4 toxicities included fatigue, rash, diarrhea, and nausea. One patient had partial response, eight patients had stable disease (SD), and three patients progressed. The median overall survival for the evaluable population was 4.9 months (2.3–16). The median progression-free survival was 3.7 months (1.9–6.6). TOI was marginally associated with the overall survival, with a hazard ratio of 0.92 (95% confidence interval: 0.84, 1.0) (P = 0.061). FACT-L score and the TOI were highly correlated (r = 0.96, P < 0.0001). TOI scores were higher in African Americans compared to Caucasians and increased with age. Conclusion: Our results suggest that gefitinib use in patients with NSCLC and poor PS may improve the QOL of older patients and African American patients. © the authors, publisher and licensee Libertas Academica Limited.
Keywords: Advanced non-small cell lung cancer; Gefitinib; Poor performance status; Quality of life

Does a community-based stress management intervention affect psychological adaptation among underserved black breast cancer survivors? - Lechner, S.C.; Whitehead, N.E.; Vargas, S.; Annane, D.W.; Robertson, B.R.; Carver, C.S.; Kobetz, E.; Antoni, M.H. (Journal of the National Cancer Institute - Monographs, 2014)
Background: In this randomized trial, Project CARE, we examined whether participation in a cognitive-behavioral stress management and breast cancer wellness and education program improved psychological outcomes among a sample of underserved black breast cancer survivors. Methods: Both complementary medicine interventions were 10-sessions, manualized, group-based, and were culturally adapted for black women in the community from evidence-based interventions. Participants were 114 black women (mean age = 51.1, 27-77 years) who had completed breast cancer treatment 0-12 months before enrollment (stages 0-IV, mean time since cancer diagnosis = 14.1 months). Women were enrolled upon completion of curative treatment (ie, surgical, chemotherapy, radiation oncology) and randomized to receive cognitivebehavioral stress management or cancer wellness and education program. Results: There was a remarkable 95% retention rate from baseline to 6-month follow-up. Participants in both conditions showed statistically significant improvement on indices of psychological well-being, including overall quality of life (Functional Assessment of Cancer Therapy-Breast), intrusive thoughts (Impact of Event Scale-Revised), depressive symptoms (Center for Epidemiologic Studies-Depression), and stress levels (Perceived Stress Scale) over the 6-month postintervention follow-up (all repeated measures analysis of variance within-subjects time effects: P < .05, except for overall mood; Profile of Mood States-Short Version). Contrary to hypotheses, however, condition × time effects were not statistically significant. Conclusions: Findings suggest that improvements in multiple measures over time may have been due to intensive training in stress management, extensive provision of breast cancer information, or participation in an ongoing supportive group of individuals from a similar racial background. Implications bear on decisions about appropriate control groups, the timing of intervention delivery during the treatment trajectory, and perceived support from the research team. © The Author 2014.

Genetic ancestry is associated with colorectal adenomas and adenocarcinomas in Latino populations - Hernandez-Suarez, G.; Sanabria, M.C.; Serrano, M.; Herran, O.F.; Perez, J.; Plata, J.L.; Zabaleta, J.; Tenesa, A. (European Journal of Human Genetics, 2014)
Colorectal cancer rates in Latin American countries are less than half of those observed in the United States. Latin Americans are the resultant of generations of an admixture of Native American, European, and African individuals. The potential role of genetic admixture in colorectal carcinogenesis has not been examined. We evaluate the association of genetic ancestry with colorectal neoplasms in 190 adenocarcinomas, 113 sporadic adenomas and 243 age-and sex-matched controls enrolled in a multicentric case-control study in Colombia. Individual ancestral genetic fractions were estimated using the STRUCTURE software, based on allele frequencies and assuming three distinct population origins. We used the Illumina Cancer Panel to genotype 1,421 sparse single-nucleotide polymorphisms (SNPs), and Northern and Western European ancestry, LWJ and Han Chinese in Beijing, China populations from the HapMap project as references. A total of 678 autosomal SNPs overlapped with the HapMap data set SNPs and were used for ancestry estimations. African mean ancestry fraction was higher in adenomas (0.13, 95% confidence interval (95% CI)=0.11-0.15) and cancer cases (0.14, 95% CI=0.12-0.16) compared with controls (0.11, 95% CI=0.10-0.12). Conditional logistic regression analysis, controlling for known risk factors, showed a positive association of African ancestry per 10% increase with both colorectal adenoma (odds ratio (OR)=1.12, 95% CI=0.97-1.30) and adenocarcinoma (OR=1.19, 95% CI=1.05-1.35). In conclusion, increased African ancestry (or variants linked to it) contributes to the increased susceptibility of colorectal cancer in admixed Latin American population. © 2014 Macmillan Publishers Limited All rights reserved.
Keywords: Colombia; colorectal neoplasm; genetic; Latin America; pedigree; polymorphism

Discussions about clinical trials among patients with newly diagnosed lung and colorectal cancer - Kehl, K.L.; Arora, N.K.; Schrag, D.; Ayanian, J.Z.; Clauser, S.B.; Klabunde, C.N.; Kahn, K.L.; Fletcher, R.H.; Keating, N.L. (Journal of the National Cancer Institute, 2014)
Background: Clinical trials are essential to establish the effectiveness of new cancer therapies, but less than 5% of adults with cancer enroll in trials. In addition to ineligibility or lack of available trials, barriers to enrollment may include limited patient awareness about the option of participation. Methods: We surveyed a multiregional cohort of patients with lung or colorectal cancer (or their surrogates) three to six months after diagnosis. We assessed whether respondents reported learning that clinical trial participation might be an option, and, if so, with whom they discussed trials. We used logistic regression to assess the association of patient characteristics with discussing trial participation and enrolling in trials. All statistical tests were two-sided. Results: Of 7887 respondents, 1114 (14.1%) reported discussing the possibility of clinical trial participation; most learned about trials from their physicians, and 287 patients (3.6% of all patients, 25.8% of trial discussants) enrolled. Among 2173 patients who received chemotherapy for advanced (stage III/IV lung or stage IV colorectal) cancer, 25.7% discussed trials, and 7.6% (29.5% of trial discussants) enrolled. Discussions were less frequent among older patients, African American or Asian vs white patients, and those with lower incomes and more comorbidity. Enrollment was higher among patients reporting shared vs physician-driven decisions (all P <.05). Conclusions: In this population-based cohort, only 14% of patients discussed participation in clinical trials. Discussions were more frequent among advanced cancer patients but were still reported by a minority of patients. Strategies to expand access to trials and facilitate patient-provider communication about participation may accelerate development of better cancer therapeutics. © The Author 2014. Published by Oxford University Press. All rights reserved.

Under-representation of racial minorities in prostate cancer studies submitted to the US Food and Drug Administration to support potential marketing approval, 1993-2013 - Wissing, M.D.; Kluetz, P.G.; Ning, Y.-M.; Bull, J.; Merenda, C.; Murgo, A.J.; Pazdur, R. (Cancer, 2014)
BACKGROUND US Food and Drug Administration (FDA) approval of new drugs depends on results from clinical trials that must be generalized to the US population. However, racial minorities are frequently under-represented in clinical studies. The enrollment of racial minorities was compared in key clinical studies submitted to the FDA in the last 10 years in support of potential marketing approval for prostate cancer (PCa) prevention or treatment. METHODS Patient demographic data were obtained from archival data sets of large registration trials submitted to the FDA to support proposed PCa indications. Six countries/regions were analyzed: the United States, Canada, Australia, Europe, the United Kingdom, and Eastern Europe. Background racial demographics were collected from national census data. RESULTS Seventeen key PCa clinical trials were analyzed. These trials were conducted in the past 20 years, comprising 39,574 patients with known racial information. Most patients were enrolled in the United States, but there appeared to be a trend toward increased non-US enrollment over time. In all countries, racial minorities were generally under-represented. There was no significant improvement in racial minority enrollment over time. The United States enrolled the largest nonwhite population (7.1%). CONCLUSIONS Over the past 20 years, racial minorities were consistently under-represented in key PCa trials. There is a need for effective measures that will improve enrollment of racial minorities. With increased global enrollment, drug developers should aim to recruit a patient population that resembles the racial demographics of the patient population to which drug use will be generalized upon approval. © 2014 American Cancer Society.
Keywords: clinical trial; phase 3; prostate cancer; race relations; US Food and Drug Administration

"We both just trusted and leaned on the Lord": a qualitative study of religiousness and spirituality among African American breast cancer survivors and their caregivers - Sterba, K.R.; Burris, J.L.; Heiney, S.P.; Ruppel, M.B.; Ford, M.E.; Zapka, J. (Quality of life research : an international journal of quality of life aspects of treatment, care and rehabilitation, 2014)
PURPOSE: Most breast cancer (BC) survivorship research focuses on the general population of survivors. Scant research investigates the potentially unique experiences of minorities, especially during and after the difficult transition from primary treatment to post-treatment. This qualitative study explored African American BC survivors' and caregivers' quality-of-life in the post-treatment period with a focus on social and spiritual well-being. METHODS: Participants included a convenience sample of African American women with stage I-III BC (N = 23) who completed treatment 6-24 months before enrollment. Primary caregivers (N = 22) included friends, spouses and other family members (21 complete dyads). Participants completed separate semi-structured telephone interviews. Template analysis was used to evaluate themes related to religiousness and spirituality, both across and within dyads. RESULTS: After treatment, religiousness and spirituality played a major role in both survivors' and caregivers' lives by: (1) providing global guidance, (2) guiding illness management efforts and (3) facilitating recovery. Participants described a spiritual connectedness with God and others in their social networks. Dyad members shared the goal of keeping a positive attitude and described positive growth from cancer. Few future concerns were expressed due to the belief that survivors were healed and "done" with cancer. Beyond practical and emotional support, provision of spiritual assistance was common. CONCLUSIONS: Results highlight the principal, positive role of religiousness and spirituality for African American BC survivors and caregivers after treatment. Findings emphasize the need to assess the importance of religious and spiritual beliefs and practices, and if appropriate, to provide resources that promote spiritual well-being.

Beyond cigarettes per day: A genome-wide association study of the biomarker carbon monoxide - Bloom, A.J.; Hartz, S.M.; Baker, T.B.; Chen, L.-S.; Piper, M.E.; Fox, L.; Martinez, M.; Hatsukami, D.; Johnson, E.O.; Laurie, C.C.; Saccone, N.L.; Goate, A.; et al. (Annals of the American Thoracic Society, 2014)
Rationale: The CHRNA5-CHRNA3-CHRNB4 locus is associated with self-reported smoking behavior and also harbors the strongest genetic associations with chronic obstructive pulmonary disease (COPD) and lung cancer. Because the associations with lung disease remain after adjustment for self-reported smoking behaviors, it has been asserted that CHRNA5-CHRNA3-CHRNB4 variants increase COPD and lung cancer susceptibility independently of their effects on smoking. Objectives: To compare the genetic associations of exhaled carbon monoxide (CO), a biomarker of current cigarette exposure, with self-reported smoking behaviors. Methods: A total of 1,521 European American and 247 African American current smokers recruited into smoking cessation studies were assessed for CO at intake before smoking cessation. DNA samples were genotyped using the Illumina Omni2.5 microarray. Genetic associations with CO and smoking behaviors (cigarettes smoked per day, Fagerstrom test for nicotine dependence) were studied. Measurements and Main Results: Variants in the CHRNA5-CHRNA3-CHRNB4 locus, including rs16969968, a nonsynonymous variant in CHRNA5, are genomewide association study-significantly associated with CO (β = 2.66; 95% confidence interval [CI], 1.74 -3.58; P = 1.65 × 10-8), and this association remains strong after adjusting for smoking behavior (β = 2.18; 95% CI, 1.32- 3.04; P = 7.47 × 10-7). The correlation between CO and cigarettes per day is statistically significantly lower ( z = 3.43; P = 6.07 × 10-4 ) in African Americans ( r = 0.14; 95% CI, 0.02- 0.26; P = 0.003) than in European-Americans (r = 0.36; 95% CI, 0.31-0.40; P = 0.0001). Conclusions: Exhaled CO, a biomarker that is simple to measure, captures aspects of cigarette smoke exposure in current smokers beyond the number of cigarettes smoked per day. Behavioral measures of smoking are therefore insufficient indices of cigarette smoke exposure, suggesting that genetic associations with COPD or lung cancer that persist after adjusting for self-reported smoking behavior may still reflect genetic effects on smoking exposure. Copyright © 2014 by the American Thoracic Society
Keywords: Chronic obstructive pulmonary disease; Lung cancer; Nicotine; Nicotinic receptor; Smoking

Decisional conflict in economically disadvantaged men with newly diagnosed prostate cancer: Baseline results from a shared decision-making trial - Kaplan, A.L.; Crespi, C.M.; Saucedo, J.D.; Connor, S.E.; Litwin, M.S.; Saigal, C.S. (Cancer, 2014)
BACKGROUND Decisional conflict is a source of anxiety and stress for men diagnosed with prostate cancer given uncertainty surrounding myriad treatment options. Few data exist to help clinicians identify which patients are at risk for decisional conflict. The purpose of this study was to examine factors associated with decisional conflict in economically disadvantaged men diagnosed with prostate cancer before any treatment choices were made. METHODS A total of 70 men were surveyed at a Veterans Administration clinic with newly diagnosed localized prostate cancer enrolled in a randomized trial testing a novel shared decision-making tool. Baseline demographic, clinical, and functional data were collected. Independent variables included age, race, education, comorbidity, relationship status, urinary/sexual dysfunction, and prostate cancer knowledge. Tested outcomes were Decisional Conflict Scale, Uncertainty Subscale, and Perceived Effectiveness Subscale. Multiple linear regression modeling was used to identify factors associated with decisional conflict. RESULTS Mean age was 63 years, 49% were African American, and 70% reported an income less than $30,000. Poor prostate cancer knowledge was associated with increased decisional conflict and higher uncertainty (P<.001 and P=0.001, respectively). Poor knowledge was also associated with lower perceived effectiveness (P=0.003) whereas being in a relationship was associated with higher decisional conflict (P=0.03). CONCLUSIONS Decreased patient knowledge about prostate cancer is associated with increased decisional conflict and lower perceived effective decision-making. Interventions to increase comprehension of prostate cancer and its treatments may reduce decisional conflict. Further work is needed to better characterize this relationship and identify effective targeted interventions. Cancer 2014;120:2721-2727. © 2014 American Cancer Society. In economically disadvantaged men with newly diagnosed prostate cancer, a poor understanding of the disease is associated with personal conflict surrounding the treatment decision. Targeted educational interventions may mitigate the decisional burden. © 2014 American Cancer Society.
Keywords: decisional conflict; knowledge; low socioeconomic status; patient education; prostate cancer

Risk factors for self-reported arm lymphedema among female breast cancer survivors: A prospective cohort study - Togawa, K.; Ma, H.; Sullivan-Halley, J.; Neuhouser, M.L.; Imayama, I.; Baumgartner, K.B.; Smith, A.W.; Alfano, C.M.; McTiernan, A.; Ballard-Barbash, R.; Bernstein, L. (Breast Cancer Research, 2014)
Introduction: Lymphedema is a potentially debilitating condition that occurs among breast cancer survivors. This study examines the incidence of self-reported lymphedema, timing of lymphedema onset, and associations between sociodemographic, clinical and lifestyle factors and lymphedema risk across racial-ethnic groups using data from a multicenter, multiethnic prospective cohort study of breast cancer survivors, the Health, Eating, Activity and Lifestyle Study. Methods: A total of 666 women diagnosed with breast cancer staged as in situ, localized or regional disease at ages 35 to 64years were recruited through the Surveillance, Epidemiology, and End Results registries in New Mexico (non-Hispanic white and Hispanic white), Los Angeles County (black), and Western Washington (non-Hispanic white) and followed for a median of 10.2years. We evaluated sociodemographic factors, breast cancer- and treatment-related factors, comorbidities, body mass index (BMI), hormonal factors, and lifestyle factors in relation to self-reported lymphedema by fitting Cox proportional hazards models, estimating hazard ratios (HR) and 95% confidence intervals (CI). Results: Over the follow-up period, 190 women (29%) reported lymphedema. The median time from breast cancer diagnosis to onset of lymphedema was 10.5months (range: 0.5 to 134.9months). Factors independently associated with lymphedema were total/modified radical mastectomy (versus partial/less than total mastectomy; HR = 1.37, 95% CI: 1.01 to 1.85), chemotherapy (versus no chemotherapy; HR = 1.48, 95% CI: 1.09 to 2.02), no lymph nodes removed (versus ≥10 lymph nodes removed; HR = 0.17, 95% CI: 0.08 to 0.33), pre-diagnostic BMI ≥30kg/m2 (versus BMI <25kg/m2; HR = 1.59, 95% CI: 1.09 to 2.31), and hypertension (versus no hypertension; HR = 1.49, 95% CI: 1.06 to 2.10). After adjusting for demographics and breast cancer- and treatment-related factors, no significant difference in lymphedema risk was observed across racial/ethnic groups. Analyses stratified by race/ethnicity showed that hypertension and chemotherapy were lymphedema risk factors only for black women. Conclusions: Breast cancer patients who have undergone extensive surgery or extensive lymph node dissection, or who have a higher BMI should be closely monitored for detection and treatment of lymphedema. Further studies are needed to understand the roles of chemotherapy and hypertension in the development of lymphedema. © 2014 Togawa et al.; licensee BioMed Central.

A 20-year-old female with hemoptysis and high blood pressure: An unusual case of papillary renal cell carcinoma - Olaniran, K.; Cheng, W.; Pulinthanathu, R. (American Journal of Case Reports, 2014)
Objective: Rare disease Background: Papillary renal cell carcinoma (PRCC) is a rare disease and is a carcinoma of the renal tubular epithelium, comprising only 10-15% of all renal cell carcinoma cases. The majority of cases occur in the sixth decade of life. PRCC rarely occurs before the fourth decade in the absence of family history. This paper describes an aggressive, sporadic case of PRCC in a 20-year-old female without family history and no risk factors. Case Report: A 20-year-old African American female was admitted for hemoptysis with elevated blood pressure and was found to have left peri-hilar opacification on chest X-ray. Further radiological studies led to the discovery of a large complex left renal lesion within the collecting system, infiltrating the renal artery and causing severe hydronephrosis with para-aortic lymphadenopathy. An MRI also showed signal heterogeneity in the L2 and L3 vertebrae. Biopsies of the left renal mass and a right endobronchial lesion confirmed metastatic PRCC. Treatment was commenced with a tyrosine kinase inhibitor. Within a few weeks, the vertebral metastatic lesions progressed to cause spinal compression. After targeted radiotherapy, the patient was referred to Memorial Sloan Kettering Cancer Center for enrolment in a clinical trial. Conclusions: PRCC rarely occurs in the second decade of life and even then, most such early cases occur in family clusters. PRCC also has a relatively benign course, constituting less than 10% of all metastatic renal cell carcinomas, further making this case a unique presentation. © Am J Case Rep, 2014.
Keywords: Carcinoma, Renal Cell; Hemoptysis; Hydronephrosis; Neoplasm Metastasis

Voluntary participation and comprehension of informed consent in a genetic epidemiological study of breast cancer in Nigeria - Marshall, P.A.; Adebamowo, C.A.; Adeyemo, A.A.; Ogundiran, T.O.; Strenski, T.; Zhou, J.; Rotimi, C.N. (BMC Medical Ethics, 2014)
Background: Studies on informed consent to medical research conducted in low or middle-income settings have increased, including empirical investigations of consent to genetic research. We investigated voluntary participation and comprehension of informed consent among women involved in a genetic epidemiological study on breast cancer in an urban setting of Nigeria comparing women in the case and control groups. Methods. Surveys were administered in face-to-face interviews with 215 participants following their enrollment in the genetic study (106 patients, 109 controls). Audio-taped in-depth interviews were conducted with a sub-sample of 17 (8%) women who completed the survey. Results: The majority of all participants reported being told that participation in the genetic study was voluntary (97%), that they did not feel pressured to participate in the study (99%), and that they could withdraw from the study (81%). The majority of the breast cancer patients (83%) compared to 58% of women in the control group reported that the study purpose was to learn about the genetic inheritance of breast cancer (OR 3.44; 95% CI =1.66, 7.14, p value = 0.001). Most participants reported being told about study procedures (95%) and study benefits (98%). Sixty-eight percent of the patients, compared to 47% of the control group reported being told about study risks (p-value <0.001). Of the 165 married women, 19% reported asking permission from their husbands to enroll in the breast cancer study; no one sought permission from local elders. In-depth interviews highlight the use of persuasion and negotiation between a wife and her husband regarding study participation. Conclusions: The global expansion of genetic and genomic research highlights our need to understand informed consent practices for studies in ethnically diverse cultural environments such as Africa. Quantitative and qualitative empirical investigations of the informed consent process for genetic and genomic research will further our knowledge of complex issues associated with communication of information, comprehension, decisional authority and voluntary participation. In the future, the development and testing of innovative strategies to promote voluntary participation and comprehension of the goals of genomic research will contribute to our understanding of strategies that enhance the consent process. © 2014 Marshall et al.; licensee BioMed Central Ltd.
Keywords: Breast cancer; Genetic epidemiological research; Informed consent; Nigeria

Characterization of black raspberry functional food products for cancer prevention human clinical trials - Gu, J.; Ahn-Jarvis, J.H.; Riedl, K.M.; Schwartz, S.J.; Clinton, S.K.; Vodovotz, Y. (Journal of Agricultural and Food Chemistry, 2014)
Our team is designing and fully characterizing black raspberry (BRB) food products suitable for long-term cancer prevention studies. The processing, scale-up, and storage effects on the consistency, quality, bioactive stability, and sensory acceptability of two BRB delivery systems of various matrices are presented. BRB dosage, pH, water activity, and texture were consistent in the scale-up production. Confections retained >90% of anthocyanins and ellagitannin after processing. Nectars had >69% of anthocyanins and >66% of ellagitannin retention, which varied with BRB dosage due to the processing difference. Texture remained unchanged during storage. BRB products consumed in a prostate cancer clinical trial were well accepted in sensory tests. Thus, this study demonstrates that two different BRB foods can be formulated to meet quality standards with a consistent bioactive pattern and successfully scaled up for a large human clinical trial focusing on cancer risk and other health outcomes. © 2013 American Chemical Society.
Keywords: black raspberry; consistency in characteristics; retention of phenolics; scale-up production; sensory acceptance; storage stability

Vitamin D deficiency predicts prostate biopsy outcomes - Murphy, A.B.; Nyame, Y.; Martin, I.K.; Catalona, W.J.; Hollowell, C.M.P.; Nadler, R.B.; Kozlowski, J.M.; Perry, K.T.; Kajdacsy-Balla, A.; Kittles, R. (Clinical Cancer Research, 2014)
Purpose: The association between vitamin D and prostate biopsy outcomes has not been evaluated. We examine serum vitamin D levels with prostate biopsy results in men with an abnormal prostate-specific antigen and/or digital rectal examination. Experimental Design: Serum 25-hydroxyvitamin D (25-OH D) was obtained from 667 men, ages 40 to 79 years, prospectively enrolled from Chicago urology clinics undergoing first prostate biopsy. Logistic regression was used to evaluate the associations between 25-OH D status and incident prostate cancer, Gleason score, and tumor stage. Results: Among European American (EA) men, there was an association of 25-OH D <12 ng/mL with higher Gleason score≥4+4 [OR, 3.66;95%confidence interval (CI), 1.41-9.50; P=0.008] and tumor stage [stage≥cT2b vs. ≤cT2a, OR, 2.42 (1.14-5.10); P=0.008]. In African American (AA) men, we find increased odds of prostate cancer diagnosis on biopsy with 25-OHD< 20 ng/mL [OR, 2.43 (1.20-4.94); P=0.01]. AA men demonstrated an association between 25-OH D < 12 ng/mL and Gleason ≥ 4+4 [OR, 4.89 (1.59-15.07); P=0.006]. There was an association with tumor stage≥cT2b vs.≤cT2a [OR, 4.22 (1.52-11.74); P= 0.003]. Conclusions: In AA men, vitamin D deficiency was associated with increased odds of prostate cancer diagnosis on biopsy. In both EA and AAmen, severe deficiency was positively associated with higher Gleason grade and tumor stage. © 2014 AACR.

Racial/ethnic differences in clinical trial enrollment, refusal rates, ineligibility, and reasons for decline among patients at sites in the National Cancer Institute's Community Cancer Centers Program - Langford, A.T.; Resnicow, K.; Dimond, E.P.; Denicoff, A.M.; Germain, D.S.; McCaskill-Stevens, W.; Enos, R.A.; Carrigan, A.; Wilkinson, K.; Go, R.S. (Cancer, 2014)
BACKGROUND This study examined racial/ethnic differences among patients in clinical trial (CT) enrollment, refusal rates, ineligibility, and desire to participate in research within the National Cancer Institute's Community Cancer Centers Program (NCCCP) Clinical Trial Screening and Accrual Log. METHODS Data from 4509 log entries were evaluated in this study. Four logistic regression models were run using physical/medical conditions, enrollment into a CT, patient eligible but declined a CT, and no desire to participate in research as dependent variables. RESULTS Age ≥ 65 years (OR = 1.51, 95% CI = 1.28-1.79), males (OR = 2.28, 95% CI = 1.92-2.71), and non-Hispanic black race (OR = 1.53, 95% CI = 1.2-1.96) were significantly associated with more physical/medical conditions. Age ≥ 65 years was significantly associated with lower CT enrollment (OR = 0.83, 95% CI = 0.7-0.98). Males (OR = 0.78, 95% CI = 0.65-0.94) and a higher grade level score for consent form readability (OR = 0.9, 95% CI = 0.83-0.97) were significantly associated with lower refusal rates. Consent page length ≥ 20 was significantly associated with lower odds of "no desire to participate in research" among CT decliners (OR = 0.75, 95% CI = 0.58-0.98). CONCLUSIONS There were no racial/ethnic differences in CT enrollment, refusal rates, or "no desire to participate in research" as the reason given for CT refusal. Higher odds of physical/medical conditions were associated with older age, males, and non-Hispanic blacks. Better management of physical/medical conditions before and during treatment may increase the pool of eligible patients for CTs. Future work should examine the role of comorbidities, sex, age, and consent form characteristics on CT participation. Cancer 2014;120:877-884. © 2013 American Cancer Society. There were no racial/ethnic differences in clinical trial (CT) enrollment, refusal rates, or "no desire to participate in research" as the reason given for CT refusal; however, higher odds of physical/medical conditions were associated with older age, males, and non-Hispanic blacks. Better management of physical/medical conditions before and during treatment may increase the pool of eligible patients for CTs. © 2013 American Cancer Society.
Keywords: African Americans; cancer; clinical trials; Hispanic; medical research; minorities; racial/ethnic

Dose response to vitamin D supplementation in African Americans: Results of a 4-arm, randomized, placebo-controlled trial - Ng, K.; Scott, J.B.; Drake, B.F.; Chan, A.T.; Hollis, B.W.; Chandler, P.D.; Bennett, G.G.; Giovannucci, E.L.; Gonzalez-Suarez, E.; Meyerhardt, J.A.; Emmons, K.M.; Fuchs, C.S. (American Journal of Clinical Nutrition, 2014)
Background: Association studies have suggested that lower circulating 25-hydroxyvitamin D [25(OH)D] in African Americans may partially underlie higher rates of cardiovascular disease and cancer in this population. Nonetheless, the relation between vitamin D supplementation and 25(OH)D concentrations in African Americans remains undefined. Objective: Our primary objective was to determine the doseresponse relation between vitamin D and plasma 25(OH)D. Design: A total of 328 African Americans in Boston, MA, were enrolled over 3 winters from 2007 to 2010 and randomly assigned to receive a placebo or 1000, 2000, or 4000 IU vitamin D3/d for 3 mo. Subjects completed sociodemographic and dietary questionnaires, and plasma samples were drawn at baseline and 3 and 6 mo. Results: Median plasma 25(OH)D concentrations at baseline were 15.1, 16.2, 13.9, and 15.7 ng/mL for subjects randomly assigned to receive the placebo or 1000, 2000, or 4000 IU/d, respectively (P = 0.63). The median plasma 25(OH)D concentration at 3 mo differed significantly between supplementation arms at 13.7, 29.7, 34.8, and 45.9 ng/mL, respectively (P < 0.001). An estimated 1640 IU vitamin D3/d was needed to raise the plasma 25(OH)D concentration to ≥20 ng/mL in ≥97.5% of participants, whereas a dose of 4000 IU/d was needed to achieve concentrations ≥33 ng/mL in ≥80% of subjects. No significant hypercalcemia was seen in a subset of participants. Conclusions: Within African Americans, an estimated 1640 IU vitamin D3/d was required to achieve concentrations of plasma 25(OH)D recommended by the Institute of Medicine, whereas 4000 IU/d was needed to reach concentrations predicted to reduce cancer and cardio-vascular disease risk in prospective observational studies. These results may be helpful for informing future trials of disease prevention. This trial was registered at clinicaltrials.gov as NCT00585637. © 2014 American Society for Nutrition.

An evaluation of a community-academic-clinical partnership to reduce prostate cancer disparities in the south - Friedman, D.B.; Owens, O.L.; Jackson, D.D.; Johnson, K.M.; Gansauer, L.; Dickey, J.; Miller, R.; Payne, J.; Bearden, J.D.; Hebert, J.R. (Journal of Cancer Education, 2014)
Engaging partners in the planning, implementation, and evaluation of cancer education programs is critical for improving the health of our communities. A 2-year pilot education intervention on prostate cancer decision making and participation in medical research was funded by the National Cancer Institute. The partnership involving community members and clinical staff at a cancer center was used to develop recruitment strategies and plan for the implementation of the intervention with African-American middle-age and older men and female family members. We assessed partners' perceptions of this community-academic-clinical research collaboration. In year 2, eight project advisory council members were selected among existing partners and year 1 participants to serve as a formal committee. Council members were required to participate in telephone and in person meetings and actively support recruitment/implementation efforts. At the conclusion of the project, 20 individuals (all clinical and community partners, including the eight advisory council members) were invited to complete a survey to assess their perceived impact of the collaboration on the community and provide suggestions for future collaborations. Most partners agreed that their organization benefitted from the collaboration and that various aspects of the advisory council process (e.g.; both formal and informal communication) worked well. The most noted accomplishment of the partnership related to leveraging the collaboration to make men more knowledgeable about prostate cancer decision making. Suggested improvements for future collaborations included distributing more frequent updates regarding project successes. Evaluating partners' perceptions of this collaboration provided important recommendations for future planning, implementation, and evaluation of community-based cancer education programs. © 2013 Springer Science+Business Media New York.
Keywords: Assessment; Community and clinical partnerships; Prostate cancer; Research collaboration

Patient-reported outcomes in women with breast cancer enrolled in a dual-center, double-blind, randomized controlled trial assessing the effect of acupuncture in reducing aromatase inhibitor-induced musculoskeletal symptoms - Bao, T.; Cai, L.; Snyder, C.; Betts, K.; Tarpinian, K.; Gould, J.; Jeter, S.; Medeiros, M.; Chumsri, S.; Bardia, A.; Tan, M.; Singh, H.; et al. (Cancer, 2014)
Background Aromatase inhibitors (AIs) have been associated with decrements in patient-reported outcomes (PROs). The objective of this study was to assess whether real acupuncture (RA), compared with sham acupuncture (SA), improves PROs in patients with breast cancer who are receiving an adjuvant AI. Methods Postmenopausal women with a stage 0 through III breast cancer who received an AI and had treatment-associated musculoskeletal symptoms were randomized to receive 8 weekly RA versus SA in a dual-center, randomized controlled trial. The National Surgical Adjuvant Breast and Bowel Project (NSABP) menopausal symptoms questionnaire, the Center for Epidemiological Studies Depression (CESD) scale, the Hospital Anxiety and Depression Scale (HADS), the Pittsburgh Sleep Quality Index (PSQI), the hot flash daily diary, the Hot Flash-Related Daily Interference Scale (HFRDI), and the European quality-of-life survey (EuroQol) were used to assess PROs at baseline and at 4weeks, 8 weeks, and 12 weeks. Results The intention-to-treat analysis included 23 patients in the RA arm and 24 patients in the SA arm. There were no significant differences in baseline characteristics between the 2 groups. Compared with baseline, scores in the RA arm improved significantly at week 8 on the CESD (P =.022), hot flash severity (P =.006), hot flash frequency (P =.011), the HFRDI (P =.014), and NSABP menopausal symptoms (P =.022); scores in the SA arm improved significantly on the EuroQol (P =.022),the HFRDI (P =.043), and NSABP menopausal symptoms (P =.005). Post-hoc analysis indicated that African American patients (n = 9) benefited more from RA than SA compared with non-African American patients (n = 38) in reducing hot flash severity (P <.001) and frequency (P <.001) scores. Conclusions Both RA and SA were associated with improvement in PROs among patients with breast cancer who were receiving AIs, and no significant difference was detected between arms. Racial differences in response to acupuncture warrant further study. © 2013 American Cancer Society.
Keywords: acupuncture; aromatase inhibitor; musculoskeletal symptoms; patient-reported outcomes

High serum miR-19a levels are associated with inflammatory breast cancer and are predictive of favorable clinical outcome in patients with metastatic HER2+ inflammatory breast cancer - Anfossi, S.; Giordano, A.; Gao, H.; Cohen, E.N.; Tin, S.; Wu, Q.; Garza, R.J.; Debeb, B.G.; Alvarez, R.H.; Valero, V.; Hortobagyi, G.N.; Calin, G.A.; et al. (PLoS ONE, 2014)
Introduction: Altered serum microRNA (miRNA) levels may be correlated with a dysregulated expression pattern in parental tumor tissue and reflect the clinical evolution of disease. The overexpression of miR-21, miR-10b, and miR-19a is associated with the acquisition of malignant characteristics (increased tumor cell proliferation, migration, invasion, dissemination, and metastasis); thus, we determined their utility as serum biomarkers for aggressive breast cancer (HER2-overexpressed or -amplified [HER2+] and inflammatory breast cancer [IBC]). Experimental Design: In this prospective study, we measured miR-21, miR-10b, and miR-19a levels using quantitative reverse transcriptase-polymerase chain reaction in the serum of 113 breast cancer patients and determined their association with clinicopathologic factors and clinical outcome. Thirty healthy donors with no history of cancer were enrolled as controls. Results: Patients with non-metastatic HER2+ breast cancer had higher serum miR-21 median levels than patients with nonmetastatic HER2- disease (p = 0.044); whereas patients with metastatic HER2+ breast cancer had higher serum miR-10b median levels than patients with metastatic HER2- disease (p = 0.0004). There were no significant differences in serum miR- 19a median levels between HER2+ and HER22 groups, regardless of the presence of metastases. High serum miR-19a levels were associated with IBC (p = 0.039). Patients with metastatic IBC had significantly higher serum miR-19a median levels than patients with metastatic non-IBC (p = 0.019). Finally, high serum miR-19a levels were associated with longer progression-free survival time (10.3 vs. 3.2 months; p = 0.022) and longer overall survival time (median not reached vs. 11.2 months; p = 0.003) in patients with metastatic HER2+ IBC. Conclusion: High levels of miR-21 and miR-10b were present in the serum of patients with non-metastatic and metastatic HER2+ breast cancer, respectively. High levels of serum miR-19a may represent a biomarker for IBC that is predictive for favorable clinical outcome in patients with metastatic HER2+ IBC. © 2014 Anfossi et al.

Breast cancer survivors willingness to participate in an acupuncture clinical trial: A qualitative study - Schapira, M.M.; Mackenzie, E.R.; Lam, R.; Casarett, D.; Seluzicki, C.M.; Barg, F.K.; Mao, J.J. (Supportive Care in Cancer, 2014)
Purpose: Acupuncture is a complementary and alternative medicine (CAM) modality that shows promise as a component of supportive breast cancer care. Lack of robust recruitment for clinical trial entry has limited the evidence base for acupuncture as a treatment modality among breast cancer survivors. The objective of this study is to identify key decision-making factors among breast cancer survivors considering entry into an acupuncture clinical trial for treatment of symptoms. Methods: Semistructured interviews were conducted among African-American (n=12) and Caucasian (n=13) breast cancer survivors. Verbatim transcripts were made and analyzed by two or more independent coders using NVivo software. Major recurring themes were identified and a theoretical framework developed. Results: Six themes emerged reflecting key attributes of the decision to enter a clinical trial: (1) symptom appraisal, (2) practical barriers (e.g., distance and travel), (3) beliefs about the interventions (e.g., fear of needles and dislike of medications), (4) comfort with elements of clinical trial design (e.g., randomization, the nature of the control intervention, and blinding), (5) trust, and (6) altruism. African-American and Caucasian women weighed similar attributes but differed in the information sources sought regarding clinical trial entry and in concerns regarding the use of a placebo in a clinical trial. Conclusions: Our findings contribute to the development of a theoretical model of decision making for breast cancer survivors considering participation in a CAM clinical trial. Insights regarding the decision making process can inform interventions to support informed decision making and robust recruitment to CAM trials among cancer survivors. © 2013 Springer-Verlag.
Keywords: Acupuncture; Breast cancer survivors; Clinical trials; Decision making

African-American breast cancer survivors' preferences for various types of physical activity interventions: A Sisters Network Inc. web-based survey - Paxton, R.J.; Nayak, P.; Taylor, W.C.; Chang, S.; Courneya, K.S.; Schover, L.; Hodges, K.; Jones, L.A. (Journal of Cancer Survivorship, 2014)
Background: Needs assessments are essential to developing lifestyle interventions for minority populations. To our knowledge, no physical activity (PA) needs assessment studies have been conducted for African-American (AA) breast cancer survivors. The purpose of this study was to determine the PA intervention preferences of AA breast cancer survivors and determine whether these preferences differ according to medical and sociodemographic factors. Methods: AA breast cancer survivors (n = 475, mean age = 54 years) were recruited using ads sent via email and social media sites. Preferences for the mode of intervention delivery were assessed via web-based questionnaires. Descriptive statistics were used to characterize their interests in PA interventions, and subgroup differences were assessed. Results: About 49 % (142 out of 291) of the participants who completed the survey were obese and 54 % did not meet the recommended guidelines for PA. Most (90 %) participants reported that they could participate in PA, and many (67 %) indicated that they were interested in receiving program materials. Participants expressed the greatest interest in email (50 %)-, web (48 %)-, or mail-based (45 %) over group (39 %), and telephone (10 %). Women also expressed the greatest interest in participating in studies that promoted walking and resistance or strength training. Intervention preferences did not differ significantly (P > 0.05) across sociodemographic or medical factors. Conclusion: Most AA breast cancer survivors can participate in PA, and many are interested in interventions that promoted walking and resistance training and were delivered via the email or web. The development of culturally sensitive interventions that provide activities consistent with preferences can assist AA breast cancer survivors to adopt and maintain a healthy lifestyle. Implications for Cancer Survivors: Despite evidence that AA breast cancer survivors are at increased risk for poor breast cancer-specific outcomes, they are underrepresented in clinical trials promoting positive health behaviors. In this study, we propose to assess their exercise preferences and receptivity to a culturally appropriate PA intervention developed in collaboration with the Sisters Network Inc. Health promotion programs developed in collaboration with a community-based organization may aid in the development of research tools and resources that AA breast cancer survivors are receptive to using. © 2013 Springer Science+Business Media New York.
Keywords: African-American women; Breast cancer; Cancer survivor; Cancer survivorship; Health disparities; Physical activity

A community-based, culturally relevant intervention to promote healthy eating and physical activity among middle-aged African American women in rural Alabama: Findings from a group randomized controlled trial - Scarinci, I.C.; Moore, A.; Wynn-Wallace, T.; Cherrington, A.; Fouad, M.; Li, Y. (Preventive Medicine, 2014)
Objective: We examined the efficacy of a community-based, culturally relevant intervention to promote healthy eating and physical activity among African American (AA) women between the ages of 45-65 years, residing in rural Alabama. Methods: We conducted a group randomized controlled trial with counties as the unit of randomization that evaluated two interventions based on health priorities identified by the community: (1) promotion of healthy eating and physical activity; and (2) promotion of breast and cervical cancer screening. A total of 6 counties with 565 participants were enrolled in the study between November 2009 and October 2011. Results: The overall retention rate at 24-month follow-up was 54.7%. Higher retention rate was observed in the "healthy lifestyle" arm (63.1%) as compared to the "screening" arm (45.3%). Participants in the "healthy lifestyle" arm showed significant positive changes compared to the "screening" arm at 12-month follow-up with regard to decrease in fried food consumption and an increase in both fruit/vegetable intake and physical activity. At 24-month follow-up, these positive changes were maintained with healthy eating behaviors, but not engagement in physical activity. Conclusions: A culturally relevant intervention, developed in collaboration with the target audience, can improve (and maintain) healthy eating among AA women living in rural areas. © 2014 Elsevier Inc.
Keywords: African American; Behavior change; Healthy lifestyle; Rural; Women

Individual, provider, and system risk factors for breast and cervical cancer screening among underserved black, Latina, and Arab women - Roman, L.; Meghea, C.; Ford, S.; Penner, L.; Hamade, H.; Estes, T.; Williams, K.P. (Journal of Women's Health, 2014)
Background: Socioeconomic and racial/ethnic disparities in breast and cervical cancer screening persist. An exploratory study was conducted to better understand co-occurring risk factors in underserved groups that could inform interventions to improve screening adherence. The objective of this study was to examine associations between breast and cervical cancer screening adherence and co-occurring risk factors in three racial/ethnic groups of underserved women. Methods: Black, Latina, and Arab women (N=514), ages 21 to 70 years, were enrolled into the Kin KeeperSM randomized controlled trial in communities around Detroit, Michigan. We used participant baseline assessments (e.g., demographic characteristics, health literacy) to explore screening risks using an additive approach and multivariate logistic analyses. Results: For black women, having more health literacy risks were associated with reduced odds of a clinical breast exam (CBE), mammogram, and Papanicolaou (Pap) test; more competing priorities were associated with reduced odds of a Pap test; lack of doctor mammogram recommendation was significantly associated with decreased odds of CBE. For Latina women, lack of doctor recommendations were significantly associated with decreased odds of CBE, mammogram, and Pap test. For Arab women, lack of doctor recommendations were significantly associated with decreased odds of CBE, mammogram, and Pap test; more competing priorities were significantly associated with reduced odds of CBE and Pap test. All results were significant at p<0.05. Conclusions: Characteristics associated with breast and cervical screening adherence differs among Black, Latina, and Arab underserved women. Interventions to improve screening should be tailored for racial/ethnic groups with particular attention to competing survival priorities, health literacy risks factors, and provider recommendations. © Copyright 2014, Mary Ann Liebert, Inc. 2014.

Effective recruitment strategies and community-based participatory research: Community networks program centers' recruitment in cancer prevention studies - Greiner, K.A.; Friedman, D.B.; Adams, S.A.; Gwede, C.K.; Cupertino, P.; Engelman, K.K.; Meade, C.D.; Hebert, J.R. (Cancer Epidemiology Biomarkers and Prevention, 2014)
Background: Community-based participatory research (CBPR) approaches that involve community and academic partners in activities ranging from protocol design through dissemination of study findings can increase recruitment of medically underserved and underrepresented racial/ethnic minority populations into biomedical research. Methods: Five cancer screening and prevention trials in three National Cancer Institute (Bethesda, MD)-funded Community Networks Program Centers (CNPC), in Florida, Kansas, and South Carolina, were conducted across diverse populations. Data were collected on total time period of recruitment, ratios of participants enrolled over potential participants approached, selected CBPR strategies, capacity-building development, and systematic procedures for community stakeholder involvement. Results: Community-engaged approaches used included establishing colearning opportunities, participatory procedures for community-Academic involvement, and community and clinical capacity building. A relatively large proportion of individuals identified for recruitment was actually approached (between 50% and 100%). The proportion of subjects who were eligible among all those approached ranged from 25% to more than 70% (in the community setting). Recruitment rates were very high (78%-100% of eligible individuals approached) and the proportion who refused or who were not interested among those approached was very low (5%-11%). Conclusions: Recruitment strategies used by the CNPCs were associated with low refusal and high enrollment ratios of potential subjects. Adherence to CBPR principles in the spectrum of research activities, from strategic planning to project implementation, has significant potential to increase involvement in biomedical research and improve our ability to make appropriate recommendations for cancer prevention and control programming in underrepresented diverse populations. Impact: CBPR strategies should be more widely implemented to enhance study recruitment. © 2014 American Association for Cancer Research.

Body mass index and mortality among blacks and whites adults in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial - Xiao, Q.; Hsing, A.W.; Park, Y.; Moore, S.C.; Matthews, C.E.; De González, A.B.; Kitahara, C.M. (Obesity, 2014)
Objective In a large prospective cohort, we examined the relationship of body mass index (BMI) with mortality among blacks and compared the results to those among whites in this population. Design and Methods The study population consisted of 7,446 non-Hispanic black and 130,598 white participants, ages 49-78 at enrollment, in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial. BMI at baseline, BMI at age 20, and BMI change were calculated using self-reported and recalled height and weight. Relative risks were stratified by race and sex and adjusted for age, education, marital status, and smoking. Results During follow-up, 1,495 black and 18,236 white participants died (mean = 13 years). Clear J-shaped associations between BMI and mortality were observed among white men and women. Among black men and women, the bottoms of these curves were flatter, and increasing risks of death with greater BMI were observed only at higher BMI levels (≥35.0). Associations for BMI at age 20 and BMI change also appeared to be stronger in magnitude in whites versus blacks, and these racial differences appeared to be more pronounced among women. Conclusion Our results suggest that BMI may be more weakly associated with mortality in blacks, particularly black women, than in whites. Copyright © 2013 The Obesity Society.

Implementation intentions and colorectal screening: A randomized trial in safety-net clinics - Greiner, K.A.; Daley, C.M.; Epp, A.; James, A.; Yeh, H.-W.; Geana, M.; Born, W.; Engelman, K.K.; Shellhorn, J.; Hester, C.M.; Lemaster, J.; Buckles, D.C.; et al. (American Journal of Preventive Medicine, 2014)
Context Low-income and racial/ethnic minority populations experience disproportionate colorectal cancer (CRC) burden and poorer survival. Novel behavioral strategies are needed to improve screening rates in these groups. Background The study aimed to test a theoretically based "implementation intentions" intervention for improving CRC screening among unscreened adults in urban safety-net clinics. Design Randomized controlled trial. Setting/participants Adults (N=470) aged ≥50 years, due for CRC screening, from urban safety-net clinics were recruited. Intervention The intervention (conducted in 2009-2011) was delivered via touchscreen computers that tailored informational messages to decisional stage and screening barriers. The computer then randomized participants to generic health information on diet and exercise (Comparison group) or "implementation intentions" questions and planning (Experimental group) specific to the CRC screening test chosen (fecal immunochemical test or colonoscopy). Main outcome measures The primary study outcome was completion of CRC screening at 26 weeks based on test reports (analysis conducted in 2012-2013). Results The study population had a mean age of 57 years and was 42% non-Hispanic African American, 28% non-Hispanic white, and 27% Hispanic. Those receiving the implementation intentions-based intervention had higher odds (AOR=1.83, 95% CI=1.23, 2.73) of completing CRC screening than the Comparison group. Those with higher self-efficacy for screening (AOR=1.57, 95% CI=1.03, 2.39), history of asthma (AOR=2.20, 95% CI=1.26, 3.84), no history of diabetes (AOR=1.86, 95% CI=1.21, 2.86), and reporting they had never heard that "cutting on cancer" makes it spread (AOR=1.78, 95% CI=1.16, 2.72) were more likely to complete CRC screening. Conclusions The results of this study suggest that programs incorporating an implementation intentions approach can contribute to successful completion of CRC screening even among very low-income and diverse primary care populations. Future initiatives to reduce CRC incidence and mortality disparities may be able to employ implementation intentions in large-scale efforts to encourage screening and prevention behaviors.

Neighborhood factors associated with time to resolution following an abnormal breast or cervical cancer screening test - Plascak, J.J.; Llanos, A.A.; Pennell, M.L.; Weier, R.C.; Paskett, E.D. (Cancer Epidemiology Biomarkers and Prevention, 2014)
Background: The effect of neighborhood and healthcare access factors on cancer outcomes among patients enrolled in navigator programs is not clearly understood. This study assessed associations between: (i) neighborhood factors and diagnostic time to resolution (TTR) and (ii) geographic access and TTR following an abnormal breast or cervical cancer screening test among women participating in the Ohio Patient Navigator Research Program (OPNRP). Methods: Patient (demographic, socioeconomic status, home-to-clinic distance) and neighborhood (deprivation, racial segregation) characteristics of 801 women living in one of 285 census tracts (CT) in greater Columbus, Ohio were examined. Randomization to receive navigation occurred at the clinic level. Multilevel Cox regression and spatial analysis were used to estimate effects of various factors on TTR and assess model assumptions, respectively. Results: TTR increased as neighborhood deprivation increased. After adjustment for age, friend social support, education, and healthcare status, the TTR among women living in a neighborhood with a moderate median household income (between $36,147 and $53,099) was shorter compared with women living in low median household income neighborhoods (<$36,147; P < 0.05). There is little evidence that unmeasured confounders are geographically patterned. Conclusions: Increased neighborhood socioeconomic deprivation was associated with longer TTR following an abnormal breast or cervical cancer screening test. Impact: These results highlight the need for addressing patient- and neighborhood-level factors to reduce cancer disparities among underserved populations. © 2014 American Association for Cancer Research.

Ethnicity and outcome of young breast cancer patients in the United Kingdom: The POSH study - Copson, E.; Maishman, T.; Gerty, S.; Eccles, B.; Stanton, L.; Cutress, R.I.; Altman, D.G.; Durcan, L.; Simmonds, P.; Jones, L.; Tapper, W.; Eccles, D. (British Journal of Cancer, 2014)
Background:Black ethnic groups have a higher breast cancer mortality than Whites. American studies have identified variations in tumour biology and unequal health-care access as causative factors. We compared tumour pathology, treatment and outcomes in three ethnic groups in young breast cancer patients treated in the United Kingdom.Methods:Women aged ≤40 years at breast cancer diagnosis were recruited to the POSH national cohort study (MREC: 00/06/69). Personal characteristics, tumour pathology and treatment data were collected at diagnosis. Follow-up data were collected annually. Overall survival (OS) and distant relapse-free survival (DRFS) were assessed using Kaplan-Meier curves, and multivariate analyses were performed using Cox regression.Results:Ethnicity data were available for 2915 patients including 2690 (91.0%) Whites, 118 (4.0%) Blacks and 87 (2.9%) Asians. Median tumour diameter at presentation was greater in Blacks than Whites (26.0 mm vs 22.0 mm, P=0.0103), and multifocal tumours were more frequent in both Blacks (43.4%) and Asians (37.0%) than Whites (28.9%). ER/PR/HER2-negative tumours were significantly more frequent in Blacks (26.1%) than Whites (18.6%, P=0.043). Use of chemotherapy was similarly high in all ethnic groups (89% B vs 88.6% W vs 89.7% A). A 5-year DRFS was significantly lower in Blacks than Asians (62.8% B vs 77.0% A, P=0.0473) or Whites (62.8 B% vs 77.0% W, P=0.0053) and a 5-year OS for Black patients, 71.1% (95% CI: 61.0-79.1%), was significantly lower than that of Whites (82.4%, 95% CI: 80.8-83.9%, W vs B: P=0.0160). In multivariate analysis, Black ethnicity had an effect on DRFS in oestrogen receptor (ER)-positive patients that is independent of body mass index, tumour size, grade or nodal status, HR: 1.60 (95% CI: 1.03-2.47, P=0.035).Conclusion:Despite equal access to health care, young Black women in the United Kingdom have a significantly poorer outcome than White patients. Black ethnicity is an independent risk factor for reduced DRFS particularly in ER-positive patients. © 2014 Cancer Research UK.
Keywords: breast cancer; ethnicity; prognosis

Mortality and complications after prostate biopsy in the Prostate, Lung, Colorectal and Ovarian Cancer Screening (PLCO) trial - Pinsky, P.F.; Parnes, H.L.; Andriole, G. (BJU International, 2014)
Objective To examine mortality and morbidity after prostate biopsy in the intervention arm of the Prostate, Lung, Colorectal and Ovarian Cancer Screening (PLCO) trial. Subjects and Methods Abstractors from the PLCO trial recorded the types and dates of diagnostic follow-up procedures after positive screens and documented the types and dates of resultant complications. Cancers and deaths among the participants were tracked. The mortality rate in the 120-day period after prostate biopsy was compared with a control rate of deaths in the 120-day period after a negative screen in men without biopsy. Multivariate analysis was performed to control for potential confounders, including age, comorbidities and smoking. Rates of any complication, infectious and non-infectious complications were computed among men with a negative biopsy. Multivariate analysis was used to examine the risk factors for complications. Results Of the 37 345 men enrolled in the PLCO trial (intervention arm), 4861 had at least one biopsy after a positive screen and 28 661 had a negative screen and no biopsy. The 120-day mortality rate after biopsy was 0.95 (per 1000), compared with the control group rate of 1.8; the multivariate relative risk was 0.49 (95% CI: 0.2-1.1). Among 3706 negative biopsies, the rates (per 1000) of any complication, infectious and non-infections complications were 20.2, 7.8 and 13.0, respectively. A history of prostate enlargement or inflammation was significantly associated with higher rates of both infectious (odds ratio [OR] = 3.7) and non-infectious (OR = 2.2) complications. Black race was associated with a higher infectious complications rate (OR = 7.1) and repeat biopsy was associated with lower rates of non-infectious complications (OR = 0.3). Conclusion Mortality rates were not found to be higher after prostate biopsy in the PLCO trial and complications were relatively infrequent, with several risk factors identified. © Published 2013. This article has been contributed to by US Government employees and their work is in the public domain in the USA. BJU International © 2013 BJU International.
Keywords: complications; mortality; prostate biopsy; prostate-specific antigen; PSA

Dealing with the financial burden of cancer: perspectives of older breast cancer survivors - Pisu, M.; Martin, M.Y.; Shewchuk, R.; Meneses, K. (Supportive Care in Cancer, 2014)
Purpose: Financial burden among cancer survivors is often overlooked in survivorship care planning. Cancer survivors with limited incomes may be particularly affected. Yet, little data are available to address financial issues among them. Eliciting the survivors’ perspectives on how to deal with this financial burden is a first crucial step to identifying the means to provide this supportive care. Methods: In this pilot study, three nominal group technique (NGT) sessions were conducted with a convenience sample of 23 older breast cancer survivors (age 52 to 83) recruited from a county safety net hospital and a Comprehensive Cancer Center. One single NGT question was posed in these sessions, namely “What could help women deal with the financial burden that cancer brings to them and their families?” Survivors responded in an iterative fashion and then ranked the most relevant responses. Results: The most relevant responses addressed the (1) need for affordable insurance; (2) need to have prompt information on treatment costs patients will face, insurance coverage, and agencies or programs that provide needed products and services; and (3) need to access social workers, navigators, support groups, or others knowledgeable about available resources. Survivors also suggested that physicians become aware of cancer costs and financial issues faced by patients and consider costs in their treatment plans. Conclusions: Older survivors face financial challenges for which there are few available resources. They suggested several avenues to address cancer-related financial issues that may be considered in developing supportive interventions. © 2014, Springer-Verlag Berlin Heidelberg.
Keywords: Breast cancer; Financial burden; Financial toxicity; Older women; Survivorship

Treatment of small cell lung cancer in academic and community settings: Factors associated with receiving standard therapy and survival - Parsons, H.M.; Harlan, L.C.; Stevens, J.L.; Ullmann, C.D. (Cancer Journal (United States), 2014)
PURPOSE: Small cell lung cancer (SCLC) historically has had poor prognosis. Clinical trials have demonstrated improved survival among patients receiving standard platinum-/etoposide-based chemotherapy. Whereas treatment patterns and outcomes have been evaluated for patients with SCLC in clinical trials, population-based practice patterns are not well known. METHODS: The National Cancer Institute's Patterns of Care study was used to evaluate patient and provider factors associated with standard treatment, clinical trial enrollment, and 12-month relative hazard of death. RESULTS: Among 931 patients with SCLC diagnosed in 2007 in academic and community settings, 72.2% of patients with limited-stage (LS) disease received chemoradiation and 42.2% of patients with extensive-stage (ES) disease received chemotherapy only; the expected treatment scenarios by stage. Less than 1% of the patients enrolled in clinical trials and 2.1% of the patients with LS disease and 3.4% of the patients with ES disease refused any type of treatment. Patients 80 years or older at diagnosis and those with pneumonia/lung collapse were less likely to receive chemoradiation for LS disease. Patients treated in hospitals with residency programs were more likely to receive chemotherapy for ES disease, and patients 80 years or older were less likely to receive chemotherapy for ES disease. Finally, female patients with LS disease, black patients with ES disease, and all patients who received chemotherapy compared to receiving radiation alone or no therapy experienced significantly lower mortality. DISCUSSION: Despite the demonstrated lower mortality, a relatively large proportion of patients with SCLC are not treated with a standard treatment regimen. Future studies should evaluate efforts to promote use of appropriate treatment regimens and encourage clinical trial participation. Copyright © 2014 Lippincott Williams & Wilkins.
Keywords: lung cancer; small cell; survival; treatment patterns

Nutrition and physical activity cancer prevention guidelines, cancer risk, and mortality in the women's health initiative - Thomson, C.A.; McCullough, M.L.; Wertheim, B.C.; Chlebowski, R.T.; Martinez, M.E.; Stefanick, M.L.; Rohan, T.E.; Manson, J.E.; Tindle, H.A.; Ockene, J.; Vitolins, M.Z.; Wactawski-Wende, J.; et al. (Cancer Prevention Research, 2014)
Healthy lifestyle behaviors are recommended to reduce cancer risk and overall mortality. Adherence to cancer-preventive health behaviors and subsequent cancer risk has not been evaluated in a diverse sample of postmenopausal women. We examined the association between the American Cancer Society (ACS) Nutrition and Physical Activity Cancer Prevention Guidelines score and risk of incident cancer, cancer-specific mortality, and all-cause mortality in 65,838 postmenopausal women enrolled in the Women's Health Initiative Observational Study. ACS guidelines scores (0-8 points) were determined from a combined measure of diet, physical activity, body mass index (current and at age 18 years), and alcohol consumption. After a mean follow-up of 12.6 years, 8,632 incident cancers and 2,356 cancer deaths were identified. The highest ACS guidelines scores compared with the lowest were associated with a 17% lower risk of any cancer [HR, 0.83; 95% confidence interval (CI), 0.75-0.92], 22% lower risk of breast cancer (HR, 0.78; 95% CI, 0.67-0.92), 52% lower risk of colorectal cancer (HR, 0.48; 95% CI, 0.32-0.73), 27% lower risk of all-cause mortality, and 20% lower risk of cancer-specific mortality (HR, 0.80; 95% CI, 0.71-0.90). Associations with lower cancer incidence and mortality were generally strongest among Asian, black, and Hispanic women and weakest among non-Hispanic whites. Behaviors concordant with Nutrition and Physical Activity Cancer Prevention Guidelines were associated with lower risk of total, breast, and colorectal cancers and lower cancer-specific mortality in postmenopausal women. ©2013 American Association for Cancer Research.

Commentary on "Intermittent versus continuous androgen deprivation in prostate cancer." - Eggener, S. (Urologic Oncology: Seminars and Original Investigations, 2014)
Background: Castration resistance occurs in most patients with metastatic hormone-sensitive prostate cancer who are receiving androgen-deprivation therapy. Replacing androgens before progression of the disease is hypothesized to prolong androgen dependence. Methods: Men with newly diagnosed, metastatic, hormone-sensitive prostate cancer, a performance status of 0 to 2, and a prostate-specific antigen (PSA) level of 5. ng per milliliter or higher received a luteinizing hormone-releasing hormone analogue and an antiandrogen agent for 7 months. We then randomly assigned patients in whom the PSA level fell to 4. ng per milliliter or lower to continuous or intermittent androgen deprivation, with patients stratified according to prior or no prior hormonal therapy, performance status, and extent of disease (minimal or extensive). The coprimary objectives were to assess whether intermittent therapy was noninferior to continuous therapy with respect to survival, with a one-sided test with an upper boundary of the hazard ratio of 1.20, and whether quality of life differed between the groups 3 months after randomization. Results: A total of 3040 patients were enrolled, of whom 1535 were included in the analysis: 765 randomly assigned to continuous androgen deprivation and 770 assigned to intermittent androgen deprivation. The median follow-up period was 9.8 years. Median survival was 5.8 years in the continuous-therapy group and 5.1 years in the intermittent-therapy group (hazard ratio for death with intermittent therapy, 1.10; 90% confidence interval, 0.99 to 1.23). Intermittent therapy was associated with better erectile function and mental health (P<0.001 and P=0.003, respectively) at month 3 but not thereafter. There were no significant differences between the groups in the number of treatment-related high-grade adverse events. Conclusions: Our findings were statistically inconclusive. In patients with metastatic hormone-sensitive prostate cancer, the confidence interval for survival exceeded the upper boundary for noninferiority, suggesting that we cannot rule out a 20% greater risk of death with intermittent therapy than with continuous therapy, but too few events occurred to rule out significant inferiority of intermittent therapy. Intermittent therapy resulted in small improvements in quality of life. (Funded by the National Cancer Institute and others; ClinicalTrials.gov number, NCT00002651.). © 2014 Elsevier Inc.

Preliminary safety and efficacy of L-carnitine infusion for the treatment of vasopressor-dependent septic shock: A randomized control trial - Puskarich, M.A.; Kline, J.A.; Krabill, V.; Claremont, H.; Jones, A.E. (Journal of Parenteral and Enteral Nutrition, 2014)
Background: Sepsis is characterized by metabolic disturbances, and previous data suggest a relative carnitine deficiency may contribute to metabolic dysfunction. Studies regarding safety and patient-centered efficacy of carnitine during septic shock are lacking. Methods: This was a double-blind randomized control trial of levocarnitine (L-carnitine) infusion vs normal saline for the treatment of vasopressor-dependent septic shock. Patients meeting consensus definition for septic shock with a cumulative vasopressor index ≥3 and sequential organ failure assessment (SOFA) score ≥5 enrolled within 16 hours of the recognition of septic shock were eligible. The primary safety outcome was difference in serious adverse events (SAEs) per patient between groups. Efficacy outcomes included proportion of patients demonstrating a decrease in SOFA score of 2 or more points at 24 hours and short- and long-term survival. Results: Of the 31 patients enrolled, 16 were in the L-carnitine and 15 were in the placebo arm. There was no difference in SAEs between placebo and intervention (2.1 vs 1.8 SAEs per patient, P =.44). There was no difference in the proportion of patients achieving a decrease in SOFA score of 2 or more points at 24 hours between placebo and treatment (53% vs 44%, P =.59). Mortality was significantly lower at 28 days in the L-carnitine group (4/16 vs 9/15, P =.048), with a nonsignificant improved survival at 1 year (P =.06). Conclusion: L-carnitine infusion appears safe in vasopressor-dependent septic shock. Preliminary efficacy data suggest potential benefit of L-carnitine treatment, and further testing is indicated. © 2013 American Society for Parenteral and Enteral Nutrition.
Keywords: carnitine; L-carnitine; randomized control trial; sepsis; shock

Simulation-based training for thoracoscopic lobectomy: A randomized controlled trial: Virtual-reality versus black-box simulation - Jensen, K.; Ringsted, C.; Hansen, H.J.; Petersen, R.H.; Konge, L. (Surgical Endoscopy, 2014)
Background: Video-assisted thoracic surgery is gradually replacing conventional open thoracotomy as the method of choice for the treatment of early-stage non-small cell lung cancers, and thoracic surgical trainees must learn and master this technique. Simulation-based training could help trainees overcome the first part of the learning curve, but no virtual-reality simulators for thoracoscopy are commercially available. This study aimed to investigate whether training on a laparoscopic simulator enables trainees to perform a thoracoscopic lobectomy. Methods: Twenty-eight surgical residents were randomized to either virtual-reality training on a nephrectomy module or traditional black-box simulator training. After a retention period they performed a thoracoscopic lobectomy on a porcine model and their performance was scored using a previously validated assessment tool. Results: The groups did not differ in age or gender. All participants were able to complete the lobectomy. The performance of the black-box group was significantly faster during the test scenario than the virtual-reality group: 26.6 min (SD 6.7 min) versus 32.7 min (SD 7.5 min). No difference existed between the two groups when comparing bleeding and anatomical and non-anatomical errors. Conclusion: Simulation-based training and targeted instructions enabled the trainees to perform a simulated thoracoscopic lobectomy. Traditional black-box training was more effective than virtual-reality laparoscopy training. Thus, a dedicated simulator for thoracoscopy should be available before establishing systematic virtual-reality training programs for trainees in thoracic surgery. © 2014 Springer Science+Business Media.
Keywords: Simulation; Simulator training; Thoracoscopy; VATS lobectomy; Virtual-reality

Evaluation of the effect of blackcurrant products on gut microbiota and on markers of risk for colon cancer in humans - Molan, A.-L.; Liu, Z.; Plimmer, G. (Phytotherapy Research, 2014)
The purpose of this study was to determine in healthy humans whether First Leaf (FL; composed of blackcurrant extract powder, lactoferrin and lutein) and Cassis Anthomix 30 (CAM30; blackcurrant extract powder) can positively modify the colonic microbiota by enhancing the growth of the beneficial bacteria and inactivating the toxic bacterial enzymes which are known to be involved in colonic carcinogenesis. Thirty healthy adult male and female volunteers were recruited for this study. Fluorescent in situ hybridization was carried out to analyse the populations of fecal microbiota. Consumption of FL and CAM30 led to significant increases (P < 0.0001) in the population sizes of lactobacilli and bifidobacteria whereas the population sizes of Clostridium spp. and Bacteroides spp were decreased significantly (P < 0.0001). In addition, feeding of FL and CAM30 decreases the activity of β-glucuronidase (bacterial enzyme which is considered to be one of the enzymes that increases risk for colorectal cancer) and significantly decreased (P < 0.05) the fecal pH. In conclusion, the results of this study open up the possibility that consumption of FL and CAM30 can offer various benefits to human health through acting as novel prebiotic agents via increasing the numbers of beneficial bacteria (lactobacilli and bifidobacteria) in the gut. © 2013 John Wiley & Sons, Ltd.
Keywords: bacterial enzymes; blackcurrant products; CAM30; FL; prebiotic activity

Vaccine for cocaine dependence: A randomized double-blind placebo-controlled efficacy trial - Kosten, T.R.; Domingo, C.B.; Shorter, D.; Orson, F.; Green, C.; Somoza, E.; Sekerka, R.; Levin, F.R.; Mariani, J.J.; Stitzer, M.; Tompkins, D.A.; Rotrosen, J.; et al. (Drug and Alcohol Dependence, 2014)
Aims: We evaluated the immunogenicity, efficacy, and safety of succinylnorcocaine conjugated to cholera toxin B protein as a vaccine for cocaine dependence. Methods: This 6-site, 24 week Phase III randomized double-blind placebo-controlled trial assessed efficacy during weeks 8 to 16. We measured urine cocaine metabolites thrice weekly as the main outcome. Results: The 300 subjects (76% male, 72% African-American, mean age 46 years) had smoked cocaine on average for 13 days monthly at baseline. We hypothesized that retention might be better and positive urines lower for subjects with anti-cocaine IgG levels of ≥42. μg/mL (high IgG), which was attained by 67% of the 130 vaccine subjects receiving five vaccinations. Almost 3-times fewer high than low IgG subjects dropped out (7% vs 20%). Although for the full 16 weeks cocaine positive urine rates showed no significant difference between the three groups (placebo, high, low IgG), after week 8, more vaccinated than placebo subjects attained abstinence for at least two weeks of the trial (24% vs 18%), and the high IgG group had the most cocaine-free urines for the last 2 weeks of treatment (OR. = 3.02), but neither were significant. Injection site reactions of induration and tenderness differed between placebo and active vaccine, and the 29 serious adverse events did not lead to treatment related withdrawals, or deaths. Conclusions: The vaccine was safe, but it only partially replicated the efficacy found in the previous study based on retention and attaining abstinence. © 2014 Elsevier Ireland Ltd.
Keywords: Clinical trial; Cocaine; Immunotherapy; Vaccine

Patient trust in physician influences colorectal cancer screening in low-income patients - Gupta, S.; Brenner, A.T.; Ratanawongsa, N.; Inadomi, J.M. (American Journal of Preventive Medicine, 2014)
Background: Colorectal cancer (CRC) screening is effective but underutilized. Although physician recommendation is an important predictor of screening, considerable variation in CRC screening completion remains. Purpose: To characterize the influence of patient trust in care providers on CRC screening behavior. Methods: Data were collected as part of a cluster-randomized CRC screening intervention trial performed in the San Francisco Community Health Network from March 2007 to January 2012 (analysis, Spring 2012). All study participants received a recommendation to complete CRC screening from their primary care provider (PCP). Included participants were aged 50-79 years, not current with screening, and completed the Wake Forest Trust Scale (WFTS) measuring trust in PCPs and doctors in general. Primary outcome was CRC screening completion (colonoscopy or fecal occult blood testing) within 12 months following enrollment. Multivariable association adjusted for race/ethnicity, language, and other sociodemographics was estimated using generalized estimating equations with logit link and binomial distribution. Results: WFTS response was 70.3% (701). Most participants (83%) were Latino, Asian, or black. Most had income <$30,000 (96%) and public health insurance (86%). Higher trust in PCP was associated with screening completion (OR=1.11, 95% CI=1.03, 1.17), but trust in doctors was not (OR=1.02, 95% CI=0.82, 1.28). Race, language, and other sociodemographic factors were not significant in multivariable analysis. Conclusions: After controlling for traditional factors, trust in PCP remained the only significant driver of CRC screening completion in low-income patients. Interventions to promote CRC screening may be improved by including efforts to enhance patient trust in PCP. © 2014 American Journal of Preventive Medicine.

The effects of a brief educational intervention on human papillomavirus knowledge and intention to initiate HPV vaccination in 18-26 year old young adults - Kester, L.M.; Shedd-Steele, R.B.; Dotson-Roberts, C.A.; Smith, J.; Zimet, G.D. (Gynecologic Oncology, 2014)
Objectives Despite the Advisory Committee on Immunization Practices (ACIP) recommendations for young adult females and males to receive the three-dose human papillomavirus (HPV) vaccine, most recent findings show that only 30% of the U.S. females aged 19-26, 2.8% of males aged 19-21, and only 1.7% of males aged 22-26 are initiating vaccination. This study evaluates the effects of a brief (5-10 min) group HPV educational intervention on knowledge and intent to vaccinate among young adults. Methods A sample of 131 18-26 year old females and males was recruited from the 2012 INShape Black and Minority Health Fair in Indiana. We randomized participants into one of two groups: (1) survey completion prior to education (control group) or (2) survey completion following education (intervention group). Written surveys assessed HPV knowledge, vaccination history, and vaccination intent (for unvaccinated participants). Results Respondents were primarily female (70%), single (85%), and the majority self-identified as non-Hispanic Black (77%). Thirty-seven percent had initiated HPV vaccination (≥ 1 dose) and 19% had completed the series. The intervention group had higher HPV knowledge scores (M = 9.1; SD = 1.8) than the control group (M = 7.0; SD = 2.9; F = 22.53). Among unvaccinated individuals (n = 79), the intervention group had higher HPV vaccination intent (86%) compared to the control group (67%) (OR = 3.09; 95%CI = 1.02-9.36). Conclusions Despite ACIP recommendations, young adults continue to have low awareness of vaccine benefits and low vaccination rates. This study suggests that educational interventions to increase HPV awareness and vaccination may help to boost vaccination rates. © 2013 Published by Elsevier Inc.
Keywords: Cervical cancer; Community education; HPV vaccination initiation; Human papillomavirus; Human papillomavirus vaccination; Immunization

Addressing the contribution of previously described genetic and epidemiological risk factors associated with increased prostate cancer risk and aggressive disease within men from South Africa - Tindall, E.A.; Bornman, M.R.; Van Zyl, S.; Segone, A.M.; Monare, L.R.; Venter, P.A.; Hayes, V.M. (BMC Urology, 2013)
Background: Although African ancestry represents a significant risk factor for prostate cancer, few studies have investigated the significance of prostate cancer and relevance of previously defined genetic and epidemiological prostate cancer risk factors within Africa. We recently established the Southern African Prostate Cancer Study (SAPCS), a resource for epidemiological and genetic analysis of prostate cancer risk and outcomes in Black men from South Africa. Biased towards highly aggressive prostate cancer disease, this is the first reported data analysis. Methods. The SAPCS is an ongoing population-based study of Black men with or without prostate cancer. Pilot analysis was performed for the first 837 participants, 522 cases and 315 controls. We investigate 46 pre-defined prostate cancer risk alleles and up to 24 epidemiological measures including demographic, lifestyle and environmental factors, for power to predict disease status and to drive on-going SAPCS recruitment, sampling procedures and research direction. Results: Preliminary results suggest that no previously defined risk alleles significantly predict prostate cancer occurrence within the SAPCS. Furthermore, genetic risk profiles did not enhance the predictive power of prostate specific antigen (PSA) testing. Our study supports several lifestyle/environmental factors contributing to prostate cancer risk including a family history of cancer, diabetes, current sexual activity and erectile dysfunction, balding pattern, frequent aspirin usage and high PSA levels. Conclusions: Despite a clear increased prostate cancer risk associated with an African ancestry, experimental data is lacking within Africa. This pilot study is therefore a significant contribution to the field. While genetic risk factors (largely European-defined) show no evidence for disease prediction in the SAPCS, several epidemiological factors were associated with prostate cancer status. We call for improved study power by building on the SAPCS resource, further validation of associated factors in independent African-based resources, and genome-wide approaches to define African-specific risk alleles. © 2013 Tindall et al.; licensee BioMed Central Ltd.
Keywords: African ancestry; Aggressive disease; Epidemiology; Genetics; Pilot analysis; Prostate cancer; Risk factors; Southern Africa

Psychosocial benefits of a novel mindfulness intervention versus standard support in distressed women with breast cancer - Monti, D.A.; Kash, K.M.; Kunkel, E.J.; Moss, A.; Mathews, M.; Brainard, G.; Anne, R.; Leiby, B.E.; Pequinot, E.; Newberg, A.B. (Psycho-Oncology, 2013)
Objective: It is well documented that stress is associated with negative health outcomes in cancer patients. The purpose of this study was to assess the effects of a novel mindfulness intervention called mindfulness-based art therapy (MBAT) versus standard educational support, on indices of stress and quality of life in breast cancer patients with high stress levels. Methods: A total of 191 women were enrolled, stratified by age and stress level, and randomized to receive either an 8-week MBAT intervention or a breast cancer educational support program of equal time and duration. Psychosocial stress was measured using the Symptoms Checklist-90-Revised, and quality of life was measured using the Medical Outcomes Study Short-Form Health Survey at baseline, immediately post-intervention, and at 6 months. Results: Results showed overall significant improvements in psychosocial stress and quality of life in both the MBAT and educational support groups immediately post-intervention; however, participants with high stress levels at baseline had significantly improved overall outcomes only in the MBAT group, both immediately post-intervention and at 6 months. In addition, at 6 months follow-up, participants attending five or more sessions trended toward retaining treatment effects better in the MBAT than in the control group. Finally, black women and white women were similar in terms of how they benefited from the MBAT intervention, even though white participants tended to have higher educational level and marital status. Conclusions: In conclusion, MBAT is associated with significant, sustained benefits across a diverse range of breast cancer patients, particularly those with high stress levels. Copyright © 2013 John Wiley & Sons, Ltd.

Behavioral treatment for weight gain prevention among black women in primary care practice: A randomized clinical trial - Bennett, G.G.; Foley, P.; Levine, E.; Whiteley, J.; Askew, S.; Steinberg, D.M.; Batch, B.; Greaney, M.L.; Miranda, H.; Wroth, T.H.; Holder, M.G.; Emmons, K.M.; et al. (JAMA Internal Medicine, 2013)
Importance Few weight loss treatments produce clinically meaningful weight loss outcomes among black women, particularly in the primary care setting. New weight management strategies are necessary for this population. Weight gain prevention might be an effective treatment option, with particular benefits for overweight and class 1 obese black women. OBJECTIVE To compare changes in weight and cardiometabolic risk during a 12-month period among black women randomized to a primary care-based behavioral weight gain prevention intervention, relative to usual care. DESIGN. SETTING. AND PARTICIPANTS Two-arm randomized clinical trial (the Shape Program). We recruited patients from a 6-site community health center system. We randomized 194 overweight and class 1 obese (body mass index [calculated as weight in kilograms divided by height in meters squared], 25-34.9) premenopausal black women aged 25 to 44 years. Enrollment began on December 7,2009; 12- and 18-month assessments were completed in February and October 2,2012. interventions The medium-intensity intervention included tailored behavior change goals, weekly self-monitoring via interactive voice response, monthly counseling calls, tailored skills training materials, and a gym membership. MAIN OUTCOMES AND MEASURES Twelve-month change in weight and body mass index and maintenance of change at 18 months. RESULTS Participants had a mean age of 35.4 years, a mean weight of 81.1 kg. and a mean body mass index of 30.2 at baseline. Most were socioeconomically disadvantaged (79.7% with educational level less than a college degree; 74.3% reporting annual income <$30 000). The 12-month weight change was larger among intervention participants (mean [SD], -1.0 [0.5] kg), relative to usual care (0.5 [0.5] kg; mean difference, -1.4 kg [95% CI. -2.8 to -0.1 kg]; P = .04). At month 12,62% of intervention participants were at or below their baseline weights compared with 45% of usual-care participants (P = .03). By 18 months, intervention participants maintained significantly larger changes in weight (mean difference, -1.7 kg; 95% CI.-3.3 to-0.2 kg). CONCLUSIONS and relevance A medium-intensity primary care-based behavioral intervention demonstrated efficacy for weight gain prevention among socioeconomically disadvantaged black women. A "maintain, don't gain" approach might be a useful alternative treatment for reducing obesity-associated disease risk among some premenopausal black women.

Implementation of culturally targeted patient navigation system for screening colonoscopy in a direct referral system - Jandorf, L.; Cooperman, J.L.; Stossel, L.M.; Itzkowitz, S.; Thompson, H.S.; Villagra, C.; Thélémaque, L.D.; McGinn, T.; Winkel, G.; Valdimarsdottir, H.; Shelton, R.C.; Redd, W. (Health Education Research, 2013)
Low-income minorities often face system-based and personal barriers to screening colonoscopy (SC). Culturally targeted patient navigation (CTPN) programs employing professional navigators (Pro-PNs) or community-based peer navigators (Peer-PNs) can help overcome barriers but are not widely implemented. In East Harlem, NY, USA, where approximately half the residents participate in SC, 315 African American patients referred for SC at a primary care clinic with a Direct Endoscopic Referral System were recruited between May 2008 and May 2010. After medical clearance, 240 were randomized to receive CTPN delivered by a Pro-PN (n=106) or Peer-PN (n=134). Successful navigation was measured by SC adherence rate, patient satisfaction and navigator trust. Study enrollment was 91.4% with no significant differences in SC adherence rates between Pro-PN (80.0%) and Peer-PN (71.3%) (P=0.178). Participants in both groups reported high levels of satisfaction and trust. These findings suggest that CTPN Pro-PN and Peer-PN programs are effective in this urban primary care setting. We detail how we recruited and trained navigators, how CTPN was implemented and provide a preliminary answer to our questions of the study aims: can peer navigators be as effective as professionals and what is the potential impact of patient navigation on screening adherence?

A novel community-based study to address disparities in hypertension and colorectal cancer: A study protocol for a randomized control trial - Ravenell, J.; Thompson, H.; Cole, H.; Plumhoff, J.; Cobb, G.; Afolabi, L.; Boutin-Foster, C.; Wells, M.; Scott, M.; Ogedegbe, G. (Trials, 2013)
Background: Black men have the greatest burden of premature death and disability from hypertension (HTN) in the United States, and the highest incidence and mortality from colorectal cancer (CRC). While several clinical trials have reported beneficial effects of lifestyle changes on blood pressure (BP) reduction, and improved CRC screening with patient navigation (PN), the effectiveness of these approaches in community-based settings remains understudied, particularly among Black men.Methods/design: MISTER B is a two-parallel-arm randomized controlled trial that will compare the effect of a motivational interviewing tailored lifestyle intervention (MINT) versus a culturally targeted PN intervention on improvement of BP and CRC screening among black men aged ≥50 with uncontrolled HTN who are eligible for CRC screening. Approximately 480 self-identified black men will be randomly assigned to one of the two study conditions. This innovative research design allows each intervention to serve as the control for the other. Specifically, the MINT arm is the control condition for the PN arm, and vice-versa. This novel, simultaneous testing of two community-based interventions in a randomized fashion is an economical and yet rigorous strategy that also enhances the acceptability of the project. Participants will be recruited during scheduled screening events at barbershops in New York City. Trained research assistants will conduct the lifestyle intervention, while trained community health workers will deliver the PN intervention. The primary outcomes will be 1) within-patient change in systolic and diastolic BP from baseline to six months and 2) CRC screening rates at six months.Discussion: This innovative study will provide a unique opportunity to test two interventions for two health disparities simultaneously in community-based settings. Our study is one of the first to test culturally targeted patient navigation for CRC screening among black men in barbershops. Thus, our study has the potential to improve the reach of hypertension control and cancer prevention efforts within a high-risk population that is under-represented in primary care settings.Trial registration: ClinicalTrials.gov, NCT01092078. © 2013 Ravenell et al.; licensee BioMed Central Ltd.
Keywords: African Americans; Barbershops; Hypertension; Patient navigation

Navigating veterans with an abnormal prostate cancer screening test: A quasi-experimental study - Simon, M.A.; Nonzee, N.J.; McKoy, J.M.; Liu, D.; Luu, T.H.; Byer, P.; Eklund, E.A.; Richey, E.A.; Wu, Z.; Dong, X.; Rademaker, A.W. (BMC Health Services Research, 2013)
Background: Prostate cancer disproportionately affects low-income and minority men. This study evaluates the impact of a patient navigation intervention on timeliness of diagnostic resolution and treatment initiation among veterans with an abnormal prostate cancer screen. Methods. Participants were enrolled between 2006 and 2010. The intervention involved a social worker and lay health worker navigation team that assisted patients in overcoming barriers to care. For navigated (n = 245) versus control (n = 245) participants, we evaluated rates of diagnostic resolution and treatment and adjusted for race, age, and Gleason score. Results: Of 490 participants, 68% were African American, 47% were ≥ 65 years old, and 35% had cancer. Among those with an abnormal screen, navigation did not have a significant effect on time to diagnostic resolution compared to controls (median days of 97 versus 111; adj. HR 1.17, 95% CI, 0.96-1.43, p = 0.12). On analysis of the period beyond 80 days, navigated men reached resolution faster than controls (median of 151 days versus 190 days; adj. HR 1.41, 95% CI, 1.07-1.86, p = 0.01). Among those with cancer, navigation did not have a significant effect on time to treatment initiation compared to controls (median of 93 days versus 87 days; adj. HR 1.15, 95% CI, 0.82-1.62, p = 0.41). Conclusion: Our navigation program did not significantly impact the overall time to resolution or treatment for men with prostate cancer compared to controls. The utility of navigation programs may extend beyond targeted navigation times, however, and future studies focusing on other outcomes measures are therefore needed. © 2013 Simon et al.; licensee BioMed Central Ltd.

Efficacy to effectiveness transition of an Educational Program to Increase Colorectal Cancer Screening (EPICS): Study protocol of a cluster randomized controlled trial - Smith, S.A.; Blumenthal, D.S. (Implementation Science, 2013)
Background: African Americans have the highest incidence and mortality and are less likely than whites to have been screened for colorectal cancer (CRC). Many interventions have been shown to increase CRC screening in research settings, but few have been evaluated specifically for use in African-American communities in real world settings. This study aims to identify the most efficacious approach to disseminate an evidence-based intervention in promoting colorectal screening in African Americans and to identify the factors associated with its efficacy.Methods/design: In this study, investigators will recruit 20 community coalitions and 7,200 African-Americans age 50 to 74 to test passive and active approaches to disseminating the Educational Program to Increase Colorectal Cancer Screening (EPICS); to measure the extent to which EPICS is accepted and the fidelity of implementation in various settings and to estimate the potential translatability and public health impact of EPICS. This four-arm cluster randomized trial compares the following implementation strategies: passive arms, (web access to facilitator training materials and toolkits without technical assistance (TA) and (web access, but with technical assistance (TA); active arms, (in-person access to facilitator training materials and toolkits without TA and (in-person access with TA). Primary outcome measures are the reach (the proportion of representative community coalitions and individuals participating) and efficacy (post-intervention changes in CRC screening rates). Secondary outcomes include adoption (percentage of community coalitions implementing the EPICS sessions) and implementation (quality and consistency of the intervention delivery). The extent to which community coalitions continue to implement EPICS post-implementation (maintenance) will also be measured. Cost-effectiveness analysis will be conducted.Discussion: Implementing EPICS in partnership with community coalitions, we hypothesized, will result in more rapid adoption than traditional top-down approaches, and resulting changes in community CRC screening practices are more likely to be sustainable over time. With its national reach, this study has the potential to enhance our understanding of barriers and enablers to the uptake of educational programs aimed at eliminating cancer disparities. © 2013 Smith and Blumenthal; licensee BioMed Central Ltd.
Keywords: Colorectal cancer screening; Community-based participatory research; Dissemination; Health disparities; Implementation

A culturally adapted family intervention for African American families coping with parental cancer: Outcomes of a pilot study - Davey, M.P.; Kissil, K.; Lynch, L.; Harmon, L.-R.; Hodgson, N. (Psycho-Oncology, 2013)
Objectives The primary objective of this 2-year pilot study was to evaluate the effectiveness of a culturally adapted family intervention in improving family communication among African American parents coping with cancer and their school-age children. A secondary objective was to determine its impact on other symptoms of psychosocial distress (depression and anxiety). The third objective was to assess for acceptability and feasibility. Methods Using a two-arm pre-intervention and post-intervention prospective design, 12 African American families received five bi-monthly sessions of either a culturally adapted family intervention (n = 7 families) or psycho-education treatment (n = 5 families). Parents and their children completed pre-intervention and post-intervention questionnaires assessing perceptions of family communication, quality of their relationship, and symptoms of depression. School-age children additionally completed a questionnaire assessing their levels of anxiety. Consumer satisfaction was also evaluated at post-intervention. Results Parents and school-age children who completed the culturally adapted family intervention reported significantly better communication with each other and were more satisfied compared with the psycho-education control group. No changes were noted in symptoms of anxiety or depression. The culturally adapted family intervention was acceptable based on our findings, families' feedback, and rates of retention. Feasibility is uncertain because our oncology clinic approach to recruitment was slower than expected. Conclusions Providing culturally adapted family intervention programs to African American families who are coping with parental cancer may result in improved family communication. This pilot study serves as the first step in the development of culturally adapted family intervention programs to help African American families cope with parental cancer. Copyright © 2012 John Wiley & Sons, Ltd. Copyright © 2012 John Wiley & Sons, Ltd.
Keywords: African American; cancer; oncology; parental cancer; psychosocial support

Adherence to World Cancer Research Fund/American institute for cancer research lifestyle recommendations reduces prostate cancer aggressiveness among African and Caucasian Americans - Arab, L.; Su, J.; Steck, S.E.; Ang, A.; Fontham, E.T.H.; Bensen, J.T.; Mohler, J.L. (Nutrition and Cancer, 2013)
The effect of adherence to the World Cancer Research Fund (WCRF) lifestyle recommendations on cancer aggressiveness is unknown. We examined associations between adherence to recommendations and risk of highly aggressive prostate cancer in research subjects enrolled in the North Carolina-Louisiana Prostate Cancer Project (PCaP). We examined associations between adherence to WCRF recommendations and risk of highly aggressive prostate cancer among 2212 newly diagnosed African Americans (AA) or Caucasian Americans (CA) aged 40-70 years in PCaP. Prostate cancer aggressiveness was based on Gleason scores, serum prostate-specific antigens, and TNM stage. Adherence to WCRF recommendations was based on point scores and odds ratios estimated. Results showed that adherence to recommendations was significantly and negatively associated with risk of a highly aggressive prostate cancer. Each additional point in the total adherence score corresponded to a 13% risk reduction. Total adherence score <4 predicted increased risk in both AA (OR = 1.36; 95% CI = 1.01-1.85) and CA (OR = 1.41; 95% CI = 1.01-1.98). Consumption of <500 g red meat per week or ≤125 total kcal/100 g solid food per day is a statistically significant protective factor in the overall cohort. Recommendations aimed at preventing all cancers also may reduce risk of highly aggressive prostate cancer. © 2013 Copyright Taylor and Francis Group, LLC.

Association between race and follow-up diagnostic care after a positive prostate cancer screening test in the Prostate, Lung, Colorectal, and Ovarian cancer screening trial - Barocas, D.A.; Grubb III, R.; Black, A.; Penson, D.F.; Fowke, J.H.; Andriole, G.; Crawford, E.D. (Cancer, 2013)
background Follow-through of a positive screening test is necessary to reap the potential benefits of cancer screening. Racial variation in follow-through diagnostic care may underlie a proportion of the known disparity in prostate cancer mortality. The authors used data from the screening arm of the Prostate, Lung, Colorectal, and Ovarian (PLCO) cancer screening trial to determine whether race is associated with the use of follow-up diagnostic testing after a positive initial screening evaluation. methods Men who had a prostate-specific antigen (PSA) level >4 ng/mL at any time during the study were included. The proportion of men who underwent follow-up evaluation with a repeat PSA, a prostate biopsy, or either test within 9 months was determined, and the authors tested for differences in follow-through according to race using mixed-effects multivariate models with a random effect for accrual site to account for clustering. Models were stratified according to age (<65 years and ≥65 years). results Among 6294 men who had a PSA elevation during the study period, 70% underwent a repeat PSA or prostate biopsy within 9 months. Non-Hispanic black men aged <65 years had 45% lower odds of undergoing a repeat PSA test or prostate biopsy compared with non-Hispanic white men (odds ratio, 0.55; 95% confidence interval, 0.37-0.82), whereas there was no racial difference in follow-through among older men. conclusions The current results suggest that limitations in access to care among non-Hispanic black men under the age of Medicare eligibility may underlie the paradoxically low use of follow-through diagnostic care among non-Hispanic black men in the United States. © 2013 American Cancer Society.
Keywords: biopsy; diagnosis; health care disparity; prostate cancer; race; screening

Psychoneuroimmunology-based stress management during adjuvant chemotherapy for early breast cancer - Robins, J.L.W.; McCain, N.L.; Elswick, R.K.; Walter, J.M.; Gray, D.P.; Tuck, I. (Evidence-based Complementary and Alternative Medicine, 2013)
Objective. In a randomized trial of women with early stage breast cancer undergoing adjuvant chemotherapy, two stress management interventions, tai chi training and spiritual growth groups, were compared to a usual care control group, to evaluate psychosocial functioning, quality of life (QOL), and biological markers thought to reflect cancer- and treatment-specific mechanisms. Method. The sample consisted of 145 women aged 27-75 years; 75% were Caucasian and 25% African American. A total of 109 participants completed the study, yielding a 75% retention rate. Grounded in a psychoneuroimmunology framework, the overarching hypothesis was that both interventions would reduce perceived stress, enhance QOL and psychosocial functioning, normalize levels of stress-related neuroendocrine mediators, and attenuate immunosuppression. Results. While interesting patterns were seen across the sample and over time, the interventions had no appreciable effects when delivered during the period of chemotherapy. Conclusions. Findings highlight the complex nature of biobehavioral interventions in relation to treatment trajectories and potential outcomes. Psychosocial interventions like these may lack sufficient power to overcome the psychosocial or physiological stress experienced during the chemotherapy treatment period. It may be that interventions requiring less activity and/or group attendance would have enhanced therapeutic effects, and more active interventions need to be tested prior to and following recovery from chemotherapy. © 2013 Jo Lynne W. Robins et al.

Gender differences in correlates of colorectal cancer screening among black medicare beneficiaries in Baltimore - Martinez, K.A.; Pollack, C.E.; Phelan, D.F.; Markakis, D.; Bone, L.; Shapiro, G.; Wenzel, J.; Howerton, M.; Johnson, L.; Garza, M.A.; Ford, J.G. (Cancer Epidemiology Biomarkers and Prevention, 2013)
Background: Previous research has shown colorectal cancer (CRC) screening disparities by gender. Little research has focused primarily on gender differences among older Black individuals, and reasons for existing gender differences remain poorly understood. Methods: Weused baseline data from the Cancer Prevention and Treatment Demonstration Screening Trial. Participants were recruited from November 2006 to March 2010. In-person interviews were used to assess selfreported CRC screening behavior. Up-to-date CRC screening was defined as self-reported colonoscopy or sigmoidoscopy in the past 10 years or fecal occult blood testing in the past year. We used multivariable logistic regression to examine the association between gender and self-reported screening, adjusting for covariates. The final model was stratified by gender to examine factors differentially associated with screening outcomes for males and females. Results: The final sample consisted of 1,552 female and 586 male Black Medicare beneficiaries in Baltimore, Maryland. Males were significantly less likely than females to report being up-to-date with screening (77.5% vs. 81.6%, P = 0.030), and this difference was significant in the fully adjusted model (OR: 0.72; 95% confidence interval, 0.52-0.99). The association between having a usual source of care and receipt of cancer screening was stronger among males compared with females. Conclusions: Although observed differences in CRC screening were small, several factors suggest that gender-specific approaches may be used to promote screening adherence among Black Medicare beneficiaries. Impact: Given disproportionate CRC mortality between White and Black Medicare beneficiaries, genderspecific interventions aimed at increasing CRC screening may be warranted among older Black patients. © 2013 American Association for Cancer Research.

National surgical adjuvant breast and bowel project study of tamoxifen and raloxifene trial: Advancing the science of recruitment and breast cancer risk assessment in minority communities - McCaskill-Stevens, W.; Wilson, J.W.; Cook, E.D.; Edwards, C.L.; Gibson, R.V.; McElwain, D.L.; Figueroa-Moseley, C.D.; Paskett, E.D.; Roberson, N.L.; Wickerham, D.L.; Wolmark, N. (Clinical Trials, 2013)
Background One of the first chemoprevention trials conducted in the western hemisphere, the National Surgical Adjuvant Breast and Bowel Project's (NSABP) Breast Cancer Prevention Trial (BCPT), demonstrated the need to evaluate all aspects of recruitment in real time and to implement strategies to enroll racial and ethnic minority women. Purpose The purpose of this report is to review various patient recruitment efforts the NSABP developed to enhance the participation of racial and ethnic minority women in the Study of Tamoxifen and Raloxifene (STAR) trial and to describe the role that the recruitment process played in the implementation and understanding of breast cancer risk assessment in minority communities. Methods The NSABP STAR trial was a randomized, double-blinded study comparing the use of tamoxifen 20 mg/day to raloxifene 60 mg/day, for a 5-year period, to reduce the risk of developing invasive breast cancer. Eligible postmenopausal women were required to have a 5-year predicted breast cancer risk of 1.66% based on the modified Gail Model. For the current report, eligibility and enrollment data were tabulated by race/ethnicity for women who submitted STAR risk assessment forms (RAFs). Results A total of 184,460 RAFs were received, 145,550 (78.9%) from white women and 38,910 (21.1%) from minority women. Of the latter group, 21,444 (11.6%) were from African Americans/blacks, 7913 (4.5%) from Hispanics/Latinas, and 9553 (5.2%) from other racial or ethnic groups. The percentages of risk-eligible women among African Americans, Hispanics/Latinas, others, and whites were 14.2%, 23.3%, 13.7%, and 57.4%, respectively. Programs targeting minority enrollment submitted large numbers of RAFs, but the eligibility rates of the women referred from those groups tended to be lower than the rates among women referred outside of those programs. The average number of completed risk assessments increased among minority women over the course of the recruitment period compared to those from whites. Limitations We have not addressed all identified barriers to the recruitment of minorities in clinical research. Our risk assessments and recruitment results do not reflect the modified Gail Model for African Americans. Conclusions Recruitment strategies used in STAR for racial and ethnic minorities contributed to doubling the minority enrollment compared to that in the BCPT and increased the awareness of breast cancer risk assessment in minority communities. Incorporation of new information into models to improve the risk estimation of diverse populations should prove beneficial. © The Author(s) 2013.

Relationship of early-onset baldness to prostate cancer in african-american men - Zeigler-Johnson, C.; Morales, K.H.; Spangler, E.; Chang, B.-L.; Rebbeck, T.R. (Cancer Epidemiology Biomarkers and Prevention, 2013)
Background: Early-onset baldness has been linked to prostate cancer; however, little is known about this relationship in AfricanAmericans who are at elevated prostate cancer risk. Methods: We recruited 219 African-American controls and 318 African-American prostate cancer cases. We determined age-stratified associations of baldness with prostate cancer occurrence and severity defined by high stage (T3/T4) or high grade (Gleason 7+.) Associations of androgen metabolism genotypes (CYP3A4, CYP3A5, CYP3A43, AR-CAG, SRD5A2 A49T, and SRD5A2 V89L), family history, alcohol intake, and smoking were examined by baldness status and age group by using multivariable logistic regression models. Results: Baldness was associated with odds of prostate cancer [OR 1.69; 95% confidence interval (CI), 1.05- 2.74]. Frontal baldness was associated with high-stage (OR 2.61; 95% CI, 1.10-6.18) and high-grade (OR 2.20; 95% CI, 1.05-4.61) tumors. Formendiagnosed less than the age of 60 years, frontal baldness was associated with high stage (OR 6.51; 95% CI, 2.11-20.06) and high grade (OR 4.23; 95% CI, 1.47-12.14). We also observed a suggestion of an interaction among smoking, median age, and any baldness (P 0.02). Conclusions: We observed significant associations between early-onset baldness and prostate cancer in African-American men. Interactions with age and smoking were suggested in these associations. Studies are needed to investigate the mechanisms influencing the relationship between baldness and prostate cancer in African-American men. Impact: African-American men present with unique risk factors including baldness patterns that may contribute to prostate cancer disparities. © 2013 American Association for Cancer Research.

Clinicopathologic features and determinants of Gleason score of prostate cancer in Ghanaian men - Yarney, J.; Vanderpuye, V.; Mensah, J. (Urologic Oncology: Seminars and Original Investigations, 2013)
Objective: Prostate cancer is reported to be more aggressive in Blacks. We studied the clinicopathologic features of prostate cancer in Ghana, in order to determine the factors responsible for them and to find out if there is any relationship between them. Method: Patients referred with a biopsy proven diagnosis of carcinoma of the prostate to the Cancer Center of Korle Bu Teaching Hospital, Accra, Ghana, from 2003 to 2007 were studied. Information with respect to age at diagnosis, presenting symptoms, initial PSA (iPSA), Gleason score, and disease extent were studied. Age was partitioned into 50-65 and >65 years, Gleason score into 2-6, 7, and 8-10, iPSA into 4-20 ng/ml and >20, and disease extent into T1, T2, vs. T3, T4, M1, and the relationship between them was determined. Various presenting symptoms were described. Known risk factors and screening in a context of high grade disease is discussed. Results: A total of 170 patients were studied. Mean age was 65.4 years. Majority of patients (73.7%) presented with an iPSA > 20 ng/ml, whilst 22 (14.1%) had PSA < 10 ng/ml. Gleason score ≥ 7 was found in 95 (56%) of patients. Asymptomatic patients constituted 24.0%, the rest had bone pain (22.6%), urinary (50.4%), and neurologic symptoms (3.0%).There was a statistically significant relationship between age and Gleason score (. P = 0.049), PSA and Gleason score (. P = 0.0001), and between extent of disease and Gleason score (. P = 0.0002). High fat diet and low intake of fruits and vegetables are probable risk factors in Ghana. Conclusion: Majority of patients present with symptomatic disease at a relatively older age. These patients tend to have high Gleason score partly attributable to advanced disease, age, PSA at the time of diagnosis, and race. Screening with PSA should be recommended and individualized in this group of patients in order to allow diagnosis of less aggressive disease until better screening tools are identified. © 2013 Elsevier Inc.
Keywords: Age; Black men; Cancer; Differentiation; Gleason score; Prostate; PSA; Risk factors

Establishing a minority-based community clinical oncology program: The University of Medicine and Dentistry of New Jersey, New Jersey Medical School-University Hospital Cancer Center experience - Wieder, R.; Teal, R.; Saunders, T.; Weiner, B.J. (Journal of Oncology Practice, 2013)
The Minority-Based Community Clinical Oncology Program (MB-CCOP) at University of Medicine and Dentistry of New Jersey, New Jersey Medical School-University Hospital Cancer Center was established to serve an unmet need in a medically, educationally, and socioeconomically underserved community of primarily African American and Latino patients in Newark and Essex County, New Jersey. The MB-CCOP was built on an existing infrastructure of multidisciplinary teams of cancer specialists who collaborated in patient care and an existing clinical research program, which included multilingual staff and a breast cancer navigator. This article highlights some of the unique opportunities and challenges involved in the startup of an MB-CCOP specifically relevant to an academic setting. We present a guide to the necessary infrastructure and institutional support that must be in place before considering such a program and some of the steps an institution can take to overcome barriers preventing successful enrollment of patients onto clinical trials. Copyright © 2012 by American Society of Clinical Oncology.

Racial/ethnic differences in use and duration of adjuvant hormonal therapy for breast cancer in the women's health initiative - Livaudais, J.C.; LaCroix, A.; Chlebowski, R.T.; Li, C.I.; Habel, L.A.; Simon, M.S.; Thompson, B.; Erwin, D.O.; Hubbell, F.A.; Coronado, G.D. (Cancer Epidemiology Biomarkers and Prevention, 2013)
Background: Five-year breast cancer survival rates are lower among Hispanic and African-American women than among Non-Hispanic White women. Differences in breast cancer treatment likely play a role. Adjuvant hormonal therapies increase overall survival among women with hormone receptor-positive breast cancer. Methods: We examined racial/ethnic differences in use and duration of adjuvant hormonal therapy among 3,588 postmenopausal women enrolled in the Women's Health Initiative (WHI) Extension Study. Women diagnosed with hormone receptor-positive localized or regional stage breast cancer after study enrollment were surveyed between September 2009 and August 2010 and asked to recall prior use and duration of adjuvant hormonal breast cancer therapy. ORs comparing self-reported use and duration with race/ethnicity (Hispanic, African-American, Asian/Pacific Islander vs. Non-Hispanic White) were estimated using multivariableadjusted logistic regression. Results: Of the 3,588 women diagnosed from 1994 to 2009; 3,039 (85%) reported any use of adjuvant hormonal therapy, and 67% of women reporting ever-use who were diagnosed before 2005 reported using adjuvant hormonal therapy for the optimal duration of 5 years or more. In adjusted analysis, no statistically significant differences in use or duration by race/ethnicity were observed. Conclusions: This study did not find significant differences in use or duration of use of adjuvant hormonal therapy by race/ethnicity. Impact: Findings should be confirmed in other population-based samples, and potential reasons for discontinuation of therapy across all racial/ethnic groups should be explored. © 2013 American Association for Cancer Research.

Kin KeeperSM: Design and baseline characteristics of a community-based randomized controlled trial promoting cancer screening in Black, Latina, and Arab women - Williams, K.P.; Roman, L.; Meghea, C.I.; Penner, L.; Hammad, A.; Gardiner, J. (Contemporary Clinical Trials, 2013)
Background: Although breast and cervical cancer deaths have declined due to early screening, detection, and more effective treatment, racial and ethnic disparities persist. This paper describes the study design and baseline characteristics of a randomized controlled trial (RCT) evaluating the effectiveness of the Kin KeeperSM Cancer Prevention Intervention, a family-focused educational intervention for underserved women applied in a community-based setting to promote health literacy and screening adherence to address cancer disparities. Methods: Female public health community health workers (CHWs) were trained to administer the intervention. They recruited female clients from their public health program caseload and asked each to assemble two to four adult female family members for the breast and cervical cancer home-based education sessions the CHWs would deliver in English, Spanish or Arabic. We randomized the clients into the kin keeper group (treatment) or the participant client group (control). Results: Complete data were obtained on 514 Black, Latina, and Arab women. Close to half were unemployed and had yearly family income below $20,000. Thirty-four percent had no medical insurance, and 21% had diabetes. Almost 40% had no mammography in the last year. Treatment and control groups were similar on most sociodemographics but showed differences in breast and cervical screening history. Conclusions: This innovative study demonstrates the implementation of an RCT using community-based participatory research, while delivering cancer prevention education across woman's life span with women not connected to the health care system. © 2012 Elsevier Inc.
Keywords: Community-based participatory research; Implementation science; Randomized controlled trial

Short- and long-term risk of colorectal adenoma recurrence among whites and blacks - Laiyemo, A.O.; Doubeni, C.; Brim, H.; Ashktorab, H.; Schoen, R.E.; Gupta, S.; Charabaty, A.; Lanza, E.; Smoot, D.T.; Platz, E.; Cross, A.J. (Gastrointestinal Endoscopy, 2013)
Background: It is unclear whether the higher burden from colorectal cancer among blacks is due to an increased biological susceptibility. Objective: To determine whether non-Hispanic blacks (blacks) have a higher risk of adenoma recurrence than non-Hispanic whites (whites) after removal of colorectal adenoma. Design: Secondary analysis of the Polyp Prevention Trial (PPT) data. Setting: United States. Patients: Patients were 1668 self-identified whites and 153 blacks who completed the 4-year trial. Of these, 688 whites and 55 blacks enrolled in a posttrial, passive Polyp Prevention Trial Continued Follow-up Study (PPT-CFS) and underwent another colonoscopy. Main Outcome Measurements: Recurrence and location of the adenoma and advanced adenoma by race-ethnicity during PPT and cumulative recurrence over a mean follow-up of 8.3 years (range, 4.9-12.4 years) among PPT-CFS enrollees. Results: Blacks had similar risk of recurrence of adenoma (39.2% vs 39.4%; incidence risk ratio [RR] =.98; 95% CI,.80-1.20) and advanced adenoma (8.5% vs 6.4%; RR = 1.18; 95% CI,.68-2.05) as whites at the end of PPT. Recurrence risk did not differ by colon subsite. Among PPT-CFS enrollees, the cumulative recurrence rate over a maximal follow-up period of 12 years was similar for blacks and whites for adenoma (67.3% vs 67.0%; RR = 1.01; 95% CI,.84-1.21) and advanced adenoma (14.5% vs 16.9%; RR = 1.03; 95% CI,.60-1.79). Limitation: There were few blacks in the long-term follow-up study. Conclusions: Adenoma and advanced adenoma recurrence did not differ by race. Our study does not support more frequent surveillance colonoscopies for blacks with a personal history of adenoma as an intervention to reduce colorectal cancer disparity. © 2013 American Society for Gastrointestinal Endoscopy.

A randomized, double-blind, placebo-controlled study of oral coenzyme Q10 to relieve self-reported treatment-related fatigue in newly diagnosed patients with breast cancer - Lesser, G.J.; Case, D.; Stark, N.; Williford, S.; Giguere, J.; Astrid Garino, L.; Naughton, M.J.; Vitolins, M.Z.; Lively, M.O.; Shaw, E.G.; for the Wake Forest University Community Clinical Oncology Program Research Base (Journal of Supportive Oncology, 2013)
Background: Coenzyme Q10 (CoQ10) is a common antioxidant supplement with known cardioprotective effects and potential anticancer benefits. Objectives We performed a randomized, double-blind, placebo-controlled study of oral CoQ10 in female breast cancer patients with the primary objective of determining CoQ10's effects on self-reported fatigue, depression, and quality of life (QOL). Methods: Eligible women with newly diagnosed breast cancer and planned adjuvant chemotherapy were randomized to oral supplements of 300 mg CoQ10 or placebo, each combined with 300 IU vitamin E, divided into 3 daily doses. Treatment was continued for 24 weeks. Blood tests, QOL measures, and levels of plasma CoQ10 and vitamin E were obtained at baseline and at 8, 16, and 24 weeks. Mixed-effects models were used to assess treatment differences in outcomes over time. Results: Between September 2004 and March 2009, 236 women were enrolled. Treatment arms were well balanced with respect to age (range, 28-85 years), pathologic stage (stage 0, 91%; stage I, 8%; stage II, 1%), ethnicity (white, 87%; black, 11%; Hispanic, 2%), and planned therapy. Baseline CoQ10 levels in the CoQ10 and placebo arms were 0.70 and 0.73 μg/mL, respectively; the 24-week CoQ10 levels were 1.83 and 0.79 μg/mL, respectively. There were no significant differences between the CoQ10 and placebo arms at 24 weeks for scores on the Profile of Mood States-Fatigue questionnaire (least squares means, 7.08 vs 8.24, P = .257), the Functional Assessment of Chronic Illness Therapy-Fatigue tool (37.6 vs 37.6, P = .965), the Functional Assessment of Cancer Therapy-Breast Cancer instrument (111.9 vs 110.4, P = .577), or the Center for Epidemiologic Studies-Depression scale (11.6 vs 12.3, P = .632). Conclusions: Supplementation with conventional doses of CoQ10 led to sustained increases in plasma CoQ10 levels but did not result in improved self-reported fatigue or QOL after 24 weeks of treatment. © 2013 Frontline Medical Communications.

Are race-specific ERCC1 haplotypes in melanoma cases versus controls related to the predictive and prognostic value of ERCC1 N118N? - Gao, R.; Reece, K.M.; Sissung, T.; Fu, S.H.; Venzon, D.J.; Reed, E.; Spencer, S.D.; Price, D.K.; Figg, W.D. (BMJ Open, 2013)
Objectives: Although it does not alter the ERCC1 phenotype, the ERCC1 500C>T (rs11615) polymorphism has undergone a myriad of investigations into its role as a marker for nucleotide excision repair (NER) function in different races, diseases and treatment outcomes. The goal of our study was to test the hypothesis that 500C>T is in linkage disequilibrium (LD) with causative alleles, and that these haplotypes are more frequent in Caucasians with melanoma than in healthy Caucasians or African Americans. Design: In this case-control study, we selected racespecific ERCC1 single-nucleotide polymorphism (SNPs), conducted LD analysis with ERCC1 500C>T and compared the frequency of ERCC1 diplotypes in Caucasians with melanoma (n=165), healthy Caucasians (n=150) and healthy African Americans (n=159). The haplotype was further studied using a fusion gene containing multiple ERCC1 SNPs. Setting: Large cancer institute in the USA. Participants: A total of 165 Caucasian melanoma patients, 159 healthy Caucasian controls and 159 African American healthy controls. Men and women were enrolled in the clinical trial; however, since the screening trial included prostate cancer screening in addition to screening for other cancers, only male controls were available. Outcome measures: The outcome measures were melanoma risk in Caucasians, and LD between ERCC1 SNP, N118N and other race-specific allelic variants. Results: When compared to ERCC1 500C>T alone, a race-specific three-SNP variant haplotype in ERCC1 (comprised of rs11615, rs3212950 and rs3212948) was even more frequent in Caucasians with melanoma than in healthy Caucasians (p=0.0034) or African Americans (p<0.0001). A plasmid containing the variant haplotype was not differentially expressed. Conclusions: We demonstrate that ERCC1 500C>T participates in a previously characterised cancer-risk haplotype found more frequently in Caucasians, while LD is weak in African Americans; this haplotype appears to also be related to melanoma. It is therefore likely that ERCC1 500C>T is only a valid NER, disease or treatment outcome marker in Caucasians.

Effect of socioeconomic status as measured by education level on survival in breast cancer clinical trials - Herndon, J.E.; Kornblith, A.B.; Holland, J.C.; Paskett, E.D. (Psycho-Oncology, 2013)
Objectives This paper aims to investigate the effect of socioeconomic status, as measured by education, on the survival of breast cancer patients treated on 10 studies conducted by the Cancer and Leukemia Group B. Methods Sociodemographic data, including education, were reported by the patient at trial enrollment. Cox proportional hazards model stratified by treatment arm/study was used to examine the effect of education on survival among patients with early stage and metastatic breast cancer, after adjustment for known prognostic factors. Results The patient population included 1020 patients with metastatic disease and 5146 patients with early stage disease. Among metastatic patients, factors associated with poorer survival in the final multivariable model included African American race, never married, negative estrogen receptor status, prior hormonal therapy, visceral involvement, and bone involvement. Among early stage patients, significant factors associated with poorer survival included African American race, separated/widowed, post/perimenopausal, negative/unknown estrogen receptor status, negative progesterone receptor status, >4 positive nodes, tumor diameter >2 cm, and education. Having not completed high school was associated with poorer survival among early stage patients. Among metastatic patients, non-African American women who lacked a high school degree had poorer survival than other non-African American women, and African American women who lacked a high school education had better survival than educated African American women. Conclusions Having less than a high school education is a risk factor for death among patients with early stage breast cancer who participated in a clinical trial, with its impact among metastatic patients being less clear. Post-trial survivorship plans need to focus on women with low social status, as measured by education. Copyright © 2011 John Wiley & Sons, Ltd.
Keywords: breast cancer; education; oncology; SES; survival

A tailored prostate cancer education intervention for low-income African Americans: Impact on knowledge and screening - Ukoli, F.A.; Patel, K.; Hargreaves, M.; Beard, K.; Moton, P.J.; Bragg, R.; Beech, D.; Davis, R. (Journal of Health Care for the Poor and Underserved, 2013)
African American men bear disproportionate burden of prostate cancer (PCa) that can be reduced by early detection. A 15-minute culturally appropriate PCa education intervention developed to communicate effective, relevant, and balanced PCa screening information to low-income African American men was evaluated in men 42 years and older who had not been screened in one year. Of 539 men enrolled, 392 (72.7%) completed the six-month follow-up. Mean age was 54.4±8.9, 34.7% had no high school diploma, and 65.3% earned less than $25,000 annually. Barriers to screening included health insurance (41.4%), discomfort of digital rectal exam (32.1%), and fear of cancer diagnosis (29.9%). Mean knowledge score of 21 points increased from 13.27±3.51 to 14.95±4.14 (p<.001), and prostate-specific antigen screening from 22.1% to 62.8%. Men without high school diploma recorded the lowest post-intervention PCa knowledge and screening rate (47.7%), suggestive of the need for more than a single education session. Annual physicals with free prostate examination can maintain the positive trend observed. © Meharry Medical College.
Keywords: African americans; Education intervention; Informed decision; Prostate cancer; Screening

Representativeness of participants in the cancer care outcomes research and surveillance consortium relative to the surveillance, epidemiology, and end results program - Catalano, P.J.; Ayanian, J.Z.; Weeks, J.C.; Kahn, K.L.; Landrum, M.B.; Zaslavsky, A.M.; Lee, J.; Pendergast, J.; Harrington, D.P. (Medical Care, 2013)
Background: The research goals of the Cancer Care Outcomes Research and Surveillance (CanCORS) Consortium are to determine how characteristics and beliefs of patients, providers, and health care organizations influence the treatments and outcomes of individuals with newly diagnosed lung and colorectal cancers. As CanCORS results will inform national policy, it is important to know how they generalize to the United States population with these cancers. Research Design: This study assessed the representativeness of the CanCORS cohort of 10,547 patients with lung cancer (LC) or colorectal cancer (CRC) enrolled between 2003 and 2005. We compared characteristics (sex, race, age, and disease stage) with the Surveillance, Epidemiology, and End Results (SEER) population of 234,464 patients with new onset of these cancers during the CanCORS recruitment period. Results: The CanCORS sample is well matched to the SEER Program for both cancers. In CanCORS, 41% LC/47% CRC were female versus 47% LC/49% CRC in SEER. African American, Hispanic, and Asian cases differed by no more than 5 percentage points between CanCORS and SEER. The SEER population is slightly older, with the percentage of patients older than 75 years 33.1% LC/37.3% CRC in SEER versus 26.9% LC/29.4% in CanCORS, and also has a slightly higher proportion of early stage patients. We also found that the CanCORS cohort was representative within specific SEER regions that map closely to CanCORS sites. Conclusions: This study demonstrates that the CanCORS Consortium was successful in enrolling a demographically representative sample within the CanCORS regions. © 2012 by Lippincott Williams & Wilkins.

Cost analysis of a patient navigation system to increase screening colonoscopy adherence among urban minorities - Jandorf, L.; Stossel, L.M.; Cooperman, J.L.; Graff Zivin, J.; Ladabaum, U.; Hall, D.; Thélémaque, L.D.; Redd, W.; Itzkowitz, S.H. (Cancer, 2013)
Background: Patient navigation (PN) is being used increasingly to help patients complete screening colonoscopy (SC) to prevent colorectal cancer. At their large, urban academic medical center with an open-access endoscopy system, the authors previously demonstrated that PN programs produced a colonoscopy completion rate of 78.5% in a cohort of 503 patients (predominantly African Americans and Latinos with public health insurance). Very little is known about the direct costs of implementing PN programs. The objective of the current study was to perform a detailed cost analysis of PN programs at the authors' institution from an institutional perspective. Methods: In 2 randomized controlled trials, average-risk patients who were referred for SC by primary care providers were recruited for PN between May 2008 and May 2010. Patients were randomized to 1 of 4 PN groups. The cost of PN and net income to the institution were determined in a cost analysis. Results: Among 395 patients who completed colonoscopy, 53.4% underwent SC alone, 30.1% underwent colonoscopy with biopsy, and 16.5% underwent snare polypectomy. Accounting for the average contribution margins of each procedure type, the total revenue was 95,266.00. The total cost of PN was 14,027.30. Net income was 81,238.70. In a model sample of 1000 patients, net incomes for the institutional completion rate (approximately 80%), the historic PN program (approximately 65%), and the national average (approximately 50%) were compared. The current PN program generated additional net incomes of 35,035.50 and 44,956.00, respectively. Conclusions: PN among minority patients with mostly public health insurance generated additional income to the institution, mainly because of increased colonoscopy completion rates. Cancer 2013. © 2012 American Cancer Society.
Keywords: colorectal cancer screening; cost analysis; patient navigation; racial disparities; screening colonoscopy

Coaching intervention as a strategy for minority recruitment to cancer clinical trials - Fracasso, P.M.; Goodner, S.A.; Creekmore, A.N.; Morgan, H.P.; Foster, D.M.; Hardmon, A.A.; Engel, S.J.; Springer, B.C.; Mathews, K.J.; Fisher, E.B.; Walker, M.S. (Journal of Oncology Practice, 2013)
Purpose: Lack of trust and rapport with health care providers has been identified in the under-representation of racial/ethnic minorities within clinical trials. Our study used a coach to promote trust among minority patients with advanced cancer. Patients and Methods: Minority patients with advanced breast, colorectal, lung, or prostate carcinoma were randomly assigned to receive a coach Intervention (CI) or usual care (UC). All patients completed baseline and 6-month telephone interviews to assess demographics, trust in health care providers, attitudes toward clinical trials, and quality of life. Patients randomly assigned to CI were assigned a coach, who made bi-weekly contacts for 6 months to address general issues, progress or development in cancer care, and available resources. Patients randomly assigned to UC received the standard of care, without this intervention. Clinical trial enrollment was assessed. Results: Over 21 months, we screened 268 patients and enrolled 73 African Americans and two Asian Americans. Patients were randomly assigned to CI (n = 38) or to UC (n = 37). Longitudinal analyses were conducted on 69 patients who completed the 6-month follow-up assessment. Trial enrollment was 16 and 13 patients for the CI and UC groups, respectively. This difference was not significant (P = .351). Higher quality of life (1-point odds ratio on Functional Assessment of Cancer Treatment-General = 1.033, P = .036) and positive attitudes toward trials predicted enrollment. There was no significant difference between these groups in quality of life, attitudes toward clinical trials, perceptions of racism, trust in doctors, or depression. Conclusions: Quality of life and positive attitude toward trials predicted trial enrollment, regardless of assignment to CI or UC. Copyright © 2013 by American Society of Clinical Oncology.

A pilot randomized controlled trial of a commercial diet and exercise weight loss program in minority breast cancer survivors - Greenlee, H.A.; Crew, K.D.; Mata, J.M.; McKinley, P.S.; Rundle, A.G.; Zhang, W.; Liao, Y.; Tsai, W.Y.; Hershman, D.L. (Obesity, 2013)
Objective: Obesity is associated with poorer breast cancer outcomes and losing weight postdiagnosis may improve survival. As Hispanic and black women have poorer breast cancer prognosis than non-Hispanic whites diagnosed at similar age and stage, and have higher rates of obesity, effective weight loss strategies are needed. We piloted a randomized, waitlist-controlled, crossover study to examine the effects and feasibility of the commercial Curves weight loss program among Hispanic, African American and Afro- Caribbean breast cancer survivors. Design and Methods: Women with stage 0-IIIa breast cancer ≥6 months posttreatment, sedentary, and BMI ≥25 kg/m2 were randomized to the immediate arm (IA): 6 months of the Curves program followed by 6 months of observation; or the waitlist control arm (WCA): 6 months of observation followed by 6 months of the Curves program. The Curves program uses a 30-min exercise circuit and a highvegetable/low-fat/calorie-restricted diet. Results: A total of 42 women enrolled (79% Hispanic, 21% black), mean age 51 (range 32-69) and mean BMI 33.2(±5.9) kg/m2; 91% were retained at month 12. At month 6, women in the IA lost an average 3.3% (±3.5%) of body weight (range: 1.7% gain to 10.6% loss), as compared with 1.8% (62.9%) weight loss in the WCA (P = 0.04). At month 12, on average women in the IA regained some but not all of the weight lost during the first 6 months (P = 0.02). Conclusions: Minority breast cancer survivors were recruited and retained in a weight loss study. Six months of the Curves program resulted in moderate weight loss, but weight loss was not maintained postintervention. Future interventions should identify methods to increase uptake and maintenance of weight loss behaviors.

Stage-adjusted lung cancer survival does not differ between low-income blacks and whites - Aldrich, M.C.; Grogan, E.L.; Munro, H.M.; Signorello, L.B.; Blot, W.J. (Journal of Thoracic Oncology, 2013)
Introduction: Few lung cancer studies have focused on lung cancer survival in underserved populations. We conducted a prospective cohort study among 81,697 racially diverse and medically underserved adults enrolled in the Southern Community Cohort Study throughout an 11-state area of the Southeast from March 2002 to September 2009. Methods: Using linkages with state cancer registries, we identified 501 incident non-small-cell lung cancer cases. We applied Cox proportional hazards models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for subsequent mortality among black and white participants. Results: The mean observed follow-up time (the time from diagnosis to death or end of follow-up) was 1.25 years (range, 0-8.3 years) and 75% (n = 376) of cases died during follow-up. More blacks were diagnosed at distant stage than whites (57 versus 45%; p = 0.03). In multivariable analyses adjusted for pack-years of smoking, age, body mass index, health insurance, socioeconomic status and disease stage, the lung cancer mortality HR was higher for men versus women (HR = 1.41; 95% CI, 1.09-1.81) but similar for blacks versus whites (HR = 0.99; 95% CI, 0.74-1.32). Conclusion: These findings suggest that although proportionally more blacks present with distant-stage disease there is no difference in stage-adjusted lung cancer mortality between blacks and whites of similar low socioeconomic status. Copyright © 2013 by the International Association for the Study of Lung Cancer.
Keywords: Disparities; Lung cancer; Race; Socioeconomic status; Survival

A randomized controlled Alzheimer's disease prevention trial's evolution into an exposure trial: The preadvise trial - Kryscio, R.J.; Abner, E.L.; Schmitt, F.A.; Goodman, P.J.; Mendiondo, M.; Caban-Holt, A.; Dennis, B.C.; Mathews, M.; Klein, E.A.; Crowley, J.J. (Journal of Nutrition, Health and Aging, 2013)
Objectives: To summarize the ongoing Prevention of Alzheimer's Disease (AD) by Vitamin E and Selenium (PREADViSE) trial as an ancillary study to SELECT (a large prostate cancer prevention trial) and to present the blinded results of the first year as an exposure study. Design: PREADViSE was designed as a double blind randomized controlled trial (RCT). Setting: SELECT terminated after median of 5.5 years of exposure to supplements due to a futility analysis. Both trials then converted into an exposure study. Participants: In the randomized component PREADViSE enrolled 7,547 men age 62 or older (60 if African American). Once the trial terminated 4,246 of these men volunteered for the exposure study. Demographics were similar for both groups with exposure volunteers having baseline mean age 67.3 ± 5.2 years, 15.3 ± 2.4 years of education, 9.8% African Americans, and 22.0% reporting a family history of dementia. Intervention: In the RCT men were randomly assigned to either daily doses of 400 IU of vitamin E or placebo and 200 μg of selenium or placebo using a 2×2 factorial structure. Measurements: In the RCT, participants completed the Memory Impairment Screen (MIS), and if they failed, underwent a longer screening (based on an expanded Consortium to Establish a Registry in AD [CERAD] battery). CERAD failure resulted in visits to their clinician for medical examination with records of these examinations forwarded to the PREADViSE center for further review. In the exposure study, men are contacted by telephone and complete the telephone version of the memory impairment screen (MIS-T) screen. If they fail the MIS-T, a Modified Telephone Interview of Cognitive Status (TICS-M) exam is given. A failed TICS-M exam also leads to a visit to their clinician for an in-depth examination and forwarding of records for a centralized consensus diagnosis by expert clinicians. A subgroup of the men who pass the MIS-T also take the TICS-M exam for validation purposes. Results: While this ancillary trial was open to all 427 SELECT clinical sites, only 130 (30.0%) of the sites chose to participate in PREADViSE. Staff turnover at the sites presented challenges when training persons unfamiliar with cognitive testing procedures to conduct the memory screens. In the RCT few participants (1.6%) failed the MIS screen and among those who passed this screen a significant practice effect was encountered. In the exposure study 3,581 men were reached by phone in year 1, 15.7% could not be reached after 5 calls, and of those contacted 6.0% refused the screen even after consenting to the procedures at their clinical site. Most notable is that the failure rate for the MIS-T increased fourfold to 7.2%. Of the 257 men who took the TICS-M, 84.0% failed and were asked to contact their physicians for a more detailed memory assessment, and approximately half of these had some form of dementia or cognitive impairment. Several of these dementia cases are not AD. Conclusion: Partnering with SELECT led to an AD prevention trial conducted at a very reasonable cost by taking advantage of the experience and efficient clinical trial management found in a cancer cooperative group (Southwest Oncology Group or SWOG). Once unblinded, the RCT and exposure study data have the potential to yield new information on long term exposure to antioxidant supplements under controlled conditions. © 2013 Serdi and Springer-Verlag France.
Keywords: Alzheimer's disease; case ascertainment; cognitive assessments; prevention; telephone screening

Out-of-pocket expenses and treatment choice for men with prostate cancer - Jung, O.S.; Guzzo, T.; Lee, D.; Mehler, M.; Christodouleas, J.; Deville, C.; Hollis, G.; Shah, A.; Vapiwala, N.; Wein, A.; Pauly, M.; Bekelman, J.E. (Urology, 2012)
Objective: To describe the knowledge of, and attitudes toward, out-of-pocket expenses (OOPE) associated with prostate cancer treatment and the influence of OOPE on the treatment choices of patients with prostate cancer. Materials and Methods: We undertook a qualitative research study for which we recruited patients with clinically localized prostate cancer. Patients answered a series of open-ended questions during a semistructured interview and completed a questionnaire about the physician's role in discussing OOPE, the burden of OOPE, the effect of OOPE on treatment decisions, and previous knowledge of OOPE. Results: A total of 41 (26 white and 15 black) eligible patients were enrolled from the urology and radiation oncology practices of the University of Pennsylvania. Qualitative assessment revealed 5 major themes: (a) "my insurance takes care of it"; (b) "health is more important than cost"; (c) "I did not look into it"; (d) "I cannot afford it but would have chosen the same treatment"; and (e) "It is not my doctor's business." Most patients (38 of 41, 93%) reported that they would not have chosen a different treatment even if they had known the actual OOPE of their treatment. Patients who reported feeling burdened by OOPE were socioeconomically heterogeneous, and their treatment choices remained unaffected. Only 2 patients stated they knew "a lot" about the likely OOPE for different prostate cancer treatments before choosing their treatment. Conclusion: Among insured patients with prostate cancer treated at a large academic medical center, few had knowledge of OOPE before making treatment choices. © 2012 Elsevier Inc. All Rights Reserved.

Follow-up and timeliness after an abnormal cancer screening among underserved, urban women in a patient navigation program - Markossian, T.W.; Darnell, J.S.; Calhoun, E.A. (Cancer Epidemiology Biomarkers and Prevention, 2012)
Background: We evaluated the efficacy of a Chicago-based cancer patient navigation program developed to increase the proportion of patients reaching diagnostic resolution and reduce the time from abnormal screening test to definitive diagnostic resolution. Methods: Women with an abnormal breast (n = 352) or cervical (n = 545) cancer screening test were recruited for the quasi-experimental study. Navigation subjects originated from five federally qualified health center sites and one safety net hospital. Records-based concurrent control subjects were selected from 20 sites. Control sites had similar characteristics to the navigated sites in terms of patient volume, racial/ethnic composition, and payor mix. Mixed-effects logistic regression and Cox proportional hazard regression analyses were conducted to compare navigation and control patients reaching diagnostic resolution by 60 days and time to resolution, adjusting for demographic covariates and site. Results: Compared with controls, the breast navigation group had shorter time to diagnostic resolution (aHR = 1.65, CI = 1.20-2.28) and the cervical navigation group had shorter time to diagnostic resolution for those who resolved after 30 days (aHR = 2.31, CI = 1.75-3.06), with no difference before 30 days (aHR = 1.42, CI = 0.83-2.43). Variables significantly associated with longer time to resolution for breast cancer screening abnormalities were being older, never partnered, abnormal mammogram and BI-RADS 3, and being younger and Black for cervical abnormalities. Conclusions: Patient navigation reduces time from abnormal cancer finding to definitive diagnosis in underserved women. Impact: Results support efforts to use patient navigation as a strategy to reduce cancer disparities among socioeconomically disadvantaged women. ©2012 AACR.

The prostate cancer intervention versus observation trial: VA/NCI/AHRQ cooperative studies program #407 (PIVOT): Design and baseline results of a randomized controlled trial comparing radical prostatectomy with watchful waiting for men with clinically localized prostate cancer - Wilt, T.J. (Journal of the National Cancer Institute - Monographs, 2012)
Prostate cancer is the most common noncutaneous malignancy and the second leading cause of cancer death in men. In the United States, 90% of men with prostate cancer are more than age 60 years, diagnosed by early detection with the prostate-specific antigen (PSA) blood test, and have disease believed confined to the prostate gland (clinically localized). Common treatments for clinically localized prostate cancer include watchful waiting (WW), surgery to remove the prostate gland (radical prostatectomy), external-beam radiation therapy and interstitial radiation therapy (brachytherapy), and androgen deprivation. Little is known about the relative effectiveness and harms of treatments because of the paucity of randomized controlled trials. The Department of Veterans Affairs/National Cancer Institute/Agency for Healthcare Research and Quality Cooperative Studies Program Study #407:Prostate Cancer Intervention Versus Observation Trial (PIVOT), initiated in 1994, is a multicenter randomized controlled trial comparing radical prostatectomy with WW in men with clinically localized prostate cancer. We describe the study rationale, design, recruitment methods, and baseline characteristics of PIVOT enrollees. We provide comparisons with eligible men declining enrollment and men participating in another recently reported randomized trial of radical prostatectomy vs WW conducted in Scandinavia. We screened 13 022 men with prostate cancer at 52 US medical centers for potential enrollment. From these, 5023 met initial age, comorbidity, and disease eligibility criteria, and a total of 731 men agreed to participate and were randomized. The mean age of enrollees was 67 years. Nearly one-third were African American. Approximately 85% reported that they were fully active. The median PSA was 7.8ng/mL (mean 10.2ng/mL). In three-fourths of men, the primary reason for biopsy leading to a diagnosis of prostate cancer was a PSA elevation or rise. Using previously developed tumor risk categorizations incorporating PSA levels, Gleason histologic grade, and tumor stage, it was found that approximately 40% had low-risk, 34% had medium-risk, and 21% had high-risk prostate cancer based on local histopathology. Comparison to our national sample of eligible men declining PIVOT participation as well as to men enrolled in the Scandinavian trial indicated that PIVOT enrollees are representative of men being diagnosed and treated in the United States and quite different from men in the Scandinavian trial. PIVOT enrolled an ethnically diverse population representative of men diagnosed with prostate cancer in the United States. Results will yield important information regarding the relative effectiveness and harms of surgery compared with WW for men with predominately PSA-detected clinically localized prostate cancer. Published by Oxford University Press 2012.

Beliefs and attitudes about lung cancer screening among smokers - Jonnalagadda, S.; Bergamo, C.; Lin, J.J.; Lurslurchachai, L.; Diefenbach, M.; Smith, C.; Nelson, J.E.; Wisnivesky, J.P. (Lung Cancer, 2012)
The National Lung Screening Trial (NLST) recently reported that annual computed tomography (CT) screening is associated with decreased lung cancer mortality in high-risk smokers. Beliefs about lung cancer and screening, particularly across race and ethnicity, and their influence on CT screening utilization are largely unexamined. Our study recruited asymptomatic, high-risk smokers, 55-74 years of age from primary care clinics in an academic urban hospital. Guided by the self-regulation theory, we evaluated cognitive and affective beliefs about lung cancer. Intention to screen for lung cancer with a CT scan was assessed by self-report. We used univariate and logistic regression analyses to compare beliefs about screening and intention to screen among minority (Blacks and Hispanics) and non-minority participants. Overall, we enrolled 108 participants, of which 40% were Black and 34% were Hispanic; the mean age was 62.3 years, and median pack-years of smoking was 26. We found that intention to screen was similar among minorities and non-minorities (p= 0.19); however, Hispanics were less likely to report intention to screen if they had to pay for the test (p= 0.02). Fatalistic beliefs, fear of radiation exposure, and anxiety related to CT scans were significantly associated with decreased intention to screen (p< 0.05). Several differences were observed in minority versus non-minority participants' beliefs toward lung cancer and screening. In conclusion, we found that concerns about cost, which were particularly prominent among Hispanics, as well as fatalism and radiation exposure fears may constitute barriers to lung cancer screening. Lung cancer screening programs should address these factors to ensure broad participation, particularly among minorities. © 2012 Elsevier Ireland Ltd.
Keywords: Cancer; Cancer screening; Cultural differences; Health behavior; Health beliefs; Race and ethnicity

A pilot program in collaboration with African American churches successfully increases awareness of the importance of cancer research and participation in cancer translational research studies among African Americans - Colon-Otero, G.; Albertie, M.; Lesperance, M.; Weis, J.A.; Coles, A.; Smith, N.; Mills, L.; Woodward, T.; Aspitia, A.M.; Vishnu, P.; Willis, F.; Isley, A.; et al. (Journal of Cancer Education, 2012)
African Americans are underrepresented in cancer research. We evaluate whether collaboration with African American churches can improve cancer awareness and increase participation in translational research protocols among African Americans. From February to April 2010, the Mayo Clinic partnered with African American Jacksonville churches to provide educational programs focused on cancer research and healthy behaviors. Education on multiple myeloma and on-site access to a translational cancer research pilot project evaluating the prevalence of monoclonal gammopathies and t(14,18) in African Americans was offered. Seventy-four percent, 236 out of 318 participants, returned the questionnaires. The majority of participants had never received information on multiple myeloma (67%), had never received clinical research study information (57%), and were enrolled in the translational research studies (55%). Partnerships with African American churches in community education projects that bring research to church venues are effective in improving cancer awareness and in increasing research participation among African Americans. © 2011 Springer Science+Business Media, LLC.
Keywords: African Americans; Cancer; Healthcare disparities; Minority health; Monoclonal proteins; Multiple myeloma; t (14,18)

Developing partnerships and recruiting dyads for a prostate cancer informed decision making program: Lessons learned from a community-academic-clinical team - Friedman, D.B.; Johnson, K.M.; Owens, O.L.; Thomas, T.L.; Dawkins, D.S.; Gansauer, L.; Bartelt, S.; Waddell, N.M.; Talley, P.J.; Bearden III, J.D.; Hébert, J.R. (Journal of Cancer Education, 2012)
Prostate cancer (PrCA) is the most commonly diagnosed non-skin cancer among men. PrCA mortality in African-American (AA) men in South Carolina is ∼50% higher than for AAs in the U.S as a whole. AA men also have low rates of participation in cancer research. This paper describes partnership development and recruitment efforts of a Community-Academic-Clinical research team for a PrCA education intervention with AA men and women that was designed to address the discordance between high rates of PrCA mortality and limited participation in cancer research. Guided by Vesey's framework on recruitment and retention of minority groups in research, recruitment strategies were selected and implemented following multiple brainstorming sessions with partners having established community relationships. Based on findings from these sessions culturally appropriate strategies are recommended for recruiting AA men and women for PrCA education research. Community-based research recruitment challenges and lessons learned are presented. © 2011 Springer Science+Business Media, LLC.
Keywords: African-American men and women; Cancer communication; Community-based participatory research; Multi-media; Recruitment; Research partnerships

Effect of comorbid conditions on adherence to colorectal cancer screening - Lukin, D.J.; Jandorf, L.H.; Dhulkifl, R.J.; Thélémaque, L.D.; Christie, J.A.; Itzkowitz, S.H.; DuHamel, K.N. (Journal of Cancer Education, 2012)
Potential barriers to colorectal cancer (CRC) screening include preexisting medical conditions (comorbidities), physician recommendation, psychosocial factors, and screening preparedness. This study's purpose was to investigate the impact of comorbid conditions on CRC screening among African Americans. A stage-matched randomized clinical trial was performed. Asymptomatic African Americans over age 50, with a primary care physician, and eligible for CRC screening were recruited at The Mount Sinai Hospital from 2005 to 2008. One hundred sixty-one patients were assessed for referral for, and completion of, CRC screening, comorbid conditions, "readiness to change," and number of physician visits within the observation period. Data was compared to a pretrial index to predict the likely effect of comorbid conditions on CRC screening. One hundred fifty-nine patients completed the study; 108 (68.9%) were referred for and 34 (21.2%) completed CRC screening. No demographic characteristics were associated with CRC screening completion. CRC screening referrals were similar for all patients, regardless of comorbidities or clinical visits. Comorbidities rated as having extreme influence on CRC screening showed a trend toward lower screening rates. There was a significant increase in screening rates among participants in advanced stages of readiness at enrollment. These data suggest that while comorbidities did not predict colonoscopy completion, they may play a role in concert with other factors. This is the only study to assess the effect of screening colonoscopy in an African American primary care setting. We must continue to explore interventions to narrow the disparate gap in screening and mortality rates. © 2011 Springer Science+Business Media, LLC.
Keywords: African Americans; Co-morbidities; Colorectal cancer; Screening barriers; Screening colonoscopy

A randomized, placebo controlled trial of oral zinc for chemotherapy-related taste and smell disorders - Lyckholm, L.; Heddinger, S.P.; Parker, G.; Coyne, P.J.; Ramakrishnan, V.; Smith, T.J.; Henkin, R.I. (Journal of Pain and Palliative Care Pharmacotherapy, 2012)
Abnormalities in taste and smell are commonly reported in patients receiving chemotherapy and may hinder appetite, dietary intake, nutritional well-being, and quality of life. Oral zinc has been used to treat taste and smell abnormalities in several altered physiologic states, including renal failure, liver disease, head trauma, and pregnancy, with varying results. The authors conducted a double-blinded, placebo-controlled randomized clinic trial over 3 months. Eligible patients were those taking chemotherapy that had alterations in taste and/or smell. The measurement of the primary end point, improvement in altered taste and smell, was made using a 0100 scale (100 describing no loss or distortion in taste and smell, and 0 describing the worst distortion or loss of taste and smell). Twenty-nine subjects were enrolled in each treatment group, of whom 31 were white, 26 African American, and 1 Native American. Forty-one patients were female. A wide range of cancer types was represented, with breast the most common (21 patients). The zinc dose was 220 mg orally twice daily (equivalent of 50 mg elemental zinc twice daily). There was no statistically significant improvement in loss or distortion of taste or smell with the addition of zinc. There was a trend toward improvement over time in all groups, except in the zinc group where there was a nonsignificant worsening in loss of smell over time. Zinc at standard doses did not provide significant benefit to taste or smell in patients receiving chemotherapy. © 2012 Informa Healthcare USA, Inc.
Keywords: Cancer; Chemotherapy; Smell; Taste; Zinc

Quality of breast cancer care: Perception versus practice - Bickell, N.A.; Neuman, J.; Fei, K.; Franco, R.; Joseph, K.-A. (Journal of Clinical Oncology, 2012)
Purpose: Because insurers use performance and quality metrics to inform reimbursement, identifying remediable causes of poor-quality cancer care is imperative. We undertook this descriptive cohort study to assess key predictors of women's perceived quality of their breast cancer care and actual guideline-concordant quality of care received. Patients and Methods: We surveyed inner-city women with newly diagnosed and surgically treated early-stage breast cancer requiring adjuvant treatment who were enrolled onto a randomized controlled trial (RCT) of patient assistance to reduce disparities in care. We assessed women's perceived quality of care and perceived quality of the process of getting care, such as getting referrals, test results, and treatments; we abstracted records to determine the actual quality of care. Results: Of the 374 new patients with early-stage breast cancer enrolled onto the RCT, only a slight majority of women (55%) perceived their quality of care as excellent; 88% actually received good-quality, guideline-concordant care. Excellent perceived quality (P < .001) was significantly associated with patients' perception of the quality of the process of getting care (adjusted relative risk [RR], 1.78; 95% CI, 1.65 to 1.87). Also associated with perceived quality - and mediated by race - were trust in one's physician (adjusted RR, 1.43; 95% CI, 1.16 to 1.64) and perceived racism, which affected black women more than women of other races/ethnicities (black race-adjusted RR for perceived racism, 0.33 [95% CI, 0.10 to 0.87]; black race-adjusted RR for trust, 1.61 [95% CI, 0.97 to 1.90]; c = 0.82 for the model; P < .001). Actual quality of care provided did not affect perceived quality of care received. Conclusion: Patients' perceived quality of care differs from their receipt of high-quality care. Mutable targets to improve perceived quality of care include the processes of getting care and trusting their physician. © 2012 by American Society of Clinical Oncology.

Prospective preference assessment of patients' willingness to participate in a randomized controlled trial of intensity-modulated radiotherapy versus proton therapy for localized prostate cancer - Shah, A.; Efstathiou, J.A.; Paly, J.J.; Halpern, S.D.; Bruner, D.W.; Christodouleas, J.P.; Coen, J.J.; Deville Jr., C.; Vapiwala, N.; Shipley, W.U.; Zietman, A.L.; Hahn, S.M.; et al. (International Journal of Radiation Oncology Biology Physics, 2012)
Purpose: To investigate patients' willingness to participate (WTP) in a randomized controlled trial (RCT) comparing intensity-modulated radiotherapy (IMRT) with proton beam therapy (PBT) for prostate cancer (PCa). Methods and Materials: We undertook a qualitative research study in which we prospectively enrolled patients with clinically localized PCa. We used purposive sampling to ensure a diverse sample based on age, race, travel distance, and physician. Patients participated in a semi-structured interview in which they reviewed a description of a hypothetical RCT, were asked open-ended and focused follow-up questions regarding their motivations for and concerns about enrollment, and completed a questionnaire assessing characteristics such as demographics and prior knowledge of IMRT or PBT. Patients' stated WTP was assessed using a 6-point Likert scale. Results: Forty-six eligible patients (33 white, 13 black) were enrolled from the practices of eight physicians. We identified 21 factors that impacted patients' WTP, which largely centered on five major themes: altruism/desire to compare treatments, randomization, deference to physician opinion, financial incentives, and time demands/scheduling. Most patients (27 of 46, 59%) stated they would either "definitely" or "probably" participate. Seventeen percent (8 of 46) stated they would "definitely not" or "probably not" enroll, most of whom (6 of 8) preferred PBT before their physician visit. Conclusions: A substantial proportion of patients indicated high WTP in a RCT comparing IMRT and PBT for PCa. © 2012 Elsevier Inc. All rights reserved.
Keywords: Intensity-modulated radiotherapy; Prostate cancer; Proton beam therapy; Randomized controlled trial

Adherence to colorectal cancer screening: A randomized clinical trial of competing strategies - Inadomi, J.M.; Vijan, S.; Janz, N.K.; Fagerlin, A.; Thomas, J.P.; Lin, Y.V.; Munõz, R.; Lau, C.; Somsouk, M.; El-Nachef, N.; Hayward, R.A. (Archives of Internal Medicine, 2012)
Background: Despite evidence that several colorectal cancer (CRC) screening strategies can reduce CRC mortality, screening rates remain low. This study aimed to determine whether the approach by which screening is recommended influences adherence. Methods: We used a cluster randomization design with clinic time block as the unit of randomization. Persons at average risk for development of CRC in a racially/ethnically diverse urban setting were randomized to receive recommendation for screening by fecal occult blood testing (FOBT), colonoscopy, or their choice of FOBT or colonoscopy. The primary outcome was completion of CRC screening within 12 months after enrollment, defined as performance of colonoscopy, or 3 FOBT cards plus colonoscopy for any positive FOBT result. Secondary analyses evaluated sociodemographic factors associated with completion of screening. Results: A total of 997 participants were enrolled; 58% completed the CRC screening strategy they were assigned or chose. However, participants who were recommended colonoscopy completed screening at a significantly lower rate (38%) than participants who were recommended FOBT (67%) (P<.001) or given a choice between FOBT or colonoscopy (69%) (P<.001). Latinos and Asians (primarily Chinese) completed screening more often than African Americans. Moreover, nonwhite participants adhered more often to FOBT, while white participants adhered more often to colonoscopy. Conclusions: The common practice of universally recommending colonoscopy may reduce adherence to CRC screening, especially among racial/ethnic minorities. Significant variation in overall and strategy-specific adherence exists between racial/ethnic groups; however, this may be a proxy for health beliefs and/or language. These results suggest that patient preferences should be considered when making CRC screening recommendations. Trial Registration: clinicaltrials.gov Identifier: NCT00705731. ©2012 American Medical Association. All rights reserved.

Increasing minority patient participation in cancer clinical trials using oncology nurse navigation - Holmes, D.R.; Major, J.; Lyonga, D.E.; Alleyne, R.S.; Clayton, S.M. (American Journal of Surgery, 2012)
Background: Residential distance from an academic or cancer center is a significant barrier to minority patient participation in cancer research. Most cancer clinical trials (CTs) are only accessible at academic and cancer centers, yet most cancer patients receive treatment in their home communities where access to CTs may be limited. Oncology nurse navigation is an innovative approach for increasing minority CT participation by facilitating access to cancer CTs in communities where minority patients live. The purpose of this study was to evaluate the impact of oncology nurse navigation on community-based recruitment of black patients to breast cancer CTs at a major cancer center. Methods: We merged the roles of a traditional oncology research nurse and a professional patient navigator to create a novel health care provider role, the oncology nurse navigator. The primary duties of the oncology nurse navigator were to engage black cancer patients in the offices of their community physicians and to collaborate with community physicians to increase black patient participation in cancer research. The oncology nurse navigator played a key role in all phases of the CT participation process (e.g., screening for eligibility and completion of informed consent and clinical research forms) and guided each patient around barriers in the health care system. The accrual of eligible patients to breast cancer CTs was used to assess the impact of oncology nurse navigation on community-based recruitment of blacks to cancer CTs. Results: Between January 2007 and December 2008, a total of 132 black breast cancer patients were screened by a single oncology nurse navigator for eligibility to University of Southern Californiasponsored breast cancer CTs. Fifty-nine patients were eligible for CTs, and each was invited to participate in 1 or more CTs for which they were eligible. Fifty-one of 59 eligible black patients (86% of eligible patients) were enrolled to 1 or more research protocols. The estimated cost per enrolled patient was $5,677, nearly half the expected per patient cost of treating patients on CT at an academic or cancer center. Conclusions: Oncology nurse navigation is an effective outreach strategy for increasing black patient participation in cancer research and may be achieved at nearly half the cost of traditional methods of enrolling patients in CTs at cancer centers. © 2012 Elsevier Inc. All rights reserved.
Keywords: African American; Blacks; Community outreach; Community partners; Community physician; Cost-effective; Heath disparities; Oncology research nurse; Underserved communities

Phase II efficacy and pharmacogenomic study of selumetinib (AZD6244; ARRY-142886) in iodine-131 refractory papillary thyroid carcinoma with or without follicular elements - Hayes, D.N.; Lucas, A.S.; Tanvetyanon, T.; Krzyzanowska, M.K.; Chung, C.H.; Murphy, B.A.; Gilbert, J.; Mehra, R.; Moore, D.T.; Sheikh, A.; Hoskins, J.; Hayward, M.C.; et al. (Clinical Cancer Research, 2012)
Purpose: A multicenter, open-label, phase II trial was conducted to evaluate the efficacy, safety, and tolerability of selumetinib in iodine-refractory papillary thyroid cancer (IRPTC). Experimental Design: Patients with advanced IRPTC with or without follicular elements and documented disease progression within the preceding 12 months were eligible to receive selumetinib at a dose of 100 mg twice daily. The primary endpoint was objective response rate using Response Evaluation Criteria in Solid Tumors. Secondary endpoints were safety, overall survival, and progression-free survival (PFS). Tumor genotype including mutations in BRAF, NRAS, and HRAS was assessed. Results: Best responses in 32 evaluable patients out of 39 enrolled were 1 partial response (3%), 21 stable disease (54%), and 11 progressive disease (28%). Disease stability maintenance occurred for 16 weeks in 49%, 24 weeks in 36%. Median PFS was 32 weeks. BRAF V600E mutants (12 of 26 evaluated, 46%) had a longer median PFS compared with patients with BRAF wild-type (WT) tumors (33 versus 11 weeks, respectively, HR = 0.6, not significant, P = 0.3). The mostcommonadverse events and grades 3 to 4 toxicities included rash, fatigue, diarrhea, and peripheral edema. Two pulmonary deaths occurred in the study and were judged unlikely to be related to the study drug. Conclusions: Selumetinib was well tolerated but the study was negative with regard to the primary outcome. Secondary analyses suggest that future studies of selumetinib and other mitogen-activated protein (MAP)/extracellular signal-regulated kinase (ERK; MEK) inhibitors in IRPTC should consider BRAF V600E mutation status in the trial design based on differential trends in outcome. ©2012 AACR.

Successful recruitment of healthy African American men to genomic studies from high-volume community health fairs: Implications for future genomic research in minority populations - Patel, Y.R.; Carr, K.A.; Magjuka, D.; Mohammadi, Y.; Dropcho, E.F.; Reed, A.D.; Moore, M.L.; Waddell, M.J.; Shedd-Steele, R.; Sweeney, C.J.; Hahn, N.M. (Cancer, 2012)
Background: Study of genomic data obtained from patient biospecimens is frequent in research of subjects with prostate and other epithelial malignancies. Understanding of the characteristics of healthy men who participate in genomic research is limited. Methods: Patients were identified through the Prostate Cancer Genetic Risk Evaluation of SNPs Study and the Indiana University Cancer Biomarker Study, 2 population-based biomarker and cohort studies. Between 2006 and 2010, healthy Caucasian (n = 774) and healthy African American (n = 381) men were recruited and enrolled at high-volume free community health fairs. Each participant completed a demographic questionnaire and provided a blood sample for genomic research investigations. Frequency differences between demographic features of healthy African American and Caucasian men were compared and analyzed by 2-sample t test and multivariate logistic regression after adjusting potential confounding variables with significance at the P <.05 level. Features examined included: age, body mass index (BMI), income, education, marital status, tobacco, alcohol, family history, prostate-specific antigen (PSA) level, and prior prostate cancer screening history. Results: Significant differences between healthy Caucasian and African American men participating in genomic research included: marital status (married, 69% Caucasian vs 46% African American, P< <.001), mean age (years, 58 Caucasian vs 54 African American, P <.001), mean BMI (kg/m 2, 30.9 Caucasian vs 32.3 African American, P =.004), annual income (P =.038), education (P =.002), and mean PSA (ng/mL, 1.2 Caucasian vs 2.0 African American, P =.005). Conclusions: Significant demographic differences exist between healthy Caucasian and African American men choosing to participate in genomic research. These differences may be important in designing genomic research study recruitment strategies. © 2011 American Cancer Society.
Keywords: African American; community health fairs; demographics; genomic research; healthy population

Immunogenicity of the quadrivalent human papillomavirus (type 6/11/16/18) vaccine in males 16 to 26 years old - Hillman, R.J.; Giuliano, A.R.; Palefsky, J.M.; Goldstone, S.; Moreira Jr., E.D.; Vardas, E.; Aranda, C.; Jessen, H.; Ferris, D.G.; Coutlee, F.; Marshall, J.B.; Vuocolo, S.; et al. (Clinical and Vaccine Immunology, 2012)
Human papillomavirus (HPV) infection can lead to significant disease in males, including anogenital warts, intraepithelial neoplasias, and several types of oral and anogenital cancers. The quadrivalent HPV (type 6/11/16/18) L1 virus-like particle (VLP) vaccine (qHPV vaccine; Gardasil) has recently been demonstrated to prevent persistent infection and associated disease related to vaccine HPV types in males. We report the overall immunogenicity results from a trial of the quadrivalent HPV vaccine in males. Overall, 3,463 heterosexual men and 602 men who had sex with men were enrolled into a randomized, placebo-controlled, double-blind safety, immunogenicity, and efficacy study. Serum samples were collected prior to vaccination at day 1 and at months 7, 24, and 36 postvaccination. Immunogenicity was evaluated with a multiplex, competitive Luminex immunoassay. Almost all subjects (97.4 to 99.2%) seroconverted for vaccine HPV types by month 7. At month 36, 88.9%, 94.0%, 97.9%, and 57.0% of subjects were still seropositive for HPV-6, -11, -16, and -18, respectively. For all vaccine HPV types, black subjects had significantly higher antibody titers at month 7 than did both Caucasian and Asian subjects. An anamnestic antibody response was seen in men seropositive before vaccination. The vaccine was highly immunogenic in males 16 to 23 years of age; responses were comparable to those observed in women. Furthermore, the immune responses were consistent with the established efficacy of the vaccine in the prevention of incident and persistent HPV infection, anogenital warts, and anal intraepithelial neoplasia. Copyright © 2012, American Society for Microbiology. All Rights Reserved.

Detection of small metastatic brain tumors: Comparison of 3D contrast-enhanced whole-brain black-blood imaging and MP-RAGE imaging - Park, J.; Kim, J.; Yoo, E.; Lee, H.; Chang, J.-H.; Kim, E.Y. (Investigative Radiology, 2012)
Objective: Early and accurate diagnosis of small metastatic brain tumors may affect outcomes and treatment strategies. For this reason, 3-dimensional (3D) thin-section imaging is preferred. However, with conventional contrast-enhanced (CE) 3D imaging, such as magnetization-prepared rapid gradient echo (MP-RAGE), many visually enhanced vessels may mimic small metastatic tumors, hindering tumor detection. CE black-blood single-slab 3D turbo-spin echo imaging (BB-ssTSE) was recently developed, which uses variable refocusing flip angles and flow-sensitizing gradient schemes, to enhance metastatic brain tumors while selectively suppressing blood vessels. The purpose of this work was to investigate the efficiency of the proposed CE BB-ssTSE in detecting small metastatic brain tumors as compared with conventional MP-RAGE. Materials and Methods: Numerical comparisons of MP-RAGE and BB-ssTSE were performed by simulation studies to investigate the signal/contrast behaviors of flowing blood and stationary CE tumors. For in vivo studies, we enrolled 35 patients (18 women; mean age, 58.1 years) with breast or lung cancer who underwent brain magnetic resonance imaging. After administering a double dose of contrast medium, whole-brain 2-dimensional T1-weighted imaging followed by high-resolution isotropic 3D BB-ssTSE and MP-RAGE was performed at 3.0 T. Two reviewers independently evaluated the presence of metastatic brain tumors using: (1) MP-RAGE; (2) BB-ssTSE; and (3) MP-RAGE + BB-ssTSE sequentially in 3 review sessions, 2 weeks apart. The lesions were classified by size into 2 groups: large (<5 mm) and small (<5 mm). Both reviewers marked all tumors detected at each session. Another reviewer combined the results of the 2 reviewers and compared the detection rates of metastatic brain tumors between BB-ssTSE and MP-RAGE by using follow-up imaging. Intraclass correlation coefficients between the 2 reviewers were measured. Results: Numerical simulations showed that the proposed BB-ssTSE effectively attenuated the signal intensity of flowing blood over the entire echo train, resulting in CE tumor-to-white matter contrast comparable with conventional MP-RAGE. The combined evaluation of MP-RAGE + BB-ssTSE showed 242 tumors in 28 patients. Of these, 153 lesions were <5 mm. MP-RAGE found 111 small metastatic brain tumors, BB-ssTSE found 150, and MP-RAGE + BB-ssTSE found 153. Significantly, more small tumors were detected by BB-ssTSE than MP-RAGE (P = 0.001, Wilcoxon signed-rank test). All large tumors were detected similarly by both MP-RAGE and BB-ssTSE. By combined results for MP-RAGE + BB-ssTSE, sensitivities for detection of small metastatic tumors were 72.5% for MP-RAGE and 98.0% for BB-ssTSE (P < 0.0001, McNemar test). Intraclass correlation coefficients between the 2 reviewers were 0.826 for MP-RAGE and 0.954 for BB-ssTSE. Conclusion: Compared with conventional MP-RAGE, the proposed CE BB-ssTSE imaging, which enhances tumors while selectively suppressing blood vessels, leads to significantly better detection of small metastatic brain tumors <5 mm. © 2012 by Lippincott Williams & Wilkins.
Keywords: black-blood; brain metastases; contrast-enhanced; MRI; spin echo; variable flip angle

Long-term follow-up of a prospective trial of trimodality therapy of weekly paclitaxel, radiation, and androgen deprivation in high-risk prostate cancer with or without prior prostatectomy - Hussain, A.; Wu, Y.; Mirmiran, A.; Dibiase, S.; Goloubeva, O.; Bridges, B.; Mannuel, H.; Engstrom, C.; Dawson, N.; Amin, P.; Kwok, Y. (International Journal of Radiation Oncology Biology Physics, 2012)
Purpose: Weekly paclitaxel, concurrent radiation, and androgen deprivation (ADT) were evaluated in patients with high-risk prostate cancer (PC) with or without prior prostatectomy (RP). Methods and Materials: Eligible post-RP patients included: pathological T3 disease, or rising prostate-specific antigen (PSA) ≥0.5 ng/mL post-RP. Eligible locally advanced PC (LAPC) patients included: 1) cT2b-4N0N+, M0; 2) Gleason score (GS) 8-10; 3) GS 7 + PSA 10-20 ng/mL; or 4) PSA 20-150 ng/mL. Treatment included ADT (4 or 24 months), weekly paclitaxel (40, 50, or 60 mg/m 2/wk), and pelvic radiation therapy (total dose: RP = 64.8 Gy; LAPC = 70.2 Gy). Results: Fifty-nine patients were enrolled (LAPC, n = 29; RP, n = 30; ADT 4 months, n = 29; 24 months, n = 30; whites n = 29, African Americans [AA], n = 28). Baseline characteristics (median [range]) were: age 67 (45-86 years), PSA 5.9 (0.1-92.1 ng/mL), GS 8 (6-9). At escalating doses of paclitaxel, 99%, 98%, and 95% of doses were given with radiation and ADT, respectively, with dose modifications required primarily in RP patients. No acute Grade 4 toxicities occurred. Grade 3 toxicities were diarrhea 15%, urinary urgency/incontinence 10%, tenesmus 5%, and leukopenia 3%. Median follow-up was 75.3 months (95% CI: 66.8-82.3). Biochemical progression occurred in 24 (41%) patients and clinical progression in 11 (19%) patients. The 5- and 7-year OS rates were 83% and 67%. There were no differences in OS between RP and LAPC, 4- and 24-month ADT, white and AA patient categories. Conclusions: In addition to LAPC, to our knowledge, this is the first study to evaluate concurrent chemoradiation with ADT in high-risk RP patients. With a median follow-up of 75.3 months, this trial also represents the longest follow-up of patients treated with taxane-based chemotherapy with EBRT in high-risk prostate cancer. Concurrent ADT, radiation, and weekly paclitaxel at 40 mg/m 2/week in RP patients and 60 mg/m 2/week in LAPC patients is feasible and well-tolerated. Copyright © 2012 Elsevier Inc. Printed in the USA. All rights reserved.
Keywords: Concurrent chemoradiation; High-risk prostate cancer; Multimodality therapy; Post-prostatectomy radiation

A pilot phase II trial of all-trans retinoic acid (Vesanoid) and paclitaxel (Taxol) in patients with recurrent or metastatic breast cancer - Bryan, M.; Pulte, E.D.; Toomey, K.C.; Pliner, L.; Pavlick, A.C.; Saunders, T.; Wieder, R. (Investigational New Drugs, 2011)
Purpose: We investigated a combination therapy with weekly paclitaxel and all trans-retinoic acid (ATRA) for tolerability, response to treatment, time to progression and survival in previously treated patients with metastatic or recurrent breast cancer. Our rationale was based on preclinical studies demonstrating potentiation of the cytotoxic effects of taxanes and induction of differentiation by ATRA. Patients and methods: Seventeen patients with previously treated metastatic or recurrent breast cancer were enrolled to a regimen of all-trans retinoic acid (Vesanoid, tretinoin, Hoffman-La Roche, Inc.) 45 mg/m 2 PO daily for 4 days starting 2 days before a 1 h treatment with paclitaxel (Taxol, Bristol-Myers Squibb, Plainsboro, NJ) 80 mg/m 2 IV administered weekly for 3 weeks, repeated in 28 day cycles until disease progression or until no longer tolerated. Patients were evaluated for toxicity, response, time to progression and survival. Patients were primarily African American and Latino, representative of the population served by our Cancer Center. Results: The regimen was relatively well tolerated. There were nine grade 3 and one grade 4 toxic events. We administered 162 treatment cycles with a mean of 7.5 per patient (range 1-22, median 5). Three patients had a partial response (17.6%) and ten patients had stable disease (58.8%), with an overall clinical benefit of 76.4%. Median time to progression was 6.0 months (range 1-21, mean 7.7 months). Fourteen evaluable patients had a median survival of 16 months (range 1-68 months, mean 25.2 months). Conclusions: The data suggest this is a well tolerated regimen with modest response rates but with time to progression and survival rates similar to those reported for paclitaxel alone and relatively high rates of stable disease in this sample of patients. © Springer Science+Business Media, LLC 2010.
Keywords: All trans retinoic acid; Metastatic breast cancer; Potentiation; Taxol

I had already made up my mind: Patients and caregivers' perspectives on making the decision to participate in research at a us cancer referral center - Shannon-Dorcy, K.; Drevdahl, D.J. (Cancer Nursing, 2011)
Background: Hematopoietic cell transplants (HCTs) are associated with high morbidity and mortality, which complicate the decision-making process for people considering HCT clinical trials. There is a lack of research examining longitudinally how patients make clinical trial participation decisions in US cancer referral centers. Objective: A qualitative study was conducted to examine how patients and their family caregivers decide to participate in HCT research at a US cancer referral center. Methods: Semistructured interviews were conducted with 25 patients enrolled in early-stage phase 2 HCT research studies and with 20 family caregivers. Interviews were conducted before HCT and approximately days 80 and 365 after HCT. Results: Most patients (92%) and their caregivers (75%) decided to participate in research well before consent conferences at the cancer referral center. Patients' reasons for deciding to participate included having "no other option," seeking a cure, and following their home oncologists' recommendations. Conclusion: Currently, US researchers are primarily guided by Federal regulations that view the decision-making process as a cognitive one. Findings confirmed cognition was a part of consent; however, most patients made the decision to participate in high-risk clinical trials long before they had been apprised of the specific information about the study and before the consent conference. Implications for Practice: The high risk of death from the disease and/or the HCT underscored the emotional component of decision making and affirmed that researchers need to acknowledge this emotional component to meet the ethical imperative of providing "informed consent. © 2011 Lippincott Williams & Wilkins.
Keywords: Clinical trial (or clinicaltrial phase 2); Decision making; Ethics; Hematologic neoplasms; Hematopoietic stem cell; Informed consent; Qualitative research; transplant

Cancer trials versus the real world in the United States - Al-Refaie, W.B.; Vickers, S.M.; Zhong, W.; Parsons, H.; Rothenberger, D.; Habermann, E.B. (Annals of Surgery, 2011)
Background: Federal policies have been implemented to mitigate underenrollment in cancer trials in the United States. We sought to identify patterns and predictors of enrollment patterns to cancer trials in a contemporary era using a real world setting. STUDY DESIGN:: The 2001-2008 California Cancer Registry was used to determine patterns and predictors of enrollment in clinical trials for stage 0 to IV solid organ malignant tumors. Multivariate techniques were used to identify predictors of enrollment in cancer protocols, controlling for covariates. Results: Less than a percent (0.64%) of patients enrolled in clinical trials (1566 of 244,528). Black patients were less likely than whites to enroll in trials (0.48% vs 0.67%, P < 0.05). On multivariate analysis, older persons (>65 years), early stage cancer, and those with lung or gastrointestinal cancers were less likely to be enrolled in cancer trials. Results were consistent when evaluated among only nonbreast cancer protocols. Though approaching significance, black, underinsured, and uninsured patients showed trends toward underenrollment. Conclusion: In addition to profoundly low overall cancer trial accrual, vast underrepresentation by age, cancer stage, and site continue to exist. The generalizability of these trials to a real world perspective remains an open question. Physicians, payers, the National Cancer Institute, and other stakeholders need to develop broader cancer trials to benefit the millions of patients with cancer in the United States. © 2011 by Lippincott Williams & Wilkins.

Racial disparities in traumatic stress in prostate cancer patients: Secondary analysis of a National URCC CCOP Study of 317 men - Purnell, J.Q.; Palesh, O.G.; Heckler, C.E.; Adams, M.J.; Chin, N.; Mohile, S.; Peppone, L.J.; Atkins, J.N.; Moore, D.F.; Spiegel, D.; Messing, E.; Morrow, G.R. (Supportive Care in Cancer, 2011)
Introduction African American men have the highest rates of prostate cancer of any racial group, but very little is known about the psychological functioning of African American men in response to prostate cancer diagnosis and treatment. Purpose In this secondary analysis of a national trial testing a psychological intervention for prostate cancer patients, we report on the traumatic stress symptoms of African American and non-African American men. Methods This analysis includes 317 men (African American: n=30, 9%; non-African American: n=287, 91%) who were enrolled in the intervention trial, which included 12 weeks of group psychotherapy and 24 months of follow-up. Using mixed model analysis, total score on the Impact of Events Scale (IES) and its Intrusion and Avoidance subscales were examined to determine mean differences in traumatic stress across all time points (0, 3, 6, 12, 18, and 24 months). In an additional analysis, relevant psychosocial, demographic, and clinical variables were added to the model. Results Results showed significantly higher levels of traumatic stress for African American men compared to non-African American men in all models independently of the intervention arm, demographics, and relevant clinical variables. African Americans also had a consistently higher prevalence of clinically significant traumatic stress symptoms (defined as IES total score ≥27). These elevations remained across all time points over 24 months. Conclusions This is the first study to showa racial disparity in traumatic stress specifically as an aspect of overall psychological adjustment to prostate cancer. Recommendations are made for appropriate assessment, referral, and treatment of psychological distress in this vulnerable population. © 2011 Springer-Verlag.
Keywords: African American; Health disparities; Prostate cancer; PTSD; Traumatic stress

Racial differences in colorectal cancer incidence and mortality in the women's health initiative - Simon, M.S.; Thomson, C.A.; Pettijohn, E.; Kato, I.; Rodabough, R.J.; Lane, D.; Hubbell, F.A.; O'Sullivan, M.J.; Adams-Campbell, L.; Mouton, C.P.; Abrams, J.; Chlebowski, R.T. (Cancer Epidemiology Biomarkers and Prevention, 2011)
Background: Colorectal cancer (CRC) incidence and mortality rates are higher in African-Americans as compared with other racial/ethnic groups. The women's health initiative (WHI) study sample was used to determine whether differences in CRC risk factors explain racial/ethnic differences in incidence and mortality. Methods: The WHI is a longitudinal study of postmenopausal women recruited from 40 centers. Baseline questionnaires were used to collect sociodemographic and health status information. All CRC diagnoses were centrally adjudicated. Cox regression models were used to compute hazard ratios (HRs) and 95% confidence intervals (CIs) for invasive CRC by race/ethnicity. Results: The study sample included 131,481 (83.7%) White, 14,323 (9.1%) African-American, 6,362 (4.1%) Hispanic, 694 (0.4%) Native American and 4,148 (2.6%) Asian/Pacific Islanders. After a mean follow-up of 10.8 years (SD 2.9), CRC incidence was the highest in African-Americans (annualized rate = 0.14%), followed by Whites and Native Americans (0.12% each), Asian/Pacific Islanders (0.10%), and Hispanics (0.08%). After adjustment for age and trial assignment, Hispanics had a lower risk compared with Whites, HR 0.73 (95% CI: 0.54-0.97) (P = 0.03), and African-Americans had a marginally greater risk, HR 1.16 (95% CI: 0.99-1.34), P = 0.06. Multivariable adjustment attenuated the difference in incidence between African-Americans and Whites (HR 0.99, 95% CI: 0.82-1.20), while strengthening the lower HR for Hispanics (HR 0.68, 95% CI: 0.48-0.97). Conclusions: African-American/White differences in CRC risk are likely due to sociodemographic/cultural factors other than race. Impact: A number of modifiable exposures could be a focus for reducing CRC risk in African-Americans. ©2011 AACR.

Changes in Risk Perceptions in Relation to Self-Reported Colorectal Cancer Screening Among First-Degree Relatives of Colorectal Cancer Cases Enrolled in a Randomized Trial - Glenn, B.A.; Herrmann, A.K.; Crespi, C.M.; Mojica, C.M.; Chang, L.C.; Maxwell, A.E.; Bastani, R. (Health Psychology, 2011)
Objective: This secondary data analysis was conducted to evaluate the applicability of the Risk Reappraisal Hypothesis, which has been proposed to explain the influence of performing a health behavior on perceived risk. Data were collected in the context of a randomized trial, which found that an individually tailored, multicomponent intervention was successful in increasing colorectal cancer (CRC) screening among first-degree relatives of CRC cases. Method: The ethnically diverse study sample (N = 841; 29% Latino, 21% African American, 20% Asian) consisted of adult siblings and children (40-80 years) of CRC cases, identified through the California Cancer Registry. Data were collected at baseline and at 6- and 12-month follow-up. Changes in self-reported risk perception (perceived likelihood of developing CRC) were examined over the study period in relation to study condition and screening status. Results: Greater increases in perceived risk were observed among intervention versus control-group participants over the study period, but increases were limited to intervention participants who had not been screened. We also examined trajectories of perceived risk in relation to timing of screening receipt (e.g., before 6 months, 6-12 months, never). Continued upward shifts in risk were observed during the study period among intervention participants not screened during the study. In contrast, participants screened by 6 months displayed a reduction or leveling off in perceived risk between 6- and 12-month follow-up. Conclusion: Results provide support for the applicability of the Risk Reappraisal Hypothesis within a high-risk sample enrolled in a CRC screening promotion trial. Future research is needed to explore the impact of short-term risk reductions on future CRC screening behavior. © 2011 American Psychological Association.
Keywords: Cancer screening; Colorectal cancer; Health behavior; Perceived risk; Theory

Studying cancer in minorities: A look at the numbers - Olson, S.H.; Layne, T.M.; Simon, J.A.; Ludwig, E.; O'Reilly, E.; Allen, P.J.; Kurtz, R.C. (Cancer, 2011)
BACKGROUND: Inclusion of minorities is an important but challenging aspect of epidemiologic studies in the United States. One aspect of this challenge that has received little attention is the actual number of minorities with specific cancers. The authors aimed to understand how population characteristics affect the numbers of minority cancer cases in Surveillance, Epidemiology, and End Results (SEER) regions. METHODS: By using SEER data, the authors identified 6 cancers with higher incidence rates in racial and ethnic minorities and reviewed the annual number of cases of those cancers in SEER areas where there are large numbers of blacks, Hispanics, and Asians. The authors examined the age characteristics of the populations in SEER areas using data from the US Census. RESULTS: Although there are substantial numbers of cases for the most common cancers with higher incidence in blacks, their numbers are quite small for other cancers, <150 cases, and in many areas, <100 per year. Few registries have substantial numbers of Hispanics or Asians. As expected, the proportion of minority populations is lower in older age groups, whereas the proportion of non-Hispanic whites is larger. CONCLUSIONS: Because of the sharp decline in minority populations associated with age and the high age-specific incidence rates of most cancers, the actual number of minority cases is quite small for several cancers. Thus, the inclusion of minority groups in studies of any but the most common cancers presents a challenge. Copyright © 2011 American Cancer Society.
Keywords: cancer; epidemiology; minorities; minority recruitment; population characteristics

A pilot phase II trial of magnesium supplements to reduce menopausal hot flashes in breast cancer patients - Park, H.; Parker, G.L.; Boardman, C.H.; Morris, M.M.; Smith, T.J. (Supportive Care in Cancer, 2011)
Background We tested if magnesium would diminish bothersome hot flashes in breast cancer patients. Methods Breast cancer patients with at least 14 hot flashes a week received magnesium oxide 400 mg for 4 weeks, escalating to 800 mg if needed. Hot flash score (frequency× severity) at baseline was compared to the end of treatment. Results Of 29 who enrolled, 25 women completed treatment. The average age was 53.5 years; six African American, the rest Caucasian; eight were on tamoxifen, nine were on aromatase inhibitors, and 14 were on antidepressants. Seventeen patients escalated the magnesium dose. Hot flash frequency/week was reduced from 52.2 (standard error (SE), 13.7) to 27.7 (SE, 5.7), a 41.4% reduction, p=0.02, two-sided paired t test. Hot flash score was reduced from 109.8 (SE, 40.9) to 47.8 (SE, 13.8), a 50.4% reduction, p=0.04. Of 25 patients, 14 (56%) had a >50% reduction in hot flash score, and 19 (76%) had a >25% reduction. Fatigue, sweating, and distress were all significantly reduced. Side effects were minor: two women stopped the drug including one each with headache and nausea, and two women had grade 1 diarrhea. Compliance was excellent, and many patients continued treatment after the trial. Conclusions Oral magnesium appears to have helped more than half of the patients and was well tolerated. Side effects and cost ($0.02/tablet) were minimal. A randomized placebo-controlled trial is planned. © 2011 Springer-Verlag.
Keywords: Breast cancer; Drug treatment; Hot flashes; Menopause; Survivorship

Effectiveness of a web-based colorectal cancer screening patient decision aid: A randomized controlled trial in a mixed-literacy population - Miller Jr., D.P.; Spangler, J.G.; Case, L.D.; Goff Jr., D.C.; Singh, S.; Pignone, M.P. (American Journal of Preventive Medicine, 2011)
Background: Colorectal cancer (CRC) screening reduces mortality yet remains underutilized. Low health literacy may contribute to this underutilization by interfering with patients' ability to understand and receive preventive health services. Purpose: To determine if a web-based multimedia CRC screening patient decision aid, developed for a mixed-literacy audience, could increase CRC screening. Design: RCT. Patients aged 5074 years and overdue for CRC screening were randomized to the web-based decision aid or a control program seen immediately before a scheduled primary care appointment. Setting/participants: A large community-based, university-affiliated internal medicine practice serving a socioeconomically disadvantaged population. Main outcome measures: Patients completed surveys to determine their ability to state a screening test preference and their readiness to receive screening. Charts were abstracted by masked observers to determine if screening tests were ordered and completed. Results: Between November 2007 and September 2008, a total of 264 patients enrolled in the study. Data collection was completed in 2009, and data analysis was completed in 2010. A majority of participants (mean age=57.8 years) were female (67%), African-American (74%), had annual household incomes of <$20,000 (76%), and had limited health literacy (56%). When compared to control participants, more decision-aid participants had a CRC screening preference (84% vs 55%, p<0.0001) and an increase in readiness to receive screening (52% vs 20%, p=0.0001). More decision-aid participants had CRC screening tests ordered (30% vs 21%) and completed (19% vs 14%), but no statistically significant differences were seen (AOR=1.6, 95% CI=0.97, 2.8, and AOR=1.7, 95% CI=0.88, 3.2, respectively). Similar results were found across literacy levels. Conclusions: The web-based decision aid increased patients' ability to form a test preference and their intent to receive screening, regardless of literacy level. Further study should examine ways the decision aid can be combined with additional system changes to increase CRC screening. © 2011 American Journal of Preventive Medicine.

Colorectal cancer screening among ethnically diverse, low-income patients: A randomized controlled trial - Lasser, K.E.; Murillo, J.; Lisboa, S.; Casimir, A.N.; Shah, L.V.; Emmons, K.M.; Fletcher, R.H.; Ayanian, J.Z. (Archives of Internal Medicine, 2011)
Background: Patient navigators may increase colorectal cancer (CRC) screening rates among adults in underserved communities, but prior randomized trials have been small or conducted at single sites and have not included substantial numbers of Haitian Creole-speaking or Portuguese- speaking patients. Methods: We identified 465 primary care patients from 4 community health centers and 2 public hospital- based clinics who were not up-to-date with CRC screening and spoke English, Haitian Creole, Portuguese, or Spanish as their primary language. We enrolled participants from September 1, 2008, through March 31, 2009, and followed them up for 1 year after enrollment. We randomly allocated patients to receive a patient navigation- based intervention or usual care. Intervention patients received an introductory letter from their primary care provider with educational material, followed by telephone calls from a language-concordant navigator. The navigators offered patients the option of being screened by fecal occult blood testing or colonoscopy. The primary outcome was completion of any CRC screening within 1 year. Secondary outcomes included the proportions of patients screened by colonoscopy who had adenomas or cancer detected. Results: During a 1-year period, intervention patients were more likely to undergo CRC screening than control patients (33.6% vs 20.0%; P<.001), to be screened by colonoscopy (26.4% vs 13.0%; P<.001), and to have adenomas detected (8.1% vs 3.9%; P=.06). In prespecified subgroup analyses, the navigator intervention was particularly beneficial for patients whose primary language was other than English (39.8% vs 18.6%; P<.001) and black patients (39.7% vs 16.7%; P=.004). Conclusions: Patient navigation increased completion of CRC screening among ethnically diverse patients. Targeting patient navigation to black and non-Englishspeaking patients may be a useful approach to reducing disparities in CRC screening. © 2011 American Medical Association.

Recruitment and early retention of women with advanced breast cancer in a complementary and alternative medicine trial - Wyatt, G.K.; Sikorskii, A.; Siddiqi, A.-E.-A.; Tamkus, D. (Evidence-based Complementary and Alternative Medicine, 2011)
More than 80 of women with breast cancer are now reported to be using complementary and alternative medicine (CAM) therapies during conventional treatment. A randomized clinical trial (RCT) of reflexology with late stage breast cancer patients serves as the data source for this article. The purposes were to investigate: (i) reasons for refusal to participate in a RCT of reflexology; (ii) the differences between those who completed the baseline interview and those who dropped out before baseline; and (iii) the utility of the Palliative Prognostic Score (PPS) as a prognostic screening tool in minimizing early attrition (before baseline) from the trial. Eligible women (N = 400) approached at 12 cancer centers in the Midwest had advanced breast cancer, were on chemotherapy or hormonal therapy, and had a PPS of 11 or less. Comparisons of those who dropped out early (N = 33) to those who stayed in the trial (N = 240) were carried out using Wilcoxon rank, t-, chi-squared and Fisher's exact tests. The reasons of being too sick or overwhelmed were given by less than 12 of the women who refused to participate. There was a higher early dropout rate among black women compared to other (primarily white) women (P =.01). Cancer recurrence and metastasis, age, and the PPS were not predictive of early retention of women. Specialized techniques may be needed to ensure black women remain in the trial once consented. Women with advanced disease were likely to enter and remain in the trial despite deterioration in health. Copyright © 2011 Alla Sikorskii et al.

Reproductive history and oral contraceptive use in relation to risk of triple-negative breast cancer - Phipps, A.I.; Chlebowski, R.T.; Prentice, R.; McTiernan, A.; Wactawski-Wende, J.; Kuller, L.H.; Adams-Campbell, L.L.; Lane, D.; Stefanick, M.L.; Vitolins, M.; Kabat, G.C.; Rohan, T.E.; et al. (Journal of the National Cancer Institute, 2011)
Background Triple-negative (ie, estrogen receptor [ER], progesterone receptor, and HER2 negative) breast cancer occurs disproportionately among African American women compared with white women and is associated with a worse prognosis than ER-positive (ER+) breast cancer. Hormonally mediated risk factors may be differentially related to risk of triple-negative and ER+ breast cancers. Methods Using data from 155723 women enrolled in the Women's Health Initiative, we assessed associations between reproductive and menstrual history, breastfeeding, oral contraceptive use, and subtype-specific breast cancer risk. We used Cox regression to evaluate associations with triple-negative (N = 307) and ER+ (N = 2610) breast cancers and used partial likelihood methods to test for differences in subtype-specific hazard ratios (HRs). Results Reproductive history was differentially associated with risk of triple-negative and ER+ breast cancers. Nulliparity was associated with decreased risk of triple-negative breast cancer (HR = 0.61, 95% confidence interval [CI] = 0.37 to 0.97) but increased risk of ER+ breast cancer (HR = 1.35, 95% CI = 1.20 to 1.52). Age-adjusted absolute rates of triple-negative breast cancer were 2.71 and 1.54 per 10000 person-years in parous and nulliparous women, respectively; by comparison, rates of ER+ breast cancer were 21.10 and 28.16 per 10000 person-years in the same two groups. Among parous women, the number of births was positively associated with risk of triple-negative disease (HR for three births or more vs one birth = 1.46, 95% CI = 0.82 to 2.63) and inversely associated with risk of ER+ disease (HR = 0.88, 95% CI = 0.74 to 1.04). Ages at menarche and menopause were modestly associated with risk of ER+ but not triple-negative breast cancer; breastfeeding and oral contraceptive use were not associated with either subtype. Conclusion The association between parity and breast cancer risk differs appreciably for ER+ and triple-negative breast cancers. These findings require further confirmation because the biological mechanisms underlying these differences are uncertain. © 2011 The Author. Published by Oxford University Press. All rights reserved.

Engaging African American breast cancer survivors in an intervention trial: Culture, responsiveness and community - Germino, B.B.; Mishel, M.H.; Alexander, G.R.; Jenerette, C.; Blyler, D.; Baker, C.; Vines, A.I.; Green, M.; Long, D.G. (Journal of Cancer Survivorship, 2011)
Introduction: Younger breast cancer survivors often lead extremely busy lives with multiple demands and responsibilities, making them difficult to recruit into clinical trials. African American women are even more difficult to recruit because of additional historical and cultural barriers. In a randomized clinical trial of an intervention, we successfully used culturally informed, population-specific recruitment and retention strategies to engage younger African-American breast cancer survivors. Methods: Caucasian and African American breast cancer survivors were recruited from multiple communities and sites. A variety of planned recruitment and retention strategies addressed cultural and population-specific barriers and were guided by three key principals: increasing familiarity with the study in the communities of interest; increasing the availability and accessibility of study information and study participation; and using cultural brokers. Results: Accrual of younger African-American breast cancer survivors increased by 373% in 11 months. The steepest rise in the numbers of African-American women recruited came when all strategies were in place and operating simultaneously. Retention rates were 87% for both Caucasian and African American women. Discusssion/Conclusions: To successfully recruit busy, younger African American cancer survivors, it is important to use a multifaceted approach, addressing cultural and racial/ethnic barriers to research participation; bridging gaps across cultures and communities; including the role of faith and beliefs in considering research participation; recognizing the demands of different life stages and economic situations and the place of research in the larger picture of peoples' lives. Designs for recruitment and retention need to be broadly conceptualized and specifically applied. Implications for Cancer Survivors: For busy cancer survivors, willingness to participate in and complete research participation is enhanced by strategies that address barriers but also acknowledge the many demands on their time by making research familiar, available, accessible and credible. © 2010 Springer Science+Business Media, LLC.
Keywords: Culturally informed recruitment and retention strategies; Minority research participation; Younger breast cancer survivors

Cancer screening behaviors of african american women enrolled in a community-based cancer prevention trial - Reiter, P.L.; Linnan, L.A. (Journal of Women's Health, 2011)
Background: African American women have increased mortality rates for cervical, breast, and colorectal cancers, yet not all receive the recommended screening tests for these cancers. We characterized the cancer screening behaviors of African American women enrolled in a community-based cancer prevention trial. Methods: We examined cross-sectional data from 1123 African American customers aged ≥18 years from 37 beauty salons in North Carolina who completed the North Carolina BEAUTY and Health Project baseline survey. Mixed logistic regression models were used to identify correlates of receiving cervical, breast, and colorectal cancer screening tests within recommended screening guidelines. Results: Overall, 94% (1026 of 1089) of women aged ≥18 years reported receiving a Pap smear test within the last 3 years, 70% (298 of 425) of women aged ≥40 years reported receiving a mammography within the last year, and 64% (116 of 180) of women aged ≥50 years were considered to be within recommended screening guidelines for colorectal cancer. Age was correlated with recent Pap smear testing and mammography. Women who reported receiving a recent Pap smear test were more likely to report a mammogram in the last year, and women with a recent mammogram were more likely to be within recommended screening guidelines for colorectal cancer. Many women reported multiple barriers to getting recommended cancer screening tests. Conclusions: Almost all women reported receiving a Pap smear test within the last 3 years. Future interventions should focus on increasing breast and colorectal cancer screening among African American women. © Copyright 2011, Mary Ann Liebert, Inc.

A review of African American-white differences in risk factors for cancer: Prostate cancer - Mordukhovich, I.; Reiter, P.L.; Backes, D.M.; Family, L.; McCullough, L.E.; O'Brien, K.M.; Razzaghi, H.; Olshan, A.F. (Cancer Causes and Control, 2011)
Objective African American men have higher prostate cancer incidence rates than White men, for reasons not completely understood. This review summarizes the existing literature of race-specific associations between risk factors and prostate cancer in order to examine whether associations differ. Methods We reviewed epidemiologic studies published between January 1970 and December 2008 that reported race-specific effect estimates. We focused mainly on modifiable risk factors related to lifestyle and health. A total of 37 articles from 21 study populations met our inclusion criteria. Results We found no evidence of racial differences in associations between prostate cancer and alcohol intake, tobacco use, and family history of prostate cancer. Research suggests that a modest positive association may exist between height and prostate cancer risk (all prostate cancer and advanced prostate cancer) among Whites only. No clear patterns were observed for associations with physical activity, weight/body mass index, dietary factors, occupational history, sexual behavior, sexually transmissible infections, and other health conditions. Discussion Our results suggest few differences in prostate cancer risk factors exist between racial groups and underscore areas where additional research is needed. Future studies should enroll higher numbers of African American participants and report results for advanced prostate cancer. © Springer Science+Business Media B.V. 2010.
Keywords: African American; Epidemiology; Prostate cancer; Race; Review

A pilot trial of decision aids to give truthful prognostic and treatment information to chemotherapy patients with advanced cancer - Smith, T.J.; Dow, L.A.; Virago, E.A.; Khatcheressian, J.; Matsuyama, R.; Lyckholm, L.J. (Journal of Supportive Oncology, 2011)
Most cancer patients do not have an explicit discussion about prognosis and treatment despite documented adverse outcomes. Few decision aids have been developed to assist the difficult discussions of palliative management. We developed decision aids for people with advanced incurable breast, colorectal, lung, and hormone-refractory prostate cancers facing first-, second-, third-, and fourth-line chemotherapy. We recruited patients from our urban oncology clinic after gaining the permission of their treating oncologist. We measured knowledge of curability and treatment benefit before and after the intervention. Twenty-six of 27 (96%) patients completed the aids, with a mean age of 63, 56% female, 56% married, 56% African American, and 67% with a high school education or more. Most patients (14/27, 52%) thought a person with their advanced cancer could be cured, which was reduced (to 8/26, 31%, P = 0.15) after the decision aid. Nearly all overestimated the effect of palliative chemotherapy. No distress was noted, and hope did not change. The majority (20/27, 74%) found the information helpful to them, and almost all (25/27, 93%) wanted to share the information with their family and physicians. It is possible to give incurable patients their prognosis, treatment options, and options for improving end-of-life care without causing distress or lack of hope. Almost all find the information helpful and want to share it with doctors and family. Research is needed to test the findings in a larger sample and measure the outcomes of truthful information on quality of life, quality of care, and costs. © 2011 Elsevier Inc.

A lay patient navigation training curriculum targeting disparities in cancer clinical trials. - Bryant, D.C.; Williamson, D.; Cartmell, K.; Jefferson, M. (Journal of National Black Nurses' Association : JNBNA, 2011)
African-Americans experience a disproportionate share of thoracic cancer burden compared to Whites. Low socioeconomic status (SES) and race are factors in low clinical trial enrollment, accounting for the disparities between African-Americans and Whites. Less than 3% of newly diagnosed cancer patients enroll in clinical trials, and of that number, only 10% represent ethnic minorities. The value of clinical trials research is not generalizable without sufficient representation by ethnic minorities. Patient navigation, an intervention designed to ensure timely and efficient access to healthcare, may improve clinical trial enrollment among African-Americans in lung and esophageal trials by influencing a patient's perception of clinical trials. The lack of navigation programs and training may negatively influence standardization of navigation techniques. The purpose of this project was to deliver and evaluate an evidence-based navigation-training curriculum for "lay" navigators. The primary outcomes measured were confidence in the role as navigator, understanding a navigator's role, and knowledge and perception of clinical trials. The results revealed overall confidence in the role as lay navigators increased from pre-to-post test. Lessons learned included the need for preparatory classes to build the navigator's confidence, and additional training components in death and dying. A larger study is warranted to confirm the findings.

Differential association of cytochrome p450 3a4 genotypes with onsets of breast tumors in african american versus caucasian patients - McDaniel, D.O.; Thurber, T.; Lewis-Traylor, A.; Berry, C.; Barber, W.H.; Zhou, X.; Bigler, S.; Vance, R. (Journal of Investigative Medicine, 2011)
Introduction: Malignant breast tumors are often hormone-dependent, and to this end, both estrogen and progesterone receptors are good prognostic markers for evaluation of the outcomes after therapy. In addition, HER-2/neu, whose expression is increasingly being associated with poor prognosis of breast cancer, has predictive potential after immunotherapy. Cytochrome P450 3A4 is highly involved in the metabolism of steroids. Thus, we investigated the impact of CYP 3A4 gene variants in association with clinical outcomes in African American (AFAM) versus Caucasian (CAU) patients with breast cancer diagnosis. Methods: Patients who had undergone biopsy procedures for diagnosis or for partial or radical mastectomy were recruited. The CYP 3A4 genotypes (A or G) were detected using polymerase chain reaction amplification and primers designed for a single nucleotide polymorphism. The messenger RNA (mRNA) transcriptswere screened by reverse transcription- polymerase chain reaction. Clinical data including tumor staging, pathology grades, and family history were evaluated. Results: Frequency of the CYP 3A4-G (mutated variant) was significantly increased in AFAMpatients as compared with controls (P < 0.001). No statistically significant difference was observed between the genotypes comparing the benign versus ductal carcinomas in situ (DCIS) or infiltrating ductal carcinomas (IDCAs). In AFAM patients, GG alleles were increased in IDCA with stage III tumors, and in CAU patients, the AA alleles were increased with stage III tumors. The mRNA expression was reduced in patients with IDCA versus DCIS or benign tumors (benign vs IDCA, P < 0.0009; DCIS vs IDCA, P G 0.005), as well in HER-2/ neuYpositive tumors versus samples negative for receptors (P < 0.0024). Conclusions: Genotype association was affected by race. Expression levels of total CYP 3A4 mRNA were inversely correlated with clinical diagnosis. This may suggest mRNA testing as an additional tool that accelerates improvement in the diagnosis of the onsets of breast cancer. Copyright © 2011 by The American Federation for Medical Research.
Keywords: African Americans; Breast cancer; Caucasians; CYP 3A4 genotypes; Receptors

A multimodal intervention to promote mammography and colorectal cancer screening in a safety-net practice - Fiscella, K.; Humiston, S.; Hendren, S.; Winters, P.; Idris, A.; Li, S.X.L.; Ford, P.; Specht, R.; Marcus, S. (Journal of the National Medical Association, 2011)
Background: There are limited data regarding interventions designed to improve cancer screening rates in safety-net practices with "real world" patients. Objective: To examine the impact of a multimodal intervention on mammography and colorectal cancer (CRC) screening rates in a safety-net practice caring for under-served patients. Methods: At an inner-city family medicine practice, all patients past due for mammography or CRC screening were assigned to receive or not receive a screening promotion intervention based on their medical record number. The 12-month intervention included outreach to patients (tailored letters, automated and personal phone calls) and point-of-care patient and clinician prompts. The trial was registered at clinicaltrials.gov, NCT00818857. Results: We enrolled 469 participants aged 40 to 74 years, including 28% African Americans, 5% Latinos, 25% with Medicaid, and 10% without any form of insurance. Participants in the intervention group showed statistically significantly higher rates of cancer screening; rates were 41% vs 16.8% for mammography and 28.8% vs 10% for CRC screening. These findings were confirmed in multivariable analysis. Similar relative improvements in screening were seen across race, ethnicity, socioeconomic status, and insurance groups. Discussion: A multimodal intervention shows promise for improving rates of mammography and colorectal cancer screening within a safety-net practice. Further study will identify the most cost-effective components of the intervention.
Keywords: Cancer; Colorectal; Urban population

Community-based participatory approach to reduce breast cancer disparities in south Dallas. - Cardarelli, K.; Jackson, R.; Martin, M.; Linnear, K.; Lopez, R.; Senteio, C.; Weaver, P.; Hill, A.; Banda, J.; Epperson-Brown, M.; Morrison, J.; Parrish, D.; et al. (Progress in community health partnerships : research, education, and action, 2011)
South Dallas experiences significant disparities in breast cancer mortality, with a high proportion of stage III and IV diagnoses. To address these rates, the Dallas Cancer Disparities Community Research Coalition created an educational intervention to promote breast health and early detection efforts. The goals of the intervention were to increase (a) knowledge regarding the chief contributing factors for breast cancer, (b) awareness of the importance of screening for early detection, and (c) the proportion of women who have engaged in appropriate breast cancer screening practices. Eligibility criteria for this nonrandomized, controlled trial included women age 40 and older, English-speaking, and having no personal history of cancer. Control participants received written breast health educational materials. Intervention participants attended 8 weekly sessions that included interactive educational materials, cooking demonstrations, and discussions emphasizing primary and secondary breast cancer prevention. All study participants completed a 1-hour survey at baseline and 4 months later. There were 59 women were enrolled in the intervention and 60 in the control group. At follow-up, after controlling for baseline mammography status, women in the intervention group were 10.4 times more likely (95% confidence interval [CI], 2.9-36.4) to have received a screening mammogram in the last year compared with the control group. Intervention participants demonstrated statistically significantly higher rates of breast self-examination (odds ratio [OR], 3.0; 95% CI, 1.0-8.6) and breast cancer knowledge (p=.003). Lessons learned from this community-based participatory research (CBPR) study can be used to create sustainable cancer disparity reduction models that can be replicated in similar communities.

Magnifying gastroscopy using a soft black hood for difficult colonoscopy - Nakamura, H.; Fu, K.; Yamamura, A. (Surgical Endoscopy, 2011)
Background Various methods are reported as aids to cecal intubation for cases in which colonoscopy is difficult. This study aimed to investigate prospectively whether a gastroscope with magnification function, narrow-band imaging (NBI), and a soft black hood can aid insertion in cases of difficult colonoscopy and facilitate both accurate diagnosis and safe treatment. Methods This prospective study recruited 177 patients. All were examined with a magnifying gastroscope. A commercially available soft black hood was attached to the gastroscope during insertion and magnification. Difficult colonoscopy was anticipated before colonoscopy in cases of patients with at least one of the following factors: low BMI (<20 kg/m2), adhesion due to previous surgery, or previous colonoscopy that could not reach to the cecum. The success rate and duration of cecal intubation then were assessed. All detected lesions were evaluated by magnifying NBI and then classified as non-neoplastic or neoplastic for endoscopic diagnosis. Subsequently, all the lesions were removed and examined histologically for comparison. Results The overall success rate of cecal intubation was 100% (177/177), and the mean time taken to reach the cecum was 5.9 min. A total of 156 lesions were detected endoscopically, and the overall diagnostic accuracy of NBI with magnification was 98.7%. No associated complications occurred. Conclusion Magnifying gastroscopy using a soft black hood and NBI is useful for cecal intubation in cases wherein colonoscopy is difficult, facilitating accurate diagnosis and safe treatment. © 2011 Springer Science+Business Media, LLC.
Keywords: Cap-or hood-assisted colonoscopy; Cecal intubation; Difficult colonoscopy; Magnifying gastroscopy; Narrow-band imaging

Comparing narrative and informational videos to increase mammography in low-income African American women - Kreuter, M.W.; Holmes, K.; Alcaraz, K.; Kalesan, B.; Rath, S.; Richert, M.; McQueen, A.; Caito, N.; Robinson, L.; Clark, E.M. (Patient Education and Counseling, 2010)
Objective: Compare effects of narrative and informational videos on use of mammography, cancer-related beliefs, recall of core content and a range of reactions to the videos.Method: African American women (n=489) ages 40 and older were recruited from low-income neighborhoods in St. Louis, MO and randomly assigned to watch a narrative video comprised of stories from African American breast cancer survivors (Living Proof) or a content-equivalent informational video using a more expository and didactic approach (Facts for Life). Effects were measured immediately post-exposure and at 3- and 6-month follow-up.Results: The narrative video was better liked, enhanced recall, reduced counterarguing, increased breast cancer discussions with family members and was perceived as more novel. Women who watched the narrative video also reported fewer barriers to mammography, more confidence that mammograms work, and were more likely to perceive cancer as an important problem affecting African Americans. Use of mammography at 6-month follow-up did not differ for the narrative vs. informational groups overall (49% vs. 40%, p=.20), but did among women with less than a high school education (65% vs. 32%, p<.01), and trended in the same direction for those who had no close friends or family with breast cancer (49% vs. 31%, p=.06) and those who were less trusting of traditional cancer information sources (48% vs. 30%, p=.06).Conclusions: Narrative forms of communication may increase the effectiveness of interventions to reduce cancer health disparities.Practice implications: Narratives appear to have particular value in certain population sub-groups; identifying these groups and matching them to specific communication approaches may increase effectiveness. © 2010 Elsevier Ireland Ltd.
Keywords: African American; Breast cancer; Cancer survivors; Health disparities; Mammography; Narrative

Fruit and vegetable intake in relation to risk of breast cancer in the black women's health study - Boggs, D.A.; Palmer, J.R.; Wise, L.A.; Spiegelman, D.; Stampfer, M.J.; Adams-Campbell, L.L.; Rosenberg, L. (American Journal of Epidemiology, 2010)
The authors prospectively examined the relation of fruit and vegetable intake to breast cancer risk among 51,928 women aged 21-69 years at enrollment in 1995 in the Black Women's Health Study. Dietary intake was assessed by using a validated food frequency questionnaire. Cox proportional hazards models were used to estimate incidence rate ratios and 95% confidence intervals, adjusted for breast cancer risk factors. During 12 years of follow-up, there were 1,268 incident cases of breast cancer. Total fruit, total vegetable, and total fruit and vegetable intakes were not significantly associated with overall risk of breast cancer. However, total vegetable consumption was associated with a decreased risk of estrogen receptor-negative/progesterone receptor-negative breast cancer (incidence rate ratio = 0.57, 95% confidence interval: 0.38, 0.85, for ≥2 servings/day relative to <4/week; Ptrend = 0.02). In addition, there was some evidence of inverse associations with breast cancer risk overall for cruciferous vegetable intake (Ptrend = 0.06) and for carrot intake (Ptrend = 0.02). Study findings suggest that frequent consumption of vegetables is inversely associated with risk of estrogen receptor-negative/progesterone receptor-negative breast cancer, and that specific vegetables may be associated with a decreased risk of breast cancer overall. © 2010 The Author.
Keywords: African Americans; Brassicaceae; breast neoplasms; carotenoids; fruit; risk; vegetables; women

Association between folate levels and CpG island hypermethylation in normal colorectal mucosa - Wallace, K.; Grau, M.V.; Levine, A.J.; Shen, L.; Hamdan, R.; Chen, X.; Gui, J.; Haile, R.W.; Barry, E.L.; Ahnen, D.; McKeown-Eyssen, G.; Baron, J.A.; et al. (Cancer Prevention Research, 2010)
Gene-specific promoter methylation of several genes occurs in aging normal tissues and may predispose to tumorigenesis. In the present study, we investigate the association of blood folate levels and dietary and lifestyle factors with CpG island (CGI) methylation in normal colorectal mucosa. Subjects were enrolled in a multicenter chemoprevention trial of aspirin or folic acid for the prevention of large bowel adenomas. We collected 1,000 biopsy specimens from 389 patients, 501 samples from the right colon and 499 from the rectum at the follow-up colonoscopy. We measured DNA methylation of estrogen receptor alpha (ERα) and secreted frizzled related protein-1 (SFRP1), using bisulfite pyrosequencing. We used generalized estimating equations regression analysis to examine the association between methylation and selected variables. For both ERα and SFRP1, percentage methylation was significantly higher in the rectum than in the right colon (P = 0.001). For each 10 years of age, we observed a 1.7% increase in methylation level for ERα and a 2.9% increase for SFRP1 (P < 0.0001). African Americans had a significantly lower level of ERα and SFRP1 methylation than Caucasians and Hispanics. Higher RBC folate levels were associated with higher levels of both ERα (P = 0.03) and SFRP1 methylation (P = 0.01). Our results suggest that CGI methylation in normal colorectal mucosa is related to advancing age, race, rectal location, and RBC folate levels. These data have important implications regarding the safety of supplementary folate administration in healthy adults, given the hypothesis that methylation in normal mucosa may predispose to colorectal neoplasia. ©2010 AACR.

Educational inequalities in quantity, duration and type of tobacco consumption among lung cancer patients in Asturias: Epidemiological analyses - Leader, A.; Fernández-Somoano, A.; López-Cima, M.F.; González-Arriaga, P.; Pascual, T.; Marrón, M.G.; Tardón, A. (Psicothema, 2010)
Socioeconomic inequalities cause different tobacco consumption patterns. The purpose of this study was to examine the relationship between educational level and smoking behaviour, including type of tobacco consumption, in lung cancer patients. To this end, epidemiological analyses of 801 lung cancer patients recruited for a case-control study in four public hospitals in Asturias, Spain, between October 2000 and April 2006 were carried out. Smoking behaviour and educational level data were obtained through personal interview. Analyses indicated that the probability of heavy smoking among low educational-level patients was approximately twice as high as for high educational-level patients (RRR>31.2packs/years = 2.04; CI 95%= 1.15-3.62; RRR>52packs/years= 2.14; CI 95%= 0.98-4.64). Low-educated patients were more than three times as likely to be long-time smokers (RRR>40years = 3.30; CI 95%= 1.43-7.62). The probability of smoking exclusively black tobacco was almost four times greater in low educational-level patients (RRRblack only= 3.72; CI 95%= 1.23-11.19). The results show that there are broad educational inequalities with regard to the quantity, duration and type of tobacco consumption among lung cancer patients in Northern Spain. © 2010 Psicothema.

Mechanistic and other relevant data (IARC Monographs on the Evaluation of Carcinogenic Risks to Humans, 2010)
In this section, the general principles of inhalation, deposition, clearance and retention of poorly soluble particles that have low toxicity are discussed. This information is also relevant to the monographs on titanium dioxide and talc in this volume.

Participation of older patients with prostate cancer in medicare eligible trials - Craig, B.M.; Gilbert, S.M.; Herndon, J.B.; Vogel, B.; Quinn, G.P. (Journal of Urology, 2010)
Purpose: On June 7, 2000 President Clinton issued an executive memorandum directing Medicare payment for routine patient care in qualifying clinical trials. We estimated the proportion of older patients with prostate cancer who were examined as part of a qualifying clinical trial, and the association between participation and patient characteristics. Materials and Methods: We performed an observational study using the Surveillance, Epidemiology and End Results Medicare database to determine participation in qualifying clinical trials in a sample of 37,216 men 66 years old or older who were enrolled in Medicare and diagnosed with prostate cancer between September 2000 and December 2002. Results: Within 3 years of diagnosis 211 men (0.567%) received routine patient care in a qualifying clinical trial. These participants were more likely to be younger than 70 years (OR 1.687, 95% CI 1.27-2.24) and less likely to be less educated and reside in low income, metropolitan neighborhoods. White men were more likely to participate in clinical trials than nonwhite men but this association was not statistically significant (OR 1.426, CI 0.97-2.09). Participation varied significantly by registry site (0% to 1.2%) but not by tumor grade or stage, or prostate specific antigen status. Conclusions: Few older patients with prostate cancer participated in qualifying trials between 2000 and 2002. Those who participated were not representative of the general population of older patients with prostate cancer. Greater efforts are required to expand trial enrollment and decrease disparities in research participation. © 2010 American Urological Association Education and Research, Inc.
Keywords: clinical trials as topic; health services accessibility; Medicare; prostate; prostatic neoplasms

Successful subject recruitment for a prostate cancer behavioral intervention trial - Heiney, S.P.; Arp Adams, S.; Drake, B.F.; Bryant, L.H.; Bridges, L.; Hebert, J.R. (Clinical Trials, 2010)
Background Inadequate participant recruitment, which may lead to unrepresentative study samples that threaten a studys validity, is often a major challenge in the conduct of research studies. Purpose The purpose of this article is to describe the development and implementation of a recruitment plan and evaluate the different recruitment strategies for a prostate cancer behavioral intervention trial. Methods Our recruitment plan was based on a framework (The Heiney-Adams Recruitment Model) that we developed, which combines relationship building and social marketing. We evaluated the success of our model using several different recruitment sources including: mailed letters, physician referral, and self-referral. Results Recruitment rates ranged from 67% for a support services department mailing to 100% for physician referral. While our original list of contacted patients was comprised of only 13% African American (AA) men, 22% of our recruited participants were AA. Limitations One of the strongest barriers to recruitment was strict patient eligibility. Another significant barrier was the lack of electronic records systems to allow for the identification of large numbers of potential participants. Conclusions In conclusion, our model incorporating social marketing and relationship building was quite successful in recruiting for a prostate cancer behavioral study, particularly AA participants. In developing strategies, future researchers should attend to issues of staffing, financial resources, physician support, and eligibility criteria in the light of study accrual. © The Author(s), 2010.

Factors associated with decisions to undergo surgery among patients with newly diagnosed early-stage lung cancer - Cykert, S.; Dilworth-Anderson, P.; Monroe, M.H.; Walker, P.; McGuire, F.R.; Corbie-Smith, G.; Edwards, L.J.; Bunton, A.J. (JAMA - Journal of the American Medical Association, 2010)
Context: Lung cancer is the leading cause of cancer death in the United States. Surgical resection for stage I or II non-small cell cancer remains the only reliable treatment for cure. Patients who do not undergo surgery have a median survival of less than 1 year. Despite the survival disadvantage, many patients with early-stage disease do not receive surgical care and rates are even lower for black patients. Objectives: To identify potentially modifiable factors regarding surgery in patients newly diagnosed with early-stage lung cancer and to explore why blacks undergo surgery less often than whites. Design, Setting, and Patients: Prospective cohort study with patients identified by pulmonary, oncology, thoracic surgery, and generalist practices in 5 communities through study referral or computerized tomography review protocol. A total of 437 patients with biopsy-proven or probable early-stage lung cancer were enrolled between December 2005 and December 2008. Before establishment of treatment plans, patients were administered a survey including questions about trust, patient-physician communication, attitudes toward cancer, and functional status. Information about comorbid illnesses was obtained through chart audits. Main Outcome Measure: Lung cancer surgery within 4 months of diagnosis. Results: A total of 386 patients met full eligibility criteria for lung resection surgery. The median age was 66 years (range, 26-90 years) and 29% of patients were black. The surgical rate was 66% for white patients (n=179/273) compared with 55% for black patients (n=62/113; P=.05). Negative perceptions of patient-physician communication manifested by a 5-point decrement on a 25-point communication scale (odds ratio [OR], 0.42; 95% confidence interval [CI], 0.32-0.74) and negative perception of 1-year prognosis postsurgery (OR, 0.27; 95% CI, 0.14-0.50; absolute risk, 34%) were associated with decisions against surgery. Surgical rates for blacks were particularly low when they had 2 or more comorbid illnesses (13% vs 62% for <2 comorbidities; OR, 0.04 [95% CI, 0.01-0.25]; absolute risk, 49%) and when blacks lacked a regular source of care (42% with no regular care vs 57% with regular care; OR, 0.20 [95% CI, 0.10-0.43]; absolute risk, 15%). Conclusions: A decision not to undergo surgery by patients with newly diagnosed lung cancer was independently associated with perceptions of communication and prognosis, older age, multiple comorbidities, and black race. Interventions to optimize surgery should consider these factors. ©2010 American Medical Association. All rights reserved.

Adapting a program to inform African American and hispanic American women about cancer clinical trials - Sadler, G.R.; Gonzalez, J.; Mumman, M.; Cullen, L.; LaHousse, S.F.; Malcarne, V.; Conde, V.; Riley, N. (Journal of Cancer Education, 2010)
The dearth of evidence-based clinical trial education programs may contribute to the underrepresentation of African American and Hispanic American women in cancer research studies. This study used focus group-derived data from80women distributed among eight Spanish- and Englishlanguage focus groups. These data guided the researchers' adaptation and refinement of the National Cancer Institute's various clinical trials education programs into a program that was specifically focused on meeting the information needs of minority women and addressing the barriers to study participation that they perceived. A "sisterhood" theme was adopted and woven throughout the presentation. © The Author(s) 2010.
Keywords: African American; Breast cancer; Clinical trials; Disparities; Focus groups; Hispanic American; Latinas; MeSH; Recruitment

Validation of the group-based medical mistrust scale among urban black men - Shelton, R.C.; Winkel, G.; Davis, S.N.; Roberts, N.; Valdimarsdottir, H.; Hall, S.J.; Thompson, H.S. (Journal of General Internal Medicine, 2010)
Background: Socioculturally relevant measures of medical mistrust are needed to better address health disparities, especially among Black men, a group with lower life expectancy and higher death rates compared to other race/gender groups. OBJECTIVES: The study aim was to investigate the psychometric properties of the Group-Based Medical Mistrust Scale (GBMMS) in a Black male sample. Design: Data were collected as part of a randomized controlled trial testing educational strategies to support Black men's decisions about prostate cancer screening. Participants: Participants included 201 Black men ages 40-75 years recruited in New York City during 2006-2007. MAIN MEASURES: The primary measures included: race-based medical mistrust, health care participation, avoidance of health care, perceived access to health care, health care satisfaction, racial identity, residential racial segregation, attitudes towards prostate cancer screening, and past prostate cancer screening behavior. KEY Results: An exploratory factor analysis suggested a three-factor structure. Confirmatory factor analysis supported the three-factor model. Internal consistency was high for the total GBMMS and the three sub-scales: Suspicion, Discrimination, and Lack of Support. Construct validity was supported by: significant positive correlations between GBMMS and avoidance of health care and racial identity as well as significant negative correlations with health care access, health care satisfaction, and attitudes about prostate cancer screening. ANOVA showed that the GBMMS was associated with greater residential racial segregation. Higher total GBMMS scores were associated with not visiting a physician in the last year and not having a regular physician. Conclusions: The present findings provide strong additional evidence that the GBMMS is a valid and reliable measure that may be used among urban Black men. © 2010 Society of General Internal Medicine.
Keywords: Black men; Medical mistrust; Psychometrics

Strategies for recruitment of healthy premenopausal women into the African American nutrition for life (A NULIFE) study - King, D.W.; Duello, T.M.; Miranda, P.Y.; Hodges, K.P.; Shelton, A.J.; Chukelu, P.; Jones, L.A. (Journal of Women's Health, 2010)
Background: Although African American women have an overall lower incidence of breast cancer, African American women <40 years of age are more likely than Caucasian women of all ages and postmenopausal African American women to be diagnosed with breast cancer and exhibit tumor characteristics associated with poorer survival. To begin to address this disparity, studies must be conducted to examine breast cancer preventive factors in this subpopulation of women. However, the strategies needed to recruit younger African American women have not been well defined. Methods: In this study, we assessed methods used for recruiting and retaining healthy premenopausal African American women into the African American Nutrition for Life (A NULIFE) Study. The number of women contacted, enrolled, and retained by each recruitment strategy and the efficiency of individual strategies were calculated. Results: Overall, recruitment through social networking was most effective in contacting large numbers of healthy premenopausal African American women. The worksite recruitment method was the most efficient recruitment strategy employed, with a ratio of 40%. The study participants (n=164) were more likely to be ≥35 years of age and have completed some college. Additionally, the interpersonal relationships recruitment approach proved most efficient (33%) in retaining participants who completed the yearlong study. Conclusions: The findings from this study add to the evolving research literature on minority recruitment strategies for research studies but specifically address effective recruitment of healthy young premenopausal African American women. The results demonstrate the need to use multiple recruitment strategies when recruiting this subgroup of African American women. © 2010, Mary Ann Liebert, Inc.

Evaluation of conceptual framework for recruitment of African American patients with Breast Cancer - Heiney, S.P.; Adams, S.A.; Wells, L.M.; Johnson, H. (Oncology Nursing Forum, 2010)
Purpose/Objectives: To describe the Heiney-Adams Recruitment Framework (H-ARF); to delineate a recruitment plan for a randomized, behavioral trial (RBT) based on H-ARF; and to provide evaluation data on its implementation. Data Sources: All data for this investigation originated from a recruitment database created for an RBT designed to test the effectiveness of a therapeutic group convened via teleconference for African American women with breast cancer. Data Synthesis: Major H-ARF concepts include social marketing and relationship building. The majority of social marketing strategies yielded 100% participant recruitment. Greater absolute numbers were recruited via Health Insurance Portability and Accountability Act waivers. Using H-ARF yielded a high recruitment rate (66%). Conclusions: Application of H-ARF led to successful recruitment in an RBT. The findings highlight three areas that researchers should consider when devising recruitment plans: absolute numbers versus recruitment rate, cost, and efficiency with institutional review board-approved access to protected health information. Implications for Nursing: H-ARF may be applied to any clinical or population-based research setting because it provides direction for researchers to develop a recruitment plan based on the target audience and cultural attributes that may hinder or help recruitment.

A trial of 3 interventions to promote colorectal cancer screening in African Americans - Blumenthal, D.S.; Smith, S.A.; Majett, C.D.; Alema-Mensah, E. (Cancer, 2010)
BACKGROUND: Colorectal cancer (CRC) is the second leading cause of cancer death in the United States. CRC incidence and mortality rates are higher among blacks than among whites, and screening rates are lower in blacks than in whites. For the current study, the authors tested 3 interventions that were intended to increase the rate of CRC screening among African Americans. METHODS: The following interventions were chosen to address evidence gaps in the Centers for Disease Control and Prevention's Guide to Community Preventive Services: one-on-one education, group education, and reducing out-of-pocket costs. Three hundred sixty-nine African-American men and women aged ≥50 years were enrolled in this randomized, controlled community intervention trial. The main outcome measures were postintervention increase in CRC knowledge and obtaining a screening test within 6 months. RESULTS: There was substantial attrition: Two hundred fifty-seven participants completed the intervention and were available for follow-up 3 months to 6 months later. Among completers, there were significant increases in knowledge in both educational cohorts but in neither of the other 2 cohorts. By the 6-month follow-up, 17.7% (11 of 62 participants) of the Control cohort reported having undergone screening compared with 33.9% (22 of 65 participants) of the Group Education cohort (P = .039). Screening rate increases in the other 2 cohorts were not statistically significant. CONCLUSIONS: The current results indicated that group education could increase CRC cancer screening rates among African Americans. The screening rate of <35% in a group of individuals who participated in an educational program through multiple sessions over a period of several weeks indicated that there still are barriers to overcome. © 2010 American Cancer Society.
Keywords: Colorectal cancer; Community-based participatory research; Health education; Health status disparities; Minority health; Screening

Impact of supplemental site grants to increase African American accrual for the selenium and vitamin e cancer prevention trial - Cook, E.D.; Arnold, K.B.; Hermos, J.A.; McCaskill-Stevens, W.; Moody-Thomas, S.; Probstfield, J.L.; Hamilton, S.J.; Campbell, R.D.; Anderson, K.B.; Minasian, L.M. (Clinical Trials, 2010)
Background African American accrual to prevention trials at rates representative of the disease burden experienced by this population requires additional resources and focused efforts. Purpose To describe the rationale, context, and criteria for selection of sites that received Minority Recruitment Enhancement Grants (MREGs) to increase African American recruitment to the Selenium and Vitamin E Cancer Prevention Trial (SELECT). To determine if African American accrual was higher among the 15 MREG sites when compared with similar nonawarded sites. Methods Changes in African American accrual at sites that received MREGs are compared with changes in a group of 15, frequency-matched, nonawarded sites using a quasi-experimental, post hoc analysis. Successful and unsuccessful recruitment strategies reported by the MREG sites are described. Results The increased number of African American participants accrued per month at MREG sites post-funding was higher than the change at comparison sites by a factor of 3.38 (p = 0.004, 95% CI: 1.51-7.57). An estimated 602 additional African American participants were recruited at MREG sites due to MREG funding, contributing to the overall 14.9% African American recruitment. Successful recruitment strategies most reported by MREG sites included increasing staff, transportation resources, recruiting through the media, mailings, and prostate cancer screening clinics during off-hours. Limitations Comparison sites were chosen retrospectively, not by randomization. Although comparison sites were selected to be similar to MREG sites with regard to potential confounding factors, it is possible that unknown factors could have biased results. Cost-effective analyses were not conducted. Conclusions MREG sites increased African American accrual in the post-funding period more than comparison sites, indicating MREG funding enhanced the sites' abilities to accrue African American participants. Targeted grants early in the accrual period may be a useful multi-site intervention to increase African American accrual for a prevention study where adequate African American representation is essential.

Evaluation of the Prostate Cancer Prevention Trial Risk calculator in a high-risk screening population - Kaplan, D.J.; Boorjian, S.A.; Ruth, K.; Egleston, B.L.; Chen, D.Y.T.; Viterbo, R.; Uzzo, R.G.; Buyyounouski, M.K.; Raysor, S.; Giri, V.N. (BJU International, 2010)
Objective: To evaluate the Prostate Cancer Prevention Trial (PCPT) risk calculator in a screening cohort of young, racially diverse, high-risk men with a low baseline prostate-specific antigen (PSA) level and enrolled in the Prostate Cancer Risk Assessment Program (PRAP). The PCPT calculator provides an assessment of prostate cancer risk based on age, PSA level, race, previous biopsy, and family history. Patients and Methods: Eligibility for PRAP includes men aged 35-69 years who are African-American, have a family history of prostate cancer, or have a known BRCA1/2 mutation. PCPT risk scores were determined for PRAP participants, and were compared to observed prostate cancer rates. Results: In all, 624 participants were evaluated, including 382 (61.2%) African-American men and 242 (38.7%) men with a family history of prostate cancer; the median (range) age was 49.0 (34.0-69.0) years and the median PSA level 0.9 (0.1-27.2) ng/mL. The PCPT risk score correlated with prostate cancer diagnosis, as the median baseline risk score in patients diagnosed with prostate cancer was 31.3%, vs 14.2% in patients not diagnosed with prostate cancer (P < 0.001). The PCPT calculator similarly stratified the risk of diagnosis of Gleason score ≥7 disease, as the median risk score was 36.2% in patients diagnosed with Gleason ≥7 prostate cancer vs 15.2% in all other participants (P < 0.001). Conclusion: The PCPT risk calculator score was found to stratify prostate cancer risk in a cohort of young, primarily African-American men with a low baseline PSA level. These Results: support further evaluation of this predictive tool for assessing the risk of prostate cancer in high-risk men. © 2009 BJU International.
Keywords: Biopsy; Calculator; Prediction; Prevention; Prostate cancer; Race

The role of race and trust in tissue/blood donation for genetic research - Bussey-Jones, J.; Garrett, J.; Henderson, G.; Moloney, M.; Blumenthal, C.; Corbie-Smith, G. (Genetics in Medicine, 2010)
BACKGROUND:: Public willingness to donate tissue samples is critical to genetic research. Prior work has linked minority status and mistrust with less willingness to provide specimens. Some have suggested recruitment of prior research participants to address these barriers. We present data from a genetic epidemiology study with a request for blood and/or saliva specimens to (1) measure willingness to donate tissue/blood samples, (2) identify demographic, trust, and other factors associated with willingness to donate samples, and (3) measure willingness to participate in future genetic research. METHODS:: We surveyed participants in the North Carolina Colorectal Cancer Study, which included biologic sample collection from consenting participants. Participants were later asked about sample provision; trust in researchers, and future research participation. RESULTS:: African Americans were less likely to give a blood sample, when compared with whites (21% vs. 13%, P < 0.05). After controlling for "trust," this difference was no longer statistically significant (17% vs. 13%, P = 0.27). Those who had given samples were more likely to express willingness to participate in future research. CONCLUSION:: Despite prior participation in a genetic epidemiology study, factors associated with provision of tissue samples reflected many previously identified demographic factors (race and trust). Interventions to improve and demonstrate the trustworthiness of the research team and recruitment of subjects with a record of sample donation might enhance future study participation. © 2010 Lippincott Williams & Wilkins.
Keywords: Biologic samples; Genetics; Research participation; Trust

A comparison of white and african american outcomes from a three-arm, randomized, phase III multicenter trial of advanced or metastatic non-small cell lung cancer - Obasaju, C.K.; Ansari, R.H.; Socinski, M.A.; Chen, R.; Monberg, M.J.; Catalano, R.B.; Marinucci, D.M.; Liles, D.K.; Ribeiro, M.-J.; Comis, R.L.; Treat, J. (Journal of Thoracic Oncology, 2010)
PURPOSE: To investigate the effect of race on the efficacy and safety of standard chemotherapy doublet regimens in African American patients, we conducted a subgroup analysis of a phase III randomized trial. PATIENTS AND METHODS: Chemonaïve patients with a performance status of 0 or 1 and stage IIIB or IV non-small cell lung cancer were randomized to arm A: gemcitabine 1000 mg/m on days 1 and 8 plus carboplatin area under the curve 5.5 on day 1; arm B: the same schedule of gemcitabine plus paclitaxel 200 mg/m on day 1; or arm C: paclitaxel 225 mg/m on day 1 plus carboplatin area under the curve 6.0 on day 1. Cycles were repeated every 21 days up to 6. A site selection tool identified institutions with potential to recruit a minority population. Outcome and toxicity data of white and African American patients were compared. RESULTS: Of 1135 total patients, 972 were white (85.6%) and 138 were African American (12.2%). Median survival was 8.3 months for white patients (95% confidence interval [CI]: 7.7-9.3) and 9.1 months for African American patients (95% CI: 8.2-11.1). Response rates were 29.1 and 29.0%, respectively. Rates of grade 3 or 4 toxicities were comparable. Among African Americans, median survival was 7.2 months (95% CI: 5.1-10.1) for gemcitabine-carboplatin (n = 47), 10.5 months (95% CI: 7.1-15.4) for gemcitabine-paclitaxel (n = 42), and 10.2 months (95% CI: 8.5-13.2) for paclitaxel-carboplatin (n = 49). CONCLUSION: Whites and African Americans had similar outcomes, although there was some variability in survival among African Americans across the three treatment groups. © 2010 by the International Association for the Study of Lung Cancer.
Keywords: Accrual; African American; Nonplatinum doublets; NSCLC; Phase III; Race

A phase II study of dasatinib in patients with chemosensitive relapsed small cell lung cancer (Cancer and Leukemia Group B 30602) - Miller, A.A.; Pang, H.; Hodgson, L.; Ramnath, N.; Otterson, G.A.; Kelley, M.J.; Kratzke, R.A.; Vokes, E.E. (Journal of Thoracic Oncology, 2010)
Introduction: SRC is an oncogene with an essential role in the invasiveness and metastasis of solid tumors including small cell lung cancer. Dasatinib is a potent inhibitor of SRC as well as other tyrosine kinases. The primary objective of this study was to determine the efficacy of second-line dasatinib in patients with chemosensitive (relapse or progression ≥90 days after completing first-line therapy) small cell lung cancer. Methods: Patients with measurable disease; performance status 0 to 1; no more than one prior platinum-based chemotherapy regimen; and adequate hematologic, hepatic, and renal function were eligible. Dasatinib was administered orally at 70 mg twice daily continuously (1 cycle = 21 days) until disease progression or unacceptable toxicity. Response was determined after every two cycles. Patients were followed until disease progression or death. The study was prospectively designed to simultaneously discriminate between complete plus partial response rates of 5% versus 20% and progression-free survival (PFS) rates at 6 weeks of 50% versus 70.7% in 53 evaluable patients with at least 92% power. The study was to be terminated early and declared negative if 1 or less objective response and 14 or fewer instances of PFS ≥6 weeks were observed among the initial 27 patients; however, patient accrual continued while the initial 27 patients were evaluated. Results: Between April 2007 and December 2008, 45 patients were enrolled, but one patient never received any protocol therapy and one patient was ineligible: male/female, 17/26; white/black/unknown, 40/2/1; median age, 64 years (range, 35-84 years); and performance status 0/1, 12/31. No objective response was recorded among the 43 eligible and treated patients. Among the initial 27 patients, only 13 instances of PFS ≥6 weeks were observed. With a median follow-up time of 7.1 months, median estimated overall survival and PFS times for the 43 eligible and treated patients were 17.0 and 5.9 weeks, respectively. Common reasons for removal of patients from protocol treatment were progressive disease (65%) and adverse events (26%). Toxicity was generally mild to moderate: grade 3 events of >5% frequency included fatigue and pleural and pericardial effusions; and no grade 4 or 5 events were encountered. Conclusions: Dasatinib did not reach our specified efficacy criteria in this clinical setting, and the study was terminated. Copyright © 2010 by the International Association.
Keywords: Dasatinib; Phase II; Small cell lung cancer

Sotrastaurin, a novel small molecule inhibiting protein kinase C: First clinical results in renal-transplant recipients - Budde, K.; Sommerer, C.; Becker, T.; Asderakis, A.; Pietruck, F.; Grinyo, J.M.; Rigotti, P.; Dantal, J.; Ng, J.; Barten, M.J.; Weber, M. (American Journal of Transplantation, 2010)
Sotrastaurin, a novel protein-kinase-C inhibitor, blocks early T-cell activation. In this 12-month, Phase II study, de novo renal-transplant patients were randomized to sotrastaurin (200 mg b.i.d.) + standard-exposure tacrolimus (SET) or reduced-exposure tacrolimus (RET) (SET: n = 76; RET: n = 66), or control (SET + mycophenolic acid [MPA, 720 mg b.i.d.]; n = 74). In both sotrastaurin groups, patients were converted from tacrolimus to MPA after Month 3, achieving calcineurin inhibitor-free immunosuppression. The primary endpoint was composite efficacy failure (treated biopsy-proven acute rejection, graft loss, death or loss to follow-up). The key secondary endpoint was glomerular filtration rate (GFR). Composite efficacy failure rates were: 4.1%, 5.4% and 1.5% at Month 3 (preconversion) and 7.8%, 44.8% and 34.1% at study end in the control, sotrastaurin + SET and sotrastaurin + RET groups, respectively; these results led to premature study discontinuation. Median GFR at Month 6 was: 57.0, 53.0 and 60.0 mL/min/1.73 m2, respectively. Study-drug discontinuations due to adverse events occurred in 16.2%, 18.4% and 12.1%, respectively. Leukopenia and neutropenia occurred more frequently preconversion in control versus sotrastaurin groups: 13.7%, 5.6%, and 4.6%; and 11.1%, 4.3% and 3.1%, respectively. The initial sotrastaurin + tacrolimus regimen was efficacious and well tolerated but the postconversion sotrastaurin + MPA regimen showed inadequate efficacy. Longer-term evaluation of sotrastaurin + tacrolimus is warranted. © 2010 The American Society of Transplantation and the American Society of Transplant Surgeons. AdverseEffects:16 (21.6%) patients had anemia, 5 (6.8%) leukocytosis, 10 (13.5%) leukopenia, 1 (1.4%) tachycardia, 12 (16.2%) abdominal pain, 12 (16.2%) abdominal pain upper, 19 (25.7%) constipation, 38 (51.4%) diarrhea, 10 (13.5%) dyspepsia, 10 (13.5%) flatulence, 19 (25.7%) nausea, 12 (16.2%) vomiting, 2 (2.7%) pain, 14 (18.9%) peripheral edema, 7 (9.5%) pyrexia, 3 (4.1%) Cytomegalovirus infection, 10 (13.5%) nasopharyngitis, 25 (33.8%) urinary tract infection, 10 (13.5%) wound complication, 9 (12.2%) blood creatinine increased, 11 (14.9%) diabetes mellitus, 6 (8.1%) hypercholesterolemia, 4 (5.4%) hyperlipidemia, 2 (2.7%) hypocalcemia, 29 (39.2%) hypomagnesemia, 16 (21.6%) hypophosphatemia, 3 (4.1%) arthralgia, 9 (12.2%) back pain, 7 (9.5%) headache, 18 (24.3%) tremor, 2 (2.7%) anxiety, 16 (21.6%) insomnia, 5 (6.8%) hematuria, 4 (5.4%) proteinuria, 8 (10.8%) acne, 26 (35.1%) bacterial infection, 9 (12.2%) Escherichia coli infection, 14 (18.9%) viral infection, 2 (2.7%) BK virus infection, 3 (4.1%) fungal infection, 37 (50%) unknown type of infection and 12 (16.4%) elevated alanine aminotransferase. AuthorsConclusions:In conclusion, the results of this study indicate that the use of sotrastaurin + MPA [mycophenolic acid] in a CNI-free regimen failed to maintain adequate efficacy for prevention of rejection in renal-transplant recipients. However, sotrastaurin warrants further investigation as a promising new drug offering potential benefits due to its distinct mechanism of action compared with CNIs. Studies are underway to determine the optimal regimen for sotrastaurin as part of multidrug immunosuppressive therapy. FreeText:TAC target levels were: Month 1: 8-15 ng/mL (SET) or 5-8 ng/mL (RET), Months 2-3: 6-12 ng/mL (SET) or 3-6 ng/mL (RET). SOT-treated recipients who met conversion criteria [absence of acute rejection, stable graft function (serum creatinine <2.5 mg/dL and no change >30% from nadir) and the absence of proteinuria >1 g/24 hours or major hematologic abnormalities (leukocytes<2500/lL, neutrophils<1500/lL, hemoglobin <10 g/dL)] at Month 3 were converted to a calcineurin inhibitor (CNI)-free regimen of SOT plus Myfortic over a 2-week period, introducing Myfortic 360 mg twice daily as add-on treatment a week before TAC was reduced to 50% and Myfortic was increased to full dose, with complete TAC discontinuation after another week. TAC target levels from Month 4 onwards were 5-10 ng/mL. All patients received two doses of basiliximab induction therapy. Steroids were started and tapered to ≥5 mg daily prednisone. The primary endpoint was composite efficacy failure [treated biopsy-proven acute rejection (BPAR), graft loss, death, or loss to follow-up]. Secondary endpoint was renal function [glomerular filtration rate (GFR)]. Safety measures: adverse events (AEs), infections, hematologic and biochemical laboratory parameters, vital signs and electrocardiograms (ECGs). Indications:Graft rejection prophylaxis in 169 patients who underwent renal transplantation. Coexisting diseases: 5 diabetes mellitus and 5 hypertension. Patients:216 de novo patients. SOT/SET group: n=76; 54 males and 12 females; age range 18-65 years (mean 43.7 years); 73 Caucasian, 1 black and 2 other; 9 received grafts from living unrelated donors, 19 from living related donors and 50 from cadaver donors; end-stage renal disease leading to transplant 16 glomerulonephritis, 15 polycystic disease, 2 diabetes mellitus, 9 hypertension, 5 unknown, 29 others; 53 were converted to Myfortic; 70 dropouts, 18 due to side effects. SOT/RET group: n=66, 48 males and 18 females, mean age 44.9 years, age range 18-67 years; 63 Caucasian, 1 black and 2 other; 8 received grafts from living unrelated donors; 14 from living related donors and 3 from cadaver donors; end-stage renal disease leading to transplant 14 glomerulonephritis, 13 polycystic disease, 1 diabetes mellitus, 2 hypertension, 4 unknown, 31 others; 43 were converted to Myfortic; 51 dropouts, 14 due to side effects. SET/Myfortic (control) group: n=74, 53 males and 21 females, mean age 44.6 years, age range 19-70 years; 71 Caucasian, 2 black and 1 other; 10 received grafts from living unrelated donors, 14 from living related donors and 50 from cadaver donors; end-stage renal disease leading to transplant 21 glomerulonephritis, 15 polycystic disease, 5 diabetes mellitus, 5 hypertension, 5 unknown, 23 others; 52 dropouts, 15 due to side effects. TypeofStudy:A 12-month, Phase II, multicenter, open-label, randomized study evaluating the efficacy of sotrastaurin (SOT) plus standard-exposure tacrolimus (SET) or reduced-exposure tacrolimus (RET), with subsequent conversion from tacrolimus (TAC) to Myfortic, or SET plus Myfortic in de novo renal transplant patients. NCT00403416. DosageDuration:In SET/Myfortic group: 720 mg bid (=1440 mg daily). During conversion: started at 360 mg bid (=720 mg daily) then increased to 720 mg bid (=1440 mg daily). Duration was 12 months. ComparativeDrug:Sotrastaurin was given at 200 mg bid (=400 mg daily). Duration was 12 months. Results:More patients in the SOT/SET and SOT/RET groups were ineligible for conversion at Month 3 vs. the SET/Myfortic group (14.5% and 23.6% vs. 8.3%). A similar number of patients in all groups were ineligible due to acute rejections; the most common reasons for ineligibility were 'poor/unstable renal function', and 'compelling reason prohibiting full-dose MPA or discontinuation of TAC'. In the control and SOT/SET groups, most patients were within the target trough range over Months 1, 2 and 3 (63% control, 74.2% SOT/SET and 77.4% SOT/RET). TAC levels achieved in the SOT/RET group were 30-40% lower vs. SOT/SET group; a substantial proportion of trough levels were above target at Months 1, 2 and 3 (45.3%, 55.4% and 46.4%, respectively). Mean daily Myfortic doses at Month 6 were 1233 mg, 1352 mg and 1331 mg for SET/Myfortic, SOT/SET and SOT/RET, respectively. During the 3-month preconversion period, both SOT/TAC regimens showed comparable efficacy to control. After conversion from TAC to Myfortic, both SOT/Myfortic regimens were inferior to the SET/Myfortic for the primary composite endpoint. Median GFR was not significantly different for the 3 groups at any time point. The most frequent AEs were gastrointestinal (GI) disorders and metabolism and nutrition disorders. The most frequent serious AEs (SAEs) were: kidney-transplant rejection (1.4% SET/Myfortic, 6.7% SOT/SET and 6.2% SOT/RET), cytomegalovirus infection (4.1%, 2.7% and 6.2%), gastroenteritis (1.4%, 4.0% and 6.2%), urinary tract infection (UTI; 4.1%, 2.7% and 6.2%), complications of the transplanted kidney (2.7%, 5.3% and 0%) and increased blood creatinine (1.4%, 12.0% and 10.8%). The highest incidence of SAEs was reported in the SOT/RET group, in part due to a higher incidence of infection SAEs. 3 (4.6%) patients in the SOT/RET group reported dysgeusia. Diarrhea was the most common GI AE and occurred more frequently in SET/Myfortic vs. SOT patients. Diarrhea caused the most drug dose reduction/interruption in the first 3 months (13.5% SET/Myfortic vs. 1.3%SOT/SET and 3.1% SOT/RET: 3.1%). The other GI AEs, vomiting, constipation and nausea were reported more frequently in the SOT groups. 1 patient in the SOT/RET group discontinued drug due to vomiting. Cardiac AEs were reported in 21.6%, 22.7% and 27.7% of the SET/Myfortic, SOT/SET and SOT/RET groups, respectively. Tachycardia occurred more frequently in both SOT groups vs. control. The incidence of new-onset diabetes mellitus (NODM) AEs in the control group was approximately twice that of the SOT groups. The incidence of hypertension and dyslipidemia AEs was similar between the groups. Prior to conversion from TAC to Myfortic at Month 3, the incidence of leukopenia and neutropenia was higher in the control compared vs. the SOT/SET and SOT/RET groups while the incidence of leukocytosis was lower in the control vs. the SOT groups up to Month 3. Over the study period the incidence of neutropenia, leukopenia and elevated alanine aminotransferase (ALT) occurred more frequently in the SET/Myfortic vs. the SOT/SET and SOT/RET groups. Infections considered to be serious occurred more frequently in the SOT/RET group compared with the SOT/SET and control groups. The most common serious infections were Cytomegalovirus and urinary tract infection; the incidence was comparable between groups. BK virus infection occurred in 2.7%, 4.0% and 0% of patients in the control, SOT/SET and SOT/RET groups, respectively. 1 patient in the SOT/RET group died on Day 163 from a sudden, massive pulmonary embolism. 4 patients died after study-drug discontinuation: 2 related to immunosuppressive treatment, 1 in the control group (cardiac arrest possibly due to a pulmonary embolism following a CMV chest infection diagnosed on Day 237. The patient died on Day 246, 3 days after study-drug discontinuation); and 1 in the SOT/SET group (septicemia following a Clostridium difficile infection and graft loss due to irreversible rejection. The patient died on Day 293, 28 days after study-drug discontinuation). 1 death in the SOT/RET group (pancreatic carcinoma on Day 251, 160 days after discontinuation) and 1 in the control group (GI hemorrhage on Day 47, 38 days after discontinuation) were considered unrelated to immunosuppressive treatment.
Keywords: Calcineurin inhibitor toxicity; Drug development; Efficacy; Mycophenolic acid; Renal function; Renal transplantation; Safety; T-cell activation; Tacrolimus

Reporting of race and ethnicity in breast cancer research: Room for improvement - Mitchell, K.W.; Carey, L.A.; Peppercorn, J. (Breast Cancer Research and Treatment, 2009)
Health disparities in breast cancer outcomes according to race/ethnicity are well documented. Randomized clinical trials (RCT) offer an opportunity to evaluate differences in disease biology and response to therapy that may contribute to disparities. We conducted a PubMed search to identify all English language original reports of breast cancer RCT from October 2001 to October 2006. The primary outcomes of interest were reporting of accrual and results by race or ethnicity of trial subjects. We evaluated the correlation between study characteristics and reporting of race/ethnicity. A total of 197 eligible trials were identified among 29 journals. Accrual was reported by race in 17% of studies and results analyzed by race in only 2%. Reporting of race was associated with National Cancer Institute funding (38 vs. 13%, P = 0.001), US cooperative group trials (52 vs. 13%, P < 0.0001), trials with US sites (43 vs. 5%, P < 0.0001), and trials enrolling > 500 subjects (24 vs. 12%, P = 0.055). Pharmaceutical industry funding, # of centers, stage of disease, nature of experimental intervention and study outcomes were not associated with reporting of race. Among US studies reporting trial accrual by race/ethnicity, the mean accrual distribution was 81% white, 7.6% black, 9.6% Asian, and 7.2% Hispanic subjects. The majority of breast cancer RCT fail to report the race/ethnicity of participants. Low accrual of black subjects and failure to report accrual and outcomes by race in RCT may contribute to difficulty in understanding and overcoming health disparities in breast cancer. © 2009 Springer Science+Business Media, LLC.
Keywords: Breast cancer; Clinical trials; Health disparities; Race

Strategies for recruiting African American men into prostate cancer screening studies - Jones, R.A.; Steeves, R.; Williams, I. (Nursing Research, 2009)
Background: Recruitment for research and clinical trials continues to be challenging. Prostate cancer is the most commonly diagnosed cancer in men and disproportionately affects African American men; thus, effective recruitment strategies are essential for this population. Objectives: The aim of this study was to focus on innovative and effective recruitment strategies for research on prostate cancer with minorities. Methods: A systematic description is provided of the recruitment efforts for a hermeneutic phenomenological qualitative study of African American men's experiences in decision making on whether to have a prostate cancer screening. Results: Seventeen African American men were enrolled from rural Central Virginia. Recruiting strategies were targeted on places where African American men usually are found but that are rarely used for recruitment: barbershops, community health centers, and churches. Word of mouth was also used, and most of the participants (n = 11) were reached through this method. Discussion: Recruitment efforts have been noted to be particularly challenging among minorities, for numerous reasons. Making minority recruitment a priority in any research or clinical trial is essential in gaining a representative sample. Word of mouth is a powerful tool that is often forgotten but should be looked at in further detail.Copyright © 2009 Lippincott Williams & Wilkins.
Keywords: African American; Health disparities; Minority recruitment; Prostate cancer

Attrition and retention in clinical trials by ethnic origin - Sangi-Haghpeykar, H.; Meddaugh, H.M.; Liu, H.; Grino, P. (Contemporary Clinical Trials, 2009)
Context: Common perceptions exist within the medical community that retention of Hispanics in clinical trials is difficult, albeit little data is available to support this conviction. Methods: A total of 541 randomly selected charts from closed clinical trials between 2000 and 2006 were reviewed. Records were from participating institutions in Texas Medical Center, Houston, and targeted diseases of high prevalence, specifically, breast cancer, prostate cancer, and chronic obstructive pulmonary disease (COPD)/asthma. Findings: Overall, 259 participants (48%) completed the trial they were enrolled in (44% whites, 69% Hispanics, 51% blacks; p < .05). Within pediatric trials, whom all were pulmonary patients, retention rates were higher among Hispanics than whites (adjusted odds ratio [OR] = 7.49, 95% confidence interval [CI] = 1.15-58.03, p = .04). Among adults, patient's ethnicity was unrelated to study completion. All associations were adjusted for possible confounders. Reasons for not completing a trial varied by ethnicity: "patient withdrawing consent" was more common among whites (51.4%) than Hispanics (21.7%) or blacks (26.2%) (p < .05). Hispanics were more inclined to be withdrawn from the trial by the investigator (43.5%) than were whites (24%, p = .04), mostly due to non-compliance with the study protocol. Conclusions: Hispanic parents of children with COPD may be more likely to complete a trial than parents of non-Hispanic whites. Among adults, Hispanics had similar completion rates as compared to whites. Culturally sensitive, multi-factorial approaches maybe imperative to increasing patient engagement in clinical trials. © 2009 Elsevier Inc. All rights reserved.
Keywords: Clinical trials; Culture; Minorities; Retention

An experimental test of the effect of incentives on recruitment of ethnically diverse colorectal cancer cases and their first-degree relatives into a research study - Maxwell, A.E.; Bastani, R.; Glenn, B.A.; Mojica, C.M.; Chang, L.C. (Cancer Epidemiology Biomarkers and Prevention, 2009)
Background: Optimizing participant response rates is important for obtaining representative samples and the timely completion of studies. It is a common practice to use participant incentives to boost response rates, but few studies have systematically examined their effectiveness, particularly among minority groups. Methods:We experimentally tested three incentive strategies for their effectiveness in improving response rates among colorectal cancer cases (n = 3,816) and their relatives (n = 2,353). A 2 x 2 x 2 factorial design compared (a) registered versus first class mail, (b) $5 cash with the initial mailing (yes/no), and (c) $20 promise (yes/no) upon completion of the information form (for cases) or $10 promise (yes/no) upon completion of the baseline survey (for relatives). Outcome measures were provision of contact information on first-degree relatives for cases and completion of the baseline survey for relatives. Results: The response rate among cases was low in all ethnic groups (28-37%) and incentive strategies did not have an effect. Among relatives, the overall baseline survey response rate was 71%, ranging from 66% among Asians to 76% among Whites. Modest absolute increases were observed for payment schedules that included a $5 cash enclosure with the initial mailing in the total sample [odds ratio (OR), 1.65 and 1.47] and among Latinos (OR, 1.94 and 1.74) but not among Asians (OR, 1.61 and 1.55) or African Americans (OR, 1.19 and 1.02). Response rates were not influenced by registered versus firstclass mailing. Conclusion: The effects of incentives in this study were modest with some suggestion of differences by ethnic group and type of incentive. Copyright © 2009 American Association for Cancer Research.

Sampling in population-based cancer caregivers research - Kim, Y.; Kashy, D.A.; Kaw, C.K.; Smith, T.; Spillers, R.L. (Quality of Life Research, 2009)
Background: Awareness that cancer impacts not only the person with the disease but also the family has increased, yet existing data provide limited information, primarily because of reliance on small geographically restricted samples. The current study used population-based sampling to develop a formula to compute the probability of survivors completing a survivor survey and nominating their family caregivers. Methods: Eleven SEER/NPCR state cancer registries participated in the American Cancer Society Study of Cancer Survivors survey, providing information about the survivors, including their age, race/ethnicity, gender, type of cancer, and stage of cancer. A total of 19,294 cancer survivors met the inclusion criteria (≥18 years old and diagnosed with one of the 10 common cancers). Results: Approximately 30% of survivors identified from state cancer registries completed the survivor survey, of whom 42% nominated a caregiver. Logistic regression analysis revealed that middle-aged, female, or non-black survivors and survivors diagnosed with breast or ovarian cancer were more likely to complete the survey and nominate a caregiver, whereas survivors with bladder or lung cancer and survivors with advanced-stage cancer were less likely to complete the survey and nominate a caregiver. Conclusions: Using the formula based on the logistic regression analysis results, a number of certain groups of survivors to be recruited from state registry can be calculated in order to have a present number of caregivers to contact for participation into a caregiver study. This is practical and valuable information, which fosters research that uses state cancer registries and increases the generalizability of findings to multiple types of cancer and different stages of cancer. © 2009 Springer Science+Business Media B.V.
Keywords: Caregivers; Methodology; Population-based research; Sampling; Survivorship

Development of wagle health-specific religiousness scale - Wagle, A.M.; Champion, V.L.; Russell, K.M.; Rawl, S.M. (Cancer Nursing, 2009)
African American women have a lower rate of regular mammography screening, resulting in higher incidence of advanced-stage breast cancer at diagnosis and a lower 5-year survival rate as compared with white women. Researchers have demonstrated that several health beliefs relate to mammography screening in African American women, but little attention has been paid to the importance of religiousness. Although some authors have attempted to determine a link between religiousness and health, we lack a valid and reliable instrument to measure religiousness that can be found in the context of health behaviors. The purpose of this article is to describe the development and psychometric testing of the Wagle Health-Specific Religiousness (WHSR) scale, an instrument used to measure religious beliefs and the influence of those beliefs on mammography screening for African American women. A sample of 344 low-income African American women who were nonadherent to mammography at accrual participating in a randomized trial completed the WHSR. Data from this trial were used to determine the validity and reliability of the WHSR. The 19-item WHSR scale had a Cronbach α of. 94. Construct validity was supported via factor analysis and analysis of theoretical relationships. Although further testing is warranted, this analysis indicates that the concept of religiousness is an important component of mammography behavior in African American women. Copyright © 2009 Lippincott Williams & Wilkins.
Keywords: African American women; Health beliefs; Health-specific religiousness; Mammography screening

An educational video to increase clinical trials enrollment among breast cancer patients - Du, W.; Mood, D.; Gadgeel, S.; Simon, M.S. (Breast Cancer Research and Treatment, 2009)
Only 3% of women with breast cancer participate in cancer clinical trials nationwide. The lack of awareness about clinical trials is a significant barrier towards clinical trials participation. A study was conducted at a large urban Comprehensive Cancer Center to test (1) the effectiveness of an 18-min educational video on improving attitudes toward clinical trials and trials enrollment among new breast cancer patients seen at the Karmanos Cancer Institute, and (2) to assess racial differences in attitudes regarding clinical trials. Participants were randomized to either the educational intervention prior to their first oncology clinic appointment or to standard care. A baseline and 2-week post-intervention survey to assess attitudes toward clinical trials participation was completed by participants. Of 218 subjects recruited, 196 (55% white vs. 45% African American (AA)) eligible patients were included in the analysis. A small increase in therapeutic clinical trial enrollment was observed in the intervention arm but was not statistically significant (10.4% vs. 6.1%; P = 0.277). The intervention also did not result in a clear improvement in patients' attitudes toward clinical trials at posttest. However, a lower enrollment rate for the AA women was noted after adjusting for stage (OR = 0.282, P = 0.049). Significantly more negative scores were noted in 3 out of the 5 baseline attitudinal scales for AA women. The educational video did not significantly increase enrollment in breast cancer clinical trials. The findings that AA women had significantly more negative attitudes toward clinical trials than white women may partially explain the racial disparity in enrollment. An educational video remains a simple and cost-effective way to educate patients. Future studies should focus on designing a new educational video to specifically target cultural and attitudinal barriers in the AA population to more effectively change attitudes and increase trial enrollment. © 2009 Springer Science+Business Media, LLC.
Keywords: Attitudes regarding clinical trials; Breast cancer; Clinical trials enrollment; Educational video; Racial disparity

Relationship of body mass, height, and weight gain to prostate cancer risk in the multiethnic cohort - Hernandez, B.Y.; Park, S.-Y.; Wilkens, L.R.; Henderson, B.E.; Kolonel, L.N. (Cancer Epidemiology Biomarkers and Prevention, 2009)
We investigated the relationship of body size and prostate cancer risk in the Multiethnic Cohort, a longitudinal study of individuals ages 45 to 75 in Hawaii and in California. Self-reported measures of height and weight were obtained at baseline. Of 83,879 men enrolled from 1993 to 1996, a total of 5,554 were diagnosed with prostate cancer during an average of 9.6 years of follow-up. The influence of baseline weight and weight change since age 21 varied by ethnic group. Whites gaining more than 10 lbs had a nonlinear, increased risk of advanced and high-grade prostate cancer [relative risks (RR), 2.12; 95% confidence intervals (CI), 1.19-3.78 for 25-39.9 lbs; P trend 0.43; and RR, 1.49; 95% CI, 1.04-2.14, for ≥40 lbs; P trend 0.20, respectively]. African American men gaining 40 lbs or more (relative to <10 lbs) had a nonmonotonic, increased risk of localized prostate cancers (RR, 1.26; 95% CI, 1.02-1.54; P trend 0.09) and those who gained 25 lbs or more were at increased risk of low-grade disease (RR, 1.28; 95% CI, 1.03-1.58, for ≥40 versus 10 lbs, respectively; P trend 0.07). Japanese men had a statistically significant, inverse association of weight gain and localized disease (RR, 0.80; 95% CI, 0.65-0.99 for ≥40 versus 10 lbs; P trend 0.05). Our findings provide evidence that adiposity and changes in adiposity between younger and older adulthood influence the development of prostate cancer. Ethnic differences in risk may be explained by variation in the distribution of accumulated body fat that could differentially affect prostate carcinogenesis. Copyright © 2009 American Association for Cancer Research.

Exploring the financial impact of breast cancer for african american medically underserved women: A qualitative study - Darby, K.; Davis, C.; Likes, W.; Bell, J. (Journal of Health Care for the Poor and Underserved, 2009)
In addition to the physical suffering experienced by cancer survivors, there are considerable financial hardships and access barriers to quality health care. The current study explored the financial burden of breast cancer on African American medically underserved women. Four focus groups were conducted in three major cities across Tennessee. Research participants (N=36) were recruited by the staff of cancer support and treatment programs in the area. Findings revealed that participants' lack of insurance or inadequate insurance resulted in missed, delayed, or fewer treatment opportunities. The financial burden of cancer was not limited to the acute treatment phase. The women in the current study reported extreme economic hardship resulting from this disease into long-term survivorship. This exploratory study confirms the importance of providing care across the continuum to address the complex needs of low-income cancer survivors.
Keywords: African American; Breast cancer; Financial; Minority; Underserved

Social workers as patient navigators for breast cancer survivors: What do african-american medically underserved women think of this idea? - Davis, C.; Darby, K.; Likes, W.; Bell, J. (Social Work in Health Care, 2009)
Patient navigation (PN) is a new initiative in health care aimed at reducing disparities by assisting patients in overcoming barriers within the health care system. As PN programs grow around the country, it is important to consult the key stakeholders in the development of these programs. The purpose of this qualitative study was to discuss the needs of medically underserved cancer patients and allow them the opportunity to provide input on models of care to meet their needs. Four focus groups were conducted in three major cities across Tennessee. Research participants (n = 36) were recruited by the staff in area cancer support programs and treatment programs across the state and through recruitment flyers at various treatment centers and community organizations. Findings revealed four key themes in the development of PN programs: (1) the PN needs to address access to quality care issues; (2) the PN needs to address the emotional and practical concerns of the cancer survivor; (3) the PN needs to address family concerns; (4) the PN needs to be involved across the continuum of care from time of diagnosis into long-term survivorship. Oncology social workers have a unique opportunity to meet the needs of medically underserved cancer patients through the PN movement. Our profession is a key stakeholder in this movement. We need to advocate for trained oncology social workers to actively pursue the role of patient navigators to ensure that the needs of medically underserved cancer survivors and their families are met.
Keywords: Breast cancer; Health disparities; Medically underserved; Patient navigation; Psychosocial; Social work

Racial disparities in cancer survival among randomized clinical trials patients of the southwest oncology group - Albain, K.S.; Unger, J.M.; Crowley, J.J.; Coltman, C.A.; Hershman, D.L. (Journal of the National Cancer Institute, 2009)
BackgroundRacial disparities in cancer outcomes have been observed in several malignancies. However, it is unclear if survival differences persist after adjusting for clinical, demographic, and treatment variables. Our objective was to determine whether racial disparities in survival exist among patients enrolled in consecutive trials conducted by the Southwest Oncology Group (SWOG).MethodsWe identified 19457 adult cancer patients (6676 with breast, 2699 with lung, 1244 with colon, 1429 with ovarian, and 1843 with prostate cancers; 1291 with lymphoma; 2067 with leukemia; and 2208 with multiple myeloma) who were treated on 35 SWOG randomized phase III clinical trials from October 1, 1974, through November 29, 2001. Patients were grouped according to studies of diseases with similar histology and stage. Cox regression was used to evaluate the association between race and overall survival within each disease site grouping, controlling for available prognostic factors plus education and income, which are surrogates for socioeconomic status. Median and ten-year overall survival estimates were derived by the Kaplan-Meier method. All statistical tests were two-sided.ResultsOf 19457 patients registered, 2308 (11.9%, range = 3.9%-21.6%) were African American. After adjustment for prognostic factors, African American race was associated with increased mortality in patients with early-stage premenopausal breast cancer (hazard ratio [HR] for death = 1.41, 95% confidence interval [CI] = 1.10 to 1.82; P =. 007), early-stage postmenopausal breast cancer (HR for death = 1.49, 95% CI = 1.28 to 1.73; P <. 001), advanced-stage ovarian cancer (HR for death = 1.61, 95% CI = 1.18 to 2.18; P =. 002), and advanced-stage prostate cancer (HR for death = 1.21, 95% CI = 1.08 to 1.37; P =. 001). No statistically significant association between race and survival for lung cancer, colon cancer, lymphoma, leukemia, or myeloma was observed. Additional adjustments for socioeconomic status did not substantially change these observations. Ten-year (and median) overall survival rates for African American vs all other patients were 68% (not reached) vs 77% (not reached), respectively, for early-stage, premenopausal breast cancer; 52% (10.2 years) vs 62% (13.5 years) for early-stage, postmenopausal breast cancer; 13% (1.3 years) vs 17% (2.3 years) for advanced ovarian cancer; and 6% (2.2 years) vs 9% (2.7 years) for advanced prostate cancer.ConclusionsAfrican American patients with sex-specific cancers had worse survival than white patients, despite enrollment on phase III SWOG trials with uniform stage, treatment, and follow-up.

Geographic recruitment of breast cancer survivors into community-based exercise interventions - Rogerino, A.; Grant, L.L.; Wilcox, H.; Schmitz, K.H. (Medicine and Science in Sports and Exercise, 2009)
PURPOSE: There is increased interest in developing and disseminating health behavior interventions for cancer survivors. Challenges in these efforts include participant burden in traveling to central intervention sites and sustainability. The purpose of this article is to report various methods used to recruit breast cancer survivors into an exercise intervention that attempts to address both of these challenges. METHODS:: Letters were mailed within specific zip codes near community-based intervention sites in cooperation with state cancer registries. Additional recruitment methods included flyers at breast care clinics and support groups, mass media, and conferences. RESULTS:: Of the 3200 women who responded, 82% (n = 2625) identified having heard about the study through state or hospital registry and 8% (n = 243) through print and broadcast media. Thirty-five percent (n = 103) of randomized women self-identified as having a minority racial background and 31.9% (n = 94) self-identified as African American. Comparisons of participant age and racial distribution to state cancer registries indicate similar age distribution but greater racial diversity among participants. CONCLUSION:: These results support the use of population-based cancer registries to recruit survivors into community-based interventions and clinical trials.

Latinas and breast cancer outcomes: Population-based sampling, ethnic identity, and acculturation assessment - Hamilton, A.S.; Hofer, T.P.; Hawley, S.T.; Morrell, D.; Leventhal, M.; Deapen, D.; Salem, B.; Katz, S.J. (Cancer Epidemiology Biomarkers and Prevention, 2009)
Purpose: Latinas and African-Americans with breast cancer, especially those of lower socioeconomic status and acculturation, have been underrepresented in studies assessing treatment satisfaction, decision-making, and quality of life. A study was designed to recruit a large and representative sample of these subgroups. Materials and Methods: Incident cases were selected by rapid case ascertainment (RCA) in the Los Angeles Surveillance, Epidemiology, and End Results Registry from 2005 to 2006, with oversampling of Latinas and African-Americans. Patients were maileda questionnaire and $10 incentive 5 to 6 months after diagnosis; nonrespondents were contacted by telephone. Multivariate analysis was usedto assess possible response bias. The RCA definition of Hispanic origin was validated by self-reports. The Short Acculturation Scale for Hispanics index for Latina respondents was used. Results: One thousand six hundred and ninety-eight eligible breast cancer cases were selected and 1,223 participated, for a response rate of 72.0%, which varied little by race/ethnicity. Age, race/ethnicity, and clinical factors were not associated with response; however, respondents were slightly more likely to be married and from higher socioeconomic status census tracts than nonrespondents. The RCA definition of Hispanic identity was highly sensitive (94.6%) and specific (90.0%). Lower acculturation was associated with lower education and literacy among Latinas. Discussion: High response rates among all subgroups were achieved due to the use of RCA, an incentive, extensive telephone follow-up, a native Spanish-speaking interviewer, and a focused questionnaire. The low acculturation index category identified a highly vulnerable subgroup. This large sample representing subgroups with greater problems will provide a basis for developing better interventions to assist these women. Copyright © 2009 American Association for Cancer Research.

Sociodemographic correlates of stage of adoption for colorectal cancer screening in African Americans - Christie, J.; Jandorf, L.; Itzkowitz, S.; Halm, E.; Freeman, K.; King, S.; Dhulkifl, R.; McNair, M.; Thelemaque, L.; Lawsin, C.; Duhamel, K. (Ethnicity and Disease, 2009)
Objectives: African Americans have the highest incidence and mortality rates from colorectal cancer in the United States. Endoscopic screening, while effective in reducing both, is greatly underutilized. This research sought to understand sociodemographic factors related to stage of readiness for endoscopic screening. Design: One hundred fifty nine African American women (76.1%) and men (mean age=57.0 years) who were non-adherent to endoscopic screening guidelines were recruited and asked to complete semi-structured interviews. Setting: Participants were all being seen for a non-acute primary care medical visit at one of two urban hospitals. The theoretical framework that informed this study was the Transtheoretical Model (TTM) and the emphasis on Stage of Change or intention for undergoing endoscopic screening. Main Outcome and Measures: Based on their stage of readiness to undergo screening, 67 (42%) were categorized as precontemplative (Has no plans to have a colonoscopy) while 92 were categoriezed as being in a contemplative or preparation stage. Using chi-square and Student t-tests, differences were examined between the two groups. Results: No sociodemographic variables distinguished the two groups. However, people in the contemplative/preparation group were more likely to: have a regularly seen healthcare professional (63.7% vs 36.3%; P=.005), have had a previous recommendation for screening (65.7% vs 34.3%; P=.003); had heard of a colonoscopy (63.6% vs 36.4%; P=.000) and have been told by a healthcare professional that they needed a colonoscopy (73.1% vs 26.9%; P=.000). Conclusions: This study helps us to better understand the relevance of sociodemographic characteristics that may be associated with completing endoscopic colorectal cancer screening. In addition, we confirm that physician recommendation and individual awareness of the procedure are significant factors in readiness to get screened.
Keywords: African Americans; Cancer prevention; Colorectal cancer screening

It's not just what you say, it's also how you say it: Opening the 'black box' of informed consent appointments in randomised controlled trials - Wade, J.; Donovan, J.L.; Athene Lane, J.; Neal, D.E.; Hamdy, F.C. (Social Science and Medicine, 2009)
Randomised controlled trials (RCTs) represent the gold standard methodology for determining effectiveness of healthcare interventions. Poor recruitment to RCTs can threaten external validity and waste resources. An inherent tension exists between safeguarding informed decision-making by participants and maximising numbers enrolled. This study investigated what occurs during informed consent appointments in an ongoing multi-centre RCT in the UK. Objectives were to investigate: 1] how study staff presented study information to participants; 2] what evidence emerged as to how well-informed participants were when proceeding to randomisation or treatment selection; and 3] what aspects of the communication process may facilitate improvements in providing evidence of informed consent. Qualitative analysis of a purposive sample of 23 recruitment appointments from three study centres and involving several recruitment staff applied techniques of thematic, content and conversation analysis (CA). Thematic analysis and CA revealed variation in appointment content and structure. Appointments were mostly recruiter-led or participant-led, and this structure was associated with what evidence emerged as to how participants understood information provided and whether they were in equipoise. Participant-led appointments provided this evidence more consistently. Detailed CA identified communication techniques which, when employed by recruiters, provided evidence as to how participants understood the choices before them. Strategic use of open questions, pauses and ceding the floor in the interaction facilitated detailed and systematic exploration of each participant's concerns and position regarding equipoise. We conclude that the current focus on content to be provided to achieve informed consent should be broadened to encompass consideration of how information is best conveyed to potential participants. A model of tailored information provision using the communication techniques identified and centred on eliciting and addressing participants' concerns is proposed. Use of these techniques is necessary to make potential participants' understanding of key issues and their position regarding equipoise explicit in order to facilitate truly informed consent. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Conversation analysis; Informed consent; Prostate cancer; Randomised controlled trial (RCT); Recruitment; Shared decision-making; UK

Host genetic variants in the interleukin-6 promoter predict poor outcome in patients with estrogen receptor-positive, node-positive breast cancer - DeMichele, A.; Gray, R.; Horn, M.; Chen, J.; Aplenc, R.; Vaughan, W.P.; Tallman, M.S. (Cancer Research, 2009)
Interleukin-6 modulates immune response, estrogen production, and growth pathways in breast cancer. We evaluated the effect of several common, functional interleukin-6 promoter variants in node-positive breast cancer patients enrolled on a multicenter, cooperative group, adjuvant chemotherapy trial to determine whether these variants were associated with clinical outcome overall and by estrogen receptor tumor phenotype. Genomic DNA and clinical data were collected from a clinical trial of adjuvant anthracycline-based chemotherapy followed by randomization to high-dose cyclophosphamide/thiotepa or observation (Intergroup Trial 0121). Genotyping for -174G>C (rs1800795), -597G>A (rs1800797), and -572G>C (rs1800796) was done by site-specific PCR and PyroSequencing, whereas the -373AnTn repeat was directly sequenced. Log-rank tests and Cox modeling were used to compare outcomes by genotype/haplotype and other factors. Three hundred forty-six patients (64% of trial) had corresponding genotype/clinical data available and did not differ from overall trial participants. After adjustment, patients with estrogen receptor-positive tumors and genotypes 597 GG or 174 GG had significantly worse disease-free survival [hazard ratio (HR), 1.6; P = 0.02 and HR, 1.71; P = 0.007, respectively], whereas the 373 8A12T repeat appeared to be protective (HR, 0.62; P = 0.02). The presence of at least one copy of the haplotype ([-597G, -572G, -373[10A/11T], -174G]) was associated with worse disease-free survival (HR, 1.46; P = 0.04). Kaplan-Meier plots show that all patients in this group relapsed by 24 months from diagnosis. This poor-risk haplotype was quite common overall (estimated frequency, 0.20) and twice as frequent among Blacks (estimated frequency, 0.41). ©2009 American Association for Cancer Research.

Treatment quality and outcomes of African American versus white breast cancer patients: Retrospective analysis of southwest oncology studies S8814/S8897 - Hershman, D.L.; Unger, J.M.; Barlow, W.E.; Hutchins, L.F.; Martino, S.; Osborne, C.K.; Livingston, R.B.; Albain, K.S. (Journal of Clinical Oncology, 2009)
Purpose: Women of African ancestry (AA) have lower WBC counts and are more likely to have treatment delays and discontinue adjuvant breast cancer therapy early compared with white women. We assessed the association between race and treatment discontinuation/delay, WBC counts, and survival in women enrolled onto breast cancer clinical trials. Patients and Methods: AA and white women from Southwest Oncology Group adjuvant breast cancer trials (S8814/ S8897) were matched by age and protocol. Only the treatment arms in which patients were scheduled to receive six cycles of chemotherapy were analyzed. Results: A total of 317 pairs of patients (n = 634) were analyzed. At baseline, AA women had higher body-surface area (P < .0001) and lower WBC (P = .0009). AA women were more likely to have tumors that were ≥ 2 cm (P = .01) and hormone receptor negative (P < .0001). AA women, versus white women, were marginally more likely to discontinue treatment early (11% v 7%, respectively; P = .07) or have one or more treatment delays (85% v 79%, respectively; P = .07) and were significantly more likely to experience the combined end point (discontinuation/delay; 87% v 81%, respectively; P = .04). The mean relative dose-intensity (RDI) was similar for both groups (87% in AA women v 86% in white women); however, overall, 43% had an RDI of less than 85%. After adjusting for baseline WBC and prognostic factors in a multivariate model, AA women had worse disease-free survival (hazard ratio [HR] = 1.56; 95% CI, 1.15 to 2.11; P = .005) and overall survival (HR = 1.95; 95% CI, 1.36 to 2.78; P = .0002). The inclusion of RDI and treatment delivery/quality in the regression had little impact on the results. Conclusion: On cooperative group breast cancer trials, AA and white women had similar RDIs, but AA women were more likely to experience early discontinuation or treatment delay. Despite correcting for these factors and known predictors of outcome, AA women still had worse survival. © 2009 by American Society of Clinical Oncology.

Addressing social determinants of health to improve access to early breast cancer detection: Results of the boston reach 2010 breast and cervical cancer coalition women's health demonstration project - Clark, C.R.; Baril, N.; Kunicki, M.; Johnson, N.; Soukup, J.; Ferguson, K.; Lipsitz, S.; Bigby, J. (Journal of Women's Health, 2009)
Background: The Boston Racial and Ethnic Approaches to Community Health (REACH) 2010 Breast and Cervical Cancer Coalition developed a case management intervention for women of African descent to identify and reduce medical and social obstacles to breast cancer screening and following up abnormal results. Methods: We targeted black women at high risk for inadequate cancer screening and follow-up as evidenced by a prior pattern of missed clinic appointments and frequent urgent care use. Case managers provided referrals to address patient-identified social concerns (e.g., transportation, housing, language barriers), as well as navigation to prompt screening and follow-up of abnormal tests. We recruited 437 black women aged 40-75, who received care at participating primary care sites. The study was conducted as a prospective cohort study rather than as a controlled trial and evaluated intervention effects on mammography uptake and longitudinal screening rates via logistic regression and timely follow-up of abnormal tests via Cox proportional hazards models. Results: A significant increase in screening uptake was found (OR 1.53, 95% CI 1.13-2.08). Housing concerns (p<0.05) and lacking a regular provider (p<0.01) predicted poor mammography uptake. Years of participation in the intervention increased odds of obtaining recommended screening by 20% (OR 1.20, 95% CI 1.02-1.40), but this effect was attenuated by covariates (p<0.53). Timely follow-up for abnormal results was achieved by most women (85%) but could not be attributed to the intervention (HR 0.95, 95% CI 0.50-1.80). Conclusions: Case management was successful at promoting mammography screening uptake, although no change in longitudinal patterns was found. Housing concerns and lacking a regular provider should be addressed to promote mammography uptake. Future research should provide social assessment and address social obstacles in a randomized controlled setting to confirm the efficacy of social determinant approaches to improve mammography use. © 2009, Mary Ann Liebert, Inc.

Issues related to implementing a smoking cessation clinical trial for cancer patients - Martinez, E.; Tatum, K.L.; Weber, D.M.; Kuzla, N.; Pendley, A.; Campbell, K.; Ridge, J.A.; Langer, C.; Miyamoto, C.; Schnoll, R.A. (Cancer Causes and Control, 2009)
Given high rates of smoking among cancer patients, smoking cessation treatment is crucial; yet limited data exist to guide integration of such trials into the oncologic context. In order to determine the feasibility of conducting smoking cessation clinical trials with cancer patients, screening and baseline data from a large randomized placebo-controlled pharmacotherapy trial were analyzed. Descriptive statistics and regression analyses were used to compare enrollees to decliners, describe program enrollees, and assess correlates of confidence in quitting smoking. Out of 14,514 screened patients, 263 (<2%) were eligible; 43 (16%) refused enrollment. Among the eligible patients, 220 (84%) enrolled. Enrollment barriers included smoking rate, medical history/contraindicated medication, lack of interest, and language. Compared to enrollees, decliners were more likely to have advanced cancer. The trial enrolled a sample of 67 (>30%) African Americans; participants had extensive smoking histories; many were highly nicotine dependent; and participants consumed about seven alcoholic beverages/week on average. Head and neck and breast cancer were the most common tumors. About 52 (25%) reported depressive symptoms. A higher level of confidence to quit smoking was related to lower depression and lower tumor stage. Integrating a smoking cessation clinical trial into the oncologic setting is challenging, yet feasible. Recruitment strategies are needed for patients with advanced disease and specific cancers. Once enrolled, addressing participant's depressive symptoms is critical for promoting cessation. © 2008 Springer Science+Business Media B.V.
Keywords: Cancer patients; Confidence; Feasibility data; Smoking cessation

A pilot trial of spirituality counseling for weight loss maintenance in African American breast cancer survivors - Djuric, Z.; Mirasolo, J.; Kimbrough, L.; Brown, D.R.; Heilbrun, L.K.; Canar, L.; Venkatranamamoorthy, R.; Simon, M.S. (Journal of the National Medical Association, 2009)
A continuing challenge in weight loss treatment is attaining maintenance of weight loss. The goal of this study was to develop a counseling method that would assist African American breast cancer survivors with weight loss maintenance. In this pilot study, 31 obese breast cancer survivors were recruited. Individualized, dietitian-led counseling by telephone and free Weight Watchers coupons were provided to all participants for 18 months. At the 6-month time point, women were randomized to receive spirituality counseling or not in addition to the standard program. The spirituality counseling was delivered via telephone using an 8-step framework. Subjects were asked to utilize daily meditation or prayer, daily readings, and the recording of thoughts in a journal. Mean weight loss from baseline to 6 months was a modest 2.0% of baseline weight. From 6 to 18 months, there was no further weight change in the spirituality arm and a gain of 0.7% in the dietitian-only arm. Despite little effect on weight loss, it did appear that spirituality counseling positively affected spiritual well-being (FACIT-Sp) scores and dietary quality. The spirituality counseling framework therefore may be further refined and useful for other health promotion studies with African American populations.
Keywords: Breast cancer; Quality of life; Weight

The Prostate cancer Intervention Versus Observation Trial:VA/NCI/AHRQ Cooperative Studies Program #407 (PIVOT): Design and baseline results of a randomized controlled trial comparing radical prostatectomy to watchful waiting for men with clinically localized prostate cancer - Wilt, T.J.; Brawer, M.K.; Barry, M.J.; Jones, K.M.; Kwon, Y.; Gingrich, J.R.; Aronson, W.J.; Nsouli, I.; Iyer, P.; Cartagena, R.; Snider, G.; Roehrborn, C.; et al. (Contemporary Clinical Trials, 2009)
Background: Prostate cancer is the most common noncutaneous malignancy and the second leading cause of cancer death in men. Ninety percent of men with prostate cancer are over aged 60 years, diagnosed by early detection with the prostate specific antigen (PSA) blood test and have disease believed confined to the prostate gland (clinically localized). Common treatments for clinically localized prostate cancer include watchful waiting surgery to remove the prostate gland (radical prostatectomy), external beam radiation therapy and interstitial radiation therapy (brachytherapy) and androgen deprivation. Little is known about the relative effectiveness and harms of treatments due to the paucity of randomized controlled trials. The VA/NCI/AHRQ Cooperative Studies Program Study #407: Prostate cancer Intervention Versus Observation Trial (PIVOT), initiated in 1994, is a multicenter randomized controlled trial comparing radical prostatectomy to watchful waiting in men with clinically localized prostate cancer. Methods: We describe the study rationale, design, recruitment methods and baseline characteristics of PIVOT enrollees. We provide comparisons with eligible men declining enrollment and men participating in another recently reported randomized trial of radical prostatectomy versus watchful waiting conducted in Scandinavia. Results: We screened 13,022 men with prostate cancer at 52 United States medical centers for potential enrollment. From these, 5023 met initial age, comorbidity and disease eligibility criteria and a total of 731 men agreed to participate and were randomized. The mean age of enrollees was 67 years. Nearly one-third were African-American. Approximately 85% reported they were fully active. The median prostate specific antigen (PSA) was 7.8 ng/mL (mean 10.2 ng/mL). In three-fourths of men the primary reason for biopsy leading to a diagnosis of prostate cancer was a PSA elevation or rise. Using previously developed tumor risk categorizations incorporating PSA levels, Gleason histologic grade and tumor stage, approximately 43% had low risk, 36% had medium risk and 20% had high-risk prostate cancer. Comparison to our national sample of eligible men declining PIVOT participation as well as to men enrolled in the Scandinavian trial indicated that PIVOT enrollees are representative of men being diagnosed and treated in the U.S. and quite different from men in the Scandinavian trial. Conclusions: PIVOT enrolled an ethnically diverse population representative of men diagnosed with prostate cancer in the United States. Results will yield important information regarding the relative effectiveness and harms of surgery compared to watchful waiting for men with predominately PSA detected clinically localized prostate cancer.
Keywords: Prostate cancer; Radical prostatectomy; Randomized clinical trial; Watchful waiting

Characterization of pneumonitis in patients with advanced non-small cell lung cancer treated with everolimus (RAD001) - White, D.A.; Schwartz, L.H.; Dimitrijevic, S.; Scala, L.D.; Hayes, W.; Gross, S.H. (Journal of Thoracic Oncology, 2009)
Purpose: To assess the incidence and radiographic and clinical presentation of pneumonitis associated with the mammalian target of rapamycin inhibitor everolimus in patients with advanced non-small cell lung cancer. PATIENTS AND Methods: A retrospective, centralized review of serial computed tomography scans and corresponding clinical data from patients with advanced non-small cell lung cancer treated with 10-mg oral once daily everolimus monotherapy in a phase II clinical study was conducted. Serial chest CT scans underwent a consensus read by two radiologists for presence of pneumonitis. These cases were then reviewed with corresponding clinical data by a pulmonologist to assess the suspected causality to everolimus and outcome. Results: Twenty-four of 64 patients reviewed were found to have radiographic evidence of pneumonitis. In 16 of these 24 patients, pneumonitis was suspected as either possibly (12) or probably (4) related to everolimus. The most common radiographic manifestations were focal areas of consolidation at the lung bases or ground-glass opacities. Pneumonitis evaluated with Common Terminology Criteria for Adverse Events (version 3) was grade 1 or 2 in 12 of 16 suspected cases, with 4 patients experiencing higher grades. In most of the patients, pneumonitis remained at the same or lower grade without discontinuation of therapy. Patients with evidence of interstitial lung disease at baseline had an increased risk of Common Terminology Criteria for Adverse Events grade more than or equal to 3 pneumonitis. Conclusion: Within the limitation of this retrospective study, Results suggest that a mostly low-grade pneumonitis with a possible or probable relationship to everolimus was relatively frequent, occurring in 25% of evaluated patients. These Results suggest a need for monitoring of pulmonary adverse events and the development of guidelines for managing pneumonitis in future studies with everolimus. © 2009 by the International Association for the Study of Lung Cancer. TypeofStudy:An open, retrospective study evaluating the radiographic patterns and clinical features of pneumonitis during Certican therapy in patients with advanced non-small cell lung cancer (NSCLC). DosageDuration:10 mg once daily orally, reduced to 5 mg daily or treatment interrupted for a maximum of 2 weeks in cases of unacceptable toxicity. Duration: 4-20 weeks. Results:Pneumonitis was noted in 24 of 64 patients. Pneumonitis developed within 3 months after starting Certican in 21 of 24 patients. CT scans showed predominantly ground-glass opacities or multifocal areas of air space consolidation with a basilar and peripheral predominance. One patient had extensive airspace consolidation following a more focal pattern of consolidation and there were 2 cases of pure interstitial lung changes. Radiographic patterns changed over observation points, most commonly between focal consolidation and ground-glass opacities. In some cases with, radiographic findings persisted while continuing treatment with Certican. Among 24 patients who developed pneumonitis, 16 cases were suspected to be related to Certican (4 classified as probable and 12 as possible). The worst CTCAE grade for the 16 patients with Certican-induced pneumonitis was grade 1 or 2 in 75% (4 had higher grades, including 1 death). Toxicity for 2 of 16 patients resolved by end of study. Interruptions of treatment (≤2 weeks) occurred in 4 of 16 patients, but only one was for a pulmonary AE: grade 3 infectious pneumopathy, which improved with antibiotics. One interruption was for grade 3 fatigue, but pneumonitis improved during temporal interruption which was maintained with resumption of Certican at a reduced dose. Another was for grade 3 stomatitis but respiratory failure occurred 4 days later with progression of disease, and Certican was discontinued. The last interruption was for grade 1 stomatitis. In the Certican-induced pneumonitis group, discontinuation occurred in 1 patient due to CTCAE grade 4 respiratory failure and left lower lobe pneumonia. One patient received a short course of corticosteroids for AEs other than pneumonitis. A possible relapse of pneumonitis was noted in 1 case. Indications:64 patients with advanced refractory non-small cell lung cancer (adenocarcinoma 36, bronchoalveolar carcinoma 6, large cell carcinoma 6, mixed epithelial cell carcinoma 1, squamous cell carcinoma 13; stage IIIb 8, stage IV 56). Coexisting diseases: pneumonitis (3), interstitial lung disease (10), chronic obstructive pulmonary disease (9). Patients:64 patients, 34 males and 30 females, age range 21-74 years (mean age 58.0 years); 11 Asian, 3 black, 48 white, 1 Pacific Islander, and 1 other; of whom 16 developed Certican-induced pneumonitis [9 males and 7 females, age range 42-74 years (mean age 62.1 years); 1 Asian, 1 black, and 14 white]. Dropouts: n=1 (due to Certican side effects). AuthorsConclusions:This study suggests that a pneumonitis, as assessed by presence of radiographic findings on review of serial chest CTs, was relatively common in patients with lung cancer during treatment with everolimus, occurring in 25% of evaluated patients. In the majority of patients, these events were low grade and persisted during ongoing treatment. These results suggest a need for development of detailed guidelines for managing pneumonitis in future clinical trials with everolimus (Supplement: recommendations for management of everolimus-related pneumonitis). AdverseEffects:16 patients developed pneumonitis [1 fatal; characterized by pleural effusion (n=6), dyspnea (n=6), cough (n=4), fatigue (n=3, 1 grade 3), fever (n=2), and infiltrative abnormalities (n=1)]; 1 grade 3 infectious pneumopathy; 1 grade 3 stomatitis, respiratory failure, and left lower lobe pneumonia leading to withdrawal; and 1 grade 1 stomatitis. FreeText:Tests: serial chest computed tomography (CT) scan, severity of adverse events by Common Terminology Criteria for Adverse Events (CTCAE), body temperature. Concomitant drugs: antibiotics, diuretics, and corticosteroids. Previous therapy: radiotherapy, gemcitabine, docetaxel, paclitaxel, gefitinib, and erlotinib.
Keywords: Everolimus; MTOR inhibitor; Non-small cell lung cancer; Pneumonitis; RAD001

Do preparation and life completion discussions improve functioning and quality of life in seriously ill patients? Pilot randomized control trial - Steinhauser, K.E.; Alexander, S.C.; Byock, I.R.; George, L.K.; Olsen, M.K.; Tulsky, J.A. (Journal of Palliative Medicine, 2008)
Background: Significant palliative care intervention has focused on physical pain and symptom control; yet less empirical evidence supports efforts to address the psychosocial and spiritual dimensions of experience. Objective: To evaluate the impact of an intervention (Outlook) that promotes discussions of end-of-life preparation and completion on health outcomes in dying persons, including pain and symptoms, physical function, emotional function (anxiety and depression), spiritual well-being, and quality of life at the end of life. Design: A three-arm pilot randomized control trial. Subjects were recruited from inpatient and outpatient hospital, palliative care, and hospice settings. Intervention subjects met with a facilitator three times and discussed issues related to life review, forgiveness, and heritage and legacy. Attention control subjects met with a facilitator three times and listened to a nonguided relaxation CD. True control subjects received no intervention. Measurements: Preoutcomes and postoutcomes included the Memorial Symptom Assessment Scale, QUAL-E, Rosow-Breslau ADL Scale, Profile of Mood States anxiety sub-scale, the CESD short version, and the Daily Spiritual Experience Scale. Results: Eighty-two hospice eligible patients enrolled in the study; 38 were women, 35 were African American. Participants' primary diagnoses included cancer (48), heart disease (5) lung disease (10), and other (19) Ages ranged from 28-96. Participants in the active discussion intervention showed improvements in functional status, anxiety, depression, and preparation for end of life. Conclusions: The Outlook intervention was acceptable to patients from a variety of educational and ethnic backgrounds and offers a brief, manualized, intervention for emotional and spiritual concerns. © 2008 Mary Ann Liebert, Inc.

Comparison of four different immunosuppression protocols without long-term steroid therapy in kidney recipients monitored by surveillance biopsy: Five-year outcomes - Anil Kumar, M.S.; Irfan Saeed, M.; Ranganna, K.; Malat, G.; Sustento-Reodica, N.; Kumar, A.M.S.; Meyers, W.C. (Transplant Immunology, 2008)
Induction and maintenance immunosuppression protocols with or without long-term steroid therapy in kidney transplant recipients are variable and are transplant center-specific. The aim of this prospective randomized pilot study was to compare 5-year outcomes in kidney recipients maintained on 4 different calcineurin inhibitor (CNI)-based immunosuppression protocols without long-term steroid therapy. Two hundred consenting patients who received kidney transplants between June 2000 and October 2004 were enrolled in 4 immunosuppression protocol groups, with 50 patients in each group: cyclosporine (CSA)/mycophenolate mofetil (MMF), CSA/sirolimus (SRL), tacrolimus (TAC)/MMF, and TAC/SRL. Induction therapy was done with basiliximab and methylprednisolone. Steroids were withdrawn on post-transplant day 2, and long-term steroid therapy was not used. Demographic characteristics among the four groups were comparable; approximately 50% of the recipients were African American and ≥ 80% of the kidneys transplanted were from deceased donors. Clinical acute rejection (CAR) was confirmed by biopsy and treated with intravenous pulse steroid therapy. Steroid-unresponsive CAR was treated with Thymoglobulin. Surveillance biopsies were performed at 1, 6, 12, 24, 36, 48, and 60 months to evaluate subclinical acute rejection (SCAR), chronic allograft injury (CAI), and other pathological changes per the Banff 2005 schema. The primary end point was CAR, and secondary end points were 5-year patient and graft survival rates, renal function, SCAR, CAI, and adverse events. In the first year post-transplant, the incidence of CAR was 18% in the CSA/MMF group, 8% in the CSA/SRL group, 14% in the TAC/MMF group, and 4% in the TAC/SRL group (CSA/MMF vs. TAC/SRL; p = 0.05). The incidence of SCAR was 22% in the CSA/MMF group, 8% in the CSA/SRL group, 16% in the TAC/MMF group, and 6% in the TAC/SRL group (CSA/MMF vs. CSA/SRL and TAC/SRL; p = 0.05). After the first year, the incidences of CAR and SCAR decreased and were comparable in all 4 groups. At 5 years post-transplant, cumulative CAI due to interstitial fibrosis/tubular atrophy (IF/TA), hypertension (HTN), and chronic calcineurin inhibitor (CNI) toxicity was observed in 54%, 48%, and 8% of the CSA/MMF group vs. 16%, 36%, and 12% of the CSA/SRL group vs. 38%, 24% and 6% of the TAC/MMF group vs. 14%, 25% and 12% of the TAC/SLR group (IF/TA: CSA/MMF vs. CSA/SRL and TAC/SRL; p = 0.04, HTN: CSA/MMF vs. TAC/MMF and TAC/SRL; p = 0.05, CNI toxicity: TAC/SRL and CSA/SRL vs. TAC/MMF; p = 0.05). Five-year patient and graft survival rates were 82% and 60% in the CSA/MMF group, 82% and 60% in the CSA/SRL group, 84% and 62% in the TAC/MMF group, and 82% and 64% in the TAC/SRL group (p = 0.9). Serum creatinine levels and creatinine clearances at 5 years were comparable among the groups. Our data show that the rates of CAR and SCAR in the first year post-transplant were significantly lower in the CSA/SRL and TAC/SRL groups and that cumulative CAI rates due to IF/TA and HTN at 5 years were significantly lower in the TAC/MMF, TAC/SRL, and CSA/SRL groups than in the CSA/MMF group. Despite significant differences in the incidences of CAR and SCAR and prevalence of different types of CAI at 5 years, renal function and patient and graft survival rates at 5 years were comparable among kidney recipients maintained on 4 different immunosuppression protocols without long-term steroid therapy. © 2008 Elsevier B.V. All rights reserved.
Keywords: Immunosuppression protocol; Kidney transplant; Steroid withdrawal

Cancer incidence in elderly medicare and dually eligible beneficiaries - Bradley, C.J.; Luo, Z.; Given, C.W. (Health Services Research, 2008)
Objective. We assessed how Medicaid enrollment and race influence cancer incidence among patients age 65 years and older. Data Sources and Method. Population-based Michigan Tumor Registry was merged with Medicaid eligibility files for 1996 through 2000. All analyses were age-adjusted and gender-specific. We compared cancer incidence in the elderly Medicaid population to the cancer incidence in the Medicare population. We then examined cancer incidence in patients continuously enrolled in Medicaid 12 or more months relative to the incidence in the Medicare population. Principal Findings. When comparing cancer incidence in Medicaid patients without regard to enrollment before diagnosis, the incidence rates of prostate cancer in black men and colorectal cancer in black women were statistically higher relative to the incidence rates in white patients. The overall cancer incidence rate for all cancers combined was statistically significantly higher for black women and men compared with white women and men (incidence rate ratio=1.18 and 1.48, 95 percent confidence interval 1.05-1.32 and 1.28-1.71, respectively). In dually eligible patients enrolled 12 or more months before diagnosis, an excess cancer incident was observed for black patients relative to white patients in every cancer site examined with the exception of lung cancer. Conclusions. Medicaid data in addition to Medicare data revealed patterns of cancer incidence that varied according to Medicaid enrollment and race. These findings suggest that the cancer burden among African Americans and dually eligible patients is substantial. © Health Research and Educational Trust.
Keywords: Cancer; Dual eligible; Incidence; Medicaid; Medicare

Racial differences in clinical outcomes from metastatic breast cancer: A pooled analysis of CALGB 9342 and 9840 - Cancer and leukemia group B - Polite, B.N.; Cirrincione, C.; Fleming, G.F.; Berry, D.A.; Seidman, A.; Muss, H.; Norton, L.; Shapiro, C.; Bakri, K.; Marcom, K.; Lake, D.; Schwartz, J.H.; et al. (Journal of Clinical Oncology, 2008)
Purpose: African American women are more likely to be diagnosed with metastatic breast cancer at the time of presentation than whites, and have shorter survival once diagnosed. This study examines racial differences in clinical outcomes in the setting of two large cooperative group randomized clinical trials. Patients and Methods: The study cohort consisted of 787 white (80%) and 195 African American (20%) patients with metastatic breast cancer enrolled in two successive Cancer and Leukemia Group B (CALGB) trials using taxanes in the metastatic setting. Differences in overall survival (OS), response incidence, and time to treatment failure (TTF) were examined by race. In addition, differences in the incidence of baseline and treatment-related toxicities were examined. Results: With 779 deaths (166 African Americans and 613 whites), median OS was 14.3 months for African Americans and 18.75 months for whites (hazard ratio [HR] = 1.37; 95% CI, 1.15 to 1.63). When adjusted for prognostic factors, African Americans had a 24% increase in the hazard of death compared with whites (HR = 1.24; 95% CI, 1.02 to 1.51). No significant differences in TTF or overall response to therapy were seen. No clinically significant toxicity differences were seen. Conclusion: African Americans with metastatic breast cancer have an increased hazard of death compared with whites despite the receipt of similar per-protocol treatment, but experience no differences in TTF or overall response to therapy. We hypothesize that more direct and robust measures of comorbidities, and perhaps other factors such as receipt of subsequent therapy could help further explain the observed survival difference. © 2008 by American Society of Clinical Oncology.

Timing is everything: Methodologic issues locating and recruiting medically underserved women for abnormal mammography follow-up research - Fair, A.M.; Wujcik, D.; Lin, J.-M.S.; Egan, K.M.; Grau, A.M.; Zheng, W. (Contemporary Clinical Trials, 2008)
Objectives: Recruiting underserved women in breast cancer research studies remains a significant challenge. We present our experience attempting to locate and recruit minority and medically underserved women identified in a Nashville, Tennessee public hospital for a mammography follow-up study. Study design: The study design was a retrospective hospital-based case-control study. Methods: We identified 227 women (88 African-American, 65 Caucasian, 36 other minority, 38 race undocumented in the medical record) who had undergone screening mammography and received an abnormal result during 2003-2004. Of the 227 women identified, 159 women were successfully located with implementation of a tracking protocol and more rigorous attempts to locate the women using online directory assistance and public record search engines. Women eligible for the study were invited to participate in a telephone research survey. Study completion was defined as fully finishing the telephone survey. Results: An average of 4.6 telephone calls (range 1-19) and 2.7 months (range 1-490 days) were required to reach the 159 women contacted. Within three contact attempts, more cases were located than controls (61% cases vs. 49% controls, p = 0.03). African-American women cases were four times likely to be recruited than African-American controls, (OR, 4.07; 95% CI, 1.59-10.30) (p = 0.003). After 3 months of effort, we located 67% of African-American women, 63% of Caucasian women, and 56% of other minorities. Ultimately, after a maximum of 12 attempts to contact women, 77% of African-American women and 71% of Caucasian women were eventually found. Of these, 59% of African-American women, 69% Caucasian women, and 50% other minorities were located and completed the study survey for an overall response rate of 59%, 71%, and 47% respectively. Conclusions: Data collection and study recruitment efforts were more challenging in racial and ethnic minorities. Continuing attempts to contact women may increase minority group study participation but does not guarantee retention or study completion. © 2008 Elsevier Inc. All rights reserved.
Keywords: Abnormal mammography follow-up; Case-control studies; Medically underserved females; Study recruitment

Influence of church attendance and spirituality in a randomized controlled trial to increase mammography use among a low-income, tri-racial, rural community - Katz, M.L.; Kauffman, R.M.; Tatum, C.M.; Paskett, E.D. (Journal of Religion and Health, 2008)
Background The influence of church attendance and spirituality on mammography use was studied among Native American, White, and African American women living in a rural county. Methods A randomized trial was conducted to increase mammography use. Women (n = 851) were randomly assigned to receive either an educational program delivered by a lay health advisor or a physician letter and brochure about cervical cancer screening (control group). Church attendance and spirituality were measured at baseline and mammography use was evaluated 12 months after enrollment using medical record review. Results Almost two-thirds of the women reported that they attended church at least once a week, and less than 4% were classified as having low spirituality. Church attendance (P = 0.299) or spirituality (P = 0.401) did not have a significant impact on mammography use. Conclusions Church attendance and spirituality did not impact mammography use. © 2008 Blanton-Peale Institute.
Keywords: Cancer screening; Mammography; Religion; Rural population; Spirituality

Effects of baseline comorbidities on cancer screening trial adherence among older African American men - Ford, M.E.; Havstad, S.L.; Fields, M.E.; Manigo, B.; McClary, B.; Lamerato, L. (Cancer Epidemiology Biomarkers and Prevention, 2008)
Background: The purpose of this study was to examine the effects of baseline comorbidities on screening adherence in a sample of older African American men (ages ≥55 years) enrolled in a case management intervention in a cancer screening trial. Methods: Baseline comorbidity data were obtained from 683 African American men who were randomly assigned to a case management intervention group (n = 344) or to a case management control group (n = 339). The effects of comorbidities on the screening adherence rates of each group were then assessed. Results: No statistically significant interactions were found between each health history characteristic and the intervention. Therefore, analyses were not stratified by intervention status. In general, participants with comorbidities were no less likely to adhere to trial screening than participants without comorbidities. Exceptions were current smokers and participants with chronic bronchitis. Current smokers were less likely than others to adhere to the prostate-specific antigen test (P = 0.02) and the digital rectal examination for prostate cancer screening (P = 0.01), to the chest X-ray for lung cancer screening (P < 0.01), and to the flexible sigmoidoscopy for colorectal cancer screening (P = 0.04). Participants with chronic bronchitis had lower rates of adherence to the chest X-ray (P = 0.06). Having a relative with cancer positively influenced adherence to the digital rectal examination (P = 0.05). Conclusions: Overall, older African American men with comorbidities appear to be very good candidates for participation in longitudinal cancer screening trials. However, smoking had a statistically significant and deleterious effect on adherence to all types of screening. Copyright © 2008 American Association for Cancer Research.

Partnership with an African American sorority to enhance participation in cancer genetics research - Olsen, S.J.; Malvern, K.T.; May, B.J.; Jenkins, I.L.; Griffin, C.A. (Community Genetics, 2008)
Background/Aims: Reduced minority participation in clinical research challenges researchers to consider novel recruitment modalities. This study describes a formal partnership between the National Educational Foundation of the Zeta Phi Beta Sorority and the Mid-Atlantic Cancer Genetics Network. The goal was to enhance awareness about inherited breast cancer and to increase enrollment in the national Cancer Genetics Network. Methods: In this descriptive, pilot study, two recruitment strategies across four states were undertaken: an onsite educational session at four Annual State Leadership Conferences and a 2-tiered direct mail campaign to the sorority membership. Results: Recruitment methods targeted over 1,200 well-educated African American women. Of the 279 attendees at the state conference educational sessions, only 3 women meeting the high risk eligibility requirement enrolled. Direct mail recruitment elicited 24 eligible women. Lessons learned are described. Conclusion: Despite low accrual, the partnership laid a foundation for broader collaboration with the Zeta Phi Beta Sorority. In the future, collaboration with minority sororities and fraternities as part of standard registry recruitment should be explored. Copyright © 2008 S. Karger AG.
Keywords: African American; Cancer; Cancer Genetics Network; Genetics; Recruitment; Research

Successful strategies for increasing African American participation in cancer genetic studies: Hopeful signs for equalizing the benefits of genetic medicine - Patterson, A.R.; Davis, H.; Shelby, K.; McCoy, J.; Robinson, L.D.; Rao, S.K.; Banerji, P.; Tomlinson, G.E. (Community Genetics, 2008)
Objective: To determine whether prior success in recruiting African Americans to an in-house cancer genetics registry could be duplicated when recruiting to a national registry requiring a significantly increased level of commitment. Additionally, to determine which recruitment sources and practices yielded the highest number of African American participants. Methods: A retrospective analysis of recruitment sources, practices, and results for recruitment to the Cancer Genetics Network (CGN; a national research registry), from 2000 to 2005 was conducted. These results were compared to previous experience in recruiting African Americans to the Family Cancer Registry (FCR; an in-house registry) during the period 1992-2005. Results: In the 1st year of recruitment to the CGN, African Americans accounted for 24% of those consenting to participate in the CGN registry from our center. This compares to an average annual rate of 27% for the FCR during the years 1998-2005, and a rate of less than 1% from 1992 to 1998. By 2005, African Americans accounted for 27% of CGN participants recruited through the University of Texas Southwestern Medical Center, one of eighteen participating institutions in the CGN. Hospital-based resources such as cancer treatment clinics and tumor registries yielded the highest percentage of African American participants (66.5%), and self-referral yielded the lowest (0%). Seventy-seven percent of African Americans were actively sought out and recruited from treatment clinics, whereas the vast majority of Caucasian participants were recruited passively during the course of genetic counseling sessions that were scheduled for reasons unrelated to participation in cancer research. There were no known instances of African Americans contacting CGN staff after reading printed recruitment materials or internet advertisements. Conclusions: The increased level of commitment required of CGN participants did not deter African Americans from participating in cancer genetics research. Recruitment strategies responsible for dramatically increasing recruitment rates to the FCR from 1998 to 2000 were equally effective when used for recruitment to the CGN. The most effective recruitment sources were high-yield venues such as cancer treatment clinics and tumor registries, and active recruitment methods yielded the highest number of African American participants. Advertising through internet announcements and printed recruitment materials did not appear to be effective. Copyright © 2008 S. Karger AG.
Keywords: African American; Cancer genetic studies; Hereditary breast cancer; Minority recruitment

A church-based program on prostate cancer screening for African American men: Reducing health disparities - Husaini, B.A.; Reece, M.C.; Emerson, J.S.; Scales, S.; Hull, P.C.; Levine, R.S. (Ethnicity and Disease, 2008)
Introduction: African American men have a significantly higher incidence of prostate cancer, are diagnosed at younger ages and more advanced stages, and have higher mortality rates from prostate cancer than do White men. Methods: This community-based intervention study employed a quasiexperimental delayed- control (crossover) design with randomization at the church level. Forty-five African American churches were randomly assigned to two study groups: early intervention and delayed intervention. A convenience sample of 430 African American male volunteers (ages 40-70) was enrolled through the churches, and 350 men remained in the study through wave 3. The intervention was a culturally tailored group educational program, which included a video and a question-and-answer session with an African American physician. Results: Within each group, knowledge, perceived threat, and screening prevalence all increased significantly. However, the magnitude of increases was similar, so the groups did not differ significantly at wave 2. Knowledge at wave 2 was associated with greater odds of having a digital rectal exam by wave 3 only for the early-intervention group. The early-intervention group was two times more likely to have talked to a physician about prostate cancer screening by wave 3. Conclusions: The findings suggest that the delayed-intervention group did not function as a pure control and may have unintentionally received a partial intervention. This finding demonstrated that a low-cost prostate cancer awareness campaign within a church may be enough to affect prostate cancer knowledge, attitudes, and behaviors among African American men. Further research should examine the church-specific intervention elements, cultural appropriateness of the messages, and whether group sessions provide additional effect.
Keywords: African american men; Community-based education; Culturally appropriate; Faith-based; Health disparities; Informed decision-making; Prostate cancer screening

Retention of African American women in cancer genetics research - Halbert, C.H.; Love, D.; Mayes, T.; Collier, A.; Weathers, B.; Kessler, L.; Stopfer, J.; Bowen, D.; Domchek, S. (American Journal of Medical Genetics, Part A, 2008)
Although retention is a critical component of longitudinal cancer genetics research, limited empirical data are available on predictors of study retention among populations that are difficult to enroll. We evaluated predictors of retention in cancer genetics research among African American women at increased risk for having a BRCA1 and BRCA2 (BRCA1/2) mutation. Participants were African American women (n = 192) at increased risk for hereditary breast-ovarian cancer who were enrolled in a longitudinal genetic counseling research study. Retention was evaluated separately for the 1-and 6-month follow-ups and in terms of overall retention (e.g., completion of both telephone interviews). Seventy-three percent of women and 65% of women were retained at the 1- and 6-month follow-ups respectively; in terms of overall retention, 60% of women were retained in both follow-up telephone interviews. Predictors of retention at 1-month included being employed (OR = 2.47, 95% CI = 1.24, 4.93, P = 0.01) whereas predictors of overall retention included having a personal history of breast and/or ovarian cancer (OR = 2.06, 95% CI = 1.07, 3.95, P = 0.03) and having completed genetic counseling (OR = 2.63, 95% CI = 1.39, 4.98, P = 0.003). These data suggest that once enrolled in genetic counseling research, the majority of African American women will continue to participate, especially if concrete clinical services are provided. © 2007 Wiley-Liss, Inc.
Keywords: African American; Cancer genetics; Research; Retention

Enrollment of racial and ethnic minorities in the prostate, lung, colorectal and ovarian cancer screening trial - Pinsky, P.F.; Ford, M.; Gamito, E.; Higgins, D.; Jenkins, V.; Lamerato, L.; Tenorio, S.; Marcus, P.M.; Gohagan, J.K. (Journal of the National Medical Association, 2008)
Background: Minority populations in the United States, especially blacks and Hispanics, are generally underrepresented among participants in clinical trials. Here, we report the experience of enrolling ethnic minorities in a large cancer screening trial. Methods: The Prostate, Colorectal, Lung and Ovarian (PLCO) Cancer Screening Trial is a multicenter randomized trial designed to evaluate the effectiveness of screening for the PLCO cancers. Subjects were recruited at 10 U.S. centers between 1993 and 2001. One screening center had a major special recruitment effort for blacks and another center had a major special recruitment effort for Hispanics. Results: Among almost 155,000 subjects enrolled in PLCO, minority enrollment was as follows: black (5.0%), Hispanic (1.8%) and Asian (3.6%). This compares to an age-eligible population in the combined catchment areas of the PLCO centers that was 14.0% black, 2.9% Hispanic and 5.4% Asian, and an age-eligible population across the U.S. that was 9.5% black, 6.5% Hispanic and 3.0% Asian. About half (45%) of Hispanics were recruited at the center with the special Hispanic recruitment effort. Seventy percent of blacks were recruited at two centers; the one with the major special recruitment effort and a center in Detroit whose catchment area was 20% black among age-eligibles. Blacks, Hispanics and (non-Hispanic) whites were all more highly educated, less likely to currently smoke and more likely to get regular exercise than their counterparts in the general population. Conclusion: Significant efforts were made to recruit racial/ethnic minorities into PLCO, and these efforts resulted in enrollment levels that were comparable to those seen in many recent cancer screening or prevention trials. Blacks and Hispanics were nonetheless underrepresented in PLCO compared to their levels among age-eligibles in the overall U.S. population or in the aggregate PLCO catchment areas.
Keywords: African Americans; Cancer; Clinical investigation; Latinos; Screening

Recruiting African-American barbershops for prostate cancer education - Hart Jr., A.; Underwood, S.M.; Smith, W.R.; Bowen, D.J.; Rivers, B.M.; Jones, R.A.; Parker, D.; Allen, J. (Journal of the National Medical Association, 2008)
Prostate cancer is the most common cause of cancer in men and the second leading cause of cancer deaths. African-American men bear a disproportionate burden of prostate cancer diagnosis and mortality. Current guidelines for prostate cancer screening differ among various medical organizations. Therefore, it is important that African-American men have the appropriate information needed to make informed decisions about prostate cancer screening. Unfortunately, a large percentage of African-American men could potentially be excluded from receiving culturally appropriate prostate cancer education. Therefore, a study was designed to recruit and intervene with African-American men and barbershops for increasing prostate cancer screening decision-making. The purpose of this study was to learn effective strategies for recruiting African-American barbershops for prostate cancer education and to determine barbershop proprietors' willingness to allow their barbershops to be used for research. In this paper, we present the outcomes of our recruitment methods for African-American barbershops, including a comparative description of participating and nonparticipating barbershops using the iMark Data System. One-hundred percent of the surveyed proprietors reported that they would allow their clients to learn about prostate cancer. Ninety-six percent reported they would consider allowing their clients to have access to handheld computers to learn about prostate cancer. We conclude from this study that African-American barbershops in general are welcoming environments in which to implement community-based prostate cancer education and public health research.
Keywords: African Americans; Prostate cancer

An examination of the influence of patient race and ethnicity on expressed interest in learning about cancer clinical trials - Markman, M.; Petersen, J.; Montgomery, R. (Journal of Cancer Research and Clinical Oncology, 2008)
Purpose: A number of factors have been identified as being associated with the documented low accrual rate of minorities into cancer-related clinical trials in the USA. An important issue is the fundamental interest, or lack thereof, of these specific patient populations in actually considering study participation. Methods: To examine this issue, aggregate data were analyzed from a proprietary Internet-based decision support program (NexProfiler Treatment Option Tools for Cancer, NexCura®, Seattle, WA, USA) embedded into approximately 100 cancer-associated Web sites where responding patients (or their families) were asked, but not required, to identify their race/ethnicity (African-American, Asian-American, Caucasian and Hispanic) and to also respond to the question, "Are you interested in learning about clinical trials?". Results: Of the >60,000 patients who both self-identified their race/ethnicity and responded to the question regarding their desire to learn about clinical trials, approximately 10% were from the minority (non-Caucasian) groups. Of note, in all four malignancies analyzed (breast, colorectal, lung, and prostate) and in both patients ≤60 and >60 years of age, each of the three non-Caucasian populations expressed an interest in learning about such studies that was equal to, if not greater than, that observed in the Caucasian respondents. Conclusion: Assuming these provocative results regarding self-declared desire to learn about clinical trials can be confirmed by others with similar Internet-associated databases, this analysis suggests Web-based recruitment strategies may be an effective method to communicate with minority populations in the US (and, perhaps, elsewhere) with a specific interest in considering participation in cancer clinical trials. © 2007 Springer-Verlag.

A randomized trial comparing web-based decision aids on prostate cancer knowledge for African-American men - Ellison, G.L.; Weinrich, S.P.; Lou, M.; Xu, H.; Powell, I.J.; Baquet, C.R. (Journal of the National Medical Association, 2008)
Context: Few decision aids are tailored for African-American men. We sought to determine if web-based decision aids increased knowledge of prostate cancer screening among African men. Methods: This postintervention, quasiexperimental research measured knowledge of prostate cancer screening among African-American men following receipt of 1 of 2 web-based decision aids: enhanced or usual care. Men ages 40-65 were recruited at the annual convention of the Prince Hall Masons in the summer of 2007, which was attended by 1,170 masons. The primary outcome was knowledge of prostate cancer screening. Results: There were 87 participants in the sample with a mean age of 52 years (standard deviation=6.9). forty-six masons were randomized to the enhanced decision aid, and 41 masons were randomized to the usual care decision aid. Knowledge scores were statistically significantly higher among the men receiving the enhanced decision aid compared to the usual care decision aid after simultaneously adjusting for age, educational level, marital status, family history, previous prostate specific antigen test and digital rectal exam (ñ=0.01). Concision: We found evidence that the enhanced web decision aid was significantly more effective than the usual care decision aid in promoting knowledge of the benefits, limitations and risks of prostate cancer screening. Webbased sites may be effective in facilitating discussions about screening between patients and health care providers.
Keywords: African Americans; Prostate cancer screening

Timing of menarche and first full-term birth in relation to breast cancer risk - Li, C.I.; Malone, K.E.; Daling, J.R.; Potter, J.D.; Bernstein, L.; Marchbanks, P.A.; Strom, B.L.; Simon, M.S.; Press, M.F.; Ursin, G.; Burkman, R.T.; Folger, S.G.; et al. (American Journal of Epidemiology, 2008)
Ages at menarche and first birth are established risk factors for breast cancer. The interval between these ages may also affect risk, since the breast is more susceptible to carcinogenic insults during this period than during the parous period. However, few investigators have studied this relation. Using logistic regression, the authors evaluated associations between the timing of reproductive events and breast cancer risk among 4,013 cases and 4,069 controls enrolled in a multicenter, population-based US case-control study of White and African-American women (1994-1998). For White, parous premenopausal and postmenopausal women, those who had an interval of ≥16 years between the ages of menarche and first birth had 1.5-fold (95% confidence interval (CI): 1.0, 2.2) and 1.4-fold (95% CI: 1.1, 1.8) increased risks of breast cancer, respectively, in comparison with those who had ≤5 years between these ages. Adjusting for age at first birth altered these risk estimates somewhat, to odds ratios of 1.5 (95% CI: 0.8, 2.9) and 1.0 (95% CI: 0.6, 1.5), respectively. These associations were stronger for lobular and hormone-receptor-positive tumors but were absent among premenopausal African-American women. The authors conclude that the interval between age at menarche and age at first birth is associated with the risk of hormonally sensitive types of breast cancer, particularly among White women. © The Author 2007. Published by the Johns Hopkins Bloomberg School of Public Health. All rights reserved.
Keywords: Breast neoplasms; Histology; Menarche; Menopause; Pregnancy; Premenopause; Receptors, estrogen; Receptors, progesterone

Harvest health: Translation of the chronic disease self-management program for older African Americans in a senior setting - Gitlin, L.N.; Chernett, N.L.; Harris, L.F.; Palmer, D.; Hopkins, P.; Dennis, M.P. (Gerontologist, 2008)
Purpose: We describe the translation of K. R. Lorig and colleagues' Chronic Disease Self-Management Program (CDSMP) for delivery in a senior center and evaluate pre-post benefits for African American participants. Design and Methods: Modifications to the CDSMP included a name change; an additional introductory session; and course augmentations involving culturally relevant foods, stress reduction techniques, and communicating with racially/ethnically diverse physicians. We recruited participants from senior center members, area churches, and word of mouth. We conducted baseline and 4-month post-interviews. Results: A total of 569 African American elders attended an introductory session, with 519 (91%) enrolling in the 6-session program. Of the 519, 444 (86%) completed ≥4 sessions and 414 (79%) completed pre-post interviews. We found small but statistically significant improvements for exercise (p = .001), use of cognitive management strategies (p = .001), energy/fatigue (p = .001), self-efficacy (p = .001), health distress (p = .001), and illness intrusiveness in different life domains (probabilities from .001-.021). We found no changes for health utilization. Outcomes did not differ by gender, number of sessions attended, number and type of chronic conditions, facilitator, leader, or recruitment site. Implications: The CDSMP can be translated for delivery by trained senior center personnel to African American elders. Participant benefits compare favorably to original trial outcomes. The translated program is replicable and may help to address health disparities.
Keywords: Chronic illness; Community participation; Disease management; Evidence-based; Program sustainability; Translational research

Using focus groups to adapt ethnically appropriate, information-seeking and recruitment messages for a prostate cancer screening program for men at high risk - Bryan, C.J.; Wetmore-Arkader, L.; Calvano, T.; Deatrick, J.A.; Giri, V.N.; Bruner, D.W. (Journal of the National Medical Association, 2008)
Purpose: To adapt ethnically appropriate radio and newspaper messages in order to increase information-seeking and recruitment to the high-risk Prostate Cancer Risk Assessment Program (PRAP) using input from focus groups. Methods: We conducted four gender- and ethnic specificfocus groups composed of up to eight participants each. Group participants ranged in age from 35-69 and were either at risk for prostate cancer or were married to someone at risk. Participants evaluated both print and radio advertisements for a PRAP media recruitment campaign, and their recommendations were used to adapt the advertisements. Results: Trigger words, e.g., "research program," were found to be a particular, issue for African-American men who cited concerns about "experimentation," while the other groups cited concerns about time commitments and cost. In the print messages, familial themes garnered an overall favorable response, but Caucasian-American participants responded negatively to the use of photos of age-appropriate models. Conclusion: Focus groups are useful in checking health professional assumptions about health messages prior to developing awareness or recruitment advertisements or materials. There was an implied preference for "younger" models among Caucasian Americans. Radio and print messages were adapted using the focus group recommendations, i.e., focusing on familial themes, adding race-specific risk estimates and using younger-than-target group models.
Keywords: Minority health; Prostate cancer; Screening

The effect of offering different numbers of colorectal cancer screening test options in a decision aid: A pilot randomized trial - Griffith, J.M.; Lewis, C.L.; Brenner, A.R.T.; Pignone, M.P. (BMC Medical Informatics and Decision Making, 2008)
Background. Decision aids can improve decision making processes, but the amount and type of information that they should attempt to communicate is controversial. We sought to compare, in a pilot randomized trial, two colorectal cancer (CRC) screening decision aids that differed in the number of screening options presented. Methods. Adults ages 48-75 not currently up to date with screening were recruited from the community and randomized to view one of two versions of our previously tested CRC screening decision aid. The first version included five screening options: fecal occult blood test (FOBT), sigmoidoscopy, a combination of FOBT and sigmoidoscopy, colonoscopy, and barium enema. The second discussed only the two most frequently selected screening options, FOBT and colonoscopy. Main outcomes were differences in screening interest and test preferences between groups after decision aid viewing. Patient test preference was elicited first without any associated out-of-pocket costs (OPC), and then with the following costs: FOBT-$10, sigmoidoscopy-$50, barium enema-$50, and colonoscopy-$200. Results. 62 adults participated: 25 viewed the 5-option decision aid, and 37 viewed the 2-option version. Mean age was 54 (range 48-72), 58% were women, 71% were White, 24% African-American; 58% had completed at least a 4-year college degree. Comparing participants that viewed the 5-option version with participants who viewed the 2-option version, there were no differences in screening interest after viewing (1.8 vs. 1.9, t-test p = 0.76). Those viewing the 2-option version were somewhat more likely to choose colonoscopy than those viewing the 5-option version when no out of pocket costs were assumed (68% vs. 46%, p = 0.11), but not when such costs were imposed (41% vs. 42%, p = 1.00). Conclusion. The number of screening options available does not appear to have a large effect on interest in colorectal cancer screening. The effect of offering differing numbers of options may affect test choice when out-of-pocket costs are not considered. © 2008 Griffith et al; licensee BioMed Central Ltd.

Neighborhood-level socioeconomic predictors of nonadherence to mammography screening guidelines - Dailey, A.B.; Kasl, S.V.; Holford, T.R.; Calvocoressi, L.; Jones, B.A. (Cancer Epidemiology Biomarkers and Prevention, 2007)
As neighborhood context is increasingly recognized as an important predictor of health outcomes and health behaviors, this analysis sought to determine the relationship between neighborhood-level socioeconomic status (SES) and regular mammography screening behavior. One thousand four hundred fifty-one women ages 40 to 79 years who obtained an "index" screening mammogram at one of five urban hospitals in Connecticut between October 1996 and January 1998 were enrolled in this prospective study. The logistic regression analysis includes the 1,229 women [484 African-American (39%) and 745 White (61%)] who completed telephone interviews at baseline and follow-up (average 29.4 months later) and for whom the study outcome, nonadherence to age-specific mammography screening guidelines, was ascertained. Neighborhood-level SES was determined using 1990 census tract information. Neighborhood-level SES variables (quartiles) were associated with nonadherence for African-American women [neighborhood-level education and composite socioeconomic position index (SEP Index)] and White women (neighborhood-level crowding and neighborhood-level assets). Using race-specific categorizations reflective of individual-level SES distributions, the SEP Index and neighborhood-level education were associated with nonadherence to mammography screening guidelines for African-American women (marginally significant for White women), independent of individual-level SES and other known predictors of mammography screening use [African-American women: SEP Index odds ratio (OR), 3.55; 95% confidence interval (95% CI), 1.33-9.51; neighborhood-level education OR, 3.21; 95% CI, 1.25-8.26; White women: SEP Index OR, 2.13; 95% CI, 0.97-4.67; neighborhood-level education OR, 2.31; 95% CI, 0.93-5.76]. The results of this analysis underscore the importance of examining neighborhood social context as well as individual factors in the study of mammography screening behavior. Copyright © 2007 American Association for Cancer Research.

Randomized controlled trial of yoga among a multiethnic sample of breast cancer patients: Effects on quality of life - Moadel, A.B.; Shah, C.; Wylie-Rosett, J.; Harris, M.S.; Patel, S.R.; Hall, C.B.; Sparano, J.A. (Journal of Clinical Oncology, 2007)
Purpose: This study examines the impact of yoga, including physical poses, breathing, and meditation exercises, on quality of life (QOL), fatigue, distressed mood, and spiritual well-being among a multiethnic sample of breast cancer patients. Patients and Methods: One hundred twenty-eight patients (42% African American, 31% Hispanic) recruited from an urban cancer center were randomly assigned (2:1 ratio) to a 12-week yoga intervention (n = 84) or a 12-week waitlist control group (n = 44). Changes in QOL (eg, Functional Assessment of Cancer Therapy) from before random assignment (T1) to the 3-month follow-up (T3) were examined; predictors of adherence were also assessed. Nearly half of all patients were receiving medical treatment. Results: Regression analyses indicated that the control group had a greater decrease in social well-being compared with the intervention group after controlling for baseline social well-being and covariates (P < .0001). Secondary analyses of 71 patients not receiving chemotherapy during the intervention period indicated favorable outcomes for the intervention group compared with the control group in overall QOL (P < .008), emotional well-being (P < .015), social well-being (P < .004), spiritual well-being (P < .009), and distressed mood (P < .031). Sixty-nine percent of intervention participants attended classes (mean number of classes attended by active class participants = 7.00 ± 3.80), with lower adherence associated with increased fatigue (P < .001), radiotherapy (P < .0001), younger age (P < .008), and no antiestrogen therapy (P < .02). Conclusion: Despite limited adherence, this intent-to-treat analysis suggests that yoga is associated with beneficial effects on social functioning among a medically diverse sample of breast cancer survivors. Among patients not receiving chemotherapy, yoga appears to enhance emotional well-being and mood and may serve to buffer deterioration in both overall and specific domains of QOL. © 2007 by American Society of Clinical Oncology.

Inverse correlation between body mass index and clinical outcomes in men with advanced castration-recurrent prostate cancer - Halabi, S.; Ou, S.-S.; Vogelzang, N.J.; Small, E.J. (Cancer, 2007)
BACKGROUND. Obesity has a variety of adverse health outcomes, but to the authors' knowledge, the effect of obesity on outcome in patients with advanced prostate cancer is not known. For this reason, the correlation between an elevated body mass index (BMI) and clinical outcomes in patients with metastatic, castration-recurrent prostate cancer (CRPC) was evaluated. METHODS. A total of 1226 men with CRPC who were enrolled in 9 prospective clinical trials conducted by the Cancer and Leukemia Group B (CALGB) for the treatment of metastatic disease were considered. Eligible patients had progressive prostate cancer during androgen deprivation therapy (with documented castrate levels of testosterone); an Eastern Cooperative Oncology Group performance status of 0 to 2; and adequate hematologic, renal, and hepatic function. Patients were classified based on BMI as normal (18.5-24.9 kg/m2), overweight (25-29.9 kg/m2), and mildly to severely obese (≥30kg/m 2). RESULTS. Approximately 24% of the patients had a normal BMI, 43% were overweight, and 33% were mildly to severely obese. On multivariable analysis, BMI was found to be a statistically significant predictor of overall survival and prostate cancer-specific mortality. Compared with men with normal BMIs, the hazard ratios for death for overweight men and mildly to severely obese men were 0.80 (95% confidence interval [95% CI], 0.68-0.93; P = .001) and 0.80 (95% CI, 0.68-0.94; P = .010), respectively. CONCLUSIONS. In patients with metastatic CRPC, obesity (as defined by an elevated BMI) appears to have a protective effect against overall mortality and prostate cancer-specific mortality. Alternatively, a higher BMI may reflect different cancer biology (ie, the lack of cachexia-producing substances). Further studies to gain a more comprehensive understanding of the mechanisms behind these clinical observations are needed. © 2007 American Cancer Society.
Keywords: Castration-recurrent prostate cancer; Clinical outcomes; Obesity; Race

A prospective study of body size and breast cancer in black women - Palmer, J.R.; Adams-Campbell, L.L.; Boggs, D.A.; Wise, L.A.; Rosenberg, L. (Cancer Epidemiology Biomarkers and Prevention, 2007)
The relation of body mass index (BMI) and weight gain to breast cancer risk is complex, and little information is available on Black women, among whom the prevalence of obesity is high. We assessed BMI and weight gain in relation to breast cancer risk in prospective data from the Black Women's Health Study. In 1995, 59,000 African American women enrolled in the Black Women's Health Study by completing mailed questionnaires. Data on anthropometric factors were obtained at baseline and every 2 years afterwards. In 10 years of follow-up, 1,062 incident cases of breast cancer occurred. Incidence rate ratios (IRR) were computed in multivariable Cox proportional hazards regression. BMI at age 18 years of ≥25 relative to <20 was associated with a reduced risk of breast cancer among both premenopausal women (IRR, 0.68; 95% confidence interval, 0.46-0.98) and postmenopausal women (IRR, 0.53; 95% confidence interval, 0.35-0.81). There was an inverse association of current BMI with premenopausal breast cancer but no association with postmenopausal breast cancer, either overall or among never-users of hormone therapy. Weight gain was not associated with postmenopausal breast cancer risk. In analyses restricted to breast cancers that were estrogen and progesterone receptor positive, IRRs for current BMI and weight gain were elevated but not statistically significant. The findings indicate that being overweight at age 18 years is associated with a reduced risk of both premenopausal and postmenopausal breast cancer in African American women. Understanding the reasons for the association may help elucidate the pathways through which adolescent exposures influence breast cancer risk. The lack of association of obesity with receptor-negative tumors in postmenopausal African American women may partially explain why breast cancer incidence in older Black women is not high relative to other ethnic groups in spite of the high prevalence of obesity in Black women. Copyright © 2007 American Association for Cancer Research.

Recruiting diverse patients to a breast cancer risk communication trial - Waiting rooms can improve access - Bodurtha, J.N.; Quillin, J.M.; Tracy, K.A.; Borzelleca, J.; McClish, D.; Wilson, D.B.; Jones, R.M.; Quillin, J.; Bowen, D. (Journal of the National Medical Association, 2007)
Low participation among underserved populations in health research constrains progress in public health practices. From 2003 to 2005, Women's Health Clinic patients at the VCU Health System were-recruited to a trial investigating breast cancer risk communication. In secondary analyses, we examined dimensions of the recruitment of these diverse women. The sample characteristics (age, insurance, race and previous mammograms) were compared to the overall clinic. Of recruitment attempts for eligible women, 45% consented; of those who declined, the top cited reasons were lack of time (40%) and lack of interest (18%). Of 899 participants, 35% qualified for the indigent care program, compared to 31% of the overall clinic (P<.001). Forty-five percent of participants were African American, compared to 54% of overall clinic patients (P<.001). Participants were younger (50 vs. 53 years, P<.001) than the overall clinic population. Nonrepresentative enrollment of patients in clinical trials is common and could lead to suboptimal applicability of findings. Although there were statistically significant race and age differences between the study sample and the overall population, we demonstrate that waiting room recruitment can engage diverse women in a clinical trial and cancer risk communication.
Keywords: Clinical investigation; Women's health

Direct mailing was a successful recruitment strategy for a lung-cancer screening trial - Hinshaw, L.B.; Jackson, S.A.; Chen, M.Y. (Journal of Clinical Epidemiology, 2007)
Objective: To analyze advertising, recruitment methods, and study participant demographics for the National Lung Screening Trial (NLST) site at Wake Forest University School of Medicine to define efficient ways to recruit participants for general clinical trials. Study Design and Setting: Recruitment method data, demographics, geographic location, and date of enrollment were collected from all 1,112 NLST participants. Marketing data and financial records were analyzed to determine the effectiveness of each recruitment method. Results: The total amount spent on advertising was $144,668, with the cost of enrollment per participant averaging $130. For black participants, the recruitment cost per person was $406, whereas for white and other race participants, the cost was $122 (P < 0.0001). To encourage minority enrollment, $13,192 was spent on television advertising geared toward black viewers, resulting in eight black participants at an average cost per person of $1,649. Direct mailing cost $143 per participant recruited, whereas TV ads cost $382 per participant. Conclusion: Direct mailing to a targeted group was the most efficient way to recruit participants. Printed advertising methods, that is, newspaper ads and brochures, were quite effective, whereas television ads were expensive. Appropriate minority recruitment needs sufficient attention and resources to ensure census groups are adequately represented. © 2007 Elsevier Inc. All rights reserved.
Keywords: Advertising; Clinical trial; Enrollment; Lung cancer screening; Recruitment method; Smokers

Who Enrolls Onto Clinical Oncology Trials? A Radiation Patterns of Care Study Analysis - Movsas, B.; Moughan, J.; Owen, J.; Coia, L.R.; Zelefsky, M.J.; Hanks, G.; Wilson, J.F. (International Journal of Radiation Oncology Biology Physics, 2007)
Purpose: To identify factors significantly influencing accrual to clinical protocols by analyzing radiation Patterns of Care Study (PCS) surveys of 3,047 randomly selected radiotherapy (RT) patients. Methods and Materials: Patterns of Care Study surveys from disease sites studied for the periods 1992-1994 and 1996-1999 (breast cancer, n = 1,080; prostate cancer, n = 1,149; esophageal cancer, n = 818) were analyzed. The PCS is a National Cancer Institute-funded national survey of randomly selected RT institutions in the United States. Patients with nonmetastatic disease who received RT as definitive or adjuvant therapy were randomly selected from eligible patients at each institution. To determine national estimates, individual patient records were weighted by the relative contribution of each institution and patients within each institution. Data regarding participation in clinical trials were recorded. The factors age, gender, race, type of insurance, and practice type of treating institution (academic or not) were studied by univariate and multivariate analyses. Results: Overall, only 2.7% of all patients were accrued to clinical protocols. Of these, 57% were enrolled on institutional review board-approved institutional trials, and 43% on National Cancer Institute collaborative group studies. On multivariate analysis, patients treated at academic facilities (p = 0.0001) and white patients (vs. African Americans, p = 0.0002) were significantly more likely to participate in clinical oncology trials. Age, gender, type of cancer, and type of insurance were not predictive. Conclusions: Practice type and race significantly influence enrollment onto clinical oncology trials. This suggests that increased communication and education regarding protocols, particularly focusing on physicians in nonacademic settings and minority patients, will be essential to enhance accrual. © 2007 Elsevier Inc. All rights reserved.
Keywords: Barriers to participation; Clinical trials

Attitudes toward participation in breast cancer randomized clinical trials in the African American community: A focus group study - Linden, H.M.; Reisch, L.M.; Hart Jr., A.; Harrington, M.A.; Nakano, C.; Jackson, J.C.; Elmore, J.G. (Cancer Nursing, 2007)
Participation of African Americans in research trials is low. Understanding the perspectives of African American patients toward participation in clinical trials is essential to understanding the disparities in participation rates compared with whites. A qualitative study was conducted to discover attitudes of the African American community regarding willingness to participate in breast cancer screening and randomized clinical trials. Six focus groups consisting of 8 to 11 African American women (N = 58), aged 30 to 65, were recruited from local churches. Focus group sessions involved a 2-hour audio-taped discussion facilitated by 2 moderators. A breast cancer randomized clinical trial involving an experimental breast cancer treatment was discussed to identify the issues related to willingness to participate in such research studies. Six themes surrounding willingness to participate in randomized clinical trials were identified: (1) Significance of the research topic to the individual and/or community; (2) level of trust in the system; (3) understanding of the elements of the trial; (4) preference for "natural treatments" or "religious intervention" over medical care; (5) cost-benefit analysis of incentives and barriers; and (6) openness to risk versus a preference for proven treatments. The majority (80%) expressed willingness or open-mindedness to the idea of participating in the hypothetical trial. Lessons learned from this study support the selection of a culturally diverse research staff and can guide the development of research protocols, recruitment efforts, and clinical procedures that are culturally sensitive and relevant. © 2007 Lippincott Williams & Wilkins, Inc.
Keywords: African American; Breast cancer; Clinical trials; Focus group study

Diagnostic accuracy of the gail model in the black women's health study - Adams-Campbell, L.L.; Makambi, K.H.; Palmer, J.R.; Rosenberg, L. (Breast Journal, 2007)
The Gail model is used to predict the risk of breast cancer in women of diverse race/ethnic groups for clinical trial protocols. However, this model has only been validated in US white women. Using a nested case-control study design, we evaluated the diagnostic accuracy of the original Gail model (GM) and that of the revised Gail model algorithm for blacks/African-Americans (GM-B) in the Black Women's Health Study (BWHS). Risk profiles were derived via a self reported questionnaire at the time of enrollment into the BWHS in 1995. Biennial questionnaires were obtained from the participants to determine the incident cases of breast cancer. The study of 725 breast cancer cases and 725 controls revealed that the 5-year risk of breast cancer based on the GM ranged from 0.2% to 15.4% among cases and 0.2% to 13.6% among the controls. Based on the GM-B, the 5-year risk of breast cancer ranged from 0.2% to 8.7% among cases and 0.2% to 7.2% among the controls. The sensitivities of the GM and GM-B model with the standard cutoff of 1.7% were 17.9% (95% CI: 15.9-19.9%) and 4.1% (95% CI: 3.0-5.2), respectively. Both the original and the modified version of the Gail model underestimate the risk of developing breast cancer in African-American women. More importantly, the modified Gail Model (GM-B) does a worse job at predicting the development of breast cancer for blacks than the original model (GM). © 2007 Copyright the Authors.
Keywords: Blacks; Breast cancer; Gail model; Sensitivity

Phase II trial of paclitaxel-topotecan-etoposide followed by consolidation chemoradiotherapy for limited-stage small cell lung cancer: CALGB 30002 - Miller, A.A.; Wang, X.F.; Bogart, J.A.; Hodgson, L.D.; Lima, C.M.S.R.; Radford, J.E.; Vokes, E.E.; Green, M.R. (Journal of Thoracic Oncology, 2007)
PURPOSE: We sought to evaluate the activity and tolerance of the rationally designed sequence of paclitaxel-topotecan-etoposide, a nonplatinum regimen, as induction therapy for limited-stage small-cell lung cancer before combined chemo- and radiotherapy. PATIENTS AND METHODS: Patients with measurable disease, performance status 0 to 2, no prior therapy, and adequate organ function were eligible. Paclitaxel (110 mg/m, administered intravenously on day 1), topotecan (1.5 mg/m, administered orally on days 2 to 4), and etoposide (160 mg/m, administered orally on days 5 to 7 every 21 days), with filgrastim for two cycles, were followed by chest irradiation to 70 Gy (to postinduction tumor volume) concurrent with carboplatin (area under the curve of 5, administered intravenously on day 1) and etoposide (100 mg/m on days 1 to 3 every 21 days) without filgrastim for three cycles (five chemotherapy cycles total). We aimed to determine the response rates to induction and overall therapy, overall and failure-free survival, and toxicity. The primary statistical endpoint was to differentiate between complete response rates of 50 and 70% for the overall treatment program. RESULTS: Between June 2001 and January 2003, 65 patients were enrolled, but one never started therapy, and one was ineligible. Patient characteristics included male/female, 27/36; white/black/other/unknown, 58/3/1/1; median age 62 (range, 38-78); performance status 0/1/2, 27/33/3. Induction chemotherapy resulted in six (10%) complete responses and 35 (56%) partial responses. Overall response to chemoradiotherapy included 27 (43%; 95% confidence interval [CI] 30-56%) complete responses and 24 (38%) partial responses. Median progression-free survival is 12 months (95% CI, 9-15 months). Median overall survival is 20 months (95% CI, 16-24 months). Frequent (>20%) grade 3/4 toxicities during all therapy included neutropenia, febrile neutropenia, anemia, thrombocytopenia, fatigue, and dysphagia. One patient died of febrile neutropenia, one died of febrile neutropenia and typhlitis, and one patient who declined transfusion for anemia died of cardiac ischemia. CONCLUSIONS: This treatment regimen has significant activity in limited-stage small-cell lung cancer but did not meet our prospectively defined criteria for further investigation in this setting. The addition of etoposide and the use of a sequenced administration schedule did not seem to improve overall activity beyond our prior experience with a topotecan-paclitaxel doublet. © 2007International Association for the Study of Lung Cancer.
Keywords: Etoposide; Paclitaxel; Phase II; Small-cell lung cancer; Topotecan

Prostate cancer community collaboration and partnership: education, awareness, recruitment, and outreach to southern African-American males. - Hughes, G.D.; Sellers, D.B.; Fraser Jr., L.; Teague, R.; Knight, B. (Journal of cultural diversity, 2007)
Prostate cancer is a significant health problem for African-American men intensified by low participation in screenings, clinical trials, and prospective cohort studies. Ten focus groups were conducted with African-American males and their female partners/spouses. Perceptions and knowledge about prostate cancer, as well as willingness to participate in screening and research studies were measured. Participants had a basic level of knowledge about prostate cancer, and the importance of education was a unified theme. Dialogue with targeted African-American men and their partners/spouses may increase awareness and retention in medical research, while influencing health promotion, education and behavior.

Perceived racial discrimination and nonadherence to screening mammography guidelines: Results from the race differences in the screening mammography process study - Dailey, A.B.; Kasl, S.V.; Holford, T.R.; Jones, B.A. (American Journal of Epidemiology, 2007)
The study objective was to determine whether perceived racial discrimination influenced nonadherence to screening mammography guidelines. Enrolled in this prospective study were 1,451 women aged 40-79 years who obtained an "index" screening mammogram at one of five urban hospitals in Connecticut between October 1996 and January 1998. This logistic regression analysis included 1,229 women (484 African American (39%), 745 White (61%)) who completed telephone interviews at baseline and follow-up (on average 29 months later). Perceived racial discrimination was measured as lifetime experience in seven possible situations. Approximately 42% of African-American women and 10% of White women reported lifetime racial discrimination. Perceived racial discrimination was not associated with nonadherence to age-specific mammography screening guidelines in unadjusted or multivariate-adjusted analyses. Although these negative findings may reflect the well-recognized problems associated with measurement of perceived discrimination, it is possible that women who recognize and report racial discrimination develop compensatory characteristics that enable positive health prevention behavior, in spite of their past experiences. Copyright © 2007 by the Johns Hopkins Bloomberg School of Public Health All rights reserved.
Keywords: African Americans; Breast neoplasms; Discrimination (psychology); Ethnic groups; Mammography; Prejudice; Risk factors

The Patient Safety in Surgery Study: Background, Study Design, and Patient Populations - Khuri, S.F.; Henderson, W.G.; Daley, J.; Jonasson, O.; Jones, R.S.; Campbell Jr., D.A.; Fink, A.S.; Mentzer Jr., R.M.; Steeger, J.E. (Journal of the American College of Surgeons, 2007)
Background: The purpose of this article is to describe the background, design, and patient populations of the Patient Safety in Surgery Study, as a preliminary to the articles in this journal that will report the results of the Study. Study Design: The Patient Safety in Surgery Study was a prospective cohort study. Trained nurses collected preoperative risk factors, operative variables, and 30-day postoperative mortality and morbidity outcomes in patients undergoing major general and vascular operations at 128 Veterans Affairs (VA) medical centers and 14 selected university medical centers between October 1, 2001 and September 30, 2004. An Internet-based data collection system was used to input data from the different private medical centers. Semiannual feedback of observed to expected mortality and morbidity ratios was provided to the participating medical centers. Results: During the 3-year study, total accrual in general surgery was 145,618 patients, including 68.5% from the VA and 31.5% from the private sector. Accrual in vascular surgery totaled 39,225 patients, including 77.8% from the VA and 22.2% from the private sector. VA patients were older and included a larger proportion of male patients and African Americans and Hispanics. The VA population included more inguinal, umbilical, and ventral hernia repairs, although the private-sector population included more thyroid and parathyroid, appendectomy, and operations for breast cancer. Preoperative comorbidities were similar in the two populations, but the rates of comorbidities were higher in the VA. American Society of Anesthesiologists classification tended to be higher in the VA. Conclusions: The National Surgical Quality Improvement Program methodology was successfully implemented in the 14 university medical centers. The data from the study provided the basis for the articles in this issue of the Journal of the American College of Surgeons. © 2007 American College of Surgeons.

Polymorphisms, mutations, and amplification of the EGFR gene in non-small cell lung cancers - Nomura, M.; Shigematsu, H.; Li, L.; Suzuki, M.; Takahashi, T.; Estess, P.; Siegelman, M.; Feng, Z.; Kato, H.; Marchetti, A.; Shay, J.W.; Spitz, M.R.; et al. (PLoS Medicine, 2007)
Background: The epidermal growth factor receptor (EGFR) gene is the prototype member of the type I receptor tyrosine kinase (TK) family and plays a pivotal role in cell proliferation and differentiation. There are three well described polymorphisms that are associated with increased protein production in experimental systems: a polymorphic dinucleotide repeat (CA simple sequence repeat 1 [CA-SSR1]) in intron one (lower number of repeats) and two single nucleotide polymorphisms (SNPs) in the promoter region, -216 (G/T or T/T) and -191 (C/A or A/A). The objective of this study was to examine distributions of these three polymorphisms and their relationships to each other and to EGFR gene mutations and allelic imbalance (AI) in non-small cell lung cancers. Methods and Findings: We examined the frequencies of the three polymorphisms of EGFR in 556 resected lung cancers and corresponding non-malignant lung tissues from 336 East Asians, 213 individuals of Northern European descent, and seven of other ethnicities. We also studied the EGFR gene in 93 corresponding non-malignant lung tissue samples from European-descent patients from Italy and in peripheral blood mononuclear cells from 250 normal healthy US individuals enrolled in epidemiological studies including individuals of European descent, African-Americans, and Mexican-Americans. We sequenced the four exons (18-21) of the TK domain known to harbor activating mutations in tumors and examined the status of the CA-SSR1 alleles (presence of heterozygosity, repeat number of the alleles, and relative amplification of one allele) and allele-specific amplification of mutant tumors as determined by a standardized semiautomated method of microsatellite analysis. Variant forms of SNP -216 (G/T or T/T) and SNP -191 (C/A or A/A) (associated with higher protein production in experimental systems) were less frequent in East Asians than in individuals of other ethnicities (p < 0.001). Both alleles of CA-SSR1 were significantly longer in East Asians than in individuals of other ethnicities (p < 0.001). Expression studies using bronchial epithelial cultures demonstrated a trend towards increased mRNA expression in cultures having the variant SNP -216 G/T or T/T genotypes. Monoallelic amplification of the CA-SSR1 locus was present in 30.6% of the informative cases and occurred more often in individuals of East Asian ethnicity. AI was present in 44.4% (95% confidence interval: 34.1%-54.7%) of mutant tumors compared with 25.9% (20.6%-31.2%) of wild-type tumors (p = 0.002). The shorter allele in tumors with AI in East Asian individuals was selectively amplified (shorter allele dominant) more often in mutant tumors (75.0%, 61.6%-88.4%) than in wild-type tumors (43.5%, 31.8%-55.2%, p = 0.003). In addition, there was a strong positive association between AI ratios of CA-SSR1 alleles and AI of mutant alleles. Conclusions: The three polymorphisms associated with increased EGFR protein production (shorter CA-SSR1 length and variant forms of SNPs -216 and -191) were found to be rare in East Asians as compared to other ethnicities, suggesting that the cells of East Asians may make relatively less intrinsic EGFR protein. Interestingly, especially in tumors from patients of East Asian ethnicity, EGFR mutations were found to favor the shorter allele of CA-SSR1, and selective amplification of the shorter allele of CA-SSR1 occurred frequently in tumors harboring a mutation. These distinct molecular events targeting the same allele would both be predicted to result in greater EGFR protein production and/or activity. Our findings may help explain to some of the ethnic differences observed in mutational frequencies and responses to TK inhibitors. © 2007 Nomura et al.

A double-blind placebo-controlled randomized study of Chinese herbal medicine as complementary therapy for reduction of chemotherapy-induced toxicity - Mok, T.S.K.; Yeo, W.; Johnson, P.J.; Hui, P.; Ho, W.M.; Lam, K.C.; Xu, M.; Chak, K.; Chan, A.; Wong, H.; Mo, F.; Zee, B. (Annals of Oncology, 2007)
Background: Chinese herbal medicine (CHM) is a common complementary therapy used by patients with cancer for reduction of chemotherapy-induced toxic effects. This study applied the highest standard of clinical trial methodology to examine the role of CHM in reducing chemotherapy-induced toxicity, while maintaining a tailored approach to therapy. Patients and methods: Patients with early-stage breast or colon cancer who required postoperative adjuvant chemotherapy were eligible for the study. Enrolled patients were randomly assigned to one of three Chinese herbalists who evaluated and prescribed a combination of single-item packaged herbal extract granules. Patients received either CHM or placebo packages with a corresponding serial number. The placebo package contained nontherapeutic herbs with an artificial smell and taste similar to a typical herbal tea. The primary end points were hematologic and non-hematologic toxicity according to the National Cancer Institute Common Toxicity Criteria Version 2. Results: One hundred and twenty patients were accrued at the time of premature study termination. Patient characteristics of the two groups were similar. The incidence of grade 3/4 anemia, leukopenia, neutropenia, and thrombocytopenia for the CHM and placebo groups were 5.4%, 47.3%, 52.7%, and 1.8% and 1.8%, 32.2%, 44.7%, and 3.6%, respectively (P = 0.27, 0.37, 0.63, and 0.13, respectively). Incidence of grade 2 nausea was the only non-hematologic toxicity that was significantly reduced in the CHM group (14.6% versus 35.7%, P = 0.04). Conclusions: Traditional CHM does not reduce the hematologic toxicity associated with chemotherapy. CHM, however, does have a significant impact on control of nausea. © 2007 Oxford University Press.
Keywords: Alternative and complementary medicine; Chemotherapy; Chinese herbal medicine; Colonic neoplasms; Emesis; Toxicity

Participation in surgical oncology clinical trials: Gender-, race/ethnicity-, and age-based disparities - Stewart, J.H.; Bertoni, A.G.; Staten, J.L.; Levine, E.A.; Gross, C.P. (Annals of Surgical Oncology, 2007)
Objective: To characterize the representation of racial/ethnic minorities, women, and older persons among participants in surgical trials sponsored by the National Cancer Institute (NCI). Methods: The NCI Clinical Trial Cooperative Group surgical oncology trials database was queried for breast, colorectal, lung, and prostate cancers treated during the period 2000-2002 (n=13,991). Data from the SEER program and the Census were used to estimate age-, gender-, and race/ethnicity-specific incidence of the same cancers among U.S. adults during the same period. Enrollment fraction (EF), defined as the number of trial enrollees divided by the estimated U.S. cancer cases in each demographic group, was the primary outcome measure. Logistic regression was used to compare the enrollment of racial/ethnic, gender and age subgroups in this analysis. Results: Relative to white patients (EF=0.72%), lower EFs were noted in African-American (0.48%, odds ratio[OR] vs whites 0.67, P<0.001), Hispanic (0.54%, OR 0.76, P<0.001), and Asian/Pacific islander (0.59%, OR 0.82, P=0.001) patients. Overall, women were more likely to enroll in surgical trials (1.12%) than men (0.22%, OR 5.06, P<0.001). Patients 65-74 years of age (EF 0.45%) were less likely to be enrolled than those 20-44 years of age (EF=2.28%, OR 0.20, P=0.001). Conclusions: The enrollment in surgical oncology trials is very low across all demographics. However, racial/ethnic minorities and older persons are less likely to be enrolled in cooperative group surgical oncology trials than are whites and younger patients. The high EF for women is due to the high availability of trials for women with breast cancer. Strategies to increase accrual to surgical trials and ameliorate disparities related to race/ethnicity, gender, and age are needed. © 2007 The Society of Surgical Oncology, Inc.
Keywords: African-Americans; Asian/Pacific Islander; Breast cancer; Clinical trials; Colorectal cancer; Disparities; Enrollment fraction; Hispanics; Lung cancer; Native Americans; Prostate cancer

Menthol cigarettes and health risks in Lung Health Study data - Murray, R.P.; Connett, J.E.; Skeans, M.A.; Tashkin, D.P. (Nicotine and Tobacco Research, 2007)
Whether menthol cigarettes confer a higher risk of death than plain cigarettes is not known. The Lung Health Study (LHS) enrolled 5,887 adult smokers in a clinical trial of smoking cessation and ipratropium in the prevention of chronic obstructive pulmonary disease. LHS participants have been subjected to surveillance for mortality from all causes for 14 years. We examined these data for differences between self-reported smokers of menthol cigarettes versus plain cigarettes. Using proportional hazards regression methods, we found no differences in hazard ratios for coronary heart disease, cardiovascular disease, lung cancer, or death from any cause. Contrary to expectations about nicotine dependence, we found that users of menthol cigarettes had smoked fewer pack-years at baseline. We found no difference in success at smoking cessation with or without menthol. We conclude that our data contain no evidence that mentholation of cigarettes increases the hazards of smoking.

Are tri-ethnic low-income women with breast cancer effective teachers of the importance of breast cancer screening to their first-degree relatives? Results from a randomized clinical trial - Oleske, D.M.; Galvez, A.; Cobleigh, M.A.; Ganschow, P.; Ayala, L.D. (Breast Journal, 2007)
The purpose of this study was to determine the efficacy of women with breast cancer as teachers of the importance of breast cancer screening to their first-degree female relatives. The sample was restricted to low-income working age women recruited from four hospitals. The study design was a randomized clinical trial. At each hospital, breast cancer patients (probands) were randomized into one of two study groups: (i) intensive, individual educational training on breast cancer screening or (ii) standard clinic education on breast cancer screening. The probands were instructed to teach at least one of their first-degree female relatives (21+ years of age) about breast cancer screening techniques. Three to six months after the enrollment of the probands, their relatives were contacted by telephone to determine breast cancer screening practices. A total of 79 probands and 96 relatives participated in the study. Relatives in the education group when compared with the control group were: 1.25 times more likely to have clinical breast examination (p = 0.005), 2.83 times more likely to have scheduled a clinical breast examination (p = 0.046), and, 1.36 times more likely to have been told about performing breast self-examination (p = 0.05). Additionally, relatives in the education group were more likely to have received a pamphlet on breast cancer screening (RR = 1.58, p = 0.009) and have discussed the importance of breast cancer screening (RR = 1.33, p = 0.020) from the proband. Special education training did not impact mammography utilization of the relatives. From these findings, a tri-ethnic group of low-income women with breast cancer can be effective teachers of breast cancer screening practices, at least for promoting clinical breast examination and transmitting messaging for performance of breast self-examination if given the adequate training. © 2007, Copyright the Authors.
Keywords: African-Americans; Breast cancer screening; Breast screening education; Latinos; Low income women; Minority women; Randomized clinical trial

The influence of race on the attitudes of radiation oncology patients towards clinical trial enrollment - Wood, C.G.; Wei, S.J.; Hampshire, M.K.; Devine, P.A.; Metz, J.M. (American Journal of Clinical Oncology: Cancer Clinical Trials, 2006)
OBJECTIVES: Enrollment of adult cancer patients in clinical trials remains low, particularly in the minority population. Understanding patient attitudes towards clinical trials during the recruitment process may enhance accrual. Unfortunately, data describing patient attitudes towards clinical trials are limited, particularly in the radiation oncology clinic setting. METHODS: A piloted questionnaire assessing basic demographics and attitudes toward clinical trials was offered in 2 radiation oncology clinics between April 2003 and October 2003. The questionnaire was completed by 166 patients. The mean age of the patients completing the questionnaire was 56 years (range, 15-84 years). Of the 166 patients included in the analysis, 108 (65%) were White. The most common cancer diagnoses included prostate (19%), head and neck (16%), and breast (14%). RESULTS: There was no statistical difference between Whites and non-Whites regarding their interest in learning about clinical trials (84.3% versus 84.9%, P = 0.92); nor was there a significant difference in the rate of previous or current trial enrollment (21.3% versus 34.0%, P = 0.08). White patients were more likely to gather information about clinical trials from the Internet (30.6% versus 11.3%, P = 0.007), and they were more likely to use physicians as a source of this information (50.0% versus 34.0%, P = 0.05). Non-White patients were more likely to obtain information about clinical trials from other patients (24.5% versus 12.0%, P = 0.04). In addition, more non-White patients believed they had been treated on clinical trials without their knowledge (21.6% versus 9.3%, P = 0.032). Patients differed somewhat in their expectations of clinical trials. More non-Whites indicated that they would need a >50% chance of benefiting from a trial (64.4% versus 45.0%, P = 0.03) to enroll on that trial, though there were no statistical differences in outlook towards potential toxicities associated with treatment on a clinical trial. CONCLUSIONS: Minority patients historically enroll in clinical trials at a significantly lower rate. Our study of radiation oncology patients documents significant differences in attitudes towards clinical trials between Whites and non-Whites. Understanding the differences in attitudes may allow physicians to overcome barriers that would otherwise hinder the enrollment of non-White patients into clinical trials. © 2006 Lippincott Williams & Wilkins, Inc.
Keywords: Attitude; Clinical trials; Neoplasms; Population groups; Radiation

Family history, perceived risk, and prostate cancer screening among African American men - Bloom, J.R.; Stewart, S.L.; Oakley-Girvans, I.; Banks, P.J.; Chang, S. (Cancer Epidemiology Biomarkers and Prevention, 2006)
Background: Many African American men have two major risk factors for prostate cancer. By ethnicity alone, they have twice the risk of Euro-American men of developing prostate cancer. Having a family history (brother or father with prostate cancer) also doubles their risk. The major hypotheses tested in this study are that men with a family history perceive their risk to be higher, are more worried about getting prostate cancer, and are more likely to have used cancer screening tests than men without such a history. Methods: A sample of 208 African American men, ages 40 to 74 years, were recruited through relatives or friends whose prostate cancer diagnosis was reported to the California Cancer Registry during the years 1997 to 2001 and from churches and African American social groups. Following a screening interview to determine eligibility, 88 men with self-reported, first-degree family history of prostate cancer and 120 without such history were interviewed by telephone. Logistic regression was used to create models of perceived risk, prostate cancer worries, receipt of a digital rectal exam, and/or prostate-specific antigen (PSA) testing. Results: Men with a self-reported family history of prostate cancer did not perceive their risk as higher than men without a family history, nor did they report more cancer worries. They were more likely to report having a recent PSA test, but not a digital rectal exam. Having a higher than average perceived risk was associated with younger age, a college education, and lower mental well-being, and reporting more prostate cancer worries and being more likely to have had a recent PSA test. Conclusions: Although there continues to be controversy about PSA testing, these data suggest that African American men at above-average risk are inclined to be screened. Copyright © 2006 American Association for Cancer Research.

Clinical trial resources on the internet must be designed to reach underrepresented minorities - Wilson, J.J.; Mick, R.; Wei, S.J.; Rustgi, A.K.; Markowitz, S.D.; Hampshire, M.; Metz, J.M. (Cancer Journal, 2006)
PURPOSE: Internet-based clinical trial information services are being developed to increase recruitment to studies. However, there are limited data that evaluate their ability to reach elderly and underrepresented minority populations. This study was designed to evaluate the ability of an established clinical trials registry to reach these populations based on expected Internet use. PATIENTS AND METHODS: This study compares general Internet users to participants who enrolled in an Internet based colorectal cancer clinical trials registry established by OncoLink (www.oncolink.org) and the National Colorectal Cancer Research Alliance. Observed rates of demographic groupings were compared to those established for general Internet users. RESULTS: Two thousand, four hundred and thirty-seven participants from the continental United States used the Internet to register for the database. New England, the Mid-Atlantic region, and the Southeast had the highest relative frequency of participation in the database, whereas the Upper Midwest, California, and the South had the lowest rates. Compared to general Internet users, there was an overrepresentation of women (73% vs. 50%) and participants over 55 years old (27% vs. 14%). However, there was an underrepresentation of minorities (10.3% vs. 22%), particularly African Americans (3.1% vs. 8%) and Hispanics (2.8% vs. 9%). DISCUSSION: The Internet is a growing medium for registry into clinical trials databases. However, even taking into account the selection bias of Internet accessibility, there are still widely disparate demographics between general Internet users and those registering for clinical trials, particularly the underrepresentation of minorities. Internet-based educational and recruitment services for clinical trials must be designed to reach these underrepresented minorities to avoid selection biases in future clinical trials. Copyright © 2006 Jones and Bartlett Publishers, Inc.
Keywords: Age; Clinical trial; Colorectal neoplasms; Continental population groups; Internet; Race; Sex

Phase II study of carboplatin, irinotecan, and thalidomide in patients with advanced non-small cell lung cancer - Miller, A.A.; Case, D.; Atkins, J.N.; Giguere, J.K.; Bearden, J.D. (Journal of Thoracic Oncology, 2006)
BACKGROUND: We hypothesized that thalidomide would improve the response and toxicity profile of chemotherapy with carboplatin and irinotecan. METHODS: The key eligibility criteria were stage IIIB (malignant pleural effusion) and IV non-small cell lung cancer, measurable disease, no prior chemotherapy, prior radiation only for brain metastasis, performance status 0 or 1, and adequate hematologic, hepatic, and renal function. Treatment consisted of carboplatin at a calculated area under the curve of 5 and infused intravenously for 30 min on day 1 and irinotecan (50 mg/m intravenously for 90 min on days 1 and 8 every 21 days). Thalidomide was given orally every evening starting on day 1 until progressive disease; the starting dose was 200 mg per day, which was escalated by 100 mg per week if tolerated (maximum 1000 mg per day). The objectives were to determine the response rate, time to progression, overall survival, and toxicity profile. RESULTS: In all, 46 patients were enrolled, but three who never received protocol treatment were excluded from the analysis. The characteristics of the 43 eligible and treated patients included median age 63 (47-79), female/male 13/30, black/white 3/40, PS 0/1 in 10/33, and stage 3/4 in 6/37. The objective response rates were complete response 1 (2%), partial response 5 (12%), stable disease 24 (56%), progressive disease 9 (21%), and unevaluable for response 4 (9%). The median time to progression was 3.7 months (95% confidence interval [CI], 2.5-4.9). The median survival time was 8.1 months (95% CI, 5.0-12.9). Frequent toxicities were neutropenia, fatigue/malaise, and nausea/vomiting. Diarrhea was uncommon and mild. CONCLUSIONS: This treatment regimen of carboplatin, irinotecan, and thalidomide was tolerable, with reversible neutropenia as the major toxicity and only minor diarrhea. The overall response rate did not meet our predetermined level of efficacy to merit further investigation. © 2006International Association for the Study of Lung Cancer.
Keywords: Carboplatin; Irinotecan; Non-small cell lung cancer; Phase II; Thalidomide

Accreditation and quality assurance for Radiation Therapy Oncology Group: Multicenter clinical trials using Stereotactic Body Radiation Therapy in lung cancer - Timmerman, R.; Galvin, J.; Michalski, J.; Straube, W.; Ibbott, G.; Martin, E.; Abdulrahman, R.; Swann, S.; Fowler, J.; Choy, H. (Acta Oncologica, 2006)
Starting in 2002, the Radiation Therapy Oncology Group in North America began the process of developing multicenter prospective trials in lung cancer using Stereotactic Body Radiation Therapy (SBRT). Much of the work was based on the prospective single institution trials from Indiana University that had been presented and published. In late 2004, RTOG 0236 using SBRT for medically inoperable patients with clinical stage I non-small cell lung cancer (NSCLC) was activated for accrual. Prior to activation, representatives from the Lung, Image-Guided Therapy, Physics, and Radiobiology Committees met on regular occasions to design the multicenter study and quality assurance measures. SBRT is not a black box, and the essence of the therapy had to be distilled via guidelines. Issues related to patient selection, method of dosimetry construction, equipment requirements, motion assessments and control, site accreditation, data exchange, and follow-up policies were worked out by compromise and consensus. RTOG 0236 has nearly completed its accrual. The Lung Committee has initiated the development of several other trials, each building on the last, to investigate the therapy in central tumors, in combinations with systemic therapy, in operable patients, and in lung metastases patients. The guidelines developed for RTOG 0236 will be refined to take advantage of more modern innovations including heterogeneity corrections and intensity modulation when appropriate. The development of RTOG 0618 using SBRT in operable patients with early stage NSCLC is a testament to both the enthusiasm from already published works and prospective multicenter clinical testing using SBRT techniques. © 2006 Taylor & Francis.

Ovarian volume: Determinants and associations with cancer among postmenopausal women - Sherman, M.E.; Lacey, J.V.; Buys, S.S.; Reding, D.J.; Berg, C.D.; Williams, C.; Hartge, P. (Cancer Epidemiology Biomarkers and Prevention, 2006)
Clinical studies have reported associations between ovarian stromal hyperplasia and the diagnosis of hormonally related tumors such as endometrial cancer. To assess the hypothesis that characteristics of benign ovaries among postmenopausal women are related to risk for breast, endometrial, and colon cancer, we analyzed systematically collected transvaginal ultrasound data for participants enrolled in the screening arm of the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. Among women without cancer, median ovarian volume declined with age from 1.25 cm3 for women between ages 55 and 59 years to 1.0 cm3 for those between ages 65 and 69 years. African American and Caucasian women had larger median ovarian volumes than Asians. Larger ovarian volume was also associated with the highest quartiles of height and weight and ever having smoked. After adjusting for race, age, parity, body mass, smoking, and hormone use, women with median ovarian volumes ≥3.0 cm3 were at increased risk for breast cancer [odds ratio (OR), 1.42; 95% confidence interval (95% CI), 1.11-1.70], endometrial cancer (OR, 1.97; 95% CI, 1.12-3.48), and colon cancer (OR, 2.00; 95% CI, 1.25-3.21). Significant trends of risk with increasing volume were found only for breast and endometrial cancers. We conclude that large ovaries among postmenopausal women may represent a marker of risk for hormonally related tumors. Confirmation of these findings in future studies, including analyses of serum hormone levels and tissues, may provide insights into hormonal carcinogenesis among older women. Copyright © 2006 American Association for Cancer Research.

Breast cancer patients' attitudes toward clinical trials in the radiation oncology clinic versus those searching for trial information on the internet - Dolinsky, C.M.; Wei, S.J.; Hampshire, M.K.; Metz, J.M. (Breast Journal, 2006)
Web-based clinical trials matching systems including breast cancer patients are expanding rapidly. However, limited data exist regarding the demographics and attitudes of breast cancer patients using the Internet to search for clinical trials information. Biases in patient populations could be introduced by recruiting patients to trials through the Internet. This study was designed to compare breast cancer patients in the radiation oncology clinic to those using the Internet to search for clinical trials information. A piloted questionnaire assessing demographics and attitudes regarding clinical trials was offered through the radiation oncology clinic at the University of Pennsylvania and on the OncoLink website (www.oncolink.org). The questionnaire consisted of 18 questions and was answered by a total of 157 patients with breast cancer. Breast cancer patients using the Web were more likely to be interested in clinical trials testing new drugs or therapies (71 [53%] versus 4 [17%], p = 0.002). More clinic patients indicated they would need a greater than 50% chance of benefiting from a trial (12 [52%] versus 33 [25%], p = 0.01) and a less than 10% potential for serious toxicity from a trial (15 [65%] versus 51 [38%], p = 0.02) for consideration of enrollment. African Americans were more likely than other races to have never used the Internet to search for cancer-related information (4 [40%] versus 18 [12%], p = 0.01), more likely to indicate that they need a greater than 50% chance of benefit to enroll in clinical trials (8 [80%] versus 37 [25%], p = 0.001), and less likely to be interested in clinical trials testing new drugs or therapies (1 [10%] versus 73 [50%], p = 0.01). Breast cancer patients have different attitudes regarding clinical trials based on race, Internet usage, and previous trial enrollment. Biases may be introduced with recruitment for clinical trials through the Internet. Radiation oncologists must consider these issues when offering clinical trials information through the Internet. © 2006 Blackwell Publishing, Inc.
Keywords: Breast cancer; Clinical trials; Internet; Race; Radiation therapy

The effects of oral Cardax™ (disodium disuccinate astaxanthin) on multiple independent oxidative stress markers in a mouse peritoneal inflammation model: influence on 5-lipoxygenase in vitro and in vivo - Lockwood, S.F.; Penn, M.S.; Hazen, S.L.; Bikádi, Z.; Zsila, F. (Life Sciences, 2006)
Disodium disuccinate astaxanthin ('rac'-dAST; Cardax™) is a water-dispersible C40 carotenoid derivative under development for oral and parenteral administration for cardioprotection of the at-risk ischemic cardiovascular patient. In experimental infarction models in animals (rats, rabbits, and dogs), significant myocardial salvage has been obtained, up to 100% at the appropriate dose in dogs. The documented mechanism of action in vitro includes direct scavenging of biologically produced superoxide anion; in vivo in rabbits, modulation of the complement activity of serum has also been shown. A direct correlation between administration of the test compound in animals and reductions of multiple, independent markers of oxidative stress in serum was recently obtained in a rat experimental infarction model. For the current study, it was hypothesized that oral Cardax™ administration would inhibit oxidative damage of multiple relevant biological targets in a representative, well-characterized murine peritoneal inflammation model. A previously developed mass spectrometry-based (LC/ESI/MS/MS) approach was used to interrogate multiple distinct pathways of oxidation in a black mouse (C57/BL6) model system. In vivo markers of oxidant stress from peritoneal lavage samples (supernatants) were evaluated in mice on day eight (8) after treatment with either Cardax™ or vehicle (lipophilic emulsion without drug) orally by gavage at 500 mg/kg once per day for seven (7) days at five (5) time points: (1) baseline prior to treatment (t = 0); (2) 16 h following intraperitoneal (i.p.) injection with thioglycollate to elicit a neutrophilic infiltrate; (3) 4 h following i.p. injection of yeast cell wall (zymosan; t = 16 h/4 h thioglycollate + zymosan); (4) 72 h following i.p. injection with thioglycollate to elicit monocyte/macrophage infiltration; and (5) 72 h/4 h thioglycollate + zymosan. A statistically significant sparing effect on the arachidonic acid (AA) and linoleic acid (LA) substrates was observed at time points two and five. When normalized to the concentration of the oxidative substrates, statistically significant reductions of 8-isoprostane-F2α (8-iso-F2α) at time point three (maximal neutrophil recruitment/activation), and 5-HETE, 5-oxo-EET, 11-HETE, 9-HODE, and PGF2α at time point five (maximal monocyte/macrophage recruitment/activation) were observed. Subsequently, the direct interaction of the optically inactive stereoisomer of Cardax™ (meso-dAST) with human 5-lipoxygenase (5-LOX) was evaluated in vitro with circular dichroism (CD) and electronic absorption (UV/Vis) spectroscopy, and subsequent molecular docking calculations were made using mammalian 15-LOX as a surrogate (for which XRC data has been reported). The results suggested that the meso-compound was capable of interaction with, and binding to, the solvent-exposed surface of the enzyme. These preliminary studies provide the foundation for more detailed evaluation of the therapeutic effects of this compound on the 5-LOX enzyme, important in chronic diseases such as atherosclerosis, asthma, and prostate cancer in humans. © 2006 Elsevier Inc. All rights reserved.
Keywords: 5-Lipoxygenase; Astaxanthin; Cardax™; Carotenoids; Disodium disuccinate astaxanthin; HETEs; HODEs; Inflammation; LC/ESI/MS/MS; Oxidative stress

Health parties for African American study recruitment - Sadler, G.R.; York, C.; Madlensky, L.; Gibson, K.; Wasserman, L.; Rosenthal, E.; Barbier, L.; Newman, V.A.; Tso, C. (Journal of Cancer Education, 2006)
Innovative strategies are needed to increase minorities' research participation. Using existing social networks within the African American community, "home health parties" were tested as a way to recruit African American women to a breast cancer control study. Parties included social, educational, and recruitment components. All women attending health parties consented, completed a survey, and received the study's preliminary breast cancer risk assessment. There were no differences in rates of participation for subsequent study components between women recruited via parties versus other methods. Health parties are viable recruitment strategies, reduce barriers to participation, provide a supportive environment, and are relatively inexpensive.

Breast biopsy and race/ethnicity among women without breast cancer - Jacobson, J.S.; Grann, V.R.; Hershman, D.; Troxel, A.B.; Li, H.; Neugut, A.I. (Cancer Detection and Prevention, 2006)
Background: Breast biopsy is essential for definitive breast cancer diagnosis, but may also play a role in determining eligibility for breast cancer preventive measures or clinical trials. In addition, the prevalence of a history of negative breast biopsy can be viewed as an indicator of the adequacy or intensity of health care in a given population. We therefore analyzed the association of a history of breast biopsy with race/ethnicity and other factors in a cohort of women without a cancer diagnosis who completed a risk assessment form for participation in the Study of Tamoxifen and Raloxifene (STAR) and a sociodemographic questionnaire. Methods: Subjects were recruited at our large, urban teaching hospital. We developed a logistic regression model with biopsy (ever/never) as the outcome and age, race/ethnicity, educational attainment, and insurance coverage as the independent variables. Results: Among 805 unaffected predominantly minority subjects, white women were more than three times as likely as black and Hispanic women (OR = 3.3, 95% CI 1.9-5.9), and insured women were twice as likely as uninsured women (OR = 2.0, 95% CI 1.4-2.9) to have had a biopsy. Biopsy results were also associated with race/ethnicity. Discussion: We view these observations as hypothesis-generating rather than definitive. If confirmed, the associations we observed between negative biopsies and insurance status may reflect disparities in the timeliness and effectiveness of follow-up of suspicious lesions found via mammography. Our findings may also be relevant to the well-known association of breast cancer stage at diagnosis with low income and minority race/ethnicity. © 2006 International Society for Preventive Oncology.
Keywords: Biopsy; Breast cancer; Disparities; Hyperplasia; Insurance; Locular carcinoma in situ; Mammography; National Surgical Adjuvant Breast and Bowel Project; NSABP; Prevention; Race/ethnicity; Raloxifene; Risk assessment; STAR trial; Survival; Tamoxifen

Psychosocial factors related to repeat mammography screening over 5 years in African American women - Russell, K.M.; Champion, V.L.; Skinner, C.S. (Cancer Nursing, 2006)
The purpose of this study was to investigate health beliefs associated with repeat mammography screening in African American women 51 years or older over a 5-year period. Long-term repeat mammography screening is inconsistent in African American women; therefore, this study measured demographic, knowledge, and health belief predictors of repeat screening. The theoretical framework for this study was the health belief model. Baseline data from a larger randomized controlled trial were analyzed using descriptive statistics and logistic regression. The sample consisted of 602 African American women with no breast cancer history and at least 1 reported screening mammogram in the past 5 years. They were recruited from 3 primary care health settings. Having been screened 4 to 5 times in the past 5 years was associated with more knowledge about screening guidelines and fewer perceived barriers to screening. Results point to the importance of collaborating with African American communities to promote life-long mammography screening by increasing access to culturally appropriate information on screening guidelines and ameliorating barriers to screening within the context of the African American experience. © 2006 Lippincott Williams & Wilkins, Inc.
Keywords: African American; Blacks; Health beliefs; Mammography screening

Randomized trial of peer counseling on reproductive health in African American breast cancer survivors - Schover, L.R.; Jenkins, R.; Sui, D.; Adams, J.H.; Marion, M.S.; Jackson, K.E. (Journal of Clinical Oncology, 2006)
Purpose: We designed a peer counseling program to improve sexual function, increase knowledge about reproductive health, and decrease menopausal symptoms and infertility-related distress for African American breast cancer survivors. Patients and Methods: Women were randomly assigned to immediate counseling or a 3-month waitlist. Three peer counselors conducted a 3-session intervention using a detailed workbook. Questionnaires at baseline, after the waitlist period, at posttreatment, and at 3-month follow-up assessed spirituality, sexual function, menopause symptoms, emotional distress, relationship satisfaction, fertility concerns, and knowledge about reproductive health and breast cancer. At the postcounseling assessment, women rated the workbook, their counselor, and the program. Results: Of 93 women screened, 60 women (65%) enrolled in the study. Women who completed counseling (80%; N = 48) had a mean age of 49 years (standard deviation [SD], 8 years) and a mean follow-up of 4.5 years (SD, 3.8 years) since cancer diagnosis. Almost all rated the workbook as very easy to understand (94%) and their counselor as very knowledgeable (96%) and very skillful (98%). Eighty-one percent rated the program as "very useful to me." Immediate counseling and waitlist groups did not differ at baseline in psychologic adjustment, nor did scores change during the waitlist period. Therefore, the groups were combined in analyzing outcomes. Knowledge of reproductive issues improved significantly from baseline to 3-month follow-up (P < .0001), as did emotional distress (P = .0047) and menopause symptoms (P = .0128). Sexually dysfunctional women became less distressed (P = .0167). Conclusion: Women valued the Sisters Peer Intervention in Reproductive Issues After Treatment program highly and found it relevant. The program had positive effects on knowledge and target symptoms. © 2006 by American Society of Clinical Oncology.

Cancer prevention trials and primary care physicians: Factors associated with recommending trial enrollment - Battaglia, T.A.; Ash, A.; Prout, M.N.; Freund, K.M. (Cancer Detection and Prevention, 2006)
Background: To explore the willingness of primary care providers (PCPs) to encourage enrollment of patients into cancer prevention trials. Methods: A self-administered survey was mailed to a random sample of PCPs in three geographic regions. Physicians were asked questions about their knowledge and attitudes towards cancer prevention trials. We presented a clinical vignette of a woman at high risk for breast cancer and asked if they would encourage her enrollment into a breast cancer chemoprevention trial (yes/no). Each survey included one of 16 possible clinical vignettes where patient characteristics (age, race socioeconomic status, physical mobility and co-morbidity) varied dichotomously. Bivariate analyses and logistic models were used to examine the independent effects of patient and physician characteristics on physician decisions. Results: Two hundred and sixty-six surveys (50% response) were analyzed. The mean age of respondents was 48; 54% were White, 35% Asian and 5% Black. By design physicians were evenly distributed by gender, specialty and geographic location. Overall, 53% would encourage enrollment into a breast cancer chemoprevention trial. Significant predictors of a recommendation to enroll were: geographic location in California or Georgia, younger vignette patient and anticipating an increase in patient trust after recommending enrollment. Conclusion: PCPs are less likely to encourage elderly patients to enroll into cancer chemoprevention trials. Decisions differ based on geographic location and perceived trust in the patient-provider relationship. To achieve successful enrollment, trial investigators must continue to educate PCPs and ensure a strong PCP-patient relationship is maintained. © 2005 International Society for Preventive Oncology. Published by Elsevier Ltd. All rights reserved.
Keywords: Breast neoplasms; Chemoprevention; Clinical trials; Decision making; Experimental design; High-risk patients; Patient-provider relationship; Prevention trials; Primary care providers; Primary prevention; Regional variability; Response rate; Tamoxifen

Are racial and ethnic minorities less willing to participate in health research? - Wendler, D.; Kington, R.; Madans, J.; Van Wye, G.; Christ-Schmidt, H.; Pratt, L.A.; Brawley, O.W.; Gross, C.P.; Emanuel, E. (PLoS Medicine, 2006)
Background: It is widely claimed that racial and ethnic minorities, especially in the US, are less willing than non-minority individuals to participate in health research. Yet, there is a paucity of empirical data to substantiate this claim. Methods and Findings: We performed a comprehensive literature search to identify all published health research studies that report consent rates by race or ethnicity. We found 20 health research studies that reported consent rates by race or ethnicity. These 20 studies reported the enrollment decisions of over 70,000 individuals for a broad range of research, from interviews to drug treatment to surgical trials. Eighteen of the twenty studies were single-site studies conducted exclusively in the US or multi-site studies where the majority of sites (i.e., at least 2/3) were in the US. Of the remaining two studies, the Concorde study was conducted at 74 sites in the United Kingdom, Ireland, and France, while the Delta study was conducted at 152 sites in Europe and 23 sites in Australia and New Zealand. For the three interview or non-intervention studies, African-Americans had a nonsignificantly lower overall consent rate than non-Hispanic whites (82.2% versus 83.5%; odds ratio [OR] = 0.92; 95% confidence interval [CI] 0.84-1.02). For these same three studies, Hispanics had a nonsignificantly higher overall consent rate than non-Hispanic whites (86.1% versus 83.5%; OR = 1.37; 95% CI 0.94-1.98). For the ten clinical intervention studies, African-Americans' overall consent rate was nonsignificantly higher than that of non-Hispanic whites (45.3% versus 41.8%; OR = 1.06; 95% CI 0.78-1.45). For these same ten studies, Hispanics had a statistically significant higher overall consent rate than non-Hispanic whites (55.9% versus 41.8%; OR = 1.33; 95% CI 1.08-1.65). For the seven surgery trials, which report all minority groups together, minorities as a group had a nonsignificantly higher overall consent rate than non-Hispanic whites (65.8% versus 47.8%; OR = 1.26; 95% CI 0.89-1.77). Given the preponderance of US sites, the vast majority of these individuals from minority groups were African-Americans or Hispanics from the US. Conclusions: We found very small differences in the willingness of minorities, most of whom were African-Americans and Hispanics in the US, to participate in health research compared to non-Hispanic whites. These findings, based on the research enrollment decisions of over 70,000 individuals, the vast majority from the US, suggest that racial and ethnic minorities in the US are as willing as non-Hispanic whites to participate in health research. Hence, efforts to increase minority participation in health research should focus on ensuring access to health research for all groups, rather than changing minority attitudes. Copyright: © 2006 Wendler et al.

Predictors of enrollment in lung cancer clinical trials - Du, W.; Gadgeel, S.M.; Simon, M.S. (Cancer, 2006)
BACKGROUND. Clinical trials may offer patients innovative therapeutic options with potentially better outcomes, which are particularly relevant for patients afflicted with lung carcinoma, because current therapies provide only modest survival benefits. Only approximately 5% of patients with newly diagnosed cancer participate in clinical trials nationwide, and African-American (AA) patients are particularly under-represented. METHODS. To determine predictors of clinical trials enrollment, the authors reviewed the medical records of 427 patients with lung carcinoma (175 AA patients and 252 non-AA patients) who were eligible for clinical trials between 1994 and 1998 at the Karmanos Cancer Institute in Detroit, Michigan. Logistic regression analysis was used to assess the association of patient demographic characteristics and clinical trial enrollment. RESULTS. Ninety-one patients (21%) were enrolled onto a lung cancer clinical trial during the period of the current study. Enrollment was associated significantly with race (P < 0.001), gender (P = 0.048), age (P = 0.005), and insurance type (P = 0.024). After multivariable adjustment, only race and gender remained significant predictors of enrollment. AA patients were less likely to enroll than non-AA patients (odds ratio [OR], 0.485; 95% confidence interval [95% CI], 0.243-0.966), and men were more likely than women to enroll (OR, 1.812; 95% CI, 1.033-3.178). CONCLUSIONS. The current results suggest disparities by race and gender in the enrollment of patients onto lung cancer clinical trials and support the need to improve educational and outreach endeavors that would make clinical trials available to a wider range of eligible patients. © 2005 American Cancer Society.
Keywords: Clinical trials; Disparity; Enrollment; Lung carcinoma; Predictors

Use of the National Cancer Data Base to develop clinical trials accrual targets that are appropriate for minority ethnicity patients: A report from the American College of Surgeons Oncology Group (ACOSOG) special populations committee - Newman, L.A.; Lee, C.T.; Parekh, L.P.; Stewart, A.K.; Thomas Jr., C.R.; Beltran, R.A.; Lucci, A.; Green, B.; Ota, D.; Nelson, H. (Cancer, 2006)
BACKGROUND. Disparities in cancer outcome among different subsets of the American population related to ethnic background have been well documented. Clinical trials represent the most powerful strategy for improving cancer treatments, but racial and ethnic minority patients are frequently underrepresented among patients accrued to these protocols. Proof of comparable efficacy for a promising cancer therapy in different groups of patients requires diversity in the clinical trial populations so that study results will be generalizable. Appropriate targets for accrual of minority ethnicity patients have not previously been defined. METHODS. The National Cancer Database (NCDB) is maintained jointly by the American Cancer Society and the American College of Surgeons. Information submitted by tumor registries throughout the United States represents an estimated 70% of newly diagnosed cancer cases. The authors analyzed NCDB reports on ethnic distribution of patients with breast, prostate, nonsmall cell lung, and colorectal cancer, stratified by stage of disease at diagnosis. RESULTS. African Americans with cancer of the breast and prostate had the most notable patterns of disproportionate representation among populations with advanced-stage disease. The authors compiled a table of suggested accrual targets for selected solid-organ cancers based on NCDB stage-specific reports. CONCLUSIONS. Clinical trial results will be more meaningful if participating patients reflect the site- and stage-specific populations that are under study. The authors recommended that clinical trial investigators incorporate accrual targets for minority ethnicity populations into the study design. © 2005 American Cancer Society.
Keywords: Breast cancer; Colorectal cancer; Disease stage; Ethnicity; Minority; National Cancer Data Base; Nonsmall cell lung cancer; Prostate cancer

Enhancing adherence among older African American men enrolled in a longitudinal cancer screening trial - Ford, M.E.; Havstad, S.; Vernon, S.W.; Davis, S.D.; Kroll, D.; Lamerato, L.; Swanson, G.M. (Gerontologist, 2006)
Purpose: The purpose of this study was to enhance adherence among older (aged 55 years and older) African American men enrolled in a cancer screening trial for prostate, lung, and colorectal cancer. For this study, we defined adherence as completing the trial screenings. Design and Methods: We used a randomized trial design. Case managers contacted intervention group participants (n = 352) at least monthly by telephone and provided information and referral services. The control group included 351 participants. Results: Among participants with low income, those in the intervention group had higher screening adherence rates than did participants in the control group for (a) prostate-specific antigen test for prostate cancer (74.3% vs 53.0%, p = .001), (b) digital rectal exam for prostate cancer (66.2% vs 46.1%, p = .011), and (c) chest x-ray for lung cancer (70.9% vs 51.3%, p = .012). We found no statistically significant differences in adherence rates for flexible sigmoidoscopy screening for colorectal cancer. In contrast, among participants with moderate-to-high income, we found no statistically significant differences in adherence rates between intervention and control group participants for any of the screening tests. Implications: The case management intervention was effective in enhancing adherence among participants with the lowest income, who in many studies are the most difficult to retain. Copyright 2006 by The Gerontological Society of America.
Keywords: African American men; Cancer screening; Case management

Intentions to participate in genetics research among African American smokers - Halbert, C.H.; Gandy Jr., O.H.; Collier, A.; Shaker, L. (Cancer Epidemiology Biomarkers and Prevention, 2006)
Although prior studies have shown that African American smokers are likely to carry some of the genetic variants associated with smoking risk, additional research with African American smokers is needed to replicate these findings. Limited information is available on interest in participating in research to identify genetic risk factors for smoking among African American smokers; therefore, the goals of the present study were to describe intentions to participate in smoking and genetics research, and to determine factors that are associated with participation intentions. Subjects were 128 African American male and female adult smokers. Sociodemographic characteristics, clinical factors, attitudes about genetic testing, and intentions to participate in genetics research were evaluated during a structured telephone interview. Overall, 58% of respondents reported that they would be very likely to participate in research to identify genetic risk factors for smoking. Greater beliefs about the benefits of participating in medical research (odds ratio, 3.17; 95% confidence interval, 1.45-6.94; P = 0.004) and fewer perceptions of the limitations and risks of genetic testing (odds ratio, 0.90; 95% confidence interval, 0.82-0.98; P = 0.01) had significant independent associations with reporting a high likelihood of participating in this type of research. Recruitment messages and protocols that address the benefits of research participation, as well as concerns about the limitations and risks of genetic testing, may enhance African American participation in research on genetics and smoking. Copyright © 2006 American Association for Cancer Research.

Impact of the year 2000 medicare policy change on older patient enrollment to cancer clinical trials - Unger, J.M.; Coltman Jr., C.A.; Crowley, J.J.; Hutchins, L.F.; Martino, S.; Livingston, R.B.; Macdonald, J.S.; Blanke, C.D.; Gandara, D.R.; Crawford, E.D.; Albain, K.S. (Journal of Clinical Oncology, 2006)
Purpose: A prior analysis by the Southwest Oncology Group (SWOG) showed that women and African American patients were adequately represented on cancer clinical treatment trials but that older patients were substantially underrepresented. Twenty-five percent of patients ≥ 65 years old were enrolled onto SWOG trials from 1993 to 1996, whereas 63% of all patients with cancer were ≥ 65 years old. Recognition of this under-representation led to a change in Medicare policy in 2000 to include coverage of routine patient care costs of clinical trials. We conducted an updated analysis of accrual trends. Methods: The proportions of enrollment onto SWOG treatment trials by sex, race/ethnicity, and age (≥ 65 years) were computed for the years 1997 to 2000; corresponding rates in the United States were derived from US Census and National Cancer Institute Surveillance, Epidemiology, and End Results data. Additionally, method of payment data were analyzed over time (1993 to 2003) to assess whether patterns in method of payment changed with the new Year 2000 Medicare policy on clinical trials coverage. Results: The results showed continued adequate representation by sex and race/ethnicity. Older patient accrual on SWOG trials increased significantly since 2000, with 31 % of patients ≥ 65 years old enrolled from 1997 to 2000 and 38% enrolled from 2001 to 2003 (v 25% from 1993 to 1996). The percentage of patients using Medicare plus supplemental insurance also increased beginning in 2000, whereas the percentage of patients using Medicare alone remained the same. Conclusion: Method of payment analyses provided evidence that the Year 2000 Medicare policy change had a positive impact, but only for those patients with supplemental private coverage of coinsurance costs. Improvements in the Medicare payment structure could further increase older patient participation in clinical trials. © 2006 by American Society of Clinical Oncology.

Factors affecting older African American women's decisions to join the PLCO cancer screening trial - Trauth, J.M.; Jernigan, J.C.; Siminoff, L.A.; Musa, D.; Neal-Ferguson, D.; Weissfeld, J. (Journal of Clinical Oncology, 2005)
Purpose: The purpose of this study is to describe the factors associated with the decisions of older African American women to join the PLCO (Prostate, Lung, Colorectal and Ovarian) Cancer Screening Trial when recruited. Methods: African American women between ages 55 and 74 years who were never diagnosed with a PLCO cancer were eligible for our study. Two methods of recruitment were used. First, mailings were sent to a random sample of women describing the PLCO followed by a telephone call to determine interest in the PLCO. If women were not interested in PLCO but consented to participate in our study, they were interviewed immediately. Second, we followed up with African American women who responded to mass mailings sent out before the start of our study by the Pittsburgh PLCO office. Women completed an interview about their cancer and clinical trial knowledge, attitudes, beliefs, and behaviors. The responses of women who joined the PLCO Trial are contrasted with the responses of women who did not join. Results: Numerous factors were associated with the decision of older African American women to join the PLCO, including perceptions of cancer prevention and detection, the experience of having a loved one with cancer, knowledge of and experience with clinical trials, and beliefs regarding the benefits and risks of clinical trial participation. Conclusion: Minority recruitment to cancer clinical trials could be increased by designing interventions focused on individual, organizational, and community needs. © 2005 by American Society of Clinical Oncology.

Recruiting African American women to participate in hereditary breast cancer research - Halbert, C.H.; Brewster, K.; Collier, A.; Smith, C.; Kessler, L.; Weathers, B.; Stopfer, J.E.; Domchek, S.; Wileyto, E.P. (Journal of Clinical Oncology, 2005)
Purpose: This study evaluated the process of recruiting African American women to participate in genetic counseling research for BRCA1 and BRCA2 (BHCA1/2) mutations with respect to referral, study enrollment, and participation in genetic counseling. Patients and Methods: African American women (n = 783) were referred for study enrollment. Results: Of 783 referrals, 164 (21%) women were eligible for enrollment. Eligible women were most likely to be referred from oncology clinics (44%) and were least likely to be referred from general medical practices (11%; χ2 = 96.80; P = .0001). Overall, 62% of eligible women enrolled onto the study and 50% of enrollees completed genetic counseling. Women with a stronger family history of cancer (odds ratio [OR] = 3.18; 95% CI, 1.36 to 7.44; P = .01) and those referred from oncology clinics and community oncology resources (OR = 2.97; 95% CI, 1.34 to 6.58; P = .01) were most likely to enroll onto the study. Referral from oncology clinics was associated significantly with participation in genetic counseling (OR = 5.46; 95% CI, 1.44 to 20.60; P = .01). Conclusion: Despite receiving a large number of referrals, only a small subset of women were eligible for enrollment. Oncology settings were the most effective at identifying eligible African American women and general medical practices were the least effective. Factors associated with enrollment included having a stronger family history of cancer and being referred from oncology clinics and community oncology resources. Referral from oncology clinics was the only factor associated significantly with participation in genetic counseling. Education about hereditary breast cancer may be needed among primary care providers to enhance appropriate referral of African American women to genetic counseling for BRCA1/2 mutations. © 2005 by American Society of Clinical Oncology.

Enrolling older persons in cancer trials: The effect of sociodemographic, protocol, and recruitment center characteristics - Gross, C.P.; Herrin, J.; Wong, N.; Krumholz, H.M. (Journal of Clinical Oncology, 2005)
Purpose: To determine the effect of patient, protocol, geographic, and institutional factors on enrollment of older persons onto cancer trials. Methods: We conducted a cross-sectional analysis of patients enrolled onto National Cancer Institute-sponsored lung, breast, colorectal, and prostate cancer trials during 1996 to 2002. We used a cross-classified logistic multilevel model to examine the associations between patient, hospital, county, and protocol characteristics, and the likelihood of participants being elderly (≥ 65 years old). Results: The final study sample consisted of 36,167 patients enrolled onto 33 trials. After accounting for cancer type, only 6% of the variation in elderly enrollment onto cancer trials was at the protocol level. In contrast, more than 55% of the variation in elderly enrollment was attributable to patient level variation. In multivariate analysis, nonwhite patients were significantly less likely to be elderly than whites (odds ratio [OR] for blacks, 0.51; 95% CI, 0.44 to 0.58; and OR for Hispanics, 0.49; 95% CI, 0.40 to 0.59 y whites). Participants living less than 7 miles from their recruitment center were significantly more likely to be elderly (OR, 1.31; 95% CI, 1.24 to 1.38). Among the 910 recruitment centers, the median adjusted proportion of patients who were elderly was 24.9% (interquartile range, 24.0% to 26.9%). There were a significantly higher number of outlier centers (≤ 20.8% or > 29.3% elderly) than would be expected by a normal distribution (68 observed v six expected; P < .0001). Conclusion: Race and proximity to trial enrollment centers were significantly related to age of trial participants after adjusting for protocol factors. Additional work should explore why some recruitment centers were outliers regarding enrollment of older persons. © 2005 by American Society of Clinical Oncology.

Nerve stimulator-guided thoracic paravertebral ropivacaine versus general anaesthesia: Effect on stress response to breast cancer surgery - Omran, A.F.; El-Sisi, A.H. (Egyptian Journal of Anaesthesia, 2005)
Background: Breast cancer surgery is usually performed under general anaesthesia (GA) and is frequently associated with postoperative nausea, vomiting and painful restricted movement of the shoulder. GA, with the exception of large doses of opioids, does not eliminate the surgical stress response. Paravertebral nerve blockade (PVB) may be an alternative to GA for this type of surgery especially in those patients with coexisting morbid diseases. However, PVB is associated with an incidence of failed black in 5-10% of cases. The aim of this study was to detect the success rate and the safety of PVB when guided by nerve stimulator and to compare the efficacy of this technique vs. GA for inhibition of surgical stress response during breast cancer surgery. Methods: Forty women were enrolled in this prospective randomized study, to receive GA (GA group; n = 20) or PVB (PVB group; n = 20) at T1-T6, using ropivacaine 0.5 % with epinephrine 1:200,000. In the PVB group, success rate and incidence of complications were recorded. In both groups, blood samples for measurement of glucose and cortisol concentrations were obtained before skin incision; 1 hour after skin incision; and at 3 and 24 hours postoperatively. Postoperative visual analogue pain scores (VAS) at rest and on moving the ipsilateral arm at predetermined time intervals postoperatively (1, 2, 6, 12 and 24 h) as well as the incidence of postoperative nausea and vomiting (PONV) throughout the 24 hours postoperatively were recorded in both groups. Results: All PVBs were successful and inadvertent complications other than hypotension (10% incidence) were not reported. There were no significant differences in the plasma glucose or cortisol concentrations between the two groups before skin incision. They were significantly lower in the PVB group 1 h after skin incision and at 3 h postoperatively. However, there were no significant differences in glucose or cortisol concentrations, between the 2 groups, at 24 h postoperatively. Patients in the PVB group had significantly lower VAS scores both at rest and on moving the arm at all the predetermined time intervals postoperatively as well as significantly lower incidence of PONV throughout the 24 h postoperatively. Conclusion: Nerve stimulator-guided PVB at the level of T1-T6 with ropivacaine represents a suitable alternative to GA for breast cancer surgery. Important benefits of PVB include reduced surgical stress response, as evidenced by lower plasma cortisol and glucose concentrations, superior postoperative analgesia and lower incidence of PONV.
Keywords: Nausea and vomiting; Nerve stimulator; Pain; Paravertebral nerve block

Minority recruitment to the Selenium and Vitamin E Cancer Prevention Trial (SELECT) - Cook, E.D.; Moody-Thomas, S.; Anderson, K.B.; Campbell, R.; Hamilton, S.J.; Harrington, J.M.; Lippman, S.M.; Minasian, L.M.; Paskett, E.D.; Craine, S.; Arnold, K.B.; Probstfield, J.L. (Clinical Trials, 2005)
Background: Previous large chemoprevention studies have not recruited significant numbers of minorities. The Selenium and Vitamin E Cancer Prevention Trial (SELECT) is a large phase III study evaluating the impact of selenium and vitamin E on the clinical incidence of prostate cancer. Over 400 SELECT study sites in the USA, Canada, and Puerto Rico recruited men to this trial. The SELECT recruitment goal was 24% minorities, with 20% black, 3% Hispanic, and 1% Asian participants. The goal for black participants was set at 20% because of their proportion in the United States population and their prevalence of prostate cancer. Methods: The minority recruitment strategies in SELECT were to: 1) consider minority recruitment during site selection; 2) expand the eligibility criteria by lowering the age criterion for black men and including men with controlled co-morbid illnesses; 3) develop a national infrastructure; 4) give additional funds to sites with the potential to increase black enrollment; and 5) provide resources to maximize free media opportunities to promote SELECT. Results: SELECT recruitment began in August 2001 and was intended to last five years, but concluded two years ahead of schedule in June 2004. Of the 35 534 participants enrolled, 21% were minorities, with 15% black, 5% Hispanic, and 1% Asian. Conclusions Careful planning, recruitment of large numbers of clinical centers and adequate resources accomplished by the combined efforts of the National Cancer Institute (NCI), Southwest Oncology Group (SWOG), SELECT Recruitment and Adherence Committee (RAC), SELECT Minority and Medically Underserved Subcommittee (MMUS), and the local SELECT sites resulted in attainment of the estimated sample size ahead of schedule and recruitment of the largest percentage of black participants ever randomized to a cancer prevention trial. © Society for Clinical Trials 2005.

5,10-Methylenetetrahydrofolate reductase 677 and 1298 polymorphisms, folate intake, and microsatellite instability in colon cancer - Eaton, A.M.; Sandler, R.; Carethers, J.M.; Millikan, R.C.; Galanko, J.; Keku, T.O. (Cancer Epidemiology Biomarkers and Prevention, 2005)
The 5,10-methylenetetrahydrofolate reductase (MTHFR) gene plays a critical role in folate metabolism. Studies on the association between MTHFR polymorphisms and length changes in short tandem repeat DNA sequences [microsatellite instability (MSI)] are inconsistent. Using data from colon cancer cases (n = 503) enrolled as part of an existing population-based case-control study, we investigated the association between MTHFR 677 and MTHFR 1298 polymorphisms and MSI. We also examined whether the association was modified by folate intake. Participants were case subjects enrolled as part of the North Carolina Colon Cancer Study. Consenting cases provided information about lifestyle and diet during in-home interviews as well as blood specimens and permission to obtain tumor blocks. DNA from normal and tumor tissue sections was used to determine microsatellite status (MSI). Tumors were classified as MSI if two or more microsatellite markers (BAT25, BAT26, D5S346, D2S123, and D17S250) had changes in the number of DNA sequence repeats compared with matched nontumor tissue. Tumors with one positive marker (MSI-low) or no positive markers (microsatellite stable) were grouped together as non-MSI tumors (microsatellite stable). MTHFR 677 and MTHFR 1298 genotypes were determined by real-time PCR using the 5′ exonuclease (Taqman) assay. Logistic regression was used to calculate odds ratio (OR) and 95% confidence intervals (95% CI). MSI was more common in proximal tumors (OR, 3.8; 95% CI, 1.7-8.4) and in current smokers (OR, 4.0; 95% CI, 1.6-9.7). Compared with MTHFR 677 CC referent, MTHFR 677 CT/TT genotype was inversely associated with MSI among White cases (OR, 0.36; 95% CI, 0.16-0.81) but not significant among African Americans. Although not statistically significant, a similar inverse association was observed between MTHFR 677 CT/TT genotype and MSI among the entire case subjects (OR, 0.54; 95% CI, 0.26-1.10). Among those with adequate folate intake (>400 μg total folate), we found strong inverse associations between combined MTHFR genotypes and MSI (677 CC + 1298 AC/CC, OR, 0.09; 95% CI, 0.01-0.59; 677 CT/TT + 1298 AA, OR, 0.13; 95% CI, 0.02-0.85) compared with the combined wild-type genotypes (677 CC + 1298 AA). This protective effect was not evident among those with low folate (<400 μg total folate) intake. Our results suggest that MTHFR variant genotypes are associated with reduced risk of MSI tumors under conditions of adequate folate intake, although the data are imprecise due to small numbers. These results indicate that the relationship between MTHFR genotypes and MSI is influenced by folate status. Copyright © 2005 American Association for Cancer Research.

The influence of gender, race, and menthol content on tobacco exposure measures - Mustonen, T.K.; Spencer, S.M.; Hoskinson Jr., R.A.; Sachs, D.P.L.; Garvey, A.J. (Nicotine and Tobacco Research, 2005)
Research has suggested that race, gender, and menthol cigarette use influence tobacco-smoke exposure measures and smoking-related disease risk. For example, a high proportion of Black smokers prefer menthol cigarettes and, despite smoking fewer cigarettes per day (CPD) than do Whites, tend to have higher cotinine levels. Additionally, Black males are more at risk for smoking-related lung cancer. High cotinine levels and smoking menthol cigarettes may lead to higher toxin intake, which contributes to increased disease risk. We explored the relationship between tobacco exposure variables (i.e., cotinine, CPD, carbon monoxide [CO], nicotine content, and nicotine dependence) with respect to race, gender, and menthol content in a sample of 307 smokers recruited from the greater Boston area to participate in a smoking cessation treatment trial. The pattern of correlations between tobacco exposure measures and cotinine showed a consistently positive correlation between cotinine and CO in all smokers and a correlation between cotinine and CPD in those who smoked nonmenthol cigarettes. Cotinine and CPD correlations varied by gender and race among menthol cigarette smokers. Consistently, we found a significant gender × race × menthol interaction on salivary cotinine level as well as cotinine/CPD ratio. These findings suggest that the relationship between number of cigarettes consumed and salivary cotinine is more complex than previously believed. It is not sufficient to look at race alone; researchers and clinicians need to look at race and gender concurrently, as well as type of cigarette consumed. © 2005 Society for Research on Nicotine and Tobacco.

Barriers to minority participation in breast carcinoma prevention trials - Grann, V.R.; Jacobson, J.S.; Troxel, A.B.; Hershman, D.; Karp, J.; Myers, C.; Neugut, A.I. (Cancer, 2005)
BACKGROUND. Breast carcinoma prevention trials must recruit large cohorts of women who have an above-average risk of developing breast carcinoma. Recruitment for the Study of Tamoxifen and Raloxifene (STAR) trial required volunteers to complete a risk assessment questionnaire form (RAF). Women whose estimated risk of developing breast carcinoma in the next 5 years was ≥ 1.67% based on the Gail model were invited to participate in STAR. Less than 4% of participants in the previously conducted P1 (tamoxifen vs. placebo) trial were minority women. We, therefore, studied barriers to minority participation in STAR among black, white, and Hispanic women who completed an RAF. METHODS. The authors analyzed the association of Gail model risk factors, education, and insurance with race/ethnicity using chi-square tests and two-sided P values. They developed logistic regression models of trial eligibility, controlling for the Gail model risk factors, education, and insurance status. RESULTS. Among 823 women who completed an RAF, white women were 10 times as likely as Hispanic women and 45 times as likely as black women to be eligible for STAR. Age at first birth (P = 0.04), having an affected first-degree relative (P < 0.0001), having had a biopsy (P < 0.0001), education (P < 0.0001), and insurance status (P < 0.0001) varied by race/ethnicity. All variables except insurance status were associated with eligibility when race was excluded from the model. In a model that included race/ethnicity, the same factors remained statistically significant. CONCLUSIONS. These findings suggested that both the race/ethnicity adjustment and socioeconomic factors were barriers to eligibility for and contribute to low minority participation in breast cancer prevention trials. © 2005 American Cancer Society.

Prostate-specific antigen screening in a high-risk population: Lessons from the community and how they relate to large-scale population-based studies - Shelton, J.B.; Barocas, D.A.; Conway, F.; Hart, K.; Nelson, K.; Richstone, L.; Gonzalez, R.R.; Raman, J.D.; Scherr, D.S. (Urology, 2005)
Objectives. To estimate the incidence of prostate cancer among African-American men and Caribbean immigrants to the United States, to assess the applicability of large-scale prostate screening trials to a community screening program, and to recruit unscreened men. Methods. African-American and Caribbean-American men were targeted with a community-based prostate cancer screening program in Jamaica, New York. Serum prostate-specific antigen determination and digital rectal examination were used to determine abnormal findings. The incidence of an abnormal screening examination was used to project the incidence of prostate cancer, which was compared with that in other reported trials. Results. The projected incidence of prostate cancer among African-Americans and Caribbean-Americans older than 50 years was 8% and 7%, respectively, similar to that reported in other trials of African-American men. The projected incidence of prostate cancer in Caribbean-American men aged 40 to 49 years was 1%, the same as the high rate reported among Caribbean men. As in other trials, a family history of prostate cancer and age were strong predictors of abnormal findings. Of the recruited men older than 50 years, 58% had never been screened compared with 42% nationally. Conclusions. Large population-based screening trials have identified ethnic groups at high risk of prostate cancer. This trial detected high rates of abnormal screening findings by targeting ethnicity. The incidence of an abnormal examination was high in Caribbean-American men younger than 50 years old. Finally, this trial successfully recruited underscreened men. © 2005 Elsevier Inc.

A combined breast health/weight loss intervention for Black women - Fitzgibbon, M.L.; Stolley, M.R.; Schiffer, L.; Sanchez-Johnsen, L.A.P.; Wells, A.M.; Dyer, A. (Preventive Medicine, 2005)
Background. Overall incidence of breast cancer is slightly lower, but mortality rates are higher, for Black women compared to White women. Higher body mass index (BMI), sedentary lifestyles, and lower compliance with recommended breast health behaviors may contribute to higher risk and mortality. Methods. A randomized pilot intervention trial was conducted to assess feasibility and efficacy of a combined breast health/weight loss intervention for 64 overweight or obese Black women, ages 35-65. The primary objectives were to determine whether a 20-week (twice weekly) intervention could decrease weight and dietary fat intake and increase physical activity and breast self-exam (BSE) proficiency. Results. The project was implemented in two cohorts and retention was high for both (96% and 89%, respectively). Both cohorts showed increased proficiency in BSE in the intervention versus the control group (2.4 vs. -0.4, P < 0.05; 3.3 vs. -0.2, P < 0.001, respectively), but only cohort 2 showed decreased percent body weight (4.0% decrease vs. 0.9% increase, P < 0.01), increased physical activity frequency (2.4 vs. 0.1 times/week, P < 0.05), and a trend for decreased dietary fat (-2.6% kcal vs. 0.0% kcal, P = 0.07) in the intervention compared to the control group. Conclusion. Few studies have documented weight loss among Black women, and no combined breast health/weight loss intervention has been conducted. This study documents the feasibility of recruiting, randomizing, and retaining women in a combined intervention and demonstrated weight loss and associated lifestyle changes. © 2004 The Institute For Cancer Prevention and Elsevier Inc. All rights reserved.
Keywords: African-American; Black; Breast cancer; Breast health; Breast self-exam; Diet; Intervention; Minority; Physical activity; Weight loss

Supportive-affective group experience for persons with life-threatening illness: Reducing spiritual, psychological, and death-related distress in dying patients - Miller, D.K.; Chibnall, J.T.; Videen, S.D.; Duckro, P.N. (Journal of Palliative Medicine, 2005)
Background: Attention to psycho-socio-spiritual needs is considered critical by patients with life-threatening illnesses and their caregivers. Palliative care interventions that address these needs - particularly spirituality - are lacking. Objective: To evaluate the effects of an innovative program to address psycho-socio-spiritual needs in patients with life-threatening illnesses. Design: A group intervention entitled Life-Threatening Illness Supportive-Affective Group Experience (LTI-SAGE) was developed for reducing patient spiritual, emotional, and death-related distress. Setting/subjects: African American and Caucasian patients (n = 69) from two hospitals in St. Louis, Missouri, with life-threatening medical conditions (cancer; human immunodeficiency virus/acquired immune deficiency syndrome [HIV/AIDS]; geriatric frailty; liver, kidney, pulmonary, or cardiovascular disease) were randomly assigned to intervention or control groups. Intervention patients participated in a maximum of 12 LTI-SAGE groups over a 12-month period. Control patients received standard care. Measurements: Outcome measures were depression symptoms, anxiety, spiritual well-being, and death-related emotional distress. Results: After attrition, 51 (73.9%) patients completed the trial. At the end of the trial, after factoring in compliance, intervention patients had significantly fewer depression symptoms and death-related feelings of meaninglessness and significantly better spiritual well-being than did control patients. Conclusions: The use of the LTI-SAGE model for enhancing the end-of-life illness experience is promising. © Mary Ann Liebert, Inc.

The impact of socioeconomic status and race on trial participation for older women with breast cancer - Gross, C.P.; Filardo, G.; Mayne, S.T.; Krumholz, H.M. (Cancer, 2005)
BACKGROUND. Older women, and older minorities in particular, are under represented in breast cancer trials. Although socioeconomic status (SES) is associated with both race and age, to the authors' knowledge little is known regarding the impact of SES on trial enrollment among older women with breast cancer. METHODS. The authors performed a case-control study comparing women who were participants in National Cancer Institute cooperative group breast cancer trials (cases) with a population-based sample of breast cancer patients (controls) obtained from the linked Surveillance, Epidemiology, and End Results (SEER)-Medicare data base. The sample was restricted to women age a 65 years who were living in SEER areas. Proxies for SES included the proportion of the population below poverty level (by zip code) and unemployed (by county) as well those with Medicaid insurance coverage. A multivariable logistic regression model was used to test the association of SES with trial participation after accounting for other patient and county characteristics. RESULTS. In bivariate analysis, trial participants were significantly less likely than community cancer patients to reside in high-poverty zip codes (20.9% vs. 24.9%, respectively; P < 0.001) or to have Medicaid insurance (2.0% vs. 10.0%; P < 0.0001). After adjusting for race, age, and county, trial participation remained inversely related to residing in areas with high poverty (odds ratio [OR] vs. residents of remaining counties, 0.78; 95% confidence interval [95% CI], 0.62-0.98), high unemployment rates (OR vs. residents of residents of counties in the lowest quartile, 0.50; 95% CI, 0.35-0.71), and having Medicaid insurance (OR vs. women without Medicaid, 0.22; 95% CI, 0.13-0.37); black race was not found to be related to trial participation (OR for black vs. white, 1.0; 95% CI, 0.67-1.47). CONCLUSIONS. Low SES was associated inversely with trial enrollment for older women with breast cancer and appeared to account for the enrollment disparities between black patients and white patients. Future efforts to enhance enrollment of elderly women in cancer research should identify specific barriers related to SES that may be amenable to intervention. © 2004 American Cancer Society.
Keywords: Age disparities; Medicaid eligibility; Racial disparities; Socioeconomic status clinical trials; Trial-enrollment strategies

Designing the Selenium and Vitamin E Cancer Prevention Trial (SELECT) - Lippman, S.M.; Goodman, P.J.; Klein, E.A.; Parnes, H.L.; Thompson Jr., I.M.; Kristal, A.R.; Santella, R.M.; Probstfield, J.L.; Moinpour, C.M.; Albanes, D.; Taylor, P.R.; Minasian, L.M.; et al. (Journal of the National Cancer Institute, 2005)
Prostate cancer continues to be a major health threat, especially among African American men. The Selenium and Vitamin E Cancer Prevention Trial (SELECT), which opened on July 25, 2001, was planned to study possible agents for the prevention of prostate cancer in a population of 32 400 men in the United States, including Puerto Rico, and Canada. SELECT is a phase III randomized, placebo-controlled trial of selenium (200 μg/day from L-selenomethionine) and/or vitamin E (400 IU/day of all rac α-tocopheryl acetate) supplementation for a minimum of 7 years (maximum of 12 years) in non-African American men at least 55 years of age and African American men at least 50 years of age. SELECT is a large, simple trial that conforms as closely as possible with community standards of care. This commentary discusses the design problems the SELECT investigators had to resolve in developing the trial, including the role of prostate cancer screening, the best forms and doses of the study agents, and estimation of the event (prostate cancer) rate of men on the placebo arm. © Oxford University Press 2005, all rights reserved.

Polymorphisms in cytochrome P4503A5 (CYP3A5) may be associated with race and tumor characteristics, but not metabolism and side effects of tamoxifen in breast cancer patients - Tucker, A.N.; Tkaczuk, K.A.; Lewis, L.M.; Tomic, D.; Lim, C.K.; Flaws, J.A. (Cancer Letters, 2005)
Tamoxifen (TAM) is widely used for treatment and prevention of breast cancer. TAM is metabolized by cytochrome P450 (CYP450) enzymes, including CYP3A5. Although two genetic polymorphisms in CYP3A5 are known (CYP3A5*3 and CYP3A5*6), the effects of these polymorphisms on TAM metabolism, TAM side effects, and tumor characteristics are unknown. Thus, this work tested the hypothesis that CYP3A5 polymorphisms are associated with differential TAM levels, TAM side effects, and tumor characteristics in breast cancer patients. Postmenopausal women with breast cancer (n=98) were recruited from a single cancer center. Polymorphic status was established using polymerase chain reactions (PCR). The associations between polymorphic status, race, TAM levels, side effects, and tumor characteristics were assessed using t-tests and logistic regression models. The data indicate that 40.7% of the breast cancer patients had the CYP3A5*3 polymorphism, and 9.1% had the CYP3A5*6 polymorphism. In addition, Caucasian women were 26 times more likely to carry the CYP3A5*3 polymorphism than African American (AA) women, whereas AA women were nine times more likely to carry the CYP3A5*6 polymorphism than Caucasian women. No significant differences were seen in TAM or TAM metabolite levels or TAM side effects by polymorphic status. There was a significant difference, however, in mean tumor size in women with the CYP3A5*6 polymorphism (3.6±0.98 cm) compared to those without the polymorphism (2.0±0.18 cm) (P<0.02). Taken together, these data suggest that racial differences in CYP3A5 polymorphisms exist although the polymorphisms do not appear to be associated with levels of TAM metabolites and side effects. © 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: Breast cancer; Cytochrome P450 3A5; Metabolism; Polymorphisms; Race/ethnicity; Tamoxifen

The deep south network for cancer control: Eliminating cancer disparities through community - Academic collaboration - Partridge, E.E.; Fouad, M.N.; Hinton, A.W.; Hardy, C.M.; Liscovicz, N.; White-Johnson, F.; Higginbotham, J.C. (Family and Community Health, 2005)
African Americans have a substantially increased mortality rate compared to Whites in many cancers, including breast and cervix. The Deep South Network for Cancer Control (the Network) was established to develop sustainable community infrastructure to promote cancer awareness, enhance participation of African Americans and other special populations in clinical trials, recruit and train minority investigators, and develop and test innovative community-based cancer control measures to eliminate cancer mortality disparities in special populations. This article describes the steps necessary to form the network and the process and activities required to establish it as an effective infrastructure for eliminating disparities between Whites and African Americans in the United States.
Keywords: African Americans; Cancer control; Health disparities; Network

Factors associated with breast cancer clinical trials participation and enrollment at a large academic medical center - Simon, M.S.; Du, W.; Flaherty, L.; Philip, P.A.; Lorusso, P.; Miree, C.; Smith, D.; Brown, D.R. (Journal of Clinical Oncology, 2004)
Purpose: The practice patterns of medical oncologists at a large National Cancer Institute Comprehensive Cancer Center in Detroit, MI were evaluated to better understand factors associated with accrual to breast cancer clinical trials. Patients and Methods: From 1996 to 1997, physicians completed surveys on 319 of 344 newly evaluated female breast cancer patients. The 19-item survey included clinical data, whether patients were offered clinical trial (CT) participation and enrollment, and when applicable, reasons why they were not. Multivariate analyses using logistic regression were performed to evaluate predictors of an offer and enrollment. Results: The patients were 57% white, 32% black, and 11% other/unknown race. One hundred six (33%) were offered participation and 36 (34%) were enrolled. In multivariate analysis, CTs were less likely offered to older women (mean age, 52 years for those offered v 57 years for those not offered; P = .0005) and black women (21% of blacks offered v 42% of whites; P = .0009). Women with stage 1 disease, poor performance status, and those who were previously diagnosed were also less likely to be offered trials. None of these factors were significant predictors of enrollment. Women were not offered trials because of ineligibility (57%), lack of available trials (41%), and noncompliance (2%). Reasons for failed enrollment included patient refusal (88%) and failed eligibility (12%). Conclusion: It is important for cooperative groups to design studies that will accommodate a broader spectrum of patients. Further work is needed to assess ways to improve communication about breast cancer CT participation to all eligible women. © 2004 by American Society of Clinical Oncology.

Phase II trial of estramustine and etoposide in androgen-sensitive metastatic prostate carcinoma - Vaishampayan, U.; Fontana, J.; Du, W.; Hussain, M. (American Journal of Clinical Oncology: Cancer Clinical Trials, 2004)
Background: Early chemohormonal therapy in metastatic prostate cancer may offer an advantage by simultaneously targeting androgen-dependent and -independent clones. Hence, a phase II trial was conducted to evaluate the efficacy and toxicity of estramustine and etoposide in hormone-sensitive metastatic prostate cancer. Patient and Methods: Eligibility consisted of untreated metastatic prostate cancer, adequate organ function, and a performance status of 0 to 2 by Zubrod criteria. A 21-day schedule of oral estramustine (10 mg/kg/day) and etoposide (50 mg/m2/day) was administered every 28 days. Hormonal therapy was allowed at the end of the protocol therapy. Toxicity was assessed weekly, PSA levels were assessed with each cycle, and objective response was evaluated every 3 cycles. Results: Twenty-one patients were enrolled (10 white, 11 black) with a median age of 59.5 years (range, 42-79 years), a median PSA of 338 ng/mL (range, 0.9-20,000 ng/mL), and a median Gleason score of 8 points. Ten patients had bone-only metastases, 11 had measurable disease, of whom 4 had visceral metastases. A total of 128 cycles were administered (median, 6 cycles). No dose reductions were required. Nineteen patients were able to be evaluated for response. Severe toxicities included thromboembolic events and anemia in 2 patients each and fatigue in 1 patient. There were no episodes of febrile neutropenia. Response was observed in 8 of 11 patients (73%) with measurable disease. Median PSA nadir after therapy was 0.45 ng/mL, and undetectable PSA (<0.1 ng/mL) was achieved in 4 patients. Median time to PSA progression was 16.65 months. At a median follow-up of 34 months, 18 patients were alive. The 1-, 2-, and 3-year overall survival rates were 90%, 82%, and 72% respectively. Median survival has not yet been reached. Conclusion: The combination of estramustine and etoposide is well tolerated, and has promising activity in newly diagnosed metastatic prostate cancer.
Keywords: Chemotherapy; Clinical trial; Hormone sensitive; Prostate cancer; Untreated

Pilot evaluation of black cohosh for the treatment of hot flashes in women - Pockaj, B.A.; Loprinzi, C.L.; Sloan, J.A.; Novotny, P.J.; Barton, D.L.; Hagenmaier, A.; Zhang, H.; Lambert, G.H.; Reeser, K.A.; Wisbey, J.A. (Cancer Investigation, 2004)
Background. Hot flashes cause significant morbidity in postmenopausal women, including women with breast cancer. We undertook a pilot study to estimate the effectiveness of black cohosh to reduce hot flashes. Methods. Women who reported significant hot flashes (≥ 14 per week) were enrolled. Black cohosh was given in the form of the commercial product Remifemin. The first week was a no-treatment baseline period, and therapy was given for the subsequent 4 weeks. Hot flash data were collected by daily questionnaires during baseline and treatment weeks. Adverse effects were recorded. Results. Twenty-one women completed the study. Their mean age was 56 years (range, 38-80). Thirteen patients had a history of breast cancer. Six patients were taking tamoxifen or raloxifene. Patients reported an average of 8.3 hot flashes per day during the baseline week. The reduction in mean daily hot flash frequency was 50% (95% CI, 34%-65%), while weekly hot flash scores were reduced 56% (95% CI, 40%-71%) at completion of the study. Overall, patients reported less trouble with sleeping, less fatigue, and less abnormal sweating. No patients stopped therapy because of adverse effects. Conclusions. Black cohosh appeared to reduce hot flashes and had a low toxicity. The efficacy found in this trial seems to be more than would be expected by a placebo effect (20%-30% hot flash reduction in previous trials). These results suggest that further evaluation of this black cohosh preparation with a phase III randomized trial is indicated.
Keywords: Alternative medicine; Breast cancer; Hot flashes; Medicine, herbal; Menopause

A report on accrual rates for elderly and minority-ethnicity cancer patients to clinical trials of the american college of surgeons oncology group - Newman, L.A.; Hurd, T.; Leitch, M.; Kuerer, H.M.; Diehl, K.; Lucci, A.; Giuliano, A.; Hunt, K.K.; Putnam, W.; Wells, S.A. (Journal of the American College of Surgeons, 2004)
Incidence and mortality rates for cancers vary by ethnic background and patient age. Accrual of diverse patient populations to cancer clinical trials is essential in order to ensure that findings related to new management strategies can be generalized. The goal of this study was to evaluate accrual patterns for patients participating in the American College of Surgeons Oncology Group (ACOSOG) cancer protocols. Ethnic diversity among clinical trial investigators may also influence accrual patterns, so the ethnic background of the ACOSOG membership was also evaluated. Demographics for the patients registered on ACOSOG breast, thoracic, and colorectal clinical trials were evaluated and compared with data on the general population and the cancer population in the United States. Accrual patterns for patients from other reported cancer clinical trials were also presented, and the self-reported ethnic distribution of the ACOSOG membership was analyzed. Distribution of African Americans, Hispanic Americans, and Asian Americans to the ACOSOG breast and colorectal clinical trials was relatively proportionate to the cancer population. African Americans were underrepresented in the thoracic clinical trials, and this disparity was partially offset by data on the proportion of African Americans with stage-eligible lung cancer. Accrual rates for patients age 65 years and older were better than those reported by most other clinical trialists. Elderly patients are successfully recruited into surgical clinical trials, and this will provide important data for future analyses regarding cancer outcomes in this growing population of cancer patients. Aggressive outreach to minority-ethnicity cancer patients for accrual into clinical trials should continue. © 2004 American College of Surgeons.

Increasing mammography screening among women over age 50 with a videotape intervention - Avis, N.E.; Smith, K.W.; Link, C.L.; Goldman, M.B. (Preventive Medicine, 2004)
Background. A randomized trial was conducted to test the effectiveness of a videotape for increasing mammography screening among a multiethnic sample of older women. Methods. A multiethnic sample of Caucasian, African-American, and Hispanic women between the ages of 50 and 70 was recruited from Resident Lists compiled by the State of Massachusetts. After completing a baseline questionnaire, women were randomized to receive either a videotape or pamphlet about mammography and recontacted at 2 and 12 months after baseline to assess attitudes, beliefs, and mammography screening. A total of 581 women completed questionnaires at all three time points. Results. At baseline, approximately 75% of women reported having a mammogram in the past year and 90% reported having one in the past 2 years. Rates did not differ between groups. At the 12-month follow-up, mammography rates, adjusted for baseline screening, were 80.4% in the video and 74.8% in the pamphlet group. Logistic regression analysis of mammography at 12 months (within past year vs. >1 year ago) controlling for baseline mammogram produced an odds ratio of 1.48 for the video group that was not significantly different from unity (95% CI = 0.95-2.28). Conclusions. The videotape had a small effect on increasing mammography screening. Although the effect was smaller than more intensive interventions, the video is a convenient, low cost, and easily implemented method to increase mammography screening. © 2004 The Institute For Cancer Prevention and Elsevier Inc. All rights reserved.
Keywords: African-American; Hispanic; Intervention; Mammography; Videotape

Breast cancer survivorship in a multiethnic sample: Challenges in recruitment and measurement - Ashing-Giwa, K.T.; Padilla, G.V.; Tejero, J.S.; Kim, J. (Cancer, 2004)
BACKGROUND. The inclusion of ethnic minorities in cancer-related studies continues to be an important concern for researchers. In this article, the authors present 1) a brief discussion of recruitment and measurement challenges in conducting multiethnic survivorship research, and 2) recruitment outcomes and sample characteristics for a health-related quality-of-life study with a multiethnic sample of breast cancer survivors (BCS). METHODS. A case-control, cross-sectional design with mixed sampling methods was used. The Contextual Model for Recruitment and Enrollment of Diverse Samples was used to guide the protocol. BCS were recruited from the California Cancer Surveillance Program, from hospital registries, and from community agencies. Participation rates, demographic factors, and medical factors were compared. The reliability of standard measures by ethnicity was assessed. RESULTS. Seven hundred three women participated, including 135 African-American women (19%), 206 Asian-American women (29%), 183 Latina-American women (26%), and 179 European-American women (26%). Participation was influenced by ethnicity, age, and site of recruitment. Overall, African Americans were least likely to participate, and European Americans most likely to participate. African Americans and Asian Americans were more likely to refuse, European Americans and Latina Americans were more likely to agree to participate, and European Americans and Asian Americans were most likely to complete the survey after consenting. Measures possessed moderate to excellent reliability (0.64-0.91). CONCLUSIONS. Despite important recruitment and measurement challenges, this study obtained acceptable participation rates and good internal consistency of the measures. The results demonstrate the utility of a culturally responsive approach to health disparities research. © 2004 American Cancer Society.
Keywords: Breast cancer; Ethnic minority; Multiethnic; Recruitment

Participation in cancer clinical trials: Race-, sex-, and age-based disparities - Murthy, V.H.; Krumholz, H.M.; Gross, C.P. (Journal of the American Medical Association, 2004)
Context: Despite the importance of diversity of cancer trial participants with regard to race, ethnicity, age, and sex, there is little recent information about the representation of these groups in clinical trials. Objective: To characterize the representation of racial and ethnic minorities, the elderly, and women in cancer trials sponsored by the National Cancer Institute. Design, Setting, and Patients: Cross-sectional population-based analysis of all participants in therapeutic nonsurgical National Cancer Institute Clinical Trial Cooperative Group breast, colorectal, lung, and prostate cancer clinical trials in 2000 through 2002. In a separate analysis, the ethnic distribution of patients enrolled in 2000 through 2002 was compared with those enrolled in 1996 through 1998, using logistic regression models to estimate the relative risk ratio of enrollment for racial and ethnic minorities to that of white patients during these time periods. Main Outcome Measure: Enrollment fraction, defined as the number of trial enrollees divided by the estimated US cancer cases in each race and age subgroup. Results: Cancer research participation varied significantly across racial/ethnic and age groups. Compared with a 1.8% enrollment fraction among white patients, lower enrollment fractions were noted in Hispanic (1.3%; odds ratio [OR] vs whites, 0.72; 95% confidence interval [CI], 0.68-0.77; P<.001) and black (1.3%; OR, 0.71; 95% CI, 0.68-0.74; P<.001) patients. There was a strong relationship between age and enrollment fraction, with trial participants 30 to 64 years of age representing 3.0% of incident cancer patients in that age group, in comparison to 1.3% of 65- to 74-year-old patients and 0.5% of patients 75 years of age and older. This inverse relationship between age and trial enrollment fraction was consistent across racial and ethnic groups, Although the total number of trial participants increased during our study period, the representation of racial and ethnic minorities decreased. In comparison to whites, after adjusting for age, cancer type, and sex, patients enrolled in 2000 through 2002 were 24% less likely to be black (adjusted relative risk ratio, 0.76; 95% CI, 0.65-0.89; P<.001). Men were more likely than women to enroll in colorectal cancer trials (enrollment fractions: 2.1% vs 1.6%, respectively; OR, 1.30; 95% CI, 1.24-1.35; P<.001) and lung cancer trials (enrollment fractions: 0.9% vs 0.7%, respectively; OR, 1.23; 95% CI, 1.16-1.31; P<.001). Conclusions: Enrollment in cancer trials is low for all patient groups. Racial and ethnic minorities, women, and the elderly were less likely to enroll in cooperative group cancer trials than were whites, men, and younger patients, respectively. The proportion of trial participants who are black has declined in recent years.

Prevalence and patterns of self-initiated nutritional supplementation in men at high risk of prostate cancer - Uzzo, R.G.; Brown, J.G.; Horwitz, E.M.; Hanlon, A.; Mazzoni, S.; Konski, A.; Greenberg, R.E.; Pollack, A.; Kolenko, V.; Watkins-Bruner, D. (BJU International, 2004)
OBJECTIVE: To define the prevalence and patterns of self-initiated herbal and vitamin supplementation among men at high risk of developing prostate cancer, as there is increasing public awareness of prostate cancer screening, risk-factor assessment and prevention, leading to increasing interest in the use and systematic study of nutritional therapies for prostate cancer prevention. SUBJECTS AND METHODS: Since 1996 our institution has prospectively maintained a prostate cancer-risk registry through its Prostate Cancer Risk Assessment Program (PRAP). Eligibility includes African-American men, any man with at least one first-degree relative or two or more second-degree relatives with prostate cancer, or men who tested positively for the BRCA1 gene mutation. A 420-item self-administered-questionnaire was completed and included the use of nutritional supplements and complementary therapies. We divided men into groups who used supplements to lessen their cancer risk and those who did not. The prevalence and patterns of use were evaluated and the two groups then compared for differences in demographic, socioeconomic and risk-perception variables. RESULTS: In all, 345 high-risk men were enrolled in the PRAP over a 5-year period. Data on the use of dietary or herbal supplements were available on 333 men (97%), of whom over half (170) reported taking one or more supplements to prevent prostate cancer. Supplement use was divided into eight categories, including vitamins, minerals, extracts from fruits/seeds, organic compounds, flowers/bulbs, leaves/ bark, roots, or animal products. Most commonly used for self-initiated chemoprevention were vitamins (95%), minerals (28%), and fruit/seed extracts (18%). More than a quarter of men (27%) took three or more agents. Men taking proactive preventative measures were statistically more likely to be Caucasian and aged >60 years (P<0.05). African-Americans were less likely to self-initiate preventative steps. Men taking supplements tended to return more often for follow-up and participate in PRAP longer, while those not taking supplements tended to earn less and report less self-perceived risk. CONCLUSIONS: A significant proportion of men at risk of developing prostate cancer initiate measures they perceive to reduce their risk. Although the chemopreventative efficacy of many of these supplements remains unsubstantiated, they are widely perceived by the public to reduce the risk of developing prostate cancer. These data provide an insight into patient perceptions and misconceptions of chemopreventative strategies, and may help to refine recruitment efforts in multiinstitutional prostate cancer prevention trials.
Keywords: Cancer; Nutrition; Prevention; Prostate; Supplement

Recruiting Black/African American Men for Research on Prostate Cancer Prevention - Woods, V.D.; Montgomery, S.B.; Herring, R.P. (Cancer, 2004)
BACKGROUND. Black/African American men die of prostate cancer at a greater rate relative to other males. During the period from 1992 to 1998, prostate cancer incidence rates in the United States were 234.2 per 100,000 persons among non-Hispanic black males and 144.6 per 100,000 persons among white males. The reasons for these increased rates of prostate cancer among black males are largely unknown, but increased mortality is associated with late detection. The authors conducted a longitudinal study of black men that investigated prostate cancer prevention behaviors within this population. The purpose of the current article is to identify successful recruitment strategies that were reported by participants in this study of prevention behaviors. METHODS. Qualitative research methods were used to elucidate men's thoughts, attitudes, beliefs, and practices regarding prostate cancer prevention behaviors and to identify strategies for attracting black men to research programs and retaining them in these programs. RESULTS. Ethnocentric recruitment strategies that were identified included the development of tailored printed materials; the use of targeted locations; and a personalized, participatory approach for engaging potential participants. We contacted 498 black men and enrolled a cohort of 277 non-Hispanic black males (75% of whom were recruited within a 9-week period) in the current study. CONCLUSIONS. Unlike other studies that reported difficulty in recruiting African American men, the current study did not encounter such difficulties. The authors attribute their success to culturally attractive Afrocentric materials; cultural sensitivity; a caring, professional, personalized ethnic approach; respect; and participatory involvement of the target population. Nonetheless, the authors did encounter barriers, such as lack of physician interest and lack of trust in quality medical care. These barriers must be overcome before black males can be engaged and retained in research studies on prostate cancer prevention. © 2004 American Cancer Society.
Keywords: African American men; Afrocentric prevention research; Black men; Prostate cancer prevention; Recruitment

A randomized trial of recruitment methods for older African American men in the Prostate, Lung, Colorectal and Ovarian (PLCO) cancer screening trial - Ford, M.E.; Havstad, S.L.; Davis, S.D. (Clinical Trials, 2004)
Background Incidence rates for many types of cancer are higher among African American men than in the general population, yet African American men are less likely to participate in cancer screening trials. This paper describes the outcomes of a randomized trial (the AAMEN Project) designed to recruit African American men aged 55–74 years to a prostate, lung and colorectal cancer screening trial. Methods The recruitment interventions address four types of barriers to clinical trial participation: sociocultural barriers, economic barriers, individual barriers and barriers inherent in study design. Subjects were randomized to a control group or one of three increasingly intensive intervention arms, which used different combinations of mail, phone and in person church-based recruitment. Results Of the 39 432 African American men residing in the geographically defined study population (southeastern Michigan and northern Ohio), 17 770 men (45%) could be contacted, and 12 400 (31% of 39 432) were found to be eligible to participate. No statistically significant differences in age, education or income level were found among participants in the four study arms. A significantly greater enrollment yield (3.9%) was seen in the most intensive, church-based intervention arm, compared to the enrollment yields in the other two intervention arms (2.5 and 2.8%) or the control group (2.9%) (P, 0.01). Conclusions The intervention that involved the highest rate of face-to-face contact with the study participants produced the highest enrollment yield, but several strategies that were thought could improve yield had no effect. These findings, which are consistent with current literature on population-based recruitment, should facilitate the development of future recruitment efforts involving older African American men. © 2004, Sage Publications. All rights reserved.

Selenium and vitamin E cancer prevention trial - Klein, E.A. (Annals of the New York Academy of Sciences, 2004)
Preclinical, epidemiological, and phase III data from randomized, placebo-controlled clinical trials suggest that both selenium and vitamin E have potential efficacy in prostate cancer prevention. In vitro evidence suggests that selenium and vitamin E work synergistically to cause cell-cycle arrest, induce caspase-mediated apoptosis, and act as antiandrogens in arresting clonal expansion of nascent tumors. The Selenium and Vitamin E Cancer Prevention Trial (SELECT), sponsored by the National Cancer Institute, is an intergroup Phase III, randomized, double-blind, placebo-controlled, population-based clinical trial designed to test the efficacy of selenium and vitamin E alone and in combination in the prevention of prostate cancer. The study has a 2 × 2 factorial design with a target accrual of 32,400. Eligibility criteria include an age of at least 50 years for African Americans and of at least 55 years for Caucasians; a DRE not suspicious for cancer; a serum PSA no greater than 4 ng/mL; and a normal blood pressure. Randomization will be equally distributed among the four study arms, with intervention consisting of a daily oral dose of study supplement (200 μg I-selenomethionine or 400 mg of racemic α-tocopheryl) or matched placebo. Study duration is planned for 12 years, with a 5-year uniform accrual period and a minimum of 7 and maximum of 12 years of intervention. The primary endpoint for SELECT is the clinical incidence of prostate cancer as determined by a recommended routine clinical diagnostic work-up, including yearly DRE and serum PSA level. SELECT is the second large-scale study of chemoprevention for prostate cancer. Enrollment began in 2001, with final results anticipated in 2013. © 2004 New York Academy of Sciences.
Keywords: Chemoprevention; Prostate cancer; Selenium; Vitamin E

Dietary manipulation, ethnicity, and serum PSA levels - Eastham, J.A.; Riedel, E.; Latkany, L.; Fleisher, M.; Schatzkin, A.; Lanza, E.; Shike, M. (Urology, 2003)
Objectives. To examine whether a diet low in fat and high in fiber, fruits, and vegetables and ethnicity had any influence on serum prostate-specific antigen (PSA) levels, because serum PSA is a marker for the presence of prostate cancer. The incidence of prostate cancer increases with age, varies by ethnicity, and is greater among men with a first-degree relative who has had the disease. Large international variations in the rates of prostate cancer incidence and mortality, as well as the incidence changes in migrants and their offspring, also suggest that exogenous factors, including diet, have a strong influence on the development of this disease. Methods. We used data and blood samples from the Polyp Prevention Trial, a multicenter randomized trial designed to evaluate the impact of a diet low in fat and high in fiber, fruits, and vegetables on the recurrence of colorectal adenomas. Recruitment was from 1991 through 1994. Participants were followed up from their baseline recruitment date for 4 years. From this group, we identified 1100 white men and 97 black men who were 35 years of age or older, did not have prostate cancer, and had serum samples available for study. Results. At baseline, no difference was present in the fat intake for the black and white men (mean ± SE, 90 ± 3.6 g/day and 84 ± 1.0 g/day, respectively; P = 0.15). The baseline serum PSA levels did not vary by ethnicity. For black men, the mean serum PSA level was 2.2 ± 0.36 ng/mL compared with 2.0 ± 0.07 ng/mL for white men (P = 0.64). Although all men assigned to the intervention group markedly reduced their fat intake by approximately 15% and increased their fruit and vegetable intake by approximately 2.25 servings per day, no difference was noted in the kinetics of the serum PSA levels by dietary intervention or race. Conclusions. Although ethnic differences in the incidence of prostate cancer are well defined, we found no difference in the baseline fat intake among black and white men that might have contributed to this difference. Serum PSA, a marker often used in early detection programs for prostate cancer, was not associated with manipulation of the amount of fat in the diet, regardless of ethnicity. © 2003 Elsevier Inc.

Randomized controlled trial of zoledronic acid to prevent bone loss in men receiving androgen deprivation therapy for nonmetastatic prostate cancer - Smith, M.R.; Eastham, J.; Gleason, D.M.; Shasha, D.; Tchekmedyian, S.; Zinner, N. (Journal of Urology, 2003)
Purpose: A multicenter double-blind, randomized, placebo controlled clinical trial was performed to assess the effect of zoledronic acid, a potent new bisphosphonate, on bone mineral density during androgen deprivation therapy for nonmetastatic prostate cancer. Materials and Methods: Men with MO (no distant metastases) prostate cancer beginning androgen deprivation therapy were randomly assigned to receive 4 mg. zoledronic acid or placebo intravenously every 3 months for 1 year. The primary efficacy variable was the percent change from baseline to 1 year in bone mineral density of the lumbar spine as measured by dual energy x-ray absorptiometry. Results: A total of 106 men were enrolled in the trial. Mean bone mineral density in the lumbar spine increased by 5.6% in men receiving zoledronic acid and decreased by 2.2% in those given placebo (mean difference 7.8%, 95% confidence interval 5.6%-10.0%, p <0.001). Mean bone mineral density of the femoral neck, trochanter and total hip also increased in the zoledronic acid group and decreased in the placebo group. Zoledronic acid was well tolerated. Conclusions: Zoledronic acid increases bone mineral density in the hip and spine during androgen deprivation therapy for nonmetastatic prostate cancer. Indications:Prevention of bone loss in 55 patients on androgen deprivation therapy. Coexisting disease: prostate cancer in all patients. Patients:106 male patients. Zometa group: n=55, mean age 71.1±8.6 years (median 73 years), 47 Whites, 3 Blacks, 2 Orientals, 8 dropouts (2 due to side effects). Placebo group: n=51, mean age 70.2±9.3 years (median 72 years), 37 Whites, 8 Blacks, 2 Orientals, 8 dropouts (3 due to side effects). TypeofStudy:A multicenter double-blind, randomized, placebo controlled study assessing the effect of Zometa on bone mineral density in men receiving androgen deprivation therapy for nonmetastatic prostate cancer. DosageDuration:4 mg iv for 15 minutes in 100 ml of 0.9% saline every 3 months for 1 year. Results:In the Zometa group 47 (86%) and in the placebo group 42 (82%) men completed the study. Lumbar spine bone mineral density increased 5.6% from baseline to 1 year in the Zometa group (p <0.001 for within treatment change from baseline) and decreased 2.2% in the placebo group (p = 0.012 for within treatment change from baseline). The difference of 7.8% in mean percent change at 1 year between the 2 groups was statistically significant (p <0.001). The difference in change from baseline in lumbar spine bone mineral density between the Zometa and placebo treatment groups was also significant in the treatment subgroups, in men with normal baseline lumbar spine bone mineral density (T-score -1 or greater) and in those with low baseline bone mineral density (T-score less than -1, -3 or greater). In the Zometa group bone mineral density also increased significantly from baseline in the femoral neck, trochanter and total hip. The mean difference in percent change from baseline differed significantly between Zometa and placebo in the femoral neck, tro-chanter, and total hip (p <0.001) but not in the nondominant forearm. No patient had a clinical (symptomatic) fracture. There were 5 radiographically diagnosed new or worsening vertebral fractures in the Zometa group and 3 in the placebo group (p = 0.29). Of the 8 men with vertebral body fractures 3 had low baseline bone mineral density of the spine and/or hip (T-scores less than - 1.0). Mean total testosterone decreased to castrate levels (less than 50 ng/dl) in both groups at 12 weeks and remained suppressed throughout the study. Mean prostate specific antigen (PSA) also decreased significantly from baseline to the end of the study in both groups. There were no statistically significant differences between the Zometa and placebo groups in the mean change from baseline in either total testosterone or PSA (p = 0.98 and p = 0.55, respectively). Severe (grade 3 or 4) adverse events were reported in 13/55 (24%) of men in the Zometa group and 20/51 (39%) in the placebo group. 2 men in the Zometa group and 3 in the placebo group withdrew from the study due to an adverse event. No adverse event of renal failure, increased serum creatinine or renal impairment was reported for any patient. AdverseEffects:32 patients experienced hot flushes, 21 fatigue, 12 arthralgia, 9 constipation, 9 nocturia, 8 urinary frequency, 7 dysuria, 7 limb pain, 7 weakness, 6 back pain, 6 erectile dysfunction, and 6 hematuria. Severe (grade 3 or 4) adverse events were reported in 13 patients. No patient experienced renal failure, increased serum creatinine or renal impairment. 2 patients withdrew due to side effects. AuthorsConclusions:Intermittent administration of zoledronic acid not only prevents treatment related bone loss, but also increases bone mineral density in men receiving androgen deprivation therapy for nonmetastatic prostate cancer. FreeText:Androgen deprivation therapy consisted of gonadotropin releasing hormone (Gn-RH) agonist (n=31), Gn-RH agonist plus antiandrogen (23), and orchiectomy (1). Other concomitant medications included calcium supplement (500 mg) and multivitamin containing vitamin D (400 IU) daily in all patients. The primary efficacy variable was the percent change from baseline to the end of the study (1 year) in bone mineral density of lumbar vertebrae L2-L4 as measured by dual energy x-ray absorptiometry. Bone mineral density of the total hip, femoral neck, trochanteric region and nondominant forearm was also measured by dual energy x-ray absorptiometry. The incidence of new and worsening vertebral fractures was assessed by radiological survey of the spine (anterolateral and lateral cervical, thoracic and lumbar spine) at baseline and at the end of the study. Safety assessments included serum chemistry, complete blood count, and urinalysis.
Keywords: Bone density; Diphosphonates; Osteoporosis; Prostatic neoplasms

Changes in the geographical and temporal patterns of cancer incidence among black gold miners working in South Africa, 1964-1996 - McGlashan, N.D.; Harington, J.S.; Chelkowska, E. (British Journal of Cancer, 2003)
We describe here the results of the final 8 years of geographical and temporal data of a 33-year study of the cancer experience of 12.8 million man-years of black miners working on the gold fields of South Africa over the period 1964-96. These workers were recruited from 15 territories, the major areas during the most recent period being Lesotho (26.8%), Transkei (21.5%) and Mozambique (15%). The earliest analyses, 1964-71 and 1972-79, showed hepatocellular and oesophageal cancers to be the most frequent cancers. The final analysis, for 1989-96, however, shows marked temporal changes in the relative position of four cancers or grouped malignancies: respiratory cancer up by 236%, hepatocellular carcinoma down to 32%, oesophageal holding steady, and lymphatic system cancers up by 420%, almost certainly because of association with HIV/AIDS infection. Significant geographical variations occurring between the home areas of the miners are important, as mining operations have little to do with the cancers that develop. The causes are essentially socio-environmental rather than occupational, and this means that the rates of the major cancers in the miners are surrogate measures of the same cancers in the home areas. © 2003 Cancer Research UK.
Keywords: Black gold miners; South Africa

Reported family history of cancer in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial - Pinsky, P.F.; Kramer, B.S.; Reding, D.; Buys, S. (American Journal of Epidemiology, 2003)
The authors analyzed data from almost 150,000 subjects aged 55-74 years enrolled in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial who completed a self-administered baseline questionnaire (1993-2001) that included items about family history of cancer. Male respondents reported significantly less family history of cancer than females. The relative underreporting by male respondents relative to females was greater for female family members (28% lower for sisters and 21% lower for mothers) than for male family members (13% lower for brothers and 9% lower for fathers). Black, Hispanic, and Asian respondents reported significantly less family history of cancer than Whites. Reported family history prevalences for parents decreased with respondents' age, while those for siblings increased with respondents' age. The four most commonly reported cancers in families were breast (11.8%), lung (10.1%), colorectal (9.4%), and prostate (7.3%) cancer. Expected prevalences in family members of history of cancer overall and history of specific types of cancer were calculated using incidence rates and life table data obtained from the Surveillance, Epidemiology, and End Results Program. Overall, the ratio of reported cancer rates to expected cancer rates in family members was approximately 0.7. Liver, bone, stomach, and brain cancer had greater-than-average reported: expected ratios, while lymphoma, bladder cancer, melanoma, and testicular cancer had lower-than-average ratios.
Keywords: Ethnic groups; Family characteristics; Genetic predisposition to disease; Neoplasms; Questionnaires; Sex factors

Factors influencing patient survival in a group of men with prostate cancer in Yaoundé, Cameroon - Angwafo III, F.F.; Atanga, P.N.; Minkoulou, E.; Fouda, P.J.; Kim, K.S.; Adams-Campbell, L.; Zoung-Kanyi, J. (UroOncology, 2003)
Purpose: We evaluated the survival time of patients with stage D cancer of the prostate (CaP) in Yaounde, Cameroon, so as to lay the groundwork for evaluating patient management and outcomes in such communities in sub-Saharan Africa. Patients and Materials: A cohort of 200 patients was recruited at diagnosis and followed over a 171 month period. They had a standard work-up and staging protocol except for the absence of bone scan. Treatment was offered after they were staged following the Whitemore ABCD-system. Standard statistical analysis was performed for quantitative variables and graphs developed for continuous variables. Pearson correlation and Chi-square tests were used to evaluate associations between variables. The Kaplan-Meier product-limit method was used to estimate survival functions and log-rank test to compare data from complete survival curves. The statistical significance level was fixed at p values less than or equal to 0.05. Results: The mean age of our patients was 67 years and 41.5% of them were in the 60-69 year-bracket. Survival was worse for those 66 years and older (p = 0.013). Patient survival correlated with tumor differentiation such that a Gleason score of 6 or greater meant diminished survival time (p = 0.014). For the entire group, median overall survival was 40.5 months, 44% at 5 years and 17% at 10 years. Patients who received multi-modal therapy (complete androgen ablation by surgical and medical means, and radiation to the pelvis and metastatic sites) seemed to have the best survival (p < 0.001) although patient stratification into treatment groups was not randomized. A comparison of survival of African-American cohorts and this group showed no statistical significance (p = 0.1). Conclusion: Survival of patients with prostate cancer in Yaounde is just as low as in African-Americans. Survival is worse however, for men older than 66 years in Yaounde. A call for comparative and collaborative clinical trials is made.
Keywords: African-Americans; Africans; Age; Prostate cancer; Stage D; Survival

The perspective of African-American breast cancer survivor-advocates - Lythcott, N.; Green, B.L.; Brown, Z.K. (Cancer, 2003)
BACKGROUND. This article discusses the sometimes unique presentation and course of breast cancer in African-American women and the impact these differences have on the perception of breast disease among African -American women. METHODS. The project described represents the thoughts of many African-American breast cancer survivors, as summarized by three breast cancer survivor-advocates who work through very different national organizations, each of whom has vast experience working directly with African-American breast cancer survivors and their families. RESULTS. In addition to discussions of compelling considerations that have an impact on survivor access, such as agency, culture, and class, other important access questions are raised for research scientists and clinicians that have an impact on the prevention, screening, and detection and treatment of breast cancer in African-American women as well as their accrual to clinical trials. CONCLUSIONS. To eradicate ethnicity-related disparities in breast cancer outcomes for African-American women, it is important for the medical community (clinicians and research scientists) to develop active partnerships with African-American and other breast cancer survivor-advocates in order to establish effective breast health awareness and breast cancer treatment programs and to develop meaningful breast cancer research programs. © 2003 American Cancer Society.
Keywords: Advocate; African American; Agency; Breast cancer; Class; Clinical trials; Culture; Spirituality; Survivor

Patient education for informed decision making about prostate cancer screening: a randomized controlled trial with 1-year follow-up. - Volk, R.J.; Spann, S.J.; Cass, A.R.; Hawley, S.T. (Annals of family medicine, 2003)
PURPOSE: The efficacy of prostate cancer screening is uncertain, and professional organizations recommend educating patients about potential harms and benefits. We evaluated the effect of a videotape decision aid on promoting informed decision making about prostate cancer screening among primary care patients. METHODS: A group of 160 men, 45 to 70 years of age, with no history of prostate cancer, were randomized to view or not to view a 20-minute educational videotape before a routine office visit at a university-based family medicine clinic. The subjects were contacted again 1 year after their visit to assess their receipt of prostate cancer screening (digital rectal examination [DRE] or prostate-specific antigen [PSA] testing), their satisfaction with their screening decision, and knowledge retention since the baseline assessment. RESULTS: Follow-up assessments were completed for 87.5% of the intervention subjects and 83.8% of the control subjects. The rate of DRE did not differ between the 2 groups. Prostate-specific antigen testing was reported by 24 of 70 (34.3%) intervention subjects and 37 of 67 (55.2%) control subjects (P = .01). African American men were more likely to have had PSA testing (9 of 16, 56.3%) than were white men (13 of 46, 28.3%) (P = .044). Satisfaction with the screening decision did not differ between the study groups. Intervention subjects were more knowledgeable of prostate cancer screening than were control subjects, although these differences declined within 1 year (P < .001). CONCLUSIONS: Decision aids for prostate cancer screening can have a long-term effect on screening behavior and appear to promote informed decision making.

Two-year results of multicenter phase III trials on the effect of the addition of sirolimus to cyclosporine-based immunosuppressive regimens in renal transplantation - Kahan, B.D. (Transplantation Proceedings, 2003)
Randomized clinical trials conducted over 24 months and including nearly 1300 renal transplant patients compared the efficacy and safety of two dose levels of sirolimus versus azathioprine (United States) or placebo (Global) comparators administered with a cyclosporine (CsA) and prednisone (Pred) baseline regimen. Analysis of 24-month data revealed that patients in the 5 mg/d sirolimus groups experienced a significant delay in the onset and reduction in the incidence of acute rejection episodes compared with azathioprine (Aza) or placebo groups (P = .02/P = .001). Graft and patient survival rates and also the occurrence of transplant-related infections, lymphoproliferative disorders, or malignancies were similar among all treatment arms. Between 12 and 24 months, patients treated with 2 mg/d sirolimus displayed relatively stable mean serum creatinine values, namely 1.9-1.8 mg/dL for the US and 1.8-1.8 mg/dL for the Global (P = NS) studies, which remained higher than those of the comparators. Both 5 mg/d groups showed an increase in mean serum creatinine during this interval, which was significantly higher than the value in both comparators at 24 months. Both sirolimus groups showed persistently elevated triglyceride levels compared with Aza-treated patients at month 24. The Global trial showed a less-pronounced difference in mean fasting triglyceride values compared with placebo. Data from both trials demonstrate that the addition of sirolimus to a CsA-Pred treatment regimen yielded a durable immunosuppressive effect associated with a progressive resolution of adverse side effects over time except for hyperlipidemia, which required continued countermeasure therapy. Indications:Graft rejection prophylaxis in 1260 patients who underwent kidney transplantation. Coexisting diseases: 280 hypertension, and 223 diabetes mellitus. Patients:1260 patients, follow-up was 2 years. U.S. Trial (n=710 patients) - Neoral/sirolimus 2 mg/prednisone group: n=281, 76 females, 208 males, 160 whites, 63 blacks, 48 Hispanics, 7 Asians, 6 other race, age range 16-79 years (mean 44.9±13.6 years), 180 cadaver donor, 86 living-related donor, 18 living unrelated donor, reasons for RTx was renal failure due to glomerulonephritis (64), hypertension (72), diabetes mellitus (59), other/unknown (89), 157 dropouts (33 due to side effects). Neoral/sirolimus 5 mg/prednisone group: n=269, 104 females, 170 males, 154 whites, 62 blacks, 42 Hispanics, 10 Asians, 6 other race, age range 13-76 years (mean 46.8±13.0 years), 167 cadaver donor, 83 living-related donor, 24 living unrelated donor, reasons for RTx was renal failure due to glomerulonephritis (50), hypertension (77), diabetes mellitus (53), other/unknown (94), 169 dropouts (57 due to side effects). Neoral/azathioprine/prednisone group: n=160, 70 females, 91 males, 92 whites, 41 blacks, 15 Hispanics, 10 Asians, 3 other race, age range 12-69 years (mean 45.6±13.0 years), 119 cadaver donor, 33 living-related donor, 9 living unrelated donor, reasons for RTx was renal failure due to glomerulonephritis (18), hypertension (47), diabetes mellitus (32), other/unknown (64), 94 dropouts (21 due to side effects). Global Trial (n=550) - Neoral/sirolimus 2 mg/prednisone group: n=218, 79 females, 148 males, 172 whites, 26 blacks, 6 Hispanics, 10 Asians, 13 other race, age range 15-71 years (mean 45.7±12.3 years), 173 cadaver donor, 39 living-related donor, 15 living unrelated donor, reasons for RTx was renal failure due to glomerulonephritis (65), hypertension (35), diabetes mellitus (28), other/unknown (99), 128 dropouts (36 due to side effects). Neoral/sirolimus 5 mg/prednisone group: n=208, 70 females, 149 males, 175 whites, 27 blacks, 2 Hispanics, 7 Asians, 8 other race, age range 17-68 years (mean 45.1±12.2 years), 174 cadaver donor, 29 living-related donor, 16 living unrelated donor, reasons for RTx was renal failure due to glomerulonephritis (51), hypertension (27), diabetes mellitus (34), other/unknown (107), 154 dropouts (59 due to side effects). Neoral/placebo/prednisone group: n=124, 39 females, 91 males, 103 whites, 13 blacks, 4 Hispanics, 3 Asians, 7 other race, age range 16-71 years (mean 46.0±13.1 years), 99 cadaver donor, 27 living-related donor, 4 living unrelated donor, reasons for RTx was renal failure due to glomerulonephritis (32), hypertension (22), diabetes mellitus (17), other/unknown (59), 75 dropouts (13 due to side effects). TypeofStudy:Two randomized, double-blind, parallel, controlled, multicenter, phase III studies comparing the effects of the addition of sirolimus, azathioprine or placebo to Sandimmun Neoral-based immunosuppressive regimens in renal transplantation (RTx). Open study for Neoral. DosageDuration:Initially 9-12 mg/kg/ daily as oral microemuslion administered in the morning within 48 hours of transplantations and adjusted to maintain whole blood trough concentrations (Cminss) within the range of 200-350 ng/mL during month 1, 200-300 ng/mL during month 2, and 150-250 ng/mL thereafter. Duration: 2 years. Results:In both trials, the Neoral doses were tapered over each time interval during 24 months, in accordance with protocol-mandated trough concentration targets, resulting in a significantly decreased Cminss exposure at 24 compared with 12 months. Patients under azathioprine or placebo treatment required significantly higher doses of Neoral than those in the sirolimus cohorts to achieve equal drug exposure. Dose-normalized Neoral exposure was significantly lower among patients in the azathioprine and placebo groups than in the sirolimus group. The area under the curve (AUC) revealed mean overall intersubject variabilities for the 2 mg/d (n = 19) and the 5 mg/d (n = 23) sirolimus arms. The corresponding intrasubject variabilities were 24% and 41%, respectively. The mean overall intersubject variabilities of Neoral exposure were only slightly less than that of sirolimus. The mean intrasubject variabilities for Neoral were %CV = 25% for the US trial and %CV = 28% for the Global trial, which was similar to that of sirolimus. A significant delay in the onset of biopsy-confirmed acute rejection episodes among patients treated with sirolimus 5 mg/day compared with those receiving azathioprine or placebo was observed. Furthermore, this dose provided a significant reduction in the incidence of acute rejection episodes at 24 months in both the US and Global trials. Graft survival rates at 24 months showed no significant differences between treatment groups in both trials. The second most common causes of graft loss were acute rejection (n = 33; 2.5%) or acute tubular necrosis (n = 30; 2.3%). Patient survival at 24 months showed similar rates among treatment groups in the US and Global trials. Pairwise comparisons of the mean 24-month serum creatinine concentrations to determine graft function revealed that the aggregate values of all patients in the 2 and the 5 mg/day study groups were higher than those of patients in the azathioprine (1.5 mg/dL) or the placebo cohorts (1.6 mg/dL). Mean values at 24 months in the comparator and the 2 mg/day groups were fairly similar to those at 12 months. Recipients in the 5 mg/day sirolimus groups showed slightly higher values at 24 months. Changes in mean calculated creatinine clearances were consistent with the creatinine data. The overall rates of discontinuation were similar among all groups in both trials except for the 5 mg/day cohort in the Global study. The primary reason for discontinuations in the comparator groups was poor efficacy; conversely, the sirolimus 5 mg/d group showed higher rates of discontinuation due to adverse events or intercurrent medical problems (US study). Sirolimus treatment was not associated with an increased risk of malignancy within 24 months. The distribution of malignancies and the incidence of posttransplant lymphoproliferative disease (PTLD) across treatment groups were similar at 24 months. Bacterial infections occurred at similar frequencies among recipients in both trials except for urinary tract infections, which occurred less often among patients receiving sirolimus 2 mg/day in the US study. Some commonly reported adverse events included peripheral edema, hypertension, and headache. The incidence of clinically important events associated with Neoral toxicity such as tremor and serious infections (US trial), hypertension (Global trial), and diabetes (both trials) were not affected by the addition of sirolimus. However, an increased incidence of diarrhea, rash, epistaxis, and HSV infection seemed to be attributable to the addition of sirolimus to a Neoral-prednisone regimen. The increase in adjusted mean aspartate aminotransferase (AST) values, which had been noted by pairwise comparisons of values at earlier time points, proved to be transient and were not sustained at 24 months. Although the mean platelet counts were not significantly different from the comparators at 24 months, the cumulative incidence of investigator-reported thrombocytopenia was higher among the sirolimus groups. Although hemoglobin values at 24 months were not significantly different among all treatment groups in the US trial, patients in the sirolimus 2 and 5 mg/day groups of the Global study displayed significantly lower hemoglobin values than those receiving placebo. Only 2 patients in each trial discontinued study medication because of anemia. AdverseEffects:219 patients discontinued due to side effects. 16 patients experienced lymphoma/posttransplant lymphoproliferative disorder, 20 basal cell carcinoma, 19 squamous cell carcinoma, 3 melanoma, 2 breast cancer, 4 lung cancer, 1 prostate cancer, 1 renal cancer, 1 pancreas cancer, 2 gastrointestinal cancer, 3 genitourinary cancer, 2 other cancers, 2 anemia (led to withdrawal), 509 hypertension, 481 hypercholesterolemia, 191 hyperkalemia, 708 peripheral edema, 349 diarrhea, 116 leukopenia, 187 thrombocytopenia, 510 hyperlipidemia, 303 arthralgia, 136 rash, 340 headache, 72 epistaxis, 107 diabetes mellitus. Unspecified number had hypertriglyceridemia (21 led to withdrawal), increased alanine aminotransferase blood level, increased lactate dehydrogenase blood level, urinary tract infection/pyelonephritis, sepsis, pneumonia, wound infection, cytomegalovirus infection, herpes simplex virus infection, herpes zoster virus infection, and Epstein-Barr virus infection. AuthorsConclusions:Data from both trials demonstrate that the addition of sirolimus to a CsA [cyclosporin A]-Pred [prednisone]treatment regimen yielded a durable immunosuppressive effect associated with a progressive resolution of adverse side effects over time except for hyperlipidemia, which required continued countermeasure therapy. FreeText:Concomitant medications included sirolimus (maintenance dose of 2 or 5 mg daily) as an oral solution (1 or 2.5 mg/mL) administered in 2 mL dose 4 hours after the morning dose of Neoral after a single 6 mL loading dose of 6 or 15 mg, azathioprine (2-3 mg/kg daily), prednisone, and placebo. The primary efficacy endpoint was efficacy failure defined as the composite of the first occurrence of graft loss, death, or biopsy-confirmed acute rejection episode. Secondary endpoints were patient and graft survival at 24 months, as well as the time to, histologic grade of, and need for antibody therapy for treatment of the first biopsy-confirmed acute rejection episode.

Outcomes and toxicity in African-American and Caucasians patients in a randomized adjuvant chemotherapy trial for colon cancer - McCollum, A.D.; Catalano, P.J.; Haller, D.G.; Mayer, R.J.; Macdonald, J.S.; Benson III, A.B.; Fuchs, C.S. (Journal of the National Cancer Institute, 2002)
Background: Previous studies have demonstrated that African-Americans with colon cancer have worse overall and stage-specific survival rates than Caucasians. Such differences could reflect variation in access to health care, in tumor biology, or in treatment efficacy. Little is known about potential differences in chemotherapy-related toxicities between African-Americans and Caucasians. In this study, we examined survival and toxic effects among African-American and Caucasian patients enrolled in a large, randomized phase III trial of adjuvant chemotherapy for resected colon cancer. Methods: We analyzed data on 3380 patients (344 African-Americans and 3036 Caucasians) enrolled in a randomized trial of adjuvant 5-fluorouracil-based chemotherapy in patients with stage II (high risk) and stage III colon cancer to evaluate differences in outcomes and toxicity. We compared disease-free survival (DFS) and overall survival (OS) between African-Americans and Caucasians by the Kaplan-Meier method, computed Cox proportional hazards by multivariable analysis, and compared treatment-related toxicity rates by Fisher's exact test. All statistical tests were two-sided. Results: We found no differences in DFS or OS between African-American and Caucasian patients. Five-year DFS was 57% (95% confidence interval [CI] = 52% to 62%) for African-Americans and 58% (95% CI = 56% to 60%) for Caucasians (P = .15), and 5-year OS was 65% (95% CI = 60% to 70%) for African-Americans and 66% (95% CI= 64% to 68%) for Caucasians (P = .38). On multivariable analysis, no statistically significant difference in disease recurrence or death was detected between the racial/ethnic groups (hazard ratios for African-Americans versus Caucasians: disease recurrence = 1.1, 95% CI = 0.9 to 1.3; death = 1.1, 95% CI = 0.9 to 1.3). Treatment-related toxicity differed between the African-American and Caucasian patients, with African-Americans experiencing statistically significantly lower rates of diarrhea (P<.001), nausea (P<.001), vomiting (P = .01), stomatitis (P<.001), and overall toxicity (P = .005). Conclusions: In this study of patients with similar access to health care resources and treatment with adjuvant chemotherapy, we found similar 5-year DFS and OS in African-Americans and Caucasians with stage II and III colon cancer. The two groups derived similar benefits from adjuvant chemotherapy. Moreover, African-Americans appeared to experience less treatment-related toxicity.

The study of tamoxifen and raloxifene: Preliminary enrollment data from a randomized breast cancer risk reduction trial - Vogel, V.G.; Costantino, J.P.; Wickerham, D.L.; Cronin, W.M.; Wolmark, N. (Clinical Breast Cancer, 2002)
Tamoxifen reduced the risk of invasive breast cancer by 49% among women at increased risk for breast cancer in the Breast Cancer Prevention Trial P-1, and raloxifene reduced breast cancer incidence by more than 70% in the Multiple Outcomes of Raloxifene Evaluation osteoporosis trial. These findings led the National Surgical Adjuvant Breast and Bowel Project to design and launch the Study of Tamoxifen and Raloxifene. Risk-eligible women are ≥ 35 years of age and postmenopausal; they have either lobular carcinoma in situ (LCIS) or a 5-year risk of invasive breast cancer of at least 1.67% as determined by the Gail model. Participants are randomly assigned to receive either tamoxifen 20 mg or raloxifene 60 mg daily. The trial opened for accrual on July 1, 1999. After 32 months of recruitment at 194 clinical centers in North America, risk assessments have been performed in 107,855 women (83.8% white, 9.4% black, 3.8% Hispanic, 3.1% other race/ethnic groups). Of the eligible patients, 12,637 have been randomized (20.9% of risk-eligible women); the median age is 58 years (mean, 58 years), and the median 5-year risk of breast cancer is 3.3% (mean, 4.0%). LCIS was reported in 8.4% of women prior to randomization. Gail model risk was ≥ 3.0% in 5 years for 59.3% of white women, 45.0% of black women, and 44.5% of Hispanic women. The trial will recruit a total of 22,000 postmenopausal women and is powered to demonstrate superior efficacy of either agent or their equivalence in reducing the incidence of primary breast cancer.
Keywords: Gail risk scores; Lobular carcinoma in situ; Raloxifene; Risk reduction; Tamoxifen

Comparisons of tailored mammography interventions at two months postintervention - Champion, V.L.; Skinner, C.S.; Menon, U.; Seshadri, R.; Anzalone, D.C.; Rawl, S.M. (Annals of Behavioral Medicine, 2002)
The recent decrease in breast cancer mortality has been linked in part to increased breast cancer screening. Although the percentage of women screened once is rising, rate of continued adherence is poor. The purpose of this article is to assess the effects of tailored mammography interventions implemented prospectively in a factorial design contrasting groups receiving either (a) usual care (no intervention), (b) tailored telephone counseling for mammography, (c) tailored mailed materials promoting mammography, or (d) a combination of tailored mail and telephone counseling. This prospective, randomized study with a 2 × 2 factorial design included women 51 years and older (N = 1,367) who were not adherent with mammography at baseline. The intervention is based on integration of the Transtheoretical and Health Belief Models. Participants were enrolled in one of two health maintenance organizations or seen in a university-related primary care clinic. Baseline data were collected on mammography history and beliefs and knowledge related to mammography. Data were collected via telephone interviews using previously developed scales. The follow-up interviewers were conducted with 976 women. The sample was 41% White, 56% African American, and 3% other. Mean age at baseline was 66.5. Logistic regression indicates that postintervention mammography status in all three intervention groups was significantly better than usual care, with odds ratios ranging from 1.66 (telephone only) to 2.16 (telephone plus mail).

Randomized trial of black cohosh for the treatment of hot flashes among women with a history of breast cancer - Jacobson, J.S.; Troxel, A.B.; Evans, J.; Klaus, L.; Vahdat, L.; Kinne, D.; Lo, K.M.S.; Moore, A.; Rosenman, P.J.; Kaufman, E.L.; Neugut, A.I.; Grann, V.R. (Journal of Clinical Oncology, 2001)
Purpose: Most breast cancer survivors experience hot flashes; many use complementary or alternative remedies for these symptoms. We undertook a randomized clinical trial of black cohosh, a widely used herbal remedy for menopausal symptoms, among breast cancer patients. Patients and Methods: Patients diagnosed with breast cancer who had completed their primary treatment were randomly assigned to black cohosh or placebo, stratified on tamoxifen use. At enrollment, patients completed a questionnaire about demographic factors and menopausal symptoms. Before starting to take the pills and at 30 and 60 days, they completed a 4-day hot flash diary. At the final visit, they completed another menopausal symptom questionnaire. Follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels were measured in a subset of patients at the first and final visits. Results: Of 85 patients (59 on tamoxifen, 26 not on tamoxifen) enrolled in the study, 42 were assigned to treatment and 43 were assigned to placebo; 69 completed all three hot flash diaries. Both treatment and placebo groups reported declines in number and intensity of hot flashes; the differences between the groups were not statistically significant. Both groups also reported improvements in menopausal symptoms that were, for the most part, not significantly different. Changes in blood levels of FSH and LH also did not differ in the two groups. Conclusion: Black cohosh was not significantly more efficacious than placebo against most menopausal symptoms, including number and intensity of hot flashes. Our study illustrates the feasibility and value of standard clinical trial methodology in assessing the efficacy and safety of herbal agents. © 2001 by American Society of Clinical Oncology.

The effect of patient reminders on the use of screening mammography in an urban health department primary care setting - Simon, M.S.; Gimotty, P.A.; Moncrease, A.; Dews, P.; Burack, R.C. (Breast Cancer Research and Treatment, 2001)
Mammography screening continues to be under-utilized, especially among women from lower socioeconomic groups. In order to determine whether having direct access to health care services has an effect on mammography use among low income women, we conducted a randomized trial of two alternative letter reminders among 1,717 women who were enrolled at two locations of a multi-site inner city health department in Detroit. All participants were 39 1/2 years of age and older and were due for a screening mammogram at randomization. A physician-directed reminder form was placed in each of the participant's medical records at the beginning of the study. In addition participants were randomized to receive either a letter directing them to visit their primary care physician, a letter directing them to contact the clinic directly to schedule a mammogram, or no letter. Study participants were predominantly African - American, two-thirds of whom were over age 50, and who had minimal health insurance coverage. During the intervention year, mammograms were completed by 179 out of 967 study women at site one (18.5%), and 90 out of 750 study women at site two (12%). A multivariate model controlling for the simultaneous effect of age, insurance type, visit history and past mammography use, showed no significant independent effect of either type of letter reminder on mammography completion during the study year. In conclusion, letters targeted at women due for screening mammograms did not have a beneficial effect on mammography utilization above and beyond that of a physician medical record reminder.
Keywords: Behavioral intervention; Breast neoplasm; Mammography; Randomized controlled trial

Molecular epidemiologic studies within the Selenium and Vitamin E Cancer Prevention Trial (SELECT) - Hoque, A.; Albanes, D.; Lippman, S.M.; Spitz, M.R.; Taylor, P.R.; Klein, E.A.; Thompson, I.M.; Goodman, P.; Stanford, J.L.; Crowley, J.J.; Coltman, C.A.; Santella, R.M. (Cancer Causes and Control, 2001)
Objective: To conduct timely epidemiologic investigations of molecular/genetic markers that may contribute to the development of prostate, lung, colorectal, or other cancers within the Selenium and Vitamin E Cancer Prevention Trial (SELECT), and to evaluate interactions between these markers and the study interventions. Methods: The epidemiologic studies within SELECT will be based on 32, 400 men aged 55 years or older (age 50 or older for the African-American men) enrolled into an intergroup, randomized, placebo-controlled, double-blind, phase III prevention trial of supplemental selenium and vitamin E developed and funded by the National Cancer Institute, and coordinated by the Southwest Oncology Group. During the 12-year study period approximately 1500-2000 cases of prostate cancer, 800 lung cancers, and 500 colon cancers are estimated to be diagnosed, based on data from the ongoing Prostate Cancer Prevention Trial of finasteride. A modified fasting blood sample will be processed to collect plasma for analysis of micronutrients, hormones, cytokines, and other proteins. Buffy-coat derived white blood cells collected at baseline will be used for isolation of DNA and establishment of immortalized cell lines. Red blood cells will be stored for analysis of hemoglobin adducts and other components. Results: Specific results anticipated from these molecular studies will provide information on factors hypothesized to contribute to prostate cancer risk and that may modify the efficacy of either trial supplement, including: steroid sex hormones and several polymorphic genes that encode proteins affecting androgenic stimulation of the prostate, including the androgen receptor, steroid 5α-reductase type II, CYP17, and β-hydroxysteroid dehydrogenase; polymorphisms of DNA repair genes and carcinogen metabolism genes, including those involved in the activation of chemical carcinogens to reactive intermediates (e.g., CYP1A1) or the detoxification of reactive intermediates (e.g., glutathione S-transferase M1); DNA and protein adducts; and insulin-like growth factors and leptin. Conclusion: SELECT offers an excellent opportunity to conduct molecular epidemiologic investigations to assess gene-environment interactions and their role in prostate, lung, and colon carcinogenesis.
Keywords: Molecular epidemiology; Primary prevention; Prostate cancer; Selenium; Vitamin E

The study of Tamoxifen and Raloxifene: Preliminary enrollment data from a randomized breast cancer risk reduction trial - Vogel, V.G.; Costantino, J.P.; Wickerham, D.L.; Cronin, W.M.; Wolmark, N. (Breast Cancer Research and Treatment, 2001)
In the Breast Cancer Prevention Trial (BCPT, P1) tamoxifen reduced the risk of invasive breast cancer by 49% in women at increased risk. In subset analyses of older postmenopausal women taking raloxifene for the treatment of osteoporosis (MORE trial) breast cancer incidence was reduced by more than 70%. These findings led the National Surgical Adjuvant Breast and Bowel Project (NSABP) to design and launch the Study of Tamoxifen and Raloxifene (STAR trial). Eligible women are at least 35 years of age and postmenopausal, and they must have either lobular carcinoma in situ (LCIS) or a 5-year risk of invasive breast cancer of at least 1.67% as determined by the Gail model. Subjects are randomly assigned to receive either tamoxifen 20 mg or raloxifene 60 mg daily in a double-blind, double dummy design. The trial opened for subject accrual on July 1, 1999. After 22 months of active recruitment at 193 clinical centers in North America through April 30, 2001, risk assessments have been performed in 83,057 women (85.2% white, 8.6% black, 3.4% Hispanic. 2.8% other), and 47,325 (57.0%) were eligible for the trial. Of the eligible subjects. 9,710 have been randomized (20.5% of those eligible). The median age of randomized women is 58 yrs (mean 58), 94.6% are white, and their median 5-yr risk of breast cancer is 3.3% (mean 4.0%). Hysterectomy was reported by 52.1 % of the randomized women; LCIS was reported by 8.5% of subjects prior to randomization. The proportion of randomized subjects with Gail model risk 3.0% by race was white, 27.9%; black, 44.1%; Hispanic, 59.3%. The trial is designed to recruit a total of 22,000 postmenopausal women and is powered to demonstrate superior efficacy of either agent or their equivalence in reducing the incidence of primary breast cancer. Additional endpoints include the incidence of cardiovascular events and bone fractures. Thromboembolic events and endometrial cancer are the predicted toxicities. Serum and lymphocytes are being collected for future studies after appropriate informed consent. Ancillary studies of cognitive function will also be performed. The successful recruitment of nearly 10,000 subjects in less than 2 years demonstrates the willingness of high-risk postmenopausal women to participate in breast cancer chemoprevention clinical trials.

A Phase II trial of bryostatin 1 in the treatment of metastatic colorectal cancer - Zonder, J.A.; Shields, A.F.; Zalupski, M.; Chaplen, R.; Heilbrun, L.K.; Arlauskas, P.; Philip, P.A. (Clinical Cancer Research, 2001)
Current chemotherapy for patients with advanced colorectal cancer is relatively ineffective and may be associated with significant toxicity. Bryostatin 1 (bryo 1) influences cell proliferation, intracellular metabolism and signaling, differentiation, and apoptosis in human cancer cell lines via modulation of protein kinase C (PKC) activity. This trial investigates the efficacy and toxicity of bryo 1 as a novel therapeutic agent for patients with advanced colorectal cancer who have had previous 5-fluorouracil therapy. The primary end point was tumor response to bryo 1. Toxicity was also assessed. Twenty-eight patients with advanced colorectal cancer were enrolled. The mean age was 59 years (range, 38-76), with 16 men and 12 women, and good minority representation (11 African-Americans). The first 10 patients initially received 25 μg/m2of bryo 1 weekly as a 24-h infusion for 3 weeks of every 4-week cycle, with dose escalation to 35 μg/m2starting with the second cycle. The remaining patients were started at 35 μg/m2and escalated to 40 μg/m2if toxicity was minimal. Twenty-five patients were evaluable for objective tumor response, and complete data on toxicity were collected on 26 patients. No partial or complete tumor responses were observed. All 25 patients had disease progression within four cycles. Myalgia was the most common toxicity. Myelosuppression was not seen. bryo 1 as a weekly 24-h continuous infusion lacks single-agent antitumor activity in advanced colorectal cancer. Toxicity differs from that of traditional chemotherapeutic drugs.

Comparisons of two breast cancer risk estimates in women with a family history of breast cancer - McTiernan, A.; Kuniyuki, A.; Yasui, Y.; Bowen, D.; Burke, W.; Culver, J.B.; Anderson, R.; Durfy, S. (Cancer Epidemiology Biomarkers and Prevention, 2001)
There is an increasing need for accurate prediction methods of assessing individual risk for breast cancer for both clinical and research purposes. The purpose of this study is to compare the Gail and Claus model risk estimates of breast cancer among women with a family history of breast cancer. This study presents risk estimates from two models of breast cancer risk in 491 women 18 to 74 years of age with a family history of breast cancer who were recruited to risk counseling clinical trials in Seattle, Washington between 1996 and 1997. These trials included women from the general population and additional samples of Ashkenazi Jewish, African-American, and lesbian women. We estimated and compared lifetime (to age 79) and 5-year risk for developing breast cancer using the National Surgical Adjuvant Breast and Bowel Project adaptation of the Gail model and the Claus model. About one-quarter of participants fell into the Gail "high" risk category (≥1.7% risk of developing breast cancer in the next 5 years). The average lifetime risk was estimated at 13.2% by the Gail model and 11.2% by the Claus model. Estimates from the two models were moderately and positively correlated (r = 0.55) with the Gail model yielding a higher estimate than the Claus model for most participants. If women with a family history of breast cancer are being counseled regarding decisions on genetic testing, tamoxifen use, or other preventive measures, presenting both Claus and Gail estimates may be the best option.

Health related quality of life differences between black and white men with prostate cancer: Data from the cancer of the prostate strategic urologic research endeavor - Lubeck, D.P.; Kim, H.; Grossfeld, G.; Ray, P.; Penson, D.F.; Flanders, S.C.; Carroll, P.R. (Journal of Urology, 2001)
Purpose: Understanding the potential consequences of racial differences in prostate cancer outcomes, from survival rates to quality of life considerations, is important for the clinician and patient. We examined demographic, clinical and health related quality of life data comparing black with white patients just after treatment of prostate cancer and 1 year later. Materials and Methods: We analyzed data on 1,178 patients who were newly diagnosed with prostate cancer in the Cancer of the Prostate Strategic Urologic Research Endeavor, a national observational database of men recruited from 35 community and academic urology practices throughout the United States. Patient demographics, clinical characteristics and validated health related quality of life questionnaires were reviewed. A total of 958 white and 161 black patients with prostate cancer who completed at least 2 surveys were compared. Results: The black patients were younger, and had lower income and education levels than white patients. Controlling for age, education and income differences, black patients generally had worse clinical characteristics at presentation and lower baseline health related quality of life data scores in most generic and disease specific categories at treatment. The most notable exception was sexual function, which was the only score that was higher in black patients at treatment. With time, health related quality of life improved in both groups but black patients had slower rates of improvement for general health, bodily pain, physical function, role function, disease worry and bowel function. They continued to have higher sexual function. Conclusions: Significant differences exist in clinical presentation, sociodemographic characteristics, and health related quality of life between black and white men with prostate cancer. These health related quality of life differences remain after treatment. Physicians should not assume that outcomes in black men would be similar to other patients.
Keywords: Minority groups; Prostatic neoplasms; Quality of life

The need for comprehensive educational osteoporosis prevention programs for young women: Results from a second osteoporosis prevention survey - Kasper, M.J.; Peterson, M.G.E.; Allegrante, J.P. (Arthritis Care and Research, 2001)
Objective. To assess osteoporosis knowledge, beliefs, and preventive behaviors among young adult women and to identify sources that they would mostly likely utilize to learn more about the disease. Methods. Information was gathered through a cross-sectional survey of 321 women (mean age 21.6 years; 63.5% were white, 29.2% were black) enrolled in a required undergraduate health course at a southeastern state university. Results. Two hundred seventy-seven (86%) of the survey participants had heard about osteoporosis, but only 3.8% of respondents reported getting both adequate exercise and the recommended 1,200 mg of calcium per day. Respondents believed that they were unlikely to develop osteoporosis and that osteoporosis is less serious than other common causes of morbidity and mortality in women, such as heart disease and breast cancer (P < 0.0001). Brochures, magazines, and short counseling sessions were preferred information sources for learning about osteoporosis. Conclusions. The majority of young women studied are at risk for developing premature osteoporosis. They prefer brochures, magazines, and short counseling sessions during medical office visits to learn about osteoporosis. © 2001 by the American College of Rheumatology.
Keywords: Community intervention; Osteoporosis prevention; Public health education

Effect of timed incentives on subject participation in a study of long-term breast cancer survivors: Are there ethnic differences? - Ashing-Giwa, K.; Ganz, P.A. (Journal of the National Medical Association, 2000)
The recruitment and retention of African Americans into cancer control studies presents a formidable task to the scientific and policy communities as well as patient and advocacy communities. The purpose of this investigation was to assess the role of a timed incentive schedule on response rates in a study of African American and white breast cancer survivors. A mailed quality-of-life survey battery was sent to 583 breast cancer survivors (50% African American, 50% white). Half of the participants received payment in advance, whereas the other half was promised payment. The overall response rate was 54% (n = 278). The timing of incentives did not affect participation rates in either ethnic group. About 51% of the respondents were from the payment-in-advance condition and 49% were from the paid-on-completion condition. Therefore, we conclude that payment on completion may be the more cost-effective approach in studies with higher socioeconomic status patients, such as this sample of breast cancer survivors.
Keywords: Breast cancer; Ethnicity; Psychosocial oncology; Timed incentives

Percentage of free PSA in black versus white men for detection and staging of prostate cancer: A prospective multicenter clinical trial - Catalona, W.J.; Partin, A.W.; Slawin, K.M.; Naughton, C.K.; Brawer, M.K.; Flanigan, R.C.; Richie, J.P.; Patel, A.; Walsh, P.C.; Scardino, P.T.; Lange, P.H.; Dekernion, J.B.; et al. (Urology, 2000)
Objectives. In predominately white populations, measurement of the percentage of free prostate-specific antigen (%fPSA) has been shown to enhance the specificity of total PSA testing for prostate cancer while maintaining high sensitivity and to aid in prostate cancer staging. This study evaluated whether the %fPSA cutoff that maintained a 95% sensitivity in a white population yielded the same sensitivity and specificity in a black population and whether %fPSA was useful in predicting postoperative pathologic features in blacks.Methods. We evaluated 647 white and 79 black men, prospectively enrolled at prostate cancer screening and surgical referral centers. Subjects were 50 to 75 years old with digital rectal examination findings that were not suspicious for prostate cancer and total PSA values between 4.0 and 10.0 ng/mL. All had undergone needle biopsy of the prostate. Hybritech's Tandem total and free PSA assays were used.Results. Ninety-five percent sensitivity was attained with a %fPSA cutoff of 25% in both races. Use of this cutoff could have avoided unnecessary biopsies in 20% of white and 17% of black subjects (P = 0.69). In receiver operating characteristic (ROC) curve analysis, the area under the curve (AUC) for %fPSA was significantly higher than for total PSA in both blacks (0.76 versus 0.56, P <0.01) and whites (0.70 versus 0.54, P <0.001). In both races, higher %fPSA values indicated a lower risk of cancer and also predicted favorable pathologic features in radical prostatectomy specimens.Conclusions. A 25% fPSA cutoff detected 95% of cancers and reduced unnecessary biopsies in both races. Higher %fPSA values were associated with favorable postoperative histopathologic findings in both races. Copyright (C) 2000 Elsevier Science Inc.

Black participation in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial. - Stallings, F.L.; Ford, M.E.; Simpson, N.K.; Fouad, M.; Jernigan, J.C.; Trauth, J.M.; Miller, D.S. (Controlled clinical trials, 2000)
The primary goal of the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial is to learn whether widespread use of screening tests to detect these cancers will reduce associated mortality. Blacks have the highest age-adjusted cancer incidence and mortality rates of any population group in the United States, but several barriers to their participation in clinical research such as the PLCO trial exist. These barriers involve sociocultural, economic, and individual factors, as well as factors inherent in trial designs. Population diversity in the PLCO trial is necessary to preserve scientific validity and generalizability of trial results. Therefore, the National Cancer Institute and the Centers for Disease Control and Prevention are collaborating to ensure adequate representation of blacks in the PLCO trial. For example, the agencies have funded several new activities designed to better understand and overcome barriers to participation in the trial. These activities include the African American Men Project, a randomized trial designed to evaluate the efficacy of three increasingly intensive recruitment interventions in recruiting black men; the establishment of a minority-focused PLCO trial screening center, a study to identify factors that influenced the decisions of black women recruited to participate in the PLCO trial; and a study to examine the psychosocial factors that influence blacks' decision making to engage in cancer screening and participation in research similar to the PLCO trial. The results of these activities will allow for a more thorough examination of cancer-related issues of importance to blacks and will help shed light on factors that influence their decisions to participate in cancer screening and prevention clinical trials.

Recruitment experience in the first phase of the African American Hereditary Prostate Cancer (AAHPC) study. - Royal, C.; Baffoe-Bonnie, A.; Kittles, R.; Powell, I.; Bennett, J.; Hoke, G.; Pettaway, C.; Weinrich, S.; Vijayakumar, S.; Ahaghotu, C.; Mason, T.; Johnson, E.; et al. (Annals of epidemiology, 2000)
The African American Hereditary Prostate Cancer (AAHPC) Study is an ongoing multicenter genetic linkage study organized by Howard University and the National Human Genome Research Institute (NHGRI), with support from the Office for Research on Minority Health and the National Cancer Institute. The goals of the study are to: (i) look for evidence of involvement of chromosome 1q24-25 (HPC1) in African American men with hereditary prostate cancer (HPC) and (ii) conduct a genome-wide search for other loci associated with HPC in African American men. To accomplish these goals, a network has been established including Howard University, the NHGRI, and six Collaborative Recruitment Centers (CRCs). The CRCs are responsible for the identification and enrollment of 100 African American families. To date, 43 families have been enrolled. Recruitment strategies have included mass media campaigns, physician referrals, community health-fairs/prostate cancer screenings, support groups, tumor registries, as well as visits to churches, barber shops, and universities. By far, the most productive recruitment mechanisms have been physician referrals and tumor registries, yielding a total of 35 (81%) families. Approximately 41% (n = 3400) of probands initially contacted by phone or mail expressed interest in participating; the families of 2% of these met the eligibility criteria, and 75% of those families have been enrolled in the study, indicating a 0.5% recruitment yield (ratio of participants to contacts). As the first large-scale genetic linkage study of African Americans, on a common disease, the challenges and successes of the recruitment process for the AAHPC Study should serve to inform future efforts to involve this population in similar studies.

Minority recruitment in the prostate cancer prevention trial. - Moinpour, C.M.; Atkinson, J.O.; Thomas, S.M.; Underwood, S.M.; Harvey, C.; Parzuchowski, J.; Lovato, L.C.; Ryan, A.M.; Hill, M.S.; Deantoni, E.; Gritz, E.R.; Thompson Jr., I.M.; et al. (Annals of epidemiology, 2000)
PURPOSE: African American men have a higher prostate cancer risk profile than that of other men in the United States. The purpose of this manuscript is to summarize the challenges associated with enrolling and randomizing African American and other minority participants in the Prostate Cancer Prevention Trial (PCPT). METHODS: The PCPT is a randomized trial of finasteride versus placebo for preventing prostate cancer in healthy men age 55 years and older; it is coordinated by the Southwest Oncology Group. The manuscript describes demographic and lifestyle characteristics of the PCPT randomized sample (18,882 men) by four racial and ethnic groups (Caucasian, African American, Hispanic, and other). African American men comprised 4% of the total randomized sample compared to our goal of 8%. Minority recruitment was emphasized through the Study Manual and training that occurred at trial activation. Supplemental minority recruitment activities were initiated a year after study activation and continued through the end of the accrual period. Minority recruitment was emphasized as follows: minority recruitment presentations at PCPT training seminars (held during twice yearly Southwest Oncology Group meetings); distribution of additional minority recruitment materials; engagement of four consultants for minority recruitment; production of a Minority Recruitment Manual; and a small pilot study involving minority outreach recruiters at five PCPT sites. RESULTS: The consultants were helpful in implementing the pilot project and in suggesting and reviewing materials for minority recruitment. The five-site pilot project did not increase either enrollment or randomization of minorities (with a possible exception at one site). CONCLUSIONS: We suggest that a long-term perspective is required for successful recruitment of minority participants in clinical trials. Likewise, extensive minority recruitment efforts must be ready to implement at trial activation.

The Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial of the National Cancer Institute: history, organization, and status. - Gohagan, J.K.; Prorok, P.C.; Hayes, R.B.; Kramer, B.S. (Controlled clinical trials, 2000)
The Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial is enrolling 148,000 men and women ages 55-74 at ten screening centers nationwide with balanced randomization to intervention and control arms. For prostate cancer, men receive a digital rectal examination and a blood test for prostate-specific antigen. For lung cancer, men and women receive a posteroanterior view chest X-ray. For colorectal cancer, men and women undergo a 60-cm flexible sigmoidoscopy. For ovarian cancer, women receive a blood test for the CA125 tumor marker and transvaginal ultrasound. Members of the control arm continue with their usual care. Follow-up in both groups will continue for at least 13 years from randomization to assess health status and cause of death. The primary endpoint is mortality from the four PLCO cancers, which accounts for about 53% of all cancer deaths in men and 41% of cancer deaths in women in the United States each year. Blood specimens are collected from screened participants, buccal cell DNA from controls, and histology slides from cases; these are maintained in a biorepository. Participants complete a baseline questionnaire (covering health status and risk factors) and a dietary questionnaire. More than 12,000 participants were enrolled in the pilot phase (concluded in September 1994). Changes in the eligibility criteria followed. As of April 2000, enrollment exceeded 144,500. Data are scanned into designated on-site computers for uploading by participant identification number to the coordinating center for quality checks, archival storage, and preparation of analysis datasets for use by the National Cancer Institute (NCI). Scientific direction is provided by NCI scientists, trial investigators, external consultants, and an independent data safety and monitoring board. Performance and data quality are monitored via data edits, site visits, random record audits, and teleconferences. The PLCO trial is formally endorsed by the American Cancer Society and has been ranked by the American Urological Association as one of the most important prostate cancer studies being conducted. Special efforts to enroll black participants are cosponsored by the U.S. Centers for Disease Control and Prevention.

Dealing with diversity: Recruiting churches and women for a randomized trial of mammography promotion - Derose, K.P.; Hawes-Dawson, J.; Fox, S.A.; Maldonado, N.; Tatum, A.; Kington, R. (Health Education and Behavior, 2000)
There is little documentation about the recruitment process for church-based health education programs. In this study, the authors recruit African American, Latino, and white churches and women members (age 50 to 80) for a randomized church-based trial of mammography promotion in Los Angeles County. Efforts to enhance recruitment began 10 months before churches were invited to participate and included a variety of community-based strategies. Subsequently, 45 churches were recruited over a 5-month period through group pastor breakfast meetings and church-specific follow-up. In close collaboration with the 45 churches, the authors administered church-based surveys over 6 months and identified 1,967 age-eligible women who agreed to be contacted by the program team. It was found that an extended resource intensive period of relationship-building and community-based activities were necessary to conduct church-based programs effectively, particularly among older and ethnically diverse urban populations.

Phase II study of dolastatin-10 in patients with hormone-refractory metastatic prostate adenocarcinoma - Vaishampayan, U.; Glode, M.; Du, W.; Kraft, A.; Hudes, G.; Wright, J.; Hussain, M. (Clinical Cancer Research, 2000)
Dolastatin-10 is a natural, cytotoxic peptide with microtubule-inhibitory and apoptotic effects. It has demonstrated in vitro and in vivo efficacy in the DU-145 human prostate cancer model. A Phase II clinical trial was designed in patients with hormone-refractory prostate cancer. Dolastatin-10 was administered at a dose of 400 μg/m2 i.v. every 3 weeks. Dose escalation to 450 μg/m2 was permitted. Toxicity evaluation was conducted every 2 weeks, and assessment of response was done at the end of every two cycles. Sixteen patients were enrolled between October 1998 to December 1999. The median age was 71 years (range, 59-79 years). Median prostate-specific antigen value was 108 ng/ml (range, 15.3-1672 ng/ml). Of the 15 eligible patients, 7 were Caucasian and 8 were African-American. Eight patients had bone-only metastases, and seven had measurable disease with or without bone metastases. A total of 56 cycles have been administered. Only 2 patients required dose adjustment because of toxicity, and in 5 patients, dose escalation was feasible to 450 μg/m2. The major toxicities observed were grade 3 and 4 neutropenia in 8 patients and grade 3 neuropathy in 1 patient. All 15 patients are evaluable for response. Three patients demonstrated stable disease; 2 of these had bone disease, and 1 had nodal metastasis. All others had disease progression. Dolastatin-10 is very well tolerated in this elderly, pretreated population but lacks significant clinical activity as a single agent.

Underrepresentation of patients 65 years of age or older in cancer- treatment trials - Hutchins, L.F.; Unger, J.M.; Crowley, J.J.; Coltman Jr., C.A.; Albain, K.S. (New England Journal of Medicine, 1999)
Background: Studies have documented the underrepresentation of women and blacks in clinical trials, and their recruitment is now federally mandated. However, little is known about the level of participation of elderly patients. We determined the rates of enrollment of patients 65 years of age or older in trials of treatment for cancer. Methods: We analyzed data on 16,396 patients consecutively enrolled in 164 Southwest Oncology Group treatment trials between 1993 and 1996 according to sex, race (black or white), and age under 65 years or 65 or older. These rates were compared with the corresponding rates in the general population of patients with cancer, derived from the 1990 U.S. Census and from the National Cancer Institute's Surveillance, Epidemiology, and End Results Program for the period from 1992 through 1994. Fifteen types of cancer were included in the analysis. Results: The overall proportions of women and blacks enrolled in Southwest Oncology Group trials were similar to or the same as the estimated proportions in the U.S. population of patients with cancer (women, 41 percent and 43 percent; blacks, 10 percent and 10 percent, respectively). In contrast, patients 65 years of age or older were underrepresented overall (25 percent vs. 63 percent, P<0.001) and in trials involving all 15 types of cancer except lymphoma. The underrepresentation was particularly notable in trials of treatment for breast cancer (9 percent vs. 49 percent, P<0.001). The findings were similar when data on patients who were 70 years of age or older were analyzed, when 15 trials that excluded older patients were eliminated from the analysis, and when community-based enrollment was analyzed separately from enrollment at academic centers. Conclusions: There is substantial underrepresentation of patients 65 years of age or older in studies of treatment for cancer. The reasons should be clarified, and policies adopted to correct this underrepresentation.

Factors associated with weight gain in women after diagnosis of breast cancer - Rock, C.L.; Flatt, S.W.; Newman, V.; Caan, B.J.; Haan, M.N.; Stefanick, M.L.; Faerber, S.; Pierce, J.P. (Journal of the American Dietetic Association, 1999)
Objective: To identify the factors associated with weight gain after diagnosis of breast cancer in a heterogeneous population of women. Design: Descriptive cross-sectional study. Subjects: 1,116 patients who had been diagnosed with stage I, stage II, or stage IIIA primary, operable breast cancer within the previous 4 years. Patients were recruited during enrollment into a diet intervention trial to reduce risk for breast cancer recurrence. Analysis Demographic data, weight history, and physical activity information obtained by questionnaire and medical information obtained by chart review; dietary assessment based on four 24-hour dietary recalls collected by telephone. Associations between weight change after the diagnosis of breast cancer and prediction variables were examined using univariate and multiple linear regression analyses. Results: Overall, 60% of the subjects reported weight gain, 26% reported weight loss, and 14% reported no change in weight after the diagnosis of breast cancer. The overall mean weight change was a gain of 2.7 kg (6 lb). Factors positively and independently associated with weight gain were time since diagnosis of breast cancer, adjuvant chemotherapy, African-American ethnicity, current energy intake, and postmenopausal status at time of study entry. Factors inversely and independently associated with weight gain were prediagnosis body mass index, age at diagnosis, education level, and exercise index score. Applications: Higher energy intake and lower level of physical activity are independently associated with increased risk for weight gain after the diagnosis of breast cancer. Strategies to modify these behaviors are likely to influence the long-term pattern of weight change.

Factors associated with attendance in a voluntary nutrition education program - Damron, D.; Langenberg, P.; Anliker, J.; Ballesteros, M.; Feldman, R.; Havas, S. (American Journal of Health Promotion, 1999)
Purpose. This paper examines factors associated with attendance in a National Cancer Institute-funded randomized trial of nutrition education to increase fruit and vegetable consumption among women served by the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Setting. The study took place at 16 WIC sites in Maryland. Subjects. The participants were 1528 women who were enrolled in WIC or who had children enrolled in WIC, were ≥ 18 years of age, and planned to continue enrollment at that WIC site for at least 6 months (68 % of eligible women approached agreed to participate). Intervention. Women received personal invitations, letters, and telephone reminders from peer educators encouraging their attendance at three bimonthly nutrition sessions. Measures. Demographic data were collected in a baseline survey. Attendance data and telephone and address changes were also collected. The postintervention survey included a question regarding reasons for nonattendance. Focus groups were also held to ascertain reasons for attendance or nonattendance. Chi-square tests of trend and multiple logistic regression, adjusted for within-site correlation, were used in statistical analyses. Results. Fifty-four percent of enrollees attended at least one session. Multiple logistic regression analysis showed increased odds of attending with higher age, breast-feeding, and/or knowledge of the recommendation to eat five or more servings of fruits and vegetables daily. There were decreased odds of attending for pregnant women who already had children. There were nonsignificant trends toward decreased attendance among unmarried women compared with married women and among blacks compared with nonblacks. Reasons given for nonattendance included withdrawal from WIC, moving, conflicting activities, negative feelings about nutrition education, and lack of transportation or child care. Conclusions. The results suggest that numerous barriers hinder participation in nutrition programs aimed at low-income women. These barriers' should be considered by health care professionals when planning intervention programs. Overcoming these barriers presents a major challenge.
Keywords: Attendance; Fruits; Nutrition Education; Vegetables; WIC

'Why don't they come to Pike Street and ask us'?: Black american women's health concerns - Freedman, T.G. (Social Science and Medicine, 1998)
It is well known that black American women are poorly represented in medically oriented research and that this has far reaching implications for their personal health, the health of their families and the overall health of the larger society. The research reported was premised on the assumption that learning more about black American women's beliefs and values regarding health and illness could inform public policy initiatives in the area of cancer prevention and control so that a more equitable basis for participation could be achieved in future medical and scientific research. Qualitative methods of research were used in this investigation. A semi-structured interview guide was used in 36 h. of in-depth and face-to-face interviews with 13 black American women recruited to the study using a snowball technique. The women interviewed were middle-class, professional and semi-professional women. The results of the study indicate that there is a poor understanding by the dominant white medical community concerning the beliefs and values of black patients and that this compromises their health and illness care. The Tuskegee Syphilis Experiment is often used as the rationale for the low recruitment of black women into clinical trials - both therapeutic and non-therapeutic. The women interviewed do not agree with this claim. These women suggest that if they were asked to participate in trials and the trial was relevant to their primary medical concerns they would consider joining. The research results indicate the importance of using specific research methodologies and a number of recommendations are presented.
Keywords: Black women; Cancer prevention; Clinical trials; Health beliefs; Woman

Effects of dialogue and therapeutic touch on preoperative and postoperative experiences of breast cancer surgery: an exploratory study. - Samarel, N.; Fawcett, J.; Davis, M.M.; Ryan, F.M. (Oncology nursing forum, 1998)
PURPOSE/OBJECTIVES: To obtain preliminary data and determine the feasibility of a large-scale experimental study to test the efficacy of the Rogerian Science of Unitary Human Beings-based intervention of dialogue and therapeutic touch (TT) on pre- and postoperative anxiety and mood and postoperative pain from breast cancer surgery. DESIGN: Experimental. SETTING: Mid-Atlantic region; ambulatory. SAMPLE: 29 Caucasian and 2 African American English-speaking women with positive breast cancer biopsy (experimental, n = 14; control, n = 17), ranging in age from 31-84 years old (F = 55.6). METHODS: Treatments administered in subjects' homes within seven days prior to surgery and 24 hours after hospital discharge. Experimental treatment consisted of 10 minutes of TT and 20 minutes of dialogue. Control treatment consisted of 10 minutes of quiet time and 20 minutes of dialogue. Data (Spielberger State-Trait Anxiety Inventory. Affects Balance Scale, and Visual Analog Scale-Pain) were collected at the conclusion of each home visit. MAIN RESEARCH VARIABLES: Anxiety, mood, and pain. FINDINGS: The experimental group had lower preoperative state anxiety than the control groups (p = 0.008). No difference was found for preoperative mood. No differences were found for any postoperative measure. CONCLUSIONS: A large-scale study of dialogue and TT would require changes in design and recruitment strategies. IMPLICATIONS FOR NURSING PRACTICE: Nurses may provide more comprehensive care by incorporating dialogue and TT or quiet time into their pre- and postoperative care. Additional research, however, is recommended to determine the differential effects of dialogue, TT, and quiet time on women's experiences with breast cancer prior to incorporating these noninvasive modalities into clinical practice.

Sociodemographic analysis of patients in Radiation Therapy Oncology Group clinical trials - Chamberlain, R.M.; Winter, K.A.; Vijayakumar, S.; Porter, A.T.; Roach III, M.; Streeter, O.; Cox, J.D.; Bondy, M.L. (International Journal of Radiation Oncology Biology Physics, 1998)
Purpose: To assess the degree to which the sociodemographic characteristics of patients enrolled in Radiation Therapy Oncology Group (RTOG) clinical trails are representative of the general population. Methods and Materials: Sociodemographic data were collected on 4016 patients entered in 33 open RTOG studies between July 1991 and June 1994. The data analyzed included educational attainment, age, gender, and race. For comparison, we obtained similar data from the U.S. Department of Census. We also compared our RTOG data with Surveillance Epidemiology and End Results (SEER) data for patients who received radiation therapy, to determine how RTOG patients compared with cancer patients in general, and with patients with cancers at sites typically treated with radiotherapy. Results: Overall, the sociodemographic characteristics of patients entered in RTOG trials were similar to those of the Census data. We found that, in every age group of African-American men and at nearly every level of educational attainment the proportion of RTOG trial participants mirrored the proportion in the census data. Significant differences were noted only in the youngest category of African-American men, where the RTOG accrues more in the lower educational categories and fewer with college experience. For African-American women, we found a similar pattern in every age group and at each level of educational attainment. As with men, RTOG trials accrued a considerably larger proportion of younger, less educated African-American women than the census reported. Using SEER for comparison, the RTOG enrolled proportionately more African- American men to trials all cancer sites combined, and for prostate and head and neck cancer. In head and neck trials, the RTOG enrolled nearly twice as many African-American men than would be predicted by SEER data. In lung cancer trials, RTOG underrepresented African-American men significantly; however, there was no difference for brain cancer trials. There were no racial differences in RTOG accrual and SEER incidence data for women on trials in brain, lung, and head and neck cancer. However, the RTOG trials accrued nearly twice the proportion of African-American women in cervical cancer trials and in all sites combined, compared to the SEER data. Conclusions. Comparisons with the U.S. Census and SEER show that African- Americans are proportionally well represented in cancer clinical trials conducted by the Radiation Therapy Oncology Group. The comparative analysis indicates that all educational levels in each age group of African-Americans generally mirror the U.S. Census, with one exception. The exception is a significant overrepresentation of less-educated African-Americans in the youngest age category. This exception is counter to the expectation that better-educated patients are more likely to enroll in trials. When compared with SEER data the RTOG trials either parallel or overrepresent African- American men and women, with the only exception being in lung cancer, where men are underrepresented. These results show that, in comparison to the Census and SEER data, the RTOG has fulfilled its commitment to enroll African-American patients in its clinical trials.
Keywords: Accrual; African- Americans; Cancer clinical trials; Cooperative groups; Enrollment; Minority representation; Recruitment

Phase II trial of pyrazine diazohydroxide in androgen-independent prostate cancer - Edelman, M.J.; Meyers, F.J.; Grennan, T.; Lauder, J.; Doroshow, J. (Investigational New Drugs, 1998)
No effective therapy has been demonstrated for hormone refractory prostate cancer (HRPC). Pyrazine diazohydroxide (PZDH) is a novel antineoplastic agent with a broad range of activity in preclinical studies and a moderate toxicity profile in Phase I trials. We undertook a Phase II study of PZDH in HRPC utilizing decline in PSA as the primary end point. Fifteen patients were enrolled, median age of 70 (55-86), median pretherapy PSA 206 ng/ml (range 42-10,000). Four patients were African American. Sites of disease: bone only 7, soft tissue only 2, both 6. All were evaluable for toxicity and response. PZDH was administered at 250 mg/m2 IV every three weeks. The median number of cycles administered was two (range 1-6). Toxicity was mild, with only one patient manifesting serious (grade 3-4) toxicity. Unfortunately, activity was minimal with only a single patient demonstrating a > 75% decline in PSA. As this patient's PSA began to rise almost immediately the response was considered transient and not felt to justify pursuing a second stage of the trial. Supporting this conclusion was the disappointing median survival of 220 days. in summary, we conclude that PZDH, while well tolerated at this dose and schedule has only minimal activity in HRPC.
Keywords: Hormone refractory; Phase II trial; Prostate cancer; Pyrazine diazohydroxide

Effect of a cancer screening intervention conducted by lay health workers among inner-city women - Sung, J.F.C.; Blumenthal, D.S.; Coates, R.J.; Williams, J.E.; Alema-Mensah, E.; Lill, J.M. (American Journal of Preventive Medicine, 1997)
Introduction: We conducted a randomized controlled trial to determine if an in-home educational intervention conducted by lay health workers (LHWs) could increase adherence among low-income, inner-city, African-American women to breast and cervical cancer screening schedules. Methods: We recruited 321 African-American women from diverse inner-city sources. After baseline interviews, they were randomly assigned to either the intervention (n = 163) or the control (n = 158) group. Those in the intervention group were visited in their homes up to three times by LHWs who provided a culturally sensitive educational program that emphasized the need for screening. Results: Ninety- three (93) women in the intervention group and 102 in the control group completed the postintervention interview. For Pap smears, the increase in screening was similar in both groups. For clinical breast exams (CBEs), however, there was a modest increase in the intervention group. The improvement was greatest for mammography, for which there was a 10% to 12% increase. Among women who were not on recommended schedules at baseline, the improvement was substantial and greater in the intervention group. Conclusions: LHWs' intervention appeared to improve the rate at which inner- city women obtained CBEs and mammograms, but had no effect on Pap smears. A high attrition rate weakened our ability to make conclusive statements about the exact impact of the intervention. Medical Subject Headings (MESH): intervention studies, Papanicolaou smear, mammography, urban health, health services, indigenous community health aides, breast.

Hormone levels during dietary changes in premenopausal African-American women - Woods, M.N.; Barnett, J.B.; Spiegelman, D.; Trail, N.; Hertzmark, E.; Longcope, C.; Gorbach, S.L. (Journal of the National Cancer Institute, 1996)
Background: In the United States, 5-year survival rates of 69% and 84%, respectively, have recently been reported for African-American and Caucasian women diagnosed with breast cancer. Differences in the levels of endogenous sex hormones in these populations could explain some of the variation in survival rates, since estrogen is recognized as a risk factor for this type of cancer. Purpose: Dietary factors are known to affect endogenous hormone levels; therefore, our study was designed to determine the serum hormone levels of African-American women consuming a typical North American diet, to determine the effect of a low-fat and high-fiber diet on their serum hormone levels, and to compare the base-line serum hormone levels in the African- American women with hormone data from our study of Caucasian women (n = 68) consuming the same control diet. Methods: Twenty-one healthy, premenopausal, African-American women who agreed to eat only food prepared in a clinical study unit were recruited into the study. The control diet was similar to their usual diet, being high in fat (40% of calories from fat) and low in fiber (12 g/day), and was consumed on average for 3 weeks. The concentrations of estrone (E1), estrone sulfate (E1SO4), estradiol (E2), free E2, androstenedione, and sex hormone-binding globulin (SHBG) in serum samples obtained from the participants during the last week of the control diet and during the follicular phase of their menstrual cycle were determined. The women were then switched to a diet low in fat (20% of calories as fat) and high in fiber (40 g/day); they consumed this diet for two menstrual cycles before blood samples were collected for determination of serum hormone levels. Repeated-measures regression modeling was used to investigate the relationship between diet and hormone levels in African-American and Caucasian women. All P values resulted from two-sided statistical tests. Results: Analysis of serum hormone levels in the African-American women indicated that the change in diet caused a significant decrease in E2 (-8.5 %; 95 % confidence interval [CI] = -16.1% to -0.3%;P-<.03) and E1SO4 (- 16.2%; 95% CI = -22.1% to -9.8%; P<.0001) and a significant increase in androstenedione levels (+18.3%; 95% CI = +10.3% to +26.8%; P<.0001). SHBG levels of the African-American women were 5.6% (95% CI = -14.0% to +3.7%) lower for those on the experimental diet compared with those on the control diet, but the difference was not statistically significant. Comparison of control serum hormone values in the African-American women in this study with those in Caucasian women previously studied indicated that the Caucasian women had statistically significant lower levels of E1 (-37%; 95% CI = - 61.2% to-16.4%; P≤.0002), E2 (-54.5%; 95% CI = -90.9% to-25.1%; P≤.0001), free E2 (-30.2%; 95% CI = -65.7% to -2.3%; P<.03), and androstenedione (- 48.3%; 95% CI = -83.7% to -19.7%; P≤.0004). Conclusion: African-American women appear to have higher levels of serum hormones than Caucasian women, and dietary modification can result in a lowering of serum estrogens.

Representation of African-Americans, Hispanics, and whites in National Cancer Institute cancer treatment trials - Tejeda, H.A.; Green, S.B.; Trimble, E.L.; Ford, L.; High, J.L.; Ungerleider, R.S.; Friedman, M.A.; Brawley, O.W. (Journal of the National Cancer Institute, 1996)
Background: The National Cancer Institute (NCI)-sponsored clinical trials cooperative groups place more than 25 000 American patients in treatment trials every year. Equal access and proportional representation of all races/ethnicities is desired. Purpose: Our objectives were to evaluate the inclusion of African-Americans, Hispanics, and non-Hispanic whites in NCI- sponsored treatment trials and to determine if there is proportional racial/ethnic representation. Methods: During the period of January 1, 1991, through June 30, 1994, 99 495 cancer patients were enrolled in clinical trials and declared themselves as non-Hispanic black, non-Hispanic white, or Hispanic (of any race). In the analysis, participants in NCI treatment trials were subdivided into three age groups: birth to 19 years, 20-49 years, and 50 or more years. The racial/ethnic composition of each of these age groups was compared with the racial/ethnic makeup of the American population with cancer. Estimates of the number of incident cancer cases per year were made for each racial/ethnic group within each age group using data from the Surveillance, Epidemiology, and End Results (SEER) Program and the 1990 Census. The percentage of all cancer patients who were in each racial/ethnic group were compared with the population that entered clinical trials. Comparisons are also made separately for patients with leukemia and breast, colorectal, lung, and prostate cancers. Results: Among patients 0-19 years old, 20-49 years old, and 50 years old or older there is relatively proportional representation of non-Hispanic blacks, Hispanics, and non- Hispanic whites in trials. It is noted that more than 70% of cancer patients aged 0-19 years are estimated to enter cooperative group clinical trials compared with 4.0% of cancer patients aged 20-49 years and 1.5% of patients aged 50 years or older. Conclusions: Accrual of American cancer patients to NCI-sponsored treatment trials generally parallels the incident burden of disease among non-Hispanic African-Americans, Hispanics, and non-Hispanic whites. Implications: This study shows that the NCI clinical trials are, as a whole, racially/ethnically representative of the American population and suggests that there is equal access to NCI clinical trials.

Attitudes of African-Americans regarding prostate cancer clinical trials - Robinson, S.B.; Ashley, M.; Haynes, M.A. (Journal of Community Health, 1996)
The purpose of this study was to qualitatively assess attitudes associated with the willingness of African-Americans to participate in prostate cancer clinical trials. Fifty-six African-American males, 40 years of age and older, were recruited from South Central Los Angeles. Respondents were divided into lower or middle socio-economic groups based on education and occupation. Focus group discussions were conducted to assess their knowledge about prostate cancer and willingness to participate in prostate cancer clinical trials. In addition, information was obtained to identify their incentives and barriers toward participating in prostate cancer research. Middle socio- economic respondents expressed a greater willingness to participate in prostate cancer clinical trials than did men of lower socio-economic status. Many indicated that they would be more likely to participate if they were encouraged to do so by a physician or researcher who was viewed as being competent and compassionate. Barriers to participation in prostate cancer clinical trials included concerns about drug toxicity, medical experimentation and distrust of the medical establishment. Endeavors aimed at increasing minority representation in prostate cancer clinical studies should address these issues.

Screening and prevention trials step up minority recruitment. - Reynolds, T. (Journal of the National Cancer Institute, 1996)

The recruitment of African-Americans to cancer prevention and control studies - Paskett, E.D.; DeGraffinreid, C.; Tatum, C.M.; Margitić, S.E. (Preventive Medicine, 1996)
Background. African-Americans have the highest overall age-adjusted cancer incidence and mortality rates of any population group in the United States. Despite this fact, this group remains underrepresented in cancer prevention and control research studies, primarily because most recruitment strategies result in limited access to African-American populations. Methods. As part of three large-scale cancer prevention and control studies, effective strategies for recruiting African-American participants were developed and implemented. Results. Eight strategies have been identified as successful recruitment strategies for involving African-Americans in cancer prevention and control studies. Utilizing these strategies resulted in recruiting a representative number of African-American participants, in relation to the local population, into the three studies. Conclusions. African-Americans can be recruited to participate in cancer control and prevention studies if plans include special strategies targeted to addressing unique barriers, beliefs, and concerns.
Keywords: African-Americans; cancer prevention; cancer screening; recruitment

Evaluation of race as a prognostic factor in multiple myeloma: An ancillary of Southwest Oncology Group study 8229 - Modiano, M.R.; Villar-Werstler, P.; Crowley, J.; Salmon, S.E. (Journal of Clinical Oncology, 1996)
Purpose: The objective of this investigation was to assess the impact of race (black v white) on the survival of patients with multiple myeloma treated within the context of a large clinical trial. Patients and Methods: A cohort of patients randomized to receive one of two treatment regimens and monitored for at least 10 years was studied to assess the impact of race as a prognostic factor, after adjusting for other known factors such as stage of disease. Patients were recruited from the referral network of the Southwest Oncology Group (SWOG), a national multiinstitutional consortium that includes both academic and community treatment centers. Patients had a diagnosis of multiple myeloma and had not previously been treated for this disease. They were carefully characterized as to demographic and clinical features, and were randomized to receive one of two treatment regimens, which proved to have virtually identical outcomes. The outcome measure was survival, measured from the date of randomization to the date of last contact. Patients still alive at last contact date were treated as censored observations. Results: Survival for black myeloma patients was similar to that for white patients, both overall and adjusted for prognostic factors such as stage. Conclusion: Observed differences in mortality between blacks and whites cannot be attributed to differences in survival after diagnosis, given comparable treatment.

Incidence of Internal Cancers and Ingested Inorganic Arsenic: A Seven-Year Follow-up Study in Taiwan - Chiou, H.-Y.; Hsueh, Y.-M.; Liaw, K.-F.; Horng, S.-F.; Chiang, M.-H.; Pu, Y.-S.; Lin, J.S.-N.; Huang, C.-H.; Chen, C.-J. (Cancer Research, 1995)
In order to elucidate the dose-response relationship between ingested inorganic arsenic and internal cancers, a total of 263 patients with black-foot disease and 2293 healthy residents in the endemic area of arseniasis were recruited and followed up for 7 years. The information on consumption of high-arsenic artesian well water, sociodemographic characteristics, life-style and dietary habits, and personal and family history of cancers was obtained through standardized interviews. The occurrence of internal cancers among study subjects was determined through annual health examinations, home visit personal interviews, household registration data checks, and national death certification and cancer registry profile linkages. A dose-response relationship was observed between the long-term arsenic exposure from drinking artesian well water and the incidence of lung cancer, bladder cancer, and cancers of all sites combined after adjustment for age, sex, and cigarette smoking through Cox's proportional hazards regression analysis. Blackfoot disease patients had a significantly increased cancer incidence after adjustment for cumulative arsenic exposure. © 1995, American Association for Cancer Research. All rights reserved.

Mutagen Sensitivity as a Biological Marker of Lung Cancer Risk in African Americans - Spitz, M.R.; Hsu, T.C.; Wu, X.; Fueger, J.J.; Amos, C.I.; Roth, J.A. (Cancer Epidemiology Biomarkers and Prevention, 1995)
Cigarette smoking is the major determinant of lung cancer. However, only a fraction of smokers develops lung cancer; genetically determined susceptibility factors seem to play an important role also. Previous case-control studies have shown that in vitro bleomycin-induced mutagen sensitivity is an independent risk factor for head-and-neck cancers, and preliminary data suggest a similar association with lung cancer. However, these studies were almost exclusively performed on Caucasian populations. To test whether ethnic differences in cancer risk are due to differences in mutagen sensitivity, we are using the in vitro mutagen sensitivity assay to conduct a case-control study of mutagen sensitivity and lung cancer risk in low-risk (Mexican-American) and high-risk (African-American) groups. Here we report the results of our ongoing study of 209 African-Americans (90 cases and 119 controls) in the Houston-Galveston area. Mexican-American data will be reported separately as case accrual increases. Predictably, all measures of cigarette smoking status (including intensity, duration, tar content, depth of inhalation, and type of cigarette) were significant predictors of risk. In addition, 55.3% of the cases were mutagen sensitive (defined as >1 break/ cell), compared with 24.6% of the controls, with an age-, sex-, and smoking-adjusted odds ratio (OR) of 3.7 (95% confidence limits = 1.4, 9.4). Of interest, higher risks were noted for former smokers (OR = 5.4) compared with current smokers (OR = 3.1) and especially for younger former smokers (<55 years). By histologic-specific analysis, mutagen sensitivity was significantly associated with risk for adenocarcinoma (OR = 4.8) and squamous cell carcinoma (OR = 8.5). Stratified analysis showed that there was an interaction between mutagen sensitivity and current and former smoking and heavy smoking (≥20 pack-years) that appeared to be greater than multiplicative. These risk estimates are generally higher than those we reported for head-and-neck cancer in Caucasian populations. Further research should focus on the cytogenetic and molecular evaluation of whether the break sites are random or occur at specific sites and on comparisons with DNA repair assay systems. © 1995, American Association for Cancer Research. All rights reserved.

A Specific African-American CYP1A1 Polymorphism Is Associated with Adenocarcinoma of the Lung - Taioli, E.; Crofts, F.; Trachman, J.; Demopoulos, R.; Toniolo, P.; Garte, S.J. (Cancer Research, 1995)
A case-control study on lung cancer in African-Americans has been conducted to assess whether a novel African-American-specific polymorphism in the CYP1A1 gene increases the susceptibility to tobacco-related lung cancer. The prevalence of the AA RFLP was 17.1% in the DNA extracted from archived tissue blocks from 76 incident cases of lung cancer, and was 163% in peripheral blood lymphocyte DNA of 123 healthy African-American volunteers recruited from a community in the eastern United States. The analysis by histological type showed an association between adenocarcinoma (AC) of the lung and the AA RFLP (odds ratio, 2.6; 95% confidence interval, 1.1-63). One homozygous variant subject was present among the AC cases. The risk of AC in subjects who both smoke and carry the AA RFLP was more than double, in comparison to subjects who only smoke (relative interaction magnitude under the additive model, 24%). The mean value of pack-year in AC with the polymorphism was 5.0 ± 2.5 and in AC without the polymorphism was 37.2 ± 6S(P < 0.05). Our data suggest that a selective association exists between the AA polymorphism and adenocarcinoma of the lung and that a lower dose of tobacco is sufficient to exert carcinogenic effects on the adenomatous tissue of subjects carrying the AA polymorphism. © 1995, American Association for Cancer Research. All rights reserved.

Changing Dietary Fat Intake in a Diverse Population. Women's Health Trial Feasibility Study in Minority Populations - Henry, H.J.; Bowen, D.; Shattuck, A.; Burrows, E. (Journal of the American Dietetic Association, 1995)
The Women's Health Trial Feasibility Study in Minority Populations (WHT:FSMP) was a multi-center randomized dietary intervention trial. The trial was designed to test whether ethnic minority and low-SES (as measured by education) post-menopausal women, ages 50-69 could be recruited and achieve a dietary pattern that included a reduction in total fat (20% of calories), saturated fat and cholesterol intake, and an increase the intake of fruits, vegetables and grain products. Sixty percent were randomized into a low-fat intervention group and 40% were randomized into a control group (usual diet). The trial was conducted in joint collaboration with the National Cancer Institute; the National Heart, Lung, and Blood Institute; three Clinical Centers - Emory University, University of Alabama at Birmingham, University of Miami; and Fred Hutchinson Cancer Research Center which served as the Statistical and Nutrition Coordinating Center. The recruitment goal for each Clinical Center was 750 women. One center was to randomize 50% or more African-American women, another center was to randomize 50% or more Hispanic women, and the third center was to randomize women in proportions representative of the local population including ethnic minorities and low-SES. A total of 2,208 women (624 African-American, 355 Hispanic and 1,229 Caucasian/Other) were randomized and minority recruitment target goals were successfully met at each Clinical Center. Dietary intake data collected at screening, baseline and follow-up visits included a food frequency questionnaire (FFQ), a four-day food record, and an eating patterns questionnaire. Twenty-four hour recall sub-samples were collected at eight- and fourteen-months post-randomization. Approximately one-half of screened women did not meet the eligibility criteria of consuming 36% or more total calories from fat as determined by the FFQ. The mean baseline fat intake for the intervention group was 39.8% (sd=7.1%, n=1235), and the mean for the control group was 39.0% (sd=6.9%, n=769) as estimated by the FFQ. The dietary intervention counseling program consisted of 18 group sessions during the first year. The group sessions (8 to 15 women per group) were facilitated by trained and certified nutritionists. Both nutritional and behavioral topics were integrated into the sessions, and self-monitoring was an important component of the intervention program. Attendance at group sessions was high and the majority of women met their fat intake goal. The results of this trial demonstrate that it is feasible to recruit women of different minority groups and socioeconomic status, and that these women can achieve and maintain a low-fat eating pattern. (Supported by NCI CN-15343). © 1995 American Dietetic Association.

Pulmonary retention of inhaled anatase (tio2) aerosols and lung tumor induction in rats simulated by a physiology-oriented model - Stöber, W.; Morrow, P.E.; Oberdörster, G. (Inhalation Toxicology, 1995)
A physiology-oriented compartmental kinetics (POCK) model of alveolar retention of respirable, insoluble particles in rats was used to simulate the results of two subchronic inhalation tests with male Fischer rats exposed to submicron anatase TiO2 particles of either 250 or 20 nm average size (Oberdorster et al., 1994). Earlier, the ultrafine variety had been used in a lifetime study with female Wistar rats (Heinrich & Fuhst, 1992) and the results were also subjected to POCK simulations. The database on anatase was not as extensive as in case of previous studies that used submicrometer carbonaceous aerosols. However, besides the usual results for the patterns of total lung burden and lymph node load, the new subchronic tests provided, for the first time, some data on anatase burdens of both the macrophage pool and the interstitium. Due to the scarcity of the data, the POCK simulation was not entirely unique, but good data representation was achieved with plausible model parameters. The substantial increase in interstitial deposits of the ultrafine anatase in comparison to the coarser sample required an increase by an order of magnitude for the rate coefficient of free particle mass transfer through the epithelial wall. The translocation of overloaded macrophages to the interstitium indicated a similar change, but Wistar rats appeared to have a lower base value. In general, the results of the simulations seem to confirm the usefulness and consistency of the model concept. At the end of the lifetime exposure study with ultra-fine anatase, conducted under high exposure rate indices up to 1330 mg/m3 × h/wk to achieve overload, Heinrich and Fuhst found lung tumors in 32% of the rats. This confirmed that overload carcinogenesis in rats is not related to molecular, DNA-reactive carcinogens. A previously proposed hypothesis of a critical dose for overload carcinogenesis in rats, which had been derived from experimental diesel soot and carbon black aerosol inhalation studies, yielded tumor induction characteristics for ultrafine anatase that were commensurable with the parameter values found for carbonaceous aerosols. This suggests that the integral over the residence time of the interstitial retention may be a consistent relative dose surrogate for overload lung tumor induction in rats. Its critical dose would correspond to a no-effect threshold. For the female Wistar rats and ultrafine anatase, this value was about 4000 mg × days. It matched closely, although probably by coincidence, the value for the female Wistar rats derived earlier from experimental diesel soot data. © 1995 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.

Is cost a barrier to screening mammography for low-income women receiving medicare benefits? A randomized trial - Kiefe, C.I.; McKay, S.V.; Halevy, A.; Brody, B.A. (Archives of Internal Medicine, 1994)
Background: In 1991, Medicare began covering screening mammograms subject to copayment and deductible. This study evaluated the effectiveness of Medicare in removing financial barriers to screening mammography among low- income older women. Methods: In an inner-city public hospital's General Medicine Clinic, 119 consecutive, eligible, and consenting Medicare-enrolled women without known risk factors for breast cancer other than age, and no mammogram in the previous 2 years, were entered into a randomized controlled trial with follow-up after 2 months. The mean age was 71 years; 77% were black, 92% had an annual income below $10 000, and 52% had had a previous mammogram. All patients were counseled concerning indications for screening mammograms and Medicare coverage, and all were referred to a low-cost mammography facility. Sixty-one subjects were randomly assigned a voucher for a free screening mammogram at the referral facility. Obtaining a mammogram within 60 days of study entry was the main outcome measure. Results: Of the women given vouchers, 27 (44%) obtained screening mammograms, compared with six (10%) of those without vouchers (P<.001). Adjustment by multiple logistic regression confirmed this association, yielding an adjusted odds ratio of 7.4 (95% confidence interval, 2.5 to 21.4). Knowledge concerning mammography and breast cancer increased significantly overall (and within randomization groups) between initial interview and follow-up; fear did not change. For women without the voucher, the main reason for not obtaining a mammogram was financial; the main reason for women with the voucher was transportation. Conclusion: In a low-income, inner-city population of older women, financial barriers to screening mammography persist despite Medicare coverage.

Model-inferred hypothesis of a critical dose for overload tumor induction by diesel soot and carbon black - Stöber, W.; Mauderly, J.L. (Inhalation Toxicology, 1994)
The application of the POCK model of pulmonary clearance and retention to new experimental results of chronic inhalation studies with rats exposed for 2 yr to diesel exhaust or carbon black is reported. For the first time in lifetime studies with these carbonaceous aerosols, experimental data became available for paniculate mass burdens in the lung-associated lymph nodes. Furthermore, seven out of eight lifetime runs used exposure rate indices causing lung overload and lung tumors. The simulations of the POCK model were consistent with previous POCK representations of diesel soot and carbon black exposure studies. The new data on lifetime patterns of lymph node loads, however, required an adjustment of the interstitial kinetics in order to account for the apparent lymph-node load stagnation after about 1 yr of chronic exposures leading to lung overload. The consistently observed coincidence of lymph-node load stagnation and tumor induction in the new exposure studies occurred always in a situation where overload caused a pronounced increase of the interstitial particle burden. These observations were thought to support a hypothesis that assumed the time integral of the interstitial burden as an effective relative dose for a rat-specific overload carcinogenesis. Depending on aerosol material and rat strain, common critical values of this dose relating to both lymph-node load stagnation and tumor induction were postulated and calculated by using the model-inferred simulation data. The low precision of the experimental data indicating lymph-node load stagnation rendered the results semiquantitative. However, a plausible evaluation of the sparse empirical dose-response data of overload carcinogenesis for the two carbonaceous aerosols yielded no-effect thresholds commensurable and compatible with the critical dose values. © 1994 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.

Cytochrome P450IIE1 Genetic Polymorphisms, Racial Variation, and Lung Cancer Risk - Kato, S.; Shields, P.G.; Weston, A.; Harris, C.C. (Cancer Research, 1992)
Cytochrome P450IIE1 is responsible for the activation of carcinogenic/V-nitrosamines, benzene, urethane, and other low-molecular-weight compounds. Restriction fragment length polymorphisms (Pstl and Rsal restriction enzymes) have been identified in the cytochrome P450IIE1 transcription regulatory region that may affect expression. This study describes the Pstl and Rsal polymorphisms in different racial populations and in a case-control study of lung cancer. The allelic frequencies were markedly different in Japanese, African-Americans, and Caucasians: the Pstl rare allele was present at a frequency of 2% in Caucasians, 5% in African-Americans, and 24% in Japanese (P < 0.05). For the Rsal rare allele, frequencies were 2% in Caucasians, 2% in African-Americans, and 27% in Japanese (P < 0.05). The assay was also applied to 128 individuals enrolled in a case-control study of lung cancer. Although limited in statistical power, the data indicate no evidence for an association in the aggregate of cytochrome P450IIE1 Pstl [for which the odds ratio was 0.7 (95% confidence interval (C.I.) = 0.2-2.8)] or Rsal [for which the odds ratio was 0.9 (95% C.I. = 0.2-5.4)] restriction fragment length polymorphisms with lung cancer in this U.S. population. When analyzed by race, the lung cancer odds ratio for the Pstl mutant allele in African-Americans was 0.19 (95% C.I. = 0.03-1.38), and in Caucasians it was 4.13 (95% CI. = 0.34-48.8). For the Rsal mutant allele, the odds ratios were 0.20 (95% CI. = 0.02-2.43) and 4.28 (95% C.I. = 0.35-50.6), respectively. The ethnic differences of these restriction fragment length polymorphisms might be related to genetic susceptibilities for lung cancer among Caucasians and for gastric or esophageal cancer among Japanese. © 1992, American Association for Cancer Research. All rights reserved.

Cancer screening intervention among black women in inner-city Atlanta - Design of a study - Sung, J.F.C.; Coates, R.J.; Williams, J.E.; Liff, J.M.; Greenberg, R.S.; McGrady, G.A.; Avery, B.Y.; Blumenthal, D.S. (Public Health Reports, 1992)
This experimental study attempts to determine if an in-home educational intervention conducted by lay health workers (LHWs) can increase adherence among low-income, inner-city black women to schedules for screening for breast cancer and cervical cancer, as well as increase the women's knowledge and change their attitudes regarding these cancers. This paper is a description of the purposes, hypotheses, design, subject recruitment, intervention, and evaluation of the study conducted by Morehouse School of Medicine. Subjects were recruited from a variety of sources, including patients seen in a community health center, women referred by the National Black Women's Health Project (NBWHP), residents of public and senior citizen housing projects, and persons identified in various community settings. Fewer than half of those asked to participate agreed to do so. The 321 women who were recruited were demographically diverse. Overall, about half of these volunteer subjects self-reported at least one Papanicolaou (Pap) smear and one breast examination within a year before enrollment in the study. There was little variation by source of recruitment in compliance with screening recommendations, except that referrals from NBWHP were more likely (P<0.01) to have had a Pap test and breast self-examination, while residents of public housing projects were somewhat less likely to have done so. About 35 percent of participants ages 35 and older had a mammogram within an appropriate interval. Participants were randomly assigned to intervention and control groups. Women in the intervention group were visited in their homes by LHWs on three occasions; the LHWs provided education on cancer and reproductive health. The groups were comparable in their baseline sociodemographic status and previous screening history.

PROCEEDINGS OF THE AUSTRALASIAN SOCIETY OF CLINICAL AND EXPERIMENTAL PHARMACOLOGISTS (Clinical and Experimental Pharmacology and Physiology, 1983)
1. Effect of chronic haloperidol treatment on D‐2 receptors labelled by (3H)‐spiperone in homogenates of rat corpus striatum. A. L. Gundlach, D. J. de Vries and P. M. Beart 2. The effects of haloperidol and apomorphine on behavioural responses in rats with modified thyroid status. M. A. Joschko, A. D. Crocker and D. H. Overstreet 3. Dopamine (DA) and dihydroxyphenylacetic acid (DOPAC) distribution within the brain and spinal cord of spontaneously hypertensive (SHR) and Wistar‐Kyoto (WK) rats at various ages. L. G. Howes, P. R. Rowe, R. J. Summers and W. J. Louis 4. Dopamine administration into the nucleus accumbens and the retention of conditioned avoidance learning by rats. P. U. Braes, P. M. Gregory and D. M. Jackson 5. Ketanserin, a serotonin‐2 antagonist, inhibits the vasoconstriction but not the vasodilation produced by serotonin. P. L. McLennan and D. A. Taylor 6. A clinical pharmacological study on ketanserin, a new serotonin antagonist. R. W. Bury, A. T. Kacprowicz, V. Iwanov, P. G. Shaw, R. F. W. Moulds 7. The differentiation of receptor activity of leu5‐ and met5‐enkephalin utilizing in vivo pA2 analysis. M. J. Quinn and M. R. Fennessy 9. The bioavailability of propantheline bromide. D. K. Moses, B. G. Charles, and P. J. Ravenscroft 10. Elimination of amphotericin B in patients with impaired renal function. M. S. Ching, D. J. Morgan, K. Raymond, R. W. Bury, M. L. Mashford, F. W. Gurr and A. A. Somogyif 11. A renal mechanism for the cloflbric acid‐probenecid interaction. P. J. Meffin and D. M. Zilm 12. pH‐Dependent rearrangement of the biosynthetic ester glucuronide of valproic acid (Epilim) to β‐glucuronidase‐resistant forms. R. G. Dickinson and M. J. Eadie 13. Interaction of purines with GABA‐independent ‘central’ but not ‘peripheral’ benzodiazepine binding sites. L. P. Davies, J. H. Skerritt, S. Chen Chow and G. A. R. Johnston 14. Benzodiazepine stimulation of GABA binding–studies with agonists and antagonists. J. H. Skerritt and G. A. R. Johnston 15. Inhibition of binding of [3H]‐batrachotoxinin A 20‐α‐benzoate to sodium channels by the anticonvulsant drugs diphenylhydantoin and carbamazepine. M. Willow and W. A. Catterall 16. Effects of mianserin on noradrenergic mechanisms. A. Rose, M. W. McCulloch and C. Sarantos‐Laska 17. The effect of olfactory bulbectomy (OB) and antidepressant drugs on circadian rhythm and pineal function in the rat. Doreen H. Leigh and K. D. Cairncross 18. Narcotic potency of the n‐alkanes. Janet De Silva, A. J. Christophers and M. W. Nott 19. Hyperactivity following fetal ethanol exposure is due to a delay in the development of the cholinergic neuro‐transmitter system. N. W. Bond 20. Prevention by aminophylline of the renal effects of both hypertonic saline and amphotericin B; possible linkage of tubuloglomerular feedback and nephrotoxicity. J. F. Gerkens and R. A. Branch (introduced by A. J. Smith) 21. Paracetamol toxicity in hamster hepatocytes: Studies with inhibitors of drug metabolism. A. W. Harman and L. J. Fischer (introduced by K. F. Ilett) 22. The mechanism of action of paracetamol protective agents in the mouse. J. O. Miners, R. Drew, J. Attwood, J. Adams and D. J. Birkett 23. Measurement of formation of reactive metabolites of phenacetin in man. M. Veronese, S. McLean and N. Davies 24. Liver injury due to chronic halothane inhalation. J. L. Plummer, P. de la M. Hall, M. J. Cousins, F. N. Bastin and A. H. Ilsley 25. Changes in rat hepatic microsomal mixed function oxidase activity following exposure to halothane. K. M. Knights, G. K. Gourlay and M. J. Cousins 26. Testicular effects of 2,4,5‐trichlorophenoxy‐acetic acid (2,4,5‐T). R. Drew and J. Rowell 27. Plasma concentrations of unbound phenytoin in the management of epilepsy. C. Kilpatrick, S. Wanwimolruk and L. M. H. Wing 28. Double‐blind comparison of ranitidine and cimetidine in the treatment of chronic gastric ulcer. J. E. Kellow, G. D. Barr, A. E. Cowen, M. Ward, L. Wood and D. W. Piper 29. Comparative evaluation of cimetidine and ranitidine for stress ulcer prophylaxis in the critically ill. D. G. More, R. F. Raper, I. Munro, J. Boutagy and G. M. Shenfield 30. The pharmacokinetics and effect on platelet aggregation of dipyridamole in humans. A. Jenkins, S. Watts, D. Imhoff, B. Duncan, F. Bochner and J. Lloyd 31. A crossover trial of combination α‐ and β‐adrenergic blockade in hypertension. G. S. Stokes, B. A. Mennie and R. Gellatly 32. Different determinants of compliance in epilepsy and hypertension. G. M. Peterson, S. McLean and K. S. Millingen 33. Positive chronotropic responses produced by cardiac α1‐adrenoceptors in the pithed rat. L.‐H. Tung, O. H. Drummer, W. J. Louis and M. J. Rand 34. Effects of partial β‐agonists and phosphodiesterase inhibition on β‐adrenoceptor responsiveness of cultured cardiac cells. A. Bobik, P. Little, J. Campbell and S. Minasian 35. In vitro cardiac activity of isoquinoline derivatives related to papaverine. P. Goadby, R. Foulkes and A. A. Anderson (introduced by C. Raper) 36. Peripheral inhibition of cardiac vagal action by sympathetic adrenergic stimulation. E. K. Potter and D. I. McCloskey (introduced by W. E. Glover) 37. Prostaglandins and the pericardial pressor chemoreflex in dogs. P. N. Nolan, D. E. Luk and J. Staszewska‐Barczak 38. Effect of capsaicin on the Bezold‐Jarisch reflex in the rabbit. Y‐M. Wang, M. L. Mashford and P. J. Harman 39. Correlations between pharmacological responses and structure of human lung parenchyma strips. R. G. Goldie, J. F. Bertram, J. M. Papadimitriou and J. W. Paterson 40. Cholinergic responses in human lung–a structure/function correlation. M. J. B. Finney, N. Berend and J. L. Black 41. Comparisons ofin vivoandin vitroresponses to histamine in human airways. K. Vincenc, J. Black, A. Woolcock and J. Shaw 42. An interaction betwen leukotriene D4 and histamine on airways resistance in anaesthetized guinea‐pigs. A. G. Stewart, D. C. Thompson and M. R. Fennessy 43. Inhaled prazosin and histamine induced bronchoconstriction. C. R. Jenkins, G. J. Hart, A. B. X. Breslin and G. E. Marlin 44. Prednisolone disposition as a function of dose and oral contraceptive use. B. C. Sallustio, P. J. Meffin, P. M. Brooks and L. M. H. Wing 45. The influence of fatty acids on the binding of prednisolone to albumin. J. M. Potter and D. M. Offerman 46. Midazolam pharmacokinetics in the elderly. M. T. Smith, V. Heazlewood, M. J. Eadie and T. O'R. Brophy 47. Temazepam pharmacokinetics in healthy adults. H. Ghabrial, P. V. Desmond, P. J. Har‐man, M. L. Mashford, B. Westwood, K. J. Breen and A. J. Gijsbers 48. The absorption of aspirin in migraine, and the effect of metoclopramide. L. M. Ross‐Lee, M. J. Eadie, V. Heazlewood and J. H. Tyrer 49. Gastric and intestinal absorption of captopril in the rat. P. J. Worland, O. H. Drummer and B. Jarrott 50. In vivoevidence of presnyaptic a‐adrenoceptors modulating inotropic responses to sympathetic stimulation. R. A. Jarvis, R. Einstein and A. H. Goodman 51. Clonidine fails to inhibit vagal bradycardia: evidence against presynaptic α‐adrenoceptors on cardiac vagal varicosities. M. J. Lew and J. A. Angus 52. Facilitation of sympathetic neuroeffector transmission in guinea‐pig isolated atria by angiotensin I and angiotensin II. J. Ziogas, D. F. Story and M. J. Rand 53. Effect of α‐adrenoreceptor antagonists and neuronal uptake inhibitors on dimethylphenyl‐piperazinium (DMPP)‐induced release of adrenaline from the rabbit adrenal gland. A. R. Collett and D. F. Story 54. Is the carrier system for extraneuronal uptake of catecholamines the same in different cell types? J. J. Cole and S. R. O'Donnell 55. Sites of extraneuronal o‐methylation of isoprenaline in guinea‐pig trachea. L. J. Bryan and S. R. O'Donnell 56. Anti‐inflammatory/anti‐arthritic activity of some copper‐D‐penicillamine complexes. I. R. Garrett and M. W. Whitehouse 57. Determination of response of individual patients with rheumatoid arthritis to auranofin. G. D. Champion, D. Bieri, C. D. Browne, D. Cairns, R. O. Day, G. G. Graham, G. Harris and P. N. Sambrook 58. Studies on the mechanism by which smoking increases the uptake of gold by red blood cells. G. G. Graham, H. M. Jones, T. M. Macpherson and G. D. Champion 59. Anti‐inflammatory drugs in a model of chronic inflammation. R. S. Hirsch and B. Vernon‐Roberts 60. Heavy metal (Au, Pt) nephropathy: studies in normal and inflamed rats. M. W. Whitehouse, I. R. Garrett and B. Vernon‐Roberts 61. Renal function and lithium treatment: a two year prospective study. G. F. S. Johnson, G. E. Hunt and G. G. Duggin 62. Extra‐visceral drug clearance. W. B. Runciman, R. N. Upton, A. H. Ilsley, R. Carapetis, T. M. Shepherd, C. Nancarrow and L. E. Mather 63. β‐Adrenoceptor antagonists as possible inhibitors of drug metabolism in man. L. M. H. Wing, J. O. Miners, B. J. Harrington, K. Lillywhite and K. J. Smith 64. Comparison of β‐adrenoceptor antagonists as modulators of drug metabolism. J. T. Ahokas, C. Davies and P. J. Ravenscroft 65. Guanethidine N‐oxide formation as a measure of flavin‐containing mono‐oxygenase enzyme activity in rat hepatocytes. M. E. McManus, P. H. Grantham, P. J. Wirth, P. P. Roller and S. S. Thorgeirsson 66. Interaction of imidazole drugs with hepatic cytochrome P‐450 dependent enzymes. J. Scott and R. Drew 67. Captopril disulphide conjugates can be reduced back to captopril in vivo. O. H. Drummer and B. Jarrott 68. The rat costo‐uterine muscle: an isolated preparation of potential use for screening drugs acting at β2‐adrenoceptors. J. N. Pennefather and M. L. Hartley 69. Dose‐related effects of ovarian steroid hormones on guinea‐pig myometrial adrenoceptors. M. E. Story, M. L. Hartley and J. N. Pennefather 70. Evidence from binding studies for alpha and beta adrenoceptors associated with rat glomeruli. G. A. McPherson and R. J. Summers 71. A comparison of the effects of phenoxybenzamine and RX781094 in the vas deferens. M. Papanicolaou, M. W. McCulloch and M. J. Rand 72. Ketanserin lowers blood pressure in rats by a‐adrenoceptor blockade. J. F. Marwood and G. S. Stokes 73. Hypotensive response to ketanserin in conscious rabbits: role of α‐adrenoceptors. C. E. Wright, J. A. Angus and G. P. Jackman 74. The influence of platelets on prostanoid release from rat hearts perfused in vitro. M. Purchase and G. J. Dusting 75. The antagonism of the effects of platelet products on a human blood vessel by verapamil, nifedipine and sodium nitrite. R. F. W. Moulds, V. Iwanov and R. L. Medcalf 76. Antagonists of endothelial cell‐mediated relaxation of arterial smooth muscle. T. M. Cocks and J. A. Angus 77. Differences in the mechanism of the endothelium‐dependent relaxing action of acetylcholine in rabbit aorta and dog femoral artery. D. Tang and W. E. Glover 78. Actions of leukotrienes C4, D4 and E, on rat isolated hearts. W. J. Hum, O. L. Woodman and G. J. Dusting 79. Study of the acute toxicity, kinetics and pharmacological action of digitoxigenin glucoside (Dt‐O‐Glu) using the guinea‐pig left atria, mouse, rabbit and open‐chest anaesthetized dog. P. M. Altaian and R. E. Thomas 80. The effect of pH on the inhibitory effect of verapamil, nifedipine and diltiazem on the ATP dependent and DTP independent Ca2+ binding activity of isolated rat cardiac carcolemmal preparation. J. S. Dillon and W. G. Nayler 81. Theobromine metabolism in man: effects of cimetidine and sulphinpyrazone. D. J. Birkett, J. O. Miners, L. M. H. Wing and J. Attwood 82. Decreased clearance of warfarin after treatment with cimetidine or ranitidine. P. V. Desmond, K. J. Breen, P. J. Harman, M. L. Mashford and B. J. Morphett 83. The influence of chemical structure on the route of metabolism of barbiturates. A. Treston, W. D. Hooper and M. J. Eadie 84. Conjugation of benzoic acid in seven species of marsupial. Almah Awaluddin and S. McLean 85. 25‐Hydroxylation of vitamin D in patients on long‐term anticonvulsant therapy and with parenchymal liver disease. A. Boroky, H. Morris C. Nordin, J. LaBrooy, and F. Bochner 86. Metabolism of tritiated glyceryl trinitrate by human erythrocytes. P. A. Cossum and M. S. Roberts 87. Metronidazole metabolism in the premature neonate. J. Baird‐Lambert, P. E. Doyle, E. Jager‐Roman and N. Buchanan 88. The measurement of motor performance in Parkinson's disease and the evaluation of a sustained release formulation of L‐dopa with benserazide. P. Paull, D. Madden, J. Morris and D. Wade 89. Modulation of dopamine responses by activation of β‐hydroxy phenethylamine receptors. D. F. H. Dougan and D. N. Wade 90. Effect of α‐methyltyrosine on the concentrations of m‐tyramine and α‐methyl m‐tyramine in rat striatum. P. H. Duffield, D. F. H. Dougan, D. N. Wade and A. M. Duffield 91. Radioreceptor assay of the pharmacokinetics of midazolam and chlordiazepoxide. K. M. Taylor, D. M. Paton and R. A. Boas 92. Properties of fentanyl binding to the μ opiate receptor. K. M. Taylor and J. W. Villiger 93. Problems with propranolol as a displacer of [3H)‐dihydroalprenolol for defining β‐receptors in the rat cerebral cortex. E. J. Begg and D. N. Wade 94. The modulation of high affinity (3H)‐spiperone binding by manganese in homogenates of the rat corpus striatum. D. J. de Vries and P. M. Beart 95. The anticonvulsant, carbamazepine, interacts with brain benzodiazepine receptors. J. H. Skerritt and S. Chen Chow 96. Potent theophylline‐like activity of some novel pyrazolopyrimidines. S. Chen Chow, J. H. Skerritt, L. P. Davies, G. A. R. Johnston and D. J. Brown 97. Modification of hypothermic effects of physostigmine by ovariectomy. R. A. Netherton and D. H. Overstreet 98. Design and activity of a new oxygen heterocyclic analogue of GABA. R. D. Allan, G. A. R. Johnston and R. Kazlauskas 99. Selectivity of antidepressants to inhibit amine uptake following in vivo administration. B. Manias and D. A. Taylor 100. Parallel cross‐tolerance to stress and morphine antinociception: no change in endogenous opioid activity following chronic opiate treatment. M. J. Christie, G. B. Chesher, and K. D. Bird 101. Mesenteric vessels from hypertensive rats exhibit an increased responsiveness to serotonin that is inhibited by ketanserin. D. A. Taylor and P. L. McLennan 102. Inhibition of 5‐hydroxytryptophan‐induced wet‐shakes by serotonin‐2 receptor antagonists. C. Y. Yap and D. A. Taylor 103. Neurally‐mediated relaxant effect of serotonin in guinea‐pig distal ileum. E.J. Mylecharane and R. McD. Sutherland 104. Antagonist activity of ketanserin in smooth muscle preparations. R. McD. Sutherland and E. J. Mylecharane 105. Metabolic profile of [3H]‐noradrenaline released by isoprenaline from rabbit atria. C. Sarantos‐Laska, M. W. McCulloch and M. J. Rand 106. Binding of (3H)‐rauwolscine to intact human blood platelets. A. J. Smith and L. M. Stewart 107. Action of opioid‐ and α‐adrenoceptor agonists on neurogenic oedema. R. Lew, G. A. Bentley and I. W. Copeland 108. Sympathetic function in the epididymal and prostatic halves of the rat vas deferens after vasectomy. R. M. DeGaris, M. L. Hartley, J. A. Leedham and J. N. Pennefather 109. Thyroid status and α‐adrenoceptors in rat mesenteric arterioles. G. J. Mammen, E. J. N. Ishac and J. N. Pennefather 110. In vivoandin vitroeffects of propylene glycol in human airways. J. Black, K. Yan, C. Salome and J. Shaw 111. Responses of guinea‐pig lung parenchymal strips to drugs affecting adrenoceptors. P. Goad‐by and M. Vadher (introduced by C. Raper) 112. The functional antagonism of carbachol‐induced contractions by β‐adrenoceptor agonists in guinea‐pig isolated tracheal smooth muscle. P. J. Henry, K. M. Lulich and J. W. Paterson 113. Verapamil inhibits thromboxane A2 release from guinea‐pig isolated perfused lungs. S. Ozols and J. P. Seale 114. The effects of fenoterol and selective β‐adrenoceptor antagonists on the release of SRS‐A leukotrienes from human lung fragments. J. M. Hughes, J. P. Seale and D. M. Temple 115. Effect of a new antiallergic compound, SM857, on the release of slow‐reacting substance (leukotrienes) from lung tissue. J. G. Kench, J. P. Seale and D. M. Temple 116. Age‐related changes in responses of human isolated arteries and veins. M. J. Stevens, S. Lipe and R. F. W. Moulds 117. Hyperventilation potentiates the nicotine‐induced depressor chemoreflex in the dog. Denise E. Luk, P. N. Nolan and Janina Staszewska‐Barczak 118. Cardiac sarcolemma during ischaemia and reperfusion: influence of verapamil. M. J. Daly, J. Elz, and W. G. Nayler 119. Structure‐activity relations at peripheral adenosine receptors. D. M. Paton 120. Computer‐assisted anticonvulsant therapy. G. M. Peterson 121. Assessment of efficacy of oral dihydroergotamine in severe orthostatic hypotension from Australian case studies. P. F. Isaac, S. A. Genge, A. Barnes and G. L. Couch 122. The influence of some different antihypertensive drugs on the cardiovascular reaction to isometric exercise. G. Nyberg 123. Comparison of colloidal bismuth subcitrate tablets and liquid in duodenal ulcer healing. J. E. Kellow, G. D. Barr, W. R. J. Middleton and D. W. Piper 124. Effects on β‐blockade on performance in competitive swimming. G. Nyberg and B. Furberg 125. Pharmacokinetic optimization of aminophylline infusion requirements in critically ill asthmatic patients. K. F. Ilett, R. L. Nation, T. E. Oh and B. Silbert 126. Utilization of drug level monitoring in a district hospital. M. Kennedy and W. Beshaw 127. Use of prophylactic antibiotics in children undergoing operations. N. Anderson, D. Cohen, D. Dorman and J. Shaw 128. Drug usage in a coronary care unit. P. Raymond, G. Hale, M. L. Mashford, K. Raymond, J. Roberts, M. Robertson and P. Seo 129. Survey of drug abuse patterns in a casualty department population. J. E. Ray, D. K. Reilly, T. Haavisto, P. D. Paull and R. O. Day 130. Structure‐activity relationships for protein binding of radiocontrast agents. S. Wan‐wimolruk and D. J. Birkett 131. Preliminary pharmacokinetic and pharmacodynamic studies with tizanidine in patients with spasticity. P. Symoniw, V. Heazlewood, P. Maruff and M. J. Eadie 132. Aspirin glucocorticosteroid interaction in man. R. O. Day, G. Harris, M. Brown and G. Graham 133. Analysis and pharmacokinetics of the β‐adrenoceptor agonist ICI 118,587 (Corwin). G. P. Jackman, C. J. Oddie, A. Bobik and G. Jennings 134. Disposition and cardiovascular effects of cimetidine in critically ill patients. R. L. Nation, K. F. Ilett, R. Tjokrosetio, T. E. Oh, P. Cameron and W. Thompson 135. The effect of cimetidine and metoclopramide on the elimination of misonidazole (Ro 07–0582) in man. K. M. Williams, E. J. Begg, D. N. Wade and K. O'Shea 136. Purification of UDP glucuronosyltransferase from mouse liver. P. I. Mackenzie and I. S. Owens (introduced by M. E. McManus) 137. Metabolism of primidone in man. W. D. Hooper, A. Treston, N. W. Jacobsent and M. J. Eadie 138. Influence of cimetidine on procainamide pharmacokinetics in man. A. Somogyi, A. McLean and B. Heinzow 139. Differential effects of hypoxia on the disposition of propranolol and sodium taurocholate by the rat isolated perfused liver. B. Jones, G. Mihaly, R. Smallwood, L. Webster, D. Morgan and M. Madsen 140. Intra‐ and extra‐hepatic carcinomas impair drug metabolism in the rat. P. J. Harman, S. E. Doig, P. V. Desmond, M. L. Mashford, K. J. Breen and B. Gray 141. Kinetic evidence for the involvement of multiple forms of human liver cytochrome P‐450 in the metabolism of acetylaminofluorene. M. E. McManus, R. F. Minchin, P. J. Wirth and S. S. Thorgeirsson 142. Dose‐response curves for the effects of enteric‐coated aspirin on platelet function. P. A. Cossum, J. H. Vial, L. J. McLeodf and M. S. Roberts 143. Converting enzyme inhibition in the rat is accompanied by potentiation of inflammation. A. P. Svolmanis and A. L. A. Boura 144. The effect of route of administration on the distribution and severity of lesions due to a compound whose toxic action is cytochrome P‐450 associated. A. A. Seawright, A. R. Mattocks and J. Hrdlicka 145. Peroxidation of rat liver microsomal membrane lipids induced by methyl mercury. M. Hicks, J. M. Gebicki and K. D. Cairncross 146. Some toxicological and behavioural effects of in utero methyl mercury exposure in the rat. Ann A. Parks, Robyn Can, M. Hicks, J. M. Gebicki and K. D. Cairncross 147. Effects of cimetidine and ranitidine on halothane metabolism and hepatotoxicity. J. L. Plummer, S. Wanwimolruk, M. A. Jenner, P. de la M. Hallt, and M. J. Cousins 148. Cardiovascular and hepatic effects of halothane and isoflurane in a guinea‐pig model of ‘halothane hepatitis'. C. A. Lunam, P. de la M. Hall and M. J. Cousins. (Introduced by M. J. Cousins.) 149. HPLC assays for β‐lactam antibiotics in body fluids. P.J. Harman, Y. M. Wang and M. L. Mashford 150. Comparison of three methods for the routine measurement of phenytoin free fraction during therapeutic drug monitoring. S. Wanwimolruk, D. J. Birkett and L. M. H. Wing 151. Measurement of propantheline bromide in serum by high performance liquid chromatography. B. G. Charles, D. K. Moses and P. J. Ravenscroft 152. The use of 2,5‐diphenyloxazole as a substrate in the assay of AAH. A. Philippides, J. Ahokas. C. Davies, N. Jacobsen and N. Kärki 153. Simultaneous HPLC assay for cimetidine and ranitidine. J. Boutagy, I. A. Munro, D. G. More and G. M. Shenfield 154. The analysis of D‐penicillamine in plasma using fluorescence derivatisation and high performance liquid chromatography. J. O. Miners, I. Fearnley, D. Smith, M. W. Whitehouse, P. Brooks, and D. J. Birkett Copyright © 1983, Wiley Blackwell. All rights reserved

Elimination of radioactivity after intratracheal instillation of tritiated 3,4-benzopyrene in hamsters - Pylev, L.N.; Roe, F.J.; Warwick, G.P. (British Journal of Cancer, 1969)
A study in hamsters of the distribution and elimination of radioactivity after a single intratracheal instillation of a suspension of [3H]3,4-benzopyrene (BP) in aminosol vitrum 100%, or of mixtures of BP and asbestos or of BP and carbon black in the same suspending medium, is reported. During the first 3 weeks of the experiment, radioactivity disappeared rapidly from the lungs irrespective of the presence or absence of carbon black. After 21 days, however, both asbestos and carbon black significantly increased retention of radioactivity. More macrophages could be recovered by use of a standard washing technique after the administration of BP + carbon black or BP + asbestos, than after the administration of BP alone, but the radioactivity per macrophage was highest in the group treated with benzopyrene only. The levels of radioactivity found in liver, kidneys, blood and urine were similar in the 3 groups of animals. In the faeces there was an earlier fall of radioactivity after treatment with BP + carbon black (between 14 and 21 days) than after treatment with BP alone (between 21 and 28 days. The significance of the results in relation to the causation of lung cancer in man is briefly discussed. © 1969, The British Empire Cancer Campaign for Research. All rights reserved.